The CARD8 inflammasome dictates HIV/SIV pathogenesis and disease progression. - Wang, Qiankun; Clark, Kolin M; Tiwari, Ritudhwaj; Raju, Nagarajan; Tharp, Gregory K; Jeffrey Rogers; R. Alan Harris; Raveendran, Muthuswamy; Bosinger, Steven E; Burdo, Tricia H; Silvestri, Guido; Shan, Liang (Cell, 2024)
While CD4 T cell depletion is key to disease progression in people living with HIV and SIV-infected macaques, the mechanisms underlying this depletion remain incompletely understood, with most cell death involving uninfected cells. In contrast, SIV infection of "natural" hosts such as sooty mangabeys does not cause CD4 depletion and AIDS despite high-level viremia. Here, we report that the CARD8 inflammasome is activated immediately after HIV entry by the viral protease encapsulated in incoming virions. Sensing of HIV protease activity by CARD8 leads to rapid pyroptosis of quiescent cells without productive infection, while T cell activation abolishes CARD8 function and increases permissiveness to infection. In humanized mice reconstituted with CARD8-deficient cells, CD4 depletion is delayed despite high viremia. Finally, we discovered loss-of-function mutations in CARD8 from "natural hosts," which may explain the peculiarly non-pathogenic nature of these infections. Our study suggests that CARD8 drives CD4 T cell depletion during pathogenic HIV/SIV infections.
Keywords: Animals; CARD Signaling Adaptor Proteins; CD4-Positive T-Lymphocytes; Disease Progression; HIV; HIV Infections; Humans; Inflammasomes; Mice; Neoplasm Proteins; Simian Acquired Immunodeficiency Syndrome; Simian Immunodeficiency Virus; Viremia

Dietary Folate and Cofactors Accelerate Age-dependent p16 Epimutation to Promote Intestinal Tumorigenesis. - Yang, Li; Peery, Robert C; Farmer, Leah M; Gao, Xia; Zhang, Yiqun; Creighton, Chad J; Zhang, Lanjing; Shen, Lanlan (Cancer Res Commun, 2024)
UNLABELLED: The extent to which non-genetic environmental factors, such as diet, contribute to carcinogenesis has been long debated. One potential mechanism for the effects of environmental factors is through epigenetic modifications that affect gene expression without changing the underlying DNA sequence. However, the functional cooperation between dietary factors and cancer-causing epigenetic regulation is largely unknown. Here, we use a mouse model of age-dependent p16 epimutation, in which the p16 gene activity is directly controlled by promoter DNA methylation. We show p16 epimutation is modulated by folate and cofactors in dietary supplementation, which leads to increased colon cancer risk. Importantly, our findings provide functional evidence concerning the safety of folate fortification in the general population. SIGNIFICANCE: Our study demonstrates that dietary folate and cofactors modulate tumor-suppressor gene methylation to increase intestinal tumorigenesis. Our findings highlight the need for monitoring the long-term safety of folate fortification in high-risk individuals.
Keywords: Animals; Carcinogenesis; Cell Transformation, Neoplastic; Cyclin-Dependent Kinase Inhibitor p16; Diet; Epigenesis, Genetic; Folic Acid; Humans; Intestinal Neoplasms; Mice

Identification of constrained sequence elements across 239 primate genomes. - Kuderna, Lukas F K; Ulirsch, Jacob C; Rashid, Sabrina; Ameen, Mohamed; Sundaram, Laksshman; Hickey, Glenn; Cox, Anthony J; Gao, Hong; Kumar, Arvind; Aguet, Francois; Christmas, Matthew J; Clawson, Hiram; et al. (Nature, 2024)
Noncoding DNA is central to our understanding of human gene regulation and complex diseases, and measuring the evolutionary sequence constraint can establish the functional relevance of putative regulatory elements in the human genome. Identifying the genomic elements that have become constrained specifically in primates has been hampered by the faster evolution of noncoding DNA compared to protein-coding DNA, the relatively short timescales separating primate species, and the previously limited availability of whole-genome sequences. Here we construct a whole-genome alignment of 239 species, representing nearly half of all extant species in the primate order. Using this resource, we identified human regulatory elements that are under selective constraint across primates and other mammals at a 5% false discovery rate. We detected 111,318 DNase I hypersensitivity sites and 267,410 transcription factor binding sites that are constrained specifically in primates but not across other placental mammals and validate their cis-regulatory effects on gene expression. These regulatory elements are enriched for human genetic variants that affect gene expression and complex traits and diseases. Our results highlight the important role of recent evolution in regulatory sequence elements differentiating primates, including humans, from other placental mammals.
Keywords: Animals; Conserved Sequence; Deoxyribonuclease I; DNA; Evolution, Molecular; Female; Gene Expression Regulation; Genome; Humans; Mammals; Placenta; Pregnancy; Primates; Proteins; Regulatory Sequences, Nucleic Acid; Reproducibility of Results; Transcription Factors

Novel, pathogenic insertion variant of GSDME associates with autosomal dominant hearing loss in a large Chinese pedigree. - Cheng, Jingliang; Li, Ting; Tan, Qi; Fu, Jiewen; Zhang, Lianmei; Yang, Luquan; Zhou, Baixu; Yang, Lisha; Fu, Shangyi; Linehan, Alora Grace; Fu, Junjiang (J Cell Mol Med, 2024)
Nonsyndromic hearing loss (NSHL) is a genetically diverse, highly heterogeneous condition characterised by deafness, and Gasdermin E (GSDME) variants have been identified as directly inducing autosomal dominant NSHL. While many NSHL cases associated with GSDME involve the skipping of exon 8, there is another, less understood pathogenic insertion variant specifically found in Chinese pedigrees that causes deafness, known as autosomal dominant 5 (DFNA5) hearing loss. In this study, we recruited a large Chinese pedigree, conducted whole-exome and Sanger sequencing to serve as a comprehensive clinical examination, and extracted genomic DNA samples for co-segregation analysis of the members. Conservation and expression analyses for GSDME were also conducted. Our clinical examinations revealed an autosomal dominant phenotype of hearing loss in the family. Genetic analysis identified a novel insertion variant in GSDME exon 8 (GSDME: NM_004403.3: c.1113_1114insGGGGTGCAGCTTACAGGGTGGGTGT: p. P372fs*36). This variant is segregated with the deafness phenotype of this pedigree. The GSDME gene was highly conserved in the different species we analysed, and its mRNA expression was ubiquitously low in different human tissues. In conclusion, we have successfully identified a novel pathogenic insertion variant of GSDME in a Chinese pedigree that causes deafness, shedding light on the genetic basis of hearing loss within this specific family. Our findings expand the spectrum of known variants associated with GSDME-related deafness and may further support both the underlying gain-of-function mechanism and functional associations of GSDME hearing loss variants.
Keywords: China; Deafness; Hearing Loss; Hearing Loss, Sensorineural; Humans; Mutation; Pedigree

Association Between Whole Blood-Derived Mitochondrial DNA Copy Number, Low-Density Lipoprotein Cholesterol, and Cardiovascular Disease Risk. - Liu, Xue; Sun, Xianbang; Zhang, Yuankai; Jiang, Wenqing; Lai, Meng; Wiggins, Kerri L; Raffield, Laura M; Bielak, Lawrence F; Zhao, Wei; Pitsillides, Achilleas; Haessler, Jeffrey; Zheng, Yinan; et al. (J Am Heart Assoc, 2023)
Background The relationship between mitochondrial DNA copy number (mtDNA CN) and cardiovascular disease remains elusive. Methods and Results We performed cross-sectional and prospective association analyses of blood-derived mtDNA CN and cardiovascular disease outcomes in 27 316 participants in 8 cohorts of multiple racial and ethnic groups with whole-genome sequencing. We also performed Mendelian randomization to explore causal relationships of mtDNA CN with coronary heart disease (CHD) and cardiometabolic risk factors (obesity, diabetes, hypertension, and hyperlipidemia). <0.01 was used for significance. We validated most of the previously reported associations between mtDNA CN and cardiovascular disease outcomes. For example, 1-SD unit lower level of mtDNA CN was associated with 1.08 (95% CI, 1.04-1.12; <0.001) times the hazard for developing incident CHD, adjusting for covariates. Mendelian randomization analyses showed no causal effect from a lower level of mtDNA CN to a higher CHD risk (β=0.091; =0.11) or in the reverse direction (β=-0.012; =0.076). Additional bidirectional Mendelian randomization analyses revealed that low-density lipoprotein cholesterol had a causal effect on mtDNA CN (β=-0.084; <0.001), but the reverse direction was not significant (=0.059). No causal associations were observed between mtDNA CN and obesity, diabetes, and hypertension, in either direction. Multivariable Mendelian randomization analyses showed no causal effect of CHD on mtDNA CN, controlling for low-density lipoprotein cholesterol level (=0.52), whereas there was a strong direct causal effect of higher low-density lipoprotein cholesterol on lower mtDNA CN, adjusting for CHD status (β=-0.092; <0.001). Conclusions Our findings indicate that high low-density lipoprotein cholesterol may underlie the complex relationships between mtDNA CN and vascular atherosclerosis.
Keywords: Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Coronary Disease; Cross-Sectional Studies; Diabetes Mellitus; DNA Copy Number Variations; DNA, Mitochondrial; Humans; Hypertension; Obesity; Risk Factors

Association of Mitochondrial DNA Copy Number With Brain MRI Markers and Cognitive Function: A Meta-analysis of Community-Based Cohorts. - Zhang, Yuankai; Liu, Xue; Wiggins, Kerri L; Kurniansyah, Nuzulul; Guo, Xiuqing; Rodrigue, Amanda L; Zhao, Wei; Yanek, Lisa R; Ratliff, Scott M; Pitsillides, Achilleas; Aguirre Patiño, Juan Sebastian; Sofer, Tamar; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: Previous studies suggest that lower mitochondrial DNA (mtDNA) copy number (CN) is associated with neurodegenerative diseases. However, whether mtDNA CN in whole blood is related to endophenotypes of Alzheimer disease (AD) and AD-related dementia (AD/ADRD) needs further investigation. We assessed the association of mtDNA CN with cognitive function and MRI measures in community-based samples of middle-aged to older adults. METHODS: We included dementia-free participants from 9 diverse community-based cohorts with whole-genome sequencing in the Trans-Omics for Precision Medicine (TOPMed) program. Circulating mtDNA CN was estimated as twice the ratio of the average coverage of mtDNA to nuclear DNA. Brain MRI markers included total brain, hippocampal, and white matter hyperintensity volumes. General cognitive function was derived from distinct cognitive domains. We performed cohort-specific association analyses of mtDNA CN with AD/ADRD endophenotypes assessed within ±5 years (i.e., cross-sectional analyses) or 5-20 years after blood draw (i.e., prospective analyses) adjusting for potential confounders. We further explored associations stratified by sex and age (<60 vs ≥60 years). Fixed-effects or sample size-weighted meta-analyses were performed to combine results. Finally, we performed mendelian randomization (MR) analyses to assess causality. RESULTS: We included up to 19,152 participants (mean age 59 years, 57% women). Higher mtDNA CN was cross-sectionally associated with better general cognitive function (β = 0.04; 95% CI 0.02-0.06) independent of age, sex, batch effects, race/ethnicity, time between blood draw and cognitive evaluation, cohort-specific variables, and education. Additional adjustment for blood cell counts or cardiometabolic traits led to slightly attenuated results. We observed similar significant associations with cognition in prospective analyses, although of reduced magnitude. We found no significant associations between mtDNA CN and brain MRI measures in meta-analyses. MR analyses did not reveal a causal relation between mtDNA CN in blood and cognition. DISCUSSION: Higher mtDNA CN in blood is associated with better current and future general cognitive function in large and diverse communities across the United States. Although MR analyses did not support a causal role, additional research is needed to assess causality. Circulating mtDNA CN could serve nevertheless as a biomarker of current and future cognitive function in the community.
Keywords: Aged; Alzheimer Disease; Brain; Cognition; Cross-Sectional Studies; DNA Copy Number Variations; DNA, Mitochondrial; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Prospective Studies

Association of Rare Protein-Truncating DNA Variants in APOB or PCSK9 With Low-density Lipoprotein Cholesterol Level and Risk of Coronary Heart Disease. - Dron, Jacqueline S; Patel, Aniruddh P; Zhang, Yiyi; Jurgens, Sean J; Maamari, Dimitri J; Wang, Minxian; Eric Boerwinkle; Morrison, Alanna C; de Vries, Paul S; Fornage, Myriam; Hou, Lifang; Lloyd-Jones, Donald M; et al. (JAMA Cardiol, 2023)
IMPORTANCE: Protein-truncating variants (PTVs) in apolipoprotein B (APOB) and proprotein convertase subtilisin/kexin type 9 (PCSK9) are associated with significantly lower low-density lipoprotein (LDL) cholesterol concentrations. The association of these PTVs with coronary heart disease (CHD) warrants further characterization in large, multiracial prospective cohort studies. OBJECTIVE: To evaluate the association of PTVs in APOB and PCSK9 with LDL cholesterol concentrations and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: This studied included participants from 5 National Heart, Lung, and Blood Institute (NHLBI) studies and the UK Biobank. NHLBI study participants aged 5 to 84 years were recruited between 1971 and 2002 across the US and underwent whole-genome sequencing. UK Biobank participants aged 40 to 69 years were recruited between 2006 and 2010 in the UK and underwent whole-exome sequencing. Data were analyzed from June 2021 to October 2022. EXPOSURES: PTVs in APOB and PCSK9. MAIN OUTCOMES AND MEASURES: Estimated untreated LDL cholesterol levels and CHD. RESULTS: Among 19 073 NHLBI participants (10 598 [55.6%] female; mean [SD] age, 52 [17] years), 139 (0.7%) carried an APOB or PCSK9 PTV, which was associated with 49 mg/dL (95% CI, 43-56) lower estimated untreated LDL cholesterol level. Over a median (IQR) follow-up of 21.5 (13.9-29.4) years, incident CHD was observed in 12 of 139 carriers (8.6%) vs 3029 of 18 934 noncarriers (16.0%), corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.28-0.89; P = .02). Among 190 464 UK Biobank participants (104 831 [55.0%] female; mean [SD] age, 57 [8] years), 662 (0.4%) carried a PTV, which was associated with 45 mg/dL (95% CI, 42-47) lower estimated untreated LDL cholesterol level. Estimated CHD risk by age 75 years was 3.7% (95% CI, 2.0-5.3) in carriers vs 7.0% (95% CI, 6.9-7.2) in noncarriers, corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.32-0.81; P = .004). CONCLUSIONS AND RELEVANCE: Among 209 537 individuals in this study, 0.4% carried an APOB or PCSK9 PTV that was associated with less exposure to LDL cholesterol and a 49% lower risk of CHD.
Keywords: Adult; Aged; Apolipoproteins B; Cholesterol, LDL; Coronary Disease; DNA; Female; Humans; Male; Middle Aged; Proprotein Convertase 9; Prospective Studies

Bi-allelic SNAPC4 variants dysregulate global alternative splicing and lead to neuroregression and progressive spastic paraparesis. - Frost, F Graeme; Morimoto, Marie; Sharma, Prashant; Ruaud, Lyse; Belnap, Newell; Calame, Daniel G; Uchiyama, Yuri; Matsumoto, Naomichi; Oud, Machteld M; Ferreira, Elise A; Narayanan, Vinodh; Rangasamy, Sampath; et al. (Am J Hum Genet, 2023)
The vast majority of human genes encode multiple isoforms through alternative splicing, and the temporal and spatial regulation of those isoforms is critical for organismal development and function. The spliceosome, which regulates and executes splicing reactions, is primarily composed of small nuclear ribonucleoproteins (snRNPs) that consist of small nuclear RNAs (snRNAs) and protein subunits. snRNA gene transcription is initiated by the snRNA-activating protein complex (SNAPc). Here, we report ten individuals, from eight families, with bi-allelic, deleterious SNAPC4 variants. SNAPC4 encoded one of the five SNAPc subunits that is critical for DNA binding. Most affected individuals presented with delayed motor development and developmental regression after the first year of life, followed by progressive spasticity that led to gait alterations, paraparesis, and oromotor dysfunction. Most individuals had cerebral, cerebellar, or basal ganglia volume loss by brain MRI. In the available cells from affected individuals, SNAPC4 abundance was decreased compared to unaffected controls, suggesting that the bi-allelic variants affect SNAPC4 accumulation. The depletion of SNAPC4 levels in HeLa cell lines via genomic editing led to decreased snRNA expression and global dysregulation of alternative splicing. Analysis of available fibroblasts from affected individuals showed decreased snRNA expression and global dysregulation of alternative splicing compared to unaffected cells. Altogether, these data suggest that these bi-allelic SNAPC4 variants result in loss of function and underlie the neuroregression and progressive spasticity in these affected individuals.
Keywords: Adolescent; Alleles; Alternative Splicing; Child; Child, Preschool; DNA-Binding Proteins; Female; HeLa Cells; Humans; Infant; Male; Paraparesis, Spastic; Pedigree; Protein Isoforms; Protein Structure, Secondary; RNA, Small Nuclear; RNA-Seq; Transcription Factors

Brain monoamine vesicular transport disease caused by homozygous SLC18A2 variants: A study in 42 affected individuals. - Saida, Ken; Maroofian, Reza; Sengoku, Toru; Mitani, Tadahiro; Pagnamenta, Alistair T; Marafi, Dana; Zaki, Maha S; O'Brien, Thomas J; Karimiani, Ehsan Ghayoor; Kaiyrzhanov, Rauan; Takizawa, Marina; Ohori, Sachiko; et al. (Genet Med, 2023)
PURPOSE: Brain monoamine vesicular transport disease is an infantile-onset movement disorder that mimics cerebral palsy. In 2013, the homozygous SLC18A2 variant, p.Pro387Leu, was first reported as a cause of this rare disorder, and dopamine agonists were efficient for treating affected individuals from a single large family. To date, only 6 variants have been reported. In this study, we evaluated genotype-phenotype correlations in individuals with biallelic SLC18A2 variants. METHODS: A total of 42 affected individuals with homozygous SLC18A2 variant alleles were identified. We evaluated genotype-phenotype correlations and the missense variants in the affected individuals based on the structural modeling of rat VMAT2 encoded by Slc18a2, with cytoplasm- and lumen-facing conformations. A Caenorhabditis elegans model was created for functional studies. RESULTS: A total of 19 homozygous SLC18A2 variants, including 3 recurrent variants, were identified using exome sequencing. The affected individuals typically showed global developmental delay, hypotonia, dystonia, oculogyric crisis, and autonomic nervous system involvement (temperature dysregulation/sweating, hypersalivation, and gastrointestinal dysmotility). Among the 58 affected individuals described to date, 16 (28%) died before the age of 13 years. Of the 17 patients with p.Pro237His, 9 died, whereas all 14 patients with p.Pro387Leu survived. Although a dopamine agonist mildly improved the disease symptoms in 18 of 21 patients (86%), some affected individuals with p.Ile43Phe and p.Pro387Leu showed milder phenotypes and presented prolonged survival even without treatment. The C. elegans model showed behavioral abnormalities. CONCLUSION: These data expand the phenotypic and genotypic spectra of SLC18A2-related disorders.
Keywords: Amines; Animals; Brain; Brain Diseases; Caenorhabditis elegans; Dystonia; Humans; Movement Disorders; Rats; Vesicular Monoamine Transport Proteins

Broadening the phenotypic and molecular spectrum of FINCA syndrome: Biallelic NHLRC2 variants in 15 novel individuals. - Sczakiel, Henrike L; Zhao, Max; Wollert-Wulf, Brigitte; Danyel, Magdalena; Ehmke, Nadja; Stoltenburg, Corinna; Damseh, Nadirah; Al-Ashhab, Motee; Balci, Tugce B; Osmond, Matthew; Andrade, Andrea; Schallner, Jens; et al. (Eur J Hum Genet, 2023)
FINCA syndrome [MIM: 618278] is an autosomal recessive multisystem disorder characterized by fibrosis, neurodegeneration and cerebral angiomatosis. To date, 13 patients from nine families with biallelic NHLRC2 variants have been published. In all of them, the recurrent missense variant p.(Asp148Tyr) was detected on at least one allele. Common manifestations included lung or muscle fibrosis, respiratory distress, developmental delay, neuromuscular symptoms and seizures often followed by early death due to rapid disease progression.Here, we present 15 individuals from 12 families with an overlapping phenotype associated with nine novel NHLRC2 variants identified by exome analysis. All patients described here presented with moderate to severe global developmental delay and variable disease progression. Seizures, truncal hypotonia and movement disorders were frequently observed. Notably, we also present the first eight cases in which the recurrent p.(Asp148Tyr) variant was not detected in either homozygous or compound heterozygous state.We cloned and expressed all novel and most previously published non-truncating variants in HEK293-cells. From the results of these functional studies, we propose a potential genotype-phenotype correlation, with a greater reduction in protein expression being associated with a more severe phenotype.Taken together, our findings broaden the known phenotypic and molecular spectrum and emphasize that NHLRC2-related disease should be considered in patients presenting with intellectual disability, movement disorders, neuroregression and epilepsy with or without pulmonary involvement.
Keywords: Disease Progression; Fibrosis; HEK293 Cells; Humans; Intellectual Disability; Movement Disorders; Phenotype; Seizures; Syndrome

The clinical and genetic spectrum of autosomal-recessive TOR1A-related disorders. - Saffari, Afshin; Lau, Tracy; Tajsharghi, Homa; Karimiani, Ehsan Ghayoor; Kariminejad, Ariana; Efthymiou, Stephanie; Zifarelli, Giovanni; Sultan, Tipu; Toosi, Mehran Beiraghi; Sedighzadeh, Sahar; Siu, Victoria Mok; Ortigoza-Escobar, Juan Darío; et al. (Brain, 2023)
In the field of rare diseases, progress in molecular diagnostics led to the recognition that variants linked to autosomal-dominant neurodegenerative diseases of later onset can, in the context of biallelic inheritance, cause devastating neurodevelopmental disorders and infantile or childhood-onset neurodegeneration. TOR1A-associated arthrogryposis multiplex congenita 5 (AMC5) is a rare neurodevelopmental disorder arising from biallelic variants in TOR1A, a gene that in the heterozygous state is associated with torsion dystonia-1 (DYT1 or DYT-TOR1A), an early-onset dystonia with reduced penetrance. While 15 individuals with AMC5-TOR1A have been reported (less than 10 in detail), a systematic investigation of the full disease-associated spectrum has not been conducted. Here, we assess the clinical, radiological and molecular characteristics of 57 individuals from 40 families with biallelic variants in TOR1A. Median age at last follow-up was 3 years (0-24 years). Most individuals presented with severe congenital flexion contractures (95%) and variable developmental delay (79%). Motor symptoms were reported in 79% and included lower limb spasticity and pyramidal signs, as well as gait disturbances. Facial dysmorphism was an integral part of the phenotype, with key features being a broad/full nasal tip, narrowing of the forehead and full cheeks. Analysis of disease-associated manifestations delineated a phenotypic spectrum ranging from normal cognition and mild gait disturbance to congenital arthrogryposis, global developmental delay, intellectual disability, absent speech and inability to walk. In a subset, the presentation was consistent with foetal akinesia deformation sequence with severe intrauterine abnormalities. Survival was 71%, with higher mortality in males. Death occurred at a median age of 1.2 months (1 week-9 years), due to respiratory failure, cardiac arrest or sepsis. Analysis of brain MRI studies identified non-specific neuroimaging features, including a hypoplastic corpus callosum (72%), foci of signal abnormality in the subcortical and periventricular white matter (55%), diffuse white matter volume loss (45%), mega cisterna magna (36%) and arachnoid cysts (27%). The molecular spectrum included 22 distinct variants, defining a mutational hotspot in the C-terminal domain of the Torsin-1A protein. Genotype-phenotype analysis revealed an association of missense variants in the 3-helix bundle domain to an attenuated phenotype, while missense variants near the Walker A/B motif as well as biallelic truncating variants were linked to early death. In summary, this systematic cross-sectional analysis of a large cohort of individuals with biallelic TOR1A variants across a wide age-range delineates the clinical and genetic spectrum of TOR1A-related autosomal-recessive disease and highlights potential predictors for disease severity and survival.
Keywords: Cross-Sectional Studies; Dystonia; Dystonic Disorders; Humans; Male; Molecular Chaperones; Mutation; Nervous System Malformations; Phenotype

Clonal haematopoiesis and risk of chronic liver disease. - Wong, Waihay J; Emdin, Connor; Bick, Alexander G; Zekavat, Seyedeh M; Niroula, Abhishek; Pirruccello, James P; Dichtel, Laura; Griffin, Gabriel; Uddin, Md Mesbah; Gibson, Christopher J; Kovalcik, Veronica; Lin, Amy E; et al. (Nature, 2023)
Chronic liver disease is a major public health burden worldwide. Although different aetiologies and mechanisms of liver injury exist, progression of chronic liver disease follows a common pathway of liver inflammation, injury and fibrosis. Here we examined the association between clonal haematopoiesis of indeterminate potential (CHIP) and chronic liver disease in 214,563 individuals from 4 independent cohorts with whole-exome sequencing data (Framingham Heart Study, Atherosclerosis Risk in Communities Study, UK Biobank and Mass General Brigham Biobank). CHIP was associated with an increased risk of prevalent and incident chronic liver disease (odds ratio = 2.01, 95% confidence interval (95% CI) [1.46, 2.79]; P < 0.001). Individuals with CHIP were more likely to demonstrate liver inflammation and fibrosis detectable by magnetic resonance imaging compared to those without CHIP (odds ratio = 1.74, 95% CI [1.16, 2.60]; P = 0.007). To assess potential causality, Mendelian randomization analyses showed that genetic predisposition to CHIP was associated with a greater risk of chronic liver disease (odds ratio = 2.37, 95% CI [1.57, 3.6]; P < 0.001). In a dietary model of non-alcoholic steatohepatitis, mice transplanted with Tet2-deficient haematopoietic cells demonstrated more severe liver inflammation and fibrosis. These effects were mediated by the NLRP3 inflammasome and increased levels of expression of downstream inflammatory cytokines in Tet2-deficient macrophages. In summary, clonal haematopoiesis is associated with an elevated risk of liver inflammation and chronic liver disease progression through an aberrant inflammatory response.
Keywords: Animals; Clonal Hematopoiesis; Disease Progression; Disease Susceptibility; Hepatitis; Inflammation; Liver Cirrhosis; Mice; Non-alcoholic Fatty Liver Disease; Odds Ratio

The complete sequence of a human Y chromosome. - Rhie, Arang; Nurk, Sergey; Cechova, Monika; Hoyt, Savannah J; Taylor, Dylan J; Altemose, Nicolas; Hook, Paul W; Koren, Sergey; Rautiainen, Mikko; Alexandrov, Ivan A; Allen, Jamie; Asri, Mobin; et al. (Nature, 2023)
The human Y chromosome has been notoriously difficult to sequence and assemble because of its complex repeat structure that includes long palindromes, tandem repeats and segmental duplications. As a result, more than half of the Y chromosome is missing from the GRCh38 reference sequence and it remains the last human chromosome to be finished. Here, the Telomere-to-Telomere (T2T) consortium presents the complete 62,460,029-base-pair sequence of a human Y chromosome from the HG002 genome (T2T-Y) that corrects multiple errors in GRCh38-Y and adds over 30 million base pairs of sequence to the reference, showing the complete ampliconic structures of gene families TSPY, DAZ and RBMY; 41 additional protein-coding genes, mostly from the TSPY family; and an alternating pattern of human satellite 1 and 3 blocks in the heterochromatic Yq12 region. We have combined T2T-Y with a previous assembly of the CHM13 genome and mapped available population variation, clinical variants and functional genomics data to produce a complete and comprehensive reference sequence for all 24 human chromosomes.
Keywords: Base Sequence; Chromosomes, Human, Y; DNA, Satellite; Genetic Variation; Genetics, Population; Genomics; Heterochromatin; Humans; Multigene Family; Reference Standards; Segmental Duplications, Genomic; Sequence Analysis, DNA; Tandem Repeat Sequences; Telomere

Deleterious heteroplasmic mitochondrial mutations are associated with an increased risk of overall and cancer-specific mortality. - Hong, Yun Soo; Battle, Stephanie L; Shi, Wen; Puiu, Daniela; Pillalamarri, Vamsee; Xie, Jiaqi; Pankratz, Nathan; Lake, Nicole J; Lek, Monkol; Rotter, Jerome I; Rich, Stephen S; Kooperberg, Charles; et al. (Nat Commun, 2023)
Mitochondria carry their own circular genome and disruption of the mitochondrial genome is associated with various aging-related diseases. Unlike the nuclear genome, mitochondrial DNA (mtDNA) can be present at 1000 s to 10,000 s copies in somatic cells and variants may exist in a state of heteroplasmy, where only a fraction of the DNA molecules harbors a particular variant. We quantify mtDNA heteroplasmy in 194,871 participants in the UK Biobank and find that heteroplasmy is associated with a 1.5-fold increased risk of all-cause mortality. Additionally, we functionally characterize mtDNA single nucleotide variants (SNVs) using a constraint-based score, mitochondrial local constraint score sum (MSS) and find it associated with all-cause mortality, and with the prevalence and incidence of cancer and cancer-related mortality, particularly leukemia. These results indicate that mitochondria may have a functional role in certain cancers, and mitochondrial heteroplasmic SNVs may serve as a prognostic marker for cancer, especially for leukemia.
Keywords: DNA, Mitochondrial; Heteroplasmy; Humans; Leukemia; Mitochondria; Mutation

Divergent BRAF Inhibitor Resistance Mechanisms Revealed through Epigenetic Mapping. - Kang, Yuanyuan; Ji, Zhenyu; Li, He; Tsao, Hensin (J Invest Dermatol, 2023)
Although tremendous progress has been made in targeted and immune-based treatments for advanced melanoma, there remains a substantial therapeutic failure rate. For patients with BRAF(V600)-mutant melanomas, resistance to BRAF inhibitors remains a significant survival hurdle. Although multiple compensatory mechanisms to bypass BRAF blockade have been discovered, the epigenetic patterns are still poorly characterized. In this report, we generated eight matched pairs of vemurafenib-sensitive/-resistant melanoma lines and subjected these to concurrent RNA-sequencing and H3K27ac chromatin immunoprecipitation sequencing analysis. Globally, we identified two classes of epigenetic profiles that correlate with resistance. Class 1 resistance involves fewer RNA expression alterations accompanied by fewer enhancer mark changes with H3K27ac. Class 2 resistance shows widespread alterations in transcription and enhancer profiles, which converge on epithelial‒mesenchymal transition and hypoxia-related pathways. We also observed significant and dynamic changes in superenhancers that underpin these transcriptomic patterns. We subsequently verified the two-class structure in pre-BRAF inhibitors and postrelapse human melanoma specimens. Our findings reveal a broad and underappreciated spectrum of epigenetic plasticity during acquired BRAF inhibitor resistance.
Keywords: Cell Line, Tumor; Drug Resistance, Neoplasm; Epigenesis, Genetic; Humans; Indoles; Melanoma; Mutation; Protein Kinase Inhibitors; Proto-Oncogene Proteins B-raf; RNA; Sulfonamides

Epigenetic and integrative cross-omics analyses of cerebral white matter hyperintensities on MRI. - Yang, Yunju; Knol, Maria J; Wang, Ruiqi; Mishra, Aniket; Liu, Dan; Luciano, Michelle; Teumer, Alexander; Armstrong, Nicola; Bis, Joshua C; Jhun, Min A; Li, Shuo; Adams, Hieab H H; et al. (Brain, 2023)
Cerebral white matter hyperintensities on MRI are markers of cerebral small vessel disease, a major risk factor for dementia and stroke. Despite the successful identification of multiple genetic variants associated with this highly heritable condition, its genetic architecture remains incompletely understood. More specifically, the role of DNA methylation has received little attention. We investigated the association between white matter hyperintensity burden and DNA methylation in blood at ∼450 000 cytosine-phosphate-guanine (CpG) sites in 9732 middle-aged to older adults from 14 community-based studies. Single CpG and region-based association analyses were carried out. Functional annotation and integrative cross-omics analyses were performed to identify novel genes underlying the relationship between DNA methylation and white matter hyperintensities. We identified 12 single CpG and 46 region-based DNA methylation associations with white matter hyperintensity burden. Our top discovery single CpG, cg24202936 (P = 7.6 × 10-8), was associated with F2 expression in blood (P = 6.4 × 10-5) and co-localized with FOLH1 expression in brain (posterior probability = 0.75). Our top differentially methylated regions were in PRMT1 and in CCDC144NL-AS1, which were also represented in single CpG associations (cg17417856 and cg06809326, respectively). Through Mendelian randomization analyses cg06809326 was putatively associated with white matter hyperintensity burden (P = 0.03) and expression of CCDC144NL-AS1 possibly mediated this association. Differentially methylated region analysis, joint epigenetic association analysis and multi-omics co-localization analysis consistently identified a role of DNA methylation near SH3PXD2A, a locus previously identified in genome-wide association studies of white matter hyperintensities. Gene set enrichment analyses revealed functions of the identified DNA methylation loci in the blood-brain barrier and in the immune response. Integrative cross-omics analysis identified 19 key regulatory genes in two networks related to extracellular matrix organization, and lipid and lipoprotein metabolism. A drug-repositioning analysis indicated antihyperlipidaemic agents, more specifically peroxisome proliferator-activated receptor-alpha, as possible target drugs for white matter hyperintensities. Our epigenome-wide association study and integrative cross-omics analyses implicate novel genes influencing white matter hyperintensity burden, which converged on pathways related to the immune response and to a compromised blood-brain barrier possibly due to disrupted cell-cell and cell-extracellular matrix interactions. The results also suggest that antihyperlipidaemic therapy may contribute to lowering risk for white matter hyperintensities possibly through protection against blood-brain barrier disruption.
Keywords: Aged; Brain; DNA Methylation; Epigenesis, Genetic; Genome-Wide Association Study; Humans; Magnetic Resonance Imaging; Middle Aged; Protein-Arginine N-Methyltransferases; Repressor Proteins; White Matter

Functional characterization of age-dependent p16 epimutation reveals biological drivers and therapeutic targets for colorectal cancer. - Yang, Li; Chen, Xiaomin; Lee, Christy; Shi, Jiejun; Lawrence, Emily B; Zhang, Lanjing; Yumei Li; Gao, Nan; Jung, Sung Yun; Creighton, Chad J; Li, Jingyi Jessica; Cui, Ya; et al. (J Exp Clin Cancer Res, 2023)
BACKGROUND: Methylation of the p16 promoter resulting in epigenetic gene silencing-known as p16 epimutation-is frequently found in human colorectal cancer and is also common in normal-appearing colonic mucosa of aging individuals. Thus, to improve clinical care of colorectal cancer (CRC) patients, we explored the role of age-related p16 epimutation in intestinal tumorigenesis. METHODS: We established a mouse model that replicates two common genetic and epigenetic events observed in human CRCs: Apc mutation and p16 epimutation. We conducted long-term survival and histological analysis of tumor development and progression. Colonic epithelial cells and tumors were collected from mice and analyzed by RNA sequencing (RNA-seq), quantitative PCR, and flow cytometry. We performed single-cell RNA sequencing (scRNA-seq) to characterize tumor-infiltrating immune cells throughout tumor progression. We tested whether anti-PD-L1 immunotherapy affects overall survival of tumor-bearing mice and whether inhibition of both epigenetic regulation and immune checkpoint is more efficacious. RESULTS: Mice carrying combined Apc mutation and p16 epimutation had significantly shortened survival and increased tumor growth compared to those with Apc mutation only. Intriguingly, colon tumors with p16 epimutation exhibited an activated interferon pathway, increased expression of programmed death-ligand 1 (Pdl1), and enhanced infiltration of immune cells. scRNA-seq further revealed the presence of Foxp3 Tregs and γδT17 cells, which contribute to an immunosuppressive tumor microenvironment (TME). Furthermore, we showed that a combined therapy using an inhibitor of DNA methylation and a PD-L1 immune checkpoint inhibitor is more effective for improving survival in tumor-bearing mice than blockade of either pathway alone. CONCLUSIONS: Our study demonstrated that age-dependent p16 epimutation creates a permissive microenvironment for malignant transformation of polyps to colon cancer. Our findings provide a mechanistic rationale for future targeted therapy in patients with p16 epimutation.
Keywords: Animals; B7-H1 Antigen; Carcinogenesis; Cell Transformation, Neoplastic; Colonic Neoplasms; Colorectal Neoplasms; DNA Methylation; Epigenesis, Genetic; Humans; Mice; Tumor Microenvironment

Gene augmentation therapy to rescue degenerative photoreceptors in a Cwc27 mutant mouse model. - Lu, Jiaxiong; Zheng, Karen Q; Bertrand, Renae Elaine; Quinlan, Joseph; Ferdous, Salma; Srinivasan, Tanmay; Oh, Soo; Wang, Keqing; Rui Chen (Exp Eye Res, 2023)
Previous reports have demonstrated that defects in the spliceosome-associated protein CWC27 can lead to the degeneration of retinal cells in Cwc27 mutant mouse models. However, it is unknown whether gene replacement therapy can rescue this phenotype. The purpose of this study was to evaluate whether AAV based gene therapy could rescue the retinal degeneration observed in Cwc27 mutant mice. By 6 months of age, Cwc27 mutant mice show a retinal degenerative phenotype, including morphological and functional abnormalities, primarily driven by the death of photoreceptors. We hypothesize that subretinal injection of AAV8 to drive exogenous CWC27 protein expression will improve the retinal phenotype. We evaluated these improvements after gene therapy with electroretinography (ERG) and histology, either hematoxylin and eosin (H&E) or immunostaining. In this study, we demonstrated that subretinal injection of AAV8-GRK-Cwc27-FLAG in mutant mice can improve the functionality and morphology of the retina. Immunostaining analyses revealed a notable decrease in photoreceptor degeneration, including cone cell degeneration, in the AAV-injected eyes compared to the PBS-injected eyes. Based on these results, gene replacement therapy could be a promising method for treating retinal degeneration caused by mutations in Cwc27.
Keywords: Animals; Disease Models, Animal; Electroretinography; Genetic Therapy; Genetic Vectors; Mice; Retina; Retinal Cone Photoreceptor Cells; Retinal Degeneration

The genomic landscape of familial glioma. - Choi, Dong-Joo; Armstrong, Georgina; Lozzi, Brittney; Vijayaraghavan, Prashanth; Plon, Sharon E; Wong, Terence C; Eric Boerwinkle; Donna M Muzny; Chen, Hsiao-Chi; Richard A Gibbs; Ostrom, Quinn T; Melin, Beatrice; et al. (Sci Adv, 2023)
Glioma is a rare brain tumor with a poor prognosis. Familial glioma is a subset of glioma with a strong genetic predisposition that accounts for approximately 5% of glioma cases. We performed whole-genome sequencing on an exploratory cohort of 203 individuals from 189 families with a history of familial glioma and an additional validation cohort of 122 individuals from 115 families. We found significant enrichment of rare deleterious variants of seven genes in both cohorts, and the most significantly enriched gene was ( = 0.0006). Furthermore, we identified rare noncoding variants in both cohorts that were predicted to affect transcription factor binding sites or cause cryptic splicing. Last, we selected a subset of discovered genes for validation by CRISPR knockdown screening and found that , have profound impacts on proliferation. This study performs comprehensive surveillance of the genomic landscape of familial glioma.
Keywords: Brain Neoplasms; Calcium-Binding Proteins; DNA-Binding Proteins; Genetic Predisposition to Disease; Genomics; Glioma; Humans; Tumor Suppressor Proteins; Whole Genome Sequencing

Global impact of somatic structural variation on the cancer proteome. - Chen, Fengju; Zhang, Yiqun; Chandrashekar, Darshan S; Varambally, Sooryanarayana; Creighton, Chad J (Nat Commun, 2023)
Both proteome and transcriptome data can help assess the relevance of non-coding somatic mutations in cancer. Here, we combine mass spectrometry-based proteomics data with whole genome sequencing data across 1307 human tumors spanning various tissues to determine the extent somatic structural variant (SV) breakpoint patterns impact protein expression of nearby genes. We find that about 25% of the hundreds of genes with SV-associated cis-regulatory alterations at the mRNA level are similarly associated at the protein level. SVs associated with enhancer hijacking, retrotransposon translocation, altered DNA methylation, or fusion transcripts are implicated in protein over-expression. SVs combined with altered protein levels considerably extend the numbers of patients with tumors somatically altered for critical pathways. We catalog both SV breakpoint patterns involving patient survival and genes with nearby SV breakpoints associated with increased cell dependency in cancer cell lines. Pan-cancer proteogenomics identifies targetable non-coding alterations, by virtue of the associated deregulated genes.
Keywords: Cell Line; DNA Methylation; Humans; Mass Spectrometry; Neoplasms; Proteome

Identification of Dietary Supplements Associated with Blood Metabolites in the Hispanic Community Health Study/Study of Latinos Cohort Study. - Kaplan, Robert C; Williams-Nguyen, Jessica S; Huang, Yuhan; Mossavar-Rahmani, Yasmin; Yu, Bing; Eric Boerwinkle; Gellman, Marc D; Daviglus, Martha; Chilcoat, Aisha; Van Horn, Linda; Faurot, Kim; Qi, Qibin; et al. (J Nutr, 2023)
BACKGROUND: Metabolomics approaches have been widely used to define the consumption of foods but have less often been used to study exposure to dietary supplements. OBJECTIVES: This study aimed to identify dietary supplements associated with metabolite levels and to examine whether these metabolites predicted incident diabetes risk. METHODS: We studied 3972 participants from a prospective cohort study of 18-74-y-old Hispanic/Latino adults. At a baseline examination, we ascertained use of dietary supplements using recall methods and concurrently, a serum metabolomic panel. After adjustment for potential confounders, we identified dietary supplements associated with metabolites. We then examined the association of these metabolites with incident diabetes at the 6-y study examination. RESULTS: We observed a total of 110 dietary supplement-metabolite associations that met the criteria for statistical significance adjusted for age, sex, field center, Hispanic/Latino background, body mass index, diet, smoking, physical activity, and number of medications (adjusted P < 0.05). This included 13 metabolites uniquely associated with only one dietary supplement ingredient. Vitamin C had the most associated metabolites (n = 15), including positive associations with oxalate, tartronate, threonate, and isocitrate, which were each in turn protective for the risk of incident diabetes. Vitamin C was also associated with higher N-acetylvaline level, which was an unfavorable diabetes risk factor. Other findings related to branched chain amino acid related compounds including α-hydroxyisovalerate and 2-hydroxy-3-methylvalerate, which were inversely associated with thiamine or riboflavin intake and also predicted higher diabetes risk. Vitamin B12 had an inverse association with γ-glutamylvaline, levels of which were positively associated with the risk of diabetes. CONCLUSIONS: Our data point to potential metabolite changes associated with vitamin C and B vitamins, which may have favorable metabolic effects. Knowledge of blood metabolites that can be modified by dietary supplement intake may aid understanding the health effects of dietary supplements and identify potential biological mediators.
Keywords: Ascorbic Acid; Cohort Studies; Dietary Supplements; Hispanic or Latino; Humans; Prospective Studies; Public Health; Vitamin B Complex

Investigating Gene-Diet Interactions Impacting the Association Between Macronutrient Intake and Glycemic Traits. - Westerman, Kenneth E; Walker, Maura E; Gaynor, Sheila M; Wessel, Jennifer; DiCorpo, Daniel; Ma, Jiantao; Alonso, Alvaro; Aslibekyan, Stella; Baldridge, Abigail S; Bertoni, Alain G; Biggs, Mary L; Brody, Jennifer A; et al. (Diabetes, 2023)
UNLABELLED: Few studies have demonstrated reproducible gene-diet interactions (GDIs) impacting metabolic disease risk factors, likely due in part to measurement error in dietary intake estimation and insufficient capture of rare genetic variation. We aimed to identify GDIs across the genetic frequency spectrum impacting the macronutrient-glycemia relationship in genetically and culturally diverse cohorts. We analyzed 33,187 participants free of diabetes from 10 National Heart, Lung, and Blood Institute Trans-Omics for Precision Medicine program cohorts with whole-genome sequencing, self-reported diet, and glycemic trait data. We fit cohort-specific, multivariable-adjusted linear mixed models for the effect of diet, modeled as an isocaloric substitution of carbohydrate for fat, and its interactions with common and rare variants genome-wide. In main effect meta-analyses, participants consuming more carbohydrate had modestly lower glycemic trait values (e.g., for glycated hemoglobin [HbA1c], -0.013% HbA1c/250 kcal substitution). In GDI meta-analyses, a common African ancestry-enriched variant (rs79762542) reached study-wide significance and replicated in the UK Biobank cohort, indicating a negative carbohydrate-HbA1c association among major allele homozygotes only. Simulations revealed that >150,000 samples may be necessary to identify similar macronutrient GDIs under realistic assumptions about effect size and measurement error. These results generate hypotheses for further exploration of modifiable metabolic disease risk in additional cohorts with African ancestry. ARTICLE HIGHLIGHTS: We aimed to identify genetic modifiers of the dietary macronutrient-glycemia relationship using whole-genome sequence data from 10 Trans-Omics for Precision Medicine program cohorts. Substitution models indicated a modest reduction in glycemia associated with an increase in dietary carbohydrate at the expense of fat. Genome-wide interaction analysis identified one African ancestry-enriched variant near the FRAS1 gene that may interact with macronutrient intake to influence hemoglobin A1c. Simulation-based power calculations accounting for measurement error suggested that substantially larger sample sizes may be necessary to discover further gene-macronutrient interactions.
Keywords: Diabetes Mellitus; Diet; Eating; Genome-Wide Association Study; Glycated Hemoglobin; Guanine Nucleotide Dissociation Inhibitors; Humans

Molecular basis of retinal remodeling in a zebrafish model of retinitis pigmentosa. - Santhanam, Abirami; Shihabeddin, Eyad; Wei, Haichao; Wu, Jiaqian; O'Brien, John (Cell Mol Life Sci, 2023)
A hallmark of inherited retinal degenerative diseases such as retinitis pigmentosa (RP) is progressive structural and functional remodeling of the remaining retinal cells as photoreceptors degenerate. Extensive remodeling of the retina stands as a barrier for the successful implementation of strategies to restore vision. To understand the molecular basis of remodeling, we performed analyses of single-cell transcriptome data from adult zebrafish retina of wild type AB strain (WT) and a P23H mutant rhodopsin transgenic model of RP with continuous degeneration and regeneration. Retinas from both female and male fish were pooled to generate each library, combining data from both sexes. We provide a benchmark atlas of retinal cell type transcriptomes in zebrafish and insight into how each retinal cell type is affected in the P23H model. Oxidative stress is found throughout the retina, with increases in reliance on oxidative metabolism and glycolysis in the affected rods as well as cones, bipolar cells, and retinal ganglion cells. There is also transcriptional evidence for widespread synaptic remodeling and enhancement of glutamatergic transmission in the inner retina. Notably, changes in circadian rhythm regulation are detected in cones, bipolar cells, and retinal pigmented epithelium. We also identify the transcriptomic signatures of retinal progenitor cells and newly formed rods essential for the regenerative process. This comprehensive transcriptomic analysis provides a molecular road map to understand how the retina remodels in the context of chronic retinal degeneration with ongoing regeneration.
Keywords: Animals; Disease Models, Animal; Female; Male; Retina; Retinal Degeneration; Retinal Rod Photoreceptor Cells; Retinitis Pigmentosa; Zebrafish

Monoallelic variation in DHX9, the gene encoding the DExH-box helicase DHX9, underlies neurodevelopment disorders and Charcot-Marie-Tooth disease. - Calame, Daniel G; Guo, Tianyu; Wang, Chen; Garrett, Lillian; Jolly, Angad; Dawood, Moez; Kurolap, Alina; Henig, Noa Zunz; Fatih, Jawid M; Herman, Isabella; Du, Haowei; Mitani, Tadahiro; et al. (Am J Hum Genet, 2023)
DExD/H-box RNA helicases (DDX/DHX) are encoded by a large paralogous gene family; in a subset of these human helicase genes, pathogenic variation causes neurodevelopmental disorder (NDD) traits and cancer. DHX9 encodes a BRCA1-interacting nuclear helicase regulating transcription, R-loops, and homologous recombination and exhibits the highest mutational constraint of all DDX/DHX paralogs but remains unassociated with disease traits in OMIM. Using exome sequencing and family-based rare-variant analyses, we identified 20 individuals with de novo, ultra-rare, heterozygous missense or loss-of-function (LoF) DHX9 variant alleles. Phenotypes ranged from NDDs to the distal symmetric polyneuropathy axonal Charcot-Marie-Tooth disease (CMT2). Quantitative Human Phenotype Ontology (HPO) analysis demonstrated genotype-phenotype correlations with LoF variants causing mild NDD phenotypes and nuclear localization signal (NLS) missense variants causing severe NDD. We investigated DHX9 variant-associated cellular phenotypes in human cell lines. Whereas wild-type DHX9 was restricted to the nucleus, NLS missense variants abnormally accumulated in the cytoplasm. Fibroblasts from an individual with an NLS variant also showed abnormal cytoplasmic DHX9 accumulation. CMT2-associated missense variants caused aberrant nucleolar DHX9 accumulation, a phenomenon previously associated with cellular stress. Two NDD-associated variants, p.Gly411Glu and p.Arg761Gln, altered DHX9 ATPase activity. The severe NDD-associated variant p.Arg141Gln did not affect DHX9 localization but instead increased R-loop levels and double-stranded DNA breaks. Dhx9 mice exhibited hypoactivity in novel environments, tremor, and sensorineural hearing loss. All together, these results establish DHX9 as a critical regulator of mammalian neurodevelopment and neuronal homeostasis.
Keywords: Animals; Cell Line; Charcot-Marie-Tooth Disease; DEAD-box RNA Helicases; Dichlorodiphenyl Dichloroethylene; DNA Helicases; Humans; Mammals; Mice; Neoplasm Proteins; Neurodevelopmental Disorders

Rare Genetic Variants Associated With Sudden Cardiac Arrest in the Young: A Prospective, Population-Based Study. - Holmstrom, Lauri; Chaudhary, Ninad S; Nakamura, Kotoka; Chugh, Harpriya; Uy-Evanado, Audrey; Norby, Faye; Ginger A Metcalf; Menon, Vipin K; Yu, Bing; Eric Boerwinkle; Chugh, Sumeet S; Akdemir, Zeynep; et al. (Circ Genom Precis Med, 2023)
Keywords: Death, Sudden, Cardiac; Heart Arrest; Humans; Prospective Studies

A single cell genomics atlas of the Drosophila larval eye reveals distinct photoreceptor developmental timelines. - Bollepogu Raja, Komal Kumar; Yeung, Kelvin; Shim, Yoon-Kyung; Yumei Li; Rui Chen; Mardon, Graeme (Nat Commun, 2023)
The Drosophila eye is a powerful model system to study the dynamics of cell differentiation, cell state transitions, cell maturation, and pattern formation. However, a high-resolution single cell genomics resource that accurately profiles all major cell types of the larval eye disc and their spatiotemporal relationships is lacking. Here, we report transcriptomic and chromatin accessibility data for all known cell types in the developing eye. Photoreceptors appear as strands of cells that represent their dynamic developmental timelines. As photoreceptor subtypes mature, they appear to assume a common transcriptomic profile that is dominated by genes involved in axon function. We identify cell type maturation genes, enhancers, and potential regulators, as well as genes with distinct R3 or R4 photoreceptor specific expression. Finally, we observe that the chromatin accessibility between cones and photoreceptors is distinct. These single cell genomics atlases will greatly enhance the power of the Drosophila eye as a model system.
Keywords: Animals; Ascomycota; Cell Differentiation; Chromatin; Drosophila; Genomics; Larva

SRSF1 haploinsufficiency is responsible for a syndromic developmental disorder associated with intellectual disability. - Bogaert, Elke; Garde, Aurore; Gautier, Thierry; Rooney, Kathleen; Duffourd, Yannis; LeBlanc, Pontus; van Reempts, Emma; Tran Mau-Them, Frederic; Wentzensen, Ingrid M; Au, Kit Sing; Richardson, Kate; Northrup, Hope; et al. (Am J Hum Genet, 2023)
SRSF1 (also known as ASF/SF2) is a non-small nuclear ribonucleoprotein (non-snRNP) that belongs to the arginine/serine (R/S) domain family. It recognizes and binds to mRNA, regulating both constitutive and alternative splicing. The complete loss of this proto-oncogene in mice is embryonically lethal. Through international data sharing, we identified 17 individuals (10 females and 7 males) with a neurodevelopmental disorder (NDD) with heterozygous germline SRSF1 variants, mostly de novo, including three frameshift variants, three nonsense variants, seven missense variants, and two microdeletions within region 17q22 encompassing SRSF1. Only in one family, the de novo origin could not be established. All individuals featured a recurrent phenotype including developmental delay and intellectual disability (DD/ID), hypotonia, neurobehavioral problems, with variable skeletal (66.7%) and cardiac (46%) anomalies. To investigate the functional consequences of SRSF1 variants, we performed in silico structural modeling, developed an in vivo splicing assay in Drosophila, and carried out episignature analysis in blood-derived DNA from affected individuals. We found that all loss-of-function and 5 out of 7 missense variants were pathogenic, leading to a loss of SRSF1 splicing activity in Drosophila, correlating with a detectable and specific DNA methylation episignature. In addition, our orthogonal in silico, in vivo, and epigenetics analyses enabled the separation of clearly pathogenic missense variants from those with uncertain significance. Overall, these results indicated that haploinsufficiency of SRSF1 is responsible for a syndromic NDD with ID due to a partial loss of SRSF1-mediated splicing activity.
Keywords: Child; Developmental Disabilities; Female; Haploinsufficiency; Humans; Intellectual Disability; Male; Mutation, Missense; Neurodevelopmental Disorders; Phenotype

Type 2 Diabetes Modifies the Association of CAD Genomic Risk Variants With Subclinical Atherosclerosis. - Hasbani, Natalie R; Westerman, Kenneth E; Kwak, Soo Heon; Chen, Han; Li, Xihao; Di Corpo, Daniel; Wessel, Jennifer; Bis, Joshua C; Sarnowski, Chloe; Wu, Peitao; Bielak, Lawrence F; Guo, Xiuqing; et al. (Circ Genom Precis Med, 2023)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of coronary artery disease (CAD), but questions remain about the underlying pathology. Identifying which CAD loci are modified by T2D in the development of subclinical atherosclerosis (coronary artery calcification [CAC], carotid intima-media thickness, or carotid plaque) may improve our understanding of the mechanisms leading to the increased CAD in T2D. METHODS: We compared the common and rare variant associations of known CAD loci from the literature on CAC, carotid intima-media thickness, and carotid plaque in up to 29 670 participants, including up to 24 157 normoglycemic controls and 5513 T2D cases leveraging whole-genome sequencing data from the Trans-Omics for Precision Medicine program. We included first-order T2D interaction terms in each model to determine whether CAD loci were modified by T2D. The genetic main and interaction effects were assessed using a joint test to determine whether a CAD variant, or gene-based rare variant set, was associated with the respective subclinical atherosclerosis measures and then further determined whether these loci had a significant interaction test. RESULTS: Using a Bonferroni-corrected significance threshold of <1.6×10, we identified 3 genes (, , and ) associated with CAC and 2 genes ( and ) associated with carotid intima-media thickness and carotid plaque, respectively, through gene-based rare variant set analysis. Both and also had significantly different associations for CAC in T2D cases versus controls. No significant interaction tests were identified through the candidate single-variant analysis. CONCLUSIONS: These results highlight T2D as an important modifier of rare variant associations in CAD loci with CAC.
Keywords: Atherosclerosis; Carotid Intima-Media Thickness; Coronary Artery Disease; Diabetes Mellitus, Type 2; Genomics; Humans; Plaque, Atherosclerotic; Risk Factors

Whole-exome sequencing study identifies four novel gene loci associated with diabetic kidney disease. - Pan, Yang; Sun, Xiao; Mi, Xuenan; Huang, Zhijie; Hsu, Yenchih; Hixson, James E; Munzy, Donna; Ginger A Metcalf; Franceschini, Nora; Tin, Adrienne; Köttgen, Anna; Francis, Michael; et al. (Hum Mol Genet, 2023)
Diabetic kidney disease (DKD) is recognized as an important public health challenge. However, its genomic mechanisms are poorly understood. To identify rare variants for DKD, we conducted a whole-exome sequencing (WES) study leveraging large cohorts well-phenotyped for chronic kidney disease and diabetes. Our two-stage WES study included 4372 European and African ancestry participants from the Chronic Renal Insufficiency Cohort and Atherosclerosis Risk in Communities studies (stage 1) and 11 487 multi-ancestry Trans-Omics for Precision Medicine participants (stage 2). Generalized linear mixed models, which accounted for genetic relatedness and adjusted for age, sex and ancestry, were used to test associations between single variants and DKD. Gene-based aggregate rare variant analyses were conducted using an optimized sequence kernel association test implemented within our mixed model framework. We identified four novel exome-wide significant DKD-related loci through initiating diabetes. In single-variant analyses, participants carrying a rare, in-frame insertion in the DIS3L2 gene (rs141560952) exhibited a 193-fold increased odds [95% confidence interval (CI): 33.6, 1105] of DKD compared with noncarriers (P = 3.59 × 10-9). Likewise, each copy of a low-frequency KRT6B splice-site variant (rs425827) conferred a 5.31-fold higher odds (95% CI: 3.06, 9.21) of DKD (P = 2.72 × 10-9). Aggregate gene-based analyses further identified ERAP2 (P = 4.03 × 10-8) and NPEPPS (P = 1.51 × 10-7), which are both expressed in the kidney and implicated in renin-angiotensin-aldosterone system modulated immune response. In the largest WES study of DKD, we identified novel rare variant loci attaining exome-wide significance. These findings provide new insights into the molecular mechanisms underlying DKD.
Keywords: Aminopeptidases; Diabetes Mellitus; Diabetic Nephropathies; Exome Sequencing; Humans; Kidney; Renal Insufficiency, Chronic

γ-aminobutyric acid B2 receptor: A potential therapeutic target for cholangiocarcinoma in patients with diabetes mellitus. - Saengboonmee, Charupong; Sorin, Supannika; Sangkhamanon, Sakkarn; Chomphoo, Surang; Indramanee, Somsiri; Seubwai, Wunchana; Thithuan, Kanyarat; Chiu, Ching-Feng; Okada, Seiji; Marie-Claude Gingras; Wongkham, Sopit (World J Gastroenterol, 2023)
BACKGROUND: The association between diabetes mellitus (DM) and the increased risk and progression of cholangiocarcinoma (CCA) has been reported with unclear underlying mechanisms. Previous studies showed that γ-aminobutyric acid (GABA) B2 receptor (GABBR2) was upregulated in CCA cells cultured in high glucose (HG) conditions. Roles of GABA receptors in CCA progression have also been studied, but their association with DM and hyperglycemia in CCA remains unclarified. AIM: To investigate the effects of hyperglycemia on GABBR2 expression and the potential use of GABBR2 as a CCA therapeutic target. METHODS: CCA cells, KKU-055 and KKU-213A, were cultured in Dulbecco Modified Eagle's Medium supplemented with 5.6 mmol/L (normal glucose, NG) or 25 mmol/L (HG) glucose and assigned as NG and HG cells, respectively. GABBR2 expression in NG and HG cells was investigated using real-time quantitative polymerase chain reaction and western blot. Expression and localization of GABBR2 in CCA cells were determined using immunocytofluorescence. GABBR2 expression in tumor tissues from CCA patients with and without DM was studied using immunohistochemistry, and the correlations of GABBR2 with the clinicopathological characteristics of patients were analyzed using univariate analysis. Effects of baclofen, a GABA-B receptor agonist, on CCA cell proliferation and clonogenicity were tested using the MTT and clonogenic assays. Phospho-kinases arrays were used to screen the affected signaling pathways after baclofen treatment, and the candidate signaling molecules were validated using the public transcriptomic data and western blot. RESULTS: GABBR2 expression in CCA cells was induced by HG in a dose- and time-dependent manner. CCA tissues from patients with DM and hyperglycemia also showed a significantly higher GABBR2 expression compared with tumor tissues from those with euglycemia ( < 0.01). High GABBR2 expression was significantly associated with a poorer non-papillary histological subtype but with smaller sizes of CCA tumors ( < 0.05). HG cells of both tested CCA cell lines were more sensitive to baclofen treatment. Baclofen significantly suppressed the proliferation and clonogenicity of CCA cells in both NG and HG conditions ( < 0.05). Phospho-kinase arrays suggested glycogen synthase kinase 3 (GSK3), β-catenin, and the signal transducer and activator of transcription 3 (STAT3) as candidate signaling molecules under the regulation of GABBR2, which were verified in NG and HG cells of the individual CCA cell lines. Cyclin D1 and c-Myc, the common downstream targets of GSK3/β-catenin and STAT3 involving cell proliferation, were accordingly downregulated after baclofen treatment. CONCLUSION: GABBR2 is upregulated by HG and holds a promising role as a therapeutic target for CCA regardless of the glucose condition.
Keywords: Baclofen; beta Catenin; Bile Duct Neoplasms; Bile Ducts, Intrahepatic; Cell Line, Tumor; Cell Proliferation; Cholangiocarcinoma; Diabetes Mellitus; Glucose; Glycogen Synthase Kinase 3; Humans; Hyperglycemia

AAV8-Mediated Gene Therapy Rescues Retinal Degeneration Phenotype in a Tlcd3b Knockout Mouse Model. - Qian, Xinye; Liu, Hehe; Fu, Shangyi; Lu, Jiaxiong; Hung, Yu-Ting; Turner, Cassidy; Gu, Haiwei; Rui Chen (Invest Ophthalmol Vis Sci, 2022)
PURPOSE: The purpose of this study was to assess the therapeutic efficacy of rAAV8-hGRK1-Tlcd3b in a Tlcd3b-/- mouse model of retinal generation and validate TLCD3B's role as a ceramide synthase in vivo. METHODS: Using Tlcd3b-/- mice as an inherited retinal disease animal model, we performed subretinal injection of rAAV8-hGRK1-Tlcd3b and evaluated the efficacy of gene replacement therapy. Tlcd3b-/- mice were treated at two time points: postnatal day 21 (P21) and postnatal day 120 (P120) with various dosages. RESULTS: Tlcd3b overexpression rescued retinal degeneration in the mutant mice, as indicated by significantly improved photoreceptor function and preservation of photoreceptor cells over the course of 1 year. Although Tlcd3b is expressed in all cell types in the retina, photoreceptor cell-specific expression of Tlcd3b is sufficient to rescue the phenotype, indicating the primary function of TLCD3B is in photoreceptors. Consistent with the idea that TLCD3B is a ceramide synthase, mass spectrometry analyses of the mutant retina indicate the reduction of C16-, C18-, and C20-ceramides in the retina, which are restored with Tlcd3b overexpression. CONCLUSIONS: Our findings demonstrated the therapeutic efficacy of gene therapy in treating Tlcd3b mutant retina, laying the foundation for developing future therapy for TLCD3B retinopathy.
Keywords: Animals; Disease Models, Animal; Electroretinography; Genetic Therapy; Genetic Vectors; Mice; Mice, Inbred C57BL; Mice, Knockout; Phenotype; Retina; Retinal Degeneration

Accurate profiling of forensic autosomal STRs using the Oxford Nanopore Technologies MinION device. - Hall, Courtney L; Kesharwani, Rupesh K; Phillips, Nicole R; Planz, John V; Fritz J Sedlazeck; Zascavage, Roxanne R (Forensic Sci Int Genet, 2022)
The high variability characteristic of short tandem repeat (STR) markers is harnessed for human identification in forensic genetic analyses. Despite the power and reliability of current typing techniques, sequence-level information both within and around STRs are masked in the length-based profiles generated. Forensic STR typing using next generation sequencing (NGS) has therefore gained attention as an alternative to traditional capillary electrophoresis (CE) approaches. In this proof-of-principle study, we evaluate the forensic applicability of the newest and smallest NGS platform available - the Oxford Nanopore Technologies (ONT) MinION device. Although nanopore sequencing on the handheld MinION offers numerous advantages, including low startup cost and on-site sample processing, the relatively high error rate and lack of forensic-specific analysis software has prevented accurate profiling across STR panels in previous studies. Here we present STRspy, a streamlined method capable of producing length- and sequence-based STR allele designations from noisy, error-prone third generation sequencing reads. To assess the capabilities of STRspy, seven reference samples (female: n = 2; male: n = 5) were amplified at 15 and 30 PCR cycles using the Promega PowerSeq 46GY System and sequenced on the ONT MinION device in triplicate. Basecalled reads were then processed with STRspy using a custom database containing alleles reported in the STRSeq BioProject NIST 1036 dataset. Resultant STR allele designations and flanking region single nucleotide polymorphism (SNP) calls were compared to the manufacturer-validated genotypes for each sample. STRspy generated robust and reliable genotypes across all autosomal STR loci amplified with 30 PCR cycles, achieving 100% concordance based on both length and sequence. Furthermore, we were able to identify flanking region SNPs in the 15-cycle dataset with > 90% accuracy. These results demonstrate that when analyzed with STRspy ONT reads can reveal additional variation in and around STR loci depending on read coverage. As the first and only third generation sequencing platform-specific method to successfully profile the entire panel of autosomal STRs amplified by a commercially available multiplex, STRspy significantly increases the feasibility of nanopore sequencing in forensic applications.
Keywords: DNA Fingerprinting; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Microsatellite Repeats; Nanopores; Reproducibility of Results; Sequence Analysis, DNA

Biallelic Variants in the Ectonucleotidase ENTPD1 Cause a Complex Neurodevelopmental Disorder with Intellectual Disability, Distinct White Matter Abnormalities, and Spastic Paraplegia. - Calame, Daniel G; Herman, Isabella; Maroofian, Reza; Marshall, Aren E; Donis, Karina Carvalho; Fatih, Jawid M; Mitani, Tadahiro; Du, Haowei; Grochowski, Christopher M; Sousa, Sergio B; Gijavanekar, Charul; Bakhtiari, Somayeh; et al. (Ann Neurol, 2022)
OBJECTIVE: Human genomics established that pathogenic variation in diverse genes can underlie a single disorder. For example, hereditary spastic paraplegia is associated with >80 genes, with frequently only few affected individuals described for each gene. Herein, we characterize a large cohort of individuals with biallelic variation in ENTPD1, a gene previously linked to spastic paraplegia 64 (Mendelian Inheritance in Man # 615683). METHODS: Individuals with biallelic ENTPD1 variants were recruited worldwide. Deep phenotyping and molecular characterization were performed. RESULTS: A total of 27 individuals from 17 unrelated families were studied; additional phenotypic information was collected from published cases. Twelve novel pathogenic ENTPD1 variants are described (NM 001776.6): c.398_399delinsAA; p.(Gly133Glu), c.540del; p.(Thr181Leufs*18), c.640del; p.(Gly216Glufs*75), c.185 T > G; p.(Leu62*), c.1531 T > C; p.(*511Glnext*100), c.967C > T; p.(Gln323*), c.414-2_414-1del, and c.146 A > G; p.(Tyr49Cys) including 4 recurrent variants c.1109 T > A; p.(Leu370*), c.574-6_574-3del, c.770_771del; p.(Gly257Glufs*18), and c.1041del; p.(Ile348Phefs*19). Shared disease traits include childhood onset, progressive spastic paraplegia, intellectual disability (ID), dysarthria, and white matter abnormalities. In vitro assays demonstrate that ENTPD1 expression and function are impaired and that c.574-6_574-3del causes exon skipping. Global metabolomics demonstrate ENTPD1 deficiency leads to impaired nucleotide, lipid, and energy metabolism. INTERPRETATION: The ENTPD1 locus trait consists of childhood disease onset, ID, progressive spastic paraparesis, dysarthria, dysmorphisms, and white matter abnormalities, with some individuals showing neurocognitive regression. Investigation of an allelic series of ENTPD1 (1) expands previously described features of ENTPD1-related neurological disease, (2) highlights the importance of genotype-driven deep phenotyping, (3) documents the need for global collaborative efforts to characterize rare autosomal recessive disease traits, and (4) provides insights into disease trait neurobiology. ANN NEUROL 2022;92:304-321.
Keywords: Apyrase; Dysarthria; Humans; Intellectual Disability; Mutation; Paraplegia; Pedigree; Phenotype; Spastic Paraplegia, Hereditary; White Matter

Clinical and molecular features of pediatric cancer patients with Lynch syndrome. - Scollon, Sarah; Eldomery, Mohammad K; Reuther, Jacquelyn; Lin, Frank Y; Potter, Samara L; Desrosiers, Lauren; McClain, Kenneth L; Smith, Valeria; Su, Jack Meng-Fen; Venkatramani, Rajkumar; Jianhong Hu; Korchina, Viktoriya; et al. (Pediatr Blood Cancer, 2022)
BACKGROUND: The association of childhood cancer with Lynch syndrome is not established compared with the significant pediatric cancer risk in recessive constitutional mismatch repair deficiency syndrome (CMMRD). PROCEDURE: We describe the clinical features, germline analysis, and tumor genomic profiling of patients with Lynch syndrome among patients enrolled in pediatric cancer genomic studies. RESULTS: There were six of 773 (0.8%) pediatric patients with solid tumors identified with Lynch syndrome, defined as a germline heterozygous pathogenic variant in one of the mismatch repair (MMR) genes (three with MSH6, two with MLH1, and one with MSH2). Tumor analysis demonstrated evidence for somatic second hits and/or increased tumor mutation burden in three of four patients with available tumor with potential implications for therapy and identification of at-risk family members. Only one patient met current guidelines for pediatric cancer genetics evaluation at the time of tumor diagnosis. CONCLUSION: Approximately 1% of children with cancer have Lynch syndrome, which is missed with current referral guidelines, suggesting the importance of adding MMR genes to tumor and hereditary pediatric cancer panels. Tumor analysis may provide the first suggestion of an underlying cancer predisposition syndrome and is useful in distinguishing between Lynch syndrome and CMMRD.
Keywords: Brain Neoplasms; Child; Colorectal Neoplasms; Colorectal Neoplasms, Hereditary Nonpolyposis; DNA Mismatch Repair; DNA-Binding Proteins; Germ-Line Mutation; Humans; MutL Protein Homolog 1; MutS Homolog 2 Protein; Neoplastic Syndromes, Hereditary

Clonal hematopoiesis of indeterminate potential, DNA methylation, and risk for coronary artery disease. - Uddin, M D Mesbah; Nguyen, Ngoc Quynh H; Yu, Bing; Brody, Jennifer A; Pampana, Akhil; Nakao, Tetsushi; Fornage, Myriam; Bressler, Jan; Sotoodehnia, Nona; Weinstock, Joshua S; Honigberg, Michael C; Nachun, Daniel; et al. (Nat Commun, 2022)
Age-related changes to the genome-wide DNA methylation (DNAm) pattern observed in blood are well-documented. Clonal hematopoiesis of indeterminate potential (CHIP), characterized by the age-related acquisition and expansion of leukemogenic mutations in hematopoietic stem cells (HSCs), is associated with blood cancer and coronary artery disease (CAD). Epigenetic regulators DNMT3A and TET2 are the two most frequently mutated CHIP genes. Here, we present results from an epigenome-wide association study for CHIP in 582 Cardiovascular Health Study (CHS) participants, with replication in 2655 Atherosclerosis Risk in Communities (ARIC) Study participants. We show that DNMT3A and TET2 CHIP have distinct and directionally opposing genome-wide DNAm association patterns consistent with their regulatory roles, albeit both promoting self-renewal of HSCs. Mendelian randomization analyses indicate that a subset of DNAm alterations associated with these two leading CHIP genes may promote the risk for CAD.
Keywords: Clonal Hematopoiesis; Coronary Artery Disease; DNA Methylation; Hematopoiesis; Hematopoietic Stem Cells; Humans

Comparative molecular genomic analyses of a spontaneous rhesus macaque model of mismatch repair-deficient colorectal cancer. - Ozirmak Lermi, Nejla; Gray, Stanton B; Bowen, Charles M; Reyes-Uribe, Laura; Dray, Beth K; Deng, Nan; R. Alan Harris; Raveendran, Muthuswamy; Benavides, Fernando; Hodo, Carolyn L; Taggart, Melissa W; Colbert Maresso, Karen; et al. (PLoS Genet, 2022)
Colorectal cancer (CRC) remains the third most common cancer in the US with 15% of cases displaying Microsatellite Instability (MSI) secondary to Lynch Syndrome (LS) or somatic hypermethylation of the MLH1 promoter. A cohort of rhesus macaques from our institution developed spontaneous mismatch repair deficient (MMRd) CRC with a notable fraction harboring a pathogenic germline mutation in MLH1 (c.1029C<G, p.Tyr343Ter). Our study aimed to provide a detailed molecular characterization of rhesus CRC for cross-comparison with human MMRd CRC. We performed PCR-based MSI testing (n = 41), transcriptomics analysis (n = 35), reduced-representation bisulfite sequencing (RRBS) (n = 28), and MLH1 DNA methylation (n = 10) using next-generation sequencing (NGS) of rhesus CRC. Systems biology tools were used to perform gene set enrichment analysis (GSEA) for pathway discovery, consensus molecular subtyping (CMS), and somatic mutation profiling. Overall, the majority of rhesus tumors displayed high levels of MSI (MSI-H) and differential gene expression profiles that were consistent with known deregulated pathways in human CRC. DNA methylation analysis exposed differentially methylated patterns among MSI-H, MSI-L (MSI-low)/MSS (MS-stable) and LS tumors with MLH1 predominantly inactivated among sporadic MSI-H CRCs. The findings from this study support the use of rhesus macaques as an alternative animal model to mice to study carcinogenesis, develop immunotherapies and vaccines, and implement chemoprevention approaches relevant to sporadic MSI-H and LS CRC in humans.
Keywords: Animals; Colonic Neoplasms; Colorectal Neoplasms; Colorectal Neoplasms, Hereditary Nonpolyposis; DNA Methylation; DNA Mismatch Repair; Genomics; Humans; Macaca mulatta; Mice; Microsatellite Instability; MutL Protein Homolog 1

De novo variants in EMC1 lead to neurodevelopmental delay and cerebellar degeneration and affect glial function in Drosophila. - Chung, Hyung-Lok; Rump, Patrick; Lu, Di; Glassford, Megan R; Mok, Jung-Wan; Fatih, Jawid; Basal, Adily; Marcogliese, Paul C; Kanca, Oguz; Rapp, Michele; Fock, Johanna M; Kamsteeg, Erik-Jan; et al. (Hum Mol Genet, 2022)
BACKGROUND: The endoplasmic reticulum (ER)-membrane protein complex (EMC) is a multi-protein transmembrane complex composed of 10 subunits that functions as a membrane-protein chaperone. Variants in EMC1 lead to neurodevelopmental delay and cerebellar degeneration. Multiple families with biallelic variants have been published, yet to date, only a single report of a monoallelic variant has been described, and functional evidence is sparse. METHODS: Exome sequencing was used to investigate the genetic cause underlying severe developmental delay in three unrelated children. EMC1 variants were modeled in Drosophila, using loss-of-function (LoF) and overexpression studies. Glial-specific and neuronal-specific assays were used to determine whether the dysfunction was specific to one cell type. RESULTS: Exome sequencing identified de novo variants in EMC1 in three individuals affected by global developmental delay, hypotonia, seizures, visual impairment and cerebellar atrophy. All variants were located at Pro582 or Pro584. Drosophila studies indicated that imbalance of EMC1-either overexpression or knockdown-results in pupal lethality and suggest that the tested homologous variants are LoF alleles. In addition, glia-specific gene dosage, overexpression or knockdown, of EMC1 led to lethality, whereas neuron-specific alterations were tolerated. DISCUSSION: We establish de novo monoallelic EMC1 variants as causative of a neurological disease trait by providing functional evidence in a Drosophila model. The identified variants failed to rescue the lethality of a null allele. Variations in dosage of the wild-type EMC1, specifically in glia, lead to pupal lethality, which we hypothesize results from the altered stoichiometry of the multi-subunit protein complex EMC.
Keywords: Animals; Basic Helix-Loop-Helix Transcription Factors; Cerebellar Diseases; Drosophila; Drosophila Proteins; Intellectual Disability; Membrane Proteins; Nervous System Malformations; Neurodegenerative Diseases; Neurodevelopmental Disorders; Neuroglia; Repressor Proteins

Distinct somatic DICER1 hotspot mutations in three metachronous ovarian Sertoli-Leydig cell tumors in a patient with DICER1 syndrome. - Garcia, Annie; Desrosiers, Lauren; Scollon, Sarah; Gruner, Stephanie; Reuther, Jacquelyn; Gandhi, Ilavarasi; Patil, Ninad; Fuller, Maren Y; Dai, Hongzheng; Donna M Muzny; Richard A Gibbs; Bercaw-Pratt, Jennifer L; et al. (Cancer Genet, 2022)
Keywords: DEAD-box RNA Helicases; Female; Humans; Mutation; Ovarian Neoplasms; Ribonuclease III; Sertoli-Leydig Cell Tumor

DNA methylation signature of chronic low-grade inflammation and its role in cardio-respiratory diseases. - Wielscher, Matthias; Mandaviya, Pooja R; Kuehnel, Brigitte; Joehanes, Roby; Mustafa, Rima; Robinson, Oliver; Zhang, Yan; Bodinier, Barbara; Walton, Esther; Mishra, Pashupati P; Schlosser, Pascal; Wilson, Rory; et al. (Nat Commun, 2022)
We performed a multi-ethnic Epigenome Wide Association study on 22,774 individuals to describe the DNA methylation signature of chronic low-grade inflammation as measured by C-Reactive protein (CRP). We find 1,511 independent differentially methylated loci associated with CRP. These CpG sites show correlation structures across chromosomes, and are primarily situated in euchromatin, depleted in CpG islands. These genomic loci are predominantly situated in transcription factor binding sites and genomic enhancer regions. Mendelian randomization analysis suggests altered CpG methylation is a consequence of increased blood CRP levels. Mediation analysis reveals obesity and smoking as important underlying driving factors for changed CpG methylation. Finally, we find that an activated CpG signature significantly increases the risk for cardiometabolic diseases and COPD.
Keywords: C-Reactive Protein; CpG Islands; DNA Methylation; Humans; Inflammation; Nucleotide Motifs

An ELF4 hypomorphic variant results in NK cell deficiency. - Salinas, Sandra Andrea; Mace, Emily M; Conte, Matilde I; Park, Chun Shik; Li, Yu; Rosario-Sepulveda, Joshua I; Mahapatra, Sanjana; Moore, Emily K; Hernandez, Evelyn R; Chinn, Ivan K; Reed, Abigail E; Lee, Barclay J; et al. (JCI Insight, 2022)
NK cell deficiencies (NKD) are a type of primary immune deficiency in which the major immunologic abnormality affects NK cell number, maturity, or function. Since NK cells contribute to immune defense against virally infected cells, patients with NKD experience higher susceptibility to chronic, recurrent, and fatal viral infections. An individual with recurrent viral infections and mild hypogammaglobulinemia was identified to have an X-linked damaging variant in the transcription factor gene ELF4. The variant does not decrease expression but disrupts ELF4 protein interactions and DNA binding, reducing transcriptional activation of target genes and selectively impairing ELF4 function. Corroborating previous murine models of ELF4 deficiency (Elf4-/-) and using a knockdown human NK cell line, we determined that ELF4 is necessary for normal NK cell development, terminal maturation, and function. Through characterization of the NK cells of the proband, expression of the proband's variant in Elf4-/- mouse hematopoietic precursor cells, and a human in vitro NK cell maturation model, we established this ELF4 variant as a potentially novel cause of NKD.
Keywords: Animals; DNA-Binding Proteins; Humans; Killer Cells, Natural; Mice; Transcription Factors

EYS-Associated Sector Retinitis Pigmentosa. - Marques, João Pedro; Porto, Fernanda Belga Ottoni; Carvalho, Ana Luísa; Neves, Emmanuel; Rui Chen; Sampaio, Shirley Aparecida Madureira; Murta, Joaquim; Saraiva, Jorge; Silva, Rufino (Graefes Arch Clin Exp Ophthalmol, 2022)
PURPOSE: Sector retinitis pigmentosa (RP) is a rare form of rod-cone degeneration typically associated with mutations in the RHO gene. We describe six unrelated patients presenting with this atypical phenotype in association with biallelic mutations in EYS gene. METHODS: Multinational, multicentre cross-sectional case series. Patients with biallelic disease-causing variants in EYS and a clinical diagnosis of sector RP were recruited from specialized centres in Portugal and Brazil. All patients underwent a comprehensive ophthalmologic examination complemented by deep phenotyping. Peripheral blood samples were collected from all probands and available relatives for genetic analysis. Genetic counselling was provided to all subjects. RESULTS: Seven disease-causing variants (4 pathogenic; 3 likely pathogenic) were identified in 6 unrelated female patients. Best-corrected visual acuity ranged from 75 to 85 ETDRS letters. All eyes showed bilateral and symmetrical areas of outer retinal atrophy distributed along the inferior vascular arcades and extending temporally and/or nasally in a crescent-shaped pattern. On fundus autofluorescence (AF), a foveal-sparing curvilinear band of hyperAF encroaching the optic nerve head and extending temporally was seen in 4 patients. The remaining 2 presented bilateral and symmetrical patches of hypoAF inside crescent-shaped areas of hyperAF along the inferior temporal vascular arcade. Visual field testing revealed superior visual field defects of varying extents, always in close association with the fundus AF findings. CONCLUSIONS: Even though EYS has only recently been listed as a cause of the sector RP phenotype, we believe that this presentation is not infrequent and should be considered an important differential for sector RP.
Keywords: Cone-Rod Dystrophies; Cross-Sectional Studies; DNA Mutational Analysis; Eye Proteins; Female; Humans; Mutation; Retinitis Pigmentosa

Genetic analyses of the electrocardiographic QT interval and its components identify additional loci and pathways. - Young, William J; Lahrouchi, Najim; Isaacs, Aaron; Duong, ThuyVy; Foco, Luisa; Ahmed, Farah; Brody, Jennifer A; Salman, Reem; Noordam, Raymond; Benjamins, Jan-Walter; Haessler, Jeffrey; Lyytikäinen, Leo-Pekka; et al. (Nat Commun, 2022)
The QT interval is an electrocardiographic measure representing the sum of ventricular depolarization and repolarization, estimated by QRS duration and JT interval, respectively. QT interval abnormalities are associated with potentially fatal ventricular arrhythmia. Using genome-wide multi-ancestry analyses (>250,000 individuals) we identify 177, 156 and 121 independent loci for QT, JT and QRS, respectively, including a male-specific X-chromosome locus. Using gene-based rare-variant methods, we identify associations with Mendelian disease genes. Enrichments are observed in established pathways for QT and JT, and previously unreported genes indicated in insulin-receptor signalling and cardiac energy metabolism. In contrast for QRS, connective tissue components and processes for cell growth and extracellular matrix interactions are significantly enriched. We demonstrate polygenic risk score associations with atrial fibrillation, conduction disease and sudden cardiac death. Prioritization of druggable genes highlight potential therapeutic targets for arrhythmia. Together, these results substantially advance our understanding of the genetic architecture of ventricular depolarization and repolarization.
Keywords: Arrhythmias, Cardiac; Death, Sudden, Cardiac; Electrocardiography; Genetic Testing; Humans; Male

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation. - Longchamps, R J; Yang, S Y; Castellani, C A; Shi, W; Lane, J; Grove, M L; Bartz, T M; Sarnowski, C; Liu, C; Burrows, K; Guyatt, A L; Gaunt, T R; et al. (Hum Genet, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes (p = 3.09 × 10) and the gene ontology (GO) terms for mtDNA metabolism (p = 1.43 × 10) and mtDNA replication (p = 1.2 × 10). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall (p = 0.044) and non-cancer mortality (p = 6.56 × 10).
Keywords: Aged; Cell Proliferation; DNA Copy Number Variations; DNA, Mitochondrial; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Megakaryocytes; Middle Aged; Mitochondria; Nucleotides; Phenotype; Platelet Activation; Polymorphism, Single Nucleotide

Global molecular alterations involving recurrence or progression of pediatric brain tumors. - Chen, Fengju; Chandrashekar, Darshan S; Scheurer, Michael E; Varambally, Sooryanarayana; Creighton, Chad J (Neoplasia, 2022)
BACKGROUND: We aimed to identify molecular changes in recurrent or progressive pediatric brain tumors, as compared to the corresponding initial tumors from the same patients, using genomic, transcriptomic, and proteomic data from a unique and large cohort of 55 patients and 63 recurrent or progressive tumors from the Children's Brain Tumor Tissue Consortium, representing various histologic types. METHODS: We carried out paired analyses for each gene between recurrent/progressive and initial tumor groups, using RNA-sequencing and mass spectrometry-based proteomic data. By whole-genome sequencing (WGS) analysis, we also examined somatic DNA events for a set of cancer-associated genes. RESULTS: Of 44 patients examined by WGS, 35 involved at least one cancer-associated gene with a somatic alteration event in a recurrent or progressive tumor that was not present in the initial tumor, including genes NF1, CDKN2A, CCND2, EGFR, and MYCN. By paired analysis, 68 mRNA transcripts were differentially expressed in recurrent/progressive tumors with p<0.001, and these genes could predict patient outcomes in an independent set of pediatric brain tumors. Gene transcript-level associations with recurrence or progression were enriched for protein-level associations. There was a significant overlap in results from pediatric brain tumors and results from adult brain tumors from The Cancer Genome Atlas. Unsupervised analysis defined five subsets of recurrent or progressive tumors, with differences in gene expression and overall patient survival. CONCLUSIONS: Our study uncovers genes showing consistent expression differences in recurrent or progressive tumors. These genes may provide molecular clues as to processes or pathways underlying more aggressive pediatric brain tumors.
Keywords: Biomarkers, Tumor; Brain Neoplasms; Child; Computational Biology; Databases, Genetic; Disease Progression; Disease Susceptibility; Exome Sequencing; Gene Expression Profiling; Genetic Predisposition to Disease; Humans; Mutation; Recurrence; Transcriptome

Glutathione peroxidase 2 is a metabolic driver of the tumor immune microenvironment and immune checkpoint inhibitor response. - Ahmed, Kazi Mokim; Veeramachaneni, Ratna; Deng, Defeng; Putluri, Nagireddy; Putluri, Vasanta; Cardenas, Maria F; David A Wheeler; Decker, William K; Frederick, Andy I; Kazi, Sawad; Sikora, Andrew G; Sandulache, Vlad C; et al. (J Immunother Cancer, 2022)
BACKGROUND: The existence of immunologically 'cold tumors' frequently found across a wide spectrum of tumor types represents a significant challenge for cancer immunotherapy. Cold tumors have poor baseline pan-leukocyte infiltration, including a low prevalence of cytotoxic lymphocytes, and not surprisingly respond unfavorably to immune checkpoint (IC) inhibitors. We hypothesized that cold tumors harbor a mechanism of immune escape upstream and independent of ICs that may be driven by tumor biology rather than differences in mutational neoantigen burden. METHODS: Using a bioinformatic approach to analyze TCGA (The Cancer Genome Atlas) RNA sequencing data we identified genes upregulated in cold versus hot tumors across four different smoking-related cancers, including squamous carcinomas from the oral cavity (OCSCC) and lung (LUSC), and adenocarcinomas of the bladder (BLCA) and lung (LUAD). Biological significance of the gene most robustly associated with a cold tumor phenotype across all four tumor types, glutathione peroxidase 2 (GPX2), was further evaluated using a combination of in silico analyses and functional genomic experiments performed both in vitro and in in vivo with preclinical models of oral cancer. RESULTS: Elevated RNA expression of five metabolic enzymes including GPX2, aldo-keto reductase family 1 members AKR1C1, AKR1C3, and cytochrome monoxygenases (CP4F11 and CYP4F3) co-occurred in cold tumors across all four smoking-related cancers. These genes have all been linked to negative regulation of arachidonic acid metabolism-a well-established inflammatory pathway-and are also known downstream targets of the redox sensitive Nrf2 transcription factor pathway. In OCSCC, LUSC, and LUAD, GPX2 expression was highly correlated with Nrf2 activation signatures, also elevated in cold tumors. In BLCA, however, GPX2 correlated more strongly than Nrf2 signatures with decreased infiltration of multiple leukocyte subtypes. GPX2 inversely correlated with expression of multiple pro- inflammatory cytokines/chemokines and NF-kB activation in cell lines and knockdown of GPX2 led to increased secretion of prostaglandin E2 (PGE2) and interleukin-6. Conversely, GPX2 overexpression led to reduced PGE2 production in a murine OCSCC model (MOC1). GPX2 overexpressing MOC1 tumors had a more suppressive tumor immune microenvironment and responded less favorably to anti-cytotoxic T-lymphocytes-associated protein 4 IC therapy in mice. CONCLUSION: GPX2 overexpression represents a novel potentially targetable effector of immune escape in cold tumors.
Keywords: Animals; Dinoprostone; Glutathione Peroxidase; Immune Checkpoint Inhibitors; Mice; NF-E2-Related Factor 2; Tumor Microenvironment

Identification of autosomal recessive novel genes and retinal phenotypes in members of the solute carrier (SLC) superfamily. - Millo, Talya; Rivera, Antonio; Obolensky, Alexey; Marks-Ohana, Devora; Xu, Mingchu; Yumei Li; Wilhelm, Enosh; Gopalakrishnan, Prakadeeswari; Gross, Menachem; Rosin, Boris; Hanany, Mor; Webster, Andrew; et al. (Genet Med, 2022)
PURPOSE: This study aimed to investigate the clinical and genetic aspects of solute carrier (SLC) genes in inherited retinal diseases (IRDs). METHODS: Exome sequencing data were filtered to identify pathogenic variants in SLC genes. Analysis of transcript and protein expression was performed on fibroblast cell lines and retinal sections. RESULTS: Comprehensive analysis of 433 SLC genes in 913 exome sequencing IRD samples revealed homozygous pathogenic variants in 6 SLC genes, including 2 candidate novel genes, which were 2 variants in SLC66A1, causing autosomal recessive retinitis pigmentosa (ARRP), and a variant in SLC39A12, causing autosomal recessive mild widespread retinal degeneration with marked macular involvement. In addition, we present 4 families with ARRP and homozygous null variants in SLC37A3 that were previously suggested to cause retinitis pigmentosa, 2 of which cause exon skipping. The recently reported SLC4A7- c.2007dup variant was found in 2 patients with ARRP resulting in the absence of protein. Finally, variants in SLC24A1 were found in 4 individuals with either ARRP or congenital stationary night blindness. CONCLUSION: We report on SLC66A1 and SLC39A12 as candidate novel IRD genes, establish SLC37A3 pathogenicity, and provide further evidence of SLC4A7 as IRD genes. We extend the phenotypic spectrum of SLC24A1 and suggest that its ARRP phenotype may be more common than previously reported.
Keywords: DNA Mutational Analysis; Genes, Recessive; Genetic Association Studies; Humans; Mutation; Pedigree; Phenotype; Retinitis Pigmentosa

Isolation and Barcoding of Trace Pollen-free DNA for Authentication of Honey. - Chavan, Dimple; Adolacion, Jay R T; Crum, Mary; Nandy, Suman; Lee, Kyung Hyun; Vu, Binh; Kourentzi, Katerina; Aniko Sabo; Willson, Richard C (J Agric Food Chem, 2022)
Adulteration and mislabeling of honey to mask its true origin have become a global concern. Pollen microscopy, the current gold standard for identifying honey's geographical and plant origins, is laborious, requires extensive training, and fails to identify filtered honey and honey spiked with pollen from a more favorable plant to disguise its origins. We successfully isolated pollen-free DNA from filtered honey using three types of adsorbents: (i) anti-dsDNA antibodies coupled to magnetic microspheres; (ii) anion-exchange adsorbent; and (iii) ceramic hydroxyapatite. The internal transcribed spacer 2 region of the captured pollen-free DNA was polymerase chain reaction-amplified and subjected to next-generation sequencing. Using an in-house bioinformatics pipeline, initial experiments showed that anion exchange had the greatest capacity to capture trace pollen-free DNA, and it was successfully applied to isolate DNA from five honey samples. Enrichment of trace pollen-free DNA from filtered honey samples opens a new approach for identifying the true origins of honey.
Keywords: DNA; DNA Barcoding, Taxonomic; Honey; Pollen

Long read sequencing and expression studies of AHDC1 deletions in Xia-Gibbs syndrome reveal a novel genetic regulatory mechanism. - Chander, Varuna; Mahmoud, Medhat; Jianhong Hu; Dardas, Zain; Grochowski, Christopher M; Dawood, Moez; Khayat, Michael M; Li, He; Li, Shoudong; Jhangiani, Shalini; Korchina, Viktoriya; Shen, Hua; et al. (Hum Mutat, 2022)
Xia-Gibbs syndrome (XGS; MIM# 615829) is a rare mendelian disorder characterized by Development Delay (DD), intellectual disability (ID), and hypotonia. Individuals with XGS typically harbor de novo protein-truncating mutations in the AT-Hook DNA binding motif containing 1 (AHDC1) gene, although some missense mutations can also cause XGS. Large de novo heterozygous deletions that encompass the AHDC1 gene have also been ascribed as diagnostic for the disorder, without substantial evidence to support their pathogenicity. We analyzed 19 individuals with large contiguous deletions involving AHDC1, along with other genes. One individual bore the smallest known contiguous AHDC1 deletion (∼350 Kb), encompassing eight other genes within chr1p36.11 (Feline Gardner-Rasheed, IFI6, FAM76A, STX12, PPP1R8, THEMIS2, RPA2, SMPDL3B) and terminating within the first intron of AHDC1. The breakpoint junctions and phase of the deletion were identified using both short and long read sequencing (Oxford Nanopore). Quantification of RNA expression patterns in whole blood revealed that AHDC1 exhibited a mono-allelic expression pattern with no deficiency in overall AHDC1 expression levels, in contrast to the other deleted genes, which exhibited a 50% reduction in mRNA expression. These results suggest that AHDC1 expression in this individual is compensated by a novel regulatory mechanism and advances understanding of mutational and regulatory mechanisms in neurodevelopmental disorders.
Keywords: Abnormalities, Multiple; DNA-Binding Proteins; Endoribonucleases; Humans; Intellectual Disability; Musculoskeletal Abnormalities; Neurodevelopmental Disorders; Phosphoprotein Phosphatases; Qa-SNARE Proteins; RNA-Binding Proteins; Sphingomyelin Phosphodiesterase

The multiple de novo copy number variant (MdnCNV) phenomenon presents with peri-zygotic DNA mutational signatures and multilocus pathogenic variation. - Du, Haowei; Jolly, Angad; Grochowski, Christopher M; Bo Yuan; Dawood, Moez; Jhangiani, Shalini N; Li, He; Donna M Muzny; Fatih, Jawid M; Coban-Akdemir, Zeynep; Carlin, Mary Esther; Scheuerle, Angela E; et al. (Genome Med, 2022)
BACKGROUND: The multiple de novo copy number variant (MdnCNV) phenotype is described by having four or more constitutional de novo CNVs (dnCNVs) arising independently throughout the human genome within one generation. It is a rare peri-zygotic mutational event, previously reported to be seen once in every 12,000 individuals referred for genome-wide chromosomal microarray analysis due to congenital abnormalities. These rare families provide a unique opportunity to understand the genetic factors of peri-zygotic genome instability and the impact of dnCNV on human diseases. METHODS: Chromosomal microarray analysis (CMA), array-based comparative genomic hybridization, short- and long-read genome sequencing (GS) were performed on the newly identified MdnCNV family to identify de novo mutations including dnCNVs, de novo single-nucleotide variants (dnSNVs), and indels. Short-read GS was performed on four previously published MdnCNV families for dnSNV analysis. Trio-based rare variant analysis was performed on the newly identified individual and four previously published MdnCNV families to identify potential genetic etiologies contributing to the peri-zygotic genomic instability. Lin semantic similarity scores informed quantitative human phenotype ontology analysis on three MdnCNV families to identify gene(s) driving or contributing to the clinical phenotype. RESULTS: In the newly identified MdnCNV case, we revealed eight de novo tandem duplications, each ~ 1 Mb, with microhomology at 6/8 breakpoint junctions. Enrichment of de novo single-nucleotide variants (SNV; 6/79) and de novo indels (1/12) was found within 4 Mb of the dnCNV genomic regions. An elevated post-zygotic SNV mutation rate was observed in MdnCNV families. Maternal rare variant analyses identified three genes in distinct families that may contribute to the MdnCNV phenomenon. Phenotype analysis suggests that gene(s) within dnCNV regions contribute to the observed proband phenotype in 3/3 cases. CNVs in two cases, a contiguous gene duplication encompassing PMP22 and RAI1 and another duplication affecting NSD1 and SMARCC2, contribute to the clinically observed phenotypic manifestations. CONCLUSIONS: Characteristic features of dnCNVs reported here are consistent with a microhomology-mediated break-induced replication (MMBIR)-driven mechanism during the peri-zygotic period. Maternal genetic variants in DNA repair genes potentially contribute to peri-zygotic genomic instability. Variable phenotypic features were observed across a cohort of three MdnCNV probands, and computational quantitative phenotyping revealed that two out of three had evidence for the contribution of more than one genetic locus to the proband's phenotype supporting the hypothesis of de novo multilocus pathogenic variation (MPV) in those families.
Keywords: Comparative Genomic Hybridization; DNA; DNA Copy Number Variations; DNA-Binding Proteins; Genomic Instability; Humans; Mutation; Nucleotides; Transcription Factors

A novel stop codon mutation of TSPAN12 gene in Chinese patients with familial exudative vitreoretinopathy. - Zou, Gang; Qi, Rui; Ma, Meijiao; Fu, Shangyi; Liang, Qingnan; Bi, Xiaojun; Wang, Chanjuan; Hu, Xuejun; Cai, Yujuan; Sheng, Xunlun (Ophthalmic Genet, 2022)
BACKGROUND: Familial exudative vitreoretinopathy (FEVR) is a group of inherited eye diseases characterized by premature arrest of retinal vessel development. The purpose of our study was to characterize the genetic causes and clinical features in eight Chinese families with FEVR using next-generation sequencing (NGS) technology. MATERIALS AND METHODS: Eight families with FEVR were included in genetic and clinical analyses. We screened the proband and the parents in eight pedigrees with FEVR using targeted NGS approach and in silico analysis to determine the causative mutation for their family's phenotype. RESULTS: Four cases (4/8, 50.0%) were confirmed to harbor mutations in known genes, including 3 novel mutations and one previously reported mutation. Among the detected mutations, accounted for 75% (3/4). We identified a novel stop codon of , a heterozygous missense mutation NM_012338.4:c.633T>A, NP_036470.1:p.Tyr211Ter involved in highly conserved residues in the proband. Retrospective analysis of its clinical manifestation showed that the mutant carrier presented mild clinical features. CONCLUSIONS: We found the novel stop codon mutation p.Tyr211Ter in the , which creates a milder phenotype. Discovery of this novel mutation expands the mutation spectrum of , and would be valuable for future genetic disease diagnosis.
Keywords: China; Codon, Terminator; DNA Mutational Analysis; Eye Diseases, Hereditary; Familial Exudative Vitreoretinopathies; Humans; Mutation; Pedigree; Phenotype; Retinal Diseases; Retrospective Studies; Tetraspanins

Phenotypic and mutational spectrum of ROR2-related Robinow syndrome. - Lima, Ariadne R; Ferreira, Barbara M; Zhang, Chaofan; Jolly, Angad; Du, Haowei; White, Janson J; Dawood, Moez; Lins, Tulio C; Chiabai, Marcela A; van Beusekom, Ellen; Cordoba, Mara S; Caldas Rosa, Erica C C; et al. (Hum Mutat, 2022)
Robinow syndrome is characterized by a triad of craniofacial dysmorphisms, disproportionate-limb short stature, and genital hypoplasia. A significant degree of phenotypic variability seems to correlate with different genes/loci. Disturbances of the noncanonical WNT-pathway have been identified as the main cause of the syndrome. Biallelic variants in ROR2 cause an autosomal recessive form of the syndrome with distinctive skeletal findings. Twenty-two patients with a clinical diagnosis of autosomal recessive Robinow syndrome were screened for variants in ROR2 using multiple molecular approaches. We identified 25 putatively pathogenic ROR2 variants, 16 novel, including single nucleotide variants and exonic deletions. Detailed phenotypic analyses revealed that all subjects presented with a prominent forehead, hypertelorism, short nose, abnormality of the nasal tip, brachydactyly, mesomelic limb shortening, short stature, and genital hypoplasia in male patients. A total of 19 clinical features were present in more than 75% of the subjects, thus pointing to an overall uniformity of the phenotype. Disease-causing variants in ROR2, contribute to a clinically recognizable autosomal recessive trait phenotype with multiple skeletal defects. A comprehensive quantitative clinical evaluation of this cohort delineated the phenotypic spectrum of ROR2-related Robinow syndrome. The identification of exonic deletion variant alleles further supports the contention of a loss-of-function mechanism in the etiology of the syndrome.
Keywords: Craniofacial Abnormalities; Dwarfism; Genes, Recessive; Humans; Limb Deformities, Congenital; Male; Phenotype; Receptor Tyrosine Kinase-like Orphan Receptors; Urogenital Abnormalities

Proteogenomic characterization of 2002 human cancers reveals pan-cancer molecular subtypes and associated pathways. - Zhang, Yiqun; Chen, Fengju; Chandrashekar, Darshan S; Varambally, Sooryanarayana; Creighton, Chad J (Nat Commun, 2022)
Mass-spectrometry-based proteomic data on human tumors-combined with corresponding multi-omics data-present opportunities for systematic and pan-cancer proteogenomic analyses. Here, we assemble a compendium dataset of proteomics data of 2002 primary tumors from 14 cancer types and 17 studies. Protein expression of genes broadly correlates with corresponding mRNA levels or copy number alterations (CNAs) across tumors, but with notable exceptions. Based on unsupervised clustering, tumors separate into 11 distinct proteome-based subtypes spanning multiple tissue-based cancer types. Two subtypes are enriched for brain tumors, one subtype associating with MYC, Wnt, and Hippo pathways and high CNA burden, and another subtype associating with metabolic pathways and low CNA burden. Somatic alteration of genes in a pathway associates with higher pathway activity as inferred by proteome or transcriptome data. A substantial fraction of cancers shows high MYC pathway activity without MYC copy gain but with mutations in genes with noncanonical roles in MYC. Our proteogenomics survey reveals the interplay between genome and proteome across tumor lineages.
Keywords: DNA Copy Number Variations; Humans; Neoplasms; Proteogenomics; Proteome; Proteomics

Rare coding variants in 35 genes associate with circulating lipid levels-A multi-ancestry analysis of 170,000 exomes. - Hindy, George; Dornbos, Peter; Chaffin, Mark D; Liu, Dajiang J; Wang, Minxian; Selvaraj, Margaret Sunitha; Zhang, David; Park, Joseph; Aguilar-Salinas, Carlos A; Antonacci-Fulton, Lucinda; Ardissino, Diego; Arnett, Donna K; et al. (Am J Hum Genet, 2022)
Large-scale gene sequencing studies for complex traits have the potential to identify causal genes with therapeutic implications. We performed gene-based association testing of blood lipid levels with rare (minor allele frequency < 1%) predicted damaging coding variation by using sequence data from >170,000 individuals from multiple ancestries: 97,493 European, 30,025 South Asian, 16,507 African, 16,440 Hispanic/Latino, 10,420 East Asian, and 1,182 Samoan. We identified 35 genes associated with circulating lipid levels; some of these genes have not been previously associated with lipid levels when using rare coding variation from population-based samples. We prioritize 32 genes in array-based genome-wide association study (GWAS) loci based on aggregations of rare coding variants; three (EVI5, SH2B3, and PLIN1) had no prior association of rare coding variants with lipid levels. Most of our associated genes showed evidence of association among multiple ancestries. Finally, we observed an enrichment of gene-based associations for low-density lipoprotein cholesterol drug target genes and for genes closest to GWAS index single-nucleotide polymorphisms (SNPs). Our results demonstrate that gene-based associations can be beneficial for drug target development and provide evidence that the gene closest to the array-based GWAS index SNP is often the functional gene for blood lipid levels.
Keywords: Alleles; Blood Glucose; Case-Control Studies; Computational Biology; Databases, Genetic; Diabetes Mellitus, Type 2; Exome; Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Lipids; Liver; Molecular Sequence Annotation; Multifactorial Inheritance; Open Reading Frames; Phenotype; Polymorphism, Single Nucleotide

A recurrent single-exon deletion in TBCK might be under-recognized in patients with infantile hypotonia and psychomotor delay. - Dai, Hongzheng; Zhu, Wenmiao; Bo Yuan; Walley, Nicole; Schoch, Kelly; Jiang, Yong-Hui; Phillips, John A; Jones, Melissa S; Liu, Pengfei; David R Murdock; Burrage, Lindsay C; Lee, Brendan; et al. (Hum Mutat, 2022)
Advanced bioinformatics algorithms allow detection of multiple-exon copy-number variations (CNVs) from exome sequencing (ES) data, while detection of single-exon CNVs remains challenging. A retrospective review of Baylor Genetics' clinical ES patient cohort identified four individuals with homozygous single-exon deletions of TBCK (exon 23, NM_001163435.2), a gene associated with an autosomal recessive neurodevelopmental phenotype. To evaluate the prevalence of this deletion and its contribution to disease, we retrospectively analyzed single nucleotide polymorphism (SNP) array data for 8194 individuals undergoing ES, followed by PCR confirmation and RT-PCR on individuals carrying homozygous or heterozygous exon 23 TBCK deletions. A fifth individual was diagnosed with the TBCK-related disorder due to a heterozygous exon 23 deletion in trans with a c.1860+1G>A (NM_001163435.2) pathogenic variant, and three additional heterozygous carriers were identified. Affected individuals and carriers were from diverse ethnicities including European Caucasian, South Asian, Middle Eastern, Hispanic American and African American, with only one family reporting consanguinity. RT-PCR revealed two out-of-frame transcripts related to the exon 23 deletion. Our results highlight the importance of identifying single-exon deletions in clinical ES, especially for genes carrying recurrent deletions. For patients with early-onset hypotonia and psychomotor delay, this single-exon TBCK deletion might be under-recognized due to technical limitations of ES.
Keywords: DNA Copy Number Variations; Exome; Exome Sequencing; Exons; Humans; Infant; Muscle Hypotonia; Muscular Diseases; Protein Serine-Threonine Kinases; Retrospective Studies

Retrospective analysis of a clinical exome sequencing cohort reveals the mutational spectrum and identifies candidate disease-associated loci for BAFopathies. - Chen, Chun-An; Lattier, John; Zhu, Wenmiao; Rosenfeld, Jill; Wang, Lei; Scott, Tiana M; Du, Haowei; Patel, Vipulkumar; Dang, Anh; Magoulas, Pilar; Streff, Haley; Sebastian, Jessica; et al. (Genet Med, 2022)
PURPOSE: BRG1/BRM-associated factor (BAF) complex is a chromatin remodeling complex that plays a critical role in gene regulation. Defects in the genes encoding BAF subunits lead to BAFopathies, a group of neurodevelopmental disorders with extensive locus and phenotypic heterogeneity. METHODS: We retrospectively analyzed data from 16,243 patients referred for clinical exome sequencing (ES) with a focus on the BAF complex. We applied a genotype-first approach, combining predicted genic constraints to propose candidate BAFopathy genes. RESULTS: We identified 127 patients carrying pathogenic variants, likely pathogenic variants, or de novo variants of unknown clinical significance in 11 known BAFopathy genes. Those include 34 patients molecularly diagnosed using ES reanalysis with new gene-disease evidence (n = 21) or variant reclassifications in known BAFopathy genes (n = 13). We also identified de novo or predicted loss-of-function variants in 4 candidate BAFopathy genes, including ACTL6A, BICRA (implicated in Coffin-Siris syndrome during this study), PBRM1, and SMARCC1. CONCLUSION: We report the mutational spectrum of BAFopathies in an ES cohort. A genotype-driven and pathway-based reanalysis of ES data identified new evidence for candidate genes involved in BAFopathies. Further mechanistic and phenotypic characterization of additional patients are warranted to confirm their roles in human disease and to delineate their associated phenotypic spectrums.
Keywords: Abnormalities, Multiple; Actins; Chromosomal Proteins, Non-Histone; DNA-Binding Proteins; Exome; Hand Deformities, Congenital; Humans; Micrognathism; Retrospective Studies

Single cell RNA sequencing of the adult Drosophila eye reveals distinct clusters and novel marker genes for all major cell types. - Yeung, Kelvin; Bollepogu Raja, Komal Kumar; Shim, Yoon-Kyung; Yumei Li; Rui Chen; Mardon, Graeme (Commun Biol, 2022)
The adult Drosophila eye is a powerful model system for phototransduction and neurodegeneration research. However, single cell resolution transcriptomic data are lacking for this tissue. We present single cell RNA-seq data on 1-day male and female, 3-day and 7-day old male adult eyes, covering early to mature adult eyes. All major cell types, including photoreceptors, cone and pigment cells in the adult eye were captured and identified. Our data sets identified novel cell type specific marker genes, some of which were validated in vivo. R7 and R8 photoreceptors form clusters that reflect their specific Rhodopsin expression and the specific Rhodopsin expression by each R7 and R8 cluster is the major determinant to their clustering. The transcriptomic data presented in this report will facilitate a deeper mechanistic understanding of the adult fly eye as a model system.
Keywords: Animals; Drosophila; Drosophila Proteins; Female; Male; Photoreceptor Cells, Invertebrate; Rhodopsin; Sequence Analysis, RNA

Spata7 is required for maintenance of the retinal connecting cilium. - Lu, Jiaxiong; Xiong, Kaitlyn; Qian, Xinye; Choi, Jongsu; Shim, Yoon-Kyung; Burnett, Jacob; Mardon, Graeme; Rui Chen (Sci Rep, 2022)
SPATA7, an early onset LCA3 retinal disease gene, encodes a putative scaffold protein that is essential for the proper assembly of the connecting cilium (CC) complex in photoreceptors. Previous studies have shown that SPATA7 interacts with other photoreceptor-specific ciliary proteins, such as RPGR and RPGRIP1, and maintains the integrity of CC integrity. However, although it is known that Spata7 is required for early formation of the CC, it is unclear if Spata7 is also required for the maintenance of the CC. To investigate Spata7 function in the retina at the adult stage, loss of function was induced in the adult retina upon tamoxifen induction of an inducible Spata7 knockout allele (Spata7; UbcCreERT2/). The phenotype of mutant retina was characterized by a combination of histology, immunobiochemistry, and electroretinography (ERG). Our results demonstrated that Spata7 is also essential for maintaining the integrity of the mature retinal CC. Loss of Spata7 in adults caused phenotypes similar to those seen in germline mutant mice, including photoreceptor cell degeneration and defective ERG responses. Close examination of the CC revealed significantly shortened NPHP1 length as a result of Spata7 deletion. Furthermore, mislocalization of rhodopsin, leading to ER stress-mediated apoptosis, was observed in the retinal layers. Our results indicate that Spata7 is required not only for the establishment but also for the maintenance of the CC of photoreceptors.
Keywords: Animals; Cilia; DNA-Binding Proteins; Electroretinography; Mice; Retina; Retinal Degeneration; Rhodopsin

Type 2 Diabetes Partitioned Polygenic Scores Associate With Disease Outcomes in 454,193 Individuals Across 13 Cohorts. - DiCorpo, Daniel; LeClair, Jessica; Cole, Joanne B; Sarnowski, Chloe; Ahmadizar, Fariba; Bielak, Lawrence F; Blokstra, Anneke; Bottinger, Erwin P; Chaker, Layal; Chen, Yii-Der I; Chen, Ye; de Vries, Paul S; et al. (Diabetes Care, 2022)
OBJECTIVE: Type 2 diabetes (T2D) has heterogeneous patient clinical characteristics and outcomes. In previous work, we investigated the genetic basis of this heterogeneity by clustering 94 T2D genetic loci using their associations with 47 diabetes-related traits and identified five clusters, termed β-cell, proinsulin, obesity, lipodystrophy, and liver/lipid. The relationship between these clusters and individual-level metabolic disease outcomes has not been assessed. RESEARCH DESIGN AND METHODS: Here we constructed individual-level partitioned polygenic scores (pPS) for these five clusters in 12 studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (n = 454,193) and tested for cross-sectional association with T2D-related outcomes, including blood pressure, renal function, insulin use, age at T2D diagnosis, and coronary artery disease (CAD). RESULTS: Despite all clusters containing T2D risk-increasing alleles, they had differential associations with metabolic outcomes. Increased obesity and lipodystrophy cluster pPS, which had opposite directions of association with measures of adiposity, were both significantly associated with increased blood pressure and hypertension. The lipodystrophy and liver/lipid cluster pPS were each associated with CAD, with increasing and decreasing effects, respectively. An increased liver/lipid cluster pPS was also significantly associated with reduced renal function. The liver/lipid cluster includes known loci linked to liver lipid metabolism (e.g., GCKR, PNPLA3, and TM6SF2), and these findings suggest that cardiovascular disease risk and renal function may be impacted by these loci through their shared disease pathway. CONCLUSIONS: Our findings support that genetically driven pathways leading to T2D also predispose differentially to clinical outcomes.
Keywords: Alleles; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Genetic Loci; Humans; Obesity; Pharmaceutical Preparations

Use of medical exome sequencing for identification of underlying genetic defects in NICU: Experience in a cohort of 2303 neonates in China. - Yang, Lin; Wei, Zejun; Chen, Xiang; Hu, Liyuan; Peng, Xiaomin; Wang, Jin; Lu, Chunmei; Kong, Yanting; Dong, Xinran; Ni, Qi; Lu, Yulan; Wu, Bingbing; et al. (Clin Genet, 2022)
Emerging evidence demonstrates the clinical utility of genomic applications in newborn intensive care unit (NICU) patients with strong indications of Mendelian etiology. However, such applications' diagnostic yield and utility remain unclear for NICU cohorts with minimal phenotype selection. In this study, focused medical exome sequencing was used as a first-tier, singleton-focused diagnostic tool for 2303 unrelated sick neonates. Integrated analysis of single nucleotide variants (SNVs), small insertions and deletions (Indels), and large copy number variants (CNVs) was performed. The diagnostic rate in this NICU cohort is 12.3% (284/2303), with 190 probands with molecular diagnoses made from SNV/Indel analyses (66.9%), 93 patients with diagnostic aneuploidy/CNVs findings (32.8%), and 1 patient with both SNV and CNV (0.4%). In addition, 54 (2.3%) of patients had a reportable incidental finding. Multiple organ involvements, craniofacial abnormalities, and dermatologic abnormalities were the strongest positive predictors for a molecular diagnosis. Among the 190 cases with SNV/Indel defects, direct impacts on medical management were observed in 46.8% of patients after the results were reported. In this study, we demonstrate that focused medical exome sequencing is a powerful first-line diagnostic tool for NICU patients. Significant number of diagnosed NICU patients can benefit from more focused medical management and long-term care.
Keywords: Alleles; China; Chromosome Mapping; DNA Copy Number Variations; Exome Sequencing; Female; Genetic Association Studies; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Humans; INDEL Mutation; Intensive Care Units, Neonatal; Male; Polymorphism, Single Nucleotide; Whole Genome Sequencing

A Validation Framework for Somatic Copy Number Detection in Targeted Sequencing Panels. - Chandramohan, Raghu; Reuther, Jacquelyn; Gandhi, Ilavarasi; Voicu, Horatiu; Alvarez, Karla R; Plon, Sharon E; López-Terrada, Dolores H; Fisher, Kevin E; Parsons, D Williams; Roy, Angshumoy (J Mol Diagn, 2022)
Somatic copy number alterations (SCNAs) in tumors are clinically significant diagnostic, prognostic, and predictive biomarkers. SCNA detection from targeted next-generation sequencing panels is increasingly common in clinical practice; however, detailed descriptions of optimization and validation of SCNA pipelines for small targeted panels are limited. This study describes the validation and implementation of a tumor-only SCNA pipeline using CNVkit, augmented with custom modules and optimized for clinical implementation by testing reference materials and clinical tumor samples with different classes of copy number variation (CNV; amplification, single copy loss, and biallelic loss). Using wet-bench and in silico methods, various parameters impacting CNV calling, including assay-intrinsic variables (establishment of normal reference and sequencing coverage), sample-intrinsic variables (tumor purity and sample quality), and CNV algorithm-intrinsic variables (bin size), were optimized. The pipeline was trained and tested on an optimization cohort and validated using an independent cohort with a sensitivity and specificity of 100% and 93%, respectively. Using custom modules, intragenic CNVs with breakpoints within tumor suppressor genes were uncovered. Using the validated pipeline, re-analysis of 28 pediatric solid tumors that had been previously profiled for mutations identified SCNAs in 86% (24/28) samples, with 46% (13/28) samples harboring findings of potential clinical relevance. Our report highlights the importance of rigorous establishment of performance characteristics of SCNA pipelines and presents a detailed validation framework for optimal SCNA detection in targeted sequencing panels.
Keywords: Algorithms; Child; DNA Copy Number Variations; High-Throughput Nucleotide Sequencing; Humans; Neoplasms; Sequence Analysis, DNA

Variant-level matching for diagnosis and discovery: Challenges and opportunities. - Rodrigues, Eliete da S; Griffith, Sean; Martin, Renan; Antonescu, Corina; Posey, Jennifer E; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Doheny, Kimberly F; James R Lupski; Valle, David; Bamshad, Michael J; Hamosh, Ada; et al. (Hum Mutat, 2022)
Here we describe MyGene2, Geno2MP, VariantMatcher, and Franklin; databases that provide variant-level information and phenotypic features to researchers, clinicians, healthcare providers and patients. Following the footsteps of the Matchmaker Exchange project that connects exome, genome, and phenotype databases at the gene level, these databases have as one goal to facilitate connection to one another using Data Connect, a standard for discovery and search of biomedical data from the Global Alliance for Genomics and Health (GA4GH).
Keywords: Databases, Genetic; Exome; Genomics; Humans; Information Dissemination; Phenotype

Absent B cells, agammaglobulinemia, and hypertrophic cardiomyopathy in folliculin-interacting protein 1 deficiency. - Saettini, Francesco; Poli, Cecilia; Vengoechea, Jaime; Bonanomi, Sonia; Orellana, Julio C; Fazio, Grazia; Rodriguez, Fred H; Noguera, Loreani P; Booth, Claire; Jarur-Chamy, Valentina; Shams, Marissa; Iascone, Maria; et al. (Blood, 2021)
Agammaglobulinemia is the most profound primary antibody deficiency that can occur due to an early termination of B-cell development. We here investigated 3 novel patients, including the first known adult, from unrelated families with agammaglobulinemia, recurrent infections, and hypertrophic cardiomyopathy (HCM). Two of them also presented with intermittent or severe chronic neutropenia. We identified homozygous or compound-heterozygous variants in the gene for folliculin interacting protein 1 (FNIP1), leading to loss of the FNIP1 protein. B-cell metabolism, including mitochondrial numbers and activity and phosphatidylinositol 3-kinase/AKT pathway, was impaired. These defects recapitulated the Fnip1-/- animal model. Moreover, we identified either uniparental disomy or copy-number variants (CNVs) in 2 patients, expanding the variant spectrum of this novel inborn error of immunity. The results indicate that FNIP1 deficiency can be caused by complex genetic mechanisms and support the clinical utility of exome sequencing and CNV analysis in patients with broad phenotypes, including agammaglobulinemia and HCM. FNIP1 deficiency is a novel inborn error of immunity characterized by early and severe B-cell development defect, agammaglobulinemia, variable neutropenia, and HCM. Our findings elucidate a functional and relevant role of FNIP1 in B-cell development and metabolism and potentially neutrophil activity.
Keywords: Adult; Agammaglobulinemia; Animals; B-Lymphocytes; Cardiomyopathy, Hypertrophic; Carrier Proteins; Child; Child, Preschool; Chromosomes, Human, Pair 5; Codon, Nonsense; Consanguinity; Crohn Disease; Developmental Disabilities; Disease Models, Animal; Disease Susceptibility; DNA Copy Number Variations; Female; Heart Defects, Congenital; Humans; Immunologic Deficiency Syndromes; Infections; Loss of Function Mutation; Lymphopenia; Male; Mice; Neutropenia; Pedigree; Uniparental Disomy; Whole Exome Sequencing

Age-related changes in the rhesus macaque eye. - Lin, Kira H; Tran, Tu; Kim, Soohyun; Park, Sangwan; Chen, Jiajia; Stout, J Timothy; Rui Chen; Jeffrey Rogers; Yiu, Glenn; Thomasy, Sara; Moshiri, Ala (Exp Eye Res, 2021)
PURPOSE: To assess age-related changes in the rhesus macaque eye and evaluate them to corresponding human age-related eye disease. METHODS: Data from eye exams and imaging tests including intraocular pressure (IOP), lens thickness, axial length, and retinal optical coherence tomography (OCT) images were evaluated from 142 individuals and statistically analyzed for age-related changes. Quantitative autofluorescence (qAF) was measured as was the presence of macular lesions as related to age. RESULTS: Ages of the 142 rhesus macaques ranged from 0.7 to 29 years (mean = 16.4 years, stdev = 7.5 years). Anterior segment measurements such as IOP, lens thickness, and axial length were acquired. Advanced retinal imaging in the form of optical coherence tomography and qAF were obtained. Quantitative assessments were made and variations by age groups were analyzed to compare with established age-related changes in human eyes. Quantitative analysis of data revealed age-related increase in intraocular pressure (0.165 mm Hg per increase in year of age), ocular biometry (lens thickness 7.2 μm per increase in year of age; and axial length 52.8 μm per increase in year of age), and presence of macular lesions. Age-related changes in thicknesses of retinal layers on OCT were observed and quantified, showing decreased thickness of the retinal ganglion cell layer and inner nuclear layer, and increased thickness of photoreceptor outer segment and choroidal layers. Age was correlated with increased qAF by 1.021 autofluorescence units per increase in year of age. CONCLUSIONS: The rhesus macaque has age-related ocular changes similar to humans. IOP increases with age while retinal ganglion cell layer thickness decreases. Macular lesions develop in some aged animals. Our findings support the concept that rhesus macaques may be useful for the study of important age-related diseases such as glaucoma, macular diseases, and cone disorders, and for development of therapies for these diseases.
Keywords: Aging; Animals; Biometry; Disease Models, Animal; Eye Diseases; Macaca mulatta; Retinal Ganglion Cells; Tomography, Optical Coherence

Alternative genomic diagnoses for individuals with a clinical diagnosis of Dubowitz syndrome. - Dyment, David A; O'Donnell-Luria, Anne; Agrawal, Pankaj B; Coban Akdemir, Zeynep; Aleck, Kyrieckos A; Antaki, Danny; Al Sharhan, Hind; Au, Ping-Yee B; Aydin, Hatip; Beggs, Alan H; Bilguvar, Kaya; Eric Boerwinkle; et al. (Am J Med Genet A, 2021)
Dubowitz syndrome (DubS) is considered a recognizable syndrome characterized by a distinctive facial appearance and deficits in growth and development. There have been over 200 individuals reported with Dubowitz or a "Dubowitz-like" condition, although no single gene has been implicated as responsible for its cause. We have performed exome (ES) or genome sequencing (GS) for 31 individuals clinically diagnosed with DubS. After genome-wide sequencing, rare variant filtering and computational and Mendelian genomic analyses, a presumptive molecular diagnosis was made in 13/27 (48%) families. The molecular diagnoses included biallelic variants in SKIV2L, SLC35C1, BRCA1, NSUN2; de novo variants in ARID1B, ARID1A, CREBBP, POGZ, TAF1, HDAC8, and copy-number variation at1p36.11(ARID1A), 8q22.2(VPS13B), Xp22, and Xq13(HDAC8). Variants of unknown significance in known disease genes, and also in genes of uncertain significance, were observed in 7/27 (26%) additional families. Only one gene, HDAC8, could explain the phenotype in more than one family (N = 2). All but two of the genomic diagnoses were for genes discovered, or for conditions recognized, since the introduction of next-generation sequencing. Overall, the DubS-like clinical phenotype is associated with extensive locus heterogeneity and the molecular diagnoses made are for emerging clinical conditions sharing characteristic features that overlap the DubS phenotype.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Eczema; Exome; Exome Sequencing; Facies; Female; Genetic Predisposition to Disease; Genome, Human; Genomics; Growth Disorders; Histone Deacetylases; Humans; Infant; Intellectual Disability; Male; Microcephaly; Phenotype; Repressor Proteins

Clan genomics: From OMIM phenotypic traits to genes and biology. - James R Lupski (Am J Med Genet A, 2021)
Clinical characterization of a patient phenotype has been the quintessential approach for elucidating a differential diagnosis and a hypothesis to explore a potential clinical diagnosis. This has resulted in a language of medicine and a semantic ontology, with both specialty- and subspecialty-specific lexicons, that can be challenging to translate and interpret. There is no 'Rosetta Stone' of clinical medicine such as the genetic code that can assist translation and interpretation of the language of genetics. Nevertheless, the information content embodied within a clinical diagnosis can guide management, therapeutic intervention, and potentially prognostic outlook of disease enabling anticipatory guidance for patients and families. Clinical genomics is now established firmly in medical practice. The granularity and informative content of a personal genome is immense. Yet, we are limited in our utility of much of that personal genome information by the lack of functional characterization of the overwhelming majority of computationally annotated genes in the haploid human reference genome sequence. Whereas DNA and the genetic code have provided a 'Rosetta Stone' to translate genetic variant information, clinical medicine, and clinical genomics provide the context to understand human biology and disease. A path forward will integrate deep phenotyping, such as available in a clinical synopsis in the Online Mendelian Inheritance in Man (OMIM) entries, with personal genome analyses.
Keywords: Computational Biology; Databases, Genetic; Genetic Diseases, Inborn; Genetics, Medical; Genomics; Humans; Phenotype

Clinical characterization of individuals with the distal 1q21.1 microdeletion. - Edwards, Stacey D; Schulze, Katharina V; Rosenfeld, Jill A; Westerfield, Lauren E; Gerard, Amanda; Bo Yuan; Grigorenko, Elena L; Posey, Jennifer E; Bi, Weimin; Liu, Pengfei (Am J Med Genet A, 2021)
Distal 1q21.1 microdeletions have shown highly variable clinical expressivity and incomplete penetrance, with affected individuals manifesting a broad spectrum of nonspecific features. The goals of this study were to better describe the phenotypic spectrum of patients with distal 1q21.1 microdeletions and to compare the clinical features among affected individuals. We performed a retrospective chart review of 47 individuals with distal 1q21.1 microdeletions tested at a large clinical genetic testing laboratory, with most patients being clinically evaluated in the same children's hospital. Health information such as growth charts, results of imaging studies, developmental history, and progress notes were collected. Statistical analysis was performed using Fisher's exact test to compare clinical features among study subjects. Common features in our cohort include microcephaly (51.2%), seizures (29.8%), developmental delay (74.5%), failure to thrive (FTT) (68.1%), dysmorphic features (63.8%), and a variety of congenital anomalies such as cardiac abnormalities (23.4%) and genitourinary abnormalities (19.1%). Compared to prior literature, we found that seizures, brain anomalies, and FTT were more prevalent among our study cohort. Females were more likely than males to have microcephaly (p = 0.0199) and cardiac abnormalities (p = 0.0018). Based on existing genome-wide clinical testing results, at least a quarter of the cohort had additional genetic findings that may impact the phenotype of the individual. Our study represents the largest cohort of distal 1q21.1 microdeletion carriers available in the literature thus far, and it further illustrates the wide spectrum of clinical manifestations among symptomatic individuals. These results may allow for improved genetic counseling and management of affected individuals. Future studies may help to elucidate the underlying molecular mechanisms impacting the phenotypic variability observed with this microdeletion.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Child; Child, Preschool; Chromosome Deletion; Chromosomes, Human, Pair 1; Developmental Disabilities; DNA Copy Number Variations; Failure to Thrive; Female; Genetic Counseling; Genetic Testing; Heart Defects, Congenital; Humans; Infant; Intellectual Disability; Male; Megalencephaly; Microcephaly; Pedigree; Seizures; Young Adult

Clinical presentation and evolution of Xia-Gibbs syndrome due to p.Gly375ArgfsTer3 variant in a patient from DR Congo (Central Africa). - Mubungu, Gerrye; Makay, Prince; Boujemla, Bouchra; Yanda, Stephane; Posey, Jennifer E; James R Lupski; Bours, Vincent; Lukusa, Prosper; Devriendt, Koenraad; Lumaka, Aimé (Am J Med Genet A, 2021)
Xia-Gibbs syndrome (XGS) is a very rare genetic condition. The clinical spectrum is very broad and variable. The phenotype and evolution in a Congolese boy with XGS have been reported. At 6 years he had speech delay, drooling, marked hyperactivity, attention deficit, aggressive behavior, and intellectual disability. Dysmorphological evaluation revealed strabismus, mild unilateral ptosis, uplifted ear lobes, flat philtrum, thin upper lip vermillion, high arched palate, and flat feet. Patient-only whole exome sequencing identified a known pathogenic frameshift variant in the AHDC1 gene [NM_001029882.3(AHDC1):c.1122dupC;(p.Gly375ArgfsTer3)]. The clinical follow-up revealed the deterioration of his fine motor skills and significant cerebellar phenotype including tremor, pes cavus, and gait instability at the age of 12 years. This patient was compared with three previously reported patients with the same variant but did not identify a consistent pattern in the evolution of symptoms with age.
Keywords: Abnormalities, Multiple; Agenesis of Corpus Callosum; Attention Deficit Disorder with Hyperactivity; Child; Democratic Republic of the Congo; Developmental Disabilities; DNA-Binding Proteins; Exome Sequencing; Face; Frameshift Mutation; Humans; Intellectual Disability; Language Development Disorders; Male; Mitral Valve Insufficiency; Palate; Syndrome; Talipes Cavus

Common variants in Alzheimer's disease and risk stratification by polygenic risk scores. - de Rojas, Itziar; Moreno-Grau, Sonia; Tesi, Niccolo; Grenier-Boley, Benjamin; Andrade, Victor; Jansen, Iris E; Pedersen, Nancy L; Stringa, Najada; Zettergren, Anna; Hernández, Isabel; Montrreal, Laura; Antúnez, Carmen; et al. (Nat Commun, 2021)
Genetic discoveries of Alzheimer's disease are the drivers of our understanding, and together with polygenetic risk stratification can contribute towards planning of feasible and efficient preventive and curative clinical trials. We first perform a large genetic association study by merging all available case-control datasets and by-proxy study results (discovery n = 409,435 and validation size n = 58,190). Here, we add six variants associated with Alzheimer's disease risk (near APP, CHRNE, PRKD3/NDUFAF7, PLCG2 and two exonic variants in the SHARPIN gene). Assessment of the polygenic risk score and stratifying by APOE reveal a 4 to 5.5 years difference in median age at onset of Alzheimer's disease patients in APOE ɛ4 carriers. Because of this study, the underlying mechanisms of APP can be studied to refine the amyloid cascade and the polygenic risk score provides a tool to select individuals at high risk of Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Protein Precursor; Apolipoproteins E; Case-Control Studies; Cohort Studies; Datasets as Topic; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Humans; Male; Middle Aged; Multifactorial Inheritance; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors

COPB2 loss of function causes a coatopathy with osteoporosis and developmental delay. - Marom, Ronit; Burrage, Lindsay C; Venditti, Rossella; Clément, Aurélie; Blanco-Sánchez, Bernardo; Jain, Mahim; Scott, Daryl A; Rosenfeld, Jill A; Sutton, V Reid; Shinawi, Marwan; Mirzaa, Ghayda; DeVile, Catherine; et al. (Am J Hum Genet, 2021)
Coatomer complexes function in the sorting and trafficking of proteins between subcellular organelles. Pathogenic variants in coatomer subunits or associated factors have been reported in multi-systemic disorders, i.e., coatopathies, that can affect the skeletal and central nervous systems. We have identified loss-of-function variants in COPB2, a component of the coatomer complex I (COPI), in individuals presenting with osteoporosis, fractures, and developmental delay of variable severity. Electron microscopy of COPB2-deficient subjects' fibroblasts showed dilated endoplasmic reticulum (ER) with granular material, prominent rough ER, and vacuoles, consistent with an intracellular trafficking defect. We studied the effect of COPB2 deficiency on collagen trafficking because of the critical role of collagen secretion in bone biology. COPB2 siRNA-treated fibroblasts showed delayed collagen secretion with retention of type I collagen in the ER and Golgi and altered distribution of Golgi markers. copb2-null zebrafish embryos showed retention of type II collagen, disorganization of the ER and Golgi, and early larval lethality. Copb2 mice exhibited low bone mass, and consistent with the findings in human cells and zebrafish, studies in Copb2 mouse fibroblasts suggest ER stress and a Golgi defect. Interestingly, ascorbic acid treatment partially rescued the zebrafish developmental phenotype and the cellular phenotype in Copb2 mouse fibroblasts. This work identifies a form of coatopathy due to COPB2 haploinsufficiency, explores a potential therapeutic approach for this disorder, and highlights the role of the COPI complex as a regulator of skeletal homeostasis.
Keywords: Animals; Ascorbic Acid; Bone and Bones; Brain; Child; Child, Preschool; Coat Protein Complex I; Coatomer Protein; Collagen Type I; Developmental Disabilities; Embryo, Nonmammalian; Endoplasmic Reticulum; Female; Fibroblasts; Gene Expression Regulation, Developmental; Golgi Apparatus; Haploinsufficiency; Humans; Intellectual Disability; Male; Mice; Osteoporosis; RNA, Small Interfering; Severity of Illness Index; Zebrafish

COVID-19 disease and malignant cancers: The impact for the gene expression in susceptibility to SARS-CoV-2. - Li, Dabing; Liu, Xiaoyan; Zhang, Lianmei; He, Jiayue; Chen, Xianmao; Liu, Shuguang; Fu, Jiewen; Fu, Shangyi; Chen, Hanchun; Fu, Junjiang; Cheng, Jingliang (Int J Biol Sci, 2021)
Furin is a proprotein convertase that activates different kinds of regulatory proteins, including SARS-CoV-2 spike protein which contains an additional furin-specific cleavage site. It is essential in predicting cancer patients' susceptibility to SARS-CoV-2 and the disease outcomes due to varying furin expressions in tumor tissues. In this study, we analyzed furin's expression, methylation, mutation rate, functional enrichment, survival rate and COVID-19 outcomes in normal and cancer tissues using online databases, and our IHC. As a result, furin presented with biased expression profiles in normal tissues, showing 12.25-fold higher than ACE2 in the lungs. The furin expression in tumors were significantly increased in ESCA and TGCT, and decreased in DLBC and THYM, indicating furin may play critical mechanistic functions in COVID-19 viral entry into cells in these cancer patients. Line with furin over/downexpression, furin promoter hypo-/hyper-methylation may be the regulatory cause of disease and lead to pathogenesis of ESCA and THYM. Furthermore, presence of FURIN-201 isoform with functional domains (P_proprotein, Peptidase_S8 and S8_pro-domain) is highest in all cancer types in comparison to other isoforms, demonstrating its use in tumorigenesis and SARS-Cov-2 entry into tumor tissues. Furin mutation frequency was highest in UCES, and its mutation might elevate ACE2 expression in LUAD and UCEC, reduce ACE2 expression in COAD, elevate HSPA5 expression in PAAD, and elevate TMPRSS2 expression in BRCA. These results showed that furin mutations mostly increased expression of ACE2, HSPA5, and TMPRSS2 in certain cancers, indicating furin mutations might facilitate COVID-19 cell entry in cancer patients. In addition, high expression of furin was significantly inversely correlated with long overall survival (OS) in LGG and correlated with long OS in COAD and KIRC, indicating that it could be used as a favorable prognostic marker for cancer patients' survival. GO and KEGG demonstrated that furin was mostly enriched in genes for metabolic and biosynthetic processes, retinal dehydrogenase activity, tRNA methyltransferase activity, and genes involving COVID-19, further supporting its role in COVID-19 and cancer metabolism. Moreover, Cordycepin (CD) inhibited furin expression in a dosage dependent manner. Altogether, furin's high expression might not only implies increased susceptibility to SARS-CoV-2 and higher severity of COVID-19 symptoms in cancer patients, but also it highlights the need for cancer treatment and therapy during the COVID-19 pandemic. CD might have a potential to develop an anti-SARS-CoV-2 drug through inhibiting furin expression.
Keywords: Antineoplastic Agents; Cell Line, Tumor; COVID-19; Deoxyadenosines; Disease Susceptibility; Endoplasmic Reticulum Chaperone BiP; Furin; Humans; Neoplasms; Protein Isoforms; Serine Endopeptidases

Cross-oncopanel study reveals high sensitivity and accuracy with overall analytical performance depending on genomic regions. - Gong, Binsheng; Li, Dan; Kusko, Rebecca; Novoradovskaya, Natalia; Zhang, Yifan; Wang, Shangzi; Pabón-Peña, Carlos; Zhang, Zhihong; Lai, Kevin; Cai, Wanshi; LoCoco, Jennifer S; Lader, Eric; et al. (Genome Biol, 2021)
BACKGROUND: Targeted sequencing using oncopanels requires comprehensive assessments of accuracy and detection sensitivity to ensure analytical validity. By employing reference materials characterized by the U.S. Food and Drug Administration-led SEquence Quality Control project phase2 (SEQC2) effort, we perform a cross-platform multi-lab evaluation of eight Pan-Cancer panels to assess best practices for oncopanel sequencing. RESULTS: All panels demonstrate high sensitivity across targeted high-confidence coding regions and variant types for the variants previously verified to have variant allele frequency (VAF) in the 5-20% range. Sensitivity is reduced by utilizing VAF thresholds due to inherent variability in VAF measurements. Enforcing a VAF threshold for reporting has a positive impact on reducing false positive calls. Importantly, the false positive rate is found to be significantly higher outside the high-confidence coding regions, resulting in lower reproducibility. Thus, region restriction and VAF thresholds lead to low relative technical variability in estimating promising biomarkers and tumor mutational burden. CONCLUSION: This comprehensive study provides actionable guidelines for oncopanel sequencing and clear evidence that supports a simplified approach to assess the analytical performance of oncopanels. It will facilitate the rapid implementation, validation, and quality control of oncopanels in clinical use.
Keywords: Biomarkers, Tumor; DNA Copy Number Variations; Genetic Testing; Genomics; Humans; Molecular Diagnostic Techniques; Mutation; Neoplasms; Oncogenes; Polymorphism, Single Nucleotide; Reproducibility of Results; Sensitivity and Specificity

Deforming Polyarthritis in a North Indian Family-Clinical Expansion of STING-Associated Vasculopathy with Onset in Infancy (SAVI). - Anjani, Gummadi; Jindal, Ankur Kumar; Prithvi, Ashwini; Kaur, Anit; Rawat, Amit; Sharma, Madhubala; Bo Yuan; Chinn, Ivan K; Singh, Surjit (J Clin Immunol, 2021)
Keywords: Anti-Inflammatory Agents; Arthritis; Biomarkers; Child; Child, Preschool; Diagnosis, Differential; Family; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Immunosuppressive Agents; India; Joints; Male; Membrane Proteins; Phenotype; Tomography, X-Ray Computed; Treatment Outcome

Determinants of penetrance and variable expressivity in monogenic metabolic conditions across 77,184 exomes. - Goodrich, Julia K; Singer-Berk, Moriel; Son, Rachel; Sveden, Abigail; Wood, Jordan; England, Eleina; Cole, Joanne B; Weisburd, Ben; Watts, Nick; Caulkins, Lizz; Dornbos, Peter; Koesterer, Ryan; et al. (Nat Commun, 2021)
Hundreds of thousands of genetic variants have been reported to cause severe monogenic diseases, but the probability that a variant carrier develops the disease (termed penetrance) is unknown for virtually all of them. Additionally, the clinical utility of common polygenetic variation remains uncertain. Using exome sequencing from 77,184 adult individuals (38,618 multi-ancestral individuals from a type 2 diabetes case-control study and 38,566 participants from the UK Biobank, for whom genotype array data were also available), we apply clinical standard-of-care gene variant curation for eight monogenic metabolic conditions. Rare variants causing monogenic diabetes and dyslipidemias display effect sizes significantly larger than the top 1% of the corresponding polygenic scores. Nevertheless, penetrance estimates for monogenic variant carriers average 60% or lower for most conditions. We assess epidemiologic and genetic factors contributing to risk prediction in monogenic variant carriers, demonstrating that inclusion of polygenic variation significantly improves biomarker estimation for two monogenic dyslipidemias.
Keywords: Adult; Biological Variation, Population; Biomarkers; Diabetes Mellitus, Type 2; Dyslipidemias; Exome; Genetic Predisposition to Disease; Genotype; Humans; Multifactorial Inheritance; Penetrance; Risk Assessment

DNA methylation patterns identify subgroups of pancreatic neuroendocrine tumors with clinical association. - Lakis, Vanessa; Lawlor, Rita T; Newell, Felicity; Patch, Ann-Marie; Mafficini, Andrea; Sadanandam, Anguraj; Koufariotis, Lambros T; Johnston, Rebecca L; Leonard, Conrad; Wood, Scott; Rusev, Borislav; Corbo, Vincenzo; et al. (Commun Biol, 2021)
Here we report the DNA methylation profile of 84 sporadic pancreatic neuroendocrine tumors (PanNETs) with associated clinical and genomic information. We identified three subgroups of PanNETs, termed T1, T2 and T3, with distinct patterns of methylation. The T1 subgroup was enriched for functional tumors and ATRX, DAXX and MEN1 wild-type genotypes. The T2 subgroup contained tumors with mutations in ATRX, DAXX and MEN1 and recurrent patterns of chromosomal losses in half of the genome with no association between regions with recurrent loss and methylation levels. T2 tumors were larger and had lower methylation in the MGMT gene body, which showed positive correlation with gene expression. The T3 subgroup harboured mutations in MEN1 with recurrent loss of chromosome 11, was enriched for grade G1 tumors and showed histological parameters associated with better prognosis. Our results suggest a role for methylation in both driving tumorigenesis and potentially stratifying prognosis in PanNETs.
Keywords: Biomarkers, Tumor; Carcinoma, Neuroendocrine; DNA Methylation; Epigenesis, Genetic; Epigenome; Epigenomics; Genetic Predisposition to Disease; Humans; Neoplasm Grading; Pancreatic Neoplasms; Phenotype; Tumor Burden

Drivers of transcriptional variance in human intestinal epithelial organoids. - Criss, Zachary K; Bhasin, Nobel; Di Rienzi, Sara C; Rajan, Anubama; Deans-Fielder, Kali; Swaminathan, Ganesh; Kamyabi, Nabiollah; Zeng, Xi-Lei; Harshavardhan Doddapaneni; Menon, Vipin K; Chakravarti, Deepavali; Estrella, Clarissa; et al. (Physiol Genomics, 2021)
Human intestinal epithelial organoids (enteroids and colonoids) are tissue cultures used for understanding the physiology of the human intestinal epithelium. Here, we explored the effect on the transcriptome of common variations in culture methods, including extracellular matrix substrate, format, tissue segment, differentiation status, and patient heterogeneity. RNA-sequencing datasets from 276 experiments performed on 37 human enteroid and colonoid lines from 29 patients were aggregated from several groups in the Texas Medical Center. DESeq2 and gene set enrichment analysis (GSEA) were used to identify differentially expressed genes and enriched pathways. PERMANOVA, Pearson's correlation, and dendrogram analysis of the data originally indicated three tiers of influence of culture methods on transcriptomic variation: substrate (collagen vs. Matrigel) and format (3-D, transwell, and monolayer) had the largest effect; segment of origin (duodenum, jejunum, ileum, colon) and differentiation status had a moderate effect; and patient heterogeneity and specific experimental manipulations (e.g., pathogen infection) had the smallest effect. GSEA identified hundreds of pathways that varied between culture methods, such as IL1 cytokine signaling enriched in transwell versus monolayer cultures and E2F target genes enriched in collagen versus Matrigel cultures. The transcriptional influence of the format was furthermore validated in a synchronized experiment performed with various format-substrate combinations. Surprisingly, large differences in organoid transcriptome were driven by variations in culture methods such as format, whereas experimental manipulations such as infection had modest effects. These results show that common variations in culture conditions can have large effects on intestinal organoids and should be accounted for when designing experiments and comparing results between laboratories. Our data constitute the largest RNA-seq dataset interrogating human intestinal epithelial organoids.
Keywords: Calcitriol; Cell Culture Techniques; Collagen; Colon; Crohn Disease; Culture Media; Drug Combinations; Escherichia coli; Escherichia coli Infections; Extracellular Matrix; Gene Expression Regulation; Humans; Intestinal Mucosa; Intestine, Small; Laminin; Organoids; Proteoglycans; RNA-Seq; Transcriptome; Virus Diseases; Viruses

Epigenome-wide association study of mitochondrial genome copy number. - Wang, Penglong; Castellani, Christina A; Yao, Jie; Huan, Tianxiao; Bielak, Lawrence F; Zhao, Wei; Haessler, Jeffrey; Joehanes, Roby; Sun, Xianbang; Guo, Xiuqing; Longchamps, Ryan J; Manson, JoAnn E; et al. (Hum Mol Genet, 2021)
We conducted cohort- and race-specific epigenome-wide association analyses of mitochondrial deoxyribonucleic acid (mtDNA) copy number (mtDNA CN) measured in whole blood from participants of African and European origins in five cohorts (n = 6182, mean age = 57-67 years, 65% women). In the meta-analysis of all the participants, we discovered 21 mtDNA CN-associated DNA methylation sites (CpG) (P < 1 × 10-7), with a 0.7-3.0 standard deviation increase (3 CpGs) or decrease (18 CpGs) in mtDNA CN corresponding to a 1% increase in DNA methylation. Several significant CpGs have been reported to be associated with at least two risk factors (e.g. chronological age or smoking) for cardiovascular disease (CVD). Five genes [PR/SET domain 16, nuclear receptor subfamily 1 group H member 3 (NR1H3), DNA repair protein, DNA polymerase kappa and decaprenyl-diphosphate synthase subunit 2], which harbor nine significant CpGs, are known to be involved in mitochondrial biosynthesis and functions. For example, NR1H3 encodes a transcription factor that is differentially expressed during an adipose tissue transition. The methylation level of cg09548275 in NR1H3 was negatively associated with mtDNA CN (effect size = -1.71, P = 4 × 10-8) and was positively associated with the NR1H3 expression level (effect size = 0.43, P = 0.0003), which indicates that the methylation level in NR1H3 may underlie the relationship between mtDNA CN, the NR1H3 transcription factor and energy expenditure. In summary, the study results suggest that mtDNA CN variation in whole blood is associated with DNA methylation levels in genes that are involved in a wide range of mitochondrial activities. These findings will help reveal molecular mechanisms between mtDNA CN and CVD.
Keywords: Aged; DNA Copy Number Variations; DNA Methylation; DNA, Mitochondrial; Epigenome; Female; Genome, Mitochondrial; Humans; Male; Middle Aged

Exome sequencing in children with clinically suspected maturity-onset diabetes of the young. - Tosur, Mustafa; Soler-Alfonso, Claudia; Chan, Katie M; Khayat, Michael M; Jhangiani, Shalini N; Meng, Qingchang; Refaey, Ahmad; Donna M Muzny; Richard A Gibbs; David R Murdock; Posey, Jennifer E; Balasubramanyam, Ashok; et al. (Pediatr Diabetes, 2021)
OBJECTIVE: Commercial gene panels identify pathogenic variants in as low as 27% of patients suspected to have MODY, suggesting the role of yet unidentified pathogenic variants. We sought to identify novel gene variants associated with MODY. RESEARCH DESIGN AND METHODS: We recruited 10 children with a clinical suspicion of MODY but non-diagnostic commercial MODY gene panels. We performed exome sequencing (ES) in them and their parents. RESULTS: Mean age at diabetes diagnosis was 10 (± 3.8) years. Six were females; 4 were non-Hispanic white, 5 Hispanic, and 1 Asian. Our variant prioritization analysis identified a pathogenic, de novo variant in INS (c.94G > A, p.Gly32Ser), confirmed by Sanger sequencing, in a proband who was previously diagnosed with "autoantibody-negative type 1 diabetes (T1D)" at 3 y/o. This rare variant, absent in the general population (gnomAD database), has been reported previously in neonatal diabetes. We also identified a frameshift deletion (c.2650delC, p.Gln884AsnfsTer57) in RFX6 in a child with a previous diagnosis of "autoantibody-negative T1D" at 12 y/o. The variant was inherited from the mother, who was diagnosed with "thin type 2 diabetes" at 25 y/o. Heterozygous protein-truncating variants in RFX6 gene have been recently reported in individuals with MODY. CONCLUSIONS: We diagnosed two patients with MODY using ES in children initially classified as "T1D". One has a likely pathogenic novel gene variant not previously associated with MODY. We demonstrate the clinical utility of ES in patients with clinical suspicion of MODY.
Keywords: Adolescent; Autoantibodies; Child; Diabetes Mellitus, Type 1; Diabetes Mellitus, Type 2; Diagnosis, Differential; Exome Sequencing; Female; Frameshift Mutation; Genetic Variation; Humans; Islets of Langerhans; Male; Mutation, Missense; Pedigree

Exome sequencing reveals genetic architecture in patients with isolated or syndromic short stature. - Fan, Xin; Zhao, Sen; Yu, Chenxi; Wu, Di; Yan, Zihui; Fan, Lijun; Song, Yanning; Wang, Yi; Li, Chuan; Ming, Yue; Gui, Baoheng; Niu, Yuchen; et al. (J Genet Genomics, 2021)
Short stature is among the most common endocrinological disease phenotypes of childhood and may occur as an isolated finding or in conjunction with other clinical manifestations. Although the diagnostic utility of clinical genetic testing in short stature has been implicated, the genetic architecture and the utility of genomic studies such as exome sequencing (ES) in a sizable cohort of patients with short stature have not been investigated systematically. In this study, we recruited 561 individuals with short stature from two centers in China during a 4-year period. We performed ES for all patients and available parents. All patients were retrospectively divided into two groups: an isolated short stature group (group I, n = 257) and an apparently syndromic short stature group (group II, n = 304). Causal variants were identified in 135 of 561 (24.1%) patients. In group I, 29 of 257 (11.3%) of the patients were solved by variants in 24 genes. In group II, 106 of 304 (34.9%) patients were solved by variants in 57 genes. Genes involved in fundamental cellular process played an important role in the genetic architecture of syndromic short stature. Distinct genetic architectures and pathophysiological processes underlie isolated and syndromic short stature.
Keywords: Adolescent; Alleles; Child; Child, Preschool; China; Disease Management; DNA Copy Number Variations; Dwarfism; Exome; Exome Sequencing; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Testing; Genotype; Humans; Male; Mutation; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Syndrome

Functional interpretation of ATAD3A variants in neuro-mitochondrial phenotypes. - Yap, Zheng Yie; Park, Yo Han; Wortmann, Saskia B; Gunning, Adam C; Ezer, Shlomit; Lee, Sukyeong; Duraine, Lita; Wilichowski, Ekkehard; Wilson, Kate; Mayr, Johannes A; Wagner, Matias; Li, Hong; et al. (Genome Med, 2021)
BACKGROUND: ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane-anchored protein involved in diverse processes including mitochondrial dynamics, mitochondrial DNA organization, and cholesterol metabolism. Biallelic deletions (null), recessive missense variants (hypomorph), and heterozygous missense variants or duplications (antimorph) in ATAD3A lead to neurological syndromes in humans. METHODS: To expand the mutational spectrum of ATAD3A variants and to provide functional interpretation of missense alleles in trans to deletion alleles, we performed exome sequencing for identification of single nucleotide variants (SNVs) and copy number variants (CNVs) in ATAD3A in individuals with neurological and mitochondrial phenotypes. A Drosophila Atad3a Gal4 knockin-null allele was generated using CRISPR-Cas9 genome editing technology to aid the interpretation of variants. RESULTS: We report 13 individuals from 8 unrelated families with biallelic ATAD3A variants. The variants included four missense variants inherited in trans to loss-of-function alleles (p.(Leu77Val), p.(Phe50Leu), p.(Arg170Trp), p.(Gly236Val)), a homozygous missense variant p.(Arg327Pro), and a heterozygous non-frameshift indel p.(Lys568del). Affected individuals exhibited findings previously associated with ATAD3A pathogenic variation, including developmental delay, hypotonia, congenital cataracts, hypertrophic cardiomyopathy, and cerebellar atrophy. Drosophila studies indicated that Phe50Leu, Gly236Val, Arg327Pro, and Lys568del are severe loss-of-function alleles leading to early developmental lethality. Further, we showed that Phe50Leu, Gly236Val, and Arg327Pro cause neurogenesis defects. On the contrary, Leu77Val and Arg170Trp are partial loss-of-function alleles that cause progressive locomotion defects and whose expression leads to an increase in autophagy and mitophagy in adult muscles. CONCLUSION: Our findings expand the allelic spectrum of ATAD3A variants and exemplify the use of a functional assay in Drosophila to aid variant interpretation.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Animals; ATPases Associated with Diverse Cellular Activities; Autophagy; Computer Simulation; Drosophila; Female; Genetic Variation; Humans; Infant; Infant, Newborn; Locomotion; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Mitophagy; Mutation, Missense; Neurogenesis; Neurons; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Young Adult

Genetic susceptibility, obesity and lifetime risk of type 2 diabetes: The ARIC study and Rotterdam Study. - Ligthart, Symen; Hasbani, Natalie R; Ahmadizar, Fariba; van Herpt, Thijs T W; Leening, Maarten J G; Uitterlinden, André G; Sijbrands, Eric J G; Morrison, Alanna C; Eric Boerwinkle; Pankow, James S; Selvin, Elizabeth; Ikram, M Arfan; et al. (Diabet Med, 2021)
AIMS: Both lifestyle factors and genetic background contribute to the development of type 2 diabetes. Estimation of the lifetime risk of diabetes based on genetic information has not been presented, and the extent to which a normal body weight can offset a high lifetime genetic risk is unknown. METHODS: We used data from 15,671 diabetes-free participants of European ancestry aged 45 years and older from the prospective population-based ARIC study and Rotterdam Study (RS). We quantified the remaining lifetime risk of diabetes stratified by genetic risk and quantified the effect of normal weight in terms of relative and lifetime risks in low, intermediate and high genetic risk. RESULTS: At age 45 years, the lifetime risk of type 2 diabetes in ARIC in the low, intermediate and high genetic risk category was 33.2%, 41.3% and 47.2%, and in RS 22.8%, 30.6% and 35.5% respectively. The absolute lifetime risk for individuals with normal weight compared to individuals with obesity was 24% lower in ARIC and 8.6% lower in RS in the low genetic risk group, 36.3% lower in ARIC and 31.3% lower in RS in the intermediate genetic risk group, and 25.0% lower in ARIC and 29.4% lower in RS in the high genetic risk group. CONCLUSIONS: Genetic variants for type 2 diabetes have value in estimating the lifetime risk of type 2 diabetes. Normal weight mitigates partly the deleterious effect of high genetic risk.
Keywords: Aged; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Life Style; Male; Middle Aged; Multifactorial Inheritance; Obesity; Risk; White People

Genome-wide ancestry and introgression in a Zambian baboon hybrid zone. - Chiou, Kenneth L; Bergey, Christina M; Burrell, Andrew S; Disotell, Todd R; Jeffrey Rogers; Jolly, Clifford J; Phillips-Conroy, Jane E (Mol Ecol, 2021)
Hybridization in nature offers unique insights into the process of natural selection in incipient species and their hybrids. In order to evaluate the patterns and targets of selection, we examine a recently discovered baboon hybrid zone in the Kafue River Valley of Zambia, where Kinda baboons (Papio kindae) and grey-footed chacma baboons (P. ursinus griseipes) coexist with hybridization. We genotyped baboons at 14,962 variable genome-wide autosomal markers using double-digest RADseq. We compared ancestry patterns from this genome-wide data set to previously reported ancestry from mitochondrial-DNA and Y-chromosome sources. We also fit a Bayesian genomic cline model to scan for genes with extreme patterns of introgression. We show that the Kinda baboon Y chromosome has penetrated the species boundary to a greater extent than either mitochondrial DNA or the autosomal chromosomes. We also find evidence for overall restricted introgression in the JAK/STAT signalling pathway. Echoing results in other species including humans, we find evidence for enhanced and/or directional introgression of immune-related genes or pathways including the toll-like receptor pathway, the blood coagulation pathway, and the LY96 gene. Finally we show enhanced introgression and excess chacma baboon ancestry in the sperm tail gene ODF2. Together, our results elucidate the dynamics of introgressive hybridization in a primate system while identifying genes and pathways possibly under selection.
Keywords: Animals; Bayes Theorem; DNA, Mitochondrial; Hybridization, Genetic; Papio; Zambia

High resolution copy number inference in cancer using short-molecule nanopore sequencing. - Baslan, Timour; Kovaka, Sam; Fritz J Sedlazeck; Zhang, Yanming; Wappel, Robert; Tian, Sha; Lowe, Scott W; Goodwin, Sara; Schatz, Michael C (Nucleic Acids Res, 2021)
Genome copy number is an important source of genetic variation in health and disease. In cancer, Copy Number Alterations (CNAs) can be inferred from short-read sequencing data, enabling genomics-based precision oncology. Emerging Nanopore sequencing technologies offer the potential for broader clinical utility, for example in smaller hospitals, due to lower instrument cost, higher portability, and ease of use. Nonetheless, Nanopore sequencing devices are limited in the number of retrievable sequencing reads/molecules compared to short-read sequencing platforms, limiting CNA inference accuracy. To address this limitation, we targeted the sequencing of short-length DNA molecules loaded at optimized concentration in an effort to increase sequence read/molecule yield from a single nanopore run. We show that short-molecule nanopore sequencing reproducibly returns high read counts and allows high quality CNA inference. We demonstrate the clinical relevance of this approach by accurately inferring CNAs in acute myeloid leukemia samples. The data shows that, compared to traditional approaches such as chromosome analysis/cytogenetics, short molecule nanopore sequencing returns more sensitive, accurate copy number information in a cost effective and expeditious manner, including for multiplex samples. Our results provide a framework for short-molecule nanopore sequencing with applications in research and medicine, which includes but is not limited to, CNAs.
Keywords: Cell Line, Tumor; DNA; DNA Copy Number Variations; Humans; Medical Oncology; Nanopore Sequencing; Neoplasms

A High-throughput Approach to Identify Effective Systemic Agents for the Treatment of Anaplastic Thyroid Carcinoma. - Henderson, Ying C; Mohamed, Abdallah S R; Maniakas, Anastasios; Chen, Yunyun; Powell, Reid T; Peng, Shaohua; Cardenas, Maria; Williams, Michelle D; Bell, Diana; Zafereo, Mark E; Wang, Rui Jennifer; Steven E Scherer; et al. (J Clin Endocrinol Metab, 2021)
BACKGROUND: Despite the use of aggressive multimodality treatment, most anaplastic thyroid carcinoma (ATC) patients die within a year of diagnosis. Although the combination of BRAF and MEK inhibitors has recently been approved for use in BRAF-mutated ATC, they remain effective in a minority of patients who are likely to develop drug resistance. There remains a critical clinical need for effective systemic agents for ATC with a reasonable toxicity profile to allow for rapid translational development. MATERIAL AND METHODS: Twelve human thyroid cancer cell lines with comprehensive genomic characterization were used in a high-throughput screening (HTS) of 257 compounds to select agents with maximal growth inhibition. Cell proliferation, colony formation, orthotopic thyroid models, and patient-derived xenograft (PDX) models were used to validate the selected agents. RESULTS: Seventeen compounds were effective, and docetaxel, LBH-589, and pralatrexate were selected for additional in vitro and in vivo analysis as they have been previously approved by the US Food and Drug Administration for other cancers. Significant tumor growth inhibition (TGI) was detected in all tested models treated with LBH-589; pralatrexate demonstrated significant TGI in the orthotopic papillary thyroid carcinoma model and 2 PDX models; and docetaxel demonstrated significant TGI only in the context of mutant TP53. CONCLUSIONS: HTS identified classes of systemic agents that demonstrate preferential effectiveness against aggressive thyroid cancers, particularly those with mutant TP53. Preclinical validation in both orthotopic and PDX models, which are accurate in vivo models mimicking tumor microenvironment, may support initiation of early-phase clinical trials in non-BRAF mutated or refractory to BRAF/MEK inhibition ATC.
Keywords: Animals; Antineoplastic Agents; Carcinogenicity Tests; Cell Line, Tumor; Disease Models, Animal; High-Throughput Screening Assays; Humans; Protein Kinase Inhibitors; Proto-Oncogene Proteins B-raf; Thyroid Carcinoma, Anaplastic; Thyroid Neoplasms; Tumor Microenvironment

Investigation of product-derived lymphoma following infusion of piggyBac-modified CD19 chimeric antigen receptor T cells. - Micklethwaite, Kenneth P; Gowrishankar, Kavitha; Gloss, Brian S; Li, Ziduo; Street, Janine A; Moezzi, Leili; Mach, Melanie A; Sutrave, Gaurav; Clancy, Leighton E; Bishop, David C; Louie, Raymond H Y; Cai, Curtis; et al. (Blood, 2021)
We performed a phase 1 clinical trial to evaluate outcomes in patients receiving donor-derived CD19-specific chimeric antigen receptor (CAR) T cells for B-cell malignancy that relapsed or persisted after matched related allogeneic hemopoietic stem cell transplant. To overcome the cost and transgene-capacity limitations of traditional viral vectors, CAR T cells were produced using the piggyBac transposon system of genetic modification. Following CAR T-cell infusion, 1 patient developed a gradually enlarging retroperitoneal tumor due to a CAR-expressing CD4+ T-cell lymphoma. Screening of other patients led to the detection, in an asymptomatic patient, of a second CAR T-cell tumor in thoracic para-aortic lymph nodes. Analysis of the first lymphoma showed a high transgene copy number, but no insertion into typical oncogenes. There were also structural changes such as altered genomic copy number and point mutations unrelated to the insertion sites. Transcriptome analysis showed transgene promoter-driven upregulation of transcription of surrounding regions despite insulator sequences surrounding the transgene. However, marked global changes in transcription predominantly correlated with gene copy number rather than insertion sites. In both patients, the CAR T-cell-derived lymphoma progressed and 1 patient died. We describe the first 2 cases of malignant lymphoma derived from CAR gene-modified T cells. Although CAR T cells have an enviable record of safety to date, our results emphasize the need for caution and regular follow-up of CAR T recipients, especially when novel methods of gene transfer are used to create genetically modified immune therapies. This trial was registered at www.anzctr.org.au as ACTRN12617001579381.
Keywords: Aged; DNA Transposable Elements; Gene Expression Regulation, Neoplastic; Gene Transfer Techniques; Humans; Immunotherapy, Adoptive; Leukemia, B-Cell; Lymphoma; Lymphoma, B-Cell; Male; Receptors, Antigen, T-Cell; T-Lymphocytes; Transcriptome; Transgenes

MED27 Variants Cause Developmental Delay, Dystonia, and Cerebellar Hypoplasia. - Meng, Linyan; Isohanni, Pirjo; Shao, Yunru; Graham, Brett H; Hickey, Scott E; Brooks, Stephanie; Suomalainen, Anu; Joset, Pascal; Steindl, Katharina; Rauch, Anita; Hackenberg, Annette; High, Frances A; et al. (Ann Neurol, 2021)
The Mediator multiprotein complex functions as a regulator of RNA polymerase II-catalyzed gene transcription. In this study, exome sequencing detected biallelic putative disease-causing variants in MED27, encoding Mediator complex subunit 27, in 16 patients from 11 families with a novel neurodevelopmental syndrome. Patient phenotypes are highly homogeneous, including global developmental delay, intellectual disability, axial hypotonia with distal spasticity, dystonic movements, and cerebellar hypoplasia. Seizures and cataracts were noted in severely affected individuals. Identification of multiple patients with biallelic MED27 variants supports the critical role of MED27 in normal human neural development, particularly for the cerebellum. ANN NEUROL 2021;89:828-833.
Keywords: Adolescent; Adult; Amino Acid Sequence; Cataract; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Dystonia; Epilepsy; Exome Sequencing; Genetic Variation; Humans; Infant; Mediator Complex; Nervous System Malformations; Phenotype

Multiplexed Simian Immunodeficiency Virus-Specific Paired RNA-Guided Cas9 Nickases Inactivate Proviral DNA. - Smith, Lisa M; Ladner, Jason T; Hodara, Vida L; Parodi, Laura M; R. Alan Harris; Callery, Jessica E; Lai, Zhao; Zou, Yi; Raveedran, Muthuswamy; Jeffrey Rogers; Giavedoni, Luis D (J Virol, 2021)
Human and simian immunodeficiency virus (HIV and SIV) infections establish lifelong reservoirs of cells harboring an integrated proviral genome. Genome editing CRISPR-associated Cas9 nucleases, combined with SIV-specific guiding RNA (gRNA) molecules, inactivate integrated provirus DNA and in animal models. We generated RNA-guided Cas9 nucleases (RGNu) and nickases (RGNi) targeting conserved SIV regions with no homology in the human or rhesus macaque genome. Assays in cells cotransfected with SIV provirus and plasmids coding for RGNus identified SIV long terminal repeat (LTR), -activation response (TAR) element, and ribosome slip site (RSS) regions as the most effective at virus suppression; RGNi targeting these regions inhibited virus production significantly. Multiplex plasmids that coexpressed these three RGNu (Nu3), or six (three pairs) RGNi (Ni6), were more efficient at virus suppression than any combination of individual RGNu and RGNi plasmids. Both Nu3 and Ni6 plasmids were tested in lymphoid cells chronically infected with SIV, and whole-genome sequencing was used to determine on- and off-target mutations. Treatment with these all-in-one plasmids resulted in similar levels of mutations of viral sequences from the cellular genome; Nu3 induced indels at the 3 SIV-specific sites, whereas for Ni6 indels were present at the LTR and TAR sites. Levels of off-target effects detected by two different algorithms were indistinguishable from background mutations. In summary, we demonstrate that Cas9 nickase in association with gRNA pairs can specifically eliminate parts of the integrated provirus DNA; also, we show that careful design of an all-in-one plasmid coding for 3 gRNAs and Cas9 nuclease inhibits SIV production with undetectable off-target mutations, making these tools a desirable prospect for moving into animal studies. Our approach to HIV cure, utilizing the translatable SIV/rhesus macaque model system, aims at provirus inactivation and its removal with the least possible off-target side effects. We developed single molecules that delivered either three truncated SIV-specific gRNAs along with Cas9 nuclease or three pairs of SIV-specific gRNAs (six individual gRNAs) along with Cas9 nickase to enhance efficacy of on-target mutagenesis. Whole-genome sequencing demonstrated effective SIV sequence mutation and inactivation and the absence of demonstrable off-target mutations. These results open the possibility to employ Cas9 variants that introduce single-strand DNA breaks to eliminate integrated proviral DNA.
Keywords: Animals; CRISPR-Cas Systems; Deoxyribonuclease I; DNA; Endonucleases; Gene Editing; HEK293 Cells; Humans; Macaca mulatta; Mutagenesis; Plasmids; Proviruses; RNA, Guide, Kinetoplastida; Simian Immunodeficiency Virus

Novel Anaplastic Thyroid Cancer PDXs and Cell Lines: Expanding Preclinical Models of Genetic Diversity. - Maniakas, Anastasios; Henderson, Ying C; Hei, Hu; Peng, Shaohua; Chen, Yunyun; Jiang, Yujie; Ji, Shuangxi; Cardenas, Maria; Chiu, Yulun; Bell, Diana; Williams, Michelle D; Hofmann, Marie-Claude; et al. (J Clin Endocrinol Metab, 2021)
CONTEXT: Anaplastic thyroid cancer (ATC) is a rare, aggressive, and deadly disease. Robust preclinical thyroid cancer models are needed to adequately develop and study novel therapeutic agents. Patient-derived xenograft (PDX) models may resemble patient tumors by recapitulating key genetic alterations and gene expression patterns, making them excellent preclinical models for drug response evaluation. OBJECTIVE: We developed distinct ATC PDX models concurrently with cell lines and characterized them in vitro and in vivo. METHODS: Fresh thyroid tumor from patients with a preoperative diagnosis of ATC was surgically collected and divided for concurrent cell line and PDX model development. Cell lines were created by generating single cells through enzymatic digestion. PDX models were developed following direct subcutaneous implantation of fresh tumor on the flank of immune compromised/athymic mice. RESULTS: Six ATC PDX models and 4 cell lines were developed with distinct genetic profiles. Mutational characterization showed one BRAF/TP53/CDKN2A, one BRAF/CDKN2A, one BRAF/TP53, one TP53 only, one TERT-promoter/HRAS, and one TERT-promoter/KRAS/TP53/NF2/NFE2L2 mutated phenotype. Hematoxylin-eosin staining comparing the PDX models to the original patient surgical specimens show remarkable resemblance, while immunohistochemistry stains for important biomarkers were in full concordance (cytokeratin, TTF-1, PAX8, BRAF). Short tandem repeats DNA fingerprinting analysis of all PDX models and cell lines showed strong concordance with the original tumor. PDX successful establishment rate was 32%. CONCLUSION: We have developed and characterized 6 novel ATC PDX models with 4 matching cell lines. Each PDX model harbors a distinct genetic profile, making them excellent tools for preclinical therapeutic trials.
Keywords: Aged; Animals; Apoptosis; Biomarkers, Tumor; Cell Proliferation; Disease Models, Animal; Female; Gene Expression Regulation, Neoplastic; Humans; Male; Mice; Middle Aged; Phenotype; Prognosis; Survival Rate; Thyroid Carcinoma, Anaplastic; Thyroid Neoplasms; Tumor Cells, Cultured; Xenograft Model Antitumor Assays

A novel homozygous SLC13A5 whole-gene deletion generated by Alu/Alu-mediated rearrangement in an Iraqi family with epileptic encephalopathy. - Duan, Ruizhi; Saadi, Nebal Waill; Grochowski, Christopher M; Bhadila, Ghalia; Faridoun, Afnan; Mitani, Tadahiro; Du, Haowei; Fatih, Jawid M; Jhangiani, Shalini N; Akdemir, Zeynep C; Richard A Gibbs; Pehlivan, Davut; et al. (Am J Med Genet A, 2021)
Biallelic loss-of-function (LoF) of SLC13A5 (solute carrier family 13, member 5) induced deficiency in sodium/citrate transporter (NaCT) causes autosomal recessive developmental epileptic encephalopathy 25 with hypoplastic amelogenesis imperfecta (DEE25; MIM #615905). Many pathogenic SLC13A5 single nucleotide variants (SNVs) and small indels have been described; however, no cases with copy number variants (CNVs) have been sufficiently investigated. We describe a consanguineous Iraqi family harboring an 88.5 kb homozygous deletion including SLC13A5 in Chr17p13.1. The three affected male siblings exhibit neonatal-onset epilepsy with fever-sensitivity, recurrent status epilepticus, global developmental delay/intellectual disability (GDD/ID), and other variable neurological findings as shared phenotypical features of DEE25. Two of the three affected subjects exhibit hypoplastic amelogenesis imperfecta (AI), while the proband shows no evidence of dental abnormalities or AI at 2 years of age with apparently unaffected primary dentition. Characterization of the genomic architecture at this locus revealed evidence for genomic instability generated by an Alu/Alu-mediated rearrangement; confirmed by break-point junction Sanger sequencing. This multiplex family from a distinct population elucidates the phenotypic consequence of complete LoF of SLC13A5 and illustrates the importance of read-depth-based CNV detection in comprehensive exome sequencing analysis to solve cases that otherwise remain molecularly unsolved.
Keywords: Alu Elements; Child, Preschool; Chromosomes, Human, Pair 17; DNA Copy Number Variations; Epilepsy, Generalized; Exome Sequencing; Female; Homozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Pedigree; Sequence Deletion; Symporters

Novel pathogenic genomic variants leading to autosomal dominant and recessive Robinow syndrome. - Zhang, Chaofan; Mazzeu, Juliana F; Eisfeldt, Jesper; Grochowski, Christopher M; White, Janson; Akdemir, Zeynep C; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; Lindstrand, Anna; James R Lupski; Sutton, V Reid; et al. (Am J Med Genet A, 2021)
Robinow syndrome (RS) is a genetically heterogeneous disorder characterized by skeletal dysplasia and a distinctive facial appearance. Previous studies have revealed locus heterogeneity with rare variants in DVL1, DVL3, FZD2, NXN, ROR2, and WNT5A underlying the etiology of RS. The aforementioned "Robinow-associated genes" and their gene products all play a role in the WNT/planar cell polarity signaling pathway. We performed gene-targeted Sanger sequencing, exome sequencing, genome sequencing, and array comparative genomic hybridization on four subjects with a clinical diagnosis of RS who had not had prior DNA testing. Individuals in our cohort were found to carry pathogenic or likely pathogenic variants in three RS related genes: DVL1, ROR2, and NXN. One subject was found to have a nonsense variant (c.817C > T [p.Gln273*]) in NXN in trans with an ~1 Mb telomeric deletion on chromosome 17p containing NXN, which supports our contention that biallelic NXN variant alleles are responsible for a novel autosomal recessive RS locus. These findings provide increased understanding of the role of WNT signaling in skeletal development and maintenance. These data further support the hypothesis that dysregulation of the noncanonical WNT pathway in humans gives rise to RS.
Keywords: Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exome Sequencing; Female; Genes, Dominant; Genes, Recessive; Genetic Heterogeneity; Genetic Predisposition to Disease; Genomic Structural Variation; Humans; Limb Deformities, Congenital; Male; Oxidoreductases; Receptor Tyrosine Kinase-like Orphan Receptors; Urogenital Abnormalities; Whole Genome Sequencing; Wnt Signaling Pathway

A novel statistical method for interpreting the pathogenicity of rare variants. - Wang, Jun; Liu, Hehe; Bertrand, Renae Elaine; Sarrion-Perdigones, Alejandro; Gonzalez, Yezabel; Venken, Koen J T; Rui Chen (Genet Med, 2021)
PURPOSE: To achieve the ultimate goal of personalized treatment of patients, accurate molecular diagnosis and precise interpretation of the impact of genetic variants on gene function is essential. With sequencing cost becoming increasingly affordable, the accurate distinguishing of benign from pathogenic variants becomes the major bottleneck. Although large normal population sequence databases have become a key resource in filtering benign variants, they are not effective at filtering extremely rare variants. METHODS: To address this challenge, we developed a novel statistical test by combining sequencing data from a patient cohort with a normal control population database. By comparing the expected and observed allele frequency in the patient cohort, variants that are likely benign can be identified. RESULTS: The performance of this new method is evaluated on both simulated and real data sets coupled with experimental validation. As a result, we demonstrate this new test is well powered to identify benign variants, and is particularly effective for variants with low frequency in the normal population. CONCLUSION: Overall, as a general test that can be applied to any type of variants in the context of all Mendelian diseases, our work provides a general framework for filtering benign variants with very low population allele frequency.
Keywords: Alleles; Databases, Genetic; Gene Frequency; Genetic Variation; Humans; Virulence

Oligonucleotide capture sequencing of the SARS-CoV-2 genome and subgenomic fragments from COVID-19 individuals. - Harshavardhan Doddapaneni; Cregeen, Sara Javornik; Sucgang, Richard; Meng, Qingchang; Xiang Qin; Avadhanula, Vasanthi; Chao, Hsu; Menon, Vipin; Nicholson, Erin; Henke, David; Piedra, Felipe-Andres; Rajan, Anubama; et al. (PLoS One, 2021)
The newly emerged and rapidly spreading SARS-CoV-2 causes coronavirus disease 2019 (COVID-19). To facilitate a deeper understanding of the viral biology we developed a capture sequencing methodology to generate SARS-CoV-2 genomic and transcriptome sequences from infected patients. We utilized an oligonucleotide probe-set representing the full-length genome to obtain both genomic and transcriptome (subgenomic open reading frames [ORFs]) sequences from 45 SARS-CoV-2 clinical samples with varying viral titers. For samples with higher viral loads (cycle threshold value under 33, based on the CDC qPCR assay) complete genomes were generated. Analysis of junction reads revealed regions of differential transcriptional activity among samples. Mixed allelic frequencies along the 20kb ORF1ab gene in one sample, suggested the presence of a defective viral RNA species subpopulation maintained in mixture with functional RNA in one sample. The associated workflow is straightforward, and hybridization-based capture offers an effective and scalable approach for sequencing SARS-CoV-2 from patient samples.
Keywords: COVID-19; DNA, Complementary; Gene Frequency; Genetic Variation; Genome, Viral; Humans; Open Reading Frames; Real-Time Polymerase Chain Reaction; RNA, Viral; SARS-CoV-2; Sequence Analysis, DNA; Viral Load

Origins and Long-Term Patterns of Copy-Number Variation in Rhesus Macaques. - Thomas, Gregg W C; Wang, Richard J; Nguyen, Jelena; R. Alan Harris; Raveendran, Muthuswamy; Jeffrey Rogers; Hahn, Matthew W (Mol Biol Evol, 2021)
Mutations play a key role in the development of disease in an individual and the evolution of traits within species. Recent work in humans and other primates has clarified the origins and patterns of single-nucleotide variants, showing that most arise in the father's germline during spermatogenesis. It remains unknown whether larger mutations, such as deletions and duplications of hundreds or thousands of nucleotides, follow similar patterns. Such mutations lead to copy-number variation (CNV) within and between species, and can have profound effects by deleting or duplicating genes. Here, we analyze patterns of CNV mutations in 32 rhesus macaque individuals from 14 parent-offspring trios. We find the rate of CNV mutations per generation is low (less than one per genome) and we observe no correlation between parental age and the number of CNVs that are passed on to offspring. We also examine segregating CNVs within the rhesus macaque sample and compare them to a similar data set from humans, finding that both species have far more segregating deletions than duplications. We contrast this with long-term patterns of gene copy-number evolution between 17 mammals, where the proportion of deletions that become fixed along the macaque lineage is much smaller than the proportion of segregating deletions. These results suggest purifying selection acting on deletions, such that the majority of them are removed from the population over time. Rhesus macaques are an important biomedical model organism, so these results will aid in our understanding of this species and the disease models it supports.
Keywords: Animals; DNA Copy Number Variations; Female; Gene Duplication; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Male; Mutation; Selection, Genetic; Sequence Deletion; Whole Genome Sequencing

Performance assessment of DNA sequencing platforms in the ABRF Next-Generation Sequencing Study. - Foox, Jonathan; Tighe, Scott W; Nicolet, Charles M; Zook, Justin M; Byrska-Bishop, Marta; Clarke, Wayne E; Khayat, Michael M; Mahmoud, Medhat; Laaguiby, Phoebe K; Herbert, Zachary T; Warner, Derek; Grills, George S; et al. (Nat Biotechnol, 2021)
Assessing the reproducibility, accuracy and utility of massively parallel DNA sequencing platforms remains an ongoing challenge. Here the Association of Biomolecular Resource Facilities (ABRF) Next-Generation Sequencing Study benchmarks the performance of a set of sequencing instruments (HiSeq/NovaSeq/paired-end 2 × 250-bp chemistry, Ion S5/Proton, PacBio circular consensus sequencing (CCS), Oxford Nanopore Technologies PromethION/MinION, BGISEQ-500/MGISEQ-2000 and GS111) on human and bacterial reference DNA samples. Among short-read instruments, HiSeq 4000 and X10 provided the most consistent, highest genome coverage, while BGI/MGISEQ provided the lowest sequencing error rates. The long-read instrument PacBio CCS had the highest reference-based mapping rate and lowest non-mapping rate. The two long-read platforms PacBio CCS and PromethION/MinION showed the best sequence mapping in repeat-rich areas and across homopolymers. NovaSeq 6000 using 2 × 250-bp read chemistry was the most robust instrument for capturing known insertion/deletion events. This study serves as a benchmark for current genomics technologies, as well as a resource to inform experimental design and next-generation sequencing variant calling.
Keywords: Base Pair Mismatch; Benchmarking; DNA; DNA, Bacterial; Genome, Bacterial; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA

PhenoDB, GeneMatcher and VariantMatcher, tools for analysis and sharing of sequence data. - Wohler, Elizabeth; Martin, Renan; Griffith, Sean; Rodrigues, Eliete da S; Antonescu, Corina; Posey, Jennifer E; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Doheny, Kimberly F; James R Lupski; Valle, David; Hamosh, Ada; et al. (Orphanet J Rare Dis, 2021)
BACKGROUND: With the advent of whole exome (ES) and genome sequencing (GS) as tools for disease gene discovery, rare variant filtering, prioritization and data sharing have become essential components of the search for disease genes and variants potentially contributing to disease phenotypes. The computational storage, data manipulation, and bioinformatic interpretation of thousands to millions of variants identified in ES and GS, respectively, is a challenging task. To aid in that endeavor, we constructed PhenoDB, GeneMatcher and VariantMatcher. RESULTS: PhenoDB is an accessible, freely available, web-based platform that allows users to store, share, analyze and interpret their patients' phenotypes and variants from ES/GS data. GeneMatcher is accessible to all stakeholders as a web-based tool developed to connect individuals (researchers, clinicians, health care providers and patients) around the globe with interest in the same gene(s), variant(s) or phenotype(s). Finally, VariantMatcher was developed to enable public sharing of variant-level data and phenotypic information from individuals sequenced as part of multiple disease gene discovery projects. Here we provide updates on PhenoDB and GeneMatcher applications and implementation and introduce VariantMatcher. CONCLUSION: Each of these tools has facilitated worldwide data sharing and data analysis and improved our ability to connect genes to phenotypic traits. Further development of these platforms will expand variant analysis, interpretation, novel disease-gene discovery and facilitate functional annotation of the human genome for clinical genomics implementation and the precision medicine initiative.
Keywords: Computational Biology; Databases, Genetic; Genomics; Humans; Phenotype; Software

Phenotypic and protein localization heterogeneity associated with AHDC1 pathogenic protein-truncating alleles in Xia-Gibbs syndrome. - Khayat, Michael M; Li, He; Chander, Varuna; Jianhong Hu; Hansen, Adam W; Li, Shoudong; Traynelis, Josh; Shen, Hua; Weissenberger, George; Stossi, Fabio; Johnson, Hannah L; James R Lupski; et al. (Hum Mutat, 2021)
Xia-Gibbs syndrome (XGS) is a rare Mendelian disease typically caused by de novo stop-gain or frameshift mutations in the AT-hook DNA binding motif containing 1 (AHDC1) gene. Patients usually present in early infancy with hypotonia and developmental delay and later exhibit intellectual disability (ID). The overall presentation is variable, however, and the emerging clinical picture is still evolving. A detailed phenotypic analysis of 34 XGS individuals revealed five core phenotypes (delayed motor milestones, speech delay, low muscle tone, ID, and hypotonia) in more than 80% of individuals and an additional 12 features that occurred more variably. Seizures and scoliosis were more frequently associated with truncations that arise before the midpoint of the protein although the occurrence of most features could not be predicted by the mutation position. Transient expression of wild type and different patient truncated AHDC1 protein forms in human cell lines revealed abnormal patterns of nuclear localization including a diffuse distribution of a short truncated form and nucleolar aggregation in mid-protein truncated forms. Overall, both the occurrence of variable phenotypes and the different distribution of the expressed protein reflect the heterogeneity of this syndrome.
Keywords: Abnormalities, Multiple; Alleles; DNA-Binding Proteins; Humans; Intellectual Disability; Mutation; Phenotype; Syndrome

Population sequencing data reveal a compendium of mutational processes in the human germ line. - Seplyarskiy, Vladimir B; Soldatov, Ruslan A; Koch, Evan; McGinty, Ryan J; Goldmann, Jakob M; Hernandez, Ryan D; Barnes, Kathleen; Correa, Adolfo; Burchard, Esteban G; Ellinor, Patrick T; McGarvey, Stephen T; Mitchell, Braxton D; et al. (Science, 2021)
Biological mechanisms underlying human germline mutations remain largely unknown. We statistically decompose variation in the rate and spectra of mutations along the genome using volume-regularized nonnegative matrix factorization. The analysis of a sequencing dataset (TOPMed) reveals nine processes that explain the variation in mutation properties between loci. We provide a biological interpretation for seven of these processes. We associate one process with bulky DNA lesions that are resolved asymmetrically with respect to transcription and replication. Two processes track direction of replication fork and replication timing, respectively. We identify a mutagenic effect of active demethylation primarily acting in regulatory regions and a mutagenic effect of long interspersed nuclear elements. We localize a mutagenic process specific to oocytes from population sequencing data. This process appears transcriptionally asymmetric.
Keywords: Algorithms; CpG Islands; DNA Damage; DNA Demethylation; DNA Mutational Analysis; DNA Replication; Genetic Variation; Genome, Human; Germ Cells; Germ-Line Mutation; Humans; Long Interspersed Nucleotide Elements; Mutagenesis; Oocytes; Transcription, Genetic

Portals for Exploring Noncoding Variants in Pediatric Cancer. - Creighton, Chad J (Trends Genet, 2021)
Zhou et al. present GenomePaint, a dynamic web-based data portal for exploring noncoding somatic alterations in cancer by genomic location. Multiple omics platforms - including whole-genome, whole-exome, transcriptome, and epigenome - can be visualized together. The portal incorporates data from >3800 pediatric tumors, and users may upload their own data.
Keywords: Databases, Genetic; Epigenome; Exome Sequencing; Genome, Human; Genomics; Humans; Internet; Mutation; Neoplasms; Pediatrics; Polymorphism, Single Nucleotide; RNA, Untranslated; Transcriptome

PRINCESS: comprehensive detection of haplotype resolved SNVs, SVs, and methylation. - Mahmoud, Medhat; Harshavardhan Doddapaneni; Timp, Winston; Fritz J Sedlazeck (Genome Biol, 2021)
Long-read sequencing has been shown to have advantages in structural variation (SV) detection and methylation calling. Many studies focus either on SV, methylation, or phasing of SNV; however, only the combination of variants provides a comprehensive insight into the sample and thus enables novel findings in biology or medicine. PRINCESS is a structured workflow that takes raw sequence reads and generates a fully phased SNV, SV, and methylation call set within a few hours. PRINCESS achieves high accuracy and long phasing even on low coverage datasets and can resolve repetitive, complex medical relevant genes that often escape detection. PRINCESS is publicly available at https://github.com/MeHelmy/princess under the MIT license.
Keywords: Charcot-Marie-Tooth Disease; DNA Methylation; Genetic Variation; Genome, Human; Haplotypes; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA; Software

Prostate adenocarcinoma and COVID-19: The possible impacts of TMPRSS2 expressions in susceptibility to SARS-CoV-2. - Cheng, Jingliang; Zhou, Ju; Fu, Shangyi; Fu, Jiewen; Zhou, Baixu; Chen, Hanchun; Fu, Junjiang; Wei, Chunli (J Cell Mol Med, 2021)
TMPRSS2 (OMIM: 602060) is a cellular protease involved in many physiological and pathological processes, and it facilitates entry of viruses such as SARS-CoV-2 into host cells. It is important to predict the prostate's susceptibility to SARS-CoV-2 infection in cancer patients and the disease outcome by assessing TMPRSS2 expression in cancer tissues. In this study, we conducted the expression profiles of the TMPRSS2 gene for COVID-19 in different normal tissues and PRAD (prostate adenocarcinoma) tumour tissues. TMPRSS2 is highly expressed in normal tissues including the small intestine, prostate, pancreas, salivary gland, colon, stomach, seminal vesicle and lung, and is increased in PRAD tissues, indicating that SARS-CoV-2 might attack not only the lungs and other normal organs, but also in PRAD cancer tissues. Hypomethylation of TMPRSS2 promoter may not be the mechanism for TMPRSS2 overexpression in PRAD tissues and PRAD pathogenesis. TMPRSS2 expresses eleven isoforms in PRAD tissues, with the TMPRSS2-001 isoform expressed highest and followed by TMPRSS2-201. Further isoform structures prediction showed that these two highly expressed isoforms have both SRCR_2 and Trypsin (Tryp_SPc) domains, which may be essential for TMPRSS2 functional roles for tumorigenesis and entry for SARS-CoV-2 in PRAD patients. Analyses of functional annotation and enrichment in TMPRSS2 showed that TMPRSS2 is mostly enriched in regulation of viral entry into host cells, protein processing and serine-type peptidase activity. TMPRSS2 is also associated with prostate gland cancer cell expression, different complex(es) formation, human influenza and carcinoma, pathways in prostate cancer, influenza A, and transcriptional misregulation in cancer. Altogether, even though high expression of TMPRSS2 may not be favourable for PRAD patient's survival, increased expression in these patients should play roles in susceptibility of the SARS-CoV-2 infection and clinical severity for COVID-19, highlighting the value of protective actions of PRAD cases by targeting or androgen-mediated therapeutic strategies in the COVID-19 pandemic.
Keywords: Adenocarcinoma; COVID-19; DNA Methylation; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Gene Ontology; Genetic Predisposition to Disease; Humans; Kaplan-Meier Estimate; Male; Promoter Regions, Genetic; Prostate; Prostatic Neoplasms; SARS-CoV-2; Serine Endopeptidases

RCL1 copy number variants are associated with a range of neuropsychiatric phenotypes. - Brownstein, Catherine A; Smith, Richard S; Rodan, Lance H; Gorman, Mark P; Hojlo, Margaret A; Garvey, Emily A; Li, Jianqiao; Cabral, Kristin; Bowen, Joshua J; Rao, Abhijit S; Genetti, Casie A; Carroll, Devon; et al. (Mol Psychiatry, 2021)
Mendelian and early-onset severe psychiatric phenotypes often involve genetic variants having a large effect, offering opportunities for genetic discoveries and early therapeutic interventions. Here, the index case is an 18-year-old boy, who at 14 years of age had a decline in cognitive functioning over the course of a year and subsequently presented with catatonia, auditory and visual hallucinations, paranoia, aggression, mood dysregulation, and disorganized thoughts. Exome sequencing revealed a stop-gain mutation in RCL1 (NM_005772.4:c.370 C > T, p.Gln124Ter), encoding an RNA 3'-terminal phosphate cyclase-like protein that is highly conserved across eukaryotic species. Subsequent investigations across two academic medical centers identified eleven additional cases of RCL1 copy number variations (CNVs) with varying neurodevelopmental or psychiatric phenotypes. These findings suggest that dosage variation of RCL1 contributes to a range of neurological and clinical phenotypes.
Keywords: Adolescent; DNA Copy Number Variations; Exome Sequencing; Humans; Male; Mutation; Phenotype

Risk of sudden cardiac death in EXOSC5-related disease. - Calame, Daniel G; Herman, Isabella; Fatih, Jawid M; Du, Haowei; Akay, Gulsen; Jhangiani, Shalini N; Coban-Akdemir, Zeynep; Milewicz, Dianna M; Richard A Gibbs; Posey, Jennifer E; Marafi, Dana; Hunter, Jill V; et al. (Am J Med Genet A, 2021)
The RNA exosome is a multi-subunit complex involved in the processing, degradation, and regulated turnover of RNA. Several subunits are linked to Mendelian disorders, including pontocerebellar hypoplasia (EXOSC3, MIM #614678; EXOSC8, MIM #616081: and EXOSC9, MIM #618065) and short stature, hearing loss, retinitis pigmentosa, and distinctive facies (EXOSC2, MIM #617763). More recently, EXOSC5 (MIM *606492) was found to underlie an autosomal recessive neurodevelopmental disorder characterized by developmental delay, hypotonia, cerebellar abnormalities, and dysmorphic facies. An unusual feature of EXOSC5-related disease is the occurrence of complete heart block requiring a pacemaker in a subset of affected individuals. Here, we provide a detailed clinical and molecular characterization of two siblings with microcephaly, developmental delay, cerebellar volume loss, hypomyelination, with cardiac conduction and rhythm abnormalities including sinus node dysfunction, intraventricular conduction delay, atrioventricular block, and ventricular tachycardia (VT) due to compound heterozygous variants in EXOSC5: (1) NM_020158.4:c.341C > T (p.Thr114Ile; pathogenic, previously reported) and (2) NM_020158.4:c.302C > A (p.Thr101Lys; novel variant). A review of the literature revealed an additional family with biallelic EXOSC5 variants and cardiac conduction abnormalities. These clinical and molecular data provide compelling evidence that cardiac conduction abnormalities and arrhythmias are part of the EXOSC5-related disease spectrum and argue for proactive screening due to potential risk of sudden cardiac death.
Keywords: Antigens, Neoplasm; Atrioventricular Block; Child; Death, Sudden, Cardiac; Echocardiography; Electrocardiography; Exosome Multienzyme Ribonuclease Complex; Facies; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Mutation; Pedigree; Phenotype; RNA-Binding Proteins; Sequence Analysis, DNA; Young Adult

Sequencing of a central nervous system tumor demonstrates cancer transmission in an organ transplant. - Marie-Claude Gingras; Aniko Sabo; Cardenas, Maria; Rana, Abbas; Dhingra, Sadhna; Meng, Qingchang; Jianhong Hu; Donna M Muzny; Harshavardhan Doddapaneni; Perez, Lesette; Korchina, Viktoriya; Nessner, Caitlin; et al. (Life Sci Alliance, 2021)
Four organ transplant recipients from an organ donor diagnosed with anaplastic pleomorphic xanthoastrocytoma developed fatal malignancies for which the origin could not be confirmed by standard methods. We identified the somatic mutational profiles of the neoplasms using next-generation sequencing technologies and tracked the relationship between the different samples. The data were consistent with the presence of an aggressive clonal entity in the donor and the subsequent proliferation of descendent tumors in each recipient. Deleterious mutations in , , , , and , and a chromosomal deletion spanning the genes, were shared between the recipients' lesions. In addition to demonstrating that DNA sequencing tracked a donor/recipient cancer transmission, this study established that the genetic profile of a donor tumor and its potential aggressive phenotype could have been determined before transplantation was considered. As the genetic correlates of tumor invasion and metastases become better known, adding genetic profiling by DNA sequencing to the data considered for transplant safety should be considered.
Keywords: Adolescent; Adult; Biomarkers, Tumor; Biopsy; Central Nervous System Neoplasms; DNA Mutational Analysis; Exome Sequencing; Female; Humans; INDEL Mutation; Male; Middle Aged; Mutation; Organ Transplantation; Prognosis; Sequence Analysis, DNA; Tissue Donors; Transplant Recipients; Transplants; Young Adult

Shotgun transcriptome, spatial omics, and isothermal profiling of SARS-CoV-2 infection reveals unique host responses, viral diversification, and drug interactions. - Butler, Daniel; Mozsary, Christopher; Meydan, Cem; Foox, Jonathan; Rosiene, Joel; Shaiber, Alon; Danko, David; Afshinnekoo, Ebrahim; MacKay, Matthew; Fritz J Sedlazeck; Ivanov, Nikolay A; Sierra, Maria; et al. (Nat Commun, 2021)
In less than nine months, the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) killed over a million people, including >25,000 in New York City (NYC) alone. The COVID-19 pandemic caused by SARS-CoV-2 highlights clinical needs to detect infection, track strain evolution, and identify biomarkers of disease course. To address these challenges, we designed a fast (30-minute) colorimetric test (LAMP) for SARS-CoV-2 infection from naso/oropharyngeal swabs and a large-scale shotgun metatranscriptomics platform (total-RNA-seq) for host, viral, and microbial profiling. We applied these methods to clinical specimens gathered from 669 patients in New York City during the first two months of the outbreak, yielding a broad molecular portrait of the emerging COVID-19 disease. We find significant enrichment of a NYC-distinctive clade of the virus (20C), as well as host responses in interferon, ACE, hematological, and olfaction pathways. In addition, we use 50,821 patient records to find that renin-angiotensin-aldosterone system inhibitors have a protective effect for severe COVID-19 outcomes, unlike similar drugs. Finally, spatial transcriptomic data from COVID-19 patient autopsy tissues reveal distinct ACE2 expression loci, with macrophage and neutrophil infiltration in the lungs. These findings can inform public health and may help develop and drive SARS-CoV-2 diagnostic, prevention, and treatment strategies.
Keywords: Adult; Aged; Angiotensin Receptor Antagonists; Angiotensin-Converting Enzyme Inhibitors; Antiviral Agents; COVID-19; COVID-19 Drug Treatment; COVID-19 Nucleic Acid Testing; Drug Interactions; Female; Gene Expression Profiling; Genome, Viral; HLA Antigens; Host Microbial Interactions; Humans; Male; Middle Aged; Molecular Diagnostic Techniques; New York City; Nucleic Acid Amplification Techniques; Pandemics; RNA-Seq; SARS-CoV-2

Stephen T. Warren: Human geneticist who advanced understanding of mutational mechanisms and developmental disorders. - Nelson, David L; Caskey, C Thomas (Proc Natl Acad Sci U S A, 2021)
Keywords: Developmental Disabilities; Genetic Diseases, Inborn; Genetics, Medical; History, 20th Century; History, 21st Century; Humans; Mutation; Physician's Role

SVExpress: identifying gene features altered recurrently in expression with nearby structural variant breakpoints. - Zhang, Yiqun; Chen, Fengju; Creighton, Chad J (BMC Bioinformatics, 2021)
BACKGROUND: Combined whole-genome sequencing (WGS) and RNA sequencing of cancers offer the opportunity to identify genes with altered expression due to genomic rearrangements. Somatic structural variants (SVs), as identified by WGS, can involve altered gene cis-regulation, gene fusions, copy number alterations, or gene disruption. The absence of computational tools to streamline integrative analysis steps may represent a barrier in identifying genes recurrently altered by genomic rearrangement. RESULTS: Here, we introduce SVExpress, a set of tools for carrying out integrative analysis of SV and gene expression data. SVExpress enables systematic cataloging of genes that consistently show increased or decreased expression in conjunction with the presence of nearby SV breakpoints. SVExpress can evaluate breakpoints in proximity to genes for potential enhancer translocation events or disruption of topologically associated domains, two mechanisms by which SVs may deregulate genes. The output from any commonly used SV calling algorithm may be easily adapted for use with SVExpress. SVExpress can readily analyze genomic datasets involving hundreds of cancer sample profiles. Here, we used SVExpress to analyze SV and expression data across 327 cancer cell lines with combined SV and expression data in the Cancer Cell Line Encyclopedia (CCLE). In the CCLE dataset, hundreds of genes showed altered gene expression in relation to nearby SV breakpoints. Altered genes involved TAD disruption, enhancer hijacking, and gene fusions. When comparing the top set of SV-altered genes from cancer cell lines with the top SV-altered genes previously reported for human tumors from The Cancer Genome Atlas and the Pan-Cancer Analysis of Whole Genomes datasets, a significant number of genes overlapped in the same direction for both cell lines and tumors, while some genes were significant for cell lines but not for human tumors and vice versa. CONCLUSION: Our SVExpress tools allow computational biologists with a working knowledge of R to integrate gene expression with SV breakpoint data to identify recurrently altered genes. SVExpress is freely available for academic or commercial use at https://github.com/chadcreighton/SVExpress . SVExpress is implemented as a set of Excel macros and R code. All source code (R and Visual Basic for Applications) is available.
Keywords: DNA Copy Number Variations; Genome; Genome, Human; Genomic Structural Variation; Genomics; Humans; Whole Genome Sequencing

TQFL12, a novel synthetic derivative of TQ, inhibits triple-negative breast cancer metastasis and invasion through activating AMPK/ACC pathway. - Wei, Chunli; Zou, Hui; Xiao, Ting; Liu, Xiaoyan; Wang, Qianqian; Cheng, Jingliang; Fu, Shangyi; Peng, Jiangzhou; Xie, Xin; Fu, Junjiang (J Cell Mol Med, 2021)
Thymoquinone (TQ) has been reported as an anti-tumour drug widely studied in various tumours, and its mechanism and effect of which has become a focus of current research. However, previous studies from our laboratory and other groups found that TQ showed weak anti-tumour effects in many cancer cell lines and animal models. Therefore, it is necessary to modify and optimize the structure of TQ to obtain new chemical entities with high efficiency and low toxicity as candidates for development of new drugs in treating cancer. Therefore, we designed and synthesized several TQ derivatives. Systematic analysis, including in vitro and in vivo, was conducted on a panel of triple-negative breast cancer (TNBC) cells and mouse model to demonstrate whether TQFL12, a new TQ derivative, is more efficient than TQ. We found that the anti-proliferative effect of TQFL12 against TNBC cells is significantly stronger than TQ. We also demonstrated TQFL12 affects different aspects in breast cancer development including cell proliferation, migration, invasion and apoptosis. Moreover, TQFL12 inhibited tumour growth and metastasis in cancer cell-derived xenograft mouse model, with less toxicity compared with TQ. Finally, mechanism research indicated that TQFL12 increased AMPK/ACC activity by stabilizing AMPKα, while molecular docking supported the direct interaction between TQFL12 and AMPKα. Taken together, our findings suggest that TQFL12, as a novel chemical entity, possesses a better inhibitory effect on TNBC cells and less toxicity in both in vitro and in vivo studies. As such, TQFL12 could serve as a potential therapeutic agent for breast cancer.
Keywords: Acetyl-CoA Carboxylase; AMP-Activated Protein Kinases; Animals; Antineoplastic Agents; Apoptosis; Benzoquinones; Cell Cycle; Cell Line, Tumor; Cell Movement; Disease Models, Animal; Drug Tapering; Humans; Mice; Models, Molecular; Protein Binding; Signal Transduction; Structure-Activity Relationship; Triple Negative Breast Neoplasms; Xenograft Model Antitumor Assays

Transcriptional Reprogramming Differentiates Active from Inactive ESR1 Fusions in Endocrine Therapy-Refractory Metastatic Breast Cancer. - Gou, Xuxu; Anurag, Meenakshi; Lei, Jonathan T; Kim, Beom-Jun; Singh, Purba; Seker, Sinem; Fandino, Diana; Han, Airi; Rehman, Saif; Jianhong Hu; Korchina, Viktoriya; Harshavardhan Doddapaneni; et al. (Cancer Res, 2021)
Genomic analysis has recently identified multiple gene translocations in estrogen receptor alpha-positive (ERα) metastatic breast cancer (MBC) that encode chimeric proteins whereby the ESR1 ligand binding domain (LBD) is replaced by C-terminal sequences from many different gene partners. Here we functionally screened 15 ESR1 fusions and identified 10 that promoted estradiol-independent cell growth, motility, invasion, epithelial-to-mesenchymal transition, and resistance to fulvestrant. RNA sequencing identified a gene expression pattern specific to functionally active ESR1 gene fusions that was subsequently reduced to a diagnostic 24-gene signature. This signature was further examined in 20 ERα patient-derived xenografts and in 55 ERα MBC samples. The 24-gene signature successfully identified cases harboring gene fusions and also accurately diagnosed the presence of activating LBD point mutations. Therefore, the 24-gene signature represents an efficient approach to screening samples for the presence of diverse somatic mutations and translocations that drive endocrine treatment failure in MBC. SIGNIFICANCE: This study identifies a gene signature diagnostic for functional ESR1 fusions that drive poor outcome in advanced breast cancer, which could also help guide precision medicine approaches in patients harboring mutations.
Keywords: Animals; Antineoplastic Agents, Hormonal; Apoptosis; Biomarkers, Tumor; Breast Neoplasms; Cell Proliferation; Drug Resistance, Neoplasm; Estrogen Receptor alpha; Female; Gene Expression Regulation, Neoplastic; Humans; Mice; Mice, Nude; Mutation; Oncogene Proteins, Fusion; Prognosis; Survival Rate; Transcriptome; Tumor Cells, Cultured; Xenograft Model Antitumor Assays

Accumulation of Molecular Aberrations Distinctive to Hepatocellular Carcinoma Progression. - Midorikawa, Yutaka; Yamamoto, Shogo; Tatsuno, Kenji; Renard-Guillet, Claire; Tsuji, Shingo; Hayashi, Akimasa; Ueda, Hiroki; Fukuda, Shiro; Fujita, Takanori; Katoh, Hiroto; Ishikawa, Shumpei; Covington, Kyle R; et al. (Cancer Res, 2020)
Cancer develops through the accumulation of genetic and epigenetic aberrations. To identify sequential molecular alterations that occur during the development of hepatocellular carcinoma (HCC), we compared 52 early and 108 overt HCC samples by genome sequencing. Gene mutations in the p53/RB1 pathway, WNT pathway, MLL protein family, SWI/SNF complexes, and AKT/PI3K pathway were common in HCC. In the early phase of all entities, was the most frequently upregulated gene owing to diverse mechanisms. Despite frequent somatic mutations in driver genes, including and , early HCC was a separate molecular entity from overt HCC, as each had a distinct expression profile. Notably, WNT target genes were not activated in early HCC regardless of mutation status because β-catenin did not translocate into the nucleus due to the E-cadherin/β-catenin complex at the membrane. Conversely, WNT targets were definitively upregulated in overt HCC, with mutation associated with downregulation of and hypomethylation of CpG islands in target genes. Similarly, cell-cycle genes downstream of the p53/RB pathway were upregulated only in overt HCC, with or gene mutations associated with chromosomal deletion of 4q or 16q. HCC was epigenetically distinguished into four subclasses: normal-like methylation, global-hypomethylation (favorable prognosis), stem-like methylation (poor prognosis), and CpG island methylation. These methylation statuses were globally maintained through HCC progression. Collectively, these data show that as HCC progresses, additional molecular events exclusive of driver gene mutations cooperatively contribute to transcriptional activation of downstream targets according to methylation status. SIGNIFICANCE: In addition to driver gene mutations in the WNT and p53 pathways, further molecular events are required for aberrant transcriptional activation of these pathways as HCC progresses.
Keywords: beta Catenin; Carcinoma, Hepatocellular; Disease Progression; DNA Methylation; DNA, Neoplasm; Epigenesis, Genetic; Gene Dosage; Gene Drive Technology; Gene Expression; Genes, cdc; Genes, p53; Histone-Lysine N-Methyltransferase; Humans; Liver Neoplasms; Mutation; Myeloid-Lymphoid Leukemia Protein; Oncogene Protein v-akt; Phosphatidylinositol 3-Kinases; Probability; Reverse Transcriptase Polymerase Chain Reaction; RNA, Neoplasm; Sequence Analysis, DNA; Telomerase; Transcriptional Activation; Up-Regulation; Wnt Proteins

Analyses of non-coding somatic drivers in 2,658 cancer whole genomes. - Rheinbay, Esther; Nielsen, Morten Muhlig; Abascal, Federico; Wala, Jeremiah A; Shapira, Ofer; Tiao, Grace; Hornshøj, Henrik; Hess, Julian M; Juul, Randi Istrup; Lin, Ziao; Feuerbach, Lars; Sabarinathan, Radhakrishnan; et al. (Nature, 2020)
The discovery of drivers of cancer has traditionally focused on protein-coding genes. Here we present analyses of driver point mutations and structural variants in non-coding regions across 2,658 genomes from the Pan-Cancer Analysis of Whole Genomes (PCAWG) Consortium of the International Cancer Genome Consortium (ICGC) and The Cancer Genome Atlas (TCGA). For point mutations, we developed a statistically rigorous strategy for combining significance levels from multiple methods of driver discovery that overcomes the limitations of individual methods. For structural variants, we present two methods of driver discovery, and identify regions that are significantly affected by recurrent breakpoints and recurrent somatic juxtapositions. Our analyses confirm previously reported drivers, raise doubts about others and identify novel candidates, including point mutations in the 5' region of TP53, in the 3' untranslated regions of NFKBIZ and TOB1, focal deletions in BRD4 and rearrangements in the loci of AKR1C genes. We show that although point mutations and structural variants that drive cancer are less frequent in non-coding genes and regulatory sequences than in protein-coding genes, additional examples of these drivers will be found as more cancer genomes become available.
Keywords: Databases, Genetic; DNA Breaks; Gene Expression Regulation, Neoplastic; Genome, Human; Genome-Wide Association Study; Humans; INDEL Mutation; Mutation; Neoplasms

BICRA, a SWI/SNF Complex Member, Is Associated with BAF-Disorder Related Phenotypes in Humans and Model Organisms. - Barish, Scott; Barakat, Tahsin Stefan; Michel, Brittany C; Mashtalir, Nazar; Phillips, Jennifer B; Valencia, Alfredo M; Ugur, Berrak; Wegner, Jeremy; Scott, Tiana M; Bostwick, Brett; David R Murdock; Dai, Hongzheng; et al. (Am J Hum Genet, 2020)
SWI/SNF-related intellectual disability disorders (SSRIDDs) are rare neurodevelopmental disorders characterized by developmental disability, coarse facial features, and fifth digit/nail hypoplasia that are caused by pathogenic variants in genes that encode for members of the SWI/SNF (or BAF) family of chromatin remodeling complexes. We have identified 12 individuals with rare variants (10 loss-of-function, 2 missense) in the BICRA (BRD4 interacting chromatin remodeling complex-associated protein) gene, also known as GLTSCR1, which encodes a subunit of the non-canonical BAF (ncBAF) complex. These individuals exhibited neurodevelopmental phenotypes that include developmental delay, intellectual disability, autism spectrum disorder, and behavioral abnormalities as well as dysmorphic features. Notably, the majority of individuals lack the fifth digit/nail hypoplasia phenotype, a hallmark of most SSRIDDs. To confirm the role of BICRA in the development of these phenotypes, we performed functional characterization of the zebrafish and Drosophila orthologs of BICRA. In zebrafish, a mutation of bicra that mimics one of the loss-of-function variants leads to craniofacial defects possibly akin to the dysmorphic facial features seen in individuals harboring putatively pathogenic BICRA variants. We further show that Bicra physically binds to other non-canonical ncBAF complex members, including the BRD9/7 ortholog, CG7154, and is the defining member of the ncBAF complex in flies. Like other SWI/SNF complex members, loss of Bicra function in flies acts as a dominant enhancer of position effect variegation but in a more context-specific manner. We conclude that haploinsufficiency of BICRA leads to a unique SSRIDD in humans whose phenotypes overlap with those previously reported.
Keywords: Adolescent; Animals; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Developmental Disabilities; Drosophila melanogaster; Drosophila Proteins; Female; Genes, Dominant; Genetic Variation; Haploinsufficiency; Humans; Infant; Male; Microscopy, Confocal; Mutation, Missense; Neuroglia; Neurons; Phenotype; Protein Binding; Tumor Suppressor Proteins; Zebrafish; Zebrafish Proteins

Clinical genomics and contextualizing genome variation in the diagnostic laboratory. - James R Lupski; Liu, Pengfei; Stankiewicz, Pawel; Carvalho, Claudia M B; Posey, Jennifer E (Expert Rev Mol Diagn, 2020)
INTRODUCTION: The human genome contains the instructions for the development and biological homeostasis of the human organism and the genetic transmission of traits. Genome variation in human populations is the basis of evolution; individual or personal genomes vary tremendously, making each of us truly unique. AREAS COVERED: Assaying this individual variation using genomic technologies has many applications in clinical medicine, from elucidating the biology of disease to designing strategies to ameliorate perturbations from homeostasis. Detecting pathogenic rare variation in a genome may provide a molecular diagnosis that can be informative for patient management and family healthcare. EXPERT OPINION: Despite the increasing clinical use of unbiased genomic testing, including chromosome microarray analysis (CMA) with array comparative genomic hybridization (aCGH) or SNP arrays, clinical exome sequencing (cES), and whole-genome sequencing (WGS), to survey genome-wide for molecular aberrations, clinical acumen paired with an understanding of the limitations of each testing type will be needed to achieve molecular diagnoses. Potential opportunities for improving case solved rates, functionally annotating the majority of genes in the human genome, and further understanding genetic contributions to disease will empower clinical genomics and the precision medicine initiative.
Keywords: Clinical Laboratory Techniques; Computational Biology; DNA Copy Number Variations; Gene Dosage; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Testing; Genetic Variation; Genome, Human; Genomics; Humans; Molecular Sequence Annotation; Mutation; Phenotype; Rare Diseases

CNVs cause autosomal recessive genetic diseases with or without involvement of SNV/indels. - Bo Yuan; Wang, Lei; Liu, Pengfei; Shaw, Chad; Dai, Hongzheng; Cooper, Lance; Zhu, Wenmiao; Anderson, Stephanie A; Meng, Linyan; Wang, Xia; Wang, Yue; Xia, Fan; et al. (Genet Med, 2020)
PURPOSE: Improved resolution of molecular diagnostic technologies enabled detection of smaller sized exonic level copy-number variants (CNVs). The contribution of CNVs to autosomal recessive (AR) conditions may be better recognized using a large clinical cohort. METHODS: We retrospectively investigated the CNVs' contribution to AR conditions in cases subjected to chromosomal microarray analysis (CMA, N = ~70,000) and/or clinical exome sequencing (ES, N = ~12,000) at Baylor Genetics; most had pediatric onset neurodevelopmental disorders. RESULTS: CNVs contributed to biallelic variations in 87 cases, including 81 singletons and three affected sibling pairs. Seventy cases had CNVs affecting both alleles, and 17 had a CNV and a single-nucleotide variant (SNV)/indel in trans. In total, 94.3% of AR-CNVs affected one gene; among these 41.4% were single-exon and 35.0% were multiexon partial-gene events. Sixty-nine percent of homozygous AR-CNVs were embedded in homozygous genomic intervals. Five cases had large deletions unmasking an SNV/indel on the intact allele for a recessive condition, resulting in multiple molecular diagnoses. CONCLUSIONS: AR-CNVs are often smaller in size, transmitted through generations, and underrecognized due to limitations in clinical CNV detection methods. Our findings from a large clinical cohort emphasized integrated CNV and SNV/indel analyses for precise clinical and molecular diagnosis especially in the context of genomic disorders.
Keywords: Child; DNA Copy Number Variations; Exome Sequencing; Exons; Humans; INDEL Mutation; Retrospective Studies

Comparison of Methods To Collect Fecal Samples for Microbiome Studies Using Whole-Genome Shotgun Metagenomic Sequencing. - Byrd, Doratha A; Sinha, Rashmi; Hoffman, Kristi L; Chen, Jun; Hua, Xing; Shi, Jianxin; Chia, Nicholas; Petrosino, Joseph; Vogtmann, Emily (mSphere, 2020)
Few previous studies have assessed stability and "gold-standard" concordance of fecal sample collection methods for whole-genome shotgun metagenomic sequencing (WGSS), an increasingly popular method for studying the gut microbiome. We used WGSS data to investigate ambient temperature stability and putative gold-standard concordance of microbial profiles in fecal samples collected and stored using fecal occult blood test (FOBT) cards, fecal immunochemical test (FIT) tubes, 95% ethanol, or RNAlater. Among 15 Mayo Clinic employees, for each collection method, we calculated intraclass correlation coefficients (ICCs) to estimate stability of fecal microbial profiles after storage for 4 days at ambient temperature and concordance with immediately frozen, no-solution samples (i.e., the putative gold standard). ICCs were estimated for multiple metrics, including relative abundances of select phyla, species, KEGG k-genes (representing any coding sequence that had >70% identity and >70% query coverage with respect to a known KEGG ortholog), KEGG modules, and KEGG pathways; species and k-gene alpha diversity; and Bray-Curtis and Jaccard species beta diversity. ICCs for microbial profile stability were excellent (≥90%) for fecal samples collected via most of the collection methods, except those preserved in 95% ethanol. Concordance with the immediately frozen, no-solution samples varied for all collection methods, but the number of observed species and the beta diversity metrics tended to have higher concordance than other metrics. Our findings, taken together with previous studies and feasibility considerations, indicated that FOBT cards, FIT tubes, and RNAlater are acceptable choices for fecal sample collection methods in future WGSS studies. A major direction for future microbiome research is implementation of fecal sample collections in large-scale, prospective epidemiologic studies. Studying microbiome-disease associations likely requires microbial data to be pooled from multiple studies. Our findings suggest collection methods that are most optimal to be used standardly across future WGSS microbiome studies.
Keywords: Adult; DNA, Bacterial; Ethanol; Feces; Female; Freezing; Gastrointestinal Microbiome; Healthy Volunteers; Humans; Male; Metagenome; Metagenomics; Middle Aged; Preservation, Biological; RNA, Ribosomal, 16S; Specimen Handling; Temperature; Whole Genome Sequencing

Complex mosaic structural variations in human fetal brains. - Sekar, Shobana; Tomasini, Livia; Proukakis, Christos; Bae, Taejeong; Manlove, Logan; Jang, Yeongjun; Scuderi, Soraya; Zhou, Bo; Kalyva, Maria; Amiri, Anahita; Mariani, Jessica; Fritz J Sedlazeck; et al. (Genome Res, 2020)
Somatic mosaicism, manifesting as single nucleotide variants (SNVs), mobile element insertions, and structural changes in the DNA, is a common phenomenon in human brain cells, with potential functional consequences. Using a clonal approach, we previously detected 200-400 mosaic SNVs per cell in three human fetal brains (15-21 wk postconception). However, structural variation in the human fetal brain has not yet been investigated. Here, we discover and validate four mosaic structural variants (SVs) in the same brains and resolve their precise breakpoints. The SVs were of kilobase scale and complex, consisting of deletion(s) and rearranged genomic fragments, which sometimes originated from different chromosomes. Sequences at the breakpoints of these rearrangements had microhomologies, suggesting their origin from replication errors. One SV was found in two clones, and we timed its origin to ∼14 wk postconception. No large scale mosaic copy number variants (CNVs) were detectable in normal fetal human brains, suggesting that previously reported megabase-scale CNVs in neurons arise at later stages of development. By reanalysis of public single nuclei data from adult brain neurons, we detected an extrachromosomal circular DNA event. Our study reveals the existence of mosaic SVs in the developing human brain, likely arising from cell proliferation during mid-neurogenesis. Although relatively rare compared to SNVs and present in ∼10% of neurons, SVs in developing human brain affect a comparable number of bases in the genome (∼6200 vs. ∼4000 bp), implying that they may have similar functional consequences.
Keywords: Brain; Clonal Evolution; DNA, Circular; Female; Genomic Structural Variation; Genotyping Techniques; Gestational Age; Humans; Mosaicism; Neurogenesis; Pregnancy; Sequence Analysis, DNA

Comprehensive analysis of structural variants in breast cancer genomes using single-molecule sequencing. - Aganezov, Sergey; Goodwin, Sara; Sherman, Rachel M; Fritz J Sedlazeck; Arun, Gayatri; Bhatia, Sonam; Lee, Isac; Kirsche, Melanie; Wappel, Robert; Kramer, Melissa; Kostroff, Karen; Spector, David L; et al. (Genome Res, 2020)
Improved identification of structural variants (SVs) in cancer can lead to more targeted and effective treatment options as well as advance our basic understanding of the disease and its progression. We performed whole-genome sequencing of the SKBR3 breast cancer cell line and patient-derived tumor and normal organoids from two breast cancer patients using Illumina/10x Genomics, Pacific Biosciences (PacBio), and Oxford Nanopore Technologies (ONT) sequencing. We then inferred SVs and large-scale allele-specific copy number variants (CNVs) using an ensemble of methods. Our findings show that long-read sequencing allows for substantially more accurate and sensitive SV detection, with between 90% and 95% of variants supported by each long-read technology also supported by the other. We also report high accuracy for long reads even at relatively low coverage (25×-30×). Furthermore, we integrated SV and CNV data into a unifying karyotype-graph structure to present a more accurate representation of the mutated cancer genomes. We find hundreds of variants within known cancer-related genes detectable only through long-read sequencing. These findings highlight the need for long-read sequencing of cancer genomes for the precise analysis of their genetic instability.
Keywords: Breast Neoplasms; Cell Line, Tumor; DNA Copy Number Variations; DNA Methylation; DNA, Neoplasm; Female; Genomic Structural Variation; Humans; Nanopores; Organoids; RNA-Seq; Whole Genome Sequencing

Copy number variants and fixed duplications among 198 rhesus macaques (Macaca mulatta). - Brasó-Vives, Marina; Povolotskaya, Inna S; Hartasánchez, Diego A; Farré, Xavier; Fernandez-Callejo, Marcos; Raveendran, Muthuswamy; R. Alan Harris; Rosene, Douglas L; Lorente-Galdos, Belen; Navarro, Arcadi; Marques-Bonet, Tomas; Jeffrey Rogers; et al. (PLoS Genet, 2020)
The rhesus macaque is an abundant species of Old World monkeys and a valuable model organism for biomedical research due to its close phylogenetic relationship to humans. Copy number variation is one of the main sources of genomic diversity within and between species and a widely recognized cause of inter-individual differences in disease risk. However, copy number differences among rhesus macaques and between the human and macaque genomes, as well as the relevance of this diversity to research involving this nonhuman primate, remain understudied. Here we present a high-resolution map of sequence copy number for the rhesus macaque genome constructed from a dataset of 198 individuals. Our results show that about one-eighth of the rhesus macaque reference genome is composed of recently duplicated regions, either copy number variable regions or fixed duplications. Comparison with human genomic copy number maps based on previously published data shows that, despite overall similarities in the genome-wide distribution of these regions, there are specific differences at the chromosome level. Some of these create differences in the copy number profile between human disease genes and their rhesus macaque orthologs. Our results highlight the importance of addressing the number of copies of target genes in the design of experiments and cautions against human-centered assumptions in research conducted with model organisms. Overall, we present a genome-wide copy number map from a large sample of rhesus macaque individuals representing an important novel contribution concerning the evolution of copy number in primate genomes.
Keywords: Animals; Chromosome Mapping; DNA Copy Number Variations; Female; Gene Duplication; Genetics, Population; Genome; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Male; Open Reading Frames; Phylogeny; Sequence Analysis, DNA; Species Specificity

Critical Role of Cytosolic DNA and Its Sensing Adaptor STING in Aortic Degeneration, Dissection, and Rupture. - Luo, Wei; Wang, Yidan; Zhang, Lin; Ren, Pingping; Zhang, Chen; Li, Yanming; Azares, Alon R; Zhang, Michelle; Guo, Jiao; Ghaghada, Ketan B; Starosolski, Zbigniew A; Rajapakshe, Kimal; et al. (Circulation, 2020)
BACKGROUND: Sporadic aortic aneurysm and dissection (AAD), caused by progressive aortic smooth muscle cell (SMC) loss and extracellular matrix degradation, is a highly lethal condition. Identifying mechanisms that drive aortic degeneration is a crucial step in developing an effective pharmacologic treatment to prevent disease progression. Recent evidence has indicated that cytosolic DNA and abnormal activation of the cytosolic DNA sensing adaptor STING (stimulator of interferon genes) play a critical role in vascular inflammation and destruction. Here, we examined the involvement of this mechanism in aortic degeneration and sporadic AAD formation. METHODS: The presence of cytosolic DNA in aortic cells and activation of the STING pathway were examined in aortic tissues from patients with sporadic ascending thoracic AAD. The role of STING in AAD development was evaluated in -deficient () mice in a sporadic AAD model induced by challenging mice with a combination of a high-fat diet and angiotensin II. We also examined the direct effects of STING on SMC death and macrophage activation in vitro. RESULTS: In human sporadic AAD tissues, we observed the presence of cytosolic DNA in SMCs and macrophages and significant activation of the STING pathway. In the sporadic AAD model, mice showed significant reductions in challenge-induced aortic enlargement, dissection, and rupture in both the thoracic and abdominal aortic regions. Single-cell transcriptome analysis revealed that aortic challenge in wild-type mice induced the DNA damage response, the inflammatory response, dedifferentiation and cell death in SMCs, and matrix metalloproteinase expression in macrophages. These changes were attenuated in challenged mice. Mechanistically, nuclear and mitochondrial DNA damage in SMCs and the subsequent leak of DNA to the cytosol activated STING signaling, which induced cell death through apoptosis and necroptosis. In addition, DNA from damaged SMCs was engulfed by macrophages in which it activated STING and its target interferon regulatory factor 3, which directly induced matrix metalloproteinase-9 expression. We also found that pharmacologically inhibiting STING activation partially prevented AAD development. CONCLUSIONS: Our findings indicate that the presence of cytosolic DNA and subsequent activation of cytosolic DNA sensing adaptor STING signaling represent a key mechanism in aortic degeneration and that targeting STING may prevent sporadic AAD development.
Keywords: Animals; Aortic Dissection; Aortic Rupture; Cytosol; DNA; Female; Male; Membrane Proteins; Mice; Mice, Knockout; Signal Transduction

Cytogenetically visible inversions are formed by multiple molecular mechanisms. - Pettersson, Maria; Grochowski, Christopher M; Wincent, Josephine; Eisfeldt, Jesper; Breman, Amy M; Cheung, Sau W; Krepischi, Ana C V; Rosenberg, Carla; James R Lupski; Ottosson, Jesper; Lovmar, Lovisa; Gacic, Jelena; et al. (Hum Mutat, 2020)
Cytogenetically detected inversions are generally assumed to be copy number and phenotypically neutral events. While nonallelic homologous recombination is thought to play a major role, recent data suggest the involvement of other molecular mechanisms in inversion formation. Using a combination of short-read whole-genome sequencing (WGS), 10X Genomics Chromium WGS, droplet digital polymerase chain reaction and array comparative genomic hybridization we investigated the genomic structure of 18 large unique cytogenetically detected chromosomal inversions and achieved nucleotide resolution of at least one chromosomal inversion junction for 13/18 (72%). Surprisingly, we observed that seemingly copy number neutral inversions can be accompanied by a copy-number gain of up to 350 kb and local genomic complexities (3/18, 17%). In the resolved inversions, the mutational signatures are consistent with nonhomologous end-joining (8/13, 62%) or microhomology-mediated break-induced replication (5/13, 38%). Our study indicates that short-read 30x coverage WGS can detect a substantial fraction of chromosomal inversions. Moreover, replication-based mechanisms are responsible for approximately 38% of those events leading to a significant proportion of inversions that are actually accompanied by additional copy-number variation potentially contributing to the overall phenotypic presentation of those patients.
Keywords: Chromosome Inversion; Comparative Genomic Hybridization; DNA End-Joining Repair; DNA Repair; Female; Gene Frequency; Haplotypes; Heterozygote; Homologous Recombination; Humans; Karyotyping; Male; Pedigree; Whole Genome Sequencing

Deficiencies in vesicular transport mediated by TRAPPC4 are associated with severe syndromic intellectual disability. - Van Bergen, Nicole J; Guo, Yiran; Al-Deri, Noraldin; Lipatova, Zhanna; Stanga, Daniela; Zhao, Sarah; Murtazina, Rakhilya; Gyurkovska, Valeriya; Pehlivan, Davut; Mitani, Tadahiro; Gezdirici, Alper; Antony, Jayne; et al. (Brain, 2020)
The conserved transport protein particle (TRAPP) complexes regulate key trafficking events and are required for autophagy. TRAPPC4, like its yeast Trs23 orthologue, is a core component of the TRAPP complexes and one of the essential subunits for guanine nucleotide exchange factor activity for Rab1 GTPase. Pathogenic variants in specific TRAPP subunits are associated with neurological disorders. We undertook exome sequencing in three unrelated families of Caucasian, Turkish and French-Canadian ethnicities with seven affected children that showed features of early-onset seizures, developmental delay, microcephaly, sensorineural deafness, spastic quadriparesis and progressive cortical and cerebellar atrophy in an effort to determine the genetic aetiology underlying neurodevelopmental disorders. All seven affected subjects shared the same identical rare, homozygous, potentially pathogenic variant in a non-canonical, well-conserved splice site within TRAPPC4 (hg19:chr11:g.118890966A>G; TRAPPC4: NM_016146.5; c.454+3A>G). Single nucleotide polymorphism array analysis revealed there was no haplotype shared between the tested Turkish and Caucasian families suggestive of a variant hotspot region rather than a founder effect. In silico analysis predicted the variant to cause aberrant splicing. Consistent with this, experimental evidence showed both a reduction in full-length transcript levels and an increase in levels of a shorter transcript missing exon 3, suggestive of an incompletely penetrant splice defect. TRAPPC4 protein levels were significantly reduced whilst levels of other TRAPP complex subunits remained unaffected. Native polyacrylamide gel electrophoresis and size exclusion chromatography demonstrated a defect in TRAPP complex assembly and/or stability. Intracellular trafficking through the Golgi using the marker protein VSVG-GFP-ts045 demonstrated significantly delayed entry into and exit from the Golgi in fibroblasts derived from one of the affected subjects. Lentiviral expression of wild-type TRAPPC4 in these fibroblasts restored trafficking, suggesting that the trafficking defect was due to reduced TRAPPC4 levels. Consistent with the recent association of the TRAPP complex with autophagy, we found that the fibroblasts had a basal autophagy defect and a delay in autophagic flux, possibly due to unsealed autophagosomes. These results were validated using a yeast trs23 temperature sensitive variant that exhibits constitutive and stress-induced autophagic defects at permissive temperature and a secretory defect at restrictive temperature. In summary we provide strong evidence for pathogenicity of this variant in a member of the core TRAPP subunit, TRAPPC4 that associates with vesicular trafficking and autophagy defects. This is the first report of a TRAPPC4 variant, and our findings add to the growing number of TRAPP-associated neurological disorders.
Keywords: Atrophy; Autophagy; Cerebellum; Cerebral Cortex; Child; Child, Preschool; Craniofacial Abnormalities; Deafness; Developmental Disabilities; Epilepsy; Female; Fibroblasts; Hearing Loss, Sensorineural; Humans; Infant; Infant, Newborn; Intellectual Disability; Male; Microcephaly; Microscopy, Fluorescence; Muscle Spasticity; Nerve Tissue Proteins; Neurodevelopmental Disorders; Pedigree; Quadriplegia; RNA Splice Sites; Syndrome; Vesicular Transport Proteins

A diagnostic ceiling for exome sequencing in cerebellar ataxia and related neurological disorders. - Ngo, Kathie J; Rexach, Jessica E; Lee, Hane; Petty, Lauren E; Perlman, Susan; Valera, Juliana M; Deignan, Joshua L; Mao, Yuanming; Aker, Mamdouh; Posey, Jennifer E; Jhangiani, Shalini N; Coban-Akdemir, Zeynep H; et al. (Hum Mutat, 2020)
Genetic ataxias are associated with mutations in hundreds of genes with high phenotypic overlap complicating the clinical diagnosis. Whole-exome sequencing (WES) has increased the overall diagnostic rate considerably. However, the upper limit of this method remains ill-defined, hindering efforts to address the remaining diagnostic gap. To further assess the role of rare coding variation in ataxic disorders, we reanalyzed our previously published exome cohort of 76 predominantly adult and sporadic-onset patients, expanded the total number of cases to 260, and introduced analyses for copy number variation and repeat expansion in a representative subset. For new cases (n = 184), our resulting clinically relevant detection rate remained stable at 47% with 24% classified as pathogenic. Reanalysis of the previously sequenced 76 patients modestly improved the pathogenic rate by 7%. For the combined cohort (n = 260), the total observed clinical detection rate was 52% with 25% classified as pathogenic. Published studies of similar neurological phenotypes report comparable rates. This consistency across multiple cohorts suggests that, despite continued technical and analytical advancements, an approximately 50% diagnostic rate marks a relative ceiling for current WES-based methods and a more comprehensive genome-wide assessment is needed to identify the missing causative genetic etiologies for cerebellar ataxia and related neurodegenerative diseases.
Keywords: Cerebellar Ataxia; DNA Copy Number Variations; Exome; Exome Sequencing; Genetic Association Studies; Genetic Linkage; Genetic Predisposition to Disease; Humans; Microsatellite Repeats; Nervous System Diseases

A diploid assembly-based benchmark for variants in the major histocompatibility complex. - Chin, Chen-Shan; Wagner, Justin; Zeng, Qiandong; Garrison, Erik; Garg, Shilpa; Fungtammasan, Arkarachai; Rautiainen, Mikko; Aganezov, Sergey; Kirsche, Melanie; Zarate, Samantha; Schatz, Michael C; Xiao, Chunlin; et al. (Nat Commun, 2020)
Most human genomes are characterized by aligning individual reads to the reference genome, but accurate long reads and linked reads now enable us to construct accurate, phased de novo assemblies. We focus on a medically important, highly variable, 5 million base-pair (bp) region where diploid assembly is particularly useful - the Major Histocompatibility Complex (MHC). Here, we develop a human genome benchmark derived from a diploid assembly for the openly-consented Genome in a Bottle sample HG002. We assemble a single contig for each haplotype, align them to the reference, call phased small and structural variants, and define a small variant benchmark for the MHC, covering 94% of the MHC and 22368 variants smaller than 50 bp, 49% more variants than a mapping-based benchmark. This benchmark reliably identifies errors in mapping-based callsets, and enables performance assessment in regions with much denser, complex variation than regions covered by previous benchmarks.
Keywords: Benchmarking; Cell Line; Diploidy; Genetic Variation; Genome, Human; Haplotypes; Humans; Major Histocompatibility Complex

Evaluation of mitochondrial DNA copy number estimation techniques. - Longchamps, Ryan J; Castellani, Christina A; Yang, Stephanie Y; Newcomb, Charles E; Sumpter, Jason A; Lane, John; Grove, Megan L; Guallar, Eliseo; Pankratz, Nathan; Taylor, Kent D; Rotter, Jerome I; Eric Boerwinkle; et al. (PLoS One, 2020)
Mitochondrial DNA copy number (mtDNA-CN), a measure of the number of mitochondrial genomes per cell, is a minimally invasive proxy measure for mitochondrial function and has been associated with several aging-related diseases. Although quantitative real-time PCR (qPCR) is the current gold standard method for measuring mtDNA-CN, mtDNA-CN can also be measured from genotyping microarray probe intensities and DNA sequencing read counts. To conduct a comprehensive examination on the performance of these methods, we use known mtDNA-CN correlates (age, sex, white blood cell count, Duffy locus genotype, incident cardiovascular disease) to evaluate mtDNA-CN calculated from qPCR, two microarray platforms, as well as whole genome (WGS) and whole exome sequence (WES) data across 1,085 participants from the Atherosclerosis Risk in Communities (ARIC) study and 3,489 participants from the Multi-Ethnic Study of Atherosclerosis (MESA). We observe mtDNA-CN derived from WGS data is significantly more associated with known correlates compared to all other methods (p < 0.001). Additionally, mtDNA-CN measured from WGS is on average more significantly associated with traits by 5.6 orders of magnitude and has effect size estimates 5.8 times more extreme than the current gold standard of qPCR. We further investigated the role of DNA extraction method on mtDNA-CN estimate reproducibility and found mtDNA-CN estimated from cell lysate is significantly less variable than traditional phenol-chloroform-isoamyl alcohol (p = 5.44x10-4) and silica-based column selection (p = 2.82x10-7). In conclusion, we recommend the field moves towards more accurate methods for mtDNA-CN, as well as re-analyze trait associations as more WGS data becomes available from larger initiatives such as TOPMed.
Keywords: Aged; DNA, Mitochondrial; Female; Gene Dosage; Genomics; Humans; Male; Middle Aged

Extensive Recombination Suppression and Epistatic Selection Causes Chromosome-Wide Differentiation of a Selfish Sex Chromosome in . - Fuller, Zachary L; Koury, Spencer A; Leonard, Christopher J; Young, Randee E; Ikegami, Kobe; Westlake, Jonathan; Stephen Richards; Schaeffer, Stephen W; Phadnis, Nitin (Genetics, 2020)
() chromosomes are selfish -chromosomes that distort Mendelian segregation and are commonly associated with inversions. These chromosomal rearrangements suppress recombination with Standard () -chromosomes and are hypothesized to maintain multiple alleles important for distortion in a single large haplotype. Here, we conduct a multifaceted study of the multiply inverted chromosome to understand the evolutionary history, genetic architecture, and present-day dynamics that shape this enigmatic selfish chromosome. The chromosome has three nonoverlapping inversions of the right arm of the metacentric -chromosome: basal, medial, and terminal. We find that 23 of 29 Mb of the -chromosome right arm is highly differentiated between the Standard and arrangements, including a 6.6 Mb collinear region between the medial and terminal inversions. Although crossing-over is heavily suppressed on this chromosome arm, we discover it is not completely eliminated, with measured rates indicating recombination suppression alone cannot explain patterns of differentiation or the near-perfect association of the three chromosome inversions in nature. We then demonstrate the ancient basal and medial inversions of the chromosome contain genes sufficient to cause weak distortion. In contrast, the younger terminal inversion cannot distort by itself, but contains at least one modifier gene necessary for full manifestation of strong sex chromosome distortion. By parameterizing population genetic models for chromosome-wide linkage disequilibrium with our experimental results, we infer that strong selection acts to maintain the near-perfect association of chromosome inversions in present-day populations. Based on comparative genomic analyses, direct recombination experiments, segregation distortion assays, and population genetic modeling, we conclude the combined action of suppressed recombination and strong, ongoing, epistatic selection shape the arrangement into a highly differentiated chromosome.
Keywords: Animals; Chromosome Inversion; Drosophila; Epistasis, Genetic; Evolution, Molecular; Genes, Modifier; Linkage Disequilibrium; Recombination, Genetic; Selection, Genetic; Suppression, Genetic; X Chromosome

Gene content evolution in the arthropods. - Thomas, Gregg W C; Dohmen, Elias; Hughes, Daniel S T; Murali, Shwetha C; Poelchau, Monica; Glastad, Karl; Anstead, Clare A; Ayoub, Nadia A; Batterham, Phillip; Bellair, Michelle; Binford, Greta J; Chao, Hsu; et al. (Genome Biol, 2020)
BACKGROUND: Arthropods comprise the largest and most diverse phylum on Earth and play vital roles in nearly every ecosystem. Their diversity stems in part from variations on a conserved body plan, resulting from and recorded in adaptive changes in the genome. Dissection of the genomic record of sequence change enables broad questions regarding genome evolution to be addressed, even across hyper-diverse taxa within arthropods. RESULTS: Using 76 whole genome sequences representing 21 orders spanning more than 500 million years of arthropod evolution, we document changes in gene and protein domain content and provide temporal and phylogenetic context for interpreting these innovations. We identify many novel gene families that arose early in the evolution of arthropods and during the diversification of insects into modern orders. We reveal unexpected variation in patterns of DNA methylation across arthropods and examples of gene family and protein domain evolution coincident with the appearance of notable phenotypic and physiological adaptations such as flight, metamorphosis, sociality, and chemoperception. CONCLUSIONS: These analyses demonstrate how large-scale comparative genomics can provide broad new insights into the genotype to phenotype map and generate testable hypotheses about the evolution of animal diversity.
Keywords: Animals; Arthropods; DNA Methylation; Evolution, Molecular; Genetic Speciation; Genetic Variation; Phylogeny

Genetics of schizophrenia in the South African Xhosa. - Gulsuner, S; Stein, D J; Susser, E S; Sibeko, G; Pretorius, A; Walsh, T; Majara, L; Mndini, M M; Mqulwana, S G; Ntola, O A; Casadei, S; Ngqengelele, L L; et al. (Science, 2020)
Africa, the ancestral home of all modern humans, is the most informative continent for understanding the human genome and its contribution to complex disease. To better understand the genetics of schizophrenia, we studied the illness in the Xhosa population of South Africa, recruiting 909 cases and 917 age-, gender-, and residence-matched controls. Individuals with schizophrenia were significantly more likely than controls to harbor private, severely damaging mutations in genes that are critical to synaptic function, including neural circuitry mediated by the neurotransmitters glutamine, γ-aminobutyric acid, and dopamine. Schizophrenia is genetically highly heterogeneous, involving severe ultrarare mutations in genes that are critical to synaptic plasticity. The depth of genetic variation in Africa revealed this relationship with a moderate sample size and informed our understanding of the genetics of schizophrenia worldwide.
Keywords: Age Factors; Autistic Disorder; Bipolar Disorder; Dopamine; Female; gamma-Aminobutyric Acid; Genetic Variation; Glutamine; Humans; Male; Mutation; Neural Pathways; Schizophrenia; Sex Factors; South Africa; Synapses; Synaptic Transmission

High-coverage whole-genome analysis of 1220 cancers reveals hundreds of genes deregulated by rearrangement-mediated cis-regulatory alterations. - Zhang, Yiqun; Chen, Fengju; Fonseca, Nuno A; He, Yao; Fujita, Masashi; Nakagawa, Hidewaki; Zhang, Zemin; Brazma, Alvis; Creighton, Chad J (Nat Commun, 2020)
The impact of somatic structural variants (SVs) on gene expression in cancer is largely unknown. Here, as part of the ICGC/TCGA Pan-Cancer Analysis of Whole Genomes (PCAWG) Consortium, which aggregated whole-genome sequencing data and RNA sequencing from a common set of 1220 cancer cases, we report hundreds of genes for which the presence within 100 kb of an SV breakpoint associates with altered expression. For the majority of these genes, expression increases rather than decreases with corresponding breakpoint events. Up-regulated cancer-associated genes impacted by this phenomenon include TERT, MDM2, CDK4, ERBB2, CD274, PDCD1LG2, and IGF2. TERT-associated breakpoints involve ~3% of cases, most frequently in liver biliary, melanoma, sarcoma, stomach, and kidney cancers. SVs associated with up-regulation of PD1 and PDL1 genes involve ~1% of non-amplified cases. For many genes, SVs are significantly associated with increased numbers or greater proximity of enhancer regulatory elements near the gene. DNA methylation near the promoter is often increased with nearby SV breakpoint, which may involve inactivation of repressor elements.
Keywords: Databases, Genetic; DNA Methylation; Enhancer Elements, Genetic; Gene Expression Regulation, Neoplastic; Genes, Tumor Suppressor; Genomic Structural Variation; Humans; Neoplasms; Oncogenes; Regulatory Sequences, Nucleic Acid; Whole Genome Sequencing

High-depth African genomes inform human migration and health. - Choudhury, Ananyo; Aron, Shaun; Botigué, Laura R; Sengupta, Dhriti; Botha, Gerrit; Bensellak, Taoufik; Wells, Gordon; Kumuthini, Judit; Shriner, Daniel; Fakim, Yasmina J; Ghoorah, Anisah W; Dareng, Eileen; et al. (Nature, 2020)
The African continent is regarded as the cradle of modern humans and African genomes contain more genetic variation than those from any other continent, yet only a fraction of the genetic diversity among African individuals has been surveyed. Here we performed whole-genome sequencing analyses of 426 individuals-comprising 50 ethnolinguistic groups, including previously unsampled populations-to explore the breadth of genomic diversity across Africa. We uncovered more than 3 million previously undescribed variants, most of which were found among individuals from newly sampled ethnolinguistic groups, as well as 62 previously unreported loci that are under strong selection, which were predominantly found in genes that are involved in viral immunity, DNA repair and metabolism. We observed complex patterns of ancestral admixture and putative-damaging and novel variation, both within and between populations, alongside evidence that Zambia was a likely intermediate site along the routes of expansion of Bantu-speaking populations. Pathogenic variants in genes that are currently characterized as medically relevant were uncommon-but in other genes, variants denoted as 'likely pathogenic' in the ClinVar database were commonly observed. Collectively, these findings refine our current understanding of continental migration, identify gene flow and the response to human disease as strong drivers of genome-level population variation, and underscore the scientific imperative for a broader characterization of the genomic diversity of African individuals to understand human ancestry and improve health.
Keywords: Africa; Datasets as Topic; DNA Repair; Female; Gene Flow; Genetic Variation; Genetics, Medical; Genetics, Population; Genome, Human; Genomics; Health; History, Ancient; Human Migration; Humans; Immunity; Language; Male; Metabolism; Selection, Genetic; Whole Genome Sequencing

Human NK cell deficiency as a result of biallelic mutations in MCM10. - Mace, Emily M; Paust, Silke; Conte, Matilde I; Baxley, Ryan M; Schmit, Megan M; Patil, Sagar L; Guilz, Nicole C; Mukherjee, Malini; Pezzi, Ashley E; Chmielowiec, Jolanta; Tatineni, Swetha; Chinn, Ivan K; et al. (J Clin Invest, 2020)
Human natural killer cell deficiency (NKD) arises from inborn errors of immunity that lead to impaired NK cell development, function, or both. Through the understanding of the biological perturbations in individuals with NKD, requirements for the generation of terminally mature functional innate effector cells can be elucidated. Here, we report a cause of NKD resulting from compound heterozygous mutations in minichromosomal maintenance complex member 10 (MCM10) that impaired NK cell maturation in a child with fatal susceptibility to CMV. MCM10 has not been previously associated with monogenic disease and plays a critical role in the activation and function of the eukaryotic DNA replisome. Through evaluation of patient primary fibroblasts, modeling patient mutations in fibroblast cell lines, and MCM10 knockdown in human NK cell lines, we have shown that loss of MCM10 function leads to impaired cell cycle progression and induction of DNA damage-response pathways. By modeling MCM10 deficiency in primary NK cell precursors, including patient-derived induced pluripotent stem cells, we further demonstrated that MCM10 is required for NK cell terminal maturation and acquisition of immunological system function. Together, these data define MCM10 as an NKD gene and provide biological insight into the requirement for the DNA replisome in human NK cell maturation and function.
Keywords: Alleles; Cell Cycle Checkpoints; Cell Differentiation; Cell Line; Codon, Nonsense; DNA Damage; Fatal Outcome; Female; Gene Knockdown Techniques; Heterozygote; Humans; Induced Pluripotent Stem Cells; Infant; Killer Cells, Natural; Male; Minichromosome Maintenance Proteins; Models, Immunological; Mutation; Mutation, Missense; Pedigree; Primary Immunodeficiency Diseases

In vivo modeling of metastatic human high-grade serous ovarian cancer in mice. - Kim, Olga; Park, Eun Young; Klinkebiel, David L; Pack, Svetlana D; Shin, Yong-Hyun; Abdullaev, Zied; Emerson, Robert E; Coffey, Donna M; Kwon, Sun Young; Creighton, Chad J; Kwon, Sanghoon; Chang, Edmund C; et al. (PLoS Genet, 2020)
Metastasis is responsible for 90% of human cancer mortality, yet it remains a challenge to model human cancer metastasis in vivo. Here we describe mouse models of high-grade serous ovarian cancer, also known as high-grade serous carcinoma (HGSC), the most common and deadliest human ovarian cancer type. Mice genetically engineered to harbor Dicer1 and Pten inactivation and mutant p53 robustly replicate the peritoneal metastases of human HGSC with complete penetrance. Arising from the fallopian tube, tumors spread to the ovary and metastasize throughout the pelvic and peritoneal cavities, invariably inducing hemorrhagic ascites. Widespread and abundant peritoneal metastases ultimately cause mouse deaths (100%). Besides the phenotypic and histopathological similarities, mouse HGSCs also display marked chromosomal instability, impaired DNA repair, and chemosensitivity. Faithfully recapitulating the clinical metastases as well as molecular and genomic features of human HGSC, this murine model will be valuable for elucidating the mechanisms underlying the development and progression of metastatic ovarian cancer and also for evaluating potential therapies.
Keywords: Animals; Antineoplastic Agents; Cell Line, Tumor; Chromosomal Instability; Cystadenocarcinoma, Serous; DEAD-box RNA Helicases; Disease Models, Animal; DNA Repair; Drug Resistance, Neoplasm; Drug Screening Assays, Antitumor; Feasibility Studies; Female; Humans; Mice; Mice, Knockout; Mutation; Neoplasm Grading; Neoplasm Metastasis; Ovarian Neoplasms; Peritoneal Neoplasms; Primary Cell Culture; PTEN Phosphohydrolase; Ribonuclease III; Tumor Suppressor Protein p53

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.
Keywords: Adult; Africa; Aged; Aged, 80 and over; alpha Karyopherins; Black People; Cell Self Renewal; Clonal Hematopoiesis; Dioxygenases; DNA-Binding Proteins; Female; Genetic Predisposition to Disease; Genome, Human; Germ-Line Mutation; Hematopoietic Stem Cells; Humans; Intracellular Signaling Peptides and Proteins; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Precision Medicine; Proto-Oncogene Proteins; Tripartite Motif Proteins; United States; Whole Genome Sequencing

Mapping the -regulatory architecture of the human retina reveals noncoding genetic variation in disease. - Cherry, Timothy J; Yang, Marty G; Harmin, David A; Tao, Peter; Timms, Andrew E; Bauwens, Miriam; Allikmets, Rando; Jones, Evan M; Rui Chen; De Baere, Elfride; Greenberg, Michael E (Proc Natl Acad Sci U S A, 2020)
The interplay of transcription factors and -regulatory elements (CREs) orchestrates the dynamic and diverse genetic programs that assemble the human central nervous system (CNS) during development and maintain its function throughout life. Genetic variation within CREs plays a central role in phenotypic variation in complex traits including the risk of developing disease. We took advantage of the retina, a well-characterized region of the CNS known to be affected by pathogenic variants in CREs, to establish a roadmap for characterizing regulatory variation in the human CNS. This comprehensive analysis of tissue-specific regulatory elements, transcription factor binding, and gene expression programs in three regions of the human visual system (retina, macula, and retinal pigment epithelium/choroid) reveals features of regulatory element evolution that shape tissue-specific gene expression programs and defines regulatory elements with the potential to contribute to Mendelian and complex disorders of human vision.
Keywords: Adult; Animals; DNA Mutational Analysis; Epigenomics; Evolution, Molecular; Female; Gene Expression Regulation, Developmental; Genetic Variation; Humans; Male; Mice; Middle Aged; Mutation; Regulatory Sequences, Nucleic Acid; Retina; Retinal Diseases; RNA-Seq; Species Specificity

Methylome-wide association study of central adiposity implicates genes involved in immune and endocrine systems. - Justice, Anne E; Chittoor, Geetha; Gondalia, Rahul; Melton, Phillip E; Lim, Elise; Grove, Megan L; Whitsel, Eric A; Liu, Ching-Ti; Cupples, L Adrienne; Fernandez-Rhodes, Lindsay; Guan, Weihua; Bressler, Jan; et al. (Epigenomics, 2020)
We conducted a methylome-wide association study to examine associations between DNA methylation in whole blood and central adiposity and body fat distribution, measured as waist circumference, waist-to-hip ratio and waist-to-height ratio adjusted for body mass index, in 2684 African-American adults in the Atherosclerosis Risk in Communities study. We validated significantly associated cytosine-phosphate-guanine methylation sites (CpGs) among adults using the Women's Health Initiative and Framingham Heart Study participants (combined n = 5743) and generalized associations in adolescents from The Raine Study (n = 820). We identified 11 CpGs that were robustly associated with one or more central adiposity trait in adults and two in adolescents, including CpG site associations near , ,  and that had not previously been associated with obesity-related traits.
Keywords: Adiposity; Cohort Studies; CpG Islands; Disease Susceptibility; DNA Methylation; Endocrine System; Epigenesis, Genetic; Epigenomics; Genome-Wide Association Study; Humans; Immune System; Obesity

Mutations in ASH1L confer susceptibility to Tourette syndrome. - Liu, Shiguo; Tian, Miaomiao; He, Fan; Li, Jiani; Xie, Hong; Liu, Wenmiao; Zhang, Yeting; Zhang, Ru; Yi, Mingji; Che, Fengyuan; Ma, Xu; Zheng, Yi; et al. (Mol Psychiatry, 2020)
Tourette syndrome (TS) is a childhood-onset neuropsychiatric disorder characterized by repetitive motor movements and vocal tics. The clinical manifestations of TS are complex and often overlap with other neuropsychiatric disorders. TS is highly heritable; however, the underlying genetic basis and molecular and neuronal mechanisms of TS remain largely unknown. We performed whole-exome sequencing of a hundred trios (probands and their parents) with detailed records of their clinical presentations and identified a risk gene, ASH1L, that was both de novo mutated and associated with TS based on a transmission disequilibrium test. As a replication, we performed follow-up targeted sequencing of ASH1L in additional 524 unrelated TS samples and replicated the association (P value = 0.001). The point mutations in ASH1L cause defects in its enzymatic activity. Therefore, we established a transgenic mouse line and performed an array of anatomical, behavioral, and functional assays to investigate ASH1L function. The Ash1l mice manifested tic-like behaviors and compulsive behaviors that could be rescued by the tic-relieving drug haloperidol. We also found that Ash1l disruption leads to hyper-activation and elevated dopamine-releasing events in the dorsal striatum, all of which could explain the neural mechanisms for the behavioral abnormalities in mice. Taken together, our results provide compelling evidence that ASH1L is a TS risk gene.
Keywords: Adolescent; Adult; Animals; Child; Child, Preschool; China; DNA-Binding Proteins; Exome Sequencing; Family; Female; Genetic Predisposition to Disease; Histone-Lysine N-Methyltransferase; Humans; Male; Mice; Mice, Transgenic; Middle Aged; Mutation; Parents; Tic Disorders; Tourette Syndrome; Transcription Factors

Nanopore sequencing and the Shasta toolkit enable efficient de novo assembly of eleven human genomes. - Shafin, Kishwar; Pesout, Trevor; Lorig-Roach, Ryan; Haukness, Marina; Olsen, Hugh E; Bosworth, Colleen; Armstrong, Joel; Tigyi, Kristof; Maurer, Nicholas; Koren, Sergey; Fritz J Sedlazeck; Marschall, Tobias; et al. (Nat Biotechnol, 2020)
De novo assembly of a human genome using nanopore long-read sequences has been reported, but it used more than 150,000 CPU hours and weeks of wall-clock time. To enable rapid human genome assembly, we present Shasta, a de novo long-read assembler, and polishing algorithms named MarginPolish and HELEN. Using a single PromethION nanopore sequencer and our toolkit, we assembled 11 highly contiguous human genomes de novo in 9 d. We achieved roughly 63× coverage, 42-kb read N50 values and 6.5× coverage in reads >100 kb using three flow cells per sample. Shasta produced a complete haploid human genome assembly in under 6 h on a single commercial compute node. MarginPolish and HELEN polished haploid assemblies to more than 99.9% identity (Phred quality score QV = 30) with nanopore reads alone. Addition of proximity-ligation sequencing enabled near chromosome-level scaffolds for all 11 genomes. We compare our assembly performance to existing methods for diploid, haploid and trio-binned human samples and report superior accuracy and speed.
Keywords: Algorithms; Benchmarking; Chromosomes, Human; Deep Learning; Genome, Human; Genomics; Haploidy; High-Throughput Nucleotide Sequencing; HLA Antigens; Humans; Nanopore Sequencing; Sequence Analysis, DNA

Next Generation Sequencing of 134 Children with Autism Spectrum Disorder and Regression. - Yin, Jiani; Chun, Chun-An; Zavadenko, Nikolay N; Pechatnikova, Natalia L; Naumova, Oxana Yu; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; Schaaf, Christian P; Grigorenko, Elena L (Genes (Basel), 2020)
Approximately 30% of individuals with autism spectrum disorder (ASD) experience developmental regression, the etiology of which remains largely unknown. We performed a complete literature search and identified 47 genes that had been implicated in such cases. We sequenced these genes in a preselected cohort of 134 individuals with regressive autism. In total, 16 variants in 12 genes with evidence supportive of pathogenicity were identified. They were classified as variants of uncertain significance based on ACMG standards and guidelines. Among these were recurring variants in and , variants in genes that were linked to syndromic forms of ASD (, , , , , and ), and variants in the form of oligogenic heterozygosity (, , and ).
Keywords: Autism Spectrum Disorder; Child; Child, Preschool; Cohort Studies; Disease Progression; Female; Gene Expression Regulation; Genetic Markers; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Infant; Male; Mutation

Parental somatic mosaicism for CNV deletions - A need for more sensitive and precise detection methods in clinical diagnostics settings. - Liu, Qian; Karolak, Justyna A; Grochowski, Christopher M; Wilson, Theresa A; Rosenfeld, Jill A; Bacino, Carlos A; Lalani, Seema R; Patel, Ankita; Breman, Amy; Smith, Janice L; Cheung, Sau Wai; James R Lupski; et al. (Genomics, 2020)
To further assess the scale and level of parental somatic mosaicism, we queried the CMA database at Baylor Genetics. We selected 50 unrelated families where clinically relevant apparent de novo CNV-deletions were found in the affected probands. Parental blood samples screening using deletion junction-specific PCR revealed four parents with somatic mosaicism. Droplet digital PCR (ddPCR), qPCR, and amplicon-based next-generation sequencing (NGS) were applied to validate these findings. Using ddPCR levels of mosaicism ranged from undetectable to 18.5%. Amplicon-based NGS and qPCR for the father with undetectable mosaicism was able to detect mosaicism at 0.39%. In one mother, ddPCR analysis revealed 15.6%, 10.6%, 8.2%, and undetectable levels of mosaicism in her blood, buccal cells, saliva, and urine samples, respectively. Our data suggest that more sensitive and precise methods, e.g. CNV junction-specific LR-PCR, ddPCR, or qPCR may allow for a more refined assessment of the potential disease recurrence risk for an identified variant.
Keywords: Clinical Laboratory Techniques; DNA Copy Number Variations; Female; High-Throughput Nucleotide Sequencing; Humans; Inheritance Patterns; Male; Mosaicism; Polymerase Chain Reaction; Sequence Analysis, DNA

Pathway and network analysis of more than 2500 whole cancer genomes. - Reyna, Matthew A; Haan, David; Paczkowska, Marta; Verbeke, Lieven P C; Vazquez, Miguel; Kahraman, Abdullah; Pulido-Tamayo, Sergio; Barenboim, Jonathan; Wadi, Lina; Dhingra, Priyanka; Shrestha, Raunak; Getz, Gad; et al. (Nat Commun, 2020)
The catalog of cancer driver mutations in protein-coding genes has greatly expanded in the past decade. However, non-coding cancer driver mutations are less well-characterized and only a handful of recurrent non-coding mutations, most notably TERT promoter mutations, have been reported. Here, as part of the ICGC/TCGA Pan-Cancer Analysis of Whole Genomes (PCAWG) Consortium, which aggregated whole genome sequencing data from 2658 cancer across 38 tumor types, we perform multi-faceted pathway and network analyses of non-coding mutations across 2583 whole cancer genomes from 27 tumor types compiled by the ICGC/TCGA PCAWG project that was motivated by the success of pathway and network analyses in prioritizing rare mutations in protein-coding genes. While few non-coding genomic elements are recurrently mutated in this cohort, we identify 93 genes harboring non-coding mutations that cluster into several modules of interacting proteins. Among these are promoter mutations associated with reduced mRNA expression in TP53, TLE4, and TCF4. We find that biological processes had variable proportions of coding and non-coding mutations, with chromatin remodeling and proliferation pathways altered primarily by coding mutations, while developmental pathways, including Wnt and Notch, altered by both coding and non-coding mutations. RNA splicing is primarily altered by non-coding mutations in this cohort, and samples containing non-coding mutations in well-known RNA splicing factors exhibit similar gene expression signatures as samples with coding mutations in these genes. These analyses contribute a new repertoire of possible cancer genes and mechanisms that are altered by non-coding mutations and offer insights into additional cancer vulnerabilities that can be investigated for potential therapeutic treatments.
Keywords: Chromatin Assembly and Disassembly; Computational Biology; Databases, Genetic; Gene Expression Regulation, Neoplastic; Genome, Human; Humans; Metabolic Networks and Pathways; Mutation; Neoplasms; Promoter Regions, Genetic; RNA Splicing

PCM1 is necessary for focal ciliary integrity and is a candidate for severe schizophrenia. - Monroe, Tanner O; Garrett, Melanie E; Kousi, Maria; Rodriguiz, Ramona M; Moon, Sungjin; Bai, Yushi; Brodar, Steven C; Soldano, Karen L; Savage, Jeremiah; Hansen, Thomas F; Donna M Muzny; Richard A Gibbs; et al. (Nat Commun, 2020)
The neuronal primary cilium and centriolar satellites have functions in neurogenesis, but little is known about their roles in the postnatal brain. We show that ablation of pericentriolar material 1 in the mouse leads to progressive ciliary, anatomical, psychomotor, and cognitive abnormalities. RNAseq reveals changes in amine- and G-protein coupled receptor pathways. The physiological relevance of this phenotype is supported by decreased available dopamine D2 receptor (D2R) levels and the failure of antipsychotic drugs to rescue adult behavioral defects. Immunoprecipitations show an association with Pcm1 and D2Rs. Finally, we sequence PCM1 in two human cohorts with severe schizophrenia. Systematic modeling of all discovered rare alleles by zebrafish in vivo complementation reveals an enrichment for pathogenic alleles. Our data emphasize a role for the pericentriolar material in the postnatal brain, with progressive degenerative ciliary and behavioral phenotypes; and they support a contributory role for PCM1 in some individuals diagnosed with schizophrenia.
Keywords: Adult; Aged; Alleles; Amines; Animals; Antipsychotic Agents; Brain; Cell Cycle Proteins; Cilia; Drug Resistance; Genetic Predisposition to Disease; Humans; Mice; Mice, Knockout; Middle Aged; Mutation; Phenotype; Receptors, Dopamine D2; Receptors, G-Protein-Coupled; Schizophrenia; Signal Transduction; Young Adult; Zebrafish

Primate phylogenomics uncovers multiple rapid radiations and ancient interspecific introgression. - Vanderpool, Dan; Minh, Bui Quang; Lanfear, Robert; Hughes, Daniel; Murali, Shwetha; R. Alan Harris; Raveendran, Muthuswamy; Donna M Muzny; Hibbins, Mark S; Williamson, Robert J; Richard A Gibbs; Kim C Worley; et al. (PLoS Biol, 2020)
Our understanding of the evolutionary history of primates is undergoing continual revision due to ongoing genome sequencing efforts. Bolstered by growing fossil evidence, these data have led to increased acceptance of once controversial hypotheses regarding phylogenetic relationships, hybridization and introgression, and the biogeographical history of primate groups. Among these findings is a pattern of recent introgression between species within all major primate groups examined to date, though little is known about introgression deeper in time. To address this and other phylogenetic questions, here, we present new reference genome assemblies for 3 Old World monkey (OWM) species: Colobus angolensis ssp. palliatus (the black and white colobus), Macaca nemestrina (southern pig-tailed macaque), and Mandrillus leucophaeus (the drill). We combine these data with 23 additional primate genomes to estimate both the species tree and individual gene trees using thousands of loci. While our species tree is largely consistent with previous phylogenetic hypotheses, the gene trees reveal high levels of genealogical discordance associated with multiple primate radiations. We use strongly asymmetric patterns of gene tree discordance around specific branches to identify multiple instances of introgression between ancestral primate lineages. In addition, we exploit recent fossil evidence to perform fossil-calibrated molecular dating analyses across the tree. Taken together, our genome-wide data help to resolve multiple contentious sets of relationships among primates, while also providing insight into the biological processes and technical artifacts that led to the disagreements in the first place.
Keywords: Animals; Biological Evolution; Cercopithecidae; Computational Biology; Databases, Genetic; Fossils; Gene Flow; Genetic Introgression; Genome; Models, Genetic; Phylogeny; Primates; Sequence Analysis, DNA

Quantitative Assessment of Parental Somatic Mosaicism for Copy-Number Variant (CNV) Deletions. - Liu, Qian; Grochowski, Christopher M; Bi, Weimin; James R Lupski; Stankiewicz, Paweł (Curr Protoc Hum Genet, 2020)
As genome sequencing methodologies have become more sensitive in detecting low-frequency rare-variant events, the link between post-zygotic mutagenesis and somatic mosaicism in the etiology of several human genetic conditions other than cancers has become more clear. Given that current clinical-genomics diagnostic methods have limited detection sensitivity for mosaic events, a copy-number variant (CNV) deletion inherited from a parent with low-level (<10%) mosaicism can be erroneously interpreted in the proband to represent a de novo germline event. Here, we describe three sensitive, precise, and cost-efficient methods that can quantitatively assess the potential degree of parental somatic mosaicism levels for CNV deletions: droplet digital PCR (ddPCR), PCR amplicon-based next-generation sequencing (NGS), and quantitative PCR. ddPCR using the EvaGreen fluorescent dye protocol can specifically quantify the deleted or non-deleted alleles by analyzing the number of droplets positive for a fluorescent signal for each event. PCR amplicon-based NGS assesses the allele frequencies of a heterozygous single-nucleotide polymorphism within a deletion region. The difference in number of reads between the two genotypes indicates the level of somatic mosaicism for the CNV deletion. Quantitative PCR can be applied where the relative quantity of the deletion junction-specific product represents the level of mosaicism. Clinical implementation of these quantitative variant-detection methods enables potentially more accurate assessment of disease recurrence risk in family-based genetic counseling, allowing couples to engage in more informed family planning. © 2020 by John Wiley & Sons, Inc. Basic Protocol: Droplet digital PCR (ddPCR) Alternate Protocol 1: PCR amplicon-based next-generation sequencing Alternate Protocol 2: Quantitative real-time PCR (qPCR).
Keywords: DNA Copy Number Variations; Genetic Diseases, Inborn; High-Throughput Nucleotide Sequencing; Humans; Mosaicism; Parents; Polymorphism, Single Nucleotide; Real-Time Polymerase Chain Reaction

Recurrent arginine substitutions in the ACTG2 gene are the primary driver of disease burden and severity in visceral myopathy. - Assia Batzir, Nurit; Kishor Bhagwat, Pranjali; Larson, Austin; Coban Akdemir, Zeynep; Bagłaj, Maciej; Bofferding, Leon; Bosanko, Katherine B; Bouassida, Skander; Callewaert, Bert; Cannon, Ashley; Enchautegui Colon, Yazmin; Garnica, Adolfo D; et al. (Hum Mutat, 2020)
Visceral myopathy with abnormal intestinal and bladder peristalsis includes a clinical spectrum with megacystis-microcolon intestinal hypoperistalsis syndrome and chronic intestinal pseudo-obstruction. The vast majority of cases are caused by dominant variants in ACTG2; however, the overall genetic architecture of visceral myopathy has not been well-characterized. We ascertained 53 families, with visceral myopathy based on megacystis, functional bladder/gastrointestinal obstruction, or microcolon. A combination of targeted ACTG2 sequencing and exome sequencing was used. We report a molecular diagnostic rate of 64% (34/53), of which 97% (33/34) is attributed to ACTG2. Strikingly, missense mutations in five conserved arginine residues involving CpG dinucleotides accounted for 49% (26/53) of disease in the cohort. As a group, the ACTG2-negative cases had a more favorable clinical outcome and more restricted disease. Within the ACTG2-positive group, poor outcomes (characterized by total parenteral nutrition dependence, death, or transplantation) were invariably due to one of the arginine missense alleles. Analysis of specific residues suggests a severity spectrum of p.Arg178>p.Arg257>p.Arg40 along with other less-frequently reported sites p.Arg63 and p.Arg211. These results provide genotype-phenotype correlation for ACTG2-related disease and demonstrate the importance of arginine missense changes in visceral myopathy.
Keywords: Abnormalities, Multiple; Actins; Adult; Amino Acid Substitution; Arginine; Colon; DNA Mutational Analysis; Exome Sequencing; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Intestinal Pseudo-Obstruction; Male; Molecular Diagnostic Techniques; Mutation; Phenotype; Urinary Bladder; Young Adult

Recurrent De Novo NAHR Reciprocal Duplications in the ATAD3 Gene Cluster Cause a Neurogenetic Trait with Perturbed Cholesterol and Mitochondrial Metabolism. - Gunning, Adam C; Strucinska, Klaudia; Muñoz Oreja, Mikel; Parrish, Andrew; Caswell, Richard; Stals, Karen L; Durigon, Romina; Durlacher-Betzer, Karina; Cunningham, Mitchell H; Grochowski, Christopher M; Baptista, Julia; Tysoe, Carolyn; et al. (Am J Hum Genet, 2020)
Recent studies have identified both recessive and dominant forms of mitochondrial disease that result from ATAD3A variants. The recessive form includes subjects with biallelic deletions mediated by non-allelic homologous recombination. We report five unrelated neonates with a lethal metabolic disorder characterized by cardiomyopathy, corneal opacities, encephalopathy, hypotonia, and seizures in whom a monoallelic reciprocal duplication at the ATAD3 locus was identified. Analysis of the breakpoint junction fragment indicated that these 67 kb heterozygous duplications were likely mediated by non-allelic homologous recombination at regions of high sequence identity in ATAD3A exon 11 and ATAD3C exon 7. At the recombinant junction, the duplication allele produces a fusion gene derived from ATAD3A and ATAD3C, the protein product of which lacks key functional residues. Analysis of fibroblasts derived from two affected individuals shows that the fusion gene product is expressed and stable. These cells display perturbed cholesterol and mitochondrial DNA organization similar to that observed for individuals with severe ATAD3A deficiency. We hypothesize that the fusion protein acts through a dominant-negative mechanism to cause this fatal mitochondrial disorder. Our data delineate a molecular diagnosis for this disorder, extend the clinical spectrum associated with structural variation at the ATAD3 locus, and identify a third mutational mechanism for ATAD3 gene cluster variants. These results further affirm structural variant mutagenesis mechanisms in sporadic disease traits, emphasize the importance of copy number analysis in molecular genomic diagnosis, and highlight some of the challenges of detecting and interpreting clinically relevant rare gene rearrangements from next-generation sequencing data.
Keywords: Amino Acid Sequence; ATPases Associated with Diverse Cellular Activities; Brain Diseases; Cardiomyopathies; Cholesterol; Corneal Opacity; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Homologous Recombination; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Diseases; Mitochondrial Proteins; Muscle Hypotonia; Mutation; Protein Conformation; Seizures; Sequence Homology

REDBot: Natural language process methods for clinical copy number variation reporting in prenatal and products of conception diagnosis. - Liu, Mengmeng; Zhong, Yunshan; Liu, Hongqian; Liang, Desheng; Liu, Erhong; Zhang, Yu; Tian, Feng; Liang, Qiaowei; Cram, David S; Wang, Hua; Wu, Lingqian; Fuli Yu (Mol Genet Genomic Med, 2020)
BACKGROUND: Current copy number variation (CNV) identification methods have rapidly become mature. However, the postdetection processes such as variant interpretation or reporting are inefficient. To overcome this situation, we developed REDBot as an automated software package for accurate and direct generation of clinical diagnostic reports for prenatal and products of conception (POC) samples. METHODS: We applied natural language process (NLP) methods for analyzing 30,235 in-house historical clinical reports through active learning, and then, developed clinical knowledge bases, evidence-based interpretation methods and reporting criteria to support the whole postdetection pipeline. RESULTS: Of the 30,235 reports, we obtained 37,175 CNV-paragraph pairs. For these pairs, the active learning approaches achieved a 0.9466 average F1-score in sentence classification. The overall accuracy for variant classification was 95.7%, 95.2%, and 100.0% in retrospective, prospective, and clinical utility experiments, respectively. CONCLUSION: By integrating NLP methods in CNVs postdetection pipeline, REDBot is a robust and rapid tool with clinical utility for prenatal and POC diagnosis.
Keywords: DNA Copy Number Variations; Electronic Health Records; Genetic Testing; Humans; Natural Language Processing; Prenatal Diagnosis; Software

Retrospective evaluation of whole exome and genome mutation calls in 746 cancer samples. - Bailey, Matthew H; Meyerson, William U; Dursi, Lewis Jonathan; Wang, Liang-Bo; Dong, Guanlan; Liang, Wen-Wei; Weerasinghe, Amila; Li, Shantao; Li, Yize; Kelso, Sean; Saksena, Gordon; Ellrott, Kyle; et al. (Nat Commun, 2020)
The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) curated consensus somatic mutation calls using whole exome sequencing (WES) and whole genome sequencing (WGS), respectively. Here, as part of the ICGC/TCGA Pan-Cancer Analysis of Whole Genomes (PCAWG) Consortium, which aggregated whole genome sequencing data from 2,658 cancers across 38 tumour types, we compare WES and WGS side-by-side from 746 TCGA samples, finding that ~80% of mutations overlap in covered exonic regions. We estimate that low variant allele fraction (VAF < 15%) and clonal heterogeneity contribute up to 68% of private WGS mutations and 71% of private WES mutations. We observe that ~30% of private WGS mutations trace to mutations identified by a single variant caller in WES consensus efforts. WGS captures both ~50% more variation in exonic regions and un-observed mutations in loci with variable GC-content. Together, our analysis highlights technological divergences between two reproducible somatic variant detection efforts.
Keywords: Base Composition; Databases, Genetic; DNA, Intergenic; Exome; Exome Sequencing; Exons; Genome, Human; Humans; Mutation; Neoplasms; Retrospective Studies; Whole Genome Sequencing

A robust benchmark for detection of germline large deletions and insertions. - Zook, Justin M; Hansen, Nancy F; Olson, Nathan D; Chapman, Lesley; Mullikin, James C; Xiao, Chunlin; Sherry, Stephen; Koren, Sergey; Phillippy, Adam M; Boutros, Paul C; Sahraeian, Sayed Mohammad E; Huang, Vincent; et al. (Nat Biotechnol, 2020)
New technologies and analysis methods are enabling genomic structural variants (SVs) to be detected with ever-increasing accuracy, resolution and comprehensiveness. To help translate these methods to routine research and clinical practice, we developed a sequence-resolved benchmark set for identification of both false-negative and false-positive germline large insertions and deletions. To create this benchmark for a broadly consented son in a Personal Genome Project trio with broadly available cells and DNA, the Genome in a Bottle Consortium integrated 19 sequence-resolved variant calling methods from diverse technologies. The final benchmark set contains 12,745 isolated, sequence-resolved insertion (7,281) and deletion (5,464) calls ≥50 base pairs (bp). The Tier 1 benchmark regions, for which any extra calls are putative false positives, cover 2.51 Gbp and 5,262 insertions and 4,095 deletions supported by ≥1 diploid assembly. We demonstrate that the benchmark set reliably identifies false negatives and false positives in high-quality SV callsets from short-, linked- and long-read sequencing and optical mapping.
Keywords: Diploidy; Genomic Structural Variation; Germ-Line Mutation; Humans; INDEL Mutation; Molecular Sequence Annotation; Sequence Analysis, DNA

Sawfly Genomes Reveal Evolutionary Acquisitions That Fostered the Mega-Radiation of Parasitoid and Eusocial Hymenoptera. - Oeyen, Jan Philip; Baa-Puyoulet, Patrice; Benoit, Joshua B; Beukeboom, Leo W; Bornberg-Bauer, Erich; Buttstedt, Anja; Calevro, Federica; Cash, Elizabeth I; Chao, Hsu; Charles, Hubert; Chen, Mei-Ju May; Childers, Christopher; et al. (Genome Biol Evol, 2020)
The tremendous diversity of Hymenoptera is commonly attributed to the evolution of parasitoidism in the last common ancestor of parasitoid sawflies (Orussidae) and wasp-waisted Hymenoptera (Apocrita). However, Apocrita and Orussidae differ dramatically in their species richness, indicating that the diversification of Apocrita was promoted by additional traits. These traits have remained elusive due to a paucity of sawfly genome sequences, in particular those of parasitoid sawflies. Here, we present comparative analyses of draft genomes of the primarily phytophagous sawfly Athalia rosae and the parasitoid sawfly Orussus abietinus. Our analyses revealed that the ancestral hymenopteran genome exhibited traits that were previously considered unique to eusocial Apocrita (e.g., low transposable element content and activity) and a wider gene repertoire than previously thought (e.g., genes for CO2 detection). Moreover, we discovered that Apocrita evolved a significantly larger array of odorant receptors than sawflies, which could be relevant to the remarkable diversification of Apocrita by enabling efficient detection and reliable identification of hosts.
Keywords: Amino Acid Sequence; Animals; Conserved Sequence; DNA Transposable Elements; Female; Gene Dosage; Genetic Speciation; Genome, Insect; Glycoproteins; Herbivory; Host-Parasite Interactions; Hymenoptera; Immunity; Insect Proteins; Male; Multigene Family; Receptors, Odorant; Social Behavior; Vision, Ocular

Serum sphingolipids and incident diabetes in a US population with high diabetes burden: the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). - Chen, Guo-Chong; Chai, Jin Choul; Yu, Bing; Michelotti, Gregory A; Grove, Megan L; Fretts, Amanda M; Daviglus, Martha L; Garcia-Bedoya, Olga L; Thyagarajan, Bharat; Schneiderman, Neil; Cai, Jianwen; Kaplan, Robert C; et al. (Am J Clin Nutr, 2020)
BACKGROUND: Genetic or pharmacological inhibition of de novo sphingolipid synthases prevented diabetes in animal studies. OBJECTIVES: We sought to evaluate prospective associations of serum sphingolipids with incident diabetes in a population-based cohort. METHODS: We included 2010 participants of the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) aged 18-74 y who were free of diabetes and other major chronic diseases at baseline (2008-2011). Metabolomic profiling of fasting serum was performed using a global, untargeted approach. A total of 43 sphingolipids were quantified and, considering subclasses and chemical structures of individual species, 6 sphingolipid scores were constructed. Diabetes status was assessed using standard procedures including blood tests. Multivariable survey Poisson regressions were applied to estimate RR and 95% CI of incident diabetes associated with individual sphingolipids or sphingolipid scores. RESULTS: There were 224 incident cases of diabetes identified during, on average, 6 y of follow-up. After adjustment for socioeconomic and lifestyle factors, a ceramide score (RR Q4 versus Q1 = 2.40; 95% CI: 1.24, 4.65; P-trend = 0.003) and a score of sphingomyelins with fully saturated sphingoid-fatty acid pairs (RR Q4 versus Q1 = 3.15; 95% CI: 1.75, 5.67; P-trend <0.001) both were positively associated with risk of diabetes, whereas scores of glycosylceramides, lactosylceramides, or other unsaturated sphingomyelins (even if having an SFA base) were not associated with risk of diabetes. After additional adjustment for numerous traditional risk factors (especially triglycerides), both associations were attenuated and only the saturated-sphingomyelin score remained associated with risk of diabetes (RR Q4 versus Q1 = 1.98; 95% CI: 1.09, 3.59; P-trend = 0.031). CONCLUSIONS: Our findings suggest that a cluster of saturated sphingomyelins may be associated with elevated risk of diabetes beyond traditional risk factors, which needs to be verified in other population studies. This study was registered at clinicaltrials.gov as NCT02060344.
Keywords: Adolescent; Adult; Aged; Diabetes Mellitus; Female; Hispanic or Latino; Humans; Male; Middle Aged; Prospective Studies; Risk Factors; Sphingolipids; United States; Young Adult

Simultaneous profiling of chromatin accessibility and methylation on human cell lines with nanopore sequencing. - Lee, Isac; Razaghi, Roham; Gilpatrick, Timothy; Molnar, Michael; Gershman, Ariel; Sadowski, Norah; Fritz J Sedlazeck; Hansen, Kasper D; Simpson, Jared T; Timp, Winston (Nat Methods, 2020)
Probing epigenetic features on DNA has tremendous potential to advance our understanding of the phased epigenome. In this study, we use nanopore sequencing to evaluate CpG methylation and chromatin accessibility simultaneously on long strands of DNA by applying GpC methyltransferase to exogenously label open chromatin. We performed nanopore sequencing of nucleosome occupancy and methylome (nanoNOMe) on four human cell lines (GM12878, MCF-10A, MCF-7 and MDA-MB-231). The single-molecule resolution allows footprinting of protein and nucleosome binding, and determination of the combinatorial promoter epigenetic signature on individual molecules. Long-read sequencing makes it possible to robustly assign reads to haplotypes, allowing us to generate a fully phased human epigenome, consisting of chromosome-level allele-specific profiles of CpG methylation and chromatin accessibility. We further apply this to a breast cancer model to evaluate differential methylation and accessibility between cancerous and noncancerous cells.
Keywords: Breast Neoplasms; Cell Line, Tumor; Chromatin; CpG Islands; DNA; DNA Methylation; Epigenome; Female; Genome, Human; Humans; MCF-7 Cells; Methyltransferases; Nanopore Sequencing; Promoter Regions, Genetic; Sequence Analysis, DNA

Single-Cell Capture, RNA-seq, and Transcriptome Analysis from the Neural Retina. - Dharmat, Rachayata; Kim, Sangbae; Yumei Li; Rui Chen (Methods Mol Biol, 2020)
Single-cell RNA sequencing (scRNA-seq) is an emerging technology that can address the challenge of cellular heterogeneity. In the last decade, the cost per cell has been dramatically reduced, and the throughput has been increased by 10-fold. Like many other tissues, the retina is highly heterogeneous with an estimated of over 100 subtypes of neuronal cells. Here, we describe the current techniques to perform scRNA-seq on the adult retinal tissue including retinal dissection, retinal dissociation, assessment of cell population, cDNA synthesis, library construction, and next-generation sequencing. In addition, we introduce a workflow of scRNA-seq data analysis using open-source tools.
Keywords: Data Analysis; DNA, Complementary; Gene Expression Profiling; High-Throughput Nucleotide Sequencing; Humans; Retina; RNA; RNA, Small Cytoplasmic; RNA-Seq; Sequence Analysis, RNA; Single-Cell Analysis; Transcriptome

Telomere Maintenance Mechanisms Define Clinical Outcome in High-Risk Neuroblastoma. - Koneru, Balakrishna; Lopez, Gonzalo; Farooqi, Ahsan; Conkrite, Karina L; Nguyen, Thinh H; Macha, Shawn J; Modi, Apexa; Rokita, Jo Lynne; Urias, Eduardo; Hindle, Ashly; Davidson, Heather; McCoy, Kristyn; et al. (Cancer Res, 2020)
Neuroblastoma is a childhood cancer with heterogeneous clinical outcomes. To comprehensively assess the impact of telomere maintenance mechanism (TMM) on clinical outcomes in high-risk neuroblastoma, we integrated the C-circle assay [a marker for alternative lengthening of telomeres (ALT)], TERT mRNA expression by RNA-sequencing, whole-genome/exome sequencing, and clinical covariates in 134 neuroblastoma patient samples at diagnosis. In addition, we assessed TMM in neuroblastoma cell lines ( = 104) and patient-derived xenografts ( = 28). ALT was identified in 23.4% of high-risk neuroblastoma tumors and genomic alterations in were detected in 60% of ALT tumors; 40% of ALT tumors lacked genomic alterations in known ALT-associated genes. Patients with high-risk neuroblastoma were classified into three subgroups (TERT-high, ALT, and TERT-low/non-ALT) based on presence of C-circles and TERT mRNA expression (above or below median TERT expression). Event-free survival was similar among TERT-high, ALT, or TERT-low/non-ALT patients. However, overall survival (OS) for TERT-low/non-ALT patients was significantly higher relative to TERT-high or ALT patients (log-rank test; < 0.01) independent of current clinical and molecular prognostic markers. Consistent with the observed higher OS in patients with TERT-low/non-ALT tumors, continuous shortening of telomeres and decreasing viability occurred in low TERT-expressing, non-ALT patient-derived high-risk neuroblastoma cell lines. These findings demonstrate that assaying TMM with TERT mRNA expression and C-circles provides precise stratification of high-risk neuroblastoma into three subgroups with substantially different OS: a previously undescribed TERT-low/non-ALT cohort with superior OS (even after relapse) and two cohorts of patients with poor survival that have distinct molecular therapeutic targets. SIGNIFICANCE: These findings assess telomere maintenance mechanisms with TERT mRNA and the ALT DNA biomarker C-circles to stratify neuroblastoma into three groups, with distinct overall survival independent of currently used clinical risk classifiers.
Keywords: Cell Line, Tumor; Child; Child, Preschool; Disease-Free Survival; Female; Follow-Up Studies; Gene Expression Regulation, Neoplastic; Humans; Infant; Male; Neoplasm Recurrence, Local; Neuroblastoma; RNA, Messenger; RNA-Seq; Telomerase; Telomere; Telomere Homeostasis; Whole Genome Sequencing; X-linked Nuclear Protein; Xenograft Model Antitumor Assays

Unusual sequence characteristics of human chromosome 19 are conserved across 11 nonhuman primates. - R. Alan Harris; Raveendran, Muthuswamy; Kim C Worley; Jeffrey Rogers (BMC Evol Biol, 2020)
BACKGROUND: Human chromosome 19 has many unique characteristics including gene density more than double the genome-wide average and 20 large tandemly clustered gene families. It also has the highest GC content of any chromosome, especially outside gene clusters. The high GC content and concomitant high content of hypermutable CpG sites raises the possibility chromosome 19 exhibits higher levels of nucleotide diversity both within and between species, and may possess greater variation in DNA methylation that regulates gene expression. RESULTS: We examined GC and CpG content of chromosome 19 orthologs across representatives of the primate order. In all 12 primate species with suitable genome assemblies, chromosome 19 orthologs have the highest GC content of any chromosome. CpG dinucleotides and CpG islands are also more prevalent in chromosome 19 orthologs than other chromosomes. GC and CpG content are generally higher outside the gene clusters. Intra-species variation based on SNPs in human common dbSNP, rhesus, crab eating macaque, baboon and marmoset datasets is most prevalent on chromosome 19 and its orthologs. Inter-species comparisons based on phyloP conservation show accelerated nucleotide evolution for chromosome 19 promoter flanking and enhancer regions. These same regulatory regions show the highest CpG density of any chromosome suggesting they possess considerable methylome regulatory potential. CONCLUSIONS: The pattern of high GC and CpG content in chromosome 19 orthologs, particularly outside gene clusters, is present from human to mouse lemur representing 74 million years of primate evolution. Much CpG variation exists both within and between primate species with a portion of this variation occurring in regulatory regions.
Keywords: Animals; Base Composition; Base Sequence; Chromosomes; Chromosomes, Human, Pair 19; Conserved Sequence; CpG Islands; Dinucleoside Phosphates; DNA Methylation; Genome; Humans; Lemur; Mice; Multigene Family; Phylogeny; Primates; Promoter Regions, Genetic; Regulatory Sequences, Nucleic Acid

Variants, N-Acetylated Amino Acids, and Progression of CKD. - Luo, Shengyuan; Surapaneni, Aditya; Zheng, Zihe; Rhee, Eugene P; Coresh, Josef; Hung, Adriana M; Nadkarni, Girish N; Yu, Bing; Eric Boerwinkle; Tin, Adrienne; Arking, Dan E; Steinbrenner, Inga; et al. (Clin J Am Soc Nephrol, 2020)
BACKGROUND AND OBJECTIVES: Genetic variants in , a liver- and kidney-specific acetyltransferase encoding gene, have been associated with eGFR and CKD in European populations. Higher circulating levels of two -associated metabolites, N--acetylornithine and N-acetyl-1-methylhistidine, have been linked to lower eGFR and higher risk of incident CKD in the Black population. We aimed to expand upon prior studies to investigate associations between rs13538, a missense variant in , N-acetylated amino acids, and kidney failure in multiple, well-characterized cohorts. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: We conducted analyses among participants with genetic and/or serum metabolomic data in the African American Study of Kidney Disease and Hypertension (AASK; =962), the Atherosclerosis Risk in Communities (ARIC) study (=1050), and Bio, an electronic health record-linked biorepository (=680). Separately, we evaluated associations between rs13538, urinary N-acetylated amino acids, and kidney failure in participants in the German CKD (GCKD) study (=1624). RESULTS: Of 31 N-acetylated amino acids evaluated, the circulating and urinary levels of 14 were associated with rs13538 (<0.05/31). Higher circulating levels of five of these N-acetylated amino acids, namely, N--acetylornithine, N-acetyl-1-methylhistidine, N-acetyl-3-methylhistidine, N-acetylhistidine, and N2,N5-diacetylornithine, were associated with kidney failure, after adjustment for confounders and combining results in meta-analysis (combined hazard ratios per two-fold higher amino acid levels: 1.48, 1.44, 1.21, 1.65, and 1.41, respectively; 95% confidence intervals: 1.21 to 1.81, 1.22 to 1.70, 1.08 to 1.37, 1.29 to 2.10, and 1.17 to 1.71, respectively; all values <0.05/14). None of the urinary levels of these N-acetylated amino acids were associated with kidney failure in the GCKD study. CONCLUSIONS: We demonstrate significant associations between an gene variant and 14 N-acetylated amino acids, five of which had circulation levels that were associated with kidney failure.
Keywords: Acetylation; Acetyltransferases; Adult; Aged; Aged, 80 and over; Amino Acids; Black People; Disease Progression; Female; Follow-Up Studies; Glomerular Filtration Rate; Histidine; Humans; Kidney Failure, Chronic; Male; Metabolomics; Methylhistidines; Middle Aged; Ornithine; Polymorphism, Single Nucleotide; Prospective Studies; Randomized Controlled Trials as Topic; White People

Whole-genome sequencing reveals complex chromosome rearrangement disrupting NIPBL in infant with Cornelia de Lange syndrome. - Plesser Duvdevani, Morasha; Pettersson, Maria; Eisfeldt, Jesper; Avraham, Ortal; Dagan, Judith; Frumkin, Ayala; James R Lupski; Lindstrand, Anna; Harel, Tamar (Am J Med Genet A, 2020)
Clinical laboratory diagnostic evaluation of the genomes of children with suspected genetic disorders, including chromosomal microarray and exome sequencing, cannot detect copy number neutral genomic rearrangements such as inversions, balanced translocations, and complex chromosomal rearrangements (CCRs). We describe an infant with a clinical diagnosis of Cornelia de Lange syndrome (CdLS) in whom chromosome analysis revealed a de novo complex balanced translocation, 46,XY,t(5;7;6)(q11.2;q32;q13)dn. Subsequent molecular characterization by whole-genome sequencing (WGS) identified 23 breakpoints, delineating segments derived from four chromosomes (5;6;7;21) in ancestral or inverted orientation. One of the breakpoints disrupted a known CdLS gene, NIPBL. Further investigation revealed paternal origin of the CCR allele, clustering of the breakpoint junctions, and molecular repair signatures suggestive of a single catastrophic event. Notably, very short DNA segments (25 and 41 bp) were included in the reassembled chromosomes, lending additional support that the DNA repair machinery can detect and repair such segments. Interestingly, there was an independent paternally derived miniscule complex rearrangement, possibly predisposing to subsequent genomic instability. In conclusion, we report a CCR causing a monogenic Mendelian disorder, urging WGS analysis of similar unsolved cases with suspected Mendelian disorders. Breakpoint analysis allowed for identification of the underlying molecular diagnosis and implicated chromoanagenesis in CCR formation.
Keywords: Cell Cycle Proteins; Chromosome Aberrations; Chromosomes; De Lange Syndrome; Genetic Predisposition to Disease; Humans; Infant; Male; Translocation, Genetic; Whole Genome Sequencing

Wolff-Parkinson-White syndrome: De novo variants and evidence for mutational burden in genes associated with atrial fibrillation. - Coban-Akdemir, Zeynep H; Charng, Wu-Lin; Azamian, Mahshid; Paine, Ingrid S; Punetha, Jaya; Grochowski, Christopher M; Gambin, Tomasz; Valdes, Santiago O; Cannon, Bryan; Zapata, Gladys; Hernandez, Patricia P; Jhangiani, Shalini; et al. (Am J Med Genet A, 2020)
BACKGROUND: Wolff-Parkinson-White (WPW) syndrome is a relatively common arrhythmia affecting ~1-3/1,000 individuals. Mutations in PRKAG2 have been described in rare patients in association with cardiomyopathy. However, the genetic basis of WPW in individuals with a structurally normal heart remains poorly understood. Sudden death due to atrial fibrillation (AF) can also occur in these individuals. Several studies have indicated that despite ablation of an accessory pathway, the risk of AF remains high in patients compared to general population. METHODS: We applied exome sequencing in 305 subjects, including 65 trios, 80 singletons, and 6 multiple affected families. We used de novo analysis, candidate gene approach, and burden testing to explore the genetic contributions to WPW. RESULTS: A heterozygous deleterious variant in PRKAG2 was identified in one subject, accounting for 0.6% (1/151) of the genetic basis of WPW in this study. Another individual with WPW and left ventricular hypertrophy carried a known pathogenic variant in MYH7. We found rare de novo variants in genes associated with arrhythmia and cardiomyopathy (ANK2, NEBL, PITX2, and PRDM16) in this cohort. There was an increased burden of rare deleterious variants (MAF ≤ 0.005) with CADD score ≥ 25 in genes linked to AF in cases compared to controls (P = .0023). CONCLUSIONS: Our findings show an increased burden of rare deleterious variants in genes linked to AF in WPW syndrome, suggesting that genetic factors that determine the development of accessory pathways may be linked to an increased susceptibility of atrial muscle to AF in a subset of patients.
Keywords: Adolescent; Adult; AMP-Activated Protein Kinases; Ankyrins; Atrial Fibrillation; Carrier Proteins; Child; Cohort Studies; Cytoskeletal Proteins; DNA-Binding Proteins; Exome Sequencing; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Atria; Homeodomain Proteins; Humans; LIM Domain Proteins; Male; Mutation; Transcription Factors; Wolff-Parkinson-White Syndrome; Young Adult

ACAT: A Fast and Powerful p Value Combination Method for Rare-Variant Analysis in Sequencing Studies. - Liu, Yaowu; Chen, Sixing; Li, Zilin; Morrison, Alanna C; Eric Boerwinkle; Lin, Xihong (Am J Hum Genet, 2019)
Set-based analysis that jointly tests the association of variants in a group has emerged as a popular tool for analyzing rare and low-frequency variants in sequencing studies. The existing set-based tests can suffer significant power loss when only a small proportion of variants are causal, and their powers can be sensitive to the number, effect sizes, and effect directions of the causal variants and the choices of weights. Here we propose an aggregated Cauchy association test (ACAT), a general, powerful, and computationally efficient p value combination method for boosting power in sequencing studies. First, by combining variant-level p values, we use ACAT to construct a set-based test (ACAT-V) that is particularly powerful in the presence of only a small number of causal variants in a variant set. Second, by combining different variant-set-level p values, we use ACAT to construct an omnibus test (ACAT-O) that combines the strength of multiple complimentary set-based tests, including the burden test, sequence kernel association test (SKAT), and ACAT-V. Through analysis of extensively simulated data and the whole-genome sequencing data from the Atherosclerosis Risk in Communities (ARIC) study, we demonstrate that ACAT-V complements the SKAT and the burden test, and that ACAT-O has a substantially more robust and higher power than those of the alternative tests.
Keywords: Algorithms; Computer Simulation; Data Interpretation, Statistical; Disease; Genetic Association Studies; Genetic Variation; Genome, Human; Humans; Models, Genetic; Sequence Analysis, DNA

Accurate circular consensus long-read sequencing improves variant detection and assembly of a human genome. - Wenger, Aaron M; Peluso, Paul; Rowell, William J; Chang, Pi-Chuan; Hall, Richard J; Concepcion, Gregory T; Ebler, Jana; Fungtammasan, Arkarachai; Kolesnikov, Alexey; Olson, Nathan D; Töpfer, Armin; Alonge, Michael; et al. (Nat Biotechnol, 2019)
The DNA sequencing technologies in use today produce either highly accurate short reads or less-accurate long reads. We report the optimization of circular consensus sequencing (CCS) to improve the accuracy of single-molecule real-time (SMRT) sequencing (PacBio) and generate highly accurate (99.8%) long high-fidelity (HiFi) reads with an average length of 13.5 kilobases (kb). We applied our approach to sequence the well-characterized human HG002/NA24385 genome and obtained precision and recall rates of at least 99.91% for single-nucleotide variants (SNVs), 95.98% for insertions and deletions <50 bp (indels) and 95.99% for structural variants. Our CCS method matches or exceeds the ability of short-read sequencing to detect small variants and structural variants. We estimate that 2,434 discordances are correctable mistakes in the 'genome in a bottle' (GIAB) benchmark set. Nearly all (99.64%) variants can be phased into haplotypes, further improving variant detection. De novo genome assembly using CCS reads alone produced a contiguous and accurate genome with a contig N50 of >15 megabases (Mb) and concordance of 99.997%, substantially outperforming assembly with less-accurate long reads.
Keywords: Base Sequence; DNA, Circular; Genetic Variation; Genome, Human; Haplotypes; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA

Activating p53 family member TAp63: A novel therapeutic strategy for targeting p53-altered tumors. - Gunaratne, Preethi H; Pan, Yinghong; Rao, Abhi K; Lin, Chunru; Hernandez-Herrera, Anadulce; Liang, Ke; Rait, Antonina S; Venkatanarayan, Avinashnarayan; Benham, Ashley L; Rubab, Farwah; Kim, Sang Soo; Rajapakshe, Kimal; et al. (Cancer, 2019)
BACKGROUND: Over 96% of high-grade ovarian carcinomas and 50% of all cancers are characterized by alterations in the p53 gene. Therapeutic strategies to restore and/or reactivate the p53 pathway have been challenging. By contrast, p63, which shares many of the downstream targets and functions of p53, is rarely mutated in cancer. METHODS: A novel strategy is presented for circumventing alterations in p53 by inducing the tumor-suppressor isoform TAp63 (transactivation domain of tumor protein p63) through its direct downstream target, microRNA-130b (miR-130b), which is epigenetically silenced and/or downregulated in chemoresistant ovarian cancer. RESULTS: Treatment with miR-130b resulted in: 1) decreased migration/invasion in HEYA8 cells (p53 wild-type) and disruption of multicellular spheroids in OVCAR8 cells (p53-mutant) in vitro, 2) sensitization of HEYA8 and OVCAR8 cells to cisplatin (CDDP) in vitro and in vivo, and 3) transcriptional activation of TAp63 and the B-cell lymphoma (Bcl)-inhibitor B-cell lymphoma 2-like protein 11 (BIM). Overexpression of TAp63 was sufficient to decrease cell viability, suggesting that it is a critical downstream effector of miR-130b. In vivo, combined miR-130b plus CDDP exhibited greater therapeutic efficacy than miR-130b or CDDP alone. Mice that carried OVCAR8 xenograft tumors and were injected with miR-130b in 1,2-dioleoyl-sn-glycero-3-phosphatidylcholine (DOPC) liposomes had a significant decrease in tumor burden at rates similar to those observed in CDDP-treated mice, and 20% of DOPC-miR-130b plus CDDP-treated mice were living tumor free. Systemic injections of scL-miR-130b plus CDDP in a clinically tested, tumor-targeted nanocomplex (scL) improved survival in 60% and complete remissions in 40% of mice that carried HEYA8 xenografts. CONCLUSIONS: The miR-130b/TAp63 axis is proposed as a new druggable pathway that has the potential to uncover broad-spectrum therapeutic options for the majority of p53-altered cancers.
Keywords: Animals; Antineoplastic Agents; Binding Sites; Cell Line, Tumor; Cell Movement; Cisplatin; Drug Resistance, Neoplasm; Female; Humans; Liposomes; Mice; Mice, Nude; MicroRNAs; Mutation, Missense; Neoplasm Invasiveness; Ovarian Neoplasms; Protein Isoforms; Signal Transduction; Transcription Factors; Transcriptional Activation; Transfection; Tumor Suppressor Protein p53; Tumor Suppressor Proteins; Xenograft Model Antitumor Assays

Approaches to Whole Mitochondrial Genome Sequencing on the Oxford Nanopore MinION. - Zascavage, Roxanne R; Hall, Courtney L; Thorson, Kelcie; Mahmoud, Medhat; Fritz J Sedlazeck; Planz, John V (Curr Protoc Hum Genet, 2019)
Traditional approaches for interrogating the mitochondrial genome often involve laborious extraction and enrichment protocols followed by Sanger sequencing. Although preparation techniques are still demanding, the advent of next-generation or massively parallel sequencing has made it possible to routinely obtain nucleotide-level data with relative ease. These short-read sequencing platforms offer deep coverage with unparalleled read accuracy in high-complexity genomic regions but encounter numerous difficulties in the low-complexity homopolymeric sequences characteristic of the mitochondrial genome. The inability to discern identical units within monomeric repeats and resolve copy-number variations for heteroplasmy detection results in suboptimal genome assemblies that ultimately complicate downstream data analysis and interpretation of biological significance. Oxford Nanopore Technologies offers the ability to generate long-read sequencing data on a pocket-sized device known as the MinION. Nanopore-based sequencing is scalable, portable, and theoretically capable of sequencing the entire mitochondrial genome in a single contig. Furthermore, the recent development of a nanopore protein with dual reader heads allows for clear identification of nucleotides within homopolymeric stretches, significantly increasing resolution throughout these regions. The unrestricted read lengths, superior homopolymeric resolution, and affordability of the MinION device make it an attractive alternative to the labor-intensive, time-consuming, and costly mainstay deep-sequencing platforms. This article describes three approaches to extract, prepare, and sequence mitochondrial DNA on the Oxford Nanopore MinION device. Two of the workflows include enrichment of mitochondrial DNA prior to sequencing, whereas the other relies on direct sequencing of native genomic DNA to allow for simultaneous assessment of the nuclear and mitochondrial genomes. © 2019 by John Wiley & Sons, Inc. Basic Protocol: Enrichment-free mitochondrial DNA sequencing Alternate Protocol 1: Mitochondrial DNA sequencing following enrichment with polymerase chain reaction (PCR) Alternate Protocol 2: Mitochondrial DNA sequencing following enrichment with PCR-free hybridization capture Support Protocol 1: DNA quantification and quality assessment using the Agilent 4200 TapeStation System Support Protocol 2: AMPure XP bead clean-up Support Protocol 3: Suggested data analysis pipeline.
Keywords: DNA, Mitochondrial; Genome, Mitochondrial; High-Throughput Nucleotide Sequencing; Humans; Nanopores; Sequence Analysis, DNA

Atlas-CNV: a validated approach to call single-exon CNVs in the eMERGESeq gene panel. - Chiang, Theodore; Liu, Xiuping; Wu, Tsung-Jung; Jianhong Hu; Fritz J Sedlazeck; White, Simon; Schaid, Daniel; Andrade, Mariza de; Jarvik, Gail P; Crosslin, David; Stanaway, Ian; Carrell, David S; et al. (Genet Med, 2019)
PURPOSE: To provide a validated method to confidently identify exon-containing copy-number variants (CNVs), with a low false discovery rate (FDR), in targeted sequencing data from a clinical laboratory with particular focus on single-exon CNVs. METHODS: DNA sequence coverage data are normalized within each sample and subsequently exonic CNVs are identified in a batch of samples, when the target log ratio of the sample to the batch median exceeds defined thresholds. The quality of exonic CNV calls is assessed by C-scores (Z-like scores) using thresholds derived from gold standard samples and simulation studies. We integrate an ExonQC threshold to lower FDR and compare performance with alternate software (VisCap). RESULTS: Thirteen CNVs were used as a truth set to validate Atlas-CNV and compared with VisCap. We demonstrated FDR reduction in validation, simulation, and 10,926 eMERGESeq samples without sensitivity loss. Sixty-four multiexon and 29 single-exon CNVs with high C-scores were assessed by Multiplex Ligation-dependent Probe Amplification (MLPA). CONCLUSION: Atlas-CNV is validated as a method to identify exonic CNVs in targeted sequencing data generated in the clinical laboratory. The ExonQC and C-score assignment can reduce FDR (identification of targets with high variance) and improve calling accuracy of single-exon CNVs respectively. We propose guidelines and criteria to identify high confidence single-exon CNVs.
Keywords: DNA Copy Number Variations; Exons; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA; Software

Biallelic and De Novo Variants in DONSON Reveal a Clinical Spectrum of Cell Cycle-opathies with Microcephaly, Dwarfism and Skeletal Abnormalities. - Karaca, Ender; Posey, Jennifer E; Bostwick, Bret; Liu, Pengfei; Gezdirici, Alper; Yesil, Gozde; Coban Akdemir, Zeynep; Bayram, Yavuz; Harms, Frederike L; Meinecke, Peter; Alawi, Malik; Bacino, Carlos A; et al. (Am J Med Genet A, 2019)
Co-occurrence of primordial dwarfism and microcephaly together with particular skeletal findings are seen in a wide range of Mendelian syndromes including microcephaly micromelia syndrome (MMS, OMIM 251230), microcephaly, short stature, and limb abnormalities (MISSLA, OMIM 617604), and microcephalic primordial dwarfisms (MPDs). Genes associated with these syndromes encode proteins that have crucial roles in DNA replication or in other critical steps of the cell cycle that link DNA replication to cell division. We identified four unrelated families with five affected individuals having biallelic or de novo variants in DONSON presenting with a core phenotype of severe short stature (z score < -3 SD), additional skeletal abnormalities, and microcephaly. Two apparently unrelated families with identical homozygous c.631C > T p.(Arg211Cys) variant had clinical features typical of Meier-Gorlin syndrome (MGS), while two siblings with compound heterozygous c.346delG p.(Asp116Ile*62) and c.1349A > G p.(Lys450Arg) variants presented with Seckel-like phenotype. We also identified a de novo c.683G > T p.(Trp228Leu) variant in DONSON in a patient with prominent micrognathia, short stature and hypoplastic femur and tibia, clinically diagnosed with Femoral-Facial syndrome (FFS, OMIM 134780). Biallelic variants in DONSON have been recently described in individuals with microcephalic dwarfism. These studies also demonstrated that DONSON has an essential conserved role in the cell cycle. Here we describe novel biallelic and de novo variants that are associated with MGS, Seckel-like phenotype and FFS, the last of which has not been associated with any disease gene to date.
Keywords: Alleles; Bone and Bones; Cell Cycle; Cell Cycle Proteins; Child; Child, Preschool; Dwarfism; Family; Female; Humans; Infant; Infant, Newborn; Male; Microcephaly; Nuclear Proteins; Pedigree; Phenotype

Bi-allelic Variants in TONSL Cause SPONASTRIME Dysplasia and a Spectrum of Skeletal Dysplasia Phenotypes. - Burrage, Lindsay C; Reynolds, John J; Baratang, Nissan Vida; Phillips, Jennifer B; Wegner, Jeremy; McFarquhar, Ashley; Higgs, Martin R; Christiansen, Audrey E; Lanza, Denise G; Seavitt, John R; Jain, Mahim; Li, Xiaohui; et al. (Am J Hum Genet, 2019)
SPONASTRIME dysplasia is an autosomal-recessive spondyloepimetaphyseal dysplasia characterized by spine (spondylar) abnormalities, midface hypoplasia with a depressed nasal bridge, metaphyseal striations, and disproportionate short stature. Scoliosis, coxa vara, childhood cataracts, short dental roots, and hypogammaglobulinemia have also been reported in this disorder. Although an autosomal-recessive inheritance pattern has been hypothesized, pathogenic variants in a specific gene have not been discovered in individuals with SPONASTRIME dysplasia. Here, we identified bi-allelic variants in TONSL, which encodes the Tonsoku-like DNA repair protein, in nine subjects (from eight families) with SPONASTRIME dysplasia, and four subjects (from three families) with short stature of varied severity and spondylometaphyseal dysplasia with or without immunologic and hematologic abnormalities, but no definitive metaphyseal striations at diagnosis. The finding of early embryonic lethality in a Tonsl murine model and the discovery of reduced length, spinal abnormalities, reduced numbers of neutrophils, and early lethality in a tonsl zebrafish model both support the hypomorphic nature of the identified TONSL variants. Moreover, functional studies revealed increased amounts of spontaneous replication fork stalling and chromosomal aberrations, as well as fewer camptothecin (CPT)-induced RAD51 foci in subject-derived cell lines. Importantly, these cellular defects were rescued upon re-expression of wild-type (WT) TONSL; this rescue is consistent with the hypothesis that hypomorphic TONSL variants are pathogenic. Overall, our studies in humans, mice, zebrafish, and subject-derived cell lines confirm that pathogenic variants in TONSL impair DNA replication and homologous recombination-dependent repair processes, and they lead to a spectrum of skeletal dysplasia phenotypes with numerous extra-skeletal manifestations.
Keywords: Adolescent; Adult; Alleles; Animals; Cells, Cultured; Child; Child, Preschool; Chromosomal Instability; DNA Damage; Exome Sequencing; Female; Fibroblasts; Genetic Association Studies; Genetic Variation; Humans; Mice; Mice, Knockout; Musculoskeletal Abnormalities; NF-kappa B; Osteochondrodysplasias; Young Adult; Zebrafish

Biallelic VARS variants cause developmental encephalopathy with microcephaly that is recapitulated in vars knockout zebrafish. - Siekierska, Aleksandra; Stamberger, Hannah; Deconinck, Tine; Oprescu, Stephanie N; Partoens, Michèle; Zhang, Yifan; Sourbron, Jo; Adriaenssens, Elias; Mullen, Patrick; Wiencek, Patrick; Hardies, Katia; Lee, Jeong-Soo; et al. (Nat Commun, 2019)
Aminoacyl tRNA synthetases (ARSs) link specific amino acids with their cognate transfer RNAs in a critical early step of protein translation. Mutations in ARSs have emerged as a cause of recessive, often complex neurological disease traits. Here we report an allelic series consisting of seven novel and two previously reported biallelic variants in valyl-tRNA synthetase (VARS) in ten patients with a developmental encephalopathy with microcephaly, often associated with early-onset epilepsy. In silico, in vitro, and yeast complementation assays demonstrate that the underlying pathomechanism of these mutations is most likely a loss of protein function. Zebrafish modeling accurately recapitulated some of the key neurological disease traits. These results provide both genetic and biological insights into neurodevelopmental disease and pave the way for further in-depth research on ARS related recessive disorders and precision therapies.
Keywords: Alleles; Animals; Brain Diseases; Cell Line; Disease Models, Animal; Epilepsy; Female; Fibroblasts; Gene Knockout Techniques; Genetic Predisposition to Disease; Humans; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Neurodevelopmental Disorders; Pedigree; Prosencephalon; Valine-tRNA Ligase; Zebrafish

Blood Leukocyte DNA Methylation Predicts Risk of Future Myocardial Infarction and Coronary Heart Disease. - Agha, Golareh; Mendelson, Michael M; Ward-Caviness, Cavin K; Joehanes, Roby; Huan, Tianxiao; Gondalia, Rahul; Salfati, Elias; Brody, Jennifer A; Fiorito, Giovanni; Bressler, Jan; Chen, Brian H; Ligthart, Symen; et al. (Circulation, 2019)
BACKGROUND: DNA methylation is implicated in coronary heart disease (CHD), but current evidence is based on small, cross-sectional studies. We examined blood DNA methylation in relation to incident CHD across multiple prospective cohorts. METHODS: Nine population-based cohorts from the United States and Europe profiled epigenome-wide blood leukocyte DNA methylation using the Illumina Infinium 450k microarray, and prospectively ascertained CHD events including coronary insufficiency/unstable angina, recognized myocardial infarction, coronary revascularization, and coronary death. Cohorts conducted race-specific analyses adjusted for age, sex, smoking, education, body mass index, blood cell type proportions, and technical variables. We conducted fixed-effect meta-analyses across cohorts. RESULTS: Among 11 461 individuals (mean age 64 years, 67% women, 35% African American) free of CHD at baseline, 1895 developed CHD during a mean follow-up of 11.2 years. Methylation levels at 52 CpG (cytosine-phosphate-guanine) sites were associated with incident CHD or myocardial infarction (false discovery rate<0.05). These CpGs map to genes with key roles in calcium regulation (ATP2B2, CASR, GUCA1B, HPCAL1), and genes identified in genome- and epigenome-wide studies of serum calcium (CASR), serum calcium-related risk of CHD (CASR), coronary artery calcified plaque (PTPRN2), and kidney function (CDH23, HPCAL1), among others. Mendelian randomization analyses supported a causal effect of DNA methylation on incident CHD; these CpGs map to active regulatory regions proximal to long non-coding RNA transcripts. CONCLUSION: Methylation of blood-derived DNA is associated with risk of future CHD across diverse populations and may serve as an informative tool for gaining further insight on the development of CHD.
Keywords: Adult; Aged; Cohort Studies; Coronary Disease; CpG Islands; DNA Methylation; Europe; Female; Genome-Wide Association Study; Humans; Incidence; Leukocytes; Male; Middle Aged; Myocardial Infarction; Population Groups; Prognosis; Prospective Studies; Risk; United States

Clinical exome sequencing reveals locus heterogeneity and phenotypic variability of cohesinopathies. - Bo Yuan; Neira, Juanita; Pehlivan, Davut; Santiago-Sim, Teresa; Song, Xiaofei; Rosenfeld, Jill; Posey, Jennifer E; Patel, Vipulkumar; Jin, Weihong; Adam, Margaret P; Baple, Emma L; Dean, John; et al. (Genet Med, 2019)
PURPOSE: Defects in the cohesin pathway are associated with cohesinopathies, notably Cornelia de Lange syndrome (CdLS). We aimed to delineate pathogenic variants in known and candidate cohesinopathy genes from a clinical exome perspective. METHODS: We retrospectively studied patients referred for clinical exome sequencing (CES, N = 10,698). Patients with causative variants in novel or recently described cohesinopathy genes were enrolled for phenotypic characterization. RESULTS: Pathogenic or likely pathogenic single-nucleotide and insertion/deletion variants (SNVs/indels) were identified in established disease genes including NIPBL (N = 5), SMC1A (N = 14), SMC3 (N = 4), RAD21 (N = 2), and HDAC8 (N = 8). The phenotypes in this genetically defined cohort skew towards the mild end of CdLS spectrum as compared with phenotype-driven cohorts. Candidate or recently reported cohesinopathy genes were supported by de novo SNVs/indels in STAG1 (N = 3), STAG2 (N = 5), PDS5A (N = 1), and WAPL (N = 1), and one inherited SNV in PDS5A. We also identified copy-number deletions affecting STAG1 (two de novo, one of unknown inheritance) and STAG2 (one of unknown inheritance). Patients with STAG1 and STAG2 variants presented with overlapping features yet without characteristic facial features of CdLS. CONCLUSION: CES effectively identified disease-causing alleles at the mild end of the cohensinopathy spectrum and enabled characterization of candidate disease genes.
Keywords: Adolescent; Alleles; Antigens, Nuclear; Biological Variation, Population; Carrier Proteins; Cell Cycle Proteins; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Cohort Studies; De Lange Syndrome; Exome; Female; Gene Frequency; Genetic Heterogeneity; Humans; INDEL Mutation; Male; Mutation; Nuclear Proteins; Phenotype; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins; Retrospective Studies; Whole Exome Sequencing

Complex Compound Inheritance of Lethal Lung Developmental Disorders Due to Disruption of the TBX-FGF Pathway. - Karolak, Justyna A; Vincent, Marie; Deutsch, Gail; Gambin, Tomasz; Cogné, Benjamin; Pichon, Olivier; Vetrini, Francesco; Mefford, Heather C; Dines, Jennifer N; Golden-Grant, Katie; Dipple, Katrina; Freed, Amanda S; et al. (Am J Hum Genet, 2019)
Primary defects in lung branching morphogenesis, resulting in neonatal lethal pulmonary hypoplasias, are incompletely understood. To elucidate the pathogenetics of human lung development, we studied a unique collection of samples obtained from deceased individuals with clinically and histopathologically diagnosed interstitial neonatal lung disorders: acinar dysplasia (n = 14), congenital alveolar dysplasia (n = 2), and other lethal lung hypoplasias (n = 10). We identified rare heterozygous copy-number variant deletions or single-nucleotide variants (SNVs) involving TBX4 (n = 8 and n = 2, respectively) or FGF10 (n = 2 and n = 2, respectively) in 16/26 (61%) individuals. In addition to TBX4, the overlapping ∼2 Mb recurrent and nonrecurrent deletions at 17q23.1q23.2 identified in seven individuals with lung hypoplasia also remove a lung-specific enhancer region. Individuals with coding variants involving either TBX4 or FGF10 also harbored at least one non-coding SNV in the predicted lung-specific enhancer region, which was absent in 13 control individuals with the overlapping deletions but without any structural lung anomalies. The occurrence of rare coding variants involving TBX4 or FGF10 with the putative hypomorphic non-coding SNVs implies a complex compound inheritance of these pulmonary hypoplasias. Moreover, they support the importance of TBX4-FGF10-FGFR2 epithelial-mesenchymal signaling in human lung organogenesis and help to explain the histopathological continuum observed in these rare lethal developmental disorders of the lung.
Keywords: DNA Copy Number Variations; Female; Fibroblast Growth Factor 10; Gene Expression Regulation; Gestational Age; Humans; Infant, Newborn; Infant, Newborn, Diseases; Lung; Lung Diseases; Male; Maternal Inheritance; Organogenesis; Paternal Inheritance; Pedigree; Polymorphism, Single Nucleotide; Receptor, Fibroblast Growth Factor, Type 2; Signal Transduction; T-Box Domain Proteins

Copy number variant and runs of homozygosity detection by microarrays enabled more precise molecular diagnoses in 11,020 clinical exome cases. - Dharmadhikari, Avinash V; Ghosh, Rajarshi; Bo Yuan; Liu, Pengfei; Dai, Hongzheng; Al Masri, Sami; Scull, Jennifer; Posey, Jennifer E; Jiang, Allen H; He, Weimin; Vetrini, Francesco; Braxton, Alicia A; et al. (Genome Med, 2019)
BACKGROUND: Exome sequencing (ES) has been successfully applied in clinical detection of single nucleotide variants (SNVs) and small indels. However, identification of copy number variants (CNVs) using ES data remains challenging. The purpose of this study is to understand the contribution of CNVs and copy neutral runs of homozygosity (ROH) in molecular diagnosis of patients referred for ES. METHODS: In a cohort of 11,020 consecutive ES patients, an Illumina SNP array analysis interrogating mostly coding SNPs was performed as a quality control (QC) measurement and for CNV/ROH detection. Among these patients, clinical chromosomal microarray analysis (CMA) was performed at Baylor Genetics (BG) on 3229 patients, either before, concurrently, or after ES. We retrospectively analyzed the findings from CMA and the QC array. RESULTS: The QC array can detect ~ 70% of pathogenic/likely pathogenic CNVs (PCNVs) detectable by CMA. Out of the 11,020 ES cases, the QC array identified PCNVs in 327 patients and uniparental disomy (UPD) disorder-related ROH in 10 patients. The overall PCNV/UPD detection rate was 5.9% in the 3229 ES patients who also had CMA at BG; PCNV/UPD detection rate was higher in concurrent ES and CMA than in ES with prior CMA (7.2% vs 4.6%). The PCNVs/UPD contributed to the molecular diagnoses in 17.4% (189/1089) of molecularly diagnosed ES cases with CMA and were estimated to contribute in 10.6% of all molecularly diagnosed ES cases. Dual diagnoses with both PCNVs and SNVs were detected in 38 patients. PCNVs affecting single recessive disorder genes in a compound heterozygous state with SNVs were detected in 4 patients, and homozygous deletions (mostly exonic deletions) were detected in 17 patients. A higher PCNV detection rate was observed for patients with syndromic phenotypes and/or cardiovascular abnormalities. CONCLUSIONS: Our clinical genomics study demonstrates that detection of PCNV/UPD through the QC array or CMA increases ES diagnostic rate, provides more precise molecular diagnosis for dominant as well as recessive traits, and enables more complete genetic diagnoses in patients with dual or multiple molecular diagnoses. Concurrent ES and CMA using an array with exonic coverage for disease genes enables most effective detection of both CNVs and SNVs and therefore is recommended especially in time-sensitive clinical situations.
Keywords: Chromosome Aberrations; DNA Copy Number Variations; Exome Sequencing; Female; Genetic Testing; Homozygote; Humans; Limit of Detection; Male; Microarray Analysis

De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
BACKGROUND: Neurodevelopmental disorders are genetically and phenotypically heterogeneous encompassing developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), structural brain abnormalities, and neurological manifestations with variants in a large number of genes (hundreds) associated. To date, a few de novo mutations potentially disrupting TCF20 function in patients with ID, ASD, and hypotonia have been reported. TCF20 encodes a transcriptional co-regulator structurally related to RAI1, the dosage-sensitive gene responsible for Smith-Magenis syndrome (deletion/haploinsufficiency) and Potocki-Lupski syndrome (duplication/triplosensitivity). METHODS: Genome-wide analyses by exome sequencing (ES) and chromosomal microarray analysis (CMA) identified individuals with heterozygous, likely damaging, loss-of-function alleles in TCF20. We implemented further molecular and clinical analyses to determine the inheritance of the pathogenic variant alleles and studied the spectrum of phenotypes. RESULTS: We report 25 unique inactivating single nucleotide variants/indels (1 missense, 1 canonical splice-site variant, 18 frameshift, and 5 nonsense) and 4 deletions of TCF20. The pathogenic variants were detected in 32 patients and 4 affected parents from 31 unrelated families. Among cases with available parental samples, the variants were de novo in 20 instances and inherited from 4 symptomatic parents in 5, including in one set of monozygotic twins. Two pathogenic loss-of-function variants were recurrent in unrelated families. Patients presented with a phenotype characterized by developmental delay, intellectual disability, hypotonia, variable dysmorphic features, movement disorders, and sleep disturbances. CONCLUSIONS: TCF20 pathogenic variants are associated with a novel syndrome manifesting clinical characteristics similar to those observed in Smith-Magenis syndrome. Together with previously described cases, the clinical entity of TCF20-associated neurodevelopmental disorders (TAND) emerges from a genotype-driven perspective.
Keywords: Adolescent; Child; Child, Preschool; Craniofacial Abnormalities; Developmental Disabilities; Female; Humans; INDEL Mutation; Infant; Intellectual Disability; Male; Muscle Hypotonia; Smith-Magenis Syndrome; Transcription Factors; Young Adult

Delineating the expanding phenotype associated with SCAPER gene mutation. - Fasham, James; Arno, Gavin; Lin, Siying; Xu, Mingchu; Carss, Keren J; Hull, Sarah; Lane, Amelia; Robson, Anthony G; Wenger, Olivia; Self, Jay E; Harlalka, Gaurav V; Salter, Claire G; et al. (Am J Med Genet A, 2019)
Keywords: Adolescent; Adult; Carrier Proteins; Child; Consanguinity; DNA Mutational Analysis; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Pedigree; Phenotype; Young Adult

Distinct patterns of complex rearrangements and a mutational signature of microhomeology are frequently observed in PLP1 copy number gain structural variants. - Bahrambeigi, Vahid; Song, Xiaofei; Sperle, Karen; Beck, Christine R; Hijazi, Hadia; Grochowski, Christopher M; Gu, Shen; Seeman, Pavel; Woodward, Karen J; Carvalho, Claudia M B; Hobson, Grace M; James R Lupski (Genome Med, 2019)
BACKGROUND: We investigated the features of the genomic rearrangements in a cohort of 50 male individuals with proteolipid protein 1 (PLP1) copy number gain events who were ascertained with Pelizaeus-Merzbacher disease (PMD; MIM: 312080). We then compared our new data to previous structural variant mutagenesis studies involving the Xq22 region of the human genome. The aggregate data from 159 sequenced join-points (discontinuous sequences in the reference genome that are joined during the rearrangement process) were studied. Analysis of these data from 150 individuals enabled the spectrum and relative distribution of the underlying genomic mutational signatures to be delineated. METHODS: Genomic rearrangements in PMD individuals with PLP1 copy number gain events were investigated by high-density customized array or clinical chromosomal microarray analysis and breakpoint junction sequence analysis. RESULTS: High-density customized array showed that the majority of cases (33/50; ~ 66%) present with single duplications, although complex genomic rearrangements (CGRs) are also frequent (17/50; ~ 34%). Breakpoint mapping to nucleotide resolution revealed further previously unknown structural and sequence complexities, even in single duplications. Meta-analysis of all studied rearrangements that occur at the PLP1 locus showed that single duplications were found in ~ 54% of individuals and that, among all CGR cases, triplication flanked by duplications is the most frequent CGR array CGH pattern observed. Importantly, in ~ 32% of join-points, there is evidence for a mutational signature of microhomeology (highly similar yet imperfect sequence matches). CONCLUSIONS: These data reveal a high frequency of CGRs at the PLP1 locus and support the assertion that replication-based mechanisms are prominent contributors to the formation of CGRs at Xq22. We propose that microhomeology can facilitate template switching, by stabilizing strand annealing of the primer using W-C base complementarity, and is a mutational signature for replicative repair.
Keywords: Chromosome Breakpoints; Comparative Genomic Hybridization; DNA Copy Number Variations; Gene Duplication; Gene Rearrangement; Genetic Association Studies; Genetic Predisposition to Disease; Genome, Human; Genomic Instability; Genomics; Humans; Mutation; Myelin Proteolipid Protein; Polymorphism, Single Nucleotide

Diversity and evolution of the transposable element repertoire in arthropods with particular reference to insects. - Petersen, Malte; Armisén, David; Richard A Gibbs; Hering, Lars; Khila, Abderrahman; Mayer, Georg; Richards, Stephen; Niehuis, Oliver; Misof, Bernhard (BMC Evol Biol, 2019)
BACKGROUND: Transposable elements (TEs) are a major component of metazoan genomes and are associated with a variety of mechanisms that shape genome architecture and evolution. Despite the ever-growing number of insect genomes sequenced to date, our understanding of the diversity and evolution of insect TEs remains poor. RESULTS: Here, we present a standardized characterization and an order-level comparison of arthropod TE repertoires, encompassing 62 insect and 11 outgroup species. The insect TE repertoire contains TEs of almost every class previously described, and in some cases even TEs previously reported only from vertebrates and plants. Additionally, we identified a large fraction of unclassifiable TEs. We found high variation in TE content, ranging from less than 6% in the antarctic midge (Diptera), the honey bee and the turnip sawfly (Hymenoptera) to more than 58% in the malaria mosquito (Diptera) and the migratory locust (Orthoptera), and a possible relationship between the content and diversity of TEs and the genome size. CONCLUSION: While most insect orders exhibit a characteristic TE composition, we also observed intraordinal differences, e.g., in Diptera, Hymenoptera, and Hemiptera. Our findings shed light on common patterns and reveal lineage-specific differences in content and evolution of TEs in insects. We anticipate our study to provide the basis for future comparative research on the insect TE repertoire.
Keywords: Animals; Antarctic Regions; Base Sequence; DNA Transposable Elements; Evolution, Molecular; Genetic Variation; Genome Size; Genome, Insect; Insecta; Phylogeny

Duplication of a domestication locus neutralized a cryptic variant that caused a breeding barrier in tomato. - Soyk, Sebastian; Lemmon, Zachary H; Fritz J Sedlazeck; Jiménez-Gómez, José M; Alonge, Michael; Hutton, Samuel F; Van Eck, Joyce; Schatz, Michael C; Lippman, Zachary B (Nat Plants, 2019)
Genome editing technologies are being widely adopted in plant breeding. However, a looming challenge of engineering desirable genetic variation in diverse genotypes is poor predictability of phenotypic outcomes due to unforeseen interactions with pre-existing cryptic mutations. In tomato, breeding with a classical MADS-box gene mutation that improves harvesting by eliminating fruit stem abscission frequently results in excessive inflorescence branching, flowering and reduced fertility due to interaction with a cryptic variant that causes partial mis-splicing in a homologous gene. Here, we show that a recently evolved tandem duplication carrying the second-site variant achieves a threshold of functional transcripts to suppress branching, enabling breeders to neutralize negative epistasis on yield. By dissecting the dosage mechanisms by which this structural variant restored normal flowering and fertility, we devised strategies that use CRISPR-Cas9 genome editing to predictably improve harvesting. Our findings highlight the under-appreciated impact of epistasis in targeted trait breeding and underscore the need for a deeper characterization of cryptic variation to enable the full potential of genome editing in agriculture.
Keywords: CRISPR-Associated Protein 9; CRISPR-Cas Systems; Domestication; Epistasis, Genetic; Flowers; Gene Duplication; Gene Editing; Genetic Variation; Plant Breeding; Plants, Genetically Modified; Quantitative Trait Loci; Reproduction; Solanum lycopersicum

Evaluation of computational genotyping of structural variation for clinical diagnoses. - Chander, Varuna; Richard A Gibbs; Fritz J Sedlazeck (Gigascience, 2019)
BACKGROUND: Structural variation (SV) plays a pivotal role in genetic disease. The discovery of SVs based on short DNA sequence reads from next-generation DNA sequence methods is error-prone, with low sensitivity and high false discovery rates. These shortcomings can be partially overcome with extensive orthogonal validation methods or use of long reads, but the current cost precludes their application for routine clinical diagnostics. In contrast, SV genotyping of known sites of SV occurrence is relatively robust and therefore offers a cost-effective clinical diagnostic tool with potentially few false-positive and false-negative results, even when applied to short-read DNA sequence data. RESULTS: We assess 5 state-of-the-art SV genotyping software methods, applied to short-read sequence data. The methods are characterized on the basis of their ability to genotype different SV types, spanning different size ranges. Furthermore, we analyze their ability to parse different VCF file subformats and assess their reliance on specific metadata. We compare the SV genotyping methods across a range of simulated and real data including SVs that were not found with Illumina data alone. We assess sensitivity and the ability to filter initial false discovery calls. We determined the impact of SV type and size on the performance for each SV genotyper. Overall, STIX performed the best on both simulated and GiaB based SV calls, demonstrating a good balance between sensitivity and specificty. CONCLUSION: Our results indicate that, although SV genotyping software methods have superior performance to SV callers, there are limitations that suggest the need for further innovation.
Keywords: Arthritis; Computer Simulation; Deafness; Genomic Structural Variation; Genotype; Humans; Polychondritis, Relapsing; Software

Evolution of DNA Methylation in Papio Baboons. - Vilgalys, Tauras P; Jeffrey Rogers; Jolly, Clifford J; Mukherjee, Sayan; Tung, Jenny (Mol Biol Evol, 2019)
Changes in gene regulation have long been thought to play an important role in primate evolution. However, although a number of studies have compared genome-wide gene expression patterns across primate species, fewer have investigated the gene regulatory mechanisms that underlie such patterns, or the relative contribution of drift versus selection. Here, we profiled genome-scale DNA methylation levels in blood samples from five of the six extant species of the baboon genus Papio (4-14 individuals per species). This radiation presents the opportunity to investigate DNA methylation divergence at both shallow and deeper timescales (0.380-1.4 My). In contrast to studies in human populations, but similar to studies in great apes, DNA methylation profiles clearly mirror genetic and geographic structure. Divergence in DNA methylation proceeds fastest in unannotated regions of the genome and slowest in regions of the genome that are likely more constrained at the sequence level (e.g., gene exons). Both heuristic approaches and Ornstein-Uhlenbeck models suggest that DNA methylation levels at a small set of sites have been affected by positive selection, and that this class is enriched in functionally relevant contexts, including promoters, enhancers, and CpG islands. Our results thus indicate that the rate and distribution of DNA methylation changes across the genome largely mirror genetic structure. However, at some CpG sites, DNA methylation levels themselves may have been a target of positive selection, pointing to loci that could be important in connecting sequence variation to fitness-related traits.
Keywords: Animals; DNA Methylation; Evolution, Molecular; Papio; Phylogeography

Exome sequencing of 20,791 cases of type 2 diabetes and 24,440 controls. - Flannick, Jason; Mercader, Josep M; Fuchsberger, Christian; Udler, Miriam S; Mahajan, Anubha; Wessel, Jennifer; Teslovich, Tanya M; Caulkins, Lizz; Koesterer, Ryan; Barajas-Olmos, Francisco; Blackwell, Thomas W; Eric Boerwinkle; et al. (Nature, 2019)
Protein-coding genetic variants that strongly affect disease risk can yield relevant clues to disease pathogenesis. Here we report exome-sequencing analyses of 20,791 individuals with type 2 diabetes (T2D) and 24,440 non-diabetic control participants from 5 ancestries. We identify gene-level associations of rare variants (with minor allele frequencies of less than 0.5%) in 4 genes at exome-wide significance, including a series of more than 30 SLC30A8 alleles that conveys protection against T2D, and in 12 gene sets, including those corresponding to T2D drug targets (P = 6.1 × 10) and candidate genes from knockout mice (P = 5.2 × 10). Within our study, the strongest T2D gene-level signals for rare variants explain at most 25% of the heritability of the strongest common single-variant signals, and the gene-level effect sizes of the rare variants that we observed in established T2D drug targets will require 75,000-185,000 sequenced cases to achieve exome-wide significance. We propose a method to interpret these modest rare-variant associations and to incorporate these associations into future target or gene prioritization efforts.
Keywords: Animals; Case-Control Studies; Decision Support Techniques; Diabetes Mellitus, Type 2; Exome; Exome Sequencing; Female; Gene Frequency; Genome-Wide Association Study; Humans; Male; Mice; Mice, Knockout

Exome Sequencing of a Primary Ovarian Insufficiency Cohort Reveals Common Molecular Etiologies for a Spectrum of Disease. - Jolly, Angad; Bayram, Yavuz; Turan, Serap; Aycan, Zehra; Tos, Tulay; Abali, Zehra Yavas; Hacihamdioglu, Bulent; Coban Akdemir, Zeynep Hande; Hijazi, Hadia; Bas, Serpil; Atay, Zeynep; Guran, Tulay; et al. (J Clin Endocrinol Metab, 2019)
CONTEXT: Primary ovarian insufficiency (POI) encompasses a spectrum of premature menopause, including both primary and secondary amenorrhea. For 75% to 90% of individuals with hypergonadotropic hypogonadism presenting as POI, the molecular etiology is unknown. Common etiologies include chromosomal abnormalities, environmental factors, and congenital disorders affecting ovarian development and function, as well as syndromic and nonsyndromic single gene disorders suggesting POI represents a complex trait. OBJECTIVE: To characterize the contribution of known disease genes to POI and identify molecular etiologies and biological underpinnings of POI. DESIGN, SETTING, AND PARTICIPANTS: We applied exome sequencing (ES) and family-based genomics to 42 affected female individuals from 36 unrelated Turkish families, including 31 with reported parental consanguinity. RESULTS: This analysis identified likely damaging, potentially contributing variants and molecular diagnoses in 16 families (44%), including 11 families with likely damaging variants in known genes and five families with predicted deleterious variants in disease genes (IGSF10, MND1, MRPS22, and SOHLH1) not previously associated with POI. Of the 16 families, 2 (13%) had evidence for potentially pathogenic variants at more than one locus. Absence of heterozygosity consistent with identity-by-descent mediated recessive disease burden contributes to molecular diagnosis in 15 of 16 (94%) families. GeneMatcher allowed identification of additional families from diverse genetic backgrounds. CONCLUSIONS: ES analysis of a POI cohort further characterized locus heterogeneity, reaffirmed the association of genes integral to meiotic recombination, demonstrated the likely contribution of genes involved in hypothalamic development, and documented multilocus pathogenic variation suggesting the potential for oligogenic inheritance contributing to the development of POI.
Keywords: Cell Cycle Proteins; Cohort Studies; DNA Helicases; DNA-Binding Proteins; Exome Sequencing; Female; Gene Frequency; Humans; Hypogonadism; Immunoglobulins; Minichromosome Maintenance Proteins; Primary Ovarian Insufficiency

Framework for microRNA variant annotation and prioritization using human population and disease datasets. - Oak, Ninad; Ghosh, Rajarshi; Huang, Kuan-Lin; David A Wheeler; Ding, Li; Plon, Sharon E (Hum Mutat, 2019)
MicroRNA (miRNA) expression is frequently deregulated in human disease, in contrast, disease-associated miRNA mutations are understudied. We developed Annotative Database of miRNA Elements, ADmiRE, which combines multiple existing and new biological annotations to aid prioritization of causal miRNA variation. We annotated 10,206 mature (3,257 within seed region) miRNA variants from multiple large sequencing datasets including gnomAD (15,496 genomes; 123,136 exomes). The pattern of miRNA variation closely resembles protein-coding exonic regions, with no difference between intragenic and intergenic miRNAs (P = 0.56), and high confidence miRNAs demonstrate higher sequence constraint (P < 0.001). Conservation analysis across 100 vertebrates identified 765 highly conserved miRNAs that also have limited genetic variation in gnomAD. We applied ADmiRE to the TCGA PanCancerAtlas WES dataset containing over 10,000 individuals across 33 adult cancers and annotated 1,267 germline (rare in gnomAD) and 1,492 somatic miRNA variants. Several miRNA families with deregulated gene expression in cancer have low levels of both somatic and germline variants, e.g., let-7 and miR-10. In addition to known somatic miR-142 mutations in hematologic cancers, we describe novel somatic miR-21 mutations in esophageal cancers impacting downstream miRNA targets. Through the development of ADmiRE, we present a framework for annotation and prioritization of miRNA variation in disease datasets.
Keywords: Animals; Base Sequence; Conserved Sequence; Databases, Genetic; Disease; Exome Sequencing; Genetics, Population; Genome, Human; Germ-Line Mutation; Humans; MicroRNAs; Molecular Sequence Annotation; Neoplasms; Phylogeny; Vertebrates

Gene Therapy Rescues Retinal Degeneration in Receptor Expression-Enhancing Protein 6 Mutant Mice. - Zaneveld, Smriti Agrawal; Eblimit, Aiden; Liang, Qingnan; Bertrand, Renae; Wu, Nathaniel; Liu, Hehe; Nguyen, Quynh; Zaneveld, Jacques; Wang, Keqing; Yumei Li; Rui Chen (Hum Gene Ther, 2019)
Hereditary retinal dystrophy is clinically defined as a broad group of chronic and progressive disorders that affect visual function by causing photoreceptor degeneration. Previously, we identified mutations in the gene encoding receptor expression-enhancing protein 6 (REEP6), in individuals with autosomal recessive retinitis pigmentosa (RP), the most common form of inherited retinal dystrophy. One individual was molecularly diagnosed with biallelic REEP6 mutations, a missense mutation over a frameshift mutation. In this study, we generated Reep6 compound heterozygous mice, Reep6, which mimic the patient genotype and recapitulate the early-onset retinal degeneration phenotypes observed in the individual with RP. To determine the feasibility of rescuing the Reep6 mutant phenotype via gene replacement therapy, we delivered Reep6.1, the mouse retina-specific isoform of REEP6, to photoreceptors of Reep6 mutant mice on postnatal day 20. Evaluation of the therapeutic effects 2 months posttreatment showed improvements in the photoresponse as well as preservation of photoreceptor cells. Importantly, guanylyl cyclase 1 (GC1) expression was also restored to the outer segment after treatment. Furthermore, rAAV8-Reep6.1 single treatment in Reep6 mutant mice 1 year postinjection showed significant improvements in retinal function and morphology, suggesting that the treatment is effective even after a prolonged period. Findings from this study show that gene replacement therapy in the retina with rAAV overexpressing Reep6 is effective, preserving photoreceptor function in Reep6 mutant mice. These findings provide evidence that rAAV8-based gene therapy can prolong survival of photoreceptors in vivo and can be potentially used as a therapeutic modality for treatment of patients with RP.
Keywords: Animals; Dependovirus; Disease Models, Animal; Electrophysiological Phenomena; Electroretinography; Endoplasmic Reticulum Stress; Eye Proteins; Gene Expression; Genetic Therapy; Genetic Vectors; Genotype; Guanylate Cyclase; Immunohistochemistry; Light; Membrane Proteins; Mice; Mice, Knockout; Mutation; Photoreceptor Cells; Protein Transport; Receptors, Cell Surface; Retinal Degeneration; Transduction, Genetic; Transgenes

A Genocentric Approach to Discovery of Mendelian Disorders. - Hansen, Adam W; Mullai Murugan; Li, He; Khayat, Michael M; Wang, Liwen; Rosenfeld, Jill; B. Kim Andrews; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Fritz J Sedlazeck; Ashley-Koch, Allison E; Liu, Pengfei; et al. (Am J Hum Genet, 2019)
The advent of inexpensive, clinical exome sequencing (ES) has led to the accumulation of genetic data from thousands of samples from individuals affected with a wide range of diseases, but for whom the underlying genetic and molecular etiology of their clinical phenotype remains unknown. In many cases, detailed phenotypes are unavailable or poorly recorded and there is little family history to guide study. To accelerate discovery, we integrated ES data from 18,696 individuals referred for suspected Mendelian disease, together with relatives, in an Apache Hadoop data lake (Hadoop Architecture Lake of Exomes [HARLEE]) and implemented a genocentric analysis that rapidly identified 154 genes harboring variants suspected to cause Mendelian disorders. The approach did not rely on case-specific phenotypic classifications but was driven by optimization of gene- and variant-level filter parameters utilizing historical Mendelian disease-gene association discovery data. Variants in 19 of the 154 candidate genes were subsequently reported as causative of a Mendelian trait and additional data support the association of all other candidate genes with disease endpoints.
Keywords: Databases, Genetic; Exome; Exome Sequencing; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Variation; Genomics; Humans; Pedigree; Phenotype

A genome-wide association study identifies new loci for factor VII and implicates factor VII in ischemic stroke etiology. - de Vries, Paul S; Sabater-Lleal, Maria; Huffman, Jennifer E; Marten, Jonathan; Song, Ci; Pankratz, Nathan; Bartz, Traci M; de Haan, Hugoline G; Delgado, Graciela E; Eicher, John D; Martinez-Perez, Angel; Ward-Caviness, Cavin K; et al. (Blood, 2019)
Factor VII (FVII) is an important component of the coagulation cascade. Few genetic loci regulating FVII activity and/or levels have been discovered to date. We conducted a meta-analysis of 9 genome-wide association studies of plasma FVII levels (7 FVII activity and 2 FVII antigen) among 27 495 participants of European and African ancestry. Each study performed ancestry-specific association analyses. Inverse variance weighted meta-analysis was performed within each ancestry group and then combined for a -ancestry meta-analysis. Our primary analysis included the 7 studies that measured FVII activity, and a secondary analysis included all 9 studies. We provided functional genomic validation for newly identified significant loci by silencing candidate genes in a human liver cell line (HuH7) using small-interfering RNA and then measuring messenger RNA and FVII protein expression. Lastly, we used meta-analysis results to perform Mendelian randomization analysis to estimate the causal effect of FVII activity on coronary artery disease, ischemic stroke (IS), and venous thromboembolism. We identified 2 novel ( and ) and 6 known loci associated with FVII activity, explaining 19.0% of the phenotypic variance. Adding FVII antigen data to the meta-analysis did not result in the discovery of further loci. Silencing in HuH7 cells upregulated FVII, whereas silencing downregulated FVII. Mendelian randomization analyses suggest that FVII activity has a positive causal effect on the risk of IS. Variants at and contribute to FVII activity by regulating expression levels. FVII activity appears to contribute to the etiology of IS in the general population.
Keywords: Brain Ischemia; Co-Repressor Proteins; Cohort Studies; Coronary Artery Disease; DNA-Binding Proteins; Factor VII; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Membrane Transport Proteins; Mendelian Randomization Analysis; Middle Aged; Neoplasm Proteins; Phenotype; Polymorphism, Single Nucleotide; Prognosis; Stroke; Venous Thromboembolism

Genome-wide patterns of transposon proliferation in an evolutionary young hybrid fish. - Dennenmoser, Stefan; Fritz J Sedlazeck; Schatz, Michael C; Altmüller, Janine; Zytnicki, Matthias; Nolte, Arne W (Mol Ecol, 2019)
Hybridization can induce transposons to jump into new genomic positions, which may result in their accumulation across the genome. Alternatively, transposon copy numbers may increase through nonallelic (ectopic) homologous recombination in highly repetitive regions of the genome. The relative contribution of transposition bursts versus recombination-based mechanisms to evolutionary processes remains unclear because studies on transposon dynamics in natural systems are rare. We assessed the genomewide distribution of transposon insertions in a young hybrid lineage ("invasive Cottus", n = 11) and its parental species Cottus rhenanus (n = 17) and Cottus perifretum(n = 9) using a reference genome assembled from long single molecule pacbio reads. An inventory of transposable elements was reconstructed from the same data and annotated. Transposon copy numbers in the hybrid lineage increased in 120 (15.9%) out of 757 transposons studied here. The copy number increased on average by 69% (range: 10%-197%). Given the age of the hybrid lineage, this suggests that they have proliferated within a few hundred generations since admixture began. However, frequency spectra of transposon insertions revealed no increase in novel and rare insertions across assembled parts of the genome. This implies that transposons were added to repetitive regions of the genome that remain difficult to assemble. Future studies will need to evaluate whether recombination-based mechanisms rather than genomewide transposition may explain the majority of the recent transposon proliferation in the hybrid lineage. Irrespectively of the underlying mechanism, the observed overabundance in repetitive parts of the genome suggests that gene-rich regions are unlikely to be directly affected.
Keywords: Animals; DNA Copy Number Variations; DNA Transposable Elements; Evolution, Molecular; Fishes; Genome; Hybridization, Genetic

A genomic atlas of systemic interindividual epigenetic variation in humans. - Gunasekara, Chathura J; Scott, C Anthony; Laritsky, Eleonora; Baker, Maria S; MacKay, Harry; Duryea, Jack D; Kessler, Noah J; Hellenthal, Garrett; Wood, Alexis C; Hodges, Kelly R; Gandhi, Manisha; Hair, Amy B; et al. (Genome Biol, 2019)
BACKGROUND: DNA methylation is thought to be an important determinant of human phenotypic variation, but its inherent cell type specificity has impeded progress on this question. At exceptional genomic regions, interindividual variation in DNA methylation occurs systemically. Like genetic variants, systemic interindividual epigenetic variants are stable, can influence phenotype, and can be assessed in any easily biopsiable DNA sample. We describe an unbiased screen for human genomic regions at which interindividual variation in DNA methylation is not tissue-specific. RESULTS: For each of 10 donors from the NIH Genotype-Tissue Expression (GTEx) program, CpG methylation is measured by deep whole-genome bisulfite sequencing of genomic DNA from tissues representing the three germ layer lineages: thyroid (endoderm), heart (mesoderm), and brain (ectoderm). We develop a computational algorithm to identify genomic regions at which interindividual variation in DNA methylation is consistent across all three lineages. This approach identifies 9926 correlated regions of systemic interindividual variation (CoRSIVs). These regions, comprising just 0.1% of the human genome, are inter-correlated over long genomic distances, associated with transposable elements and subtelomeric regions, conserved across diverse human ethnic groups, sensitive to periconceptional environment, and associated with genes implicated in a broad range of human disorders and phenotypes. CoRSIV methylation in one tissue can predict expression of associated genes in other tissues. CONCLUSIONS: In addition to charting a previously unexplored molecular level of human individuality, this atlas of human CoRSIVs provides a resource for future population-based investigations into how interindividual epigenetic variation modulates risk of disease.
Keywords: Aged; Brain; Case-Control Studies; Child; Disease; DNA Methylation; Epigenesis, Genetic; Female; Gambia; Genetic Variation; Genome, Human; Humans; Male; Middle Aged; Myocardium; Pregnancy; Prenatal Nutritional Physiological Phenomena; Seasons; Thyroid Gland

Genomic Profiling of Childhood Tumor Patient-Derived Xenograft Models to Enable Rational Clinical Trial Design. - Rokita, Jo Lynne; Rathi, Komal S; Cardenas, Maria F; Upton, Kristen A; Jayaseelan, Joy; Cross, Katherine L; Pfeil, Jacob; Egolf, Laura E; Way, Gregory P; Farrel, Alvin; Kendsersky, Nathan M; Patel, Khushbu; et al. (Cell Rep, 2019)
Accelerating cures for children with cancer remains an immediate challenge as a result of extensive oncogenic heterogeneity between and within histologies, distinct molecular mechanisms evolving between diagnosis and relapsed disease, and limited therapeutic options. To systematically prioritize and rationally test novel agents in preclinical murine models, researchers within the Pediatric Preclinical Testing Consortium are continuously developing patient-derived xenografts (PDXs)-many of which are refractory to current standard-of-care treatments-from high-risk childhood cancers. Here, we genomically characterize 261 PDX models from 37 unique pediatric cancers; demonstrate faithful recapitulation of histologies and subtypes; and refine our understanding of relapsed disease. In addition, we use expression signatures to classify tumors for TP53 and NF1 pathway inactivation. We anticipate that these data will serve as a resource for pediatric oncology drug development and will guide rational clinical trial design for children with cancer.
Keywords: Animals; Cell Line, Tumor; Central Nervous System Neoplasms; Child; Clinical Trials as Topic; Disease Models, Animal; Exome Sequencing; Genomics; Humans; Mice; Mutation; Neuroblastoma; Neurofibromin 1; Osteosarcoma; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Recurrence; Rhabdomyosarcoma; Sarcoma, Ewing; Tumor Suppressor Protein p53; Wilms Tumor; Xenograft Model Antitumor Assays

The Genomics of Arthrogryposis, a Complex Trait: Candidate Genes and Further Evidence for Oligogenic Inheritance. - Pehlivan, Davut; Bayram, Yavuz; Gunes, Nilay; Coban Akdemir, Zeynep; Shukla, Anju; Bierhals, Tatjana; Tabakci, Burcu; Sahin, Yavuz; Gezdirici, Alper; Fatih, Jawid M; Gulec, Elif Yilmaz; Yesil, Gozde; et al. (Am J Hum Genet, 2019)
Arthrogryposis is a clinical finding that is present either as a feature of a neuromuscular condition or as part of a systemic disease in over 400 Mendelian conditions. The underlying molecular etiology remains largely unknown because of genetic and phenotypic heterogeneity. We applied exome sequencing (ES) in a cohort of 89 families with the clinical sign of arthrogryposis. Additional molecular techniques including array comparative genomic hybridization (aCGH) and Droplet Digital PCR (ddPCR) were performed on individuals who were found to have pathogenic copy number variants (CNVs) and mosaicism, respectively. A molecular diagnosis was established in 65.2% (58/89) of families. Eleven out of 58 families (19.0%) showed evidence for potential involvement of pathogenic variation at more than one locus, probably driven by absence of heterozygosity (AOH) burden due to identity-by-descent (IBD). RYR3, MYOM2, ERGIC1, SPTBN4, and ABCA7 represent genes, identified in two or more families, for which mutations are probably causative for arthrogryposis. We also provide evidence for the involvement of CNVs in the etiology of arthrogryposis and for the idea that both mono-allelic and bi-allelic variants in the same gene cause either similar or distinct syndromes. We were able to identify the molecular etiology in nine out of 20 families who underwent reanalysis. In summary, our data from family-based ES further delineate the molecular etiology of arthrogryposis, yielded several candidate disease-associated genes, and provide evidence for mutational burden in a biological pathway or network. Our study also highlights the importance of reanalysis of individuals with unsolved diagnoses in conjunction with sequencing extended family members.
Keywords: Adolescent; Adult; Arthrogryposis; Child; Child, Preschool; Cohort Studies; Connectin; DNA Copy Number Variations; Exome Sequencing; Female; Genetic Markers; Genomics; Gestational Age; Humans; Infant; Infant, Newborn; Male; Mosaicism; Multifactorial Inheritance; Mutation; Pedigree; Ryanodine Receptor Calcium Release Channel; Vesicular Transport Proteins; Young Adult

Heterozygous CTNNB1 and TBX4 variants in a patient with abnormal lung growth, pulmonary hypertension, microcephaly, and spasticity. - Karolak, Justyna A; Szafranski, Przemyslaw; Kilner, David; Patel, Chirag; Scurry, Bonnie; Kinning, Esther; Chandler, Kate; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; James R Lupski; Popek, Edwina; Stankiewicz, Paweł (Clin Genet, 2019)
The canonical wingless (Wnt) and fibroblast growth factor (FGF) signaling pathways involving CTNNB1 and TBX4, respectively, are crucial for the regulation of human development. Perturbations of these pathways and disruptions from biological homeostasis have been associated with abnormal morphogenesis of multiple organs, including the lung. The aim of this study was to identify the underlying genetic cause of abnormal lung growth, pulmonary hypertension (PAH), severe microcephaly, and muscle spasticity in a full-term newborn, who died at 4 months of age due to progressively worsening PAH and respiratory failure. Family trio exome sequencing showed a de novo heterozygous nonsense c.1603C>T (p.Arg535*) variant in CTNNB1 and a paternally inherited heterozygous missense c.1198G>A (p.Glu400Lys) variant in TBX4, both predicted to be likely deleterious. We expand the phenotypic spectrum associated with CTNNB1 and TBX4 variants and indicate that they could act synergistically to produce a distinct more severe phenotype. Our findings further support a recently proposed complex compound inheritance model in lethal lung developmental diseases and the contention that dual molecular diagnoses can parsimoniously explain blended phenotypes.
Keywords: Alleles; beta Catenin; DNA Mutational Analysis; Exome Sequencing; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Heterozygote; Humans; Hypertension, Pulmonary; Immunohistochemistry; Microcephaly; Muscle Spasticity; Mutation; Phenotype; T-Box Domain Proteins

Identification of Polycystic Kidney Disease 1 Like 1 Gene Variants in Children With Biliary Atresia Splenic Malformation Syndrome. - Berauer, John-Paul; Mezina, Anya I; Okou, David T; Aniko Sabo; Donna M Muzny; Richard A Gibbs; Hegde, Madhuri R; Chopra, Pankaj; Cutler, David J; Perlmutter, David H; Bull, Laura N; Thompson, Richard J; et al. (Hepatology, 2019)
Biliary atresia (BA) is the most common cause of end-stage liver disease in children and the primary indication for pediatric liver transplantation, yet underlying etiologies remain unknown. Approximately 10% of infants affected by BA exhibit various laterality defects (heterotaxy) including splenic abnormalities and complex cardiac malformations-a distinctive subgroup commonly referred to as the biliary atresia splenic malformation (BASM) syndrome. We hypothesized that genetic factors linking laterality features with the etiopathogenesis of BA in BASM patients could be identified through whole-exome sequencing (WES) of an affected cohort. DNA specimens from 67 BASM subjects, including 58 patient-parent trios, from the National Institute of Diabetes and Digestive and Kidney Diseases-supported Childhood Liver Disease Research Network (ChiLDReN) underwent WES. Candidate gene variants derived from a prespecified set of 2,016 genes associated with ciliary dysgenesis and/or dysfunction or cholestasis were prioritized according to pathogenicity, population frequency, and mode of inheritance. Five BASM subjects harbored rare and potentially deleterious biallelic variants in polycystic kidney disease 1 like 1 (PKD1L1), a gene associated with ciliary calcium signaling and embryonic laterality determination in fish, mice, and humans. Heterozygous PKD1L1 variants were found in 3 additional subjects. Immunohistochemical analysis of liver from the one BASM subject available revealed decreased PKD1L1 expression in bile duct epithelium when compared to normal livers and livers affected by other noncholestatic diseases. Conclusion: WES identified biallelic and heterozygous PKD1L1 variants of interest in 8 BASM subjects from the ChiLDReN data set; the dual roles for PKD1L1 in laterality determination and ciliary function suggest that PKD1L1 is a biologically plausible, cholangiocyte-expressed candidate gene for the BASM syndrome.
Keywords: Abnormalities, Multiple; Biliary Atresia; Child; Databases, Factual; Exome Sequencing; Female; Gene Expression Regulation, Developmental; Genetic Variation; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Polycystic Kidney Diseases; Retrospective Studies; Spleen; Syndrome

Impact of Rare and Common Genetic Variants on Diabetes Diagnosis by Hemoglobin A1c in Multi-Ancestry Cohorts: The Trans-Omics for Precision Medicine Program. - Sarnowski, Chloe; Leong, Aaron; Raffield, Laura M; Wu, Peitao; de Vries, Paul S; DiCorpo, Daniel; Guo, Xiuqing; Xu, Huichun; Liu, Yongmei; Zheng, Xiuwen; Hu, Yao; Brody, Jennifer A; et al. (Am J Hum Genet, 2019)
Hemoglobin A1c (HbA1c) is widely used to diagnose diabetes and assess glycemic control in individuals with diabetes. However, nonglycemic determinants, including genetic variation, may influence how accurately HbA1c reflects underlying glycemia. Analyzing the NHLBI Trans-Omics for Precision Medicine (TOPMed) sequence data in 10,338 individuals from five studies and four ancestries (6,158 Europeans, 3,123 African-Americans, 650 Hispanics, and 407 East Asians), we confirmed five regions associated with HbA1c (GCK in Europeans and African-Americans, HK1 in Europeans and Hispanics, FN3K and/or FN3KRP in Europeans, and G6PD in African-Americans and Hispanics) and we identified an African-ancestry-specific low-frequency variant (rs1039215 in HBG2 and HBE1, minor allele frequency (MAF) = 0.03). The most associated G6PD variant (rs1050828-T, p.Val98Met, MAF = 12% in African-Americans, MAF = 2% in Hispanics) lowered HbA1c (-0.88% in hemizygous males, -0.34% in heterozygous females) and explained 23% of HbA1c variance in African-Americans and 4% in Hispanics. Additionally, we identified a rare distinct G6PD coding variant (rs76723693, p.Leu353Pro, MAF = 0.5%; -0.98% in hemizygous males, -0.46% in heterozygous females) and detected significant association with HbA1c when aggregating rare missense variants in G6PD. We observed similar magnitude and direction of effects for rs1039215 (HBG2) and rs76723693 (G6PD) in the two largest TOPMed African American cohorts, and we replicated the rs76723693 association in the UK Biobank African-ancestry participants. These variants in G6PD and HBG2 were monomorphic in the European and Asian samples. African or Hispanic ancestry individuals carrying G6PD variants may be underdiagnosed for diabetes when screened with HbA1c. Thus, assessment of these variants should be considered for incorporation into precision medicine approaches for diabetes diagnosis.
Keywords: Cohort Studies; Diabetes Mellitus; Female; Genetic Variation; Glycated Hemoglobin; Humans; Male; Polymorphism, Single Nucleotide; Population Groups; Precision Medicine

Insights into genetics, human biology and disease gleaned from family based genomic studies. - Posey, Jennifer E; O'Donnell-Luria, Anne H; Chong, Jessica X; Harel, Tamar; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Buyske, Steven; Pehlivan, Davut; Carvalho, Claudia M B; Baxter, Samantha; Sobreira, Nara; Liu, Pengfei; et al. (Genet Med, 2019)
Identifying genes and variants contributing to rare disease phenotypes and Mendelian conditions informs biology and medicine, yet potential phenotypic consequences for variation of >75% of the ~20,000 annotated genes in the human genome are lacking. Technical advances to assess rare variation genome-wide, particularly exome sequencing (ES), enabled establishment in the United States of the National Institutes of Health (NIH)-supported Centers for Mendelian Genomics (CMGs) and have facilitated collaborative studies resulting in novel "disease gene" discoveries. Pedigree-based genomic studies and rare variant analyses in families with suspected Mendelian conditions have led to the elucidation of hundreds of novel disease genes and highlighted the impact of de novo mutational events, somatic variation underlying nononcologic traits, incompletely penetrant alleles, phenotypes with high locus heterogeneity, and multilocus pathogenic variation. Herein, we highlight CMG collaborative discoveries that have contributed to understanding both rare and common diseases and discuss opportunities for future discovery in single-locus Mendelian disorder genomics. Phenotypic annotation of all human genes; development of bioinformatic tools and analytic methods; exploration of non-Mendelian modes of inheritance including reduced penetrance, multilocus variation, and oligogenic inheritance; construction of allelic series at a locus; enhanced data sharing worldwide; and integration with clinical genomics are explored. Realizing the full contribution of rare disease research to functional annotation of the human genome, and further illuminating human biology and health, will lay the foundation for the Precision Medicine Initiative.
Keywords: Databases, Genetic; Exome Sequencing; Genetic Diseases, Inborn; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; National Institutes of Health (U.S.); Pedigree; United States

Integrated Analysis of TP53 Gene and Pathway Alterations in The Cancer Genome Atlas. - Donehower, Lawrence A; Soussi, Thierry; Korkut, Anil; Liu, Yuexin; Schultz, Andre; Cardenas, Maria; Li, Xubin; Babur, Ozgun; Hsu, Teng-Kuei; Lichtarge, Olivier; Weinstein, John N; Akbani, Rehan; et al. (Cell Rep, 2019)
The TP53 tumor suppressor gene is frequently mutated in human cancers. An analysis of five data platforms in 10,225 patient samples from 32 cancers reported by The Cancer Genome Atlas (TCGA) enables comprehensive assessment of p53 pathway involvement in these cancers. More than 91% of TP53-mutant cancers exhibit second allele loss by mutation, chromosomal deletion, or copy-neutral loss of heterozygosity. TP53 mutations are associated with enhanced chromosomal instability, including increased amplification of oncogenes and deep deletion of tumor suppressor genes. Tumors with TP53 mutations differ from their non-mutated counterparts in RNA, miRNA, and protein expression patterns, with mutant TP53 tumors displaying enhanced expression of cell cycle progression genes and proteins. A mutant TP53 RNA expression signature shows significant correlation with reduced survival in 11 cancer types. Thus, TP53 mutation has profound effects on tumor cell genomic structure, expression, and clinical outlook.
Keywords: Databases, Nucleic Acid; Gene Expression Regulation, Neoplastic; Humans; Loss of Heterozygosity; MicroRNAs; Neoplasms; RNA, Neoplasm; Tumor Suppressor Protein p53

Interchromosomal template-switching as a novel molecular mechanism for imprinting perturbations associated with Temple syndrome. - Carvalho, Claudia M B; Coban-Akdemir, Zeynep; Hijazi, Hadia; Bo Yuan; Pendleton, Matthew; Harrington, Eoghan; Beaulaurier, John; Juul, Sissel; Turner, Daniel J; Kanchi, Rupa S; Jhangiani, Shalini N; Donna M Muzny; et al. (Genome Med, 2019)
BACKGROUND: Intrachromosomal triplications (TRP) can contribute to disease etiology via gene dosage effects, gene disruption, position effects, or fusion gene formation. Recently, post-zygotic de novo triplications adjacent to copy-number neutral genomic intervals with runs of homozygosity (ROH) have been shown to result in uniparental isodisomy (UPD). The genomic structure of these complex genomic rearrangements (CGRs) shows a consistent pattern of an inverted triplication flanked by duplications (DUP-TRP/INV-DUP) formed by an iterative DNA replisome template-switching mechanism during replicative repair of a single-ended, double-stranded DNA (seDNA), the ROH results from an interhomolog or nonsister chromatid template switch. It has been postulated that these CGRs may lead to genetic abnormalities in carriers due to dosage-sensitive genes mapping within the copy-number variant regions, homozygosity for alleles at a locus causing an autosomal recessive (AR) disease trait within the ROH region, or imprinting-associated diseases. METHODS: Here, we report a family wherein the affected subject carries a de novo 2.2-Mb TRP followed by 42.2 Mb of ROH and manifests clinical features overlapping with those observed in association with chromosome 14 maternal UPD (UPD(14)mat). UPD(14)mat can cause clinical phenotypic features enabling a diagnosis of Temple syndrome. This CGR was then molecularly characterized by high-density custom aCGH, genome-wide single-nucleotide polymorphism (SNP) and methylation arrays, exome sequencing (ES), and the Oxford Nanopore long-read sequencing technology. RESULTS: We confirmed the postulated DUP-TRP/INV-DUP structure by multiple orthogonal genomic technologies in the proband. The methylation status of known differentially methylated regions (DMRs) on chromosome 14 revealed that the subject shows the typical methylation pattern of UPD(14)mat. Consistent with these molecular findings, the clinical features overlap with those observed in Temple syndrome, including speech delay. CONCLUSIONS: These data provide experimental evidence that, in humans, triplication can lead to segmental UPD and imprinting disease. Importantly, genotype/phenotype analyses further reveal how a post-zygotically generated complex structural variant, resulting from a replication-based mutational mechanism, contributes to expanding the clinical phenotype of known genetic syndromes. Mechanistically, such events can distort transmission genetics resulting in homozygosity at a locus for which only one parent is a carrier as well as cause imprinting diseases.
Keywords: Chromosome Aberrations; Chromosome Disorders; Chromosomes, Human, Pair 14; DNA Methylation; DNA Replication; Genomic Imprinting; Humans; Male; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Young Adult

Megabase Length Hypermutation Accompanies Human Structural Variation at 17p11.2. - Beck, Christine R; Carvalho, Claudia M B; Akdemir, Zeynep C; Fritz J Sedlazeck; Song, Xiaofei; Meng, Qingchang; Hu, Jianhong; Harshavardhan Doddapaneni; Chong, Zechen; Chen, Edward S; Thornton, Philip C; Liu, Pengfei; et al. (Cell, 2019)
DNA rearrangements resulting in human genome structural variants (SVs) are caused by diverse mutational mechanisms. We used long- and short-read sequencing technologies to investigate end products of de novo chromosome 17p11.2 rearrangements and query the molecular mechanisms underlying both recurrent and non-recurrent events. Evidence for an increased rate of clustered single-nucleotide variant (SNV) mutation in cis with non-recurrent rearrangements was found. Indel and SNV formation are associated with both copy-number gains and losses of 17p11.2, occur up to ∼1 Mb away from the breakpoint junctions, and favor C > G transversion substitutions; results suggest that single-stranded DNA is formed during the genesis of the SV and provide compelling support for a microhomology-mediated break-induced replication (MMBIR) mechanism for SV formation. Our data show an additional mutational burden of MMBIR consisting of hypermutation confined to the locus and manifesting as SNVs and indels predominantly within genes.
Keywords: Abnormalities, Multiple; Chromosome Breakpoints; Chromosome Disorders; Chromosome Duplication; Chromosomes, Human, Pair 17; DNA Copy Number Variations; DNA Repair; DNA Replication; Gene Rearrangement; Genome, Human; Genomic Structural Variation; Humans; INDEL Mutation; Models, Genetic; Mutation; Polymorphism, Single Nucleotide; Recombination, Genetic; Sequence Analysis, DNA; Smith-Magenis Syndrome

Molecular profiling predicts meningioma recurrence and reveals loss of DREAM complex repression in aggressive tumors. - Patel, Akash J; Wan, Ying-Wooi; Al-Ouran, Rami; Revelli, Jean-Pierre; Cardenas, Maria F; Oneissi, Mazen; Xi, Liu; Jalali, Ali; Magnotti, John F; Donna M Muzny; Harshavardhan Doddapaneni; Sebastian, Sherly; et al. (Proc Natl Acad Sci U S A, 2019)
Meningiomas account for one-third of all primary brain tumors. Although typically benign, about 20% of meningiomas are aggressive, and despite the rigor of the current histopathological classification system there remains considerable uncertainty in predicting tumor behavior. Here, we analyzed 160 tumors from all 3 World Health Organization (WHO) grades (I through III) using clinical, gene expression, and sequencing data. Unsupervised clustering analysis identified 3 molecular types (A, B, and C) that reliably predicted recurrence. These groups did not directly correlate with the WHO grading system, which classifies more than half of the tumors in the most aggressive molecular type as benign. Transcriptional and biochemical analyses revealed that aggressive meningiomas involve loss of the repressor function of the DREAM complex, which results in cell-cycle activation; only tumors in this category tend to recur after full resection. These findings should improve our ability to predict recurrence and develop targeted treatments for these clinically challenging tumors.
Keywords: Adult; Aged; Aged, 80 and over; Cell Cycle; Cell Line; Disease Progression; DNA Copy Number Variations; Female; Gene Expression Profiling; Humans; Kv Channel-Interacting Proteins; Male; Meningeal Neoplasms; Meningioma; Middle Aged; Neoplasm Recurrence, Local; Prognosis; Repressor Proteins; Young Adult

A multi-task convolutional deep neural network for variant calling in single molecule sequencing. - Luo, Ruibang; Fritz J Sedlazeck; Lam, Tak-Wah; Schatz, Michael C (Nat Commun, 2019)
The accurate identification of DNA sequence variants is an important, but challenging task in genomics. It is particularly difficult for single molecule sequencing, which has a per-nucleotide error rate of ~5-15%. Meeting this demand, we developed Clairvoyante, a multi-task five-layer convolutional neural network model for predicting variant type (SNP or indel), zygosity, alternative allele and indel length from aligned reads. For the well-characterized NA12878 human sample, Clairvoyante achieves 99.67, 95.78, 90.53% F1-score on 1KP common variants, and 98.65, 92.57, 87.26% F1-score for whole-genome analysis, using Illumina, PacBio, and Oxford Nanopore data, respectively. Training on a second human sample shows Clairvoyante is sample agnostic and finds variants in less than 2 h on a standard server. Furthermore, we present 3,135 variants that are missed using Illumina but supported independently by both PacBio and Oxford Nanopore reads. Clairvoyante is available open-source ( https://github.com/aquaskyline/Clairvoyante ), with modules to train, utilize and visualize the model.
Keywords: Base Sequence; Computational Biology; DNA Mutational Analysis; Genome, Human; Genome-Wide Association Study; Genomics; Genotype; Genotyping Techniques; Humans; INDEL Mutation; Nanopores; Neural Networks, Computer; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Software

Mutations in ANKLE2, a ZIKA Virus Target, Disrupt an Asymmetric Cell Division Pathway in Drosophila Neuroblasts to Cause Microcephaly. - Link, Nichole; Chung, Hyunglok; Jolly, Angad; Withers, Marjorie; Tepe, Burak; Arenkiel, Benjamin R; Shah, Priya S; Krogan, Nevan J; Aydin, Hatip; Geckinli, Bilgen B; Tos, Tulay; Isikay, Sedat; et al. (Dev Cell, 2019)
The apical Par complex, which contains atypical protein kinase C (aPKC), Bazooka (Par-3), and Par-6, is required for establishing polarity during asymmetric division of neuroblasts in Drosophila, and its activity depends on L(2)gl. We show that loss of Ankle2, a protein associated with microcephaly in humans and known to interact with Zika protein NS4A, reduces brain volume in flies and impacts the function of the Par complex. Reducing Ankle2 levels disrupts endoplasmic reticulum (ER) and nuclear envelope morphology, releasing the kinase Ballchen-VRK1 into the cytosol. These defects are associated with reduced phosphorylation of aPKC, disruption of Par-complex localization, and spindle alignment defects. Importantly, removal of one copy of ballchen or l(2)gl suppresses Ankle2 mutant phenotypes and restores viability and brain size. Human mutational studies implicate the above-mentioned genes in microcephaly and motor neuron disease. We suggest that NS4A, ANKLE2, VRK1, and LLGL1 define a pathway impinging on asymmetric determinants of neural stem cell division.
Keywords: Animals; Asymmetric Cell Division; Cell Division; Cell Polarity; Drosophila melanogaster; Humans; Membrane Proteins; Microcephaly; Mutation; Neural Stem Cells; Neurons; Nuclear Proteins; Zika Virus

Neurodevelopmental disorder with dysmorphic facies and distal limb anomalies syndrome due to disruption of BPTF in a 35-year-old man initially diagnosed with Silver-Russell syndrome. - Midro, Alina T; Tommerup, Niels; Borys, Jan; Panasiuk, Barbara; Kosztyła-Hojna, Bożena; Zalewska, Renata; Konstantynowicz, Jerzy; Łebkowska, Urszula; Cooper, Lance; Steven E Scherer; Mehrjouy, Manna M; Liu, Qian; et al. (Clin Genet, 2019)
Keywords: Abnormalities, Multiple; Adult; Diagnosis, Differential; Facies; Humans; Male; Musculoskeletal Abnormalities; Neurodevelopmental Disorders; Phenotype; Radiography; Silver-Russell Syndrome; Syndrome

A nonhuman primate model of inherited retinal disease. - Moshiri, Ala; Rui Chen; Kim, Soohyun; R. Alan Harris; Yumei Li; Raveendran, Muthuswamy; Davis, Sarah; Liang, Qingnan; Pomerantz, Ori; Wang, Jun; Garzel, Laura; Cameron, Ashley; et al. (J Clin Invest, 2019)
Inherited retinal degenerations are a common cause of untreatable blindness worldwide, with retinitis pigmentosa and cone dystrophy affecting approximately 1 in 3500 and 1 in 10,000 individuals, respectively. A major limitation to the development of effective therapies is the lack of availability of animal models that fully replicate the human condition. Particularly for cone disorders, rodent, canine, and feline models with no true macula have substantive limitations. By contrast, the cone-rich macula of a nonhuman primate (NHP) closely mirrors that of the human retina. Consequently, well-defined NHP models of heritable retinal diseases, particularly cone disorders that are predictive of human conditions, are necessary to more efficiently advance new therapies for patients. We have identified 4 related NHPs at the California National Primate Research Center with visual impairment and findings from clinical ophthalmic examination, advanced retinal imaging, and electrophysiology consistent with achromatopsia. Genetic sequencing confirmed a homozygous R565Q missense mutation in the catalytic domain of PDE6C, a cone-specific phototransduction enzyme associated with achromatopsia in humans. Biochemical studies demonstrate that the mutant mRNA is translated into a stable protein that displays normal cellular localization but is unable to hydrolyze cyclic GMP (cGMP). This NHP model of a cone disorder will not only serve as a therapeutic testing ground for achromatopsia gene replacement, but also for optimization of gene editing in the macula and of cone cell replacement in general.
Keywords: Amino Acid Substitution; Animals; Color Vision Defects; Cone Dystrophy; Cyclic Nucleotide Phosphodiesterases, Type 6; Disease Models, Animal; Eye Proteins; Female; HEK293 Cells; Humans; Macaca mulatta; Male; Mutation, Missense; Retinitis Pigmentosa

A novel disorder involving dyshematopoiesis, inflammation, and HLH due to aberrant CDC42 function. - Lam, Michael T; Coppola, Simona; Krumbach, Oliver H F; Prencipe, Giusi; Insalaco, Antonella; Cifaldi, Cristina; Brigida, Immacolata; Zara, Erika; Scala, Serena; Di Cesare, Silvia; Martinelli, Simone; Di Rocco, Martina; et al. (J Exp Med, 2019)
Hemophagocytic lymphohistiocytosis (HLH) is characterized by immune dysregulation due to inadequate restraint of overactivated immune cells and is associated with a variable clinical spectrum having overlap with more common pathophysiologies. HLH is difficult to diagnose and can be part of inflammatory syndromes. Here, we identify a novel hematological/autoinflammatory condition (NOCARH syndrome) in four unrelated patients with superimposable features, including neonatal-onset cytopenia with dyshematopoiesis, autoinflammation, rash, and HLH. Patients shared the same de novo mutation (Chr1:22417990C>T, p.R186C) and altered hematopoietic compartment, immune dysregulation, and inflammation. mutations had been associated with syndromic neurodevelopmental disorders. In vitro and in vivo assays documented unique effects of p.R186C on CDC42 localization and function, correlating with the distinctiveness of the trait. Emapalumab was critical to the survival of one patient, who underwent successful bone marrow transplantation. Early recognition of the disorder and establishment of treatment followed by bone marrow transplant are important to survival.
Keywords: Alleles; Amino Acid Substitution; Animals; Binding Sites; cdc42 GTP-Binding Protein; Cell Line, Tumor; Child; Disease Susceptibility; Female; Genetic Association Studies; Genotype; Humans; Infant; Lymphohistiocytosis, Hemophagocytic; Male; Mice; Models, Molecular; Molecular Conformation; Mutation; Phenotype; Protein Binding

Paralog Studies Augment Gene Discovery: DDX and DHX Genes. - Paine, Ingrid; Posey, Jennifer E; Grochowski, Christopher M; Jhangiani, Shalini N; Rosenheck, Sarah; Kleyner, Robert; Marmorale, Taylor; Yoon, Margaret; Wang, Kai; Robison, Reid; Cappuccio, Gerarda; Pinelli, Michele; et al. (Am J Hum Genet, 2019)
Members of a paralogous gene family in which variation in one gene is known to cause disease are eight times more likely to also be associated with human disease. Recent studies have elucidated DHX30 and DDX3X as genes for which pathogenic variant alleles are involved in neurodevelopmental disorders. We hypothesized that variants in paralogous genes encoding members of the DExD/H-box RNA helicase superfamily might also underlie developmental delay and/or intellectual disability (DD and/or ID) disease phenotypes. Here we describe 15 unrelated individuals who have DD and/or ID, central nervous system (CNS) dysfunction, vertebral anomalies, and dysmorphic features and were found to have probably damaging variants in DExD/H-box RNA helicase genes. In addition, these individuals exhibit a variety of other tissue and organ system involvement including ocular, outer ear, hearing, cardiac, and kidney tissues. Five individuals with homozygous (one), compound-heterozygous (two), or de novo (two) missense variants in DHX37 were identified by exome sequencing. We identified ten total individuals with missense variants in three other DDX/DHX paralogs: DHX16 (four individuals), DDX54 (three individuals), and DHX34 (three individuals). Most identified variants are rare, predicted to be damaging, and occur at conserved amino acid residues. Taken together, these 15 individuals implicate the DExD/H-box helicases in both dominantly and recessively inherited neurodevelopmental phenotypes and highlight the potential for more than one disease mechanism underlying these disorders.
Keywords: DEAD-box RNA Helicases; Exome Sequencing; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Male; Mutation, Missense; Neoplasm Proteins; Neurodevelopmental Disorders; Pedigree; RNA Helicases

PHENOTYPIC VARIABILITY OF RECESSIVE RDH12-ASSOCIATED RETINAL DYSTROPHY. - Zou, Xuan; Fu, Qing; Fang, Sha; Li, Hui; Ge, Zhongqi; Yang, Lizhu; Xu, Mingchu; Sun, Zixi; Li, Huajin; Yumei Li; Dong, Fangtian; Rui Chen; et al. (Retina, 2019)
PURPOSE: To characterize the phenotypic variability and report the genetic defects in a cohort of Chinese patients with biallelic variants of the retinol dehydrogenase 12 (RDH12) gene. METHODS: The study included 38 patients from 38 unrelated families with biallelic pathogenic RDH12 variants. Systematic next-generation sequencing data analysis, Sanger sequencing validation, and segregation analysis were used to identify the pathogenic mutations. Detailed ophthalmic examinations, including electroretinogram, fundus photography, fundus autofluorescence and optical coherence tomography, and statistical analysis were performed to evaluate phenotype variability. RESULTS: Twenty-five different mutations of RDH12 were identified in the 38 families. Six of these variants were novel. Val146Asp was observed at the highest frequency (23.7%), and it was followed by Arg62Ter (14.5%) and Thr49Met (9.2%). Twenty-three probands were diagnosed with early-onset severe retinal dystrophy, 6 with Leber congenital amaurosis, 7 with autosomal recessive retinitis pigmentosa, and 2 with cone-rod dystrophy. Self-reported nyctalopia occurred in about a half of patients (55.3%) and was significantly more common among older patients (P < 0.01). Nyctalopia was not significantly associated with best-corrected visual acuity (P = 0.72), but older patients had significantly greater best-corrected visual acuity loss (P < 0.01). Only 15.8% of the patients had nystagmus, which was significantly more likely to occur among 36.8% of the patients with hyperopia >3D (P < 0.01) and/or in cases of reduced best-corrected visual acuity (P = 0.01), but was not associated with age (P = 0.87). CONCLUSION: Several high-frequency RDH12 variants were identified in patients with inherited retinal dystrophies, most of which were missense mutations. Variable but characteristic phenotypes of a progressive nature was observed. Overall, the findings indicated that biallelic RDH12 mutations are a common cause of early-onset retinal dystrophy and a rare cause of cone-rod dystrophy.
Keywords: Adolescent; Adult; Alcohol Oxidoreductases; Biological Variation, Population; Child; Child, Preschool; DNA Mutational Analysis; Electroretinography; Eye Diseases, Hereditary; Female; Genotype; Humans; Male; Middle Aged; Mutation; Pedigree; Phenotype; Retinal Dystrophies; Visual Acuity; Young Adult

Prospective virome analyses in young children at increased genetic risk for type 1 diabetes. - Vehik, Kendra; Lynch, Kristian F; Wong, Matthew C; Tian, Xiangjun; Ross, Matthew C; Richard A Gibbs; Ajami, Nadim J; Petrosino, Joseph F; Rewers, Marian; Toppari, Jorma; Ziegler, Anette G; She, Jin-Xiong; et al. (Nat Med, 2019)
Viruses are implicated in autoimmune destruction of pancreatic islet β cells, which results in insulin deficiency and type 1 diabetes (T1D). Certain enteroviruses can infect β cells in vitro, have been detected in the pancreatic islets of patients with T1D and have shown an association with T1D in meta-analyses. However, establishing consistency in findings across studies has proven difficult. Obstacles to convincingly linking RNA viruses to islet autoimmunity may be attributed to rapid viral mutation rates, the cyclical periodicity of viruses and the selection of variants with altered pathogenicity and ability to spread in populations. β cells strongly express cell-surface coxsackie and adenovirus receptor (CXADR) genes, which can facilitate enterovirus infection. Studies of human pancreata and cultured islets have shown significant variation in enteroviral virulence to β cells between serotypes and within the same serotype. In this large-scale study of known eukaryotic DNA and RNA viruses in stools from children, we evaluated fecally shed viruses in relation to islet autoimmunity and T1D. This study showed that prolonged enterovirus B rather than independent, short-duration enterovirus B infections may be involved in the development of islet autoimmunity, but not T1D, in some young children. Furthermore, we found that fewer early-life human mastadenovirus C infections, as well as CXADR rs6517774, independently correlated with islet autoimmunity.
Keywords: Adolescent; Autoimmunity; Child; Child, Preschool; Diabetes Mellitus, Type 1; Enterovirus; Feces; Female; Humans; Infant; Insulin; Insulin-Secreting Cells; Islets of Langerhans; Male; Pancreas; RNA, Viral

Protein-coding variants implicate novel genes related to lipid homeostasis contributing to body-fat distribution. - Justice, Anne E; Karaderi, Tugce; Highland, Heather M; Young, Kristin L; Graff, Mariaelisa; Lu, Yingchang; Turcot, Valérie; Auer, Paul L; Fine, Rebecca S; Guo, Xiuqing; Schurmann, Claudia; Lempradl, Adelheid; et al. (Nat Genet, 2019)
Body-fat distribution is a risk factor for adverse cardiovascular health consequences. We analyzed the association of body-fat distribution, assessed by waist-to-hip ratio adjusted for body mass index, with 228,985 predicted coding and splice site variants available on exome arrays in up to 344,369 individuals from five major ancestries (discovery) and 132,177 European-ancestry individuals (validation). We identified 15 common (minor allele frequency, MAF ≥5%) and nine low-frequency or rare (MAF <5%) coding novel variants. Pathway/gene set enrichment analyses identified lipid particle, adiponectin, abnormal white adipose tissue physiology and bone development and morphology as important contributors to fat distribution, while cross-trait associations highlight cardiometabolic traits. In functional follow-up analyses, specifically in Drosophila RNAi-knockdowns, we observed a significant increase in the total body triglyceride levels for two genes (DNAH10 and PLXND1). We implicate novel genes in fat distribution, stressing the importance of interrogating low-frequency and protein-coding variants.
Keywords: Animals; Body Fat Distribution; Body Mass Index; Case-Control Studies; Drosophila; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeostasis; Humans; Lipids; Male; Proteins; Risk Factors; Waist-Hip Ratio

Rare variants in SLC5A10 are associated with serum 1,5-anhydroglucitol (1,5-AG) in the Atherosclerosis Risk in Communities (ARIC) Study. - Loomis, Stephanie J; Köttgen, Anna; Li, Man; Tin, Adrienne; Coresh, Josef; Eric Boerwinkle; Richard A Gibbs; Donna M Muzny; Pankow, James; Selvin, Elizabeth; Duggal, Priya (Sci Rep, 2019)
Serum 1,5-anhydroglucitol (1,5-AG) is an emerging biomarker used to monitor glycemic control in persons with diabetes. We performed whole-exome sequencing, examining the association between rare, coding genetic variants and 1,5-AG among European ancestry (N = 6,589) and African ancestry (N = 2,309) participants without diagnosed diabetes in the Atherosclerosis Risk in Communities (ARIC) Study. Five variants representing 3 independent signals on chromosome 17 in SLC5A10, a glucose transporter not previously known to transport 1,5-AG, were associated with 1,5-AG levels up to 10.38 µg/mL lower per allele (1,5-AG range 3.4-32.8 µg/mL) in the European ancestry sample and validated in the African ancestry sample. Together these variants explained 6% of the variance in 1,5-AG. Two of these variants (rs61741107, p = 8.85E-56; rs148178887, p = 1.13E-36) were rare, nonsynonymous, and predicted to be damaging or deleterious by multiple algorithms. Gene-based SKAT-O analysis supported these results (SLC5A10 p = 5.13E-64 in European ancestry, validated in African ancestry, p = 0.006). Interestingly, these novel variants are not associated with other biomarkers of hyperglycemia or diabetes (p > 0.2). The large effect sizes and protein-altering, multiple independent signals suggest SLC5A10 may code for an important transporter of 1,5-AG in the kidney, with a potential nonglucose-related effect on 1,5-AG, impacting its clinical utility as a diabetes biomarker in this subpopulation.
Keywords: Atherosclerosis; Deoxyglucose; Exome Sequencing; Female; Humans; Longitudinal Studies; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Sodium-Glucose Transport Proteins

Subtle changes in chromatin loop contact propensity are associated with differential gene regulation and expression. - Greenwald, William W; Li, He; Benaglio, Paola; Jakubosky, David; Matsui, Hiroko; Schmitt, Anthony; Selvaraj, Siddarth; D'Antonio, Matteo; D'Antonio-Chronowska, Agnieszka; Smith, Erin N; Frazer, Kelly A (Nat Commun, 2019)
While genetic variation at chromatin loops is relevant for human disease, the relationships between contact propensity (the probability that loci at loops physically interact), genetics, and gene regulation are unclear. We quantitatively interrogate these relationships by comparing Hi-C and molecular phenotype data across cell types and haplotypes. While chromatin loops consistently form across different cell types, they have subtle quantitative differences in contact frequency that are associated with larger changes in gene expression and H3K27ac. For the vast majority of loci with quantitative differences in contact frequency across haplotypes, the changes in magnitude are smaller than those across cell types; however, the proportional relationships between contact propensity, gene expression, and H3K27ac are consistent. These findings suggest that subtle changes in contact propensity have a biologically meaningful role in gene regulation and could be a mechanism by which regulatory genetic variants in loop anchors mediate effects on expression.
Keywords: Adolescent; Adult; Aged; Cell Line; Chromatin; DNA; Female; Gene Expression Regulation; Histones; Humans; Induced Pluripotent Stem Cells; Male; Middle Aged; Myocytes, Cardiac; Nucleic Acid Conformation; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Whole Genome Sequencing; Young Adult

TBX6-associated congenital scoliosis (TACS) as a clinically distinguishable subtype of congenital scoliosis: further evidence supporting the compound inheritance and TBX6 gene dosage model. - Liu, Jiaqi; Wu, Nan; Yang, Nan; Takeda, Kazuki; Chen, Weisheng; Li, Weiyu; Du, Renqian; Liu, Sen; Zhou, Yangzhong; Zhang, Ling; Liu, Zhenlei; Zuo, Yuzhi; et al. (Genet Med, 2019)
PURPOSE: To characterize clinically measurable endophenotypes, implicating the TBX6 compound inheritance model. METHODS: Patients with congenital scoliosis (CS) from China(N = 345, cohort 1), Japan (N = 142, cohort 2), and the United States (N = 10, cohort 3) were studied. Clinically measurable endophenotypes were compared according to the TBX6 genotypes. A mouse model for Tbx6 compound inheritance (N = 52) was investigated by micro computed tomography (micro-CT). A clinical diagnostic algorithm (TACScore) was developed to assist in clinical recognition of TBX6-associated CS (TACS). RESULTS: In cohort 1, TACS patients (N = 33) were significantly younger at onset than the remaining CS patients (P = 0.02), presented with one or more hemivertebrae/butterfly vertebrae (P = 4.9 × 10), and exhibited vertebral malformations involving the lower part of the spine (T8-S5, P = 4.4 × 10); observations were confirmed in two replication cohorts. Simple rib anomalies were prevalent in TACS patients (P = 3.1 × 10), while intraspinal anomalies were uncommon (P = 7.0 × 10). A clinically usable TACScore was developed with an area under the curve (AUC) of 0.9 (P = 1.6 × 10). A Tbx6 mouse model supported that a gene dosage effect underlies the TACS phenotype. CONCLUSION: TACS is a clinically distinguishable entity with consistent clinically measurable endophenotypes. The type and distribution of vertebral column abnormalities in TBX6/Tbx6 compound inheritance implicate subtle perturbations in gene dosage as a cause of spine developmental birth defects responsible for about 10% of CS.
Keywords: Animals; Cohort Studies; Disease Models, Animal; Gene Dosage; Humans; Inheritance Patterns; Mice; Models, Genetic; Scoliosis; Spine; T-Box Domain Proteins

Transcriptomic profiles of retinal ganglion cells are defined by the magnitude of intraocular pressure elevation in adult mice. - Park, Yong H; Snook, Joshua D; Ostrin, Edwin J; Kim, Sangbae; Rui Chen; Frankfort, Benjamin J (Sci Rep, 2019)
Elevated intraocular pressure (IOP) is the major risk factor for glaucoma, a sight threatening disease of retinal ganglion cells (RGCs) and their axons. Despite the central importance of IOP, details of the impact of IOP elevation on RGC gene expression remain elusive. We developed a 4-step immunopanning protocol to extract adult mouse RGCs with high fidelity and used it to isolate RGCs from wild type mice exposed to 2 weeks of IOP elevation generated by the microbead model. IOP was elevated to 2 distinct levels which were defined as Mild (IOP increase >1 mmHg and <4 mmHg) and Moderate (IOP increase ≥4 mmHg). RNA sequencing was used to compare the transcriptional environment at each IOP level. Differentially expressed genes were markedly different between the 2 groups, and pathway analysis revealed frequently opposed responses between the IOP levels. These results suggest that the magnitude of IOP elevation has a critical impact on RGC transcriptional changes. Furthermore, it is possible that IOP-based set points exist within RGCs to impact the direction of transcriptional change. It is possible that this improved understanding of changes in RGC gene expression can ultimately lead to novel diagnostics and therapeutics for glaucoma.
Keywords: Animals; Biomarkers; Disease Models, Animal; Female; Glaucoma; Intraocular Pressure; Male; Mice; Mice, Inbred C57BL; Retinal Ganglion Cells; Sequence Analysis, RNA; Transcriptome

Use of >100,000 NHLBI Trans-Omics for Precision Medicine (TOPMed) Consortium whole genome sequences improves imputation quality and detection of rare variant associations in admixed African and Hispanic/Latino populations. - Kowalski, Madeline H; Qian, Huijun; Hou, Ziyi; Rosen, Jonathan D; Tapia, Amanda L; Shan, Yue; Jain, Deepti; Argos, Maria; Arnett, Donna K; Avery, Christy; Barnes, Kathleen C; Becker, Lewis C; et al. (PLoS Genet, 2019)
Most genome-wide association and fine-mapping studies to date have been conducted in individuals of European descent, and genetic studies of populations of Hispanic/Latino and African ancestry are limited. In addition, these populations have more complex linkage disequilibrium structure. In order to better define the genetic architecture of these understudied populations, we leveraged >100,000 phased sequences available from deep-coverage whole genome sequencing through the multi-ethnic NHLBI Trans-Omics for Precision Medicine (TOPMed) program to impute genotypes into admixed African and Hispanic/Latino samples with genome-wide genotyping array data. We demonstrated that using TOPMed sequencing data as the imputation reference panel improves genotype imputation quality in these populations, which subsequently enhanced gene-mapping power for complex traits. For rare variants with minor allele frequency (MAF) < 0.5%, we observed a 2.3- to 6.1-fold increase in the number of well-imputed variants, with 11-34% improvement in average imputation quality, compared to the state-of-the-art 1000 Genomes Project Phase 3 and Haplotype Reference Consortium reference panels. Impressively, even for extremely rare variants with minor allele count <10 (including singletons) in the imputation target samples, average information content rescued was >86%. Subsequent association analyses of TOPMed reference panel-imputed genotype data with hematological traits (hemoglobin (HGB), hematocrit (HCT), and white blood cell count (WBC)) in ~21,600 African-ancestry and ~21,700 Hispanic/Latino individuals identified associations with two rare variants in the HBB gene (rs33930165 with higher WBC [p = 8.8x10-15] in African populations, rs11549407 with lower HGB [p = 1.5x10-12] and HCT [p = 8.8x10-10] in Hispanics/Latinos). By comparison, neither variant would have been genome-wide significant if either 1000 Genomes Project Phase 3 or Haplotype Reference Consortium reference panels had been used for imputation. Our findings highlight the utility of the TOPMed imputation reference panel for identification of novel rare variant associations not previously detected in similarly sized genome-wide studies of under-represented African and Hispanic/Latino populations.
Keywords: Adult; Aged; Aged, 80 and over; beta-Globins; Black or African American; Computational Biology; Databases, Genetic; Female; Gene Frequency; Genetic Predisposition to Disease; Genetics, Population; Genome-Wide Association Study; Genotyping Techniques; Hispanic or Latino; Humans; Linkage Disequilibrium; Male; Middle Aged; Precision Medicine; United States; Whole Genome Sequencing

VCPA: genomic variant calling pipeline and data management tool for Alzheimer's Disease Sequencing Project. - Leung, Yuk Yee; Valladares, Otto; Chou, Yi-Fan; Lin, Han-Jen; Kuzma, Amanda B; Cantwell, Laura; Qu, Liming; Gangadharan, Prabhakaran; Salerno, William J; Schellenberg, Gerard D; Wang, Li-San (Bioinformatics, 2019)
SUMMARY: We report VCPA, our SNP/Indel Variant Calling Pipeline and data management tool used for the analysis of whole genome and exome sequencing (WGS/WES) for the Alzheimer's Disease Sequencing Project. VCPA consists of two independent but linkable components: pipeline and tracking database. The pipeline, implemented using the Workflow Description Language and fully optimized for the Amazon elastic compute cloud environment, includes steps from aligning raw sequence reads to variant calling using GATK. The tracking database allows users to view job running status in real time and visualize >100 quality metrics per genome. VCPA is functionally equivalent to the CCDG/TOPMed pipeline. Users can use the pipeline and the dockerized database to process large WGS/WES datasets on Amazon cloud with minimal configuration. AVAILABILITY AND IMPLEMENTATION: VCPA is released under the MIT license and is available for academic and nonprofit use for free. The pipeline source code and step-by-step instructions are available from the National Institute on Aging Genetics of Alzheimer's Disease Data Storage Site (http://www.niagads.org/VCPA). SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Alzheimer Disease; Data Management; Genomics; High-Throughput Nucleotide Sequencing; Humans; Software

Whole-Organ Genomic Characterization of Mucosal Field Effects Initiating Bladder Carcinogenesis. - Majewski, Tadeusz; Yao, Hui; Bondaruk, Jolanta; Chung, Woonbok; Lee, Sangkyou; Lee, June Goo; Zhang, Shizhen; Cogdell, David; Yang, Guoliang; Choi, Woonyoung; Dinney, Colin; Grossman, H Barton; et al. (Cell Rep, 2019)
We used whole-organ mapping to study the locoregional molecular changes in a human bladder containing multifocal cancer. Widespread DNA methylation changes were identified in the entire mucosa, representing the initial field effect. The field effect was associated with subclonal low-allele frequency mutations and a small number of DNA copy alterations. A founder mutation in the RNA splicing gene, ACIN1, was identified in normal mucosa and expanded clonally with an additional 21 mutations in progression to carcinoma. The patterns of mutations and copy number changes in carcinoma in situ and foci of carcinoma were almost identical, confirming their clonal origins. The pathways affected by the DNA copy alterations and mutations, including the Kras pathway, were preceded by the field changes in DNA methylation, suggesting that they reinforced mechanisms that had already been initiated by methylation. The results demonstrate that DNA methylation can serve as the initiator of bladder carcinogenesis.
Keywords: Carcinogenesis; Carcinoma; Clonal Evolution; DNA Methylation; Genome, Human; Humans; Male; Middle Aged; Mucous Membrane; Mutation; Nuclear Proteins; Urinary Bladder Neoplasms; Urothelium

Accurate detection of complex structural variations using single-molecule sequencing. - Sedlazeck, Fritz J; Rescheneder, Philipp; Smolka, Moritz; Fang, Han; Nattestad, Maria; von Haeseler, Arndt; Schatz, Michael C (Nat Methods, 2018)
Structural variations are the greatest source of genetic variation, but they remain poorly understood because of technological limitations. Single-molecule long-read sequencing has the potential to dramatically advance the field, although high error rates are a challenge with existing methods. Addressing this need, we introduce open-source methods for long-read alignment (NGMLR; https://github.com/philres/ngmlr ) and structural variant identification (Sniffles; https://github.com/fritzsedlazeck/Sniffles ) that provide unprecedented sensitivity and precision for variant detection, even in repeat-rich regions and for complex nested events that can have substantial effects on human health. In several long-read datasets, including healthy and cancerous human genomes, we discovered thousands of novel variants and categorized systematic errors in short-read approaches. NGMLR and Sniffles can automatically filter false events and operate on low-coverage data, thereby reducing the high costs that have hindered the application of long reads in clinical and research settings.
Keywords: DNA Mutational Analysis; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA

Allele-specific epigenome maps reveal sequence-dependent stochastic switching at regulatory loci. - Onuchic, Vitor; Lurie, Eugene; Carrero, Ivenise; Pawliczek, Piotr; Patel, Ronak Y; Rozowsky, Joel; Galeev, Timur; Huang, Zhuoyi; Altshuler, Robert C; Zhang, Zhizhuo; R. Alan Harris; Coarfa, Cristian; et al. (Science, 2018)
To assess the impact of genetic variation in regulatory loci on human health, we constructed a high-resolution map of allelic imbalances in DNA methylation, histone marks, and gene transcription in 71 epigenomes from 36 distinct cell and tissue types from 13 donors. Deep whole-genome bisulfite sequencing of 49 methylomes revealed sequence-dependent CpG methylation imbalances at thousands of heterozygous regulatory loci. Such loci are enriched for stochastic switching, which is defined as random transitions between fully methylated and unmethylated states of DNA. The methylation imbalances at thousands of loci are explainable by different relative frequencies of the methylated and unmethylated states for the two alleles. Further analyses provided a unifying model that links sequence-dependent allelic imbalances of the epigenome, stochastic switching at gene regulatory loci, and disease-associated genetic variation.
Keywords: Alleles; Allelic Imbalance; Binding Sites; CpG Islands; Disease; DNA Methylation; Epigenesis, Genetic; Gene Regulatory Networks; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Sulfites; Transcription Factors

Allelic decomposition and exact genotyping of highly polymorphic and structurally variant genes. - Numanagić, Ibrahim; Malikić, Salem; Ford, Michael; Qin, Xiang; Toji, Lorraine; Radovich, Milan; Skaar, Todd C; Pratt, Victoria M; Berger, Bonnie; Scherer, Steve; Sahinalp, S Cenk (Nat Commun, 2018)
High-throughput sequencing provides the means to determine the allelic decomposition for any gene of interest-the number of copies and the exact sequence content of each copy of a gene. Although many clinically and functionally important genes are highly polymorphic and have undergone structural alterations, no high-throughput sequencing data analysis tool has yet been designed to effectively solve the full allelic decomposition problem. Here we introduce a combinatorial optimization framework that successfully resolves this challenging problem, including for genes with structural alterations. We provide an associated computational tool Aldy that performs allelic decomposition of highly polymorphic, multi-copy genes through using whole or targeted genome sequencing data. For a large diverse sequencing data set, Aldy identifies multiple rare and novel alleles for several important pharmacogenes, significantly improving upon the accuracy and utility of current genotyping assays. As more data sets become available, we expect Aldy to become an essential component of genotyping toolkits.
Keywords: Alleles; Chromosome Mapping; Cytochrome P-450 CYP2D6; DNA Copy Number Variations; Genome, Human; Genotype; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Isoenzymes; Phenotype; Polymorphism, Genetic; Sequence Analysis, DNA; Software

CD163+ macrophages promote angiogenesis and vascular permeability accompanied by inflammation in atherosclerosis. - Guo, Liang; Akahori, Hirokuni; Harari, Emanuel; Smith, Samantha L; Polavarapu, Rohini; Karmali, Vinit; Otsuka, Fumiyuki; Gannon, Rachel L; Braumann, Ryan E; Dickinson, Megan H; Gupta, Anuj; Jenkins, Audrey L; et al. (J Clin Invest, 2018)
Intake of hemoglobin by the hemoglobin-haptoglobin receptor CD163 leads to a distinct alternative non-foam cell antiinflammatory macrophage phenotype that was previously considered atheroprotective. Here, we reveal an unexpected but important pathogenic role for these macrophages in atherosclerosis. Using human atherosclerotic samples, cultured cells, and a mouse model of advanced atherosclerosis, we investigated the role of intraplaque hemorrhage on macrophage function with respect to angiogenesis, vascular permeability, inflammation, and plaque progression. In human atherosclerotic lesions, CD163+ macrophages were associated with plaque progression, microvascularity, and a high level of HIF1α and VEGF-A expression. We observed irregular vascular endothelial cadherin in intraplaque microvessels surrounded by CD163+ macrophages. Within these cells, activation of HIF1α via inhibition of prolyl hydroxylases promoted VEGF-mediated increases in intraplaque angiogenesis, vascular permeability, and inflammatory cell recruitment. CD163+ macrophages increased intraplaque endothelial VCAM expression and plaque inflammation. Subjects with homozygous minor alleles of the SNP rs7136716 had elevated microvessel density, increased expression of CD163 in ruptured coronary plaques, and a higher risk of myocardial infarction and coronary heart disease in population cohorts. Thus, our findings highlight a nonlipid-driven mechanism by which alternative macrophages promote plaque angiogenesis, leakiness, inflammation, and progression via the CD163/HIF1α/VEGF-A pathway.
Keywords: Adult; Animals; Antigens, CD; Antigens, Differentiation, Myelomonocytic; Atherosclerosis; Coronary Disease; Coronary Vessels; Disease Progression; Female; Hemoglobins; Humans; Inflammation; Macrophages; Male; Mice; Mice, Inbred C57BL; Middle Aged; Myocardial Infarction; Neovascularization, Pathologic; Oxidative Stress; Permeability; Phenotype; Polymorphism, Single Nucleotide; Receptors, Cell Surface; Signal Transduction

Challenges of Francisella classification exemplified by an atypical clinical isolate. - Matz, L M; Kamdar, K Y; Holder, M E; Metcalf, G A; Weissenberger, G M; Meng, Q; Vee, V; Han, Y; Muzny, D M; Gibbs, R A; Johnson, C L; Revell, P A; et al. (Diagn Microbiol Infect Dis, 2018)
The accumulation of sequenced Francisella strains has made it increasingly apparent that the 16S rRNA gene alone is not enough to stratify the Francisella genus into precise and clinically useful classifications. Continued whole-genome sequencing of isolates will provide a larger base of knowledge for targeted approaches with broad applicability. Additionally, examination of genomic information on a case-by-case basis will help resolve outstanding questions regarding strain stratification. We report the complete genome sequence of a clinical isolate, designated here as F. novicida-like strain TCH2015, acquired from the lymph node of a 6-year-old male. Two features were atypical for F. novicida: exhibition of functional oxidase activity and additional gene content, including proposed virulence determinants. These differences, which could potentially impact virulence and clinical diagnosis, emphasize the need for more comprehensive methods to profile Francisella isolates. This study highlights the value of whole-genome sequencing, which will lead to a more robust database of environmental and clinical genomes and inform strategies to improve detection and classification of Francisella strains.
Keywords: Child; DNA, Bacterial; Francisella; Genes, Bacterial; Genetic Variation; Genome, Bacterial; Genotype; Humans; Lymph Nodes; Male; Oxidoreductases; Sequence Analysis, DNA; Tularemia; Virulence Factors; Whole Genome Sequencing

The coexistence of copy number variations (CNVs) and single nucleotide polymorphisms (SNPs) at a locus can result in distorted calculations of the significance in associating SNPs to disease. - Liu, Jiaqi; Zhou, Yangzhong; Liu, Sen; Song, Xiaofei; Yang, Xin-Zhuang; Fan, Yanhui; Chen, Weisheng; Akdemir, Zeynep Coban; Yan, Zihui; Zuo, Yuzhi; Du, Renqian; Liu, Zhenlei; et al. (Hum Genet, 2018)
With the recent advance in genome-wide association studies (GWAS), disease-associated single nucleotide polymorphisms (SNPs) and copy number variants (CNVs) have been extensively reported. Accordingly, the issue of incorrect identification of recombination events that can induce the distortion of multi-allelic or hemizygous variants has received more attention. However, the potential distorted calculation bias or significance of a detected association in a GWAS due to the coexistence of CNVs and SNPs in the same genomic region may remain under-recognized. Here we performed the association study within a congenital scoliosis (CS) cohort whose genetic etiology was recently elucidated as a compound inheritance model, including mostly one rare variant deletion CNV null allele and one common variant non-coding hypomorphic haplotype of the TBX6 gene. We demonstrated that the existence of a deletion in TBX6 led to an overestimation of the contribution of the SNPs on the hypomorphic allele. Furthermore, we generalized a model to explain the calculation bias, or distorted significance calculation for an association study, that can be 'induced' by CNVs at a locus. Meanwhile, overlapping between the disease-associated SNPs from published GWAS and common CNVs (overlap 10%) and pathogenic/likely pathogenic CNVs (overlap 99.69%) was significantly higher than the random distribution (p < 1 × 10 and p = 0.034, respectively), indicating that such co-existence of CNV and SNV alleles might generally influence data interpretation and potential outcomes of a GWAS. We also verified and assessed the influence of colocalizing CNVs to the detection sensitivity of disease-associated SNP variant alleles in another adolescent idiopathic scoliosis (AIS) genome-wide association study. We proposed that detecting co-existent CNVs when evaluating the association signals between SNPs and disease traits could improve genetic model analyses and better integrate GWAS with robust Mendelian principles.
Keywords: Adolescent; Congenital Abnormalities; DNA Copy Number Variations; Female; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genomics; Genotype; Haplotypes; Humans; Phenotype; Polymorphism, Single Nucleotide; Scoliosis

Comparison of vitamin D metabolites in wild and captive baboons. - Ziegler, Toni E; Kapoor, Amita; Binkley, Neil C; Rice, Karen S; Jeffrey Rogers; Jolly, Clifford J; Phillips-Conroy, Jane E (Am J Primatol, 2018)
Vitamin D adequacy is essential for multiple physiologic processes. With limited exposure to sunlight for vitamin D synthesis, captive primates are supplemented with vitamin D (cholecalciferol). Vitamin D metabolite data from wild primates living indigenously could suggest optimum levels. The purpose of this study was to: 1) to explore whether baboons, a speciose genus whose members have significant exposed skin, coat color variation and wide geographical distribution, mirrors the skin pigmentation-vitamin D relationship found in humans; 2) compare vitamin D metabolite levels in wild and captive members of the same or similar baboon species; and 3) apply a recently developed method currently used in humans for measuring multiple vitamin D metabolites as a panel to explore if/how these metabolites can inform us on vitamin D sufficiency. Serum samples from males of three baboon species in the wild: Papio anubis (olive baboon, dark exposed skin), P. cynocephalus (yellow baboon, brown exposed skin), and P. hamadryas (hamadryas baboon, pink exposed skin), were compared with vitamin D supplemented captive olive baboons with sun exposure. Liquid chromatography/tandem mass spectrometry (LC/MS/MS) measured vitamin D and its main metabolites. Cholecalciferol, 25 hydroxyvitamin D (25(OH)D ), and 24,25 dihydroxyvitamin D (24,25(OH) D ), showed significant differences by species. The levels of cholecalciferol due to supplements in the captive olive baboons did not convert to higher 25(OH)D while the wild olive baboons exhibited the lowest levels for both cholecalciferol and 25(OH)D . Further metabolic conversion of 25(OH)D to 24,25(OH) D indicated that all baboons had more similar conversion ratios and these were within the same range found for humans that are depicted as having adequate vitamin D levels. This study provided evidence that exposed skin color does influence vitamin D3 levels, with lower levels in darker skinned species, but these differences are eliminated in the downstream metabolite conversion indicating strong regulatory control.
Keywords: Africa South of the Sahara; Aging; Animal Distribution; Animals; Animals, Wild; Animals, Zoo; Dietary Supplements; Male; Papio; Skin Pigmentation; Species Specificity; Vitamin D; Vitamin D Deficiency

Comprehensive Characterization of Cancer Driver Genes and Mutations. - Bailey, Matthew H; Tokheim, Collin; Porta-Pardo, Eduard; Sengupta, Sohini; Bertrand, Denis; Weerasinghe, Amila; Colaprico, Antonio; Wendl, Michael C; Kim, Jaegil; Reardon, Brendan; Ng, Patrick Kwok-Shing; Jeong, Kang Jin; et al. (Cell, 2018)
Identifying molecular cancer drivers is critical for precision oncology. Multiple advanced algorithms to identify drivers now exist, but systematic attempts to combine and optimize them on large datasets are few. We report a PanCancer and PanSoftware analysis spanning 9,423 tumor exomes (comprising all 33 of The Cancer Genome Atlas projects) and using 26 computational tools to catalog driver genes and mutations. We identify 299 driver genes with implications regarding their anatomical sites and cancer/cell types. Sequence- and structure-based analyses identified >3,400 putative missense driver mutations supported by multiple lines of evidence. Experimental validation confirmed 60%-85% of predicted mutations as likely drivers. We found that >300 MSI tumors are associated with high PD-1/PD-L1, and 57% of tumors analyzed harbor putative clinically actionable events. Our study represents the most comprehensive discovery of cancer genes and mutations to date and will serve as a blueprint for future biological and clinical endeavors.
Keywords: Algorithms; B7-H1 Antigen; Computational Biology; Databases, Genetic; Entropy; Humans; Microsatellite Instability; Mutation; Neoplasms; Principal Component Analysis; Programmed Cell Death 1 Receptor

A comprehensive clinical and genetic study in 127 patients with ID in Kinshasa, DR Congo. - Lumaka, Aimé; Race, Valerie; Peeters, Hilde; Corveleyn, Anniek; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Song, Xiaofei; Mubungu, Gerrye; Posey, Jennifer; Lupski, James R; Vermeesch, Joris R; Lukusa, Prosper; et al. (Am J Med Genet A, 2018)
Pathogenic variants account for 4 to 41% of patients with intellectual disability (ID) or developmental delay (DD). In Sub-Saharan Africa, the prevalence of ID is thought to be higher, but data in Central Africa are limited to some case reports. In addition, clinical descriptions of some syndromes are not available for this population. This study aimed at providing an estimate for the fraction of ID/DD for which an underlying etiological genetic cause may be elucidated and provide insights into their clinical presentation in special institutions in a Central African country. A total of 127 patients (33 females and 94 males, mean age 10.03 ± 4.68 years), were recruited from six institutions across Kinshasa. A clinical diagnosis was achieved in 44 but molecular confirmation was achieved in 21 of the 22 patients with expected genetic defect (95% clinical sensitivity). Identified diseases included Down syndrome (15%), submicroscopic copy number variants (9%), aminoacylase deficiency (0.8%), Partington syndrome in one patient (0.8%) and his similarly affected brother, X-linked syndromic Mental Retardation type 33 (0.8%), and two conditions without clear underlying molecular genetic etiologies (Oculo-Auriculo-Vertebral and Amniotic Bands Sequence). We have shown that genetic etiologies, similar to those reported in Caucasian subjects, are a common etiologic cause of ID in African patients from Africa. We have confirmed the diagnostic utility of clinical characterization prior to genetic testing. Finally, our clinical descriptions provide insights into the presentation of these genetic diseases in African patients.
Keywords: Adolescent; Adult; Algorithms; Child; Child, Preschool; Comparative Genomic Hybridization; Democratic Republic of the Congo; Developmental Disabilities; Disease Management; Exome Sequencing; Facies; Female; Genetic Association Studies; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Homeodomain Proteins; Humans; Infant; Intellectual Disability; Male; Phenotype; Syndrome; Transcription Factors; Trinucleotide Repeat Expansion; Trinucleotide Repeats; Workflow; X Chromosome Inactivation; Young Adult

Comprehensive genomic analysis of patients with disorders of cerebral cortical development. - Wiszniewski, Wojciech; Gawlinski, Pawel; Gambin, Tomasz; Bekiesinska-Figatowska, Monika; Obersztyn, Ewa; Antczak-Marach, Dorota; Akdemir, Zeynep Hande Coban; Harel, Tamar; Karaca, Ender; Jurek, Marta; Sobecka, Katarzyna; Nowakowska, Beata; et al. (Eur J Hum Genet, 2018)
Malformations of cortical development (MCDs) manifest with structural brain anomalies that lead to neurologic sequelae, including epilepsy, cerebral palsy, developmental delay, and intellectual disability. To investigate the underlying genetic architecture of patients with disorders of cerebral cortical development, a cohort of 54 patients demonstrating neuroradiologic signs of MCDs was investigated. Individual genomes were interrogated for single-nucleotide variants (SNV) and copy number variants (CNV) with whole-exome sequencing and chromosomal microarray studies. Variation affecting known MCDs-associated genes was found in 16/54 cases, including 11 patients with SNV, 2 patients with CNV, and 3 patients with both CNV and SNV, at distinct loci. Diagnostic pathogenic SNV and potentially damaging variants of unknown significance (VUS) were identified in two groups of seven individuals each. We demonstrated that de novo variants are important among patients with MCDs as they were identified in 10/16 individuals with a molecular diagnosis. Three patients showed changes in known MCDs genes  and a clinical phenotype beyond the usual characteristics observed, i.e., phenotypic expansion, for a particular known disease gene clinical entity. We also discovered 2 likely candidate genes, CDH4, and ASTN1, with human and animal studies supporting their roles in brain development, and 5 potential candidate genes. Our findings emphasize genetic heterogeneity of MCDs disorders and postulate potential novel candidate genes involved in cerebral cortical development.
Keywords: Cadherins; DNA Copy Number Variations; Exome; Female; Genetic Heterogeneity; Humans; Male; Malformations of Cortical Development; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Cell Surface

A Comprehensive Pan-Cancer Molecular Study of Gynecologic and Breast Cancers. - Berger, Ashton C; Korkut, Anil; Kanchi, Rupa S; Hegde, Apurva M; Lenoir, Walter; Liu, Wenbin; Liu, Yuexin; Fan, Huihui; Shen, Hui; Ravikumar, Visweswaran; Rao, Arvind; Schultz, Andre; et al. (Cancer Cell, 2018)
We analyzed molecular data on 2,579 tumors from The Cancer Genome Atlas (TCGA) of four gynecological types plus breast. Our aims were to identify shared and unique molecular features, clinically significant subtypes, and potential therapeutic targets. We found 61 somatic copy-number alterations (SCNAs) and 46 significantly mutated genes (SMGs). Eleven SCNAs and 11 SMGs had not been identified in previous TCGA studies of the individual tumor types. We found functionally significant estrogen receptor-regulated long non-coding RNAs (lncRNAs) and gene/lncRNA interaction networks. Pathway analysis identified subtypes with high leukocyte infiltration, raising potential implications for immunotherapy. Using 16 key molecular features, we identified five prognostic subtypes and developed a decision tree that classified patients into the subtypes based on just six features that are assessable in clinical laboratories.
Keywords: Breast Neoplasms; Databases, Genetic; DNA Copy Number Variations; Female; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Gene Regulatory Networks; Genetic Predisposition to Disease; Genital Neoplasms, Female; Humans; Mutation; Organ Specificity; Prognosis; Receptors, Estrogen; RNA, Long Noncoding

Conditional loss of Spata7 in photoreceptors causes progressive retinal degeneration in mice. - Eblimit, Aiden; Agrawal, Smriti Akshay; Thomas, Kandace; Anastassov, Ivan Assenov; Abulikemu, Tajiguli; Moayedi, Yalda; Mardon, Graeme; Chen, Rui (Exp Eye Res, 2018)
The mammalian retina consists of multiple cell layers including photoreceptor cells, which are light sensing neurons that play essential functions in the visual process. Previously, we identified mutations in SPATA7, encoding spermatogenesis associated protein 7, in families with Leber Congenital Amaurosis (LCA) and juvenile Retinitis Pigmentosa (RP), and showed that Spata7 null mice recapitulate the human disease phenotype of retinal degeneration. SPATA7 is expressed in the connecting cilium of photoreceptor (PR) cells in the mouse retina, as well as in retinal pigment epithelium (RPE) cells, but the functional role of Spata7 in the RPE remains unknown. To investigate whether Spata7 is required in PRs, the RPE, or both, we conditionally knocked out Spata7 in photoreceptors and RPE cells using Crx-Cre and Best1-Cre transgenic mouse lines, respectively. In Spata7 photoreceptor-specific conditional (cKO) mice, both rod and cone photoreceptor dysfunction and degeneration is observed, characterized by progressive thinning of the outer nuclear layer and reduced response to light; however, RPE-specific deletion of Spata7 does not impair retinal function or cell survival. Furthermore, our findings show that both Rhodopsin and RPGRIP1 are mislocalized in the Spata7; Crx-Cre cKO mice, suggesting that loss of Spata7 in photoreceptors alone can result in altered trafficking of these proteins in the connecting cilium. Together, our findings suggest that loss of Spata7 in photoreceptors alone is sufficient to cause photoreceptor degeneration, but its function in the RPE is not required for photoreceptor survival; therefore, loss of Spata7 in photoreceptors alters both rod and cone function and survival, consistent with the clinical phenotypes observed in LCA and RP patients with mutations in SPATA7.
Keywords: Animals; Cytoskeletal Proteins; Disease Models, Animal; DNA-Binding Proteins; Electroretinography; Mice; Mice, Knockout; Proteins; Retina; Retinal Cone Photoreceptor Cells; Retinal Degeneration; Retinal Rod Photoreceptor Cells; Retinitis Pigmentosa; Rhodopsin

DNA methylation age is associated with an altered hemostatic profile in a multiethnic meta-analysis. - Ward-Caviness, Cavin K; Huffman, Jennifer E; Everett, Karl; Germain, Marine; van Dongen, Jenny; Hill, W David; Jhun, Min A; Brody, Jennifer A; Ghanbari, Mohsen; Du, Lei; Roetker, Nicholas S; de Vries, Paul S; et al. (Blood, 2018)
Many hemostatic factors are associated with age and age-related diseases; however, much remains unknown about the biological mechanisms linking aging and hemostatic factors. DNA methylation is a novel means by which to assess epigenetic aging, which is a measure of age and the aging processes as determined by altered epigenetic states. We used a meta-analysis approach to examine the association between measures of epigenetic aging and hemostatic factors, as well as a clotting time measure. For fibrinogen, we performed European and African ancestry-specific meta-analyses which were then combined via a random effects meta-analysis. For all other measures we could not estimate ancestry-specific effects and used a single fixed effects meta-analysis. We found that 1-year higher extrinsic epigenetic age as compared with chronological age was associated with higher fibrinogen (0.004 g/L/y; 95% confidence interval, 0.001-0.007; = .01) and plasminogen activator inhibitor 1 (PAI-1; 0.13 U/mL/y; 95% confidence interval, 0.07-0.20; = 6.6 10) concentrations, as well as lower activated partial thromboplastin time, a measure of clotting time. We replicated PAI-1 associations using an independent cohort. To further elucidate potential functional mechanisms, we associated epigenetic aging with expression levels of the PAI-1 protein encoding gene () and the 3 fibrinogen subunit-encoding genes (, , and ) in both peripheral blood and aorta intima-media samples. We observed associations between accelerated epigenetic aging and transcription of in both tissues. Collectively, our results indicate that accelerated epigenetic aging is associated with a procoagulation hemostatic profile, and that epigenetic aging may regulate hemostasis in part via gene transcription.
Keywords: Aging; DNA Methylation; Epigenesis, Genetic; Hemostasis; Humans

Editorial overview: Insect genomics: Arthropod genomic resources for the 21st century: It only counts if it's in the database! - Richards, Stephen; Childers, Anna; Childers, Christopher (Curr Opin Insect Sci, 2018)
Keywords: Animals; Arthropods; Databases, Genetic; Genome, Insect; Insecta; Transcriptome

Effects of Gender-Specific Differences, Inflammatory Response, and Genetic Variation on the Associations Among Depressive Symptoms and the Risk of Major Adverse Coronary Events in Patients With Acute Coronary Syndrome. - Sanner, Jennifer; Grove, Megan L; Yu, Erica; Moeller, F Gerard; Cron, Stanley G; Boerwinkle, Eric; Morrison, Alanna C; Frazier, Lorraine (Biol Res Nurs, 2018)
Depressive symptoms independently contribute to major adverse coronary events (MACEs), with the biological immune response to depression being a likely mediator of this relationship. To determine whether genetic- and/or gender-specific phenotypic differences contribute to associations among depressive symptoms, inflammatory response, and risk of MACE in patients with acute coronary syndrome (ACS), we conducted a prospective study of 1,117 ACS patients to test a gender-specific model in which depressive symptoms (Beck Depression Inventory-II [BDI-II]) are associated with risk of MACE. Cox proportional hazards models were used to model time to incident MACE and determine whether single-nucleotide polymorphisms (SNPs) in specific inflammatory protein-coding genes and depressive symptoms interact to influence levels of inflammatory proteins or risk of MACE. Females had significantly higher high-sensitivity C-reactive protein and monocyte chemoattractant protein-1 levels. Depression status differed by gender (29.9% of females and 21.1% of males had BDI-II scores indicative of depression [ p = .0014]). Depressive symptoms were associated with MACE; however, the interaction between these symptoms and gender was not significant. SNPs and depressive symptoms did not interact to influence inflammation or MACE. More females than males had BDI-II scores indicative of depression, yet the association between positive depressive symptom status and MACE did not vary by gender. Nor did the SNPs interact with depressive symptoms to influence inflammation or MACE. It remains of interest to identify a high-risk subgroup of ACS patients with genetic polymorphisms that result in immunoinflammatory dysregulation in the presence of depressive symptoms.
Keywords: Acute Coronary Syndrome; Aged; Depression; Female; Genetic Variation; Humans; Inflammation; Male; Middle Aged; Prospective Studies; Risk Assessment; Sex Factors

Elucidating the molecular pathogenesis of glioma: integrated germline and somatic profiling of a familial glioma case series. - Jacobs, Daniel I; Fukumura, Kazutaka; Bainbridge, Matthew N; Armstrong, Georgina N; Tsavachidis, Spiridon; Gu, Xiangjun; Harshavardhan Doddapaneni; Jianhong Hu; Jayaseelan, Joy C; Donna M Muzny; Huse, Jason T; Bondy, Melissa L (Neuro Oncol, 2018)
BACKGROUND: The genomic characterization of sporadically arising gliomas has delineated molecularly and clinically distinct subclasses of disease. However, less is known about the molecular nature of gliomas that are familial in origin. We performed molecular subtyping of 163 tumor specimens from individuals with a family history of glioma and integrated germline and somatic genomic data to characterize the pathogenesis of 20 tumors in additional detail. METHODS: Immunohistochemical analyses were performed on formalin-fixed, paraffin-embedded tumor sections to determine molecular subtypes of glioma. For 20 cases, tumor DNA was exome sequenced on an Illumina HiSeq 2000 platform and copy number profiling was performed on the Illumina HumanOmniExpress BeadChip. Genotypes at glioma risk polymorphisms were determined from germline DNA profiled on the Illumina Infinium OncoArray and deleterious germline mutations were identified from germline sequencing data. RESULTS: All 3 molecular subtypes of sporadic glioma were represented in the overall case series, including molecular glioblastoma (n = 102), oligodendroglioma (n = 21), and astrocytoma (n = 20). Detailed profiling of 20 of these cases showed characteristic subtype-specific alterations at frequencies comparable to sporadic glioma cases. All 20 cases had alterations in genes regulating telomere length. Frequencies of common glioma risk alleles were similar to those among sporadic cases, and correlations between risk alleles and same-gene somatic mutations were not observed. CONCLUSIONS: This study illustrates that the molecular characteristics of familial tumors profiled largely recapitulate what is known about sporadic glioma and that both germline and somatic molecular features target common core pathways involved in gliomagenesis. KEY POINTS: 1. Familial and sporadic gliomas display highly comparable molecular landscapes. 2. Germline and somatic molecular events target common core pathways involved in gliomagenesis. 3. Carriage of germline glioma risk variants is not associated with somatic events in the same gene.
Keywords: Adult; Biomarkers, Tumor; Brain Neoplasms; DNA Copy Number Variations; DNA, Neoplasm; Exome; Genetic Predisposition to Disease; Genomics; Germ-Line Mutation; Glioma; Humans; Middle Aged; Prognosis

An Epigenome-Wide Association Study of Obesity-Related Traits. - Dhana, Klodian; Braun, Kim V E; Nano, Jana; Voortman, Trudy; Demerath, Ellen W; Guan, Weihua; Fornage, Myriam; van Meurs, Joyce B J; Uitterlinden, André G; Hofman, Albert; Franco, Oscar H; Dehghan, Abbas (Am J Epidemiol, 2018)
We conducted an epigenome-wide association study on obesity-related traits. We used data from 2 prospective, population-based cohort studies: the Rotterdam Study (RS) (2006-2013) and the Atherosclerosis Risk in Communities (ARIC) Study (1990-1992). We used the RS (n = 1,450) as the discovery panel and the ARIC Study (n = 2,097) as the replication panel. Linear mixed-effect models were used to assess the cross-sectional associations between genome-wide DNA methylation in leukocytes and body mass index (BMI) and waist circumference (WC), adjusting for sex, age, smoking, leukocyte proportions, array number, and position on array. The latter 2 variables were modeled as random effects. Fourteen 5'-C-phosphate-G-3' (CpG) sites were associated with BMI and 26 CpG sites with WC in the RS after Bonferroni correction (P < 1.07 × 10-7), of which 12 and 13 CpGs were replicated in the ARIC Study, respectively. The most significant novel CpGs were located on the Musashi RNA binding protein 2 gene (MSI2; cg21139312) and the leucyl-tRNA synthetase 2, mitochondrial gene (LARS2; cg18030453) and were associated with both BMI and WC. CpGs at BRDT, PSMD1, IFI44L, MAP1A, and MAP3K5 were associated with BMI. CpGs at LGALS3BP, MAP2K3, DHCR24, CPSF4L, and TMEM49 were associated with WC. We report novel associations between methylation at MSI2 and LARS2 and obesity-related traits. These results provide further insight into mechanisms underlying obesity-related traits, which can enable identification of new biomarkers in obesity-related chronic diseases.
Keywords: Amino Acyl-tRNA Synthetases; Biomarkers; CpG Islands; DNA Methylation; Epigenomics; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Netherlands; Obesity; Phenotype; Prospective Studies; RNA-Binding Proteins; United States

Expansions of key protein families in the German cockroach highlight the molecular basis of its remarkable success as a global indoor pest. - Harrison, Mark C; Arning, Nicolas; Kremer, Lukas P M; Ylla, Guillem; Belles, Xavier; Bornberg-Bauer, Erich; Huylmans, Ann Kathrin; Jongepier, Evelien; Piulachs, Maria-Dolors; Richards, Stephen; Schal, Coby (J Exp Zool B Mol Dev Evol, 2018)
The German cockroach, Blattella germanica, is a worldwide pest that infests buildings, including homes, restaurants, and hospitals, often living in unsanitary conditions. As a disease vector and producer of allergens, this species has major health and economic impacts on humans. Factors contributing to the success of the German cockroach include its resistance to a broad range of insecticides, immunity to many pathogens, and its ability, as an extreme generalist omnivore, to survive on most food sources. The recently published genome shows that B. germanica has an exceptionally high number of protein coding genes. In this study, we investigate the functions of the 93 significantly expanded gene families with the aim to better understand the success of B. germanica as a major pest despite such inhospitable conditions. We find major expansions in gene families with functions related to the detoxification of insecticides and allelochemicals, defense against pathogens, digestion, sensory perception, and gene regulation. These expansions might have allowed B. germanica to develop multiple resistance mechanisms to insecticides and pathogens, and enabled a broad, flexible diet, thus explaining its success in unsanitary conditions and under recurrent chemical control. The findings and resources presented here provide insights for better understanding molecular mechanisms that will facilitate more effective cockroach control.
Keywords: Animals; Blattellidae; Diet; Evolution, Molecular; Genome, Insect; Inactivation, Metabolic; Insect Proteins; Insecticide Resistance; Multigene Family; Pest Control; Receptors, Cell Surface

Full disclosure: Genome assembly is still hard. - Richards, Stephen (PLoS Biol, 2018)
Two recent papers highlight the fascinating comparative genomics of anhydrobiosis, the ability to withstand complete desiccation, in bdelloid rotifers and tardigrades. However, both groups had to openly deal with the significant difficulties of generating and interpreting short-read draft assemblies-especially challenging in microscopic species with high sequence polymorphism. These exemplars demonstrate the need to go beyond single draft-quality reference genomes to high-quality multiple species comparative genomics if we are to fully capture the value of genomics.
Keywords: Animals; Desiccation; Genome; Genomics; Rotifera; Tardigrada

Genetic Mechanisms of Immune Evasion in Colorectal Cancer. - Grasso, Catherine S; Giannakis, Marios; Wells, Daniel K; Hamada, Tsuyoshi; Mu, Xinmeng Jasmine; Quist, Michael; Nowak, Jonathan A; Nishihara, Reiko; Qian, Zhi Rong; Inamura, Kentaro; Morikawa, Teppei; Nosho, Katsuhiko; et al. (Cancer Discov, 2018)
To understand the genetic drivers of immune recognition and evasion in colorectal cancer, we analyzed 1,211 colorectal cancer primary tumor samples, including 179 classified as microsatellite instability-high (MSI-high). This set includes The Cancer Genome Atlas colorectal cancer cohort of 592 samples, completed and analyzed here. MSI-high, a hypermutated, immunogenic subtype of colorectal cancer, had a high rate of significantly mutated genes in important immune-modulating pathways and in the antigen presentation machinery, including biallelic losses of and genes due to copy-number alterations and copy-neutral loss of heterozygosity. WNT/β-catenin signaling genes were significantly mutated in all colorectal cancer subtypes, and activated WNT/β-catenin signaling was correlated with the absence of T-cell infiltration. This large-scale genomic analysis of colorectal cancer demonstrates that MSI-high cases frequently undergo an immunoediting process that provides them with genetic events allowing immune escape despite high mutational load and frequent lymphocytic infiltration and, furthermore, that colorectal cancer tumors have genetic and methylation events associated with activated WNT signaling and T-cell exclusion. This multi-omic analysis of 1,211 colorectal cancer primary tumors reveals that it should be possible to better monitor resistance in the 15% of cases that respond to immune blockade therapy and also to use WNT signaling inhibitors to reverse immune exclusion in the 85% of cases that currently do not. .
Keywords: beta 2-Microglobulin; Colorectal Neoplasms; DNA Copy Number Variations; DNA Methylation; Germ-Line Mutation; HLA Antigens; Humans; Loss of Heterozygosity; Microsatellite Instability; Tumor Escape; Wnt Signaling Pathway

Genomes of Diptera. - Wiegmann, Brian M; Richards, Stephen (Curr Opin Insect Sci, 2018)
Diptera (true flies) are among the most diverse holometabolan insect orders and were the first eukaryotic order to have a representative genome fully sequenced. 110 fly species have publically available genome assemblies and many hundreds of population-level genomes have been generated in the model organisms Drosophila melanogaster and the malaria mosquito Anopheles gambiae. Comparative genomics carried out in a phylogenetic context is illuminating many aspects of fly biology, providing unprecedented insight into variability in genome structure, gene content, genetic mechanisms, and rates and patterns of evolution in genes, populations, and species. Despite the rich availability of genomic resources in flies, there remain many fly lineages to which new genome sequencing efforts should be directed. Such efforts would be most valuable in fly families or clades that exhibit multiple origins of key fly behaviors such as blood feeding, phytophagy, parasitism, pollination, and mycophagy.
Keywords: Animals; Diptera; Genome, Insect; Genomics; Phylogeny

Genomic and Molecular Landscape of DNA Damage Repair Deficiency across The Cancer Genome Atlas. - Knijnenburg, Theo A; Wang, Linghua; Zimmermann, Michael T; Chambwe, Nyasha; Gao, Galen F; Cherniack, Andrew D; Fan, Huihui; Shen, Hui; Way, Gregory P; Greene, Casey S; Liu, Yuexin; Akbani, Rehan; et al. (Cell Rep, 2018)
DNA damage repair (DDR) pathways modulate cancer risk, progression, and therapeutic response. We systematically analyzed somatic alterations to provide a comprehensive view of DDR deficiency across 33 cancer types. Mutations with accompanying loss of heterozygosity were observed in over 1/3 of DDR genes, including TP53 and BRCA1/2. Other prevalent alterations included epigenetic silencing of the direct repair genes EXO5, MGMT, and ALKBH3 in ∼20% of samples. Homologous recombination deficiency (HRD) was present at varying frequency in many cancer types, most notably ovarian cancer. However, in contrast to ovarian cancer, HRD was associated with worse outcomes in several other cancers. Protein structure-based analyses allowed us to predict functional consequences of rare, recurrent DDR mutations. A new machine-learning-based classifier developed from gene expression data allowed us to identify alterations that phenocopy deleterious TP53 mutations. These frequent DDR gene alterations in many human cancers have functional consequences that may determine cancer progression and guide therapy.
Keywords: Cell Line, Tumor; DNA Damage; Gene Silencing; Genome, Human; Humans; Loss of Heterozygosity; Machine Learning; Mutation; Neoplasms; Recombinational DNA Repair; Tumor Suppressor Proteins

Genomic disorders 20 years on-mechanisms for clinical manifestations. - Harel, T; Lupski, J R (Clin Genet, 2018)
Genomic disorders result from copy-number variants (CNVs) or submicroscopic rearrangements of the genome rather than from single nucleotide variants (SNVs). Diverse technologies, including array comparative genomic hybridization (aCGH) and single nucleotide polymorphism (SNP) microarrays, and more recently, whole genome sequencing and whole-exome sequencing, have enabled robust genome-wide unbiased detection of CNVs in affected individuals and in reportedly healthy controls. Sequencing of breakpoint junctions has allowed for elucidation of upstream mechanisms leading to genomic instability and resultant structural variation, whereas studies of the association between CNVs and specific diseases or susceptibility to morbid traits have enhanced our understanding of the downstream effects. In this review, we discuss the hallmarks of genomic disorders as they were defined during the first decade of the field, including genomic instability and the mechanism for rearrangement defined as nonallelic homologous recombination (NAHR); recurrent vs nonrecurrent rearrangements; and gene dosage sensitivity. Moreover, we highlight the exciting advances of the second decade of this field, including a deeper understanding of genomic instability and the mechanisms underlying complex rearrangements, mechanisms for constitutional and somatic chromosomal rearrangements, structural intra-species polymorphisms and susceptibility to NAHR, the role of CNVs in the context of genome-wide copy number and single nucleotide variation, and the contribution of noncoding CNVs to human disease.
Keywords: DNA Copy Number Variations; Genetic Association Studies; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Genetic Variation; Genome, Human; Genomic Instability; Genomics; History, 20th Century; History, 21st Century; Humans; Phenotype

Genomic, Pathway Network, and Immunologic Features Distinguishing Squamous Carcinomas. - Campbell, Joshua D; Yau, Christina; Bowlby, Reanne; Liu, Yuexin; Brennan, Kevin; Fan, Huihui; Taylor, Alison M; Wang, Chen; Walter, Vonn; Akbani, Rehan; Byers, Lauren Averett; Creighton, Chad J; et al. (Cell Rep, 2018)
This integrated, multiplatform PanCancer Atlas study co-mapped and identified distinguishing molecular features of squamous cell carcinomas (SCCs) from five sites associated with smoking and/or human papillomavirus (HPV). SCCs harbor 3q, 5p, and other recurrent chromosomal copy-number alterations (CNAs), DNA mutations, and/or aberrant methylation of genes and microRNAs, which are correlated with the expression of multi-gene programs linked to squamous cell stemness, epithelial-to-mesenchymal differentiation, growth, genomic integrity, oxidative damage, death, and inflammation. Low-CNA SCCs tended to be HPV(+) and display hypermethylation with repression of TET1 demethylase and FANCF, previously linked to predisposition to SCC, or harbor mutations affecting CASP8, RAS-MAPK pathways, chromatin modifiers, and immunoregulatory molecules. We uncovered hypomethylation of the alternative promoter that drives expression of the ΔNp63 oncogene and embedded miR944. Co-expression of immune checkpoint, T-regulatory, and Myeloid suppressor cells signatures may explain reduced efficacy of immune therapy. These findings support possibilities for molecular classification and therapeutic approaches.
Keywords: Carcinoma, Squamous Cell; Cell Line, Tumor; DNA Methylation; Epithelial-Mesenchymal Transition; Gene Expression Regulation, Neoplastic; Genomics; Humans; Metabolic Networks and Pathways; Polymorphism, Genetic

Identification of a pathogenic PMP2 variant in a multi-generational family with CMT type 1: Clinical gene panels versus genome-wide approaches to molecular diagnosis. - Punetha, Jaya; Mackay-Loder, Loren; Harel, Tamar; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Richard A Gibbs; Lee, Ian; Terespolsky, Deborah; Lupski, James R; Posey, Jennifer E (Mol Genet Metab, 2018)
Charcot-Marie-Tooth (CMT) disease type 1 is an inherited peripheral neuropathy characterized by demyelination and reduced nerve conduction velocities. We present a multi-generational family with peripheral neuropathy in whom clinical CMT panel testing failed to conclude a molecular diagnosis. We found a PMP2 pathogenic variant c.155T > C, p.(Ile52Thr) that segregates with disease suggesting that PMP2 variants should be considered in patients with neuropathy and that it may be prudent to include in clinical CMT gene panels.
Keywords: Charcot-Marie-Tooth Disease; Demyelinating Diseases; Humans; Mutation; Myelin P2 Protein; Neural Conduction; Pathology, Molecular; Peripheral Nervous System Diseases

Identifying Genes Whose Mutant Transcripts Cause Dominant Disease Traits by Potential Gain-of-Function Alleles. - Coban-Akdemir, Zeynep; White, Janson J; Song, Xiaofei; Jhangiani, Shalini N; Fatih, Jawid M; Gambin, Tomasz; Bayram, Yavuz; Chinn, Ivan K; Karaca, Ender; Punetha, Jaya; Poli, Cecilia; Eric Boerwinkle; et al. (Am J Hum Genet, 2018)
Premature termination codon (PTC)-bearing transcripts are often degraded by nonsense-mediated decay (NMD) resulting in loss-of-function (LoF) alleles. However, not all PTCs result in LoF mutations, i.e., some such transcripts escape NMD and are translated to truncated peptide products that result in disease due to gain-of-function (GoF) effects. Since the location of the PTC is a major factor determining transcript fate, we hypothesized that depletion of protein-truncating variants (PTVs) within the gene region predicted to escape NMD in control databases could provide a rank for genic susceptibility for disease through GoF versus LoF. We developed an NMD escape intolerance score to rank genes based on the depletion of PTVs that would render them able to escape NMD using the Atherosclerosis Risk in Communities Study (ARIC) and the Exome Aggregation Consortium (ExAC) control databases, which was further used to screen the Baylor-Center for Mendelian Genomics disease database. This analysis revealed 1,996 genes significantly depleted for PTVs that are predicted to escape from NMD, i.e., PTVesc; further studies provided evidence that revealed a subset as candidate genes underlying Mendelian phenotypes. Importantly, these genes have characteristically low pLI scores, which can cause them to be overlooked as candidates for dominant diseases. Collectively, we demonstrate that this NMD escape intolerance score is an effective and efficient tool for gene discovery in Mendelian diseases due to production of truncated or altered proteins. More importantly, we provide a complementary analytical tool to aid identification of genes associated with dominant traits through a mechanism distinct from LoF.
Keywords: Alleles; Codon, Nonsense; Databases, Genetic; Exome; Gain of Function Mutation; Humans; Mutation; Nonsense Mediated mRNA Decay; Phenotype

Integrated Molecular Characterization of Testicular Germ Cell Tumors. - Shen, Hui; Shih, Juliann; Hollern, Daniel P; Wang, Linghua; Bowlby, Reanne; Tickoo, Satish K; Thorsson, Vesteinn; Mungall, Andrew J; Newton, Yulia; Hegde, Apurva M; Armenia, Joshua; Sánchez-Vega, Francisco; et al. (Cell Rep, 2018)
We studied 137 primary testicular germ cell tumors (TGCTs) using high-dimensional assays of genomic, epigenomic, transcriptomic, and proteomic features. These tumors exhibited high aneuploidy and a paucity of somatic mutations. Somatic mutation of only three genes achieved significance-KIT, KRAS, and NRAS-exclusively in samples with seminoma components. Integrated analyses identified distinct molecular patterns that characterized the major recognized histologic subtypes of TGCT: seminoma, embryonal carcinoma, yolk sac tumor, and teratoma. Striking differences in global DNA methylation and microRNA expression between histology subtypes highlight a likely role of epigenomic processes in determining histologic fates in TGCTs. We also identified a subset of pure seminomas defined by KIT mutations, increased immune infiltration, globally demethylated DNA, and decreased KRAS copy number. We report potential biomarkers for risk stratification, such as miRNA specifically expressed in teratoma, and others with molecular diagnostic potential, such as CpH (CpA/CpC/CpT) methylation identifying embryonal carcinomas.
Keywords: DNA Copy Number Variations; DNA Methylation; Gene Expression Regulation, Neoplastic; Humans; Male; MicroRNAs; Neoplasms, Germ Cell and Embryonal; Proto-Oncogene Proteins c-kit; ras Proteins; Seminoma; Testicular Neoplasms

Integrative genomic analysis reveals novel regulatory mechanisms of eyeless during Drosophila eye development. - Yeung, Kelvin; Wang, Feng; Yumei Li; Wang, Keqing; Mardon, Graeme; Rui Chen (Nucleic Acids Res, 2018)
Eyeless (ey) is one of the most critical transcription factors for initiating the entire eye development in Drosophila. However, the molecular mechanisms through which Ey regulates target genes and pathways have not been characterized at the genomic level. Using ChIP-Seq, we generated an endogenous Ey-binding profile in Drosophila developing eyes. We found that Ey binding occurred more frequently at promoter compared to non-promoter regions. Ey promoter binding was correlated with the active transcription of genes involved in development and transcription regulation. An integrative analysis revealed that Ey directly regulated a broad and highly connected genetic network, including many essential patterning pathways, and known and novel eye genes. Interestingly, we observed that Ey could target multiple components of the same pathway, which might enhance its control of these pathways during eye development. In addition to protein-coding genes, we discovered Ey also targeted non-coding RNAs, which represents a new regulatory mechanism employed by Ey. These findings suggest that Ey could use multiple molecular mechanisms to regulate target gene expression and pathway function, which might enable Ey to exhibit a greater flexibility in controlling different processes during eye development.
Keywords: Animals; Body Patterning; Cell Lineage; Compound Eye, Arthropod; DNA-Binding Proteins; Drosophila melanogaster; Drosophila Proteins; Enhancer Elements, Genetic; Gene Expression Regulation, Developmental; Genomics; Photoreceptor Cells, Invertebrate; Promoter Regions, Genetic; RNA, Untranslated

Making Use of Cancer Genomic Databases. - Creighton, Chad J (Curr Protoc Mol Biol, 2018)
The vast amounts of genomic data now deposited in public repositories represent rich resources for cancer researchers. Large-scale genomics initiatives such as The Cancer Genome Atlas have made available data from multiple molecular profiling platforms (e.g., somatic mutation, RNA and protein expression, and DNA methylation) for the same set of over 10,000 human tumors. There has been much collective effort toward providing user-friendly software tools for biologists lacking computational skills to ask questions of large-scale genomic datasets. At the same time, there remains a clear need for skilled bioinformatics analysts to answer the types of questions that cannot easily be addressed using the public user-friendly software tools. This overview introduces the reader to the many resources available for working with cancer genomic databases. © 2018 by John Wiley & Sons, Inc.
Keywords: Databases, Genetic; DNA Methylation; Gene Expression Regulation, Neoplastic; Genomics; Humans; Mutation; Neoplasms; Software

Mutations in the mitochondrial ribosomal protein MRPS22 lead to primary ovarian insufficiency. - Chen, Anlu; Tiosano, Dov; Guran, Tulay; Baris, Hagit N; Bayram, Yavuz; Mory, Adi; Shapiro-Kulnane, Laura; Hodges, Craig A; Akdemir, Zeynep C; Turan, Serap; Jhangiani, Shalini N; van den Akker, Focco; et al. (Hum Mol Genet, 2018)
Primary ovarian insufficiency (POI) is characterized by amenorrhea and loss or dysfunction of ovarian follicles prior to the age of 40. POI has been associated with autosomal recessive mutations in genes involving hormonal signaling and folliculogenesis, however, the genetic etiology of POI most often remains unknown. Here we report MRPS22 homozygous missense variants c.404G>A (p.R135Q) and c.605G>A (p.R202H) identified in four females from two independent consanguineous families as a novel genetic cause of POI in adolescents. Both missense mutations identified in MRPS22 are rare, occurred in highly evolutionarily conserved residues, and are predicted to be deleterious to protein function. In contrast to prior reports of mutations in MRPS22 associated with severe mitochondrial disease, the POI phenotype is far less severe. Consistent with this genotype-phenotype correlation, mitochondrial defects in oxidative phosphorylation or rRNA levels were not detected in fibroblasts derived from the POI patients, suggesting a non-bioenergetic or tissue-specific mitochondrial defect. Furthermore, we demonstrate in a Drosophila model that mRpS22 deficiency specifically in somatic cells of the ovary had no effect on fertility, whereas flies with mRpS22 deficiency specifically in germ cells were infertile and agametic, demonstrating a cell autonomous requirement for mRpS22 in germ cell development. These findings collectively identify that MRPS22, a component of the small mitochondrial ribosome subunit, is critical for ovarian development and may therefore provide insight into the pathophysiology and treatment of ovarian dysfunction.
Keywords: Adolescent; Adult; Amenorrhea; Animals; Disease Models, Animal; Drosophila; Drosophila Proteins; Female; Fertility; Homozygote; Humans; Menopause, Premature; Mitochondrial Proteins; Mutation, Missense; Ovarian Follicle; Primary Ovarian Insufficiency; Ribosomal Proteins; Young Adult

National Cancer Institute Biospecimen Evidence-Based Practices: Harmonizing Procedures for Nucleic Acid Extraction from Formalin-Fixed, Paraffin-Embedded Tissue. - Greytak, Sarah R; Engel, Kelly B; Zmuda, Erik; Casas-Silva, Esmeralda; Guan, Ping; Hoadley, Katherine A; Mungall, Andrew J; Wheeler, David A; Doddapaneni, Harsha V; Moore, Helen M (Biopreserv Biobank, 2018)
Keywords: DNA; Evidence-Based Practice; Gene Library; Genomics; Humans; National Cancer Institute (U.S.); Nucleic Acids; Paraffin Embedding; RNA; United States

A novel NAA10 variant with impaired acetyltransferase activity causes developmental delay, intellectual disability, and hypertrophic cardiomyopathy. - Støve, Svein Isungset; Blenski, Marina; Stray-Pedersen, Asbjørg; Wierenga, Klaas J; Jhangiani, Shalini N; Akdemir, Zeynep Coban; Crawford, David; McTiernan, Nina; Myklebust, Line M; Purcarin, Gabriela; McNall-Knapp, Rene; Wadley, Alexandrea; et al. (Eur J Hum Genet, 2018)
The NAA10-NAA15 complex (NatA) is an N-terminal acetyltransferase that catalyzes N-terminal acetylation of ~40% of all human proteins. N-terminal acetylation has several different roles in the cell, including altering protein stability and degradation, protein localization and protein-protein interactions. In recent years several X-linked NAA10 variants have been associated with genetic disorders. We have identified a previously undescribed NAA10 c.215T>C p.(Ile72Thr) variant in three boys from two unrelated families with a milder phenotypic spectrum in comparison to most of the previously described patients with NAA10 variants. These boys have development delay, intellectual disability, and cardiac abnormalities as overlapping phenotypes. Functional studies reveal that NAA10 Ile72Thr is destabilized, while binding to NAA15 most likely is intact. Surprisingly, the NatA activity of NAA10 Ile72Thr appears normal while its monomeric activity is decreased. This study further broadens the phenotypic spectrum associated with NAA10 deficiency, and adds to the evidence that genotype-phenotype correlations for NAA10 variants are much more complex than initially anticipated.
Keywords: Cardiomyopathy, Hypertrophic; Child, Preschool; Developmental Disabilities; Enzyme Stability; HeLa Cells; Humans; Infant; Intellectual Disability; Male; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Phenotype; Protein Binding; Syndrome

A Pan-Cancer Compendium of Genes Deregulated by Somatic Genomic Rearrangement across More Than 1,400 Cases. - Zhang, Yiqun; Yang, Lixing; Kucherlapati, Melanie; Chen, Fengju; Hadjipanayis, Angela; Pantazi, Angeliki; Bristow, Christopher A; Lee, Eunjung A; Mahadeshwar, Harshad S; Tang, Jiabin; Zhang, Jianhua; Seth, Sahil; et al. (Cell Rep, 2018)
A systematic cataloging of genes affected by genomic rearrangement, using multiple patient cohorts and cancer types, can provide insight into cancer-relevant alterations outside of exomes. By integrative analysis of whole-genome sequencing (predominantly low pass) and gene expression data from 1,448 cancers involving 18 histopathological types in The Cancer Genome Atlas, we identified hundreds of genes for which the nearby presence (within 100 kb) of a somatic structural variant (SV) breakpoint is associated with altered expression. While genomic rearrangements are associated with widespread copy-number alteration (CNA) patterns, approximately 1,100 genes-including overexpressed cancer driver genes (e.g., TERT, ERBB2, CDK12, CDK4) and underexpressed tumor suppressors (e.g., TP53, RB1, PTEN, STK11)-show SV-associated deregulation independent of CNA. SVs associated with the disruption of topologically associated domains, enhancer hijacking, or fusion transcripts are implicated in gene upregulation. For cancer-relevant pathways, SVs considerably expand our understanding of how genes are affected beyond point mutation or CNA.
Keywords: Base Sequence; Carcinogenesis; DNA Copy Number Variations; Enhancer Elements, Genetic; Gene Expression Regulation, Neoplastic; Gene Rearrangement; Genes, Neoplasm; Genome, Human; Humans; Neoplasms

Pan-Cancer Molecular Classes Transcending Tumor Lineage Across 32 Cancer Types, Multiple Data Platforms, and over 10,000 Cases. - Chen, Fengju; Zhang, Yiqun; Gibbons, Don L; Deneen, Benjamin; Kwiatkowski, David J; Ittmann, Michael; Creighton, Chad J (Clin Cancer Res, 2018)
The Cancer Genome Atlas data resources represent an opportunity to explore commonalities across cancer types involving multiple molecular levels, but tumor lineage and histology can represent a barrier in moving beyond differences related to cancer type. On the basis of gene expression data, we classified 10,224 cancers, representing 32 major types, into 10 molecular-based "classes." Molecular patterns representing tissue or histologic dominant effects were first removed computationally, with the resulting classes representing emergent themes across tumor lineages. Key differences involving mRNAs, miRNAs, proteins, and DNA methylation underscored the pan-cancer classes. One class expressing neuroendocrine and cancer-testis antigen markers represented ∼4% of cancers surveyed. Basal-like breast cancers segregated into an exclusive class, distinct from all other cancers. Immune checkpoint pathway markers and molecular signatures of immune infiltrates were most strongly manifested within a class representing ∼13% of cancers. Pathway-level differences involving hypoxia, NRF2-ARE, Wnt, and Notch were manifested in two additional classes enriched for mesenchymal markers and miR200 silencing. All pan-cancer molecular classes uncovered here, with the important exception of the basal-like breast cancer class, involve a wide range of cancer types and would facilitate understanding the molecular underpinnings of cancers beyond tissue-oriented domains. Numerous biological processes associated with cancer in the laboratory setting were found here to be coordinately manifested across large subsets of human cancers. The number of cancers manifesting features of neuroendocrine tumors may be much higher than previously thought, which disease is known to occur in many different tissues. .
Keywords: Biomarkers, Tumor; DNA Methylation; Epigenesis, Genetic; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Genetic Variation; Genomics; Humans; Immunomodulation; Neoplasms; Signal Transduction; Transcriptome

Perspective on Oncogenic Processes at the End of the Beginning of Cancer Genomics. - Ding, Li; Bailey, Matthew H; Porta-Pardo, Eduard; Thorsson, Vesteinn; Colaprico, Antonio; Bertrand, Denis; Gibbs, David L; Weerasinghe, Amila; Huang, Kuan-Lin; Tokheim, Collin; Cortés-Ciriano, Isidro; Jayasinghe, Reyka; et al. (Cell, 2018)
The Cancer Genome Atlas (TCGA) has catalyzed systematic characterization of diverse genomic alterations underlying human cancers. At this historic junction marking the completion of genomic characterization of over 11,000 tumors from 33 cancer types, we present our current understanding of the molecular processes governing oncogenesis. We illustrate our insights into cancer through synthesis of the findings of the TCGA PanCancer Atlas project on three facets of oncogenesis: (1) somatic driver mutations, germline pathogenic variants, and their interactions in the tumor; (2) the influence of the tumor genome and epigenome on transcriptome and proteome; and (3) the relationship between tumor and the microenvironment, including implications for drugs targeting driver events and immunotherapies. These results will anchor future characterization of rare and common tumor types, primary and relapsed tumors, and cancers across ancestry groups and will guide the deployment of clinical genomic sequencing.
Keywords: Carcinogenesis; Databases, Genetic; DNA Repair; Genes, Neoplasm; Genomics; Humans; Metabolic Networks and Pathways; Microsatellite Instability; Mutation; Neoplasms; Transcriptome; Tumor Microenvironment

The phenotypic spectrum of Xia-Gibbs syndrome. - Jiang, Yunyun; Wangler, Michael F; McGuire, Amy L; Lupski, James R; Posey, Jennifer E; Khayat, Michael M; Murdock, David R; Sanchez-Pulido, Luis; Ponting, Chris P; Xia, Fan; Hunter, Jill V; Meng, Qingchang; et al. (Am J Med Genet A, 2018)
Xia-Gibbs syndrome (XGS: OMIM # 615829) results from de novo truncating mutations within the AT-Hook DNA Binding Motif Containing 1 gene (AHDC1). To further define the phenotypic and molecular spectrum of this disorder, we established an XGS Registry and recruited patients from a worldwide pool of approximately 60 probands. Additional de novo truncating mutations were observed among 25 individuals, extending both the known number of mutation sites and the range of positions within the coding region that were sensitive to alteration. Detailed phenotypic examination of 20 of these patients via clinical records review and data collection from additional surveys showed a wider age range than previously described. Data from developmental milestones showed evidence for delayed speech and that males were more severely affected. Neuroimaging from six available patients showed an associated thinning of the corpus callosum and posterior fossa cysts. An increased risk of both scoliosis and seizures relative to the population burden was also observed. Data from a modified autism screening tool revealed that XGS shares significant overlap with autism spectrum disorders. These details of the phenotypic heterogeneity of XGS implicate specific genotype/phenotype correlations and suggest potential clinical management guidelines.
Keywords: Autism Spectrum Disorder; Child; Cognition; Corpus Callosum; Developmental Disabilities; DNA-Binding Proteins; Face; Female; Humans; Male; Mutation; Pedigree; Phenotype; Registries; Seizures; Syndrome; Young Adult

Pigmentary Maculopathy Associated with Chronic Exposure to Pentosan Polysulfate Sodium. - Pearce, William A; Rui Chen; Jain, Nieraj (Ophthalmology, 2018)
PURPOSE: To describe the clinical features of a unique pigmentary maculopathy noted in the setting of chronic exposure to pentosan polysulfate sodium (PPS), a therapy for interstitial cystitis (IC). DESIGN: Retrospective case series. PARTICIPANTS: Six adult patients evaluated by a single clinician between May 1, 2015, and October 1, 2017. METHODS: Patients were identified by query of the electronic medical record system. Local records were reviewed, including results of the clinical examination, retinal imaging, and visual function assessment with static perimetry and electroretinography. Molecular testing assessed for known macular dystrophy and mitochondrial cytopathy genotypes. MAIN OUTCOME MEASURES: Mean best-corrected visual acuity (BCVA; in logarithm of the minimum angle of resolution units), median cumulative PPS exposure, subjective nature of the associated visual disturbance, qualitative examination and imaging features, and molecular testing results. RESULTS: The median age at presentation was 60 years (range, 37-62 years). All patients received PPS for a diagnosis of IC, with a median cumulative exposure of 2263 g (range, 1314-2774 g), over a median duration of exposure of 186 months (range, 144-240 months). Most patients (4 of 6) reported difficulty reading as the most bothersome symptom. Mean BCVA was 0.1±0.18 logarithm of the minimum angle of resolution. On fundus examination, nearly all eyes showed subtle paracentral hyperpigmentation at the level of the retinal pigment epithelium (RPE) with a surrounding array of vitelliform-like deposits. Four eyes of 2 patients showed paracentral RPE atrophy, and no eyes demonstrated choroidal neovascularization. Multimodal retinal imaging demonstrated abnormality of the RPE generally contained in a well-delineated area in the posterior pole. None of the 4 patients who underwent molecular testing of nuclear DNA returned a pathogenic mutation. Additionally, all 6 patients showed negative results for pathogenic variants in the mitochondrial gene MTTL1. CONCLUSIONS: We describe a novel and possibly avoidable maculopathy associated with chronic exposure to PPS. Patients reported symptoms of difficulty reading and prolonged dark adaptation despite generally intact visual acuity and subtle funduscopic findings. Multimodal imaging and functional studies are suggestive of a primary RPE injury. Additional investigation is warranted to explore causality further.
Keywords: Adult; Anticoagulants; Cystitis, Interstitial; Dyslexia; Electroretinography; Female; Fluorescein Angiography; Genetic Testing; High-Throughput Nucleotide Sequencing; Humans; Middle Aged; Multimodal Imaging; Pentosan Sulfuric Polyester; Retinal Pigment Epithelium; Retinitis Pigmentosa; Retrospective Studies; Tomography, Optical Coherence; Vision Disorders; Visual Acuity

Predicting human genes susceptible to genomic instability associated with /-mediated rearrangements. - Song, Xiaofei; Beck, Christine R; Du, Renqian; Campbell, Ian M; Coban-Akdemir, Zeynep; Gu, Shen; Breman, Amy M; Stankiewicz, Pawel; Ira, Grzegorz; Shaw, Chad A; Lupski, James R (Genome Res, 2018)
elements, the short interspersed element numbering more than 1 million copies per human genome, can mediate the formation of copy number variants (CNVs) between substrate pairs. These /-mediated rearrangements (AAMRs) can result in pathogenic variants that cause diseases. To investigate the impact of AAMR on gene variation and human health, we first characterized s that are involved in mediating CNVs (CNV-s) and observed that these s tend to be evolutionarily younger. We then computationally generated, with the assistance of a supercomputer, a test data set consisting of 78 million pairs and predicted ∼18% of them are potentially susceptible to AAMR. We further determined the relative risk of AAMR in 12,074 OMIM genes using the count of predicted CNV- pairs and experimentally validated the predictions with 89 samples selected by correlating predicted hotspots with a database of CNVs identified by clinical chromosomal microarrays (CMAs) on the genomes of approximately 54,000 subjects. We fine-mapped 47 duplications, 40 deletions, and two complex rearrangements and examined a total of 52 breakpoint junctions of simple CNVs. Overall, 94% of the candidate breakpoints were at least partially mediated. We successfully predicted all (100%) of pairs that mediated deletions ( = 21) and achieved an 87% positive predictive value overall when including AAMR-generated deletions and duplications. We provided a tool, AluAluCNVpredictor, for assessing AAMR hotspots and their role in human disease. These results demonstrate the utility of our predictive model and provide insights into the genomic features and molecular mechanisms underlying AAMR.
Keywords: Alu Elements; DNA Copy Number Variations; Gene Duplication; Genome, Human; Genomic Instability; Humans; Sequence Deletion

Prospective chromosome analysis of 3429 amniocentesis samples in China using copy number variation sequencing. - Wang, Jing; Chen, Lin; Zhou, Cong; Wang, Li; Xie, Hanbing; Xiao, Yuanyuan; Zhu, Hongmei; Hu, Ting; Zhang, Zhu; Zhu, Qian; Liu, Zhiying; Liu, Shanlin; et al. (Am J Obstet Gynecol, 2018)
BACKGROUND: Next-generation sequencing is emerging as a viable alternative to chromosome microarray analysis for the diagnosis of chromosome disease syndromes. One next-generation sequencing methodology, copy number variation sequencing, has been shown to deliver high reliability, accuracy, and reproducibility for detection of fetal copy number variations in prenatal samples. However, its clinical utility as a first-tier diagnostic method has yet to be demonstrated in a large cohort of pregnant women referred for fetal chromosome testing. OBJECTIVE: We sought to evaluate copy number variation sequencing as a first-tier diagnostic method for detection of fetal chromosome anomalies in a general population of pregnant women with high-risk prenatal indications. STUDY DESIGN: This was a prospective analysis of 3429 pregnant women referred for amniocentesis and fetal chromosome testing for different risk indications, including advanced maternal age, high-risk maternal serum screening, and positivity for an ultrasound soft marker. Amniocentesis was performed by standard procedures. Amniocyte DNA was analyzed by copy number variation sequencing with a chromosome resolution of 0.1 Mb. Fetal chromosome anomalies including whole chromosome aneuploidy and segmental imbalances were independently confirmed by gold standard cytogenetic and molecular methods and their pathogenicity determined following guidelines of the American College of Medical Genetics for sequence variants. RESULTS: Clear interpretable copy number variation sequencing results were obtained for all 3429 amniocentesis samples. Copy number variation sequencing identified 3293 samples (96%) with a normal molecular karyotype and 136 samples (4%) with an altered molecular karyotype. A total of 146 fetal chromosome anomalies were detected, comprising 46 whole chromosome aneuploidies (pathogenic), 29 submicroscopic microdeletions/microduplications with known or suspected associations with chromosome disease syndromes (pathogenic), 22 other microdeletions/microduplications (likely pathogenic), and 49 variants of uncertain significance. Overall, the cumulative frequency of pathogenic/likely pathogenic and variants of uncertain significance chromosome anomalies in the patient cohort was 2.83% and 1.43%, respectively. In the 3 high-risk advanced maternal age, high-risk maternal serum screening, and ultrasound soft marker groups, the most common whole chromosome aneuploidy detected was trisomy 21, followed by sex chromosome aneuploidies, trisomy 18, and trisomy 13. Across all clinical indications, there was a similar incidence of submicroscopic copy number variations, with approximately equal proportions of pathogenic/likely pathogenic and variants of uncertain significance copy number variations. If karyotyping had been used as an alternate cytogenetics detection method, copy number variation sequencing would have returned a 1% higher yield of pathogenic or likely pathogenic copy number variations. CONCLUSION: In a large prospective clinical study, copy number variation sequencing delivered high reliability and accuracy for identifying clinically significant fetal anomalies in prenatal samples. Based on key performance criteria, copy number variation sequencing appears to be a well-suited methodology for first-tier diagnosis of pregnant women in the general population at risk of having a suspected fetal chromosome abnormality.
Keywords: Adult; Amniocentesis; Aneuploidy; China; Chromosome Aberrations; Chromosome Disorders; DNA Copy Number Variations; Down Syndrome; Female; High-Throughput Nucleotide Sequencing; Humans; In Situ Hybridization, Fluorescence; Karyotyping; Microarray Analysis; Pregnancy; Prenatal Diagnosis; Prospective Studies; Sequence Analysis, DNA; Sex Chromosome Aberrations; Trisomy 13 Syndrome; Trisomy 18 Syndrome

Prospective Study of Epigenetic Age Acceleration and Incidence of Cardiovascular Disease Outcomes in the ARIC Study (Atherosclerosis Risk in Communities). - Roetker, Nicholas S; Pankow, James S; Bressler, Jan; Morrison, Alanna C; Boerwinkle, Eric (Circ Genom Precis Med, 2018)
BACKGROUND: DNA methylation-based patterns of biological aging, known as epigenetic age acceleration, are predictive of all-cause mortality, but little is known about their association with cardiovascular disease (CVD). METHODS: We estimated 2 versions of epigenetic age acceleration (Horvath and Hannum) using whole-blood samples from 2543 blacks. Linear and Cox proportional hazards regression, respectively, were used to assess the association of age acceleration with carotid intima-media thickness (cross-sectionally) and incident cardiovascular events, including CVD mortality, myocardial infarction, fatal coronary heart disease, peripheral arterial disease, and heart failure, during a median 21-year follow-up. All models were adjusted for chronological age and traditional CVD risk factors. RESULTS: In comparison to chronological age, the 2 measures of epigenetic age acceleration were weaker, but independent, potential risk markers for subclinical atherosclerosis and most incident cardiovascular outcomes, including fatal coronary heart disease, peripheral arterial disease, and heart failure. For example, each 5-year increment of epigenetic age acceleration was associated with an average of 0.01 mm greater carotid intima-media thickness (each ≤0.01), and the hazard ratios (95% confidence intervals) of fatal coronary heart disease per 5-year increment in Horvath and Hannum age acceleration were 1.17 (1.02-1.33) and 1.22 (1.04-1.44), respectively. CONCLUSIONS: In this sample of blacks, increased epigenetic age acceleration in whole blood was a potential risk marker for incident fatal coronary heart disease, peripheral arterial disease, and heart failure independently of chronological age and traditional CVD risk factors. DNA methylation-based measures of biological aging may help to identify new pathophysiological mechanisms contributing to the development of CVD.
Keywords: Age Factors; Black or African American; Cardiovascular Diseases; Carotid Intima-Media Thickness; DNA Methylation; Female; Humans; Male; Middle Aged; Prevalence; Proportional Hazards Models; Prospective Studies; Risk Factors

Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2018)
Genome-wide association studies (GWAS) have identified >250 loci for body mass index (BMI), implicating pathways related to neuronal biology. Most GWAS loci represent clusters of common, noncoding variants from which pinpointing causal genes remains challenging. Here we combined data from 718,734 individuals to discover rare and low-frequency (minor allele frequency (MAF) < 5%) coding variants associated with BMI. We identified 14 coding variants in 13 genes, of which 8 variants were in genes (ZBTB7B, ACHE, RAPGEF3, RAB21, ZFHX3, ENTPD6, ZFR2 and ZNF169) newly implicated in human obesity, 2 variants were in genes (MC4R and KSR2) previously observed to be mutated in extreme obesity and 2 variants were in GIPR. The effect sizes of rare variants are ~10 times larger than those of common variants, with the largest effect observed in carriers of an MC4R mutation introducing a stop codon (p.Tyr35Ter, MAF = 0.01%), who weighed ~7 kg more than non-carriers. Pathway analyses based on the variants associated with BMI confirm enrichment of neuronal genes and provide new evidence for adipocyte and energy expenditure biology, widening the potential of genetically supported therapeutic targets in obesity.
Keywords: Adult; Animals; Body Mass Index; Drosophila; Energy Intake; Energy Metabolism; Female; Gene Frequency; Genetic Variation; Humans; Male; Obesity; Proteins; Syndrome

A proteomic landscape of diffuse-type gastric cancer. - Ge, Sai; Xia, Xia; Ding, Chen; Zhen, Bei; Zhou, Quan; Feng, Jinwen; Yuan, Jiajia; Chen, Rui; Li, Yumei; Ge, Zhongqi; Ji, Jiafu; Zhang, Lianhai; et al. (Nat Commun, 2018)
The diffuse-type gastric cancer (DGC) is a subtype of gastric cancer with the worst prognosis and few treatment options. Here we present a dataset from 84 DGC patients, composed of a proteome of 11,340 gene products and mutation information of 274 cancer driver genes covering paired tumor and nearby tissue. DGC can be classified into three subtypes (PX1-3) based on the altered proteome alone. PX1 and PX2 exhibit dysregulation in the cell cycle and PX2 features an additional EMT process; PX3 is enriched in immune response proteins, has the worst survival, and is insensitive to chemotherapy. Data analysis revealed four major vulnerabilities in DGC that may be targeted for treatment, and allowed the nomination of potential immunotherapy targets for DGC patients, particularly for those in PX3. This dataset provides a rich resource for information and knowledge mining toward altered signaling pathways in DGC and demonstrates the benefit of proteomic analysis in cancer molecular subtyping.
Keywords: Chemoradiotherapy, Adjuvant; Datasets as Topic; DNA Mutational Analysis; Down-Regulation; Exome; Follow-Up Studies; Gastrectomy; Genes, Neoplasm; Humans; Immunohistochemistry; Mutation; Neoadjuvant Therapy; Neoplasm Proteins; Neoplasm Staging; Oligonucleotide Array Sequence Analysis; Prognosis; Proteomics; Sequence Analysis, DNA; Signal Transduction; Stomach; Stomach Neoplasms; Survival Analysis; Tandem Mass Spectrometry; Up-Regulation

Refining the accuracy of validated target identification through coding variant fine-mapping in type 2 diabetes. - Mahajan, Anubha; Wessel, Jennifer; Willems, Sara M; Zhao, Wei; Robertson, Neil R; Chu, Audrey Y; Gan, Wei; Kitajima, Hidetoshi; Taliun, Daniel; Rayner, N William; Guo, Xiuqing; Lu, Yingchang; et al. (Nat Genet, 2018)
We aggregated coding variant data for 81,412 type 2 diabetes cases and 370,832 controls of diverse ancestry, identifying 40 coding variant association signals (P < 2.2 × 10); of these, 16 map outside known risk-associated loci. We make two important observations. First, only five of these signals are driven by low-frequency variants: even for these, effect sizes are modest (odds ratio ≤1.29). Second, when we used large-scale genome-wide association data to fine-map the associated variants in their regional context, accounting for the global enrichment of complex trait associations in coding sequence, compelling evidence for coding variant causality was obtained for only 16 signals. At 13 others, the associated coding variants clearly represent 'false leads' with potential to generate erroneous mechanistic inference. Coding variant associations offer a direct route to biological insight for complex diseases and identification of validated therapeutic targets; however, appropriate mechanistic inference requires careful specification of their causal contribution to disease predisposition.
Keywords: Alleles; Chromosome Mapping; Diabetes Mellitus, Type 2; Exome Sequencing; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; White People

SPATA7 maintains a novel photoreceptor-specific zone in the distal connecting cilium. - Dharmat, Rachayata; Eblimit, Aiden; Robichaux, Michael A; Zhang, Zhixian; Nguyen, Thanh-Minh T; Jung, Sung Yun; He, Feng; Jain, Antrix; Li, Yumei; Qin, Jun; Overbeek, Paul; Roepman, Ronald; et al. (J Cell Biol, 2018)
Photoreceptor-specific ciliopathies often affect a structure that is considered functionally homologous to the ciliary transition zone (TZ) called the connecting cilium (CC). However, it is unclear how mutations in certain ciliary genes disrupt the photoreceptor CC without impacting the primary cilia systemically. By applying stochastic optical reconstruction microscopy technology in different genetic models, we show that the CC can be partitioned into two regions: the proximal CC (PCC), which is homologous to the TZ of primary cilia, and the distal CC (DCC), a photoreceptor-specific extension of the ciliary TZ. This specialized distal zone of the CC in photoreceptors is maintained by SPATA7, which interacts with other photoreceptor-specific ciliary proteins such as RPGR and RPGRIP1. The absence of results in the mislocalization of DCC proteins without affecting the PCC protein complexes. This collapse results in destabilization of the axonemal microtubules, which consequently results in photoreceptor degeneration. These data provide a novel mechanism to explain how genetic disruption of ubiquitously present ciliary proteins exerts tissue-specific ciliopathy phenotypes.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Antigens, Neoplasm; Carrier Proteins; Cell Cycle Proteins; Cytoskeletal Proteins; DNA-Binding Proteins; Eye Proteins; Mice; Mice, Inbred C57BL; Nuclear Proteins; Photoreceptor Connecting Cilium; Protein Transport

Temporal development of the gut microbiome in early childhood from the TEDDY study. - Stewart, Christopher J; Ajami, Nadim J; O'Brien, Jacqueline L; Hutchinson, Diane S; Smith, Daniel P; Wong, Matthew C; Ross, Matthew C; Lloyd, Richard E; Harshavardhan Doddapaneni; Ginger A Metcalf; Donna M Muzny; Richard A Gibbs; et al. (Nature, 2018)
The development of the microbiome from infancy to childhood is dependent on a range of factors, with microbial-immune crosstalk during this time thought to be involved in the pathobiology of later life diseases such as persistent islet autoimmunity and type 1 diabetes. However, to our knowledge, no studies have performed extensive characterization of the microbiome in early life in a large, multi-centre population. Here we analyse longitudinal stool samples from 903 children between 3 and 46 months of age by 16S rRNA gene sequencing (n = 12,005) and metagenomic sequencing (n = 10,867), as part of the The Environmental Determinants of Diabetes in the Young (TEDDY) study. We show that the developing gut microbiome undergoes three distinct phases of microbiome progression: a developmental phase (months 3-14), a transitional phase (months 15-30), and a stable phase (months 31-46). Receipt of breast milk, either exclusive or partial, was the most significant factor associated with the microbiome structure. Breastfeeding was associated with higher levels of Bifidobacterium species (B. breve and B. bifidum), and the cessation of breast milk resulted in faster maturation of the gut microbiome, as marked by the phylum Firmicutes. Birth mode was also significantly associated with the microbiome during the developmental phase, driven by higher levels of Bacteroides species (particularly B. fragilis) in infants delivered vaginally. Bacteroides was also associated with increased gut diversity and faster maturation, regardless of the birth mode. Environmental factors including geographical location and household exposures (such as siblings and furry pets) also represented important covariates. A nested case-control analysis revealed subtle associations between microbial taxonomy and the development of islet autoimmunity or type 1 diabetes. These data determine the structural and functional assembly of the microbiome in early life and provide a foundation for targeted mechanistic investigation into the consequences of microbial-immune crosstalk for long-term health.
Keywords: Adolescent; Animals; Bifidobacterium; Breast Feeding; Case-Control Studies; Child; Child, Preschool; Cluster Analysis; Datasets as Topic; Diabetes Mellitus, Type 1; Female; Firmicutes; Gastrointestinal Microbiome; Humans; Infant; Male; Milk, Human; Pets; RNA, Ribosomal, 16S; Siblings; Surveys and Questionnaires; Time Factors

The transcription factor POU3F2 regulates a gene coexpression network in brain tissue from patients with psychiatric disorders. - Chen, Chao; Meng, Qingtuan; Xia, Yan; Ding, Chaodong; Wang, Le; Dai, Rujia; Cheng, Lijun; Gunaratne, Preethi; Richard A Gibbs; Min, Shishi; Coarfa, Cristian; Reid, Jeffrey G; et al. (Sci Transl Med, 2018)
Schizophrenia and bipolar disorder are complex psychiatric diseases with risks contributed by multiple genes. Dysregulation of gene expression has been implicated in these disorders, but little is known about such dysregulation in the human brain. We analyzed three transcriptome datasets from 394 postmortem brain tissue samples from patients with schizophrenia or bipolar disorder or from healthy control individuals without a known history of psychiatric disease. We built genome-wide coexpression networks that included microRNAs (miRNAs). We identified a coexpression network module that was differentially expressed in the brain tissue from patients compared to healthy control individuals. This module contained genes that were principally involved in glial and neural cell genesis and glial cell differentiation, and included schizophrenia risk genes carrying rare variants. This module included five miRNAs and 545 mRNAs, with six transcription factors serving as hub genes in this module. We found that the most connected transcription factor gene , also identified on a genome-wide association study for bipolar disorder, could regulate the miRNA and other putative target mRNAs. These regulatory relationships were replicated using PsychENCODE/BrainGVEX datasets and validated by knockdown and overexpression experiments in SH-SY5Y cells and human neural progenitor cells in vitro. Thus, we identified a brain gene expression module that was enriched for rare coding variants in genes associated with schizophrenia and that contained the putative bipolar disorder risk gene The transcription factor may be a key regulator of gene expression in this disease-associated gene coexpression module.
Keywords: Brain; Cell Differentiation; Cell Proliferation; Databases, Genetic; Gene Expression Regulation; Gene Regulatory Networks; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeodomain Proteins; Humans; Mental Disorders; Neural Stem Cells; Postmortem Changes; POU Domain Factors; Reproducibility of Results; RNA, Messenger

Whole-exome sequencing revealed HKDC1 as a candidate gene associated with autosomal-recessive retinitis pigmentosa. - Zhang, Lin; Sun, Zixi; Zhao, Peiquan; Huang, Lulin; Xu, Mingchu; Yang, Yeming; Chen, Xue; Lu, Fang; Zhang, Xiang; Wang, Hui; Zhang, Shanshan; Liu, Wenjing; et al. (Hum Mol Genet, 2018)
Retinitis pigmentosa (RP) is an inheritable retina degenerative disease leading to blindness. Despite the identification of 70 genes associated with RP, the genetic cause of ∼40% of RP patients remains to be elucidated. Whole-exome sequencing was applied on the probands of a RP cohort of 68 unsolved cases to identify candidate genetic mutations. A homozygous missense variant (c.173C > T, p.T58 M) was found in HKDC1 in two unrelated families presenting late-onset retinal degeneration. This variant affects highly conserved amino acid residue and is very rare in several databases and absent in 4000 ethnic-matched controls. Mutant HKDC1 protein partially lost hexokinase activity. Hkdc1 is expressed in the mouse retina and localized to photoreceptor inner segments. To elucidate the in vivo roles of Hkdc1 in the retina, we generated Hkdc1 knockout (KO) mouse models using CRISPR/Cas9 technique. Two independent alleles were identified and backcrossed to C57BL/6 J for 6 generations. Absence of HKDC1 expression in the Hkdc1 KO retina was confirmed by western blot and immunostaning using HKDC1 antibody. Hkdc1 KO mice exhibited reduced scotopic electroretinogram response and thinner outer nuclear layer, similar to some of the human patient phenotypes. Loss of Hkdc1 led to mislocalization of rhodopsin to the inner segments and cell bodies of rods in some regions in the retina. Taken together, our data demonstrated that HKDC1 is associated with autosomal recessively inherited RP.
Keywords: Animals; Disease Models, Animal; Exome; Exome Sequencing; Female; Genetic Association Studies; Hexokinase; Homozygote; Humans; Male; Mice, Knockout; Mutation; Pedigree; Retina; Retinal Degeneration; Retinitis Pigmentosa

WNT Signaling Perturbations Underlie the Genetic Heterogeneity of Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Coban-Akdemir, Zeynep; Bayram, Yavuz; Bahrambeigi, Vahid; Hoischen, Alexander; van Bon, Bregje W M; Gezdirici, Alper; Gulec, Elif Yilmaz; Ramond, Francis; Touraine, Renaud; Thevenon, Julien; et al. (Am J Hum Genet, 2018)
Locus heterogeneity characterizes a variety of skeletal dysplasias often due to interacting or overlapping signaling pathways. Robinow syndrome is a skeletal disorder historically refractory to molecular diagnosis, potentially stemming from substantial genetic heterogeneity. All current known pathogenic variants reside in genes within the noncanonical Wnt signaling pathway including ROR2, WNT5A, and more recently, DVL1 and DVL3. However, ∼70% of autosomal-dominant Robinow syndrome cases remain molecularly unsolved. To investigate this missing heritability, we recruited 21 families with at least one family member clinically diagnosed with Robinow or Robinow-like phenotypes and performed genetic and genomic studies. In total, four families with variants in FZD2 were identified as well as three individuals from two families with biallelic variants in NXN that co-segregate with the phenotype. Importantly, both FZD2 and NXN are relevant protein partners in the WNT5A interactome, supporting their role in skeletal development. In addition to confirming that clustered -1 frameshifting variants in DVL1 and DVL3 are the main contributors to dominant Robinow syndrome, we also found likely pathogenic variants in candidate genes GPC4 and RAC3, both linked to the Wnt signaling pathway. These data support an initial hypothesis that Robinow syndrome results from perturbation of the Wnt/PCP pathway, suggest specific relevant domains of the proteins involved, and reveal key contributors in this signaling cascade during human embryonic development. Contrary to the view that non-allelic genetic heterogeneity hampers gene discovery, this study demonstrates the utility of rare disease genomic studies to parse gene function in human developmental pathways.
Keywords: Adolescent; Adult; Base Sequence; Child; Child, Preschool; Chromosome Segregation; Craniofacial Abnormalities; Diagnosis, Differential; Dwarfism; Female; Genes, Dominant; Genetic Association Studies; Genetic Heterogeneity; Humans; Limb Deformities, Congenital; Male; Middle Aged; Mutation, Missense; Phenotype; Urogenital Abnormalities; Wnt Signaling Pathway

22q11.2q13 duplication including SOX10 causes sex-reversal and peripheral demyelinating neuropathy, central dysmyelinating leukodystrophy, Waardenburg syndrome, and Hirschsprung disease. - Falah, Nadia; Posey, Jennifer E; Thorson, Willa; Benke, Paul; Tekin, Mustafa; Tarshish, Brocha; Lupski, James R; Harel, Tamar (Am J Med Genet A, 2017)
Diagnosis of genetic syndromes may be difficult when specific components of a disorder manifest at a later age. We present a follow up of a previous report [Seeherunvong et al., (2004); AJMGA 127: 149-151], of an individual with 22q duplication and sex-reversal syndrome. The subject's phenotype evolved to include peripheral and central demyelination, Waardenburg syndrome type IV, and Hirschsprung disease (PCWH; MIM 609136). DNA microarray analysis defined the duplication at 22q11.2q13, including SOX10. Sequencing of the coding region of SOX10 did not reveal any mutations. Our data suggest that SOX10 duplication can cause disorders of sex development and PCWH, supporting the hypothesis that SOX10 toxic gain of function rather than dominant negative activity underlies PCWH.
Keywords: 46, XX Testicular Disorders of Sex Development; Black or African American; Chromosome Duplication; Chromosomes, Human, Pair 22; Demyelinating Diseases; Hirschsprung Disease; Humans; Kidney Failure, Chronic; Male; Pelizaeus-Merzbacher Disease; SOXE Transcription Factors; Waardenburg Syndrome

Activating MAPK1 (ERK2) mutation in an aggressive case of disseminated juvenile xanthogranuloma. - Chakraborty, Rikhia; Hampton, Oliver A; Abhyankar, Harshal; Zinn, Daniel J; Grimes, Amanda; Skull, Brooks; Eckstein, Olive; Mahmood, Nadia; Wheeler, David A; López-Terrada, Dolores; Peters, Tricia L; Hicks, John M; et al. (Oncotarget, 2017)
Juvenile xanthogranuloma (JXG) is a rare histiocytic disorder that is usually benign and self-limiting. We present a case of atypical, aggressive JXG harboring a novel mitogen-activated protein kinase (MAPK) pathway mutation in the MAPK1 gene, which encodes mitogen-activated protein kinase 1 or extracellular signal-regulated 2 (ERK2). Our analysis revealed that the mutation results in constitutive ERK activation that is resistant to BRAF or MEK inhibitors but susceptible to an ERK inhibitor. These data highlight the importance of identifying specific MAPK pathway alterations as part of the diagnostic workup for patients with histiocytic disorders rather than initiating empiric treatment with MEK inhibitors.
Keywords: Cells, Cultured; Child; Drug Therapy; Histiocytes; Humans; Lymph Nodes; Male; Mitogen-Activated Protein Kinase 1; Remission Induction; Signal Transduction; Stem Cell Transplantation; Xanthogranuloma, Juvenile

Association between mitochondrial DNA copy number and sudden cardiac death: findings from the Atherosclerosis Risk in Communities study (ARIC). - Zhang, Yiyi; Guallar, Eliseo; Ashar, Foram N; Longchamps, Ryan J; Castellani, Christina A; Lane, John; Grove, Megan L; Coresh, Josef; Sotoodehnia, Nona; Ilkhanoff, Leonard; Boerwinkle, Eric; Pankratz, Nathan; et al. (Eur Heart J, 2017)
AIMS: Sudden cardiac death (SCD) is a major public health burden. Mitochondrial dysfunction has been implicated in a wide range of cardiovascular diseases including cardiomyopathy, heart failure, and arrhythmias, but it is unknown if it also contributes to SCD risk. We sought to examine the prospective association between mtDNA copy number (mtDNA-CN), a surrogate marker of mitochondrial function, and SCD risk. METHODS AND RESULTS: We measured baseline mtDNA-CN in 11 093 participants from the Atherosclerosis Risk in Communities (ARIC) study. mtDNA copy number was calculated from probe intensities of mitochondrial single nucleotide polymorphisms (SNP) on the Affymetrix Genome-Wide Human SNP Array 6.0. Sudden cardiac death was defined as a sudden pulseless condition presumed due to a ventricular tachyarrhythmia in a previously stable individual without evidence of a non-cardiac cause of cardiac arrest. Sudden cardiac death cases were reviewed and adjudicated by an expert committee. During a median follow-up of 20.4 years, we observed 361 SCD cases. After adjusting for age, race, sex, and centre, the hazard ratio for SCD comparing the 1st to the 5th quintiles of mtDNA-CN was 2.24 (95% confidence interval 1.58-3.19; P-trend <0.001). When further adjusting for traditional cardiovascular disease risk factors, prevalent coronary heart disease, heart rate, QT interval, and QRS duration, the association remained statistically significant. Spline regression models showed that the association was approximately linear over the range of mtDNA-CN values. No apparent interaction by race or by sex was detected. CONCLUSION: In this community-based prospective study, mtDNA-CN in peripheral blood was inversely associated with the risk of SCD.
Keywords: Coronary Artery Disease; Death, Sudden, Cardiac; DNA Copy Number Variations; DNA, Mitochondrial; Female; Humans; Male; Middle Aged; Prospective Studies; Risk Factors

Association of Body Mass Index with DNA Methylation and Gene Expression in Blood Cells and Relations to Cardiometabolic Disease: A Mendelian Randomization Approach. - Mendelson, Michael M; Marioni, Riccardo E; Joehanes, Roby; Liu, Chunyu; Hedman, Åsa K; Aslibekyan, Stella; Demerath, Ellen W; Guan, Weihua; Zhi, Degui; Yao, Chen; Huan, Tianxiao; Willinger, Christine; et al. (PLoS Med, 2017)
BACKGROUND: The link between DNA methylation, obesity, and adiposity-related diseases in the general population remains uncertain. METHODS AND FINDINGS: We conducted an association study of body mass index (BMI) and differential methylation for over 400,000 CpGs assayed by microarray in whole-blood-derived DNA from 3,743 participants in the Framingham Heart Study and the Lothian Birth Cohorts, with independent replication in three external cohorts of 4,055 participants. We examined variations in whole blood gene expression and conducted Mendelian randomization analyses to investigate the functional and clinical relevance of the findings. We identified novel and previously reported BMI-related differential methylation at 83 CpGs that replicated across cohorts; BMI-related differential methylation was associated with concurrent changes in the expression of genes in lipid metabolism pathways. Genetic instrumental variable analysis of alterations in methylation at one of the 83 replicated CpGs, cg11024682 (intronic to sterol regulatory element binding transcription factor 1 [SREBF1]), demonstrated links to BMI, adiposity-related traits, and coronary artery disease. Independent genetic instruments for expression of SREBF1 supported the findings linking methylation to adiposity and cardiometabolic disease. Methylation at a substantial proportion (16 of 83) of the identified loci was found to be secondary to differences in BMI. However, the cross-sectional nature of the data limits definitive causal determination. CONCLUSIONS: We present robust associations of BMI with differential DNA methylation at numerous loci in blood cells. BMI-related DNA methylation and gene expression provide mechanistic insights into the relationship between DNA methylation, obesity, and adiposity-related diseases.
Keywords: Aged; Body Mass Index; Coronary Artery Disease; DNA Methylation; Epigenesis, Genetic; Female; Gene Expression Regulation; Genome-Wide Association Study; Humans; Leukocytes; Lipid Metabolism; Male; Mendelian Randomization Analysis; Obesity; Oligonucleotide Array Sequence Analysis

Characterization of chromosomal abnormalities in pregnancy losses reveals critical genes and loci for human early development. - Chen, Yiyun; Bartanus, Justin; Liang, Desheng; Zhu, Hongmin; Breman, Amy M; Smith, Janice L; Wang, Hua; Ren, Zhilin; Patel, Ankita; Stankiewicz, Pawel; Cram, David S; Cheung, Sau Wai; et al. (Hum Mutat, 2017)
Detailed characterization of chromosomal abnormalities, a common cause for congenital abnormalities and pregnancy loss, is critical for elucidating genes for human fetal development. Here, 2,186 product-of-conception samples were tested for copy-number variations (CNVs) at two clinical diagnostic centers using whole-genome sequencing and high-resolution chromosomal microarray analysis. We developed a new gene discovery approach to predict potential developmental genes and identified 275 candidate genes from CNVs detected from both datasets. Based on Mouse Genome Informatics (MGI) and Zebrafish model organism database (ZFIN), 75% of identified genes could lead to developmental defects when mutated. Genes involved in embryonic development, gene transcription, and regulation of biological processes were significantly enriched. Especially, transcription factors and gene families sharing specific protein domains predominated, which included known developmental genes such as HOX, NKX homeodomain genes, and helix-loop-helix containing HAND2, NEUROG2, and NEUROD1 as well as potential novel developmental genes. We observed that developmental genes were denser in certain chromosomal regions, enabling identification of 31 potential genomic loci with clustered genes associated with development.
Keywords: Animals; Chromosome Aberrations; Chromosome Disorders; DNA Copy Number Variations; Embryonic Development; Female; Genome, Human; Humans; Mice; Microarray Analysis; Pregnancy; Transcription Factors; Zebrafish

Comprehensive and Integrative Genomic Characterization of Hepatocellular Carcinoma. (Cell, 2017)
Liver cancer has the second highest worldwide cancer mortality rate and has limited therapeutic options. We analyzed 363 hepatocellular carcinoma (HCC) cases by whole-exome sequencing and DNA copy number analyses, and we analyzed 196 HCC cases by DNA methylation, RNA, miRNA, and proteomic expression also. DNA sequencing and mutation analysis identified significantly mutated genes, including LZTR1, EEF1A1, SF3B1, and SMARCA4. Significant alterations by mutation or downregulation by hypermethylation in genes likely to result in HCC metabolic reprogramming (ALB, APOB, and CPS1) were observed. Integrative molecular HCC subtyping incorporating unsupervised clustering of five data platforms identified three subtypes, one of which was associated with poorer prognosis in three HCC cohorts. Integrated analyses enabled development of a p53 target gene expression signature correlating with poor survival. Potential therapeutic targets for which inhibitors exist include WNT signaling, MDM4, MET, VEGFA, MCL1, IDH1, TERT, and immune checkpoint proteins CTLA-4, PD-1, and PD-L1.
Keywords: Carcinoma, Hepatocellular; DNA Methylation; Genomics; Humans; Isocitrate Dehydrogenase; Liver Neoplasms; MicroRNAs; Mutation

Comprehensive Genomic Characterization of Upper Tract Urothelial Carcinoma. - Moss, Tyler J; Qi, Yuan; Xi, Liu; Peng, Bo; Kim, Tae-Beom; Ezzedine, Nader E; Mosqueda, Maribel E; Guo, Charles C; Czerniak, Bogdan A; Ittmann, Michael; Wheeler, David A; Lerner, Seth P; et al. (Eur Urol, 2017)
BACKGROUND: Upper urinary tract urothelial cancer (UTUC) may have unique etiologic and genomic factors compared to bladder cancer. OBJECTIVE: To characterize the genomic landscape of UTUC and provide insights into its biology using comprehensive integrated genomic analyses. DESIGN, SETTING, AND PARTICIPANTS: We collected 31 untreated snap-frozen UTUC samples from two institutions and carried out whole-exome sequencing (WES) of DNA, RNA sequencing (RNAseq), and protein analysis. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Adjusting for batch effects, consensus mutation calls from independent pipelines identified DNA mutations, gene expression clusters using unsupervised consensus hierarchical clustering (UCHC), and protein expression levels that were correlated with relevant clinical variables, The Cancer Genome Atlas, and other published data. RESULTS AND LIMITATIONS: WES identified mutations in FGFR3 (74.1%; 92% low-grade, 60% high-grade), KMT2D (44.4%), PIK3CA (25.9%), and TP53 (22.2%). APOBEC and CpG were the most common mutational signatures. UCHC of RNAseq data segregated samples into four molecular subtypes with the following characteristics. Cluster 1: no PIK3CA mutations, nonsmokers, high-grade <pT2 tumors, high recurrences. Cluster 2: 100% FGFR3 mutations, low-grade tumors, tobacco use, noninvasive disease, no bladder recurrences. Cluster 3: 100% FGFR3 mutations, 71% PIK3CA, no TP53 mutations, five bladder recurrences, tobacco use, tumors all <pT2. Cluster 4: KMT2D (62.5%), FGFR3 (50%), TP53 (50%) mutations, no PIK3CA mutations, high-grade pT2+ disease, tobacco use, carcinoma in situ, shorter survival. We identified a novel SH3KBP1-CNTNAP5 fusion. CONCLUSIONS: Mutations in UTUC occur at differing frequencies from bladder cancer, with four unique molecular and clinical subtypes. A novel SH3KBP1 fusion regulates RTK signaling. Further studies are needed to validate the described subtypes, explore their responses to therapy, and better define the novel fusion mutation. PATIENT SUMMARY: We conducted a comprehensive study of the genetics of upper urinary tract urothelial cancer by evaluating DNA, RNA and protein expression in 31 tumors. We identified four molecular subtypes with distinct behaviors. Future studies will determine if these subtypes appear to have different responses to treatments.
Keywords: Aged; Aged, 80 and over; Biomarkers, Tumor; Cluster Analysis; Computational Biology; Databases, Genetic; DNA Mutational Analysis; Exome Sequencing; Female; Gene Expression Profiling; Genetic Predisposition to Disease; Genomics; Humans; Kidney Neoplasms; Kidney Pelvis; Male; Multigene Family; Mutation; Mutation Rate; Phenotype; Sequence Analysis, Protein; Sequence Analysis, RNA; Texas; Treatment Outcome; Ureter; Ureteral Neoplasms; Urinary Bladder Neoplasms; Urothelium

Congenital heart defects and left ventricular non-compaction in males with loss-of-function variants in NONO. - Scott, Daryl A; Hernandez-Garcia, Andres; Azamian, Mahshid S; Jordan, Valerie K; Kim, Bum Jun; Starkovich, Molly; Zhang, Jinglan; Wong, Lee-Jun; Darilek, Sandra A; Breman, Amy M; Yang, Yaping; Lupski, James R; et al. (J Med Genet, 2017)
BACKGROUND: The non-POU domain containing octamer-binding gene (NONO) is located on chromosome Xq13.1 and encodes a member of a small family of RNA-binding and DNA-binding proteins that perform a variety of tasks involved in RNA synthesis, transcriptional regulation and DNA repair. Loss-of-function variants in NONO have been described as a cause of intellectual disability in males but have not been described in association with congenital heart defects or cardiomyopathy. In this article, we seek to further define the phenotypic consequences of NONO depletion in human subjects. METHODS: We searched a clinical database of over 6000 individuals referred for exome sequencing and over 60 000 individuals referred for CNV analysis. RESULTS: We identified two males with atrial and ventricular septal defects, left ventricular non-compaction (LVNC), developmental delay and intellectual disability, who harboured de novo, loss-of-function variants in NONO. We also identified a male infant with developmental delay, congenital brain anomalies and severe LVNC requiring cardiac transplantation, who inherited a single-gene deletion of NONO from his asymptomatic mother. CONCLUSIONS: We conclude that in addition to global developmental delay and intellectual disability, males with loss-of-function variants in NONO may also be predisposed to developing congenital heart defects and LVNC with the penetrance of these cardiac-related problems being influenced by genetic, epigenetic, environmental or stochastic factors. Brain imaging of males with NONO deficiency may reveal structural defects with abnormalities of the corpus callosum being the most common. Although dysmorphic features vary between affected individuals, relative macrocephaly is a common feature.
Keywords: Child; Child, Preschool; Developmental Disabilities; DNA-Binding Proteins; Exome; Heart Defects, Congenital; Heart Ventricles; Humans; Infant; Male; Nuclear Matrix-Associated Proteins; Octamer Transcription Factors; RNA-Binding Proteins

Copy number increases of transposable elements and protein-coding genes in an invasive fish of hybrid origin. - Dennenmoser, Stefan; Sedlazeck, Fritz J; Iwaszkiewicz, Elzbieta; Li, Xiang-Yi; Altmüller, Janine; Nolte, Arne W (Mol Ecol, 2017)
Evolutionary dynamics of structural genetic variation in lineages of hybrid origin is not well explored, although structural mutations may increase in controlled hybrid crosses. We therefore tested whether structural variants accumulate in a fish of recent hybrid origin, invasive Cottus, relative to both parental species Cottus rhenanus and Cottus perifretum. Copy-number variation in exons of 10,979 genes was assessed using comparative genome hybridization arrays. Twelve genes showed significantly higher copy numbers in invasive Cottus compared to both parents. This coincided with increased expression for three genes related to vision, detoxification and muscle development, suggesting possible gene dosage effects. Copy number increases of putative transposons were assessed by comparative mapping of genomic DNA reads against a de novo assembly of 1,005 repetitive elements. In contrast to exons, copy number increases of repetitive elements were common (20.7%) in invasive Cottus, whereas decrease was very rare (0.01%). Among the increased repetitive elements, 53.8% occurred at higher numbers in C. perifretum compared to C. rhenanus, while only 1.4% were more abundant in C. rhenanus. This implies a biased mutational process that amplifies genetic material from one ancestor. To assess the frequency of de novo mutations through hybridization, we screened 64 laboratory-bred F offspring between the parental species for copy-number changes at five candidate loci. We found no evidence for new structural variants, indicating that they are too rare to be detected given our sampling scheme. Instead, they must have accumulated over more generations than we observed in a controlled cross.
Keywords: Animals; Biological Evolution; DNA Copy Number Variations; DNA Transposable Elements; Hybridization, Genetic; Introduced Species; Perciformes

Corner fracture type spondylometaphyseal dysplasia: Overlap with type II collagenopathies. - Machol, Keren; Jain, Mahim; Almannai, Mohammed; Orand, Thibault; Lu, James T; Tran, Alyssa; Chen, Yuqing; Schlesinger, Alan; Gibbs, Richard; Bonafe, Luisa; Campos-Xavier, Ana Belinda; Unger, Sheila; et al. (Am J Med Genet A, 2017)
Spondylometaphyseal dysplasia (SMD) corner fracture type (also known as SMD "Sutcliffe" type, MIM 184255) is a rare skeletal dysplasia that presents with mild to moderate short stature, developmental coxa vara, mild platyspondyly, corner fracture-like lesions, and metaphyseal abnormalities with sparing of the epiphyses. The molecular basis for this disorder has yet to be clarified. We describe two patients with SMD corner fracture type and heterozygous pathogenic variants in COL2A1. These two cases together with a third case of SMD corner fracture type with a heterozygous COL2A1 pathogenic variant previously described suggest that this disorder overlaps with type II collagenopathies. The finding of one of the pathogenic variants in a previously reported case of spondyloepimetaphyseal dysplasia (SEMD) Strudwick type and the significant clinical similarity suggest an overlap between SMD corner fracture and SEMD Strudwick types. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; Amino Acid Substitution; Bone Diseases, Developmental; Child, Preschool; Collagen Type II; Diagnosis, Differential; Exome; Genetic Association Studies; Genotype; Growth Disorders; High-Throughput Nucleotide Sequencing; Hip Joint; Humans; Infant; Male; Mutation; Osteochondrodysplasias; Phenotype; Radiography; Tibial Fractures

De Novo Disruption of the Proteasome Regulatory Subunit PSMD12 Causes a Syndromic Neurodevelopmental Disorder. - Küry, Sébastien; Besnard, Thomas; Ebstein, Frédéric; Khan, Tahir N; Gambin, Tomasz; Douglas, Jessica; Bacino, Carlos A; Craigen, William J; Sanders, Stephan J; Lehmann, Andrea; Latypova, Xénia; Khan, Kamal; et al. (Am J Hum Genet, 2017)
Degradation of proteins by the ubiquitin-proteasome system (UPS) is an essential biological process in the development of eukaryotic organisms. Dysregulation of this mechanism leads to numerous human neurodegenerative or neurodevelopmental disorders. Through a multi-center collaboration, we identified six de novo genomic deletions and four de novo point mutations involving PSMD12, encoding the non-ATPase subunit PSMD12 (aka RPN5) of the 19S regulator of 26S proteasome complex, in unrelated individuals with intellectual disability, congenital malformations, ophthalmologic anomalies, feeding difficulties, deafness, and subtle dysmorphic facial features. We observed reduced PSMD12 levels and an accumulation of ubiquitinated proteins without any impairment of proteasome catalytic activity. Our PSMD12 loss-of-function zebrafish CRISPR/Cas9 model exhibited microcephaly, decreased convolution of the renal tubules, and abnormal craniofacial morphology. Our data support the biological importance of PSMD12 as a scaffolding subunit in proteasome function during development and neurogenesis in particular; they enable the definition of a neurodevelopmental disorder due to PSMD12 variants, expanding the phenotypic spectrum of UPS-dependent disorders.
Keywords: Adolescent; Animals; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Down-Regulation; Female; Gene Deletion; Humans; Infant; Intellectual Disability; Male; Microcephaly; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Proteasome Endopeptidase Complex; Zebrafish

De Novo Missense Mutations in DHX30 Impair Global Translation and Cause a Neurodevelopmental Disorder. - Lessel, Davor; Schob, Claudia; Küry, Sébastien; Reijnders, Margot R F; Harel, Tamar; Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Denecke, Jonas; Edvardson, Shimon; Colin, Estelle; Stegmann, Alexander P A; Gerkes, Erica H; et al. (Am J Hum Genet, 2017)
DHX30 is a member of the family of DExH-box helicases, which use ATP hydrolysis to unwind RNA secondary structures. Here we identified six different de novo missense mutations in DHX30 in twelve unrelated individuals affected by global developmental delay (GDD), intellectual disability (ID), severe speech impairment and gait abnormalities. While four mutations are recurrent, two are unique with one affecting the codon of one recurrent mutation. All amino acid changes are located within highly conserved helicase motifs and were found to either impair ATPase activity or RNA recognition in different in vitro assays. Moreover, protein variants exhibit an increased propensity to trigger stress granule (SG) formation resulting in global translation inhibition. Thus, our findings highlight the prominent role of translation control in development and function of the central nervous system and also provide molecular insight into how DHX30 dysfunction might cause a neurodevelopmental disorder.
Keywords: Adenosine Triphosphatases; Adolescent; Amino Acids; Cell Line; Cell Line, Tumor; Central Nervous System; Child; Child, Preschool; Developmental Disabilities; Female; HEK293 Cells; Humans; Intellectual Disability; Male; Mutation, Missense; RNA; RNA Helicases

DNA Methylation Analysis Identifies Loci for Blood Pressure Regulation. - Richard, Melissa A; Huan, Tianxiao; Ligthart, Symen; Gondalia, Rahul; Jhun, Min A; Brody, Jennifer A; Irvin, Marguerite R; Marioni, Riccardo; Shen, Jincheng; Tsai, Pei-Chien; Montasser, May E; Jia, Yucheng; et al. (Am J Hum Genet, 2017)
Genome-wide association studies have identified hundreds of genetic variants associated with blood pressure (BP), but sequence variation accounts for a small fraction of the phenotypic variance. Epigenetic changes may alter the expression of genes involved in BP regulation and explain part of the missing heritability. We therefore conducted a two-stage meta-analysis of the cross-sectional associations of systolic and diastolic BP with blood-derived genome-wide DNA methylation measured on the Infinium HumanMethylation450 BeadChip in 17,010 individuals of European, African American, and Hispanic ancestry. Of 31 discovery-stage cytosine-phosphate-guanine (CpG) dinucleotides, 13 replicated after Bonferroni correction (discovery: N = 9,828, p < 1.0 × 10; replication: N = 7,182, p < 1.6 × 10). The replicated methylation sites are heritable (h > 30%) and independent of known BP genetic variants, explaining an additional 1.4% and 2.0% of the interindividual variation in systolic and diastolic BP, respectively. Bidirectional Mendelian randomization among up to 4,513 individuals of European ancestry from 4 cohorts suggested that methylation at cg08035323 (TAF1B-YWHAQ) influences BP, while BP influences methylation at cg00533891 (ZMIZ1), cg00574958 (CPT1A), and cg02711608 (SLC1A5). Gene expression analyses further identified six genes (TSPAN2, SLC7A11, UNC93B1, CPT1A, PTMS, and LPCAT3) with evidence of triangular associations between methylation, gene expression, and BP. Additional integrative Mendelian randomization analyses of gene expression and DNA methylation suggested that the expression of TSPAN2 is a putative mediator of association between DNA methylation at cg23999170 and BP. These findings suggest that heritable DNA methylation plays a role in regulating BP independently of previously known genetic variants.
Keywords: Aged; Blood Pressure; CpG Islands; Cross-Sectional Studies; DNA Methylation; Epigenesis, Genetic; Genetic Variation; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Middle Aged; Nerve Tissue Proteins; Quantitative Trait Loci; Tetraspanins

Enrichment of mutations in chromatin regulators in people with Rett syndrome lacking mutations in MECP2. - Sajan, Samin A; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; Glaze, Daniel G; Kaufmann, Walter E; Skinner, Steven A; Annese, Fran; Friez, Michael J; Lane, Jane; Percy, Alan K; et al. (Genet Med, 2017)
PURPOSE: Rett syndrome (RTT) is a neurodevelopmental disorder caused primarily by de novo mutations in MECP2 and sometimes in CDKL5 and FOXG1. However, some RTT patients lack mutations in these genes. METHODS: Twenty-two RTT patients without apparent MECP2, CDKL5, and FOXG1 mutations were subjected to both whole-exome sequencing and single-nucleotide polymorphism array-based copy-number variant (CNV) analyses. RESULTS: Three patients had MECP2 mutations initially missed by clinical testing. Of the remaining 19, 17 (89.5%) had 29 other likely pathogenic intragenic mutations and/or CNVs (10 patients had 2 or more). Interestingly, 13 patients had mutations in a gene/region previously reported in other neurodevelopmental disorders (NDDs), thereby providing a potential diagnostic yield of 68.4%. These mutations were significantly enriched in chromatin regulators (corrected P = 0.0068) and moderately enriched in postsynaptic cell membrane molecules (corrected P = 0.076), implicating glutamate receptor signaling. CONCLUSION: The genetic etiology of RTT without MECP2, CDKL5, and FOXG1 mutations is heterogeneous, overlaps with other NDDs, and complicated by a high mutation burden. Dysregulation of chromatin structure and abnormal excitatory synaptic signaling may form two common pathological bases of RTT.Genet Med 19 1, 13-19.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromatin; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Humans; Infant; Male; Methyl-CpG-Binding Protein 2; Mutation; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases; Rett Syndrome

Evolutionary History of Chemosensory-Related Gene Families across the Arthropoda. - Eyun, Seong-Il; Soh, Ho Young; Posavi, Marijan; Munro, James B; Hughes, Daniel S T; Murali, Shwetha C; Qu, Jiaxin; Dugan, Shannon; Lee, Sandra L; Chao, Hsu; Dinh, Huyen; Han, Yi; et al. (Mol Biol Evol, 2017)
Chemosensory-related gene (CRG) families have been studied extensively in insects, but their evolutionary history across the Arthropoda had remained relatively unexplored. Here, we address current hypotheses and prior conclusions on CRG family evolution using a more comprehensive data set. In particular, odorant receptors were hypothesized to have proliferated during terrestrial colonization by insects (hexapods), but their association with other pancrustacean clades and with independent terrestrial colonizations in other arthropod subphyla have been unclear. We also examine hypotheses on which arthropod CRG family is most ancient. Thus, we reconstructed phylogenies of CRGs, including those from new arthropod genomes and transcriptomes, and mapped CRG gains and losses across arthropod lineages. Our analysis was strengthened by including crustaceans, especially copepods, which reside outside the hexapod/branchiopod clade within the subphylum Pancrustacea. We generated the first high-resolution genome sequence of the copepod Eurytemora affinis and annotated its CRGs. We found odorant receptors and odorant binding proteins present only in hexapods (insects) and absent from all other arthropod lineages, indicating that they are not universal adaptations to land. Gustatory receptors likely represent the oldest chemosensory receptors among CRGs, dating back to the Placozoa. We also clarified and confirmed the evolutionary history of antennal ionotropic receptors across the Arthropoda. All antennal ionotropic receptors in E. affinis were expressed more highly in males than in females, suggestive of an association with male mate-recognition behavior. This study is the most comprehensive comparative analysis to date of CRG family evolution across the largest and most speciose metazoan phylum Arthropoda.
Keywords: Animals; Arthropods; Chemoreceptor Cells; Copepoda; Crustacea; Databases, Nucleic Acid; Evolution, Molecular; Genome; Insecta; Multigene Family; Phylogeny; Receptors, Odorant

Exome-wide association study of plasma lipids in >300,000 individuals. - Liu, Dajiang J; Peloso, Gina M; Yu, Haojie; Butterworth, Adam S; Wang, Xiao; Mahajan, Anubha; Saleheen, Danish; Emdin, Connor; Alam, Dewan; Alves, Alexessander Couto; Amouyel, Philippe; Di Angelantonio, Emanuele; et al. (Nat Genet, 2017)
We screened variants on an exome-focused genotyping array in >300,000 participants (replication in >280,000 participants) and identified 444 independent variants in 250 loci significantly associated with total cholesterol (TC), high-density-lipoprotein cholesterol (HDL-C), low-density-lipoprotein cholesterol (LDL-C), and/or triglycerides (TG). At two loci (JAK2 and A1CF), experimental analysis in mice showed lipid changes consistent with the human data. We also found that: (i) beta-thalassemia trait carriers displayed lower TC and were protected from coronary artery disease (CAD); (ii) excluding the CETP locus, there was not a predictable relationship between plasma HDL-C and risk for age-related macular degeneration; (iii) only some mechanisms of lowering LDL-C appeared to increase risk for type 2 diabetes (T2D); and (iv) TG-lowering alleles involved in hepatic production of TG-rich lipoproteins (TM6SF2 and PNPLA3) tracked with higher liver fat, higher risk for T2D, and lower risk for CAD, whereas TG-lowering alleles involved in peripheral lipolysis (LPL and ANGPTL4) had no effect on liver fat but decreased risks for both T2D and CAD.
Keywords: Coronary Artery Disease; Diabetes Mellitus, Type 2; Exome; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Lipids; Macular Degeneration; Phenotype; Risk Factors

An Expanded Genome-Wide Association Study of Type 2 Diabetes in Europeans. - Scott, Robert A; Scott, Laura J; Mägi, Reedik; Marullo, Letizia; Gaulton, Kyle J; Kaakinen, Marika; Pervjakova, Natalia; Pers, Tune H; Johnson, Andrew D; Eicher, John D; Jackson, Anne U; Ferreira, Teresa; et al. (Diabetes, 2017)
To characterize type 2 diabetes (T2D)-associated variation across the allele frequency spectrum, we conducted a meta-analysis of genome-wide association data from 26,676 T2D case and 132,532 control subjects of European ancestry after imputation using the 1000 Genomes multiethnic reference panel. Promising association signals were followed up in additional data sets (of 14,545 or 7,397 T2D case and 38,994 or 71,604 control subjects). We identified 13 novel T2D-associated loci ( < 5 × 10), including variants near the , , and genes. Our analysis brought the total number of independent T2D associations to 128 distinct signals at 113 loci. Despite substantially increased sample size and more complete coverage of low-frequency variation, all novel associations were driven by common single nucleotide variants. Credible sets of potentially causal variants were generally larger than those based on imputation with earlier reference panels, consistent with resolution of causal signals to common risk haplotypes. Stratification of T2D-associated loci based on T2D-related quantitative trait associations revealed tissue-specific enrichment of regulatory annotations in pancreatic islet enhancers for loci influencing insulin secretion and in adipocytes, monocytes, and hepatocytes for insulin action-associated loci. These findings highlight the predominant role played by common variants of modest effect and the diversity of biological mechanisms influencing T2D pathophysiology.
Keywords: Diabetes Mellitus, Type 2; Gene Expression Regulation; Genetic Variation; Genome-Wide Association Study; Humans; White People

The Genetic Causes of Nonsyndromic Congenital Retinal Detachment: A Genetic and Phenotypic Study of Pakistani Families. - Keser, Vafa; Khan, Ayesha; Siddiqui, Sorath; Lopez, Irma; Ren, Huanan; Qamar, Raheel; Nadaf, Javad; Majewski, Jacek; Chen, Rui; Koenekoop, Robert K (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: To evaluate consanguineous pedigrees from Pakistan with a clinical diagnosis of nonsyndromic congenital retinal nonattachment (NCRNA) and identify genes responsible for the disease as currently only one NCRNA gene is known (atonal basic helix-loop-helix transcription factor 7: ATOH7). METHODS: We implemented a three-step genotyping platform: single nucleotide polymorphism genotyping to identify loss of heterozygosity regions in patients, Retinal Information Network panel screening for mutations in currently known retinal genes. Negative patients were then subjected to whole exome sequencing. RESULTS: We evaluated 21 consanguineous NCRNA pedigrees and identified the causal mutations in known retinal genes in 13 out of our 21 families. We found mutations in ATOH7 in three families. Surprisingly, we then found mutations in familial exudative vitreoretinopathy (FEVR) genes; low-density lipoprotein receptor-related protein 5 mutations (six families), tetraspanin 12 mutations (two families), and NDP mutations (two families). Thus, 62% of the patients were successfully genotyped in our study with seven novel and six previously reported mutations in known retinal genes. CONCLUSIONS: Although the clinical diagnosis of all children was NCRNA with severe congenital fibrotic retinal detachments, the molecular diagnosis determined that the disease process was in fact a very severe form of FEVR in 10 families. Because severe congenital retinal detachment has not been previously associated with all the FEVR genes, we have thus expanded the phenotypic spectrum of FEVR, a highly variable retinal detachment phenotype that has clinical overlap with NCRNA. We identified seven novel mutations. We also established for the first time genetic overlap between the Iranian and Pakistani populations. We identified eight NCRNA families that do not harbor mutations in any known retinal genes, suggesting novel causal genes in these families.
Keywords: Basic Helix-Loop-Helix Transcription Factors; Child; Child, Preschool; DNA Mutational Analysis; Female; Genotype; Helix-Loop-Helix Motifs; Humans; Incidence; Infant; Male; Mutation; Pakistan; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Retina; Retinal Diseases

Genetic variants associated with risk of Alzheimer's disease contribute to cognitive change in midlife: The Atherosclerosis Risk in Communities Study. - Bressler, Jan; Mosley, Thomas H; Penman, Alan; Gottesman, Rebecca F; Windham, Beverly Gwen; Knopman, David S; Wruck, Lisa M; Boerwinkle, Eric (Am J Med Genet B Neuropsychiatr Genet, 2017)
Alzheimer's disease (AD) is the most common form of dementia and is characterized by impairment in memory, behavioral changes, and gradual loss of autonomy. Since there is a long latent period prior to diagnosis, the aim of this study was to determine whether twenty single nucleotide polymorphisms identified in genome-wide association analyses of AD are associated with cognitive change in 8,320 white and 2,039 African-American middle-aged adults enrolled in the prospective Atherosclerosis Risk in Communities (ARIC) study. Cognition was evaluated using the Delayed Word Recall Test (DWRT; verbal memory), Digit Symbol Substitution Test (DSST; processing speed), and Word Fluency Test (WFT; executive function). General linear models were used to assess mean differences in 6-year change in test scores among individuals categorized by genotype after adjusting for age, gender, and years of education. Addition of the minor allele for rs670139 (MS4A4E), rs9331896 (CLU), and rs12155159 (NME8) was nominally associated with change on the DWRT, DSST, and WFT, respectively, in whites. The ZCWPW1 (rs1476679) and CDS33 (rs3865444) variants were nominally associated with change on the DWRT and WFT in African-Americans. For rs670139 and rs9331896 the association was only significant in individuals bearing at least one APOE ϵ4 allele in stratified analyses. An unweighted genetic risk score aggregating the risk alleles for 15 polymorphisms was not associated with change in cognitive function. Although the AD-associated genetic variants appear to have small effects on early cognitive change, replication will be required to establish whether there is a discernible influence on cognitive status in midlife. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; Alzheimer Disease; Atherosclerosis; Black or African American; Black People; Clusterin; Cognition; Cognition Disorders; Dementia; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Membrane Proteins; Memory; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Thioredoxins; White People

Genome-wide association study of 1,5-anhydroglucitol identifies novel genetic loci linked to glucose metabolism. - Li, Man; Maruthur, Nisa M; Loomis, Stephanie J; Pietzner, Maik; North, Kari E; Mei, Hao; Morrison, Alanna C; Friedrich, Nele; Pankow, James S; Nauck, Matthias; Boerwinkle, Eric; Teumer, Alexander; et al. (Sci Rep, 2017)
1,5-anhydroglucitol (1,5-AG) is a biomarker of hyperglycemic excursions associated with diabetic complications. Because of its structural similarity to glucose, genetic studies of 1,5-AG can deliver complementary insights into glucose metabolism. We conducted genome-wide association studies of serum 1,5-AG concentrations in 7,550 European ancestry (EA) and 2,030 African American participants (AA) free of diagnosed diabetes from the ARIC Study. Seven loci in/near EFNA1/SLC50A1, MCM6/LCT, SI, MGAM, MGAM2, SLC5A10, and SLC5A1 showed genome-wide significant associations (P < 5 × 10) among EA participants, five of which were novel. Six of the seven loci were successfully replicated in 8,790 independent EA individuals, and MCM6/LCT and SLC5A10 were also associated among AA. Most of 1,5-AG-associated index SNPs were not associated with the clinical glycemic markers fasting glucose or the  HbA1c, and vice versa. Only the index variant in SLC5A1 showed a significant association with fasting glucose in the expected opposing direction. Products of genes in all 1,5-AG-associated loci have known roles in carbohydrate digestion and enteral or renal glucose transport, suggesting that genetic variants associated with 1,5-AG influence its concentration via effects on glucose metabolism and handling.
Keywords: Aged; Black or African American; Deoxyglucose; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose; Glycated Hemoglobin; Humans; Hyperglycemia; Insulin; Male; Middle Aged; Minichromosome Maintenance Complex Component 6; Sodium-Glucose Transporter 1; White People

Genomics of natural populations: Evolutionary forces that establish and maintain gene arrangements in Drosophila pseudoobscura. - Fuller, Zachary L; Haynes, Gwilym D; Richards, Stephen; Schaeffer, Stephen W (Mol Ecol, 2017)
The evolution of complex traits in heterogeneous environments may shape the order of genes within chromosomes. Drosophila pseudoobscura has a rich gene arrangement polymorphism that allows one to test evolutionary genetic hypotheses about how chromosomal inversions are established in populations. D. pseudoobscura has >30 gene arrangements on a single chromosome that were generated through a series of overlapping inversion mutations with >10 inversions with appreciable frequencies and wide geographic distributions. This study analyses the genomic sequences of 54 strains of Drosophila pseudoobscura that carry one of six different chromosomal arrangements to test whether (i) genetic drift, (ii) hitchhiking with an adaptive allele, (iii) direct effects of inversions to create gene disruptions caused by breakpoints, or (iv) indirect effects of inversions in limiting the formation of recombinant gametes are responsible for the establishment of new gene arrangements. We found that the inversion events do not disrupt the structure of protein coding genes at the breakpoints. Population genetic analyses of 2,669 protein coding genes identified 277 outlier loci harbouring elevated frequencies of arrangement-specific derived alleles. Significant linkage disequilibrium occurs among distant loci interspersed between regions with low levels of association indicating that distant allelic combinations are held together despite shared polymorphism among arrangements. Outlier genes showing evidence of genetic differentiation between arrangements are enriched for sensory perception and detoxification genes. The data presented here support the indirect effect of inversion hypothesis where chromosomal inversions are favoured because they maintain linked associations among multilocus allelic combinations among different arrangements.
Keywords: Alleles; Animals; Chromosome Inversion; Chromosome Mapping; Drosophila; Evolution, Molecular; Gene Frequency; Gene Order; Genetics, Population; High-Throughput Nucleotide Sequencing; Linkage Disequilibrium; Phylogeny; Sequence Analysis, DNA

A golden goat genome. - Worley, Kim C (Nat Genet, 2017)
The newly described de novo goat genome sequence is the most contiguous diploid vertebrate assembly generated thus far using whole-genome assembly and scaffolding methods. The contiguity of this assembly is approaching that of the finished human and mouse genomes and suggests an affordable roadmap to high-quality references for thousands of species.
Keywords: Aged; Animals; Diploidy; Genome; Goats; Humans; Mice

The gut mycobiome of the Human Microbiome Project healthy cohort. - Nash, Andrea K; Auchtung, Thomas A; Wong, Matthew C; Smith, Daniel P; Gesell, Jonathan R; Ross, Matthew C; Stewart, Christopher J; Metcalf, Ginger A; Muzny, Donna M; Gibbs, Richard A; Ajami, Nadim J; Petrosino, Joseph F (Microbiome, 2017)
BACKGROUND: Most studies describing the human gut microbiome in healthy and diseased states have emphasized the bacterial component, but the fungal microbiome (i.e., the mycobiome) is beginning to gain recognition as a fundamental part of our microbiome. To date, human gut mycobiome studies have primarily been disease centric or in small cohorts of healthy individuals. To contribute to existing knowledge of the human mycobiome, we investigated the gut mycobiome of the Human Microbiome Project (HMP) cohort by sequencing the Internal Transcribed Spacer 2 (ITS2) region as well as the 18S rRNA gene. RESULTS: Three hundred seventeen HMP stool samples were analyzed by ITS2 sequencing. Fecal fungal diversity was significantly lower in comparison to bacterial diversity. Yeast dominated the samples, comprising eight of the top 15 most abundant genera. Specifically, fungal communities were characterized by a high prevalence of Saccharomyces, Malassezia, and Candida, with S. cerevisiae, M. restricta, and C. albicans operational taxonomic units (OTUs) present in 96.8, 88.3, and 80.8% of samples, respectively. There was a high degree of inter- and intra-volunteer variability in fungal communities. However, S. cerevisiae, M. restricta, and C. albicans OTUs were found in 92.2, 78.3, and 63.6% of volunteers, respectively, in all samples donated over an approximately 1-year period. Metagenomic and 18S rRNA gene sequencing data agreed with ITS2 results; however, ITS2 sequencing provided greater resolution of the relatively low abundance mycobiome constituents. CONCLUSIONS: Compared to bacterial communities, the human gut mycobiome is low in diversity and dominated by yeast including Saccharomyces, Malassezia, and Candida. Both inter- and intra-volunteer variability in the HMP cohort were high, revealing that unlike bacterial communities, an individual's mycobiome is no more similar to itself over time than to another person's. Nonetheless, several fungal species persisted across a majority of samples, evidence that a core gut mycobiome may exist. ITS2 sequencing data provided greater resolution of the mycobiome membership compared to metagenomic and 18S rRNA gene sequencing data, suggesting that it is a more sensitive method for studying the mycobiome of stool samples.
Keywords: Candida; Cohort Studies; DNA, Ribosomal Spacer; Feces; Fungi; Gastrointestinal Microbiome; Genetic Variation; Healthy Volunteers; High-Throughput Nucleotide Sequencing; Humans; Malassezia; Metagenomics; Microbiota; Mycobiome; RNA, Ribosomal, 18S; Saccharomyces; Sequence Analysis, DNA

Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features. - Zhang, Jing; Gambin, Tomasz; Yuan, Bo; Szafranski, Przemyslaw; Rosenfeld, Jill A; Balwi, Mohammed Al; Alswaid, Abdulrahman; Al-Gazali, Lihadh; Shamsi, Aisha M Al; Komara, Makanko; Ali, Bassam R; Roeder, Elizabeth; et al. (Hum Genet, 2017)
Impairment of ubiquitin-proteasome system activity involving ubiquitin ligase genes UBE3A, UBE3B, and HUWE1 and deubiquitinating enzyme genes USP7 and USP9X has been reported in patients with neurodevelopmental delays. To date, only a handful of single-nucleotide variants (SNVs) and copy-number variants (CNVs) involving TRIP12, encoding a member of the HECT domain E3 ubiquitin ligases family on chromosome 2q36.3 have been reported. Using chromosomal microarray analysis and whole-exome sequencing (WES), we have identified, respectively, five deletion CNVs and four inactivating SNVs (two frameshifts, one missense, and one splicing) in TRIP12. Seven of these variants were found to be de novo; parental studies could not be completed in two families. Quantitative PCR analyses of the splicing mutation showed a dramatically decreased level of TRIP12 mRNA in the proband compared to the family controls, indicating a loss-of-function mechanism. The shared clinical features include intellectual disability with or without autistic spectrum disorders, speech delay, and facial dysmorphism. Our findings demonstrate that E3 ubiquitin ligase TRIP12 plays an important role in nervous system development and function. The nine presented pathogenic variants further document that TRIP12 haploinsufficiency causes a childhood-onset neurodevelopmental disorder. Finally, our data enable expansion of the phenotypic spectrum of ubiquitin-proteasome dependent disorders.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Cohort Studies; DNA Copy Number Variations; Facies; Female; Haploinsufficiency; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Ubiquitin-Protein Ligases

Heterozygous variants in ACTL6A, encoding a component of the BAF complex, are associated with intellectual disability. - Marom, Ronit; Jain, Mahim; Burrage, Lindsay C; Song, I-Wen; Graham, Brett H; Brown, Chester W; Stevens, Servi J C; Stegmann, Alexander P A; Gunter, Andrew T; Kaplan, Julie D; Gavrilova, Ralitza H; Shinawi, Marwan; et al. (Hum Mutat, 2017)
Pathogenic variants in genes encoding components of the BRG1-associated factor (BAF) chromatin remodeling complex have been associated with intellectual disability syndromes. We identified heterozygous, novel variants in ACTL6A, a gene encoding a component of the BAF complex, in three subjects with varying degrees of intellectual disability. Two subjects have missense variants affecting highly conserved amino acid residues within the actin-like domain. Missense mutations in the homologous region in yeast actin were previously reported to be dominant lethal and were associated with impaired binding of the human ACTL6A to β-actin and BRG1. A third subject has a splicing variant that creates an in-frame deletion. Our findings suggest that the variants identified in our subjects may have a deleterious effect on the function of the protein by disturbing the integrity of the BAF complex. Thus, ACTL6A gene mutation analysis should be considered in patients with intellectual disability, learning disabilities, or developmental language disorder.
Keywords: Actins; Adolescent; Child; Chromatin Assembly and Disassembly; Chromosomal Proteins, Non-Histone; DNA Helicases; DNA-Binding Proteins; Exome; Face; Female; Hand Deformities, Congenital; Heterozygote; Humans; Intellectual Disability; Male; Micrognathism; Multiprotein Complexes; Mutation, Missense; Nuclear Proteins; Protein Binding; Transcription Factors

Homozygous and hemizygous CNV detection from exome sequencing data in a Mendelian disease cohort. - Gambin, Tomasz; Akdemir, Zeynep C; Yuan, Bo; Gu, Shen; Chiang, Theodore; Carvalho, Claudia M B; Shaw, Chad; Jhangiani, Shalini; Boone, Philip M; Eldomery, Mohammad K; Karaca, Ender; Bayram, Yavuz; et al. (Nucleic Acids Res, 2017)
We developed an algorithm, HMZDelFinder, that uses whole exome sequencing (WES) data to identify rare and intragenic homozygous and hemizygous (HMZ) deletions that may represent complete loss-of-function of the indicated gene. HMZDelFinder was applied to 4866 samples in the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) cohort and detected 773 HMZ deletion calls (567 homozygous or 206 hemizygous) with an estimated sensitivity of 86.5% (82% for single-exonic and 88% for multi-exonic calls) and precision of 78% (53% single-exonic and 96% for multi-exonic calls). Out of 773 HMZDelFinder-detected deletion calls, 82 were subjected to array comparative genomic hybridization (aCGH) and/or breakpoint PCR and 64 were confirmed. These include 18 single-exon deletions out of which 8 were exclusively detected by HMZDelFinder and not by any of seven other CNV detection tools examined. Further investigation of the 64 validated deletion calls revealed at least 15 pathogenic HMZ deletions. Of those, 7 accounted for 17-50% of pathogenic CNVs in different disease cohorts where 7.1-11% of the molecular diagnosis solved rate was attributed to CNVs. In summary, we present an algorithm to detect rare, intragenic, single-exon deletion CNVs using WES data; this tool can be useful for disease gene discovery efforts and clinical WES analyses.
Keywords: Algorithms; Alternative Splicing; Cohort Studies; Computational Biology; Consanguinity; Datasets as Topic; DNA Copy Number Variations; Exome; Genetic Diseases, Inborn; Hemizygote; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Inheritance Patterns; Models, Genetic; Pedigree; Reproducibility of Results; Sequence Deletion; Workflow

Identification of established arrhythmogenic right ventricular cardiomyopathy mutation in a patient with the contrasting phenotype of hypertrophic cardiomyopathy. - Bainbridge, Matthew Neil; Li, Lili; Tan, Yanli; Cheong, Benjamin Y; Marian, Ali J (BMC Med Genet, 2017)
BACKGROUND: Advances in the nucleic acid sequencing technologies have ushered in the era of genetic-based "precision medicine". Applications of the genetic discoveries to practice of medicine, however, are hindered by phenotypic variability of the genetic variants. The report illustrates extreme pleiotropic phenotypes associated with an established causal mutation for hereditary cardiomyopathy. CASE PRESENTATION: We report a 61-year old white female who presented with syncope and echocardiographic and cardiac magnetic resonance (CMR) imaging findings consistent with the diagnosis of hypertrophic cardiomyopathy (HCM). The electrocardiogram, however, showed a QRS pattern resembling an Epsilon wave, a feature of arrhythmogenic right ventricular cardiomyopathy (ARVC). Whole exome sequencing (mean depth of coverage of exons 178X) analysis did not identify a pathogenic variant in the known HCM genes but identified an established causal mutation for ARVC. The mutation involves a canonical splice accepter site (c.2146-1G > C) in the PKP2 gene, which encodes plakophillin 2. Sanger sequencing confirmed the mutation. PKP2 is the most common causal gene for ARVC but has not been implicated in HCM. Findings on echocardiography and CMR during the course of 4-year follow up showed septal hypertrophy and a hyperdynamic left ventricle, consistent with the diagnosis of HCM. However, neither baseline nor follow up echocardiography and CMR studies showed evidence of ARVC. The right ventricle was normal in size, thickness, and function and there was no evidence of fibro-fatty infiltration in the myocardium. CONCLUSIONS: The patient carries an established pathogenic mutation for ARVC and a subtle finding of ARVC but exhibits the classic phenotype of HCM, a contrasting phenotype to ARVC. The case illustrates the need for detailed phenotypic characterization for patients with hereditary cardiomyopathies as well as the challenges physicians face in applying the genetic discoveries in practicing genetic-based "precision medicine".
Keywords: Cardiomyopathy, Hypertrophic; DNA; DNA Mutational Analysis; Echocardiography; Female; Heart; Heart Ventricles; Humans; Magnetic Resonance Imaging; Middle Aged; Pedigree; Phenotype; Plakophilins

Identification of novel candidate disease genes from de novo exonic copy number variants. - Gambin, Tomasz; Bo Yuan; Bi, Weimin; Liu, Pengfei; Rosenfeld, Jill A; Coban-Akdemir, Zeynep; Pursley, Amber N; Nagamani, Sandesh C S; Marom, Ronit; Golla, Sailaja; Dengle, Lauren; Petrie, Heather G; et al. (Genome Med, 2017)
BACKGROUND: Exon-targeted microarrays can detect small (<1000 bp) intragenic copy number variants (CNVs), including those that affect only a single exon. This genome-wide high-sensitivity approach increases the molecular diagnosis for conditions with known disease-associated genes, enables better genotype-phenotype correlations, and facilitates variant allele detection allowing novel disease gene discovery. METHODS: We retrospectively analyzed data from 63,127 patients referred for clinical chromosomal microarray analysis (CMA) at Baylor Genetics laboratories, including 46,755 individuals tested using exon-targeted arrays, from 2007 to 2017. Small CNVs harboring a single gene or two to five non-disease-associated genes were identified; the genes involved were evaluated for a potential disease association. RESULTS: In this clinical population, among rare CNVs involving any single gene reported in 7200 patients (11%), we identified 145 de novo autosomal CNVs (117 losses and 28 intragenic gains), 257 X-linked deletion CNVs in males, and 1049 inherited autosomal CNVs (878 losses and 171 intragenic gains); 111 known disease genes were potentially disrupted by de novo autosomal or X-linked (in males) single-gene CNVs. Ninety-one genes, either recently proposed as candidate disease genes or not yet associated with diseases, were disrupted by 147 single-gene CNVs, including 37 de novo deletions and ten de novo intragenic duplications on autosomes and 100 X-linked CNVs in males. Clinical features in individuals with de novo or X-linked CNVs encompassing at most five genes (224 bp to 1.6 Mb in size) were compared to those in individuals with larger-sized deletions (up to 5 Mb in size) in the internal CMA database or loss-of-function single nucleotide variants (SNVs) detected by clinical or research whole-exome sequencing (WES). This enabled the identification of recently published genes (BPTF, NONO, PSMD12, TANGO2, and TRIP12), novel candidate disease genes (ARGLU1 and STK3), and further confirmation of disease association for two recently proposed disease genes (MEIS2 and PTCHD1). Notably, exon-targeted CMA detected several pathogenic single-exon CNVs missed by clinical WES analyses. CONCLUSIONS: Together, these data document the efficacy of exon-targeted CMA for detection of genic and exonic CNVs, complementing and extending WES in clinical diagnostics, and the potential for discovery of novel disease genes by genome-wide assay.
Keywords: Cohort Studies; DNA Copy Number Variations; Exons; Genetic Diseases, Inborn; Genome, Human; Homeodomain Proteins; Humans; Intracellular Signaling Peptides and Proteins; Membrane Proteins; Neurodevelopmental Disorders; Protein Serine-Threonine Kinases; Retrospective Studies; Serine-Threonine Kinase 3; Transcription Factors; Whole Genome Sequencing

IFT81 as a Candidate Gene for Nonsyndromic Retinal Degeneration. - Dharmat, Rachayata; Liu, Wei; Ge, Zhongqi; Sun, Zixi; Yang, Lizhu; Li, Yumei; Wang, Keqing; Thomas, Kandace; Sui, Ruifang; Chen, Rui (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: IFT81, a core component of the IFT-B complex, involved in the bidirectional transport of ciliary proteins, has been recently implicated in syndromic ciliopathies. However, none of the IFT-B core complex proteins have been associated with nonsyndromic retinal dystrophies. Given the importance of ciliary transport in photoreceptor function and structural maintenance, we sought to investigate the impact of IFT (intraflagellar transport) mutations in nonsyndromic retinopathies. METHODS: Whole exome sequencing was performed on 50 cone-rod dystrophy (CRD) patients that were previously screened for mutations in known retinal disease genes. The impact of candidate mutation was studied using in vitro cell system and in vivo zebrafish assay to determine the pathogenicity of the variant. RESULTS: Compound heterozygous mutations in IFT81, including one nonsense (c.1213C>T, p.R405*) and one missense variant (c.1841T>C, p.L614P), were identified in a nonsyndromic CRD proband. Extensive functional analyses of the missense variant in cell culture and zebrafish strongly suggests its pathogenic nature. Loss of IFT81 impairs ciliogenesis and, interestingly, the missense variant displayed significantly reduced rescue of ciliogenesis in the IFT81 knockdown in vitro system. Consistently, dramatic reduction of rescue efficiency of the ift81 mutant zebrafish embryo by mRNA with the missense variant was observed, further supporting its pathogenicity. CONCLUSIONS: Consistent with the function of the IFT-B complex in the maintenance of photoreceptor cilium, we report a case of mutations in a core IFT-B protein, IFT81. This represents the first report of mutations in IFT81 as a candidate gene for nonsyndromic retinal dystrophy, hence expanding the phenotype spectrum of IFT-B components.
Keywords: Animals; Cells, Cultured; Codon, Nonsense; Disease Models, Animal; DNA; DNA Mutational Analysis; Female; Humans; Male; Muscle Proteins; Mutation; Phenotype; Retina; Retinal Degeneration; Zebrafish

Improved annotation of the insect vector of citrus greening disease: biocuration by a diverse genomics community. - Saha, Surya; Hosmani, Prashant S; Villalobos-Ayala, Krystal; Miller, Sherry; Shippy, Teresa; Flores, Mirella; Rosendale, Andrew; Cordola, Chris; Bell, Tracey; Mann, Hannah; DeAvila, Gabe; DeAvila, Daniel; et al. (Database (Oxford), 2017)
https://citrusgreening.org/.
Keywords: Animals; Citrus; Databases, Genetic; Genome, Insect; Hemiptera; Insect Vectors; Pest Control; Plant Diseases; Rhizobiaceae

Integrative Genomic Analysis of Cholangiocarcinoma Identifies Distinct IDH-Mutant Molecular Profiles. - Farshidfar, Farshad; Zheng, Siyuan; Gingras, Marie-Claude; Newton, Yulia; Shih, Juliann; Robertson, A Gordon; Hinoue, Toshinori; Hoadley, Katherine A; Gibb, Ewan A; Roszik, Jason; Covington, Kyle R; Wu, Chia-Chin; et al. (Cell Rep, 2017)
Cholangiocarcinoma (CCA) is an aggressive malignancy of the bile ducts, with poor prognosis and limited treatment options. Here, we describe the integrated analysis of somatic mutations, RNA expression, copy number, and DNA methylation by The Cancer Genome Atlas of a set of predominantly intrahepatic CCA cases and propose a molecular classification scheme. We identified an IDH mutant-enriched subtype with distinct molecular features including low expression of chromatin modifiers, elevated expression of mitochondrial genes, and increased mitochondrial DNA copy number. Leveraging the multi-platform data, we observed that ARID1A exhibited DNA hypermethylation and decreased expression in the IDH mutant subtype. More broadly, we found that IDH mutations are associated with an expanded histological spectrum of liver tumors with molecular features that stratify with CCA. Our studies reveal insights into the molecular pathogenesis and heterogeneity of cholangiocarcinoma and provide classification information of potential therapeutic significance.
Keywords: Adult; Aged; Aged, 80 and over; Bile Duct Neoplasms; Cholangiocarcinoma; Chromatin; DNA Methylation; DNA-Binding Proteins; Female; Gene Expression Regulation, Neoplastic; Genomics; Humans; Isocitrate Dehydrogenase; Liver; Liver Neoplasms; Male; Middle Aged; Mitochondria; Mutation; Nuclear Proteins; Pancreatic Neoplasms; Promoter Regions, Genetic; RNA, Long Noncoding; RNA, Messenger; Transcription Factors

Kaufman oculo-cerebro-facial syndrome in a child with small and absent terminal phalanges and absent nails. - Kariminejad, Ariana; Ajeawung, Norbert Fonya; Bozorgmehr, Bita; Dionne-Laporte, Alexandre; Molidperee, Sirinart; Najafi, Kimia; Gibbs, Richard A; Lee, Brendan H; Hennekam, Raoul C; Campeau, Philippe M (J Hum Genet, 2017)
Kaufman oculo-cerebro-facial syndrome (KOS) is caused by recessive UBE3B mutations and presents with microcephaly, ocular abnormalities, distinctive facial morphology, low cholesterol levels and intellectual disability. We describe a child with microcephaly, brachycephaly, hearing loss, ptosis, blepharophimosis, hypertelorism, cleft palate, multiple renal cysts, absent nails, small or absent terminal phalanges, absent speech and intellectual disability. Syndromes that were initially considered include DOORS syndrome, Coffin-Siris syndrome and Dubowitz syndrome. Clinical investigations coupled with karyotype analysis, array-comparative genomic hybridization, exome and Sanger sequencing were performed to characterize the condition in this child. Sanger sequencing was negative for the DOORS syndrome gene TBC1D24 but exome sequencing identified a homozygous deletion in UBE3B (NM_183415:c.3139_3141del, p.1047_1047del) located within the terminal portion of the HECT domain. This finding coupled with the presence of characteristic features such as brachycephaly, ptosis, blepharophimosis, hypertelorism, short palpebral fissures, cleft palate and developmental delay allowed us to make a diagnosis of KOS. In conclusion, our findings highlight the importance of considering KOS as a differential diagnosis for patients under evaluation for DOORS syndrome and expand the phenotype of KOS to include small or absent terminal phalanges, nails, and the presence of hallux varus and multicystic dysplastic kidneys.
Keywords: Abnormalities, Multiple; Adult; Carrier Proteins; Child; Child, Preschool; Diagnosis, Differential; Eczema; Eye Abnormalities; Face; Facies; Female; Growth Disorders; GTPase-Activating Proteins; Hand Deformities, Congenital; Humans; Intellectual Disability; Karyotype; Limb Deformities, Congenital; Male; Membrane Proteins; Microcephaly; Micrognathism; Mutation; Neck; Nerve Tissue Proteins; Pathology, Molecular; Sequence Analysis, DNA; Ubiquitin-Protein Ligases

Lessons learned from additional research analyses of unsolved clinical exome cases. - Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Harel, Tamar; Rosenfeld, Jill A; Gambin, Tomasz; Stray-Pedersen, Asbjørg; Küry, Sébastien; Mercier, Sandra; Lessel, Davor; Denecke, Jonas; Wiszniewski, Wojciech; Penney, Samantha; et al. (Genome Med, 2017)
BACKGROUND: Given the rarity of most single-gene Mendelian disorders, concerted efforts of data exchange between clinical and scientific communities are critical to optimize molecular diagnosis and novel disease gene discovery. METHODS: We designed and implemented protocols for the study of cases for which a plausible molecular diagnosis was not achieved in a clinical genomics diagnostic laboratory (i.e. unsolved clinical exomes). Such cases were recruited to a research laboratory for further analyses, in order to potentially: (1) accelerate novel disease gene discovery; (2) increase the molecular diagnostic yield of whole exome sequencing (WES); and (3) gain insight into the genetic mechanisms of disease. Pilot project data included 74 families, consisting mostly of parent-offspring trios. Analyses performed on a research basis employed both WES from additional family members and complementary bioinformatics approaches and protocols. RESULTS: Analysis of all possible modes of Mendelian inheritance, focusing on both single nucleotide variants (SNV) and copy number variant (CNV) alleles, yielded a likely contributory variant in 36% (27/74) of cases. If one includes candidate genes with variants identified within a single family, a potential contributory variant was identified in a total of ~51% (38/74) of cases enrolled in this pilot study. The molecular diagnosis was achieved in 30/63 trios (47.6%). Besides this, the analysis workflow yielded evidence for pathogenic variants in disease-associated genes in 4/6 singleton cases (66.6%), 1/1 multiplex family involving three affected siblings, and 3/4 (75%) quartet families. Both the analytical pipeline and the collaborative efforts between the diagnostic and research laboratories provided insights that allowed recent disease gene discoveries (PURA, TANGO2, EMC1, GNB5, ATAD3A, and MIPEP) and increased the number of novel genes, defined in this study as genes identified in more than one family (DHX30 and EBF3). CONCLUSION: An efficient genomics pipeline in which clinical sequencing in a diagnostic laboratory is followed by the detailed reanalysis of unsolved cases in a research environment, supplemented with WES data from additional family members, and subject to adjuvant bioinformatics analyses including relaxed variant filtering parameters in informatics pipelines, can enhance the molecular diagnostic yield and provide mechanistic insights into Mendelian disorders. Implementing these approaches requires collaborative clinical molecular diagnostic and research efforts.
Keywords: Adenosine Triphosphatases; ATPases Associated with Diverse Cellular Activities; Computational Biology; DNA Copy Number Variations; DNA-Binding Proteins; Exome; Female; Genetic Diseases, Inborn; Genomics; GTP-Binding Protein beta Subunits; Humans; Male; Membrane Proteins; Metalloendopeptidases; Mitochondrial Proteins; Pilot Projects; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Transcription Factors

Loss of Nardilysin, a Mitochondrial Co-chaperone for α-Ketoglutarate Dehydrogenase, Promotes mTORC1 Activation and Neurodegeneration. - Yoon, Wan Hee; Sandoval, Hector; Nagarkar-Jaiswal, Sonal; Jaiswal, Manish; Yamamoto, Shinya; Haelterman, Nele A; Putluri, Nagireddy; Putluri, Vasanta; Sreekumar, Arun; Tos, Tulay; Aksoy, Ayse; Donti, Taraka; et al. (Neuron, 2017)
We previously identified mutations in Nardilysin (dNrd1) in a forward genetic screen designed to isolate genes whose loss causes neurodegeneration in Drosophila photoreceptor neurons. Here we show that NRD1 is localized to mitochondria, where it recruits mitochondrial chaperones and assists in the folding of α-ketoglutarate dehydrogenase (OGDH), a rate-limiting enzyme in the Krebs cycle. Loss of Nrd1 or Ogdh leads to an increase in α-ketoglutarate, a substrate for OGDH, which in turn leads to mTORC1 activation and a subsequent reduction in autophagy. Inhibition of mTOR activity by rapamycin or partially restoring autophagy delays neurodegeneration in dNrd1 mutant flies. In summary, this study reveals a novel role for NRD1 as a mitochondrial co-chaperone for OGDH and provides a mechanistic link between mitochondrial metabolic dysfunction, mTORC1 signaling, and impaired autophagy in neurodegeneration.
Keywords: Animals; Autophagy; Drosophila; Drosophila melanogaster; Drosophila Proteins; Ketoglutarate Dehydrogenase Complex; Ketoglutaric Acids; Lysine; Mechanistic Target of Rapamycin Complex 1; Metalloendopeptidases; Mitochondria; Molecular Chaperones; Multiprotein Complexes; Neurodegenerative Diseases; TOR Serine-Threonine Kinases

MicroRNAs in the miR-17 and miR-15 families are downregulated in chronic kidney disease with hypertension. - Nandakumar, Priyanka; Tin, Adrienne; Grove, Megan L; Ma, Jianzhong; Boerwinkle, Eric; Coresh, Josef; Chakravarti, Aravinda (PLoS One, 2017)
BACKGROUND: In older adults (aged 70-74 years), African-Americans have 4-fold higher risk of developing hypertension-attributed end-stage renal disease (ESRD) than European-Americans. A hypothesized mechanism linking hypertension and progressive chronic kidney disease (CKD) is the innate immune response and inflammation. Persons with CKD are also more susceptible to infection. Gene expression in peripheral blood can provide a view of the innate immune activation profile. We aimed to identify differentially expressed genes, microRNAs, and pathways in peripheral blood between cases with CKD and high blood pressure under hypertension treatment versus controls without CKD and with controlled blood pressure in African Americans. METHODS: Case and control pairs (N = 15x2) were selected from those without diabetes and were matched for age, sex, body mass index, APOL1 risk allele count, and hypertension medication use. High blood pressure under hypertension treatment was defined as hypertension medication use and systolic blood pressure (SBP) ≥ 145 mmHg. CKD was defined as estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73m2. Cases were selected from those with CKD and high blood pressure under hypertension treatment, and controls were selected from those without CKD (eGFR: 75-120 mL/min/1.73m2 and urine albumin-to-creatinine ratio < 30mg/g) and with blood pressure controlled by hypertension medication use (SBP < 135 mmHg and D(diastolic)BP < 90 mm Hg). We perform RNA sequencing of mRNA and microRNA and conducted differential expression and co-expression network analysis. RESULTS: Of 347 miRNAs included in the analysis, 14 were significantly associated with case status (Benjamini-Hochberg adjusted p-value [BH p] < 0.05). Of these, ten were downregulated in cases: three of each belong to the miR-17 and miR-15 families. In co-expression network analysis of miRNA, one module, which included 13 of the 14 significant miRNAs, had significant association with case status. Of the 14,488 genes and 41,739 transcripts included in the analysis, none had significant association with case status. Gene co-expression network analyses did not yield any significant associations for mRNA. CONCLUSION: We have identified 14 differentially expressed miRNAs in the peripheral blood of CKD cases with high blood pressure under hypertension treatment as compared to appropriate controls. Most of the significant miRNAs were downregulated and have critical roles in immune cell functions. Future studies are needed to replicate our findings and determine whether the downregulation of these miRNAs in immune cells may influence CKD progression or complications.
Keywords: Down-Regulation; Female; Gene Expression Profiling; Gene Ontology; Gene Regulatory Networks; Humans; Hypertension; Male; MicroRNAs; Middle Aged; Renal Insufficiency, Chronic; RNA, Messenger; Sequence Analysis, RNA

Mutations in EBF3 Disturb Transcriptional Profiles and Cause Intellectual Disability, Ataxia, and Facial Dysmorphism. - Harms, Frederike Leonie; Girisha, Katta M; Hardigan, Andrew A; Kortüm, Fanny; Shukla, Anju; Alawi, Malik; Dalal, Ashwin; Brady, Lauren; Tarnopolsky, Mark; Bird, Lynne M; Ceulemans, Sophia; Bebin, Martina; et al. (Am J Hum Genet, 2017)
From a GeneMatcher-enabled international collaboration, we identified ten individuals affected by intellectual disability, speech delay, ataxia, and facial dysmorphism and carrying a deleterious EBF3 variant detected by whole-exome sequencing. One 9-bp duplication and one splice-site, five missense, and two nonsense variants in EBF3 were found; the mutations occurred de novo in eight individuals, and the missense variant c.625C>T (p.Arg209Trp) was inherited by two affected siblings from their healthy mother, who is mosaic. EBF3 belongs to the early B cell factor family (also known as Olf, COE, or O/E) and is a transcription factor involved in neuronal differentiation and maturation. Structural assessment predicted that the five amino acid substitutions have damaging effects on DNA binding of EBF3. Transient expression of EBF3 mutant proteins in HEK293T cells revealed mislocalization of all but one mutant in the cytoplasm, as well as nuclear localization. By transactivation assays, all EBF3 mutants showed significantly reduced or no ability to activate transcription of the reporter gene CDKN1A, and in situ subcellular fractionation experiments demonstrated that EBF3 mutant proteins were less tightly associated with chromatin. Finally, in RNA-seq and ChIP-seq experiments, EBF3 acted as a transcriptional regulator, and mutant EBF3 had reduced genome-wide DNA binding and gene-regulatory activity. Our findings demonstrate that variants disrupting EBF3-mediated transcriptional regulation cause intellectual disability and developmental delay and are present in ∼0.1% of individuals with unexplained neurodevelopmental disorders.
Keywords: Adolescent; Adult; Amino Acid Substitution; Ataxia; Child; Child, Preschool; Chromatin; Cyclin-Dependent Kinase Inhibitor p21; Developmental Disabilities; Exome; Face; Female; Gene Expression Regulation; Genes, Reporter; HEK293 Cells; Humans; Intellectual Disability; Language Development Disorders; Male; Models, Molecular; Mosaicism; Mutation; Neurodevelopmental Disorders; Protein Transport; Syndrome; Transcription Factors; Transcription, Genetic

Non-malignant respiratory epithelial cells preferentially proliferate from resected non-small cell lung cancer specimens cultured under conditionally reprogrammed conditions. - Gao, Boning; Huang, Chunxian; Kernstine, Kemp; Pelekanou, Vasiliki; Kluger, Yuval; Jiang, Tingting; Peters-Hall, Jennifer R; Coquelin, Melissa; Girard, Luc; Zhang, Wei; Huffman, Kenneth; Oliver, Dwight; et al. (Oncotarget, 2017)
The "conditionally reprogrammed cells" (CRC) method, using a Rho kinase inhibitor and irradiated mouse fibroblast cells has been described for the efficient growth of cells from malignant and non-malignant samples from primary tumor and non-malignant sites. Using the CRC method, four institutions independently cultured tumor tissues from 48 non-small cell lung cancers (NSCLC, mostly from primary resected tumors) and 22 non-malignant lungs. We found that epithelial cells could be cultured from tumor and non-malignant lung. However, epithelial cells cultured from tumors had features of non-malignant respiratory epithelial cells which include: 1) among 22 mutations found in the original tumors only two mutations were found in the CRC cultures with reduced frequency (31% to 13% and 92% to 15% from original tumor and CRC culture respectively); 2) copy number variation was analyzed in 9 tumor and their CRC cultures and only diploid patterns were found in CRC cultures; 3) mRNA expression profiles were similar to those of normal respiratory epithelial cells; and 4) co-culture of tumor and non-malignant lung epithelial cells resulted in mostly non-malignant cells. We conclude that CRC method is a highly selective and useful method for the growth of non-malignant respiratory epithelial cells from tumor specimens and only occasionally do such CRC cultures contain a small subpopulation of cancer cells marked by oncogenic mutations. While our findings are restricted to resected primary NSCLC, they indicated the necessity to fully characterize all CRC cultures and the need to develop culture technology that facilitates the growth of primary lung cancers.
Keywords: A549 Cells; Adult; Aged; Aged, 80 and over; Base Sequence; Carcinoma, Non-Small-Cell Lung; Cell Line, Tumor; Cell Proliferation; Cells, Cultured; Coculture Techniques; DNA Copy Number Variations; DNA Mutational Analysis; Epithelial Cells; Female; Gene Expression Profiling; Genetic Predisposition to Disease; Humans; Lung Neoplasms; Male; Middle Aged; Mutation; Respiratory Mucosa; Tumor Cells, Cultured

An Organismal CNV Mutator Phenotype Restricted to Early Human Development. - Liu, Pengfei; Yuan, Bo; Carvalho, Claudia M B; Wuster, Arthur; Walter, Klaudia; Zhang, Ling; Gambin, Tomasz; Chong, Zechen; Campbell, Ian M; Coban Akdemir, Zeynep; Gelowani, Violet; Writzl, Karin; et al. (Cell, 2017)
De novo copy number variants (dnCNVs) arising at multiple loci in a personal genome have usually been considered to reflect cancer somatic genomic instabilities. We describe a multiple dnCNV (MdnCNV) phenomenon in which individuals with genomic disorders carry five to ten constitutional dnCNVs. These CNVs originate from independent formation incidences, are predominantly tandem duplications or complex gains, exhibit breakpoint junction features reminiscent of replicative repair, and show increased de novo point mutations flanking the rearrangement junctions. The active CNV mutation shower appears to be restricted to a transient perizygotic period. We propose that a defect in the CNV formation process is responsible for the "CNV-mutator state," and this state is dampened after early embryogenesis. The constitutional MdnCNV phenomenon resembles chromosomal instability in various cancers. Investigations of this phenomenon may provide unique access to understanding genomic disorders, structural variant mutagenesis, human evolution, and cancer biology.
Keywords: Chromosome Aberrations; Chromosome Breakpoints; Chromosome Duplication; DNA Copy Number Variations; DNA Replication; Embryonic Development; Female; Gametogenesis; Genetic Diseases, Inborn; Genomic Instability; Humans; Male; Mutation

A Pan-Cancer Proteogenomic Atlas of PI3K/AKT/mTOR Pathway Alterations. - Zhang, Yiqun; Kwok-Shing Ng, Patrick; Kucherlapati, Melanie; Chen, Fengju; Liu, Yuexin; Tsang, Yiu Huen; De Velasco, Guillermo; Jeong, Kang Jin; Akbani, Rehan; Hadjipanayis, Angela; Pantazi, Angeliki; Bristow, Christopher A; et al. (Cancer Cell, 2017)
Molecular alterations involving the PI3K/AKT/mTOR pathway (including mutation, copy number, protein, or RNA) were examined across 11,219 human cancers representing 32 major types. Within specific mutated genes, frequency, mutation hotspot residues, in silico predictions, and functional assays were all informative in distinguishing the subset of genetic variants more likely to have functional relevance. Multiple oncogenic pathways including PI3K/AKT/mTOR converged on similar sets of downstream transcriptional targets. In addition to mutation, structural variations and partial copy losses involving PTEN and STK11 showed evidence for having functional relevance. A substantial fraction of cancers showed high mTOR pathway activity without an associated canonical genetic or genomic alteration, including cancers harboring IDH1 or VHL mutations, suggesting multiple mechanisms for pathway activation.
Keywords: Databases, Genetic; Gene Expression Profiling; Humans; Mutation; Neoplasms; Phosphatidylinositol 3-Kinases; Proteogenomics; Proto-Oncogene Proteins c-akt; Signal Transduction; Survival Analysis; TOR Serine-Threonine Kinases

Pan-urologic cancer genomic subtypes that transcend tissue of origin. - Chen, Fengju; Zhang, Yiqun; Bossé, Dominick; Lalani, Aly-Khan A; Hakimi, A Ari; Hsieh, James J; Choueiri, Toni K; Gibbons, Don L; Ittmann, Michael; Creighton, Chad J (Nat Commun, 2017)
Urologic cancers include cancers of the bladder, kidney, prostate, and testes, with common molecular features spanning different types. Here, we show that 1954 urologic cancers can be classified into nine major genomic subtypes, on the basis of multidimensional and comprehensive molecular characterization (including DNA methylation and copy number, and RNA and protein expression). Tissue dominant effects are first removed computationally in order to define these subtypes, which reveal common processes-reflecting in part tumor microenvironmental influences-driving cellular behavior across tumor lineages. Six of the subtypes feature a mixture of represented cancer types as defined by tissue or cell of origin. Differences in patient survival and in the manifestation of specific pathways-including hypoxia, metabolism, NRF2-ARE, Hippo, and immune checkpoint-can further distinguish the subtypes. Immune checkpoint markers and molecular signatures of macrophages and T cell infiltrates are relatively high within distinct subsets of each cancer type studied. The pan-urologic cancer genomic subtypes would facilitate information sharing involving therapeutic implications between tissue-oriented domains.Urological cancers have disparate tissues and cells of origin but share many molecular features. Here, the authors use multidimensional and comprehensive molecular characterization to classify urological cancers into nine major genomic subtypes, highlighting potential therapeutic targets.
Keywords: DNA Methylation; Gene Expression Profiling; Genetic Predisposition to Disease; Genomics; Humans; Mutation; Proteomics; Signal Transduction; Tumor Microenvironment; Urologic Neoplasms

The performance of deleteriousness prediction scores for rare non-protein-changing single nucleotide variants in human genes. - Liu, Xiaoming; Li, Chang; Boerwinkle, Eric (J Med Genet, 2017)
Keywords: Databases, Genetic; Genes; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Reproducibility of Results; ROC Curve

Primary immunodeficiency diseases: Genomic approaches delineate heterogeneous Mendelian disorders. - Stray-Pedersen, Asbjørg; Sorte, Hanne Sørmo; Samarakoon, Pubudu; Gambin, Tomasz; Chinn, Ivan K; Coban Akdemir, Zeynep H; Erichsen, Hans Christian; Forbes, Lisa R; Gu, Shen; Yuan, Bo; Jhangiani, Shalini N; Muzny, Donna M; et al. (J Allergy Clin Immunol, 2017)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are clinically and genetically heterogeneous disorders thus far associated with mutations in more than 300 genes. The clinical phenotypes derived from distinct genotypes can overlap. Genetic etiology can be a prognostic indicator of disease severity and can influence treatment decisions. OBJECTIVE: We sought to investigate the ability of whole-exome screening methods to detect disease-causing variants in patients with PIDDs. METHODS: Patients with PIDDs from 278 families from 22 countries were investigated by using whole-exome sequencing. Computational copy number variant (CNV) prediction pipelines and an exome-tiling chromosomal microarray were also applied to identify intragenic CNVs. Analytic approaches initially focused on 475 known or candidate PIDD genes but were nonexclusive and further tailored based on clinical data, family history, and immunophenotyping. RESULTS: A likely molecular diagnosis was achieved in 110 (40%) unrelated probands. Clinical diagnosis was revised in about half (60/110) and management was directly altered in nearly a quarter (26/110) of families based on molecular findings. Twelve PIDD-causing CNVs were detected, including 7 smaller than 30 Kb that would not have been detected with conventional diagnostic CNV arrays. CONCLUSION: This high-throughput genomic approach enabled detection of disease-related variants in unexpected genes; permitted detection of low-grade constitutional, somatic, and revertant mosaicism; and provided evidence of a mutational burden in mixed PIDD immunophenotypes.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; DNA Copy Number Variations; Female; Genomics; High-Throughput Nucleotide Sequencing; Humans; Immunologic Deficiency Syndromes; Infant; Male; Middle Aged; Young Adult

PRUNE is crucial for normal brain development and mutated in microcephaly with neurodevelopmental impairment. - Zollo, Massimo; Ahmed, Mustafa; Ferrucci, Veronica; Salpietro, Vincenzo; Asadzadeh, Fatemeh; Carotenuto, Marianeve; Maroofian, Reza; Al-Amri, Ahmed; Singh, Royana; Scognamiglio, Iolanda; Mojarrad, Majid; Musella, Luca; et al. (Brain, 2017)
PRUNE is a member of the DHH (Asp-His-His) phosphoesterase protein superfamily of molecules important for cell motility, and implicated in cancer progression. Here we investigated multiple families from Oman, India, Iran and Italy with individuals affected by a new autosomal recessive neurodevelopmental and degenerative disorder in which the cardinal features include primary microcephaly and profound global developmental delay. Our genetic studies identified biallelic mutations of PRUNE1 as responsible. Our functional assays of disease-associated variant alleles revealed impaired microtubule polymerization, as well as cell migration and proliferation properties, of mutant PRUNE. Additionally, our studies also highlight a potential new role for PRUNE during microtubule polymerization, which is essential for the cytoskeletal rearrangements that occur during cellular division and proliferation. Together these studies define PRUNE as a molecule fundamental for normal human cortical development and define cellular and clinical consequences associated with PRUNE mutation.
Keywords: Adolescent; Brain; Carrier Proteins; Cell Differentiation; Cell Movement; Cerebral Cortex; Child; Child, Preschool; Cytoskeleton; Developmental Disabilities; Female; Genes, Recessive; Heredodegenerative Disorders, Nervous System; Humans; Infant; Male; Microcephaly; Microtubules; Mutation; Pedigree; Phosphoric Monoester Hydrolases; Young Adult

SeqCNV: a novel method for identification of copy number variations in targeted next-generation sequencing data. - Chen, Yong; Zhao, Li; Wang, Yi; Cao, Ming; Gelowani, Violet; Xu, Mingchu; Agrawal, Smriti A; Li, Yumei; Daiger, Stephen P; Gibbs, Richard; Wang, Fei; Chen, Rui (BMC Bioinformatics, 2017)
BACKGROUND: Targeted next-generation sequencing (NGS) has been widely used as a cost-effective way to identify the genetic basis of human disorders. Copy number variations (CNVs) contribute significantly to human genomic variability, some of which can lead to disease. However, effective detection of CNVs from targeted capture sequencing data remains challenging. RESULTS: Here we present SeqCNV, a novel CNV calling method designed to use capture NGS data. SeqCNV extracts the read depth information and utilizes the maximum penalized likelihood estimation (MPLE) model to identify the copy number ratio and CNV boundary. We applied SeqCNV to both bacterial artificial clone (BAC) and human patient NGS data to identify CNVs. These CNVs were validated by array comparative genomic hybridization (aCGH). CONCLUSIONS: SeqCNV is able to robustly identify CNVs of different size using capture NGS data. Compared with other CNV-calling methods, SeqCNV shows a significant improvement in both sensitivity and specificity.
Keywords: DNA Copy Number Variations; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Likelihood Functions; Sensitivity and Specificity; Sequence Analysis, DNA; Software

The SWI/SNF Protein PBRM1 Restrains VHL-Loss-Driven Clear Cell Renal Cell Carcinoma. - Nargund, Amrita M; Pham, Can G; Dong, Yiyu; Wang, Patricia I; Osmangeyoglu, Hatice U; Xie, Yuchen; Aras, Omer; Han, Song; Oyama, Toshinao; Takeda, Shugaku; Ray, Chelsea E; Dong, Zhenghong; et al. (Cell Rep, 2017)
PBRM1 is the second most commonly mutated gene after VHL in clear cell renal cell carcinoma (ccRCC). However, the biological consequences of PBRM1 mutations for kidney tumorigenesis are unknown. Here, we find that kidney-specific deletion of Vhl and Pbrm1, but not either gene alone, results in bilateral, multifocal, transplantable clear cell kidney cancers. PBRM1 loss amplified the transcriptional outputs of HIF1 and STAT3 incurred by Vhl deficiency. Analysis of mouse and human ccRCC revealed convergence on mTOR activation, representing the third driver event after genetic inactivation of VHL and PBRM1. Our study reports a physiological preclinical ccRCC mouse model that recapitulates somatic mutations in human ccRCC and provides mechanistic and therapeutic insights into PBRM1 mutated subtypes of human ccRCC.
Keywords: Animals; Carcinoma, Renal Cell; DNA-Binding Proteins; Down-Regulation; Gene Deletion; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; HMGB Proteins; Humans; Hydronephrosis; Hypoxia-Inducible Factor 1, alpha Subunit; Integrases; Kidney; Kidney Neoplasms; Mechanistic Target of Rapamycin Complex 1; Mice; Nuclear Proteins; Oxidative Phosphorylation; Signal Transduction; STAT3 Transcription Factor; Transcription Factors; Transcription, Genetic; Von Hippel-Lindau Tumor Suppressor Protein

Transcriptomic variation of pharmacogenes in multiple human tissues and lymphoblastoid cell lines. - Chhibber, A; French, C E; Yee, S W; Gamazon, E R; Theusch, E; Xiang Qin; Webb, A; Papp, A C; Wang, A; Simmons, C Q; Konkashbaev, A; Chaudhry, A S; et al. (Pharmacogenomics J, 2017)
Variation in the expression level and activity of genes involved in drug disposition and action ('pharmacogenes') can affect drug response and toxicity, especially when in tissues of pharmacological importance. Previous studies have relied primarily on microarrays to understand gene expression differences, or have focused on a single tissue or small number of samples. The goal of this study was to use RNA-sequencing (RNA-seq) to determine the expression levels and alternative splicing of 389 Pharmacogenomics Research Network pharmacogenes across four tissues (liver, kidney, heart and adipose) and lymphoblastoid cell lines, which are used widely in pharmacogenomics studies. Analysis of RNA-seq data from 139 different individuals across the 5 tissues (20-45 individuals per tissue type) revealed substantial variation in both expression levels and splicing across samples and tissue types. Comparison with GTEx data yielded a consistent picture. This in-depth exploration also revealed 183 splicing events in pharmacogenes that were previously not annotated. Overall, this study serves as a rich resource for the research community to inform biomarker and drug discovery and use.
Keywords: Adipose Tissue; Alternative Splicing; Cell Line; Computational Biology; Databases, Genetic; Genotype; High-Throughput Nucleotide Sequencing; Humans; Kidney; Liver; Myocardium; Pharmacogenetics; Pharmacogenomic Variants; Phenotype; Sequence Analysis, RNA; Transcriptome

Transient structural variations have strong effects on quantitative traits and reproductive isolation in fission yeast. - Jeffares, Daniel C; Jolly, Clemency; Hoti, Mimoza; Speed, Doug; Shaw, Liam; Rallis, Charalampos; Balloux, Francois; Dessimoz, Christophe; Bähler, Jürg; Sedlazeck, Fritz J (Nat Commun, 2017)
Large structural variations (SVs) within genomes are more challenging to identify than smaller genetic variants but may substantially contribute to phenotypic diversity and evolution. We analyse the effects of SVs on gene expression, quantitative traits and intrinsic reproductive isolation in the yeast Schizosaccharomyces pombe. We establish a high-quality curated catalogue of SVs in the genomes of a worldwide library of S. pombe strains, including duplications, deletions, inversions and translocations. We show that copy number variants (CNVs) show a variety of genetic signals consistent with rapid turnover. These transient CNVs produce stoichiometric effects on gene expression both within and outside the duplicated regions. CNVs make substantial contributions to quantitative traits, most notably intracellular amino acid concentrations, growth under stress and sugar utilization in winemaking, whereas rearrangements are strongly associated with reproductive isolation. Collectively, these findings have broad implications for evolution and for our understanding of quantitative traits including complex human diseases.
Keywords: Chromosome Inversion; Chromosomes, Fungal; DNA Copy Number Variations; Evolution, Molecular; Gene Expression Regulation, Fungal; Genome, Fungal; Quantitative Trait, Heritable; Reproductive Isolation; Schizosaccharomyces; Translocation, Genetic

UALCAN: A Portal for Facilitating Tumor Subgroup Gene Expression and Survival Analyses. - Chandrashekar, Darshan S; Bashel, Bhuwan; Balasubramanya, Sai Akshaya Hodigere; Creighton, Chad J; Ponce-Rodriguez, Israel; Chakravarthi, Balabhadrapatruni V S K; Varambally, Sooryanarayana (Neoplasia, 2017)
Genomics data from The Cancer Genome Atlas (TCGA) project has led to the comprehensive molecular characterization of multiple cancer types. The large sample numbers in TCGA offer an excellent opportunity to address questions associated with tumo heterogeneity. Exploration of the data by cancer researchers and clinicians is imperative to unearth novel therapeutic/diagnostic biomarkers. Various computational tools have been developed to aid researchers in carrying out specific TCGA data analyses; however there is need for resources to facilitate the study of gene expression variations and survival associations across tumors. Here, we report UALCAN, an easy to use, interactive web-portal to perform to in-depth analyses of TCGA gene expression data. UALCAN uses TCGA level 3 RNA-seq and clinical data from 31 cancer types. The portal's user-friendly features allow to perform: 1) analyze relative expression of a query gene(s) across tumor and normal samples, as well as in various tumor sub-groups based on individual cancer stages, tumor grade, race, body weight or other clinicopathologic features, 2) estimate the effect of gene expression level and clinicopathologic features on patient survival; and 3) identify the top over- and under-expressed (up and down-regulated) genes in individual cancer types. This resource serves as a platform for in silico validation of target genes and for identifying tumor sub-group specific candidate biomarkers. Thus, UALCAN web-portal could be extremely helpful in accelerating cancer research. UALCAN is publicly available at http://ualcan.path.uab.edu.
Keywords: Computational Biology; Databases, Genetic; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Humans; Kaplan-Meier Estimate; Neoplasms; Prognosis; Software; Survival Analysis; User-Computer Interface; Web Browser

Use of Exome Sequencing for Infants in Intensive Care Units: Ascertainment of Severe Single-Gene Disorders and Effect on Medical Management. - Meng, Linyan; Pammi, Mohan; Saronwala, Anirudh; Magoulas, Pilar; Ghazi, Andrew Ray; Vetrini, Francesco; Zhang, Jing; He, Weimin; Dharmadhikari, Avinash V; Qu, Chunjing; Ward, Patricia; Braxton, Alicia; et al. (JAMA Pediatr, 2017)
IMPORTANCE: While congenital malformations and genetic diseases are a leading cause of early infant death, to our knowledge, the contribution of single-gene disorders in this group is undetermined. OBJECTIVE: To determine the diagnostic yield and use of clinical exome sequencing in critically ill infants. DESIGN, SETTING, AND PARTICIPANTS: Clinical exome sequencing was performed for 278 unrelated infants within the first 100 days of life who were admitted to Texas Children's Hospital in Houston, Texas, during a 5-year period between December 2011 and January 2017. Exome sequencing types included proband exome, trio exome, and critical trio exome, a rapid genomic assay for seriously ill infants. MAIN OUTCOMES AND MEASURES: Indications for testing, diagnostic yield of clinical exome sequencing, turnaround time, molecular findings, patient age at diagnosis, and effect on medical management among a group of critically ill infants who were suspected to have genetic disorders. RESULTS: The mean (SEM) age for infants participating in the study was 28.5 (1.7) days; of these, the mean (SEM) age was 29.0 (2.2) days for infants undergoing proband exome sequencing, 31.5 (3.9) days for trio exome, and 22.7 (3.9) days for critical trio exome. Clinical indications for exome sequencing included a range of medical concerns. Overall, a molecular diagnosis was achieved in 102 infants (36.7%) by clinical exome sequencing, with relatively low yield for cardiovascular abnormalities. The diagnosis affected medical management for 53 infants (52.0%) and had a substantial effect on informed redirection of care, initiation of new subspecialist care, medication/dietary modifications, and furthering life-saving procedures in select patients. Critical trio exome sequencing revealed a molecular diagnosis in 32 of 63 infants (50.8%) at a mean (SEM) of 33.1 (5.6) days of life with a mean (SEM) turnaround time of 13.0 (0.4) days. Clinical care was altered by the diagnosis in 23 of 32 patients (71.9%). The diagnostic yield, patient age at diagnosis, and medical effect in the group that underwent critical trio exome sequencing were significantly different compared with the group who underwent regular exome testing. For deceased infants (n = 81), genetic disorders were molecularly diagnosed in 39 (48.1%) by exome sequencing, with implications for recurrence risk counseling. CONCLUSIONS AND RELEVANCE: Exome sequencing is a powerful tool for the diagnostic evaluation of critically ill infants with suspected monogenic disorders in the neonatal and pediatric intensive care units and its use has a notable effect on clinical decision making.
Keywords: Adult; Critical Care; Disease Management; Exome; Exome Sequencing; Genetic Counseling; Genetic Diseases, Inborn; Humans; Infant; Infant Care; Infant, Newborn; Intensive Care Units, Pediatric; Length of Stay; Retrospective Studies; Texas

Whole Transcriptome Sequencing Analyses Reveal Molecular Markers of Blood Pressure Response to Thiazide Diuretics. - Sá, Ana Caroline C; Webb, Amy; Gong, Yan; McDonough, Caitrin W; Datta, Somnath; Langaee, Taimour Y; Turner, Stephen T; Beitelshees, Amber L; Chapman, Arlene B; Boerwinkle, Eric; Gums, John G; Scherer, Steven E; et al. (Sci Rep, 2017)
Thiazide diuretics (TD) are commonly prescribed anti-hypertensives worldwide. However, <40% of patients treated with thiazide monotherapy achieve BP control. This study uses whole transcriptome sequencing to identify novel molecular markers associated with BP response to TD. We assessed global RNA expression levels in whole blood samples from 150 participants, representing patients in the upper and lower quartile of BP response to TD from the Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) (50 whites) and from PEAR-2 (50 whites and 50 blacks). In each study cohort, we performed poly-A RNA-sequencing in baseline samples from 25 responders and 25 non-responders to hydrochlorothiazide (HCTZ) or chlorthalidone. At FDR adjusted p-value < 0.05, 29 genes were differentially expressed in relation to HCTZ or chlorthalidone BP response in whites. For each differentially expressed gene, replication was attempted in the alternate white group and PEAR-2 blacks. CEBPD (meta-analysis p = 1.8 × 10) and TSC22D3 (p = 1.9 × 10) were differentially expressed in all 3 cohorts, and explain, in aggregate, 21.9% of response variability to TD. This is the first report of the use of transcriptome-wide sequencing data to identify molecular markers of antihypertensive drug response. These findings support CEBPD and TSC22D3 as potential biomarkers of BP response to TD.
Keywords: Alleles; Biomarkers; Blood Pressure; CCAAT-Enhancer-Binding Protein-delta; Chlorthalidone; Diuretics; Female; Gene Expression Profiling; Gene Expression Regulation; Humans; Hydrochlorothiazide; Logistic Models; Male; Middle Aged; Potassium; Reproducibility of Results; RNA, Messenger; ROC Curve; Transcription Factors; Uric Acid

Whole-exome sequencing in the molecular diagnosis of individuals with congenital anomalies of the kidney and urinary tract and identification of a new causative gene. - Bekheirnia, Mir Reza; Bekheirnia, Nasim; Bainbridge, Matthew N; Gu, Shen; Coban Akdemir, Zeynep Hande; Gambin, Tomek; Janzen, Nicolette K; Jhangiani, Shalini N; Muzny, Donna M; Michael, Mini; Brewer, Eileen D; Elenberg, Ewa; et al. (Genet Med, 2017)
PURPOSE: To investigate the utility of whole-exome sequencing (WES) to define a molecular diagnosis for patients clinically diagnosed with congenital anomalies of kidney and urinary tract (CAKUT). METHODS: WES was performed in 62 families with CAKUT. WES data were analyzed for single-nucleotide variants (SNVs) in 35 known CAKUT genes, putatively deleterious sequence changes in new candidate genes, and potentially disease-associated copy-number variants (CNVs). RESULTS: In approximately 5% of families, pathogenic SNVs were identified in PAX2, HNF1B, and EYA1. Observed phenotypes in these families expand the current understanding about the role of these genes in CAKUT. Four pathogenic CNVs were also identified using two CNV detection tools. In addition, we found one deleterious de novo SNV in FOXP1 among the 62 families with CAKUT. The clinical database of the Baylor Miraca Genetics laboratory was queried and seven additional unrelated individuals with novel de novo SNVs in FOXP1 were identified. Six of these eight individuals with FOXP1 SNVs have syndromic urinary tract defects, implicating this gene in urinary tract development. CONCLUSION: We conclude that WES can be used to identify molecular etiology (SNVs, CNVs) in a subset of individuals with CAKUT. WES can also help identify novel CAKUT genes.Genet Med 19 4, 412-420.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Genetic Predisposition to Disease; Hepatocyte Nuclear Factor 1-beta; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Nuclear Proteins; PAX2 Transcription Factor; Pedigree; Polymorphism, Single Nucleotide; Protein Tyrosine Phosphatases; Repressor Proteins; Urogenital Abnormalities; Vesico-Ureteral Reflux; Young Adult

Whole-genome landscape of pancreatic neuroendocrine tumours. - Scarpa, Aldo; Chang, David K; Nones, Katia; Corbo, Vincenzo; Patch, Ann-Marie; Bailey, Peter; Lawlor, Rita T; Johns, Amber L; Miller, David K; Mafficini, Andrea; Rusev, Borislav; Scardoni, Maria; et al. (Nature, 2017)
The diagnosis of pancreatic neuroendocrine tumours (PanNETs) is increasing owing to more sensitive detection methods, and this increase is creating challenges for clinical management. We performed whole-genome sequencing of 102 primary PanNETs and defined the genomic events that characterize their pathogenesis. Here we describe the mutational signatures they harbour, including a deficiency in G:C > T:A base excision repair due to inactivation of MUTYH, which encodes a DNA glycosylase. Clinically sporadic PanNETs contain a larger-than-expected proportion of germline mutations, including previously unreported mutations in the DNA repair genes MUTYH, CHEK2 and BRCA2. Together with mutations in MEN1 and VHL, these mutations occur in 17% of patients. Somatic mutations, including point mutations and gene fusions, were commonly found in genes involved in four main pathways: chromatin remodelling, DNA damage repair, activation of mTOR signalling (including previously undescribed EWSR1 gene fusions), and telomere maintenance. In addition, our gene expression analyses identified a subgroup of tumours associated with hypoxia and HIF signalling.
Keywords: Base Sequence; Calmodulin-Binding Proteins; Carcinoma, Neuroendocrine; Chromatin Assembly and Disassembly; Chromosome Aberrations; DNA Copy Number Variations; DNA Glycosylases; DNA Mutational Analysis; DNA Repair; Female; Genome, Human; Genomics; Germ-Line Mutation; Humans; Male; Pancreatic Neoplasms; RNA-Binding Protein EWS; RNA-Binding Proteins; Telomere; TOR Serine-Threonine Kinases

Acquired uniparental disomy of chromosome 9p in hematologic malignancies. - Wang, Linghua; Wheeler, David A; Prchal, Josef T (Exp Hematol, 2016)
Acquired uniparental disomy (aUPD) is a common and recurrent molecular event in human cancers that leads to homozygosity for tumor suppressor genes as well as oncogenes, while retaining the diploid chromosomal complement. Because of the lack of copy number change, aUPD is undetectable by comparative genome hybridization, so the magnitude of this genetic change was underappreciated in the past. 9p aUPD was first described in 2002 in patients with polycythemia vera (PV). Since then, systematic application of genomewide single-nucleotide polymorphism arrays has indicated that 9p aUPD is the most common chromosomal aberration in myeloproliferative neoplasms (MPNs), contributing to discovery of the PV-defining mutation JAK2V617F21. It was also found in other myeloid and lymphoid malignancies, though at a relatively lower frequency. By leading to JAK2V617F 23 homozygosity, 9p aUPD plays a causal role in the development of PV and is also associated with less favorable clinical outcomes. It is also possible that new targets other than JAK2V617F 25 are present within 9p aUPD that may contribute to diversity of PV outcome and phenotype. This review summarizes recent discoveries on 9p aUPD in hematologic malignancies and discusses possible underlying mechanisms and potential roles of 9p aUPD in the pathogenesis of PV, the relationship between 9p aUPD and JAK2V617F29, and possible new cancer-related targets within the 9p aUPD region.
Keywords: Animals; Chromosomes, Human, Pair 9; Disease Progression; Gene Frequency; Hematologic Neoplasms; Humans; Janus Kinase 2; Mutation; Polycythemia Vera; Prognosis; Uniparental Disomy

Altered neuronal network and rescue in a human MECP2 duplication model. - Nageshappa, S; Carromeu, C; Trujillo, C A; Mesci, P; Espuny-Camacho, I; Pasciuto, E; Vanderhaeghen, P; Verfaillie, C M; Raitano, S; Kumar, A; Carvalho, C M B; Bagni, C; et al. (Mol Psychiatry, 2016)
Increased dosage of methyl-CpG-binding protein-2 (MeCP2) results in a dramatic neurodevelopmental phenotype with onset at birth. We generated induced pluripotent stem cells (iPSCs) from patients with the MECP2 duplication syndrome (MECP2dup), carrying different duplication sizes, to study the impact of increased MeCP2 dosage in human neurons. We show that cortical neurons derived from these different MECP2dup iPSC lines have increased synaptogenesis and dendritic complexity. In addition, using multi-electrodes arrays, we show that neuronal network synchronization was altered in MECP2dup-derived neurons. Given MeCP2 functions at the epigenetic level, we tested whether these alterations were reversible using a library of compounds with defined activity on epigenetic pathways. One histone deacetylase inhibitor, NCH-51, was validated as a potential clinical candidate. Interestingly, this compound has never been considered before as a therapeutic alternative for neurological disorders. Our model recapitulates early stages of the human MECP2 duplication syndrome and represents a promising cellular tool to facilitate therapeutic drug screening for severe neurodevelopmental disorders.
Keywords: Cell Differentiation; Dendrites; Gene Dosage; Gene Duplication; Genetic Association Studies; Humans; Induced Pluripotent Stem Cells; Male; Methyl-CpG-Binding Protein 2; Nerve Net; Neurogenesis; Neurons

Ampullary Cancers Harbor ELF3 Tumor Suppressor Gene Mutations and Exhibit Frequent WNT Dysregulation. - Gingras, Marie-Claude; Covington, Kyle R; Chang, David K; Donehower, Lawrence A; Gill, Anthony J; Ittmann, Michael M; Creighton, Chad J; Johns, Amber L; Shinbrot, Eve; Dewal, Ninad; Fisher, William E; Pilarsky, Christian; et al. (Cell Rep, 2016)
The ampulla of Vater is a complex cellular environment from which adenocarcinomas arise to form a group of histopathologically heterogenous tumors. To evaluate the molecular features of these tumors, 98 ampullary adenocarcinomas were evaluated and compared to 44 distal bile duct and 18 duodenal adenocarcinomas. Genomic analyses revealed mutations in the WNT signaling pathway among half of the patients and in all three adenocarcinomas irrespective of their origin and histological morphology. These tumors were characterized by a high frequency of inactivating mutations of ELF3, a high rate of microsatellite instability, and common focal deletions and amplifications, suggesting common attributes in the molecular pathogenesis are at play in these tumors. The high frequency of WNT pathway activating mutation, coupled with small-molecule inhibitors of β-catenin in clinical trials, suggests future treatment decisions for these patients may be guided by genomic analysis.
Keywords: Adenocarcinoma; Ampulla of Vater; Base Sequence; DNA-Binding Proteins; Duodenal Neoplasms; Genomic Instability; Humans; Microsatellite Repeats; Molecular Sequence Data; Mutation; Pancreatic Neoplasms; Proto-Oncogene Proteins c-ets; Transcription Factors; Wnt Signaling Pathway

Association of MTOR Mutations With Developmental Brain Disorders, Including Megalencephaly, Focal Cortical Dysplasia, and Pigmentary Mosaicism. - Mirzaa, Ghayda M; Campbell, Catarina D; Solovieff, Nadia; Goold, Carleton; Jansen, Laura A; Menon, Suchithra; Timms, Andrew E; Conti, Valerio; Biag, Jonathan D; Adams, Carissa; Boyle, Evan August; Collins, Sarah; et al. (JAMA Neurol, 2016)
IMPORTANCE: Focal cortical dysplasia (FCD), hemimegalencephaly, and megalencephaly constitute a spectrum of malformations of cortical development with shared neuropathologic features. These disorders are associated with significant childhood morbidity and mortality. OBJECTIVE: To identify the underlying molecular cause of FCD, hemimegalencephaly, and diffuse megalencephaly. DESIGN, SETTING, AND PARTICIPANTS: Patients with FCD, hemimegalencephaly, or megalencephaly (mean age, 11.7 years; range, 2-32 years) were recruited from Pediatric Hospital A. Meyer, the University of Hong Kong, and Seattle Children's Research Institute from June 2012 to June 2014. Whole-exome sequencing (WES) was performed on 8 children with FCD or hemimegalencephaly using standard-depth (50-60X) sequencing in peripheral samples (blood, saliva, or skin) from the affected child and their parents and deep (150-180X) sequencing in affected brain tissue. Targeted sequencing and WES were used to screen 93 children with molecularly unexplained diffuse or focal brain overgrowth. Histopathologic and functional assays of phosphatidylinositol 3-kinase-AKT (serine/threonine kinase)-mammalian target of rapamycin (mTOR) pathway activity in resected brain tissue and cultured neurons were performed to validate mutations. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing and targeted sequencing identified variants associated with this spectrum of developmental brain disorders. RESULTS: Low-level mosaic mutations of MTOR were identified in brain tissue in 4 children with FCD type 2a with alternative allele fractions ranging from 0.012 to 0.086. Intermediate-level mosaic mutation of MTOR (p.Thr1977Ile) was also identified in 3 unrelated children with diffuse megalencephaly and pigmentary mosaicism in skin. Finally, a constitutional de novo mutation of MTOR (p.Glu1799Lys) was identified in 3 unrelated children with diffuse megalencephaly and intellectual disability. Molecular and functional analysis in 2 children with FCD2a from whom multiple affected brain tissue samples were available revealed a mutation gradient with an epicenter in the most epileptogenic area. When expressed in cultured neurons, all MTOR mutations identified here drive constitutive activation of mTOR complex 1 and enlarged neuronal size. CONCLUSIONS AND RELEVANCE: In this study, mutations of MTOR were associated with a spectrum of brain overgrowth phenotypes extending from FCD type 2a to diffuse megalencephaly, distinguished by different mutations and levels of mosaicism. These mutations may be sufficient to cause cellular hypertrophy in cultured neurons and may provide a demonstration of the pattern of mosaicism in brain and substantiate the link between mosaic mutations of MTOR and pigmentary mosaicism in skin.
Keywords: Adolescent; Adult; Amino Acids; Animals; Cells, Cultured; Cerebral Cortex; Child; Child, Preschool; Developmental Disabilities; Embryo, Mammalian; Female; Gene Expression Regulation; Genetic Association Studies; Humans; Intercellular Signaling Peptides and Proteins; Male; Malformations of Cortical Development; Mechanistic Target of Rapamycin Complex 1; Megalencephaly; Mosaicism; Multiprotein Complexes; Mutation; Nerve Tissue Proteins; Neurons; Rats; Retrospective Studies; TOR Serine-Threonine Kinases; Young Adult

Avirulence gene mapping in the Hessian fly (Mayetiola destructor) reveals a protein phosphatase 2C effector gene family. - Zhao, Chaoyang; Shukle, Richard; Navarro-Escalante, Lucio; Chen, Mingshun; Richards, Stephen; Stuart, Jeffrey J (J Insect Physiol, 2016)
The genetic tractability of the Hessian fly (HF, Mayetiola destructor) provides an opportunity to investigate the mechanisms insects use to induce plant gall formation. Here we demonstrate that capacity using the newly sequenced HF genome by identifying the gene (vH24) that elicits effector-triggered immunity in wheat (Triticum spp.) seedlings carrying HF resistance gene H24. vH24 was mapped within a 230-kb genomic fragment near the telomere of HF chromosome X1. That fragment contains only 21 putative genes. The best candidate vH24 gene in this region encodes a protein containing a secretion signal and a type-2 serine/threonine protein phosphatase (PP2C) domain. This gene has an H24-virulence associated insertion in its promoter that appears to silence transcription of the gene in H24-virulent larvae. Candidate vH24 is a member of a small family of genes that encode secretion signals and PP2C domains. It belongs to the fraction of genes in the HF genome previously predicted to encode effector proteins. Because PP2C proteins are not normally secreted, our results suggest that these are PP2C effectors that HF larvae inject into wheat cells to redirect, or interfere, with wheat signal transduction pathways.
Keywords: Animals; Chromosome Mapping; Crosses, Genetic; Diptera; Female; Genes, Insect; Genes, Plant; Genes, Recessive; Genes, X-Linked; Host-Parasite Interactions; Male; Phosphoprotein Phosphatases; Plant Immunity; Plant Proteins; Plant Tumors; Protein Phosphatase 2C; Telomere; Triticum; Virulence

Base-Biased Evolution of Disease-Associated Mutations in the Human Genome. - Xue, Cheng; Chen, Hua; Fuli Yu (Hum Mutat, 2016)
Understanding the evolution of disease-associated mutations is fundamental to analyze pathogenetics of diseases. Mutation, recombination (by GC-biased gene conversion, gBGC), and selection have been known to shape the evolution of disease-associated mutations, but how these evolutionary forces work together is still an open question. In this study, we analyzed several human large-scale datasets (1000 Genomes, ESP6500, ExAC and ClinVar), and found that base-biased mutagenesis generates more GC→AT than AT→GC mutations, while gBGC promotes the fixation of AT→GC mutations to balance the impact of base-biased mutation on genome. Due to this effect of gBGC, purifying selection removes more deleterious AT→GC mutations than GC→AT from population, but many high-frequency (fixed and nearly fixed) deleterious AT→GC mutations are remained possibly due to high genetic load. As a special subset, disease-associated mutations follow this evolutionary rule, in which disease-associated GC→AT mutations are more enriched in rare mutations compared with AT→GC, while disease-associated AT→GC are more enriched in mutations with high frequency. Thus, we presented a base-biased evolutionary framework that explains the base-biased generation and accumulation of disease-associated mutations in human populations.
Keywords: Base Composition; Databases, Genetic; Evolution, Molecular; Gene Conversion; Genetic Predisposition to Disease; Genome, Human; Humans; Models, Genetic; Mutation; Recombination, Genetic; Selection, Genetic

Coexistence of gain-of-function JAK2 germ line mutations with JAK2V617F in polycythemia vera. - Lanikova, Lucie; Babosova, Olga; Swierczek, Sabina; Wang, Linghua; Wheeler, David A; Divoky, Vladimir; Korinek, Vladimir; Prchal, Josef T (Blood, 2016)
Keywords: Amino Acid Substitution; Cells, Cultured; Cohort Studies; DNA Mutational Analysis; Germ-Line Mutation; Humans; Janus Kinase 2; Mutation, Missense; Phenylalanine; Polycythemia Vera; Polymorphism, Single Nucleotide; Valine

Comparative genomic study of arachnid immune systems indicates loss of beta-1,3-glucanase-related proteins and the immune deficiency pathway. - Bechsgaard, J; Vanthournout, B; Funch, P; Vestbo, S; Gibbs, R A; Richards, S; Sanggaard, K W; Enghild, J J; Bilde, T (J Evol Biol, 2016)
Analyses of arthropod genomes have shown that the genes in the different innate humoral immune responses are conserved. These genes encode proteins that are involved in immune signalling pathways that recognize pathogens and activate immune responses. These immune responses include phagocytosis, encapsulation of the pathogen and production of effector molecules for pathogen elimination. So far, most studies have focused on insects leaving other major arthropod groups largely unexplored. Here, we annotate the immune-related genes of six arachnid genomes and present evidence for a conserved pattern of some immune genes, but also evolutionary changes in the arachnid immune system. Specifically, our results suggest that the family of recognition molecules of beta-1,3-glucanase-related proteins (βGRPs) and the genes from the immune deficiency (IMD) signalling pathway have been lost in a common ancestor of arachnids. These findings are consistent with previous work suggesting that the humoral immune effector proteins are constitutively produced in arachnids in contrast to insects, where these have to be induced. Further functional studies are needed to verify this. We further show that the full haemolymph clotting cascade found in the horseshoe crab is retrieved in most arachnid genomes. Tetranychus lacks at least one major component, although it is possible that this cascade could still function through recruitment of a different protein. The gel-forming protein in horseshoe crabs, coagulogen, was not recovered in any of the arachnid genomes; however, it is possible that the arachnid clot consists of a related protein, spätzle, that is present in all of the genomes.
Keywords: Amino Acid Sequence; Animals; Antimicrobial Cationic Peptides; Arachnida; Blood Proteins; Defensins; Gene Dosage; Genome; Genomics; Hemolymph; Immune System; Immunity, Innate; Protein Domains; Sequence Alignment; Signal Transduction

Comparative Genomics of a Parthenogenesis-Inducing Wolbachia Symbiont. - Lindsey, Amelia R I; Werren, John H; Richards, Stephen; Stouthamer, Richard (G3 (Bethesda), 2016)
Wolbachia is an intracellular symbiont of invertebrates responsible for inducing a wide variety of phenotypes in its host. These host-Wolbachia relationships span the continuum from reproductive parasitism to obligate mutualism, and provide a unique system to study genomic changes associated with the evolution of symbiosis. We present the genome sequence from a parthenogenesis-inducing Wolbachia strain (wTpre) infecting the minute parasitoid wasp Trichogramma pretiosum The wTpre genome is the most complete parthenogenesis-inducing Wolbachia genome available to date. We used comparative genomics across 16 Wolbachia strains, representing five supergroups, to identify a core Wolbachia genome of 496 sets of orthologous genes. Only 14 of these sets are unique to Wolbachia when compared to other bacteria from the Rickettsiales. We show that the B supergroup of Wolbachia, of which wTpre is a member, contains a significantly higher number of ankyrin repeat-containing genes than other supergroups. In the wTpre genome, there is evidence for truncation of the protein coding sequences in 20% of ORFs, mostly as a result of frameshift mutations. The wTpre strain represents a conversion from cytoplasmic incompatibility to a parthenogenesis-inducing lifestyle, and is required for reproduction in the Trichogramma host it infects. We hypothesize that the large number of coding frame truncations has accompanied the change in reproductive mode of the wTpre strain.
Keywords: Animals; Ankyrin Repeat; Bacterial Proteins; Biological Evolution; Culicidae; Drosophila; Frameshift Mutation; Genome, Bacterial; Genomics; Host Specificity; Open Reading Frames; Parthenogenesis; Phylogeny; Symbiosis; Wasps; Wolbachia

Comparative Genomics of Two Closely Related Wolbachia with Different Reproductive Effects on Hosts. - Newton, Irene L G; Clark, Michael E; Kent, Bethany N; Bordenstein, Seth R; Qu, Jiaxin; Richards, Stephen; Kelkar, Yogeshwar D; Werren, John H (Genome Biol Evol, 2016)
Wolbachia pipientis are obligate intracellular bacteria commonly found in many arthropods. They can induce various reproductive alterations in hosts, including cytoplasmic incompatibility, male-killing, feminization, and parthenogenetic development, and can provide host protection against some viruses and other pathogens. Wolbachia differ from many other primary endosymbionts in arthropods because they undergo frequent horizontal transmission between hosts and are well known for an abundance of mobile elements and relatively high recombination rates. Here, we compare the genomes of two closely related Wolbachia (with 0.57% genome-wide synonymous divergence) that differ in their reproductive effects on hosts. wVitA induces a sperm-egg incompatibility (also known as cytoplasmic incompatibility) in the parasitoid insect Nasonia vitripennis, whereas wUni causes parthenogenetic development in a different parasitoid, Muscidifurax uniraptor Although these bacteria are closely related, the genomic comparison reveals rampant rearrangements, protein truncations (particularly in proteins predicted to be secreted), and elevated substitution rates. These changes occur predominantly in the wUni lineage, and may be due in part to adaptations by wUni to a new host environment, or its phenotypic shift to parthenogenesis induction. However, we conclude that the approximately 8-fold elevated synonymous substitution rate in wUni is due to a either an elevated mutation rate or a greater number of generations per year in wUni, which occurs in semitropical host species. We identify a set of genes whose loss or pseudogenization in the wUni lineage implicates them in the phenotypic shift from cytoplasmic incompatibility to parthenogenesis induction. Finally, comparison of these closely related strains allows us to determine the fine-scale mutation patterns in Wolbachia Although Wolbachia are AT rich, mutation probabilities estimated from 4-fold degenerate sites are not AT biased, and predict an equilibrium AT content much less biased than observed (57-50% AT predicted vs. 76% current content at degenerate sites genome wide). The contrast suggests selection for increased AT content within Wolbachia genomes.
Keywords: Animals; Arthropods; Cytoplasm; Drosophila; Genome, Bacterial; Genomics; Host Specificity; Male; Mutation; Phylogeny; Reproduction; Selection, Genetic; Wolbachia

Complex inheritance of ABCA4 disease: four mutations in a family with multiple macular phenotypes. - Lee, Winston; Xie, Yajing; Zernant, Jana; Bo Yuan; Bearelly, Srilaxmi; Tsang, Stephen H; James R Lupski; Allikmets, Rando (Hum Genet, 2016)
Over 800 mutations in the ABCA4 gene cause autosomal recessive Stargardt disease. Due to extensive genetic heterogeneity, observed variant-associated phenotypes can manifest tremendous variability of expression. Furthermore, the high carrier frequency of pathogenic ABCA4 alleles in the general population (~1:20) often results in pseudo-dominant inheritance patterns further complicating the diagnosis and characterization of affected individuals. This study describes a genotype/phenotype analysis of an unusual family with multiple macular disease phenotypes spanning across two generations and segregating four distinct ABCA4 mutant alleles. Complete sequencing of ABCA4 discovered two known missense mutations, p.C54Y and p.G1961E. Array comparative genomic hybridization revealed a large novel deletion combined with a small insertion, c.6148-698_c.6670del/insTGTGCACCTCCCTAG, and complete sequencing of the entire ABCA4 genomic locus uncovered a new deep intronic variant, c.302+68C>T. Patients with the p.G1961E mutation had the mildest, confined maculopathy phenotype with peripheral flecks while those with all other mutant allele combinations exhibited a more advanced stage of generalized retinal and choriocapillaris atrophy. This family epitomizes the clinical and genetic complexity of ABCA4-associated diseases. It contained variants from all classes of mutations, in the coding region, deep intronic, both single nucleotide variants and copy number variants that accounted for varying phenotypes segregating in an apparent dominant fashion. Unequivocally defining disease-associated alleles in the ABCA4 locus requires a multifaceted approach that includes advanced mutation detection methods and a thorough analysis of clinical phenotypes.
Keywords: Adult; Aged; ATP-Binding Cassette Transporters; Comparative Genomic Hybridization; DNA Copy Number Variations; Electroretinography; Female; High-Throughput Nucleotide Sequencing; Humans; Macula Lutea; Macular Degeneration; Male; Middle Aged; Mutation; Pedigree; Phenotype; Stargardt Disease

Comprehensive Pan-Genomic Characterization of Adrenocortical Carcinoma. - Zheng, Siyuan; Cherniack, Andrew D; Dewal, Ninad; Moffitt, Richard A; Danilova, Ludmila; Murray, Bradley A; Lerario, Antonio M; Else, Tobias; Knijnenburg, Theo A; Ciriello, Giovanni; Kim, Seungchan; Assie, Guillaume; et al. (Cancer Cell, 2016)
We describe a comprehensive genomic characterization of adrenocortical carcinoma (ACC). Using this dataset, we expand the catalogue of known ACC driver genes to include PRKAR1A, RPL22, TERF2, CCNE1, and NF1. Genome wide DNA copy-number analysis revealed frequent occurrence of massive DNA loss followed by whole-genome doubling (WGD), which was associated with aggressive clinical course, suggesting WGD is a hallmark of disease progression. Corroborating this hypothesis were increased TERT expression, decreased telomere length, and activation of cell-cycle programs. Integrated subtype analysis identified three ACC subtypes with distinct clinical outcome and molecular alterations which could be captured by a 68-CpG probe DNA-methylation signature, proposing a strategy for clinical stratification of patients based on molecular markers.
Keywords: Adolescent; Adrenal Cortex Neoplasms; Adrenocortical Carcinoma; Adult; Aged; Aged, 80 and over; Child; Disease-Free Survival; DNA Methylation; Female; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; Male; Middle Aged; Mutation; Outcome Assessment, Health Care; Prognosis; Young Adult

Conditional knockout of retinal determination genes in differentiating cells in Drosophila. - Jin, Meng; Eblimit, Aiden; Pulikkathara, Merlyn; Corr, Stuart; Chen, Rui; Mardon, Graeme (FEBS J, 2016)
Conditional gene knockout in postmitotic cells is a valuable technique which allows the study of gene function with spatiotemporal control. Surprisingly, in contrast to its long-term and extensive use in mouse studies, this technology is lacking in Drosophila. Here, we use a novel method for generating complete loss of eyes absent (eya) or sine oculis (so) function in postmitotic cells posterior to the morphogenetic furrow (MF). Specifically, genomic rescue constructs with flippase recognition target (FRT) sequences flanking essential exons are used to generate conditional null alleles. By removing gene function in differentiating cells, we show that eya and so are dispensable for larval photoreceptor differentiation, but are required for differentiation during pupal development. Both eya and so are necessary for photoreceptor survival and the apoptosis caused by loss of eya or so function is likely a secondary consequence of inappropriate differentiation. We also confirm their requirement for cone cell development and reveal a novel role in interommatidial bristle (IOB) formation. In addition, so is required for normal eye disc morphology. This is the first report of a knockout method to study eya and so function in postmitotic cells. This technology will open the door to a large array of new functional studies in virtually any tissue and at any stage of development or in adults.
Keywords: Alleles; Animals; Cell Differentiation; Drosophila; Drosophila Proteins; Eye; Eye Proteins; Gene Knockout Techniques; Homeodomain Proteins; Larva; Photoreceptor Cells, Invertebrate; Retina

Copy-Number Variation Contributes to the Mutational Load of Bardet-Biedl Syndrome. - Lindstrand, Anna; Frangakis, Stephan; Carvalho, Claudia M B; Richardson, Ellen B; McFadden, Kelsey A; Willer, Jason R; Pehlivan, Davut; Liu, Pengfei; Pediaditakis, Igor L; Sabo, Aniko; Lewis, Richard Alan; Banin, Eyal; et al. (Am J Hum Genet, 2016)
Bardet-Biedl syndrome (BBS) is a defining ciliopathy, notable for extensive allelic and genetic heterogeneity, almost all of which has been identified through sequencing. Recent data have suggested that copy-number variants (CNVs) also contribute to BBS. We used a custom oligonucleotide array comparative genomic hybridization (aCGH) covering 20 genes that encode intraflagellar transport (IFT) components and 74 ciliopathy loci to screen 92 unrelated individuals with BBS, irrespective of their known mutational burden. We identified 17 individuals with exon-disruptive CNVs (18.5%), including 13 different deletions in eight BBS genes (BBS1, BBS2, ARL6/BBS3, BBS4, BBS5, BBS7, BBS9, and NPHP1) and a deletion and a duplication in other ciliopathy-associated genes (ALMS1 and NPHP4, respectively). By contrast, we found a single heterozygous exon-disruptive event in a BBS-associated gene (BBS9) in 229 control subjects. Superimposing these data with resequencing revealed CNVs to (1) be sufficient to cause disease, (2) Mendelize heterozygous deleterious alleles, and (3) contribute oligogenic alleles by combining point mutations and exonic CNVs in multiple genes. Finally, we report a deletion and a splice site mutation in IFT74, inherited under a recessive paradigm, defining a candidate BBS locus. Our data suggest that CNVs contribute pathogenic alleles to a substantial fraction of BBS-affected individuals and highlight how either deletions or point mutations in discrete splice isoforms can induce hypomorphic mutations in genes otherwise intolerant to deleterious variation. Our data also suggest that CNV analyses and resequencing studies unbiased for previous mutational burden is necessary to delineate the complexity of disease architecture.
Keywords: Adolescent; Adult; Alleles; Animals; Bardet-Biedl Syndrome; Child; Child, Preschool; Chromosome Breakpoints; Cytoskeletal Proteins; DNA Copy Number Variations; Exons; Female; Gastrulation; Genes, Recessive; Humans; Infant; Male; Mutation; Pedigree; Young Adult; Zebrafish; Zebrafish Proteins

CRIPT exonic deletion and a novel missense mutation in a female with short stature, dysmorphic features, microcephaly, and pigmentary abnormalities. - Leduc, Magalie S; Niu, Zhiyv; Bi, Weimin; Zhu, Wenmiao; Miloslavskaya, Irene; Chiang, Theodore; Streff, Haley; Seavitt, John R; Murray, Stephen A; Eng, Christine; Chan, Audrey; Yang, Yaping; et al. (Am J Med Genet A, 2016)
Mutations in CRIPT encoding cysteine-rich PDZ domain-binding protein are rare, and to date have been reported in only two patients with autosomal recessive primordial dwarfism and distinctive facies. Here, we describe a female with biallelic mutations in CRIPT presenting with postnatal growth retardation, global developmental delay, and dysmorphic features including frontal bossing, high forehead, and sparse hair and eyebrows. Additional clinical features included high myopia, admixed hyper- and hypopigmented macules primarily on the face, arms, and legs, and syndactyly of 4-5 toes bilaterally. Using whole exome sequencing (WES) and chromosomal microarray analysis (CMA), we detected a c.8G>A (p.C3Y) missense variant in exon 1 of the CRIPT gene inherited from the mother and a 1,331 bp deletion encompassing exon 1, inherited from the father. The c.8G>A (p.C3Y) missense variant in CRIPT was apparently homozygous in the proband due to the exon 1 deletion. Our findings illustrate the clinical utility of combining WES with copy number variant (CNV) analysis to provide a molecular diagnosis to patients with rare Mendelian disorders. Our findings also illustrate the clinical spectrum of CRIPT related mutations. © 2016 Wiley Periodicals, Inc.
Keywords: Abnormalities, Multiple; Adaptor Proteins, Signal Transducing; Alleles; Amino Acid Substitution; Child, Preschool; DNA Mutational Analysis; Dwarfism; Exons; Facies; Female; Genetic Association Studies; Humans; Microcephaly; Mutation, Missense; Pedigree; Phenotype; Sequence Deletion

Cross-species identification of genomic drivers of squamous cell carcinoma development across preneoplastic intermediates. - Chitsazzadeh, Vida; Coarfa, Cristian; Drummond, Jennifer A; Nguyen, Tri; Joseph, Aaron; Chilukuri, Suneel; Charpiot, Elizabeth; Adelmann, Charles H; Ching, Grace; Nguyen, Tran N; Nicholas, Courtney; Thomas, Valencia D; et al. (Nat Commun, 2016)
Cutaneous squamous cell carcinoma (cuSCC) comprises 15-20% of all skin cancers, accounting for over 700,000 cases in USA annually. Most cuSCC arise in association with a distinct precancerous lesion, the actinic keratosis (AK). To identify potential targets for molecularly targeted chemoprevention, here we perform integrated cross-species genomic analysis of cuSCC development through the preneoplastic AK stage using matched human samples and a solar ultraviolet radiation-driven Hairless mouse model. We identify the major transcriptional drivers of this progression sequence, showing that the key genomic changes in cuSCC development occur in the normal skin to AK transition. Our data validate the use of this ultraviolet radiation-driven mouse cuSCC model for cross-species analysis and demonstrate that cuSCC bears deep molecular similarities to multiple carcinogen-driven SCCs from diverse sites, suggesting that cuSCC may serve as an effective, accessible model for multiple SCC types and that common treatment and prevention strategies may be feasible.
Keywords: Animals; Antineoplastic Agents; Carcinogenesis; Carcinoma, Squamous Cell; Disease Progression; DNA Mutational Analysis; Exome Sequencing; Female; Gene Expression Profiling; Genomics; High-Throughput Nucleotide Sequencing; Humans; Keratosis, Actinic; Mice; Mice, Hairless; Molecular Targeted Therapy; Precancerous Conditions; Sequence Analysis, RNA; Skin; Skin Neoplasms; Ultraviolet Rays

Destabilized SMC5/6 complex leads to chromosome breakage syndrome with severe lung disease. - van der Crabben, Saskia N; Hennus, Marije P; McGregor, Grant A; Ritter, Deborah I; Nagamani, Sandesh C S; Wells, Owen S; Harakalova, Magdalena; Chinn, Ivan K; Alt, Aaron; Vondrova, Lucie; Hochstenbach, Ron; van Montfrans, Joris M; et al. (J Clin Invest, 2016)
The structural maintenance of chromosomes (SMC) family of proteins supports mitotic proliferation, meiosis, and DNA repair to control genomic stability. Impairments in chromosome maintenance are linked to rare chromosome breakage disorders. Here, we have identified a chromosome breakage syndrome associated with severe lung disease in early childhood. Four children from two unrelated kindreds died of severe pulmonary disease during infancy following viral pneumonia with evidence of combined T and B cell immunodeficiency. Whole exome sequencing revealed biallelic missense mutations in the NSMCE3 (also known as NDNL2) gene, which encodes a subunit of the SMC5/6 complex that is essential for DNA damage response and chromosome segregation. The NSMCE3 mutations disrupted interactions within the SMC5/6 complex, leading to destabilization of the complex. Patient cells showed chromosome rearrangements, micronuclei, sensitivity to replication stress and DNA damage, and defective homologous recombination. This work associates missense mutations in NSMCE3 with an autosomal recessive chromosome breakage syndrome that leads to defective T and B cell function and acute respiratory distress syndrome in early childhood.
Keywords: Abnormalities, Multiple; Alleles; B-Lymphocytes; Cell Cycle Proteins; Cell Proliferation; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Chromosome Breakage; Chromosome Segregation; Chromosomes; DNA Damage; DNA Repair; DNA Replication; Family Health; Female; Fibroblasts; Homozygote; Humans; Infant; Intracellular Signaling Peptides and Proteins; Lung Diseases; Male; Meiosis; Mitosis; Mutation, Missense; Pedigree; Recombination, Genetic; Syndrome; T-Lymphocytes

Discovery of Genetic Variation on Chromosome 5q22 Associated with Mortality in Heart Failure. - Smith, J Gustav; Felix, Janine F; Morrison, Alanna C; Kalogeropoulos, Andreas; Trompet, Stella; Wilk, Jemma B; Gidlöf, Olof; Wang, Xinchen; Morley, Michael; Mendelson, Michael; Joehanes, Roby; Ligthart, Symen; et al. (PLoS Genet, 2016)
Failure of the human heart to maintain sufficient output of blood for the demands of the body, heart failure, is a common condition with high mortality even with modern therapeutic alternatives. To identify molecular determinants of mortality in patients with new-onset heart failure, we performed a meta-analysis of genome-wide association studies and follow-up genotyping in independent populations. We identified and replicated an association for a genetic variant on chromosome 5q22 with 36% increased risk of death in subjects with heart failure (rs9885413, P = 2.7x10-9). We provide evidence from reporter gene assays, computational predictions and epigenomic marks that this polymorphism increases activity of an enhancer region active in multiple human tissues. The polymorphism was further reproducibly associated with a DNA methylation signature in whole blood (P = 4.5x10-40) that also associated with allergic sensitization and expression in blood of the cytokine TSLP (P = 1.1x10-4). Knockdown of the transcription factor predicted to bind the enhancer region (NHLH1) in a human cell line (HEK293) expressing NHLH1 resulted in lower TSLP expression. In addition, we observed evidence of recent positive selection acting on the risk allele in populations of African descent. Our findings provide novel genetic leads to factors that influence mortality in patients with heart failure.
Keywords: Alleles; Basic Helix-Loop-Helix Transcription Factors; Black or African American; Chromosomes, Human, Pair 5; DNA Methylation; Female; Gene Expression Regulation; Gene Knockdown Techniques; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genotype; Heart Failure; HEK293 Cells; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Cytokine

DNA methylation-based measures of biological age: meta-analysis predicting time to death. - Chen, Brian H; Marioni, Riccardo E; Colicino, Elena; Peters, Marjolein J; Ward-Caviness, Cavin K; Tsai, Pei-Chien; Roetker, Nicholas S; Just, Allan C; Demerath, Ellen W; Guan, Weihua; Bressler, Jan; Fornage, Myriam; et al. (Aging (Albany NY), 2016)
Estimates of biological age based on DNA methylation patterns, often referred to as "epigenetic age", "DNAm age", have been shown to be robust biomarkers of age in humans. We previously demonstrated that independent of chronological age, epigenetic age assessed in blood predicted all-cause mortality in four human cohorts. Here, we expanded our original observation to 13 different cohorts for a total sample size of 13,089 individuals, including three racial/ethnic groups. In addition, we examined whether incorporating information on blood cell composition into the epigenetic age metrics improves their predictive power for mortality. All considered measures of epigenetic age acceleration were predictive of mortality (p≤8.2x10, independent of chronological age, even after adjusting for additional risk factors (p<5.4x10, and within the racial/ethnic groups that we examined (non-Hispanic whites, Hispanics, African Americans). Epigenetic age estimates that incorporated information on blood cell composition led to the smallest p-values for time to death (p=7.5x10). Overall, this study a) strengthens the evidence that epigenetic age predicts all-cause mortality above and beyond chronological age and traditional risk factors, and b) demonstrates that epigenetic age estimates that incorporate information on blood cell counts lead to highly significant associations with all-cause mortality.
Keywords: Aging; DNA Methylation; Epigenesis, Genetic; Female; Humans; Logistic Models; Male; Mortality; Racial Groups; Risk Factors; Survival Analysis; T-Lymphocyte Subsets

DNAism: exploring genomic datasets on the web with Horizon Charts. - Rio Deiros, David; Gibbs, Richard A; Rogers, Jeffrey (BMC Bioinformatics, 2016)
BACKGROUND: Computational biologists daily face the need to explore massive amounts of genomic data. New visualization techniques can help researchers navigate and understand these big data. Horizon Charts are a relatively new visualization method that, under the right circumstances, maximizes data density without losing graphical perception. RESULTS: Horizon Charts have been successfully applied to understand multi-metric time series data. We have adapted an existing JavaScript library (Cubism) that implements Horizon Charts for the time series domain so that it works effectively with genomic datasets. We call this new library DNAism. CONCLUSIONS: Horizon Charts can be an effective visual tool to explore complex and large genomic datasets. Researchers can use our library to leverage these techniques to extract additional insights from their own datasets.
Keywords: Computational Biology; Computer Graphics; Datasets as Topic; Gene Library; Genome, Human; Genomics; Humans; Internet; Software

DVL3 Alleles Resulting in a -1 Frameshift of the Last Exon Mediate Autosomal-Dominant Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Hoischen, Alexander; Bayram, Yavuz; Withers, Marjorie; Gezdirici, Alper; Kimonis, Virginia; Steehouwer, Marloes; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; van Bon, Bregje W M; et al. (Am J Hum Genet, 2016)
Robinow syndrome is a rare congenital disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features. Recent reports have identified, in individuals with dominant Robinow syndrome, a specific type of variant characterized by being uniformly located in the penultimate exon of DVL1 and resulting in a -1 frameshift allele with a premature termination codon that escapes nonsense-mediated decay. Here, we studied a cohort of individuals who had been clinically diagnosed with Robinow syndrome but who had not received a molecular diagnosis from variant studies of DVL1, WNT5A, and ROR2. Because of the uniform location of frameshift variants in DVL1-mediated Robinow syndrome and the functional redundancy of DVL1, DVL2, and DVL3, we elected to pursue direct Sanger sequencing of the penultimate exon of DVL1 and its paralogs DVL2 and DVL3 to search for potential disease-associated variants. Remarkably, targeted sequencing identified five unrelated individuals harboring heterozygous, de novo frameshift variants in DVL3, including two splice acceptor mutations and three 1 bp deletions. Similar to the variants observed in DVL1-mediated Robinow syndrome, all variants in DVL3 result in a -1 frameshift, indicating that these highly specific alterations might be a common cause of dominant Robinow syndrome. Here, we review the current knowledge of these peculiar variant alleles in DVL1- and DVL3-mediated Robinow syndrome and further elucidate the phenotypic features present in subjects with DVL1 and DVL3 frameshift mutations.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Base Sequence; Codon, Nonsense; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exons; Female; Frameshift Mutation; Genetic Variation; Humans; Limb Deformities, Congenital; Male; Molecular Sequence Data; Phosphoproteins; Proto-Oncogene Proteins; Receptor Tyrosine Kinase-like Orphan Receptors; Sequence Analysis, DNA; Sequence Deletion; Urogenital Abnormalities; Wnt Proteins; Wnt-5a Protein

An Empirical Comparison of Joint and Stratified Frameworks for Studying G × E Interactions: Systolic Blood Pressure and Smoking in the CHARGE Gene-Lifestyle Interactions Working Group. - Sung, Yun Ju; Winkler, Thomas W; Manning, Alisa K; Aschard, Hugues; Gudnason, Vilmundur; Harris, Tamara B; Smith, Albert V; Boerwinkle, Eric; Brown, Michael R; Morrison, Alanna C; Fornage, Myriam; Lin, Li-An; et al. (Genet Epidemiol, 2016)
Studying gene-environment (G × E) interactions is important, as they extend our knowledge of the genetic architecture of complex traits and may help to identify novel variants not detected via analysis of main effects alone. The main statistical framework for studying G × E interactions uses a single regression model that includes both the genetic main and G × E interaction effects (the "joint" framework). The alternative "stratified" framework combines results from genetic main-effect analyses carried out separately within the exposed and unexposed groups. Although there have been several investigations using theory and simulation, an empirical comparison of the two frameworks is lacking. Here, we compare the two frameworks using results from genome-wide association studies of systolic blood pressure for 3.2 million low frequency and 6.5 million common variants across 20 cohorts of European ancestry, comprising 79,731 individuals. Our cohorts have sample sizes ranging from 456 to 22,983 and include both family-based and population-based samples. In cohort-specific analyses, the two frameworks provided similar inference for population-based cohorts. The agreement was reduced for family-based cohorts. In meta-analyses, agreement between the two frameworks was less than that observed in cohort-specific analyses, despite the increased sample size. In meta-analyses, agreement depended on (1) the minor allele frequency, (2) inclusion of family-based cohorts in meta-analysis, and (3) filtering scheme. The stratified framework appears to approximate the joint framework well only for common variants in population-based cohorts. We conclude that the joint framework is the preferred approach and should be used to control false positives when dealing with low-frequency variants and/or family-based cohorts.
Keywords: Blood Pressure; Cohort Studies; Databases, Factual; Family; Gene Frequency; Gene-Environment Interaction; Genome-Wide Association Study; Genotype; Humans; Phenotype; Smoking

The Ensembl gene annotation system. - Aken, Bronwen L; Ayling, Sarah; Barrell, Daniel; Clarke, Laura; Curwen, Valery; Fairley, Susan; Fernandez Banet, Julio; Billis, Konstantinos; García Girón, Carlos; Hourlier, Thibaut; Howe, Kevin; Kähäri, Andreas; et al. (Database (Oxford), 2016)
The Ensembl gene annotation system has been used to annotate over 70 different vertebrate species across a wide range of genome projects. Furthermore, it generates the automatic alignment-based annotation for the human and mouse GENCODE gene sets. The system is based on the alignment of biological sequences, including cDNAs, proteins and RNA-seq reads, to the target genome in order to construct candidate transcript models. Careful assessment and filtering of these candidate transcripts ultimately leads to the final gene set, which is made available on the Ensembl website. Here, we describe the annotation process in detail.Database URL: http://www.ensembl.org/index.html.
Keywords: Animals; Databases, Nucleic Acid; Databases, Protein; Humans; Internet; Mice; Molecular Sequence Annotation

The ethics of conducting molecular autopsies in cases of sudden death in the young. - McGuire, Amy L; Moore, Quianta; Majumder, Mary; Walkiewicz, Magdalena; Eng, Christine M; Belmont, John W; Nassef, Salma; Darilek, Sandra; Rutherford, Katie; Pereira, Stacey; Steven E Scherer; Sutton, V Reid; et al. (Genome Res, 2016)
Keywords: Autopsy; Child; Child, Preschool; Confidentiality; Consent Forms; Coroners and Medical Examiners; Disclosure; Ethics, Medical; Genetic Testing; Humans; Infant; Infant, Newborn

Exome sequencing in mostly consanguineous Arab families with neurologic disease provides a high potential molecular diagnosis rate. - Charng, Wu-Lin; Karaca, Ender; Coban Akdemir, Zeynep; Gambin, Tomasz; Atik, Mehmed M; Gu, Shen; Posey, Jennifer E; Jhangiani, Shalini N; Muzny, Donna M; Doddapaneni, Harsha; Hu, Jianhong; Boerwinkle, Eric; et al. (BMC Med Genomics, 2016)
BACKGROUND: Neurodevelopment is orchestrated by a wide range of genes, and the genetic causes of neurodevelopmental disorders are thus heterogeneous. We applied whole exome sequencing (WES) for molecular diagnosis and in silico analysis to identify novel disease gene candidates in a cohort from Saudi Arabia with primarily Mendelian neurologic diseases. METHODS: We performed WES in 31 mostly consanguineous Arab families and analyzed both single nucleotide and copy number variants (CNVs) from WES data. Interaction/expression network and pathway analyses, as well as paralog studies were utilized to investigate potential pathogenicity and disease association of novel candidate genes. Additional cases for candidate genes were identified through the clinical WES database at Baylor Miraca Genetics Laboratories and GeneMatcher. RESULTS: We found known pathogenic or novel variants in known disease genes with phenotypic expansion in 6 families, disease-associated CNVs in 2 families, and 12 novel disease gene candidates in 11 families, including KIF5B, GRM7, FOXP4, MLLT1, and KDM2B. Overall, a potential molecular diagnosis was provided by variants in known disease genes in 17 families (54.8 %) and by novel candidate disease genes in an additional 11 families, making the potential molecular diagnostic rate ~90 %. CONCLUSIONS: Molecular diagnostic rate from WES is improved by exome-predicted CNVs. Novel candidate disease gene discovery is facilitated by paralog studies and through the use of informatics tools and available databases to identify additional evidence for pathogenicity. TRIAL REGISTRATION: Not applicable.
Keywords: Arabs; Cohort Studies; Consanguinity; Data Mining; Databases, Genetic; DNA Copy Number Variations; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Molecular Diagnostic Techniques; Nervous System Diseases; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Genetic Variants in LRP1 and ULK4 Are Associated with Acute Aortic Dissections. - Guo, Dong-chuan; Grove, Megan L; Prakash, Siddharth K; Eriksson, Per; Hostetler, Ellen M; LeMaire, Scott A; Body, Simon C; Shalhub, Sherene; Estrera, Anthony L; Safi, Hazim J; Regalado, Ellen S; Zhou, Wei; et al. (Am J Hum Genet, 2016)
Acute aortic dissections are a preventable cause of sudden death if individuals at risk are identified and surgically repaired in a non-emergency setting. Although mutations in single genes can be used to identify at-risk individuals, the majority of dissection case subjects do not have evidence of a single gene disorder, but rather have the other major risk factor for dissections, hypertension. Initial genome-wide association studies (GWASs) identified SNPs at the FBN1 locus associated with both thoracic aortic aneurysms and dissections. Here, we used the Illumina HumanExome array to genotype 753 individuals of European descent presenting specifically with non-familial, sporadic thoracic aortic dissection (STAD) and compared them to the genotypes of 2,259 control subjects from the Atherosclerosis Risk in Communities (ARIC) study matched for age, gender, and, for the majority of cases, hypertension. SNPs in FBN1, LRP1, and ULK4 were identified to be significantly associated with STAD, and these results were replicated in two independent cohorts. Combining the data from all cohorts confirmed an inverse association between LRP1 rs11172113 and STAD (p = 2.74 × 10(-8); OR = 0.82, 95% CI = 0.76-0.89) and a direct association between ULK4 rs2272007 and STAD (p = 1.15 × 10(-9); OR = 1.35, 95% CI = 1.23-1.49). Genomic copy-number variation analysis independently confirmed that ULK4 deletions were significantly associated with development of thoracic aortic disease. These results indicate that genetic variations in LRP1 and ULK4 contribute to risk for presenting with an acute aortic dissection.
Keywords: Aged; Aortic Aneurysm, Thoracic; Aortic Dissection; Atherosclerosis; Case-Control Studies; Cohort Studies; DNA Copy Number Variations; Europe; Exome; Female; Fibrillin-1; Gene Deletion; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Hypertension; Linkage Disequilibrium; Low Density Lipoprotein Receptor-Related Protein-1; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases; Risk Factors

Genomic analyses identify molecular subtypes of pancreatic cancer. - Bailey, Peter; Chang, David K; Nones, Katia; Johns, Amber L; Patch, Ann-Marie; Marie-Claude Gingras; Miller, David K; Christ, Angelika N; Bruxner, Tim J C; Quinn, Michael C; Nourse, Craig; Murtaugh, L Charles; et al. (Nature, 2016)
Integrated genomic analysis of 456 pancreatic ductal adenocarcinomas identified 32 recurrently mutated genes that aggregate into 10 pathways: KRAS, TGF-β, WNT, NOTCH, ROBO/SLIT signalling, G1/S transition, SWI-SNF, chromatin modification, DNA repair and RNA processing. Expression analysis defined 4 subtypes: (1) squamous; (2) pancreatic progenitor; (3) immunogenic; and (4) aberrantly differentiated endocrine exocrine (ADEX) that correlate with histopathological characteristics. Squamous tumours are enriched for TP53 and KDM6A mutations, upregulation of the TP63∆N transcriptional network, hypermethylation of pancreatic endodermal cell-fate determining genes and have a poor prognosis. Pancreatic progenitor tumours preferentially express genes involved in early pancreatic development (FOXA2/3, PDX1 and MNX1). ADEX tumours displayed upregulation of genes that regulate networks involved in KRAS activation, exocrine (NR5A2 and RBPJL), and endocrine differentiation (NEUROD1 and NKX2-2). Immunogenic tumours contained upregulated immune networks including pathways involved in acquired immune suppression. These data infer differences in the molecular evolution of pancreatic cancer subtypes and identify opportunities for therapeutic development.
Keywords: Animals; Basic Helix-Loop-Helix Transcription Factors; Carcinoma, Pancreatic Ductal; Cell Line, Tumor; DNA Methylation; DNA-Binding Proteins; Gene Expression Regulation, Neoplastic; Gene Regulatory Networks; Genes, Neoplasm; Genome, Human; Genomics; Hepatocyte Nuclear Factor 3-beta; Hepatocyte Nuclear Factor 3-gamma; Histone Demethylases; Homeobox Protein Nkx-2.2; Homeodomain Proteins; Humans; Mice; Mutation; Nuclear Proteins; Pancreatic Neoplasms; Prognosis; Receptors, Cytoplasmic and Nuclear; Survival Analysis; Trans-Activators; Transcription Factors; Transcription, Genetic; Transcriptome; Tumor Suppressor Protein p53; Tumor Suppressor Proteins; Zebrafish Proteins

A genomic approach to therapeutic target validation identifies a glucose-lowering GLP1R variant protective for coronary heart disease. - Scott, Robert A; Freitag, Daniel F; Li, Li; Chu, Audrey Y; Surendran, Praveen; Young, Robin; Grarup, Niels; Stančáková, Alena; Chen, Yuning; Varga, Tibor V; Yaghootkar, Hanieh; Luan, Jian'an; et al. (Sci Transl Med, 2016)
Regulatory authorities have indicated that new drugs to treat type 2 diabetes (T2D) should not be associated with an unacceptable increase in cardiovascular risk. Human genetics may be able to guide development of antidiabetic therapies by predicting cardiovascular and other health endpoints. We therefore investigated the association of variants in six genes that encode drug targets for obesity or T2D with a range of metabolic traits in up to 11,806 individuals by targeted exome sequencing and follow-up in 39,979 individuals by targeted genotyping, with additional in silico follow-up in consortia. We used these data to first compare associations of variants in genes encoding drug targets with the effects of pharmacological manipulation of those targets in clinical trials. We then tested the association of those variants with disease outcomes, including coronary heart disease, to predict cardiovascular safety of these agents. A low-frequency missense variant (Ala316Thr; rs10305492) in the gene encoding glucagon-like peptide-1 receptor (GLP1R), the target of GLP1R agonists, was associated with lower fasting glucose and T2D risk, consistent with GLP1R agonist therapies. The minor allele was also associated with protection against heart disease, thus providing evidence that GLP1R agonists are not likely to be associated with an unacceptable increase in cardiovascular risk. Our results provide an encouraging signal that these agents may be associated with benefit, a question currently being addressed in randomized controlled trials. Genetic variants associated with metabolic traits and multiple disease outcomes can be used to validate therapeutic targets at an early stage in the drug development process.
Keywords: Alleles; Coronary Disease; Diabetes Mellitus, Type 2; Dipeptidyl Peptidase 4; Genotype; Glucagon-Like Peptide-1 Receptor; Humans; Obesity; Receptor, Cannabinoid, CB2; Receptor, Serotonin, 5-HT2C; Receptors, Somatostatin; Sodium-Glucose Transporter 1

The genomic basis of circadian and circalunar timing adaptations in a midge. - Kaiser, Tobias S; Poehn, Birgit; Szkiba, David; Preussner, Marco; Sedlazeck, Fritz J; Zrim, Alexander; Neumann, Tobias; Nguyen, Lam-Tung; Betancourt, Andrea J; Hummel, Thomas; Vogel, Heiko; Dorner, Silke; et al. (Nature, 2016)
Organisms use endogenous clocks to anticipate regular environmental cycles, such as days and tides. Natural variants resulting in differently timed behaviour or physiology, known as chronotypes in humans, have not been well characterized at the molecular level. We sequenced the genome of Clunio marinus, a marine midge whose reproduction is timed by circadian and circalunar clocks. Midges from different locations show strain-specific genetic timing adaptations. We examined genetic variation in five C. marinus strains from different locations and mapped quantitative trait loci for circalunar and circadian chronotypes. The region most strongly associated with circadian chronotypes generates strain-specific differences in the abundance of calcium/calmodulin-dependent kinase II.1 (CaMKII.1) splice variants. As equivalent variants were shown to alter CaMKII activity in Drosophila melanogaster, and C. marinus (Cma)-CaMKII.1 increases the transcriptional activity of the dimer of the circadian proteins Cma-CLOCK and Cma-CYCLE, we suggest that modulation of alternative splicing is a mechanism for natural adaptation in circadian timing.
Keywords: Acclimatization; Alternative Splicing; Animals; Calcium-Calmodulin-Dependent Protein Kinase Type 2; Chironomidae; Circadian Clocks; Circadian Rhythm; CLOCK Proteins; Drosophila melanogaster; Genetic Association Studies; Genetic Variation; Genome, Insect; Genomics; Male; Moon; Phenotype; Quantitative Trait Loci; Reproduction; Species Specificity; Tidal Waves; Time Factors; Transcription, Genetic

Genomic Profiling of Pediatric Acute Myeloid Leukemia Reveals a Changing Mutational Landscape from Disease Diagnosis to Relapse. - Farrar, Jason E; Schuback, Heather L; Ries, Rhonda E; Wai, Daniel; Hampton, Oliver A; Treviño, Lisa R; Alonzo, Todd A; Guidry Auvil, Jaime M; Davidsen, Tanja M; Gesuwan, Patee; Hermida, Leandro; Muzny, Donna M; et al. (Cancer Res, 2016)
The genomic and clinical information used to develop and implement therapeutic approaches for acute myelogenous leukemia (AML) originated primarily from adult patients and has been generalized to patients with pediatric AML. However, age-specific molecular alterations are becoming more evident and may signify the need to age-stratify treatment regimens. The NCI/COG TARGET-AML initiative used whole exome capture sequencing (WXS) to interrogate the genomic landscape of matched trios representing specimens collected upon diagnosis, remission, and relapse from 20 cases of de novo childhood AML. One hundred forty-five somatic variants at diagnosis (median 6 mutations/patient) and 149 variants at relapse (median 6.5 mutations) were identified and verified by orthogonal methodologies. Recurrent somatic variants [in (greater than or equal to) 2 patients] were identified for 10 genes (FLT3, NRAS, PTPN11, WT1, TET2, DHX15, DHX30, KIT, ETV6, KRAS), with variable persistence at relapse. The variant allele fraction (VAF), used to measure the prevalence of somatic mutations, varied widely at diagnosis. Mutations that persisted from diagnosis to relapse had a significantly higher diagnostic VAF compared with those that resolved at relapse (median VAF 0.43 vs. 0.24, P < 0.001). Further analysis revealed that 90% of the diagnostic variants with VAF >0.4 persisted to relapse compared with 28% with VAF <0.2 (P < 0.001). This study demonstrates significant variability in the mutational profile and clonal evolution of pediatric AML from diagnosis to relapse. Furthermore, mutations with high VAF at diagnosis, representing variants shared across a leukemic clonal structure, may constrain the genomic landscape at relapse and help to define key pathways for therapeutic targeting. Cancer Res; 76(8); 2197-205. ©2016 AACR.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Female; Gene Expression Profiling; Humans; Infant; Leukemia, Myeloid, Acute; Male; Mutation; Recurrence

Genomics of Natural Populations: How Differentially Expressed Genes Shape the Evolution of Chromosomal Inversions in Drosophila pseudoobscura. - Fuller, Zachary L; Haynes, Gwilym D; Richards, Stephen; Schaeffer, Stephen W (Genetics, 2016)
Chromosomal rearrangements can shape the structure of genetic variation in the genome directly through alteration of genes at breakpoints or indirectly by holding combinations of genetic variants together due to reduced recombination. The third chromosome of Drosophila pseudoobscura is a model system to test hypotheses about how rearrangements are established in populations because its third chromosome is polymorphic for >30 gene arrangements that were generated by a series of overlapping inversion mutations. Circumstantial evidence has suggested that these gene arrangements are selected. Despite the expected homogenizing effects of extensive gene flow, the frequencies of arrangements form gradients or clines in nature, which have been stable since the system was first described >80 years ago. Furthermore, multiple arrangements exist at appreciable frequencies across several ecological niches providing the opportunity for heterokaryotypes to form. In this study, we tested whether genes are differentially expressed among chromosome arrangements in first instar larvae, adult females and males. In addition, we asked whether transcriptional patterns in heterokaryotypes are dominant, semidominant, overdominant, or underdominant. We find evidence for a significant abundance of differentially expressed genes across the inverted regions of the third chromosome, including an enrichment of genes involved in sensory perception for males. We find the majority of loci show additivity in heterokaryotypes. Our results suggest that multiple genes have expression differences among arrangements that were either captured by the original inversion mutation or accumulated after it reached polymorphic frequencies, providing a potential source of genetic variation for selection to act upon. These data suggest that the inversions are favored because of their indirect effect of recombination suppression that has held different combinations of differentially expressed genes together in the various gene arrangement backgrounds.
Keywords: Animals; Biological Evolution; Chromosome Inversion; Chromosomes, Insect; Drosophila; Female; Gene Expression Regulation; Gene Flow; Gene Order; Genomics; Male; Metagenomics; Transcriptome

A hybrid computational strategy to address WGS variant analysis in >5000 samples. - Huang, Zhuoyi; Rustagi, Navin; Veeraraghavan, Narayanan; Carroll, Andrew; Gibbs, Richard; Boerwinkle, Eric; Venkata, Manjunath Gorentla; Yu, Fuli (BMC Bioinformatics, 2016)
BACKGROUND: The decreasing costs of sequencing are driving the need for cost effective and real time variant calling of whole genome sequencing data. The scale of these projects are far beyond the capacity of typical computing resources available with most research labs. Other infrastructures like the cloud AWS environment and supercomputers also have limitations due to which large scale joint variant calling becomes infeasible, and infrastructure specific variant calling strategies either fail to scale up to large datasets or abandon joint calling strategies. RESULTS: We present a high throughput framework including multiple variant callers for single nucleotide variant (SNV) calling, which leverages hybrid computing infrastructure consisting of cloud AWS, supercomputers and local high performance computing infrastructures. We present a novel binning approach for large scale joint variant calling and imputation which can scale up to over 10,000 samples while producing SNV callsets with high sensitivity and specificity. As a proof of principle, we present results of analysis on Cohorts for Heart And Aging Research in Genomic Epidemiology (CHARGE) WGS freeze 3 dataset in which joint calling, imputation and phasing of over 5300 whole genome samples was produced in under 6 weeks using four state-of-the-art callers. The callers used were SNPTools, GATK-HaplotypeCaller, GATK-UnifiedGenotyper and GotCloud. We used Amazon AWS, a 4000-core in-house cluster at Baylor College of Medicine, IBM power PC Blue BioU at Rice and Rhea at Oak Ridge National Laboratory (ORNL) for the computation. AWS was used for joint calling of 180 TB of BAM files, and ORNL and Rice supercomputers were used for the imputation and phasing step. All other steps were carried out on the local compute cluster. The entire operation used 5.2 million core hours and only transferred a total of 6 TB of data across the platforms. CONCLUSIONS: Even with increasing sizes of whole genome datasets, ensemble joint calling of SNVs for low coverage data can be accomplished in a scalable, cost effective and fast manner by using heterogeneous computing platforms without compromising on the quality of variants.
Keywords: Databases, Genetic; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans

Identification of Intellectual Disability Genes in Female Patients with a Skewed X-Inactivation Pattern. - Fieremans, Nathalie; Van Esch, Hilde; Holvoet, Maureen; Van Goethem, Gert; Devriendt, Koenraad; Rosello, Monica; Mayo, Sonia; Martinez, Francisco; Jhangiani, Shalini; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; et al. (Hum Mutat, 2016)
Intellectual disability (ID) is a heterogeneous disorder with an unknown molecular etiology in many cases. Previously, X-linked ID (XLID) studies focused on males because of the hemizygous state of their X chromosome. Carrier females are generally unaffected because of the presence of a second normal allele, or inactivation of the mutant X chromosome in most of their cells (skewing). However, in female ID patients, we hypothesized that the presence of skewing of X-inactivation would be an indicator for an X chromosomal ID cause. We analyzed the X-inactivation patterns of 288 females with ID, and found that 22 (7.6%) had extreme skewing (>90%), which is significantly higher than observed in the general population (3.6%; P = 0.029). Whole-exome sequencing of 19 females with extreme skewing revealed causal variants in six females in the XLID genes DDX3X, NHS, WDR45, MECP2, and SMC1A. Interestingly, variants in genes escaping X-inactivation presumably cause both XLID and skewing of X-inactivation in three of these patients. Moreover, variants likely accounting for skewing only were detected in MED12, HDAC8, and TAF9B. All tested candidate causative variants were de novo events. Hence, extreme skewing is a good indicator for the presence of X-linked variants in female patients.
Keywords: Carrier Proteins; Cell Cycle Proteins; Chromosomal Proteins, Non-Histone; DEAD-box RNA Helicases; Exome; Female; Genetic Variation; Humans; Intellectual Disability; Membrane Proteins; Methyl-CpG-Binding Protein 2; Nuclear Proteins; Sequence Analysis, DNA; X Chromosome Inactivation

Identification of novel direct targets of Drosophila Sine oculis and Eyes absent by integration of genome-wide data sets. - Jin, Meng; Aibar, Sara; Ge, Zhongqi; Chen, Rui; Aerts, Stein; Mardon, Graeme (Dev Biol, 2016)
Drosophila eye development is a complex process that involves many transcription factors (TFs) and interactions with their cofactors and targets. The TF Sine oculis (So) and its cofactor Eyes absent (Eya) are highly conserved and are both necessary and sufficient for eye development. Despite their many important roles during development, the direct targets of So are still largely unknown. Therefore the So-dependent regulatory network governing eye determination and differentiation is poorly understood. In this study, we intersected gene expression profiles of so or eya mutant eye tissue prepared from three different developmental stages and identified 1731 differentially expressed genes across the Drosophila genome. A combination of co-expression analyses and motif discovery identified a set of twelve putative direct So targets, including three known and nine novel targets. We also used our previous So ChIP-seq data to assess motif predictions for So and identified a canonical So binding motif. Finally, we performed in vivo enhancer reporter assays to test predicted enhancers from six candidate target genes and find that at least one enhancer from each gene is expressed in the developing eye disc and that their expression patterns overlap with that of So. We furthermore confirmed that the expression level of predicted direct So targets, for which antibodies are available, are reduced in so or eya post-mitotic knockout eye discs. In summary, we expand the set of putative So targets and show for the first time that the combined use of expression profiling of so with its cofactor eya is an effective method to identify novel So targets. Moreover, since So is highly conserved throughout the metazoa, our results provide the basis for future functional studies in a wide variety of organisms.
Keywords: Amino Acid Motifs; Amino Acid Sequence; Animals; Chromatin Immunoprecipitation; Compound Eye, Arthropod; Consensus Sequence; Drosophila melanogaster; Drosophila Proteins; Eye Proteins; Gene Expression Regulation, Developmental; Gene Ontology; Genetic Association Studies; Genome-Wide Association Study; Homeodomain Proteins; Imaginal Discs; Larva; Pupa; RNA, Messenger; Transcription, Genetic; Transcriptome

Mechanisms for Complex Chromosomal Insertions. - Gu, Shen; Szafranski, Przemyslaw; Akdemir, Zeynep Coban; Yuan, Bo; Cooper, Mitchell L; Magriñá, Maria A; Bacino, Carlos A; Lalani, Seema R; Breman, Amy M; Smith, Janice L; Patel, Ankita; Song, Rodger H; et al. (PLoS Genet, 2016)
Chromosomal insertions are genomic rearrangements with a chromosome segment inserted into a non-homologous chromosome or a non-adjacent locus on the same chromosome or the other homologue, constituting ~2% of nonrecurrent copy-number gains. Little is known about the molecular mechanisms of their formation. We identified 16 individuals with complex insertions among 56,000 individuals tested at Baylor Genetics using clinical array comparative genomic hybridization (aCGH) and fluorescence in situ hybridization (FISH). Custom high-density aCGH was performed on 10 individuals with available DNA, and breakpoint junctions were fine-mapped at nucleotide resolution by long-range PCR and DNA sequencing in 6 individuals to glean insights into potential mechanisms of formation. We observed microhomologies and templated insertions at the breakpoint junctions, resembling the breakpoint junction signatures found in complex genomic rearrangements generated by replication-based mechanism(s) with iterative template switches. In addition, we analyzed 5 families with apparently balanced insertion in one parent detected by FISH analysis and found that 3 parents had additional small copy-number variants (CNVs) at one or both sides of the inserting fragments as well as at the inserted sites. We propose that replicative repair can result in interchromosomal complex insertions generated through chromothripsis-like chromoanasynthesis involving two or three chromosomes, and cause a significant fraction of apparently balanced insertions harboring small flanking CNVs.
Keywords: Chromosome Aberrations; Chromosome Inversion; Comparative Genomic Hybridization; DNA Copy Number Variations; DNA Replication; Female; Gene Duplication; Genome, Human; Humans; In Situ Hybridization, Fluorescence; Male; Sequence Analysis, DNA; Translocation, Genetic

Mechanisms for the Generation of Two Quadruplications Associated with Split-Hand Malformation. - Gu, Shen; Posey, Jennifer E; Yuan, Bo; Carvalho, Claudia M B; Luk, H M; Erikson, Kelly; Lo, Ivan F M; Leung, Gordon K C; Pickering, Curtis R; Chung, Brian H Y; Lupski, James R (Hum Mutat, 2016)
Germline copy-number variants (CNVs) involving quadruplications are rare and the mechanisms generating them are largely unknown. Previously, we reported a 20-week gestation fetus with split-hand malformation; clinical microarray detected two maternally inherited triplications separated by a copy-number neutral region at 17p13.3, involving BHLHA9 and part of YWHAE. Here, we describe an 18-month-old male sibling of the previously described fetus with split-hand malformation. Custom high-density microarray and digital droplet PCR revealed the copy-number gains were actually quadruplications in the mother, the fetus, and her later born son. This quadruplication-normal-quadruplication pattern was shown to be expanded from the triplication-normal-triplication CNV at the same loci in the maternal grandmother. We mapped two breakpoint junctions and demonstrated that both are mediated by Alu repetitive elements and identical in these four individuals. We propose a three-step process combining Alu-mediated replicative-repair-based mechanism(s) and intergenerational, intrachromosomal nonallelic homologous recombination to generate the quadruplications in this family.
Keywords: 14-3-3 Proteins; Adult; Aged; Alu Elements; Base Sequence; Basic Helix-Loop-Helix Transcription Factors; Chromosome Duplication; Chromosomes, Human, Pair 17; DNA Copy Number Variations; Female; Genetic Loci; Genome, Human; Hand Deformities, Congenital; Humans; Infant; Male; Molecular Sequence Data; Pedigree; Sequence Alignment; Sequence Analysis, DNA

Microfluidic Cell Deformability Assay for Rapid and Efficient Kinase Screening with the CRISPR-Cas9 System. - Han, Xin; Liu, Zongbin; Zhao, Li; Wang, Feng; Yu, Yang; Yang, Jianhua; Chen, Rui; Qin, Lidong (Angew Chem Int Ed Engl, 2016)
Herein we report a CRISPR-Cas9-mediated loss-of-function kinase screen for cancer cell deformability and invasive potential in a high-throughput microfluidic chip. In this microfluidic cell separation platform, flexible cells with high deformability and metastatic propensity flowed out, while stiff cells remained trapped. Through deep sequencing, we found that loss of certain kinases resulted in cells becoming more deformable and invasive. High-ranking candidates identified included well-reported tumor suppressor kinases, such as chk2, IKK-α, p38 MAPKs, and DAPK2. A high-ranking candidate STK4 was chosen for functional validation and identified to play an important role in the regulation of cell deformability and tumor suppression. Collectively, we have demonstrated that CRISPR-based on-chip mechanical screening is a potentially powerful strategy to facilitate systematic genetic analyses.
Keywords: Cell Line, Tumor; Cell Movement; Checkpoint Kinase 2; CRISPR-Cas Systems; Cytochalasin D; Death-Associated Protein Kinases; Dimethyl Sulfoxide; Humans; I-kappa B Kinase; Intracellular Signaling Peptides and Proteins; Lab-On-A-Chip Devices; Microfluidics; Microscopy, Fluorescence; p38 Mitogen-Activated Protein Kinases; Protein Kinases; Protein Serine-Threonine Kinases

Mixed-phenotype acute leukemia (MPAL) exhibits frequent mutations in DNMT3A and activated signaling genes. - Eckstein, Olive S; Wang, Linghua; Punia, Jyotinder N; Kornblau, Steven M; Andreeff, Michael; Wheeler, David A; Goodell, Margaret A; Rau, Rachel E (Exp Hematol, 2016)
Mixed-phenotype acute leukemia (MPAL) is a heterogeneous group of poor-prognosis leukemias with immunophenotypic features of at least two cell lineages. The full spectrum of genetic mutations in this rare disease has not been elucidated, limiting our understanding of disease pathogenesis and our ability to devise targeted therapeutic strategies. Here, we sought to define the mutational landscape of MPAL by performing whole-exome sequencing on samples from 23 adult and pediatric MPAL patients. We identified frequent mutations of epigenetic modifiers, most notably mutations of DNMT3A, in 33% of adult MPAL patients. Mutations of activated signaling pathways, tumor suppressors, and transcription factors were also frequent. Importantly, many of the identified mutations are potentially therapeutically targetable, with agents currently available or in various stages of clinical development. Therefore, the mutational spectrum that we have identified provides potential biological insights and is likely to have clinical relevance for patients with this poor-prognosis disease.
Keywords: Adolescent; Adult; Clonal Evolution; Cluster Analysis; DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; Epigenesis, Genetic; Exome; Gene Expression Profiling; Gene Expression Regulation, Leukemic; High-Throughput Nucleotide Sequencing; Humans; Leukemia, Biphenotypic, Acute; Middle Aged; Mutation; Signal Transduction; Young Adult

Molecular and Clinical Findings in Patients With Knobloch Syndrome. - Hull, Sarah; Arno, Gavin; Ku, Cristy A; Ge, Zhongqi; Waseem, Naushin; Chandra, Aman; Webster, Andrew R; Robson, Anthony G; Michaelides, Michel; Weleber, Richard G; Davagnanam, Indran; Rui Chen; et al. (JAMA Ophthalmol, 2016)
IMPORTANCE: Knobloch syndrome is a rare, recessively inherited disorder classically characterized by high myopia, retinal detachment, and occipital encephalocele, but it is now known to have an increasingly variable phenotype. There is a lack of reported electrophysiologic data, and some key clinical features have yet to be described. OBJECTIVE: To expand on current clinical, electrophysiologic, and molecular genetic findings in Knobloch syndrome. DESIGN, SETTING, AND PARTICIPANTS: Twelve patients from 7 families underwent full ophthalmic examination and retinal imaging. Further investigations included electroretinography and neuroradiologic imaging. Bidirectional Sanger sequencing of COL18A1 was performed with segregation on available relatives. The study was conducted from July 4, 2013, to October 5, 2015. Data analysis was performed from May 20, 2014, to November 3, 2015. MAIN OUTCOMES AND MEASURES: Results of ophthalmic and neuroradiologic assessment and sequence analysis of COL18A1. RESULTS: Of the 12 patients (6 males; mean age at last review, 16 years [range, 2-38 years]), all had high myopia in at least 1 eye and severely reduced vision. A sibling pair had unilateral high myopia in their right eyes and near emmetropia in their left eyes from infancy. Anterior segment abnormalities included absent iris crypts, iris transillumination, lens subluxation, and cataract. Two patients with iris transillumination had glaucoma. Fundus characteristics included abnormal collapsed vitreous, macular atrophy, and a tesselated fundus. Five patients had previous retinal detachment. Electroretinography revealed a cone-rod pattern of dysfunction in 8 patients, was severely reduced or undetectable in 2 patients, and demonstrated cone-rod dysfunction in 1 eye with undetectable responses in the other eye in 2 patients. Radiologic imaging demonstrated occipital encephalocele or meningocele in 3 patients, occipital skull defects in 4 patients, minor occipital changes in 2 patients, and no abnormalities in 2 patients. Cutaneous scalp changes were present in 5 patients. Systemic associations were identified in 8 patients, including learning difficulties, epilepsy, and congenital renal abnormalities. Biallelic mutations including 2 likely novel mutations in COL18A1, were identified in 6 families that were consistent with autosomal recessive inheritance with a single mutation identified in a family with 2 affected children. CONCLUSIONS AND RELEVANCE: This report describes new features in patients with Knobloch syndrome, including pigment dispersion syndrome and glaucoma as well as cone-rod dysfunction on electroretinography. Two patients had normal neuroradiologic findings, emphasizing that some affected individuals have isolated ocular disease. Awareness of the ocular phenotype may aid early diagnosis, appropriate genetic counseling, and monitoring for potential complications.
Keywords: Adolescent; Adult; Child; Child, Preschool; Collagen Type VIII; Collagen Type XVIII; DNA Mutational Analysis; Electroretinography; Encephalocele; Exfoliation Syndrome; Exons; Female; Glaucoma, Open-Angle; Humans; Magnetic Resonance Imaging; Male; Molecular Biology; Mutation; Myopia, Degenerative; Pedigree; Photoreceptor Cells, Vertebrate; Polymerase Chain Reaction; Retinal Degeneration; Retinal Detachment; Vision Disorders; Young Adult

Monoallelic and Biallelic Variants in EMC1 Identified in Individuals with Global Developmental Delay, Hypotonia, Scoliosis, and Cerebellar Atrophy. - Harel, Tamar; Yesil, Gozde; Bayram, Yavuz; Coban-Akdemir, Zeynep; Charng, Wu-Lin; Karaca, Ender; Al Asmari, Ali; Eldomery, Mohammad K; Hunter, Jill V; Jhangiani, Shalini N; Rosenfeld, Jill A; Pehlivan, Davut; et al. (Am J Hum Genet, 2016)
The paradigm of a single gene associated with one specific phenotype and mode of inheritance has been repeatedly challenged. Genotype-phenotype correlations can often be traced to different mutation types, localization of the variants in distinct protein domains, or the trigger of or escape from nonsense-mediated decay. Using whole-exome sequencing, we identified homozygous variants in EMC1 that segregated with a phenotype of developmental delay, hypotonia, scoliosis, and cerebellar atrophy in three families. In addition, a de novo heterozygous EMC1 variant was seen in an individual with a similar clinical and MRI imaging phenotype. EMC1 encodes a member of the endoplasmic reticulum (ER)-membrane protein complex (EMC), an evolutionarily conserved complex that has been proposed to have multiple roles in ER-associated degradation, ER-mitochondria tethering, and proper assembly of multi-pass transmembrane proteins. Perturbations of protein folding and organelle crosstalk have been implicated in neurodegenerative processes including cerebellar atrophy. We propose EMC1 as a gene in which either biallelic or monoallelic variants might lead to a syndrome including intellectual disability and preferential degeneration of the cerebellum.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Atrophy; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Female; Genetic Association Studies; Genetic Variation; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Membrane Proteins; Molecular Sequence Data; Muscle Hypotonia; Mutation; Pedigree; Protein Folding; Proteins; Scoliosis

Nonrecurrent PMP22-RAI1 contiguous gene deletions arise from replication-based mechanisms and result in Smith-Magenis syndrome with evident peripheral neuropathy. - Yuan, Bo; Neira, Juanita; Gu, Shen; Harel, Tamar; Liu, Pengfei; Briceño, Ignacio; Elsea, Sarah H; Gómez, Alberto; Potocki, Lorraine; Lupski, James R (Hum Genet, 2016)
Hereditary neuropathy with liability to pressure palsies (HNPP) and Smith-Magenis syndrome (SMS) are genomic disorders associated with deletion copy number variants involving chromosome 17p12 and 17p11.2, respectively. Nonallelic homologous recombination (NAHR)-mediated recurrent deletions are responsible for the majority of HNPP and SMS cases; the rearrangement products encompass the key dosage-sensitive genes PMP22 and RAI1, respectively, and result in haploinsufficiency for these genes. Less frequently, nonrecurrent genomic rearrangements occur at this locus. Contiguous gene duplications encompassing both PMP22 and RAI1, i.e., PMP22-RAI1 duplications, have been investigated, and replication-based mechanisms rather than NAHR have been proposed for these rearrangements. In the current study, we report molecular and clinical characterizations of six subjects with the reciprocal phenomenon of deletions spanning both genes, i.e., PMP22-RAI1 deletions. Molecular studies utilizing high-resolution array comparative genomic hybridization and breakpoint junction sequencing identified mutational signatures that were suggestive of replication-based mechanisms. Systematic clinical studies revealed features consistent with SMS, including features of intellectual disability, speech and gross motor delays, behavioral problems and ocular abnormalities. Five out of six subjects presented clinical signs and/or objective electrophysiologic studies of peripheral neuropathy. Clinical profiling may improve the clinical management of this unique group of subjects, as the peripheral neuropathy can be more severe or of earlier onset as compared to SMS patients having the common recurrent deletion. Moreover, the current study, in combination with the previous report of PMP22-RAI1 duplications, contributes to the understanding of rare complex phenotypes involving multiple dosage-sensitive genes from a genetic mechanistic standpoint.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromosomes, Human, Pair 17; DNA Copy Number Variations; DNA Replication; Female; Gene Deletion; Haploinsufficiency; Homologous Recombination; Humans; Intellectual Disability; Male; Mutation; Myelin Proteins; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors

Novel patient-derived xenograft and cell line models for therapeutic testing of pediatric liver cancer. - Bissig-Choisat, Beatrice; Kettlun-Leyton, Claudia; Legras, Xavier D; Zorman, Barry; Barzi, Mercedes; Chen, Leon L; Amin, Mansi D; Huang, Yung-Hsin; Pautler, Robia G; Hampton, Oliver A; Prakash, Masand M; Yang, Diane; et al. (J Hepatol, 2016)
BACKGROUND & AIMS: Pediatric liver cancer is a rare but serious disease whose incidence is rising, and for which the therapeutic options are limited. Development of more targeted, less toxic therapies is hindered by the lack of an experimental animal model that captures the heterogeneity and metastatic capability of these tumors. METHODS: Here we established an orthotopic engraftment technique to model a series of patient-derived tumor xenograft (PDTX) from pediatric liver cancers of all major histologic subtypes: hepatoblastoma, hepatocellular cancer and hepatocellular malignant neoplasm. We utilized standard (immuno) staining methods for histological characterization, RNA sequencing for gene expression profiling and genome sequencing for identification of druggable targets. We also adapted stem cell culturing techniques to derive two new pediatric cancer cell lines from the xenografted mice. RESULTS: The patient-derived tumor xenografts recapitulated the histologic, genetic, and biological characteristics-including the metastatic behavior-of the corresponding primary tumors. Furthermore, the gene expression profiles of the two new liver cancer cell lines closely resemble those of the primary tumors. Targeted therapy of PDTX from an aggressive hepatocellular malignant neoplasm with the MEK1 inhibitor trametinib and pan-class I PI3 kinase inhibitor NVP-BKM120 resulted in significant growth inhibition, thus confirming this PDTX model as a valuable tool to study tumor biology and patient-specific therapeutic responses. CONCLUSIONS: The novel metastatic xenograft model and the isogenic xenograft-derived cell lines described in this study provide reliable tools for developing mutation- and patient-specific therapies for pediatric liver cancer. LAY SUMMARY: Pediatric liver cancer is a rare but serious disease and no experimental animal model currently captures the complexity and metastatic capability of these tumors. We have established a novel animal model using human tumor tissue that recapitulates the genetic and biological characteristics of this cancer. We demonstrate that our patient-derived animal model, as well as two new cell lines, are useful tools for experimental therapies.
Keywords: Animals; Carcinoma, Hepatocellular; Cell Line, Tumor; Child; Disease Models, Animal; Heterografts; Humans; Liver Neoplasms; Mice; Neoplasm Transplantation; Xenograft Model Antitumor Assays

An open access pilot freely sharing cancer genomic data from participants in Texas. - Becnel, Lauren B; Pereira, Stacey; Drummond, Jennifer A; Gingras, Marie-Claude; Covington, Kyle R; Kovar, Christie L; Doddapaneni, Harsha Vardhan; Hu, Jianhong; Muzny, Donna; McGuire, Amy L; Wheeler, David A; Gibbs, Richard A (Sci Data, 2016)
Genomic data sharing in cancer has been restricted to aggregate or controlled-access initiatives to protect the privacy of research participants. By limiting access to these data, it has been argued that the autonomy of individuals who decide to participate in data sharing efforts has been superseded and the utility of the data as research and educational tools reduced. In a pilot Open Access (OA) project from the CPRIT-funded Texas Cancer Research Biobank, many Texas cancer patients were willing to openly share genomic data from tumor and normal matched pair specimens. For the first time, genetic data from 7 human cancer cases with matched normal are freely available without requirement for data use agreements nor any major restriction except that end users cannot attempt to re-identify the participants (http://txcrb.org/open.html).
Keywords: Access to Information; Biological Specimen Banks; Databases, Genetic; DNA, Neoplasm; Genome, Human; Humans; Information Dissemination; Pancreatic Neoplasms; Texas

Phased diploid genome assembly with single-molecule real-time sequencing. - Chin, Chen-Shan; Peluso, Paul; Sedlazeck, Fritz J; Nattestad, Maria; Concepcion, Gregory T; Clum, Alicia; Dunn, Christopher; O'Malley, Ronan; Figueroa-Balderas, Rosa; Morales-Cruz, Abraham; Cramer, Grant R; Delledonne, Massimo; et al. (Nat Methods, 2016)
While genome assembly projects have been successful in many haploid and inbred species, the assembly of noninbred or rearranged heterozygous genomes remains a major challenge. To address this challenge, we introduce the open-source FALCON and FALCON-Unzip algorithms (https://github.com/PacificBiosciences/FALCON/) to assemble long-read sequencing data into highly accurate, contiguous, and correctly phased diploid genomes. We generate new reference sequences for heterozygous samples including an F1 hybrid of Arabidopsis thaliana, the widely cultivated Vitis vinifera cv. Cabernet Sauvignon, and the coral fungus Clavicorona pyxidata, samples that have challenged short-read assembly approaches. The FALCON-based assemblies are substantially more contiguous and complete than alternate short- or long-read approaches. The phased diploid assembly enabled the study of haplotype structure and heterozygosities between homologous chromosomes, including the identification of widespread heterozygous structural variation within coding sequences.
Keywords: Algorithms; Arabidopsis; Basidiomycota; Diploidy; DNA, Fungal; DNA, Plant; Genome, Fungal; Genome, Plant; Genomics; Haplotypes; Heterozygote; Humans; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Vitis

Phenotypic expansion of TBX4 mutations to include acinar dysplasia of the lungs. - Szafranski, Przemyslaw; Coban-Akdemir, Zeynep H; Rupps, Rosemarie; Grazioli, Serge; Wensley, David; Jhangiani, Shalini N; Popek, Edwina; Lee, Anna F; Lupski, James R; Boerkoel, Cornelius F; Stankiewicz, Paweł (Am J Med Genet A, 2016)
Mutations in the T-box transcription factor TBX4 gene have been reported in patients with Ischiocoxopodopatellar syndrome (MIM# 147891) and childhood-onset pulmonary arterial hypertension. Whole exome sequencing of DNA from a 1 day old deceased newborn, with severe diffuse developmental lung disorder exhibiting features of acinar dysplasia, and her unaffected parents identified a de novo TBX4 missense mutation p.E86Q (c.256G>C) in the DNA-binding T-box domain. We propose phenotypic expansion of the TBX4-related clinical disease spectrum to include acinar dysplasia of the lungs. The reported mutation is the first identified genetic variant causative for acinar dysplasia. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; Autopsy; Chromosomes, Human, Pair 16; DNA Copy Number Variations; DNA Mutational Analysis; Fatal Outcome; Female; Genetic Association Studies; Genotype; Heterozygote; Humans; Infant, Newborn; Karyotype; Lung; Mutation; Pedigree; Phenotype; Radiography, Thoracic; T-Box Domain Proteins

Postmortem genetic screening for the identification, verification, and reporting of genetic variants contributing to the sudden death of the young. - Methner, D Nicole R; Steven E Scherer; Welch, Katherine; Walkiewicz, Magdalena; Eng, Christine M; Belmont, John W; Powell, Mark C; Korchina, Viktoriya; Harshavardhan Doddapaneni; Donna M Muzny; Richard A Gibbs; Wolf, Dwayne A; et al. (Genome Res, 2016)
Each year in the United States, thousands of cases of sudden and unexpected deaths of infants, children, and young adults are assigned an undetermined cause of death after postmortem investigation and autopsy. Heritable genetic variants have been suggested as the cause of up to a third of sudden death (SD) cases. Elucidation of the genetic variants involved in SD cases is important to not only help establish cause and manner of death of these individuals, but to also aid in determining whether familial genetic testing should be considered. Previously, these types of postmortem screenings have not been a feasible option for most county medical examiners' and coroners' offices. We sequenced full exons of 64 genes associated with SD in the largest known cohort (351) of infant and young SD decedents using massively parallel sequencing at <$600 per sample. Genetic variants were assessed through literature review and clinical evaluation by a multidisciplinary consortium of experts. Thirteen individuals (3.7%), eight infants (2.8% of those <1 yr of age) and five children/young adults (7.0% of those >1 yr of age), were found to have a reportable genetic variant contributing to SD. These percentages represent an estimate lower than those previously reported. Overall yields and results likely vary between studies due to differences in evaluation techniques and reporting. Additionally, we recommend ongoing assessment of data, including nonreported novel variants, as technology and literature continually advance. This study demonstrates a strategy to implement molecular autopsies in medicolegal investigations of young SD decedents.
Keywords: Adolescent; Adult; Autopsy; Cardiomyopathies; Child; Child, Preschool; Death, Sudden; Diagnosis; Female; Genetic Testing; Genetic Variation; Humans; Infant; Infant, Newborn; Male; United States; Young Adult

Predictive Value of Antiviral Effects in the Development of Hepatocellular Carcinoma in the General Korean Population with Chronic Hepatitis B. - Shim, Jae-Jun; Oh, In Hwan; Kim, Sang Bae; Kim, Jung Wook; Lee, Chang Kyun; Jang, Jae Young; Lee, Ju-Seog; Kim, Byung-Ho (Gut Liver, 2016)
BACKGROUND/AIMS: The benefit of oral antiviral therapy in preventing hepatocellular carcinoma (HCC) in the general population is not well understood. We used a novel prediction method to estimate the risk of HCC in the Korean population based on various treatment guidelines. METHODS: The 5-year risk of HCC following antiviral therapy was calculated using an HCC risk prediction model. A virtual cohort that represented Koreans (>40 years old) with chronic hepatitis B virus (HBV) infection was established using the fifth National Health and Nutrition Examination Survey. The antiviral indications tested were the Korean National Health Insurance (NHI) and European Association for the Study of the Liver (EASL) guidelines as well as a new extended indication (serum HBV DNA >2,000 IU/mL regardless of serum aminotransferase level). RESULTS: A total of 993,872 subjects were infected with HBV in the general Korean population. Over a 5-year period, 2,725 HCC cases were predicted per 100,000 persons (0.55%/yr). When the cohort was treated based on the Korean NHI, the EASL, and the newly extended indications, HCC risks decreased to 2,531 (-7.1%), 2,089 (-23.3%), and 1,122 (-58.8%) cases per 100,000 persons, respectively (p<0.0001). CONCLUSIONS: Simulated risk prediction suggests that extending of oral antiviral indication may reduce the HCC risk in the general population.
Keywords: Adult; Antiviral Agents; Carcinoma, Hepatocellular; DNA, Viral; Female; Hepatitis B virus; Hepatitis B, Chronic; Humans; Liver Neoplasms; Male; Middle Aged; Nutrition Surveys; Predictive Value of Tests; Republic of Korea; Risk Assessment; Risk Factors; Transaminases

Rare Functional Variant in TM2D3 is Associated with Late-Onset Alzheimer's Disease. - Jakobsdottir, Johanna; van der Lee, Sven J; Bis, Joshua C; Chouraki, Vincent; Li-Kroeger, David; Yamamoto, Shinya; Grove, Megan L; Naj, Adam; Vronskaya, Maria; Salazar, Jose L; DeStefano, Anita L; Brody, Jennifer A; et al. (PLoS Genet, 2016)
We performed an exome-wide association analysis in 1393 late-onset Alzheimer's disease (LOAD) cases and 8141 controls from the CHARGE consortium. We found that a rare variant (P155L) in TM2D3 was enriched in Icelanders (~0.5% versus <0.05% in other European populations). In 433 LOAD cases and 3903 controls from the Icelandic AGES sub-study, P155L was associated with increased risk and earlier onset of LOAD [odds ratio (95% CI) = 7.5 (3.5-15.9), p = 6.6x10-9]. Mutation in the Drosophila TM2D3 homolog, almondex, causes a phenotype similar to loss of Notch/Presenilin signaling. Human TM2D3 is capable of rescuing these phenotypes, but this activity is abolished by P155L, establishing it as a functionally damaging allele. Our results establish a rare TM2D3 variant in association with LOAD susceptibility, and together with prior work suggests possible links to the β-amyloid cascade.
Keywords: Age of Onset; Aged; Alleles; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Apolipoproteins E; Drosophila melanogaster; Drosophila Proteins; Exome; Female; Genome-Wide Association Study; Genomics; Humans; Iceland; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Mutation; Phenotype; Receptors, Notch; Tropomyosin; White People

Recurrent De Novo and Biallelic Variation of ATAD3A, Encoding a Mitochondrial Membrane Protein, Results in Distinct Neurological Syndromes. - Harel, Tamar; Yoon, Wan Hee; Garone, Caterina; Gu, Shen; Coban-Akdemir, Zeynep; Eldomery, Mohammad K; Posey, Jennifer E; Jhangiani, Shalini N; Rosenfeld, Jill A; Cho, Megan T; Fox, Stephanie; Withers, Marjorie; et al. (Am J Hum Genet, 2016)
ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane protein implicated in mitochondrial dynamics, nucleoid organization, protein translation, cell growth, and cholesterol metabolism. We identified a recurrent de novo ATAD3A c.1582C>T (p.Arg528Trp) variant by whole-exome sequencing (WES) in five unrelated individuals with a core phenotype of global developmental delay, hypotonia, optic atrophy, axonal neuropathy, and hypertrophic cardiomyopathy. We also describe two families with biallelic variants in ATAD3A, including a homozygous variant in two siblings, and biallelic ATAD3A deletions mediated by nonallelic homologous recombination (NAHR) between ATAD3A and gene family members ATAD3B and ATAD3C. Tissue-specific overexpression of bor, the Drosophila mutation homologous to the human c.1582C>T (p.Arg528Trp) variant, resulted in a dramatic decrease in mitochondrial content, aberrant mitochondrial morphology, and increased autophagy. Homozygous null bor larvae showed a significant decrease of mitochondria, while overexpression of bor resulted in larger, elongated mitochondria. Finally, fibroblasts of an affected individual exhibited increased mitophagy. We conclude that the p.Arg528Trp variant functions through a dominant-negative mechanism that results in small mitochondria that trigger mitophagy, resulting in a reduction in mitochondrial content. ATAD3A variation represents an additional link between mitochondrial dynamics and recognizable neurological syndromes, as seen with MFN2, OPA1, DNM1L, and STAT2 mutations.
Keywords: Adenosine Triphosphatases; Adult; Alleles; Animals; ATPases Associated with Diverse Cellular Activities; Axons; Cardiomyopathies; Child; Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Drosophila melanogaster; Female; Fibroblasts; Homozygote; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Muscle Hypotonia; Muscles; Mutation; Nervous System Diseases; Neurons; Optic Atrophy; Phenotype; Polymorphism, Single Nucleotide; Syndrome; Young Adult

The role of combined SNV and CNV burden in patients with distal symmetric polyneuropathy. - Pehlivan, Davut; Beck, Christine R; Okamoto, Yuji; Harel, Tamar; Akdemir, Zeynep H C; Jhangiani, Shalini N; Withers, Marjorie A; Goksungur, Meryem Tuba; Carvalho, Claudia M B; Czesnik, Dirk; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; et al. (Genet Med, 2016)
PURPOSE: Charcot-Marie-Tooth (CMT) disease is a heterogeneous group of genetic disorders of the peripheral nervous system. Copy-number variants (CNVs) contribute significantly to CMT, as duplication of PMP22 underlies the majority of CMT1 cases. We hypothesized that CNVs and/or single-nucleotide variants (SNVs) might exist in patients with CMT with an unknown molecular genetic etiology. METHODS: Two hundred patients with CMT, negative for both SNV mutations in several CMT genes and for CNVs involving PMP22, were screened for CNVs by high-resolution oligonucleotide array comparative genomic hybridization. Whole-exome sequencing was conducted on individuals with rare, potentially pathogenic CNVs. RESULTS: Putatively causative CNVs were identified in five subjects (~2.5%); four of the five map to known neuropathy genes. Breakpoint sequencing revealed Alu-Alu-mediated junctions as a predominant contributor. Exome sequencing identified MFN2 SNVs in two of the individuals. CONCLUSION: Neuropathy-associated CNV outside of the PMP22 locus is rare in CMT. Nevertheless, there is potential clinical utility in testing for CNVs and exome sequencing in CMT cases negative for the CMT1A duplication. These findings suggest that complex phenotypes including neuropathy can potentially be caused by a combination of SNVs and CNVs affecting more than one disease-associated locus and contributing to a mutational burden.Genet Med 18 5, 443-451.
Keywords: Adult; Age of Onset; Charcot-Marie-Tooth Disease; Child, Preschool; Comparative Genomic Hybridization; DNA Copy Number Variations; Exome; Female; Genetic Predisposition to Disease; GTP Phosphohydrolases; High-Throughput Nucleotide Sequencing; Humans; Male; Mitochondrial Proteins; Motor Neurons; Myelin P0 Protein; Myelin Proteins; Neural Conduction; Polymorphism, Single Nucleotide; Polyneuropathies

Structural and transcriptomic response to antenatal corticosteroids in an Erk3-null mouse model of respiratory distress. - Pew, Braden K; Harris, R Alan; Sbrana, Elena; Guaman, Milenka Cuevas; Shope, Cynthia; Chen, Rui; Meloche, Sylvain; Aagaard, Kjersti (Am J Obstet Gynecol, 2016)
BACKGROUND: Neonatal respiratory distress syndrome in preterm infants is a leading cause of neonatal death. Pulmonary insufficiency-related infant mortality rates have improved with antenatal glucocorticoid treatment and neonatal surfactant replacement. However, the mechanism of glucocorticoid-promoted fetal lung maturation is not understood fully, despite decades of clinical use. We previously have shown that genetic deletion of Erk3 in mice results in growth restriction, cyanosis, and early neonatal lethality because of pulmonary immaturity and respiratory distress. Recently, we demonstrated that the addition of postnatal surfactant administration to antenatal dexamethasone treatment resulted in enhanced survival of neonatal Erk3-null mice. OBJECTIVE: To better understand the molecular underpinnings of corticosteroid-mediated lung maturation, we used high-throughput transcriptomic and high-resolution morphologic analysis of the murine fetal lung. We sought to examine the alterations in fetal lung structure and function that are associated with neonatal respiratory distress and antenatal glucocorticoid treatment. STUDY DESIGN: Dexamethasone (0.4 mg/kg) or saline solution was administered to pregnant dams on embryonic days 16.5 and 17.5. Fetal lungs were collected and analyzed by microCT and RNA-seq for differential gene expression and pathway interactions with genotype and treatment. Results from transcriptomic analysis guided further investigation of candidate genes with the use of immunostaining in murine and human fetal lung tissue. RESULTS: Erk3(-/-) mice exhibited atelectasis with decreased overall porosity and saccular space relative to wild type, which was ameliorated by glucocorticoid treatment. Of 596 differentially expressed genes (q < 0.05) that were detected by RNA-seq, pathway analysis revealed 36 genes (q < 0.05) interacting with dexamethasone, several with roles in lung development, which included corticotropin-releasing hormone and surfactant protein B. Corticotropin-releasing hormone protein was detected in wild-type and Erk3(-/-) lungs at E14.5, with significantly temporally altered expression through embryonic day 18.5. Antenatal dexamethasone attenuated corticotropin-releasing hormone at embryonic day 18.5 in both wild-type and Erk3(-/-) lungs (0.56-fold and 0.67-fold; P < .001). Wild type mice responded to glucocorticoid administration with increased pulmonary surfactant protein B (P = .003). In contrast, dexamethasone treatment in Erk3(-/-) mice resulted in decreased surfactant protein B (P = .012). In human validation studies, we confirmed that corticotropin-releasing hormone protein is present in the fetal lung at 18 weeks of gestation and increases in expression with progression towards viability (22 weeks of gestation; P < .01). CONCLUSION: Characterization of whole transcriptome gene expression revealed glucocorticoid-mediated regulation of corticotropin-releasing hormone and surfactant protein B via Erk3-independent and -dependent mechanisms, respectively. We demonstrated for the first time the expression and temporal regulation of corticotropin-releasing hormone protein in midtrimester human fetal lung. This unique model allows the effects of corticosteroids on fetal pulmonary morphologic condition to be distinguished from functional gene pathway regulation. These findings implicate Erk3 as a potentially important molecular mediator of antenatal glucocorticoid action in promoting surfactant protein production in the preterm neonatal lung and expanding our understanding of key mechanisms of clinical therapy to improve neonatal survival.
Keywords: Animals; Animals, Newborn; Corticotropin-Releasing Hormone; Dexamethasone; Disease Models, Animal; Female; Glucocorticoids; Insulin-Like Growth Factor II; Lung; Mice, Knockout; Mitogen-Activated Protein Kinase 6; Pregnancy; Pulmonary Surfactant-Associated Protein D; Respiratory Distress Syndrome, Newborn; X-Ray Microtomography

A visual and curatorial approach to clinical variant prioritization and disease gene discovery in genome-wide diagnostics. - James, Regis A; Campbell, Ian M; Chen, Edward S; Boone, Philip M; Rao, Mitchell A; Bainbridge, Matthew N; Lupski, James R; Yang, Yaping; Eng, Christine M; Posey, Jennifer E; Shaw, Chad A (Genome Med, 2016)
BACKGROUND: Genome-wide data are increasingly important in the clinical evaluation of human disease. However, the large number of variants observed in individual patients challenges the efficiency and accuracy of diagnostic review. Recent work has shown that systematic integration of clinical phenotype data with genotype information can improve diagnostic workflows and prioritization of filtered rare variants. We have developed visually interactive, analytically transparent analysis software that leverages existing disease catalogs, such as the Online Mendelian Inheritance in Man database (OMIM) and the Human Phenotype Ontology (HPO), to integrate patient phenotype and variant data into ranked diagnostic alternatives. METHODS: Our tool, "OMIM Explorer" ( http://www.omimexplorer.com ), extends the biomedical application of semantic similarity methods beyond those reported in previous studies. The tool also provides a simple interface for translating free-text clinical notes into HPO terms, enabling clinical providers and geneticists to contribute phenotypes to the diagnostic process. The visual approach uses semantic similarity with multidimensional scaling to collapse high-dimensional phenotype and genotype data from an individual into a graphical format that contextualizes the patient within a low-dimensional disease map. The map proposes a differential diagnosis and algorithmically suggests potential alternatives for phenotype queries--in essence, generating a computationally assisted differential diagnosis informed by the individual's personal genome. Visual interactivity allows the user to filter and update variant rankings by interacting with intermediate results. The tool also implements an adaptive approach for disease gene discovery based on patient phenotypes. RESULTS: We retrospectively analyzed pilot cohort data from the Baylor Miraca Genetics Laboratory, demonstrating performance of the tool and workflow in the re-analysis of clinical exomes. Our tool assigned to clinically reported variants a median rank of 2, placing causal variants in the top 1 % of filtered candidates across the 47 cohort cases with reported molecular diagnoses of exome variants in OMIM Morbidmap genes. Our tool outperformed Phen-Gen, eXtasy, PhenIX, PHIVE, and hiPHIVE in the prioritization of these clinically reported variants. CONCLUSIONS: Our integrative paradigm can improve efficiency and, potentially, the quality of genomic medicine by more effectively utilizing available phenotype information, catalog data, and genomic knowledge.
Keywords: Computational Biology; Diagnosis, Differential; Disease; Genetic Variation; Genome-Wide Association Study; Humans; Phenotype; Pilot Projects; Retrospective Studies; Software

Whole exome sequencing identifies the first STRADA point mutation in a patient with polyhydramnios, megalencephaly, and symptomatic epilepsy syndrome (PMSE). - Bi, Weimin; Glass, Ian A; Donna M Muzny; Richard A Gibbs; Eng, Christine M; Yang, Yaping; Sun, Angela (Am J Med Genet A, 2016)
Polyhydramnios, megalencephaly, and symptomatic epilepsy syndrome (PMSE) is an ultra rare neurodevelopmental disorder characterized by severe, infantile-onset intractable epilepsy, neurocognitive delay, macrocephaly, and craniofacial dysmorphism. The molecular diagnosis of this condition has thus far only been made in 16 Old Order Mennonite patients carrying a homozygous 7 kb founder deletion of exons 9-13 of STRADA. We performed clinical whole exome sequencing (WES) on a 4-year-old Indian male with global developmental delay, history of failure to thrive, infantile spasms, repetitive behaviors, hypotonia, low muscle mass, marked joint laxity, and dysmorphic facial features including tall forehead, long face, arched eyebrows, small chin, wide mouth, and tented upper lip. A homozygous single nucleotide duplication, c.842dupA (p.D281fs), in exon 10 of STRADA was identified. Sanger sequencing confirmed the mutation in the individual and identified both parents as carriers. In light of the molecular discoveries, the patient's clinical phenotype was considered to be a good fit for PMSE. We identified for the first time a homozygous point mutation in STRADA causing PMSE. Additional bi-allelic mutations related to PMSE thus far have not been observed in Baylor ∼6,000 consecutive clinical WES cases, supporting the rarity of this disorder. Our findings may have treatment implications for the patient since previous studies have shown rapamycin as a potential therapeutic agent for the seizures and cognitive problems in PMSE patients. © 2016 Wiley Periodicals, Inc.
Keywords: Adaptor Proteins, Vesicular Transport; Child, Preschool; DNA Mutational Analysis; Epilepsy; Exome; Facies; Genetic Association Studies; Genotype; High-Throughput Nucleotide Sequencing; Humans; Male; Megalencephaly; Pedigree; Phenotype; Physical Examination; Point Mutation; Polyhydramnios; Psychomotor Disorders; Syndrome

Whole-Exome Sequencing Identifies Loci Associated with Blood Cell Traits and Reveals a Role for Alternative GFI1B Splice Variants in Human Hematopoiesis. - Polfus, Linda M; Khajuria, Rajiv K; Schick, Ursula M; Pankratz, Nathan; Pazoki, Raha; Brody, Jennifer A; Chen, Ming-Huei; Auer, Paul L; Floyd, James S; Huang, Jie; Lange, Leslie; van Rooij, Frank J A; et al. (Am J Hum Genet, 2016)
Circulating blood cell counts and indices are important indicators of hematopoietic function and a number of clinical parameters, such as blood oxygen-carrying capacity, inflammation, and hemostasis. By performing whole-exome sequence association analyses of hematologic quantitative traits in 15,459 community-dwelling individuals, followed by in silico replication in up to 52,024 independent samples, we identified two previously undescribed coding variants associated with lower platelet count: a common missense variant in CPS1 (rs1047891, MAF = 0.33, discovery + replication p = 6.38 × 10(-10)) and a rare synonymous variant in GFI1B (rs150813342, MAF = 0.009, discovery + replication p = 1.79 × 10(-27)). By performing CRISPR/Cas9 genome editing in hematopoietic cell lines and follow-up targeted knockdown experiments in primary human hematopoietic stem and progenitor cells, we demonstrate an alternative splicing mechanism by which the GFI1B rs150813342 variant suppresses formation of a GFI1B isoform that preferentially promotes megakaryocyte differentiation and platelet production. These results demonstrate how unbiased studies of natural variation in blood cell traits can provide insight into the regulation of human hematopoiesis.
Keywords: Alternative Splicing; Blood Platelets; CRISPR-Cas Systems; DNA Mutational Analysis; Exome; Gene Editing; Genetic Loci; Hematopoiesis; Hematopoietic Stem Cells; Humans; Megakaryocytes; Platelet Count; Proto-Oncogene Proteins; Repressor Proteins

AAV8(Y733F)-mediated gene therapy in a Spata7 knockout mouse model of Leber congenital amaurosis and retinitis pigmentosa. - Zhong, H; Eblimit, A; Moayedi, Y; Boye, S L; Chiodo, V A; Chen, Y; Li, Y; Nichols, R M; Hauswirth, W W; Chen, R; Mardon, G (Gene Ther, 2015)
Loss of SPATA7 function causes the pathogenesis of Leber congenital amaurosis and retinitis pigmentosa. Spata7 knockout mice mimic human SPATA7-related retinal disease with apparent photoreceptor degeneration observed as early as postnatal day 15 (P15). To test the efficacy of adeno-associated virus (AAV)-mediated gene therapy for rescue of photoreceptor survival and function in Spata7 mutant mice, we employed the AAV8(Y733F) vector carrying hGRK1-driven full-length FLAG-tagged Spata7 cDNA to target both rod and cone photoreceptors. Following subretinal injection of this vector, FLAG-tagged SPATA7 was found to colocalize with endogenous SPATA7 in wild-type mice. In Spata7 mutant mice initially treated at P15, we observed improvement of photoresponse, photoreceptor ultrastructure and significant alleviation of photoreceptor degeneration. Furthermore, we performed treatments at P28 and P56 and found that all treatments (P15-P56) can ameliorate rod and cone loss in the long term (1 year); however, none efficiently protect photoreceptors from degeneration by 86 weeks of age as only a small amount of treated photoreceptors can survive to this time. This study demonstrates long-term improvement of photoreceptor function by AAV8(Y733F)-introduced Spata7 expression in a mouse model as potential treatment of the human disease, but also suggests that treated mutant photoreceptors still undergo progressive degeneration.
Keywords: Animals; Dependovirus; Disease Models, Animal; DNA-Binding Proteins; Genetic Therapy; Genetic Vectors; Leber Congenital Amaurosis; Mice, Inbred C57BL; Mice, Knockout; Retinal Cone Photoreceptor Cells; Retinal Rod Photoreceptor Cells; Retinitis Pigmentosa

Absence of heterozygosity due to template switching during replicative rearrangements. - Carvalho, Claudia M B; Pfundt, Rolph; King, Daniel A; Lindsay, Sarah J; Zuccherato, Luciana W; Macville, Merryn V E; Liu, Pengfei; Johnson, Diana; Stankiewicz, Pawel; Brown, Chester W; Shaw, Chad A; Hurles, Matthew E; et al. (Am J Hum Genet, 2015)
We investigated complex genomic rearrangements (CGRs) consisting of triplication copy-number variants (CNVs) that were accompanied by extended regions of copy-number-neutral absence of heterozygosity (AOH) in subjects with multiple congenital abnormalities. Molecular analyses provided observational evidence that in humans, post-zygotically generated CGRs can lead to regional uniparental disomy (UPD) due to template switches between homologs versus sister chromatids by using microhomology to prime DNA replication-a prediction of the replicative repair model, MMBIR. Our findings suggest that replication-based mechanisms might underlie the formation of diverse types of genomic alterations (CGRs and AOH) implicated in constitutional disorders.
Keywords: Base Sequence; DNA Copy Number Variations; DNA Repair; DNA Replication; Gene Rearrangement; Humans; In Situ Hybridization, Fluorescence; Loss of Heterozygosity; Models, Genetic; Molecular Sequence Data; Netherlands; Polymerase Chain Reaction; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Uniparental Disomy

Adult presentation of X-linked Conradi-Hünermann-Happle syndrome. - Posey, Jennifer E; Burrage, Lindsay C; Campeau, Philippe M; Lu, James T; Eble, Tanya N; Kratz, Lisa; Schlesinger, Alan E; Gibbs, Richard A; Lee, Brendan H; Nagamani, Sandesh C S (Am J Med Genet A, 2015)
Conradi-Hünermann-Happle syndrome, or X-linked dominant chondrodysplasia punctata type 2 (CDPX2), is a genodermatosis caused by mutations in EBP. While typically lethal in males, females with CDPX2 generally manifest by infancy or childhood with variable features including congenital ichthyosiform erythroderma, chondrodysplasia punctata, asymmetric shortening of the long bones, and cataracts. We present a 36-year-old female with short stature, rhizomelic and asymmetric limb shortening, severe scoliosis, a sectorial cataract, and no family history of CDPX2. Whole exome sequencing (WES) revealed a p.Arg63del mutation in EBP, and biochemical studies confirmed a diagnosis of CDPX2. Short stature in combination with ichthyosis or alopecia, cataracts, and limb shortening in an adult should prompt consideration of a diagnosis of CDPX2. As in many genetic syndromes, the hallmark features of CDPX2 in pediatric patients are not readily identifiable in adults. This demonstrates the utility of WES as a diagnostic tool in the evaluation of adults with genetic disorders.
Keywords: Adult; Alopecia; Base Sequence; Black or African American; Cataract; Chondrodysplasia Punctata; Dwarfism; Exome; Female; Genes, X-Linked; Humans; Molecular Sequence Data; Sequence Deletion; Steroid Isomerases

Alu-mediated diverse and complex pathogenic copy-number variants within human chromosome 17 at p13.3. - Gu, Shen; Yuan, Bo; Campbell, Ian M; Beck, Christine R; Carvalho, Claudia M B; Nagamani, Sandesh C S; Erez, Ayelet; Patel, Ankita; Bacino, Carlos A; Shaw, Chad A; Stankiewicz, Paweł; Cheung, Sau Wai; et al. (Hum Mol Genet, 2015)
Alu repetitive elements are known to be major contributors to genome instability by generating Alu-mediated copy-number variants (CNVs). Most of the reported Alu-mediated CNVs are simple deletions and duplications, and the mechanism underlying Alu-Alu-mediated rearrangement has been attributed to non-allelic homologous recombination (NAHR). Chromosome 17 at the p13.3 genomic region lacks extensive low-copy repeat architecture; however, it is highly enriched for Alu repetitive elements, with a fraction of 30% of total sequence annotated in the human reference genome, compared with the 10% genome-wide and 18% on chromosome 17. We conducted mechanistic studies of the 17p13.3 CNVs by performing high-density oligonucleotide array comparative genomic hybridization, specifically interrogating the 17p13.3 region with ∼150 bp per probe density; CNV breakpoint junctions were mapped to nucleotide resolution by polymerase chain reaction and Sanger sequencing. Studied rearrangements include 5 interstitial deletions, 14 tandem duplications, 7 terminal deletions and 13 complex genomic rearrangements (CGRs). Within the 17p13.3 region, Alu-Alu-mediated rearrangements were identified in 80% of the interstitial deletions, 46% of the tandem duplications and 50% of the CGRs, indicating that this mechanism was a major contributor for formation of breakpoint junctions. Our studies suggest that Alu repetitive elements facilitate formation of non-recurrent CNVs, CGRs and other structural aberrations of chromosome 17 at p13.3. The common observation of Alu-mediated rearrangement in CGRs and breakpoint junction sequences analysis further demonstrates that this type of mechanism is unlikely attributed to NAHR, but rather may be due to a recombination-coupled DNA replicative repair process.
Keywords: Alleles; Alu Elements; Base Sequence; Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Genome, Human; Genomic Instability; Genomics; Homologous Recombination; Humans; Male; Molecular Sequence Data; Segmental Duplications, Genomic; Sequence Deletion

Androgen receptor promotes tamoxifen agonist activity by activation of EGFR in ERα-positive breast cancer. - Ciupek, Andrew; Rechoum, Yassine; Gu, Guowei; Gelsomino, Luca; Beyer, Amanda R; Brusco, Lauren; Covington, Kyle R; Tsimelzon, Anna; Fuqua, Suzanne A W (Breast Cancer Res Treat, 2015)
Tamoxifen (Tam) resistance represents a significant clinical problem in estrogen receptor (ER) α-positive breast cancer. We previously showed that decreased expression of Rho guanine nucleotide dissociation inhibitor (Rho GDI) α, a negative regulator of the Rho GTPase pathway, is associated with Tam resistance. We now discover that androgen receptor (AR) is overexpressed in cells with decreased Rho GDIα and seek to determine AR's contribution to resistance. We engineered ERα-positive cell lines with stable knockdown (KD) of Rho GDIα (KD cells). Resistance mechanisms were examined using microarray profiling, protein-interaction studies, growth and reporter gene assays, and Western blot analysis combined with a specific AR antagonist and other signaling inhibitors. Tam-resistant tumors and cell lines with low Rho GDIα levels exhibited upregulated AR expression. Microarray of Rho GDIα KD cells indicated that activation of EGFR and ERα was associated with Tam treatment. When AR levels were elevated, interaction between AR and EGFR was detected. Constitutive and Tam-induced phosphorylation of EGFR and ERK1/2 was blocked by the AR antagonist Enzalutamide, suggesting that AR-mediated EGFR activation was a mechanism of resistance in these cells. Constitutive ERα phosphorylation and transcriptional activity was inhibited by Enzalutamide and the EGFR inhibitor gefitinib, demonstrating that AR-mediated EGFR signaling activated ERα. Tam exhibited agonist activity in AR overexpressing cells, stimulating ERα transcriptional activity and proliferation, which was blocked by Enzalutamide and gefitinib. We describe a novel model of AR-mediated Tam resistance through activation of EGFR signaling leading to ER activation in ERα-positive cells with low expression of Rho GDIα.
Keywords: Antineoplastic Agents, Hormonal; Breast Neoplasms; Cell Line, Tumor; Cell Proliferation; Drug Resistance, Neoplasm; ErbB Receptors; Estrogen Receptor alpha; Female; Gene Expression; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Humans; MAP Kinase Signaling System; Protein Binding; Receptors, Androgen; rho Guanine Nucleotide Dissociation Inhibitor alpha; Tamoxifen; Transcriptional Activation

Apparent underdiagnosis of Cerebrotendinous Xanthomatosis revealed by analysis of ~60,000 human exomes. - Appadurai, Vivek; DeBarber, Andrea; Chiang, Pei-Wen; Patel, Shailendra B; Steiner, Robert D; Tyler, Charles; Bonnen, Penelope E (Mol Genet Metab, 2015)
Cerebrotendinous Xanthomatosis (CTX) is a treatable inborn error of metabolism caused by recessive variants in CYP27A1. Clinical presentation varies, but typically includes infant-onset chronic diarrhea, juvenile-onset bilateral cataracts, and later-onset tendinous xanthomas and progressive neurological dysfunction. CYP27A1 plays an essential role in side-chain oxidation of cholesterol necessary for the synthesis of the bile acid, chenodeoxycholic acid, and perturbations in this gene that reduce enzyme activity result in elevations of cholestanol. It is commonly held that CTX is exceedingly rare, but epidemiological studies are lacking. In order to provide an accurate incidence estimate of CTX, we studied the ExAC cohort of ~60,000 unrelated adults from global populations to determine the allele frequency of the 57 variants in CYP27A1 reported pathogenic for CTX. In addition, we conducted bioinformatics analyses on these CTX-causing variants and determined a bioinformatics profile to predict variants that may be pathogenic but have not yet been reported in the CTX patient literature. An additional 29 variants were identified that met bioinformatics criteria for being potentially pathogenic. Incidence was estimated based allele frequencies of pathogenic CTX variants plus those determined to be potentially pathogenic. One variant, p.P384L, previously reported in three unrelated CTX families had an allele frequency ≥ 1% in European, Latino and Asian populations. Three additional mutations had a frequency of ≥ 0.1% in Asian populations. CTX disease incidence was calculated excluding the high frequency p.P384L and separately using a genetic paradigm where this high frequency variant only causes classic CTX when paired in trans with a null variant. These calculations place CTX incidence ranging from 1:134,970 to 1:461,358 in Europeans, 1:263,222 to 1:468,624 in Africans, 1:71,677 to 1:148,914 in Americans, 1:64,267 to 1:64,712 in East Asians and 1:36,072 to 1:75,601 in South Asians. This work indicates CTX is under-diagnosed and improved patient screening is needed as early intervention prevents disease progression.
Keywords: Africa; Alleles; Americas; Asia; Cataract; Chenodeoxycholic Acid; Cholestanetriol 26-Monooxygenase; Cholestanol; Cholesterol; Chronic Disease; Computational Biology; Databases, Genetic; Diarrhea; Europe; Exome; Gene Frequency; Genes, Recessive; Humans; Incidence; Mutation; Xanthomatosis; Xanthomatosis, Cerebrotendinous

Assessing structural variation in a personal genome-towards a human reference diploid genome. - English, Adam C; Salerno, William J; Hampton, Oliver A; Gonzaga-Jauregui, Claudia; Ambreth, Shruthi; Ritter, Deborah I; Beck, Christine R; Davis, Caleb F; Dahdouli, Mahmoud; Ma, Singer; Carroll, Andrew; Veeraraghavan, Narayanan; et al. (BMC Genomics, 2015)
BACKGROUND: Characterizing large genomic variants is essential to expanding the research and clinical applications of genome sequencing. While multiple data types and methods are available to detect these structural variants (SVs), they remain less characterized than smaller variants because of SV diversity, complexity, and size. These challenges are exacerbated by the experimental and computational demands of SV analysis. Here, we characterize the SV content of a personal genome with Parliament, a publicly available consensus SV-calling infrastructure that merges multiple data types and SV detection methods. RESULTS: We demonstrate Parliament's efficacy via integrated analyses of data from whole-genome array comparative genomic hybridization, short-read next-generation sequencing, long-read (Pacific BioSciences RSII), long-insert (Illumina Nextera), and whole-genome architecture (BioNano Irys) data from the personal genome of a single subject (HS1011). From this genome, Parliament identified 31,007 genomic loci between 100 bp and 1 Mbp that are inconsistent with the hg19 reference assembly. Of these loci, 9,777 are supported as putative SVs by hybrid local assembly, long-read PacBio data, or multi-source heuristics. These SVs span 59 Mbp of the reference genome (1.8%) and include 3,801 events identified only with long-read data. The HS1011 data and complete Parliament infrastructure, including a BAM-to-SV workflow, are available on the cloud-based service DNAnexus. CONCLUSIONS: HS1011 SV analysis reveals the limits and advantages of multiple sequencing technologies, specifically the impact of long-read SV discovery. With the full Parliament infrastructure, the HS1011 data constitute a public resource for novel SV discovery, software calibration, and personal genome structural variation analysis.
Keywords: Computational Biology; Databases, Genetic; Diploidy; Genome, Human; Genomic Structural Variation; Humans; Sequence Analysis, DNA; Software

Clinical, morphological, biochemical, imaging and outcome parameters in 21 individuals with mitochondrial maintenance defect related to FBXL4 mutations. - Huemer, Martina; Karall, Daniela; Schossig, Anna; Abdenur, Jose E; Al Jasmi, Fatma; Biagosch, Caroline; Distelmaier, Felix; Freisinger, Peter; Graham, Brett H; Haack, Tobias B; Hauser, Natalie; Hertecant, Jozef; et al. (J Inherit Metab Dis, 2015)
FBXL4 deficiency is a recently described disorder of mitochondrial maintenance associated with a loss of mitochondrial DNA in cells. To date, the genetic diagnosis of FBXL4 deficiency has been established in 28 individuals. This paper retrospectively reviews proxy-reported clinical and biochemical findings and evaluates brain imaging, morphological and genetic data in 21 of those patients. Neonatal/early-onset severe lactic acidosis, muscular hypotonia, feeding problems and failure to thrive is the characteristic pattern at first presentation. Facial dysmorphic features are present in 67% of cases. Seven children died (mean age 37 months); 11 children were alive (mean age at follow-up 46 months), three children were lost to follow-up. All survivors developed severe psychomotor retardation. Brain imaging was non-specific in neonates but a later-onset, rapidly progressive brain atrophy was noted. Elevated blood lactate and metabolic acidosis were observed in all individuals; creatine kinase was elevated in 45% of measurements. Diagnostic workup in patient tissues and cells revealed a severe combined respiratory chain defect with a general decrease of enzymes associated with mitochondrial energy metabolism and a relative depletion of mitochondrial DNA content. Mutations were detected throughout the FBXL4 gene albeit with no clear delineation of a genotype-phenotype correlation. Treatment with "mitochondrial medications" did not prove effective. In conclusion, a clinical pattern of early-onset encephalopathy, persistent lactic acidosis, profound muscular hypotonia and typical facial dysmorphism should prompt initiation of molecular genetic analysis of FBXL4. Establishment of the diagnosis permits genetic counselling, prevents patients undergoing unhelpful diagnostic procedures and allows for accurate prognosis.
Keywords: Acidosis, Lactic; Child; Child, Preschool; Disease Progression; F-Box Proteins; Facial Asymmetry; Family; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Male; Mitochondrial Diseases; Muscle Hypotonia; Mutation; Neuroimaging; Prognosis; Retrospective Studies; Ubiquitin-Protein Ligases

Cognitive phenotypes and genomic copy number variations. - Lupski, James R (JAMA, 2015)
Keywords: DNA Copy Number Variations; Female; Heterozygote; Humans; Intellectual Disability; Male; Mental Disorders

Comprehensive analysis of patients with Stargardt macular dystrophy reveals new genotype-phenotype correlations and unexpected diagnostic revisions. - Zaneveld, Jacques; Siddiqui, Sorath; Li, Huajin; Wang, Xia; Wang, Hui; Wang, Keqing; Li, Hui; Ren, Huanan; Lopez, Irma; Dorfman, Allison; Khan, Ayesha; Wang, Feng; et al. (Genet Med, 2015)
PURPOSE: Stargardt macular dystrophy (STGD) results in early central vision loss. We sought to explain the genetic cause of STGD in a cohort of 88 patients from three different cultural backgrounds. METHODS: Next-generation sequencing using a novel capture panel was used to search for disease-causing mutations. Patients with undetermined causes were clinically reexamined and tested for copy-number variations as well as intronic mutations. RESULTS: We determined the cause of disease in 67% of our patients. Our analysis identified 35 novel ABCA4 alleles. Eleven patients had mutations in genes not previously reported to cause STGD. Finally, 45% of our patients with unsolved causes had single deleterious mutations in ABCA4, a recessive disease gene. No likely pathogenic copy-number variations were identified. CONCLUSION: This study expands our knowledge of STGD by identifying dozens of novel alleles that cause the disease. The frequency of single mutations in ABCA4 among STGD patients is higher than that among controls, indicating that these mutations contribute to disease. Disease in 11 patients was explained by mutations outside ABCA4, underlining the need to genotype all retinal disease genes to maximize genetic diagnostic rates. Few ABCA4 mutations were observed in our French Canadian patients. This population may contain an unidentified founder mutation. Our results indicate that copy-number variations are unlikely to be a major cause of STGD.
Keywords: Adult; ATP-Binding Cassette Transporters; DNA Copy Number Variations; DNA Mutational Analysis; Female; Genetic Association Studies; High-Throughput Nucleotide Sequencing; Humans; Macular Degeneration; Male; Middle Aged; Sequence Deletion; Stargardt Disease

Comprehensive genomic characterization of head and neck squamous cell carcinomas. (Nature, 2015)
The Cancer Genome Atlas profiled 279 head and neck squamous cell carcinomas (HNSCCs) to provide a comprehensive landscape of somatic genomic alterations. Here we show that human-papillomavirus-associated tumours are dominated by helical domain mutations of the oncogene PIK3CA, novel alterations involving loss of TRAF3, and amplification of the cell cycle gene E2F1. Smoking-related HNSCCs demonstrate near universal loss-of-function TP53 mutations and CDKN2A inactivation with frequent copy number alterations including amplification of 3q26/28 and 11q13/22. A subgroup of oral cavity tumours with favourable clinical outcomes displayed infrequent copy number alterations in conjunction with activating mutations of HRAS or PIK3CA, coupled with inactivating mutations of CASP8, NOTCH1 and TP53. Other distinct subgroups contained loss-of-function alterations of the chromatin modifier NSD1, WNT pathway genes AJUBA and FAT1, and activation of oxidative stress factor NFE2L2, mainly in laryngeal tumours. Therapeutic candidate alterations were identified in most HNSCCs.
Keywords: Carcinoma, Squamous Cell; DNA Copy Number Variations; DNA, Neoplasm; Female; Gene Expression Regulation, Neoplastic; Genome, Human; Genomics; Head and Neck Neoplasms; Humans; Male; Molecular Targeted Therapy; Mutation; Oncogenes; RNA, Neoplasm; Signal Transduction; Squamous Cell Carcinoma of Head and Neck; Transcription Factors

De Novo GMNN Mutations Cause Autosomal-Dominant Primordial Dwarfism Associated with Meier-Gorlin Syndrome. - Burrage, Lindsay C; Charng, Wu-Lin; Eldomery, Mohammad K; Willer, Jason R; Davis, Erica E; Lugtenberg, Dorien; Zhu, Wenmiao; Leduc, Magalie S; Akdemir, Zeynep C; Azamian, Mahshid; Zapata, Gladys; Hernandez, Patricia P; et al. (Am J Hum Genet, 2015)
Meier-Gorlin syndrome (MGS) is a genetically heterogeneous primordial dwarfism syndrome known to be caused by biallelic loss-of-function mutations in one of five genes encoding pre-replication complex proteins: ORC1, ORC4, ORC6, CDT1, and CDC6. Mutations in these genes cause disruption of the origin of DNA replication initiation. To date, only an autosomal-recessive inheritance pattern has been described in individuals with this disorder, with a molecular etiology established in about three-fourths of cases. Here, we report three subjects with MGS and de novo heterozygous mutations in the 5' end of GMNN, encoding the DNA replication inhibitor geminin. We identified two truncating mutations in exon 2 (the 1(st) coding exon), c.16A>T (p.Lys6(∗)) and c.35_38delTCAA (p.Ile12Lysfs(∗)4), and one missense mutation, c.50A>G (p.Lys17Arg), affecting the second-to-last nucleotide of exon 2 and possibly RNA splicing. Geminin is present during the S, G2, and M phases of the cell cycle and is degraded during the metaphase-anaphase transition by the anaphase-promoting complex (APC), which recognizes the destruction box sequence near the 5' end of the geminin protein. All three GMNN mutations identified alter sites 5' to residue Met28 of the protein, which is located within the destruction box. We present data supporting a gain-of-function mechanism, in which the GMNN mutations result in proteins lacking the destruction box and hence increased protein stability and prolonged inhibition of replication leading to autosomal-dominant MGS.
Keywords: Adolescent; Amino Acid Sequence; Base Sequence; Cell Cycle; Child, Preschool; Congenital Microtia; Dwarfism; Exons; Female; Geminin; Gene Expression; Genes, Dominant; Growth Disorders; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Inheritance Patterns; Male; Micrognathism; Molecular Sequence Data; Mutation; Patella; Pedigree; Protein Stability; Proteolysis; RNA Splicing; Sequence Alignment

DNA REPAIR. Mus81 and converging forks limit the mutagenicity of replication fork breakage. - Mayle, Ryan; Campbell, Ian M; Beck, Christine R; Yu, Yang; Wilson, Marenda; Shaw, Chad A; Bjergbaek, Lotte; Lupski, James R; Ira, Grzegorz (Science, 2015)
Most spontaneous DNA double-strand breaks (DSBs) result from replication-fork breakage. Break-induced replication (BIR), a genome rearrangement-prone repair mechanism that requires the Pol32/POLD3 subunit of eukaryotic DNA Polδ, was proposed to repair broken forks, but how genome destabilization is avoided was unknown. We show that broken fork repair initially uses error-prone Pol32-dependent synthesis, but that mutagenic synthesis is limited to within a few kilobases from the break by Mus81 endonuclease and a converging fork. Mus81 suppresses template switches between both homologous sequences and diverged human Alu repetitive elements, highlighting its importance for stability of highly repetitive genomes. We propose that lack of a timely converging fork or Mus81 may propel genome instability observed in cancer.
Keywords: Alu Elements; Base Sequence; DNA Breaks, Double-Stranded; DNA Repair; DNA Replication; DNA-Binding Proteins; DNA-Directed DNA Polymerase; Endonucleases; Genomic Instability; Humans; Molecular Sequence Data; Neoplasms; Saccharomyces cerevisiae; Saccharomyces cerevisiae Proteins

Dnmt3a loss predisposes murine hematopoietic stem cells to malignant transformation. - Mayle, Allison; Yang, Liubin; Rodriguez, Benjamin; Zhou, Ting; Chang, Edmund; Curry, Choladda V; Challen, Grant A; Li, Wei; Wheeler, David; Rebel, Vivienne I; Goodell, Margaret A (Blood, 2015)
DNA methyltransferase 3A (DNMT3A) is mutated in hematologic malignancies affecting myeloid, mixed, and lymphoid lineages, and these mutations are associated with poor prognosis. Past studies in mice revealed Dnmt3a-knockout (KO)hematopoietic stem cells (HSCs) had increased self-renewal, but no leukemia was observed. Here, all lethally irradiated mice transplanted with Dnmt3a-deleted HSCs died within 1 year. Animals were diagnosed with a spectrum of malignancies similar to those seen in patients with DNMT3A mutations, including myelodysplastic syndrome, acute myeloid leukemia, primary myelofibrosis, and T- and B-cell acute lymphocytic leukemia. In some cases, acquired malignancies exhibited secondary mutations similar to those identified in patients. Loss of Dnmt3a led to disturbed methylation patterns that were distinct in lymphoid and myeloid disease, suggesting lineage-specific methylation aberrations promoted by Dnmt3a loss. Global hypomethylation was observed in all of the malignancies, but lymphoid malignancies also exhibited hypermethylation, particularly at promoter regions. This mouse model underscores the important role of Dnmt3a in normal hematopoietic development and demonstrates that Dnmt3a loss of function confers a preleukemic phenotype on murine HSCs. This model may serve as a tool to study DNMT3A mutation associated malignancies and for developing targeted strategies for eliminating preleukemic cells for prevention and treatment of hematologic malignancies in the future.
Keywords: Animals; Cell Transformation, Neoplastic; DNA (Cytosine-5-)-Methyltransferases; DNA Methylation; DNA Methyltransferase 3A; DNA, Neoplasm; Hematologic Neoplasms; Hematopoietic Stem Cells; Mice; Mice, Knockout; Promoter Regions, Genetic

Durable sequence stability and bone marrow tropism in a macaque model of human pegivirus infection. - Bailey, Adam L; Lauck, Michael; Mohns, Mariel; Peterson, Eric J; Beheler, Kerry; Brunner, Kevin G; Crosno, Kristin; Mejia, Andres; Mutschler, James; Gehrke, Matthew; Greene, Justin; Ericsen, Adam J; et al. (Sci Transl Med, 2015)
Human pegivirus (HPgV)-formerly known as GB virus C and hepatitis G virus-is a poorly characterized RNA virus that infects about one-sixth of the global human population and is transmitted frequently in the blood supply. We create an animal model of HPgV infection by infecting macaque monkeys with a new simian pegivirus (SPgV) discovered in wild baboons. Using this model, we provide a high-resolution, longitudinal picture of SPgV viremia where the dose, route, and timing of infection are known. We detail the highly variable acute phase of SPgV infection, showing that the viral load trajectory early in infection is dependent on the infecting dose, whereas the chronic-phase viremic set point is not. We also show that SPgV has an extremely low propensity for accumulating sequence variation, with no consensus-level variants detected during the acute phase of infection and an average of only 1.5 variants generated per 100 infection-days. Finally, we show that SPgV RNA is highly concentrated in only two tissues: spleen and bone marrow, with bone marrow likely producing most of the virus detected in plasma. Together, these results reconcile several paradoxical observations from cross-sectional analyses of HPgV in humans and provide an animal model for studying pegivirus biology.
Keywords: Acquired Immunodeficiency Syndrome; Animals; Bone Marrow; Disease Models, Animal; Evolution, Molecular; Female; Flaviviridae Infections; GB virus C; Genetic Variation; High-Throughput Nucleotide Sequencing; HIV Infections; Humans; Likelihood Functions; Macaca; Male; Papio; Phylogeny; Reverse Transcriptase Polymerase Chain Reaction; RNA, Viral; Viral Load; Viral Tropism; Viremia

DVL1 frameshift mutations clustering in the penultimate exon cause autosomal-dominant Robinow syndrome. - White, Janson; Mazzeu, Juliana F; Hoischen, Alexander; Jhangiani, Shalini N; Gambin, Tomasz; Alcino, Michele Calijorne; Penney, Samantha; Saraiva, Jorge M; Hove, Hanne; Skovby, Flemming; Kayserili, Hulya; Estrella, Elicia; et al. (Am J Hum Genet, 2015)
Robinow syndrome is a genetically heterogeneous disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features and for which both autosomal-recessive and autosomal-dominant inheritance patterns have been described. Causative variants in the non-canonical signaling gene WNT5A underlie a subset of autosomal-dominant Robinow syndrome (DRS) cases, but most individuals with DRS remain without a molecular diagnosis. We performed whole-exome sequencing in four unrelated DRS-affected individuals without coding mutations in WNT5A and found heterozygous DVL1 exon 14 mutations in three of them. Targeted Sanger sequencing in additional subjects with DRS uncovered DVL1 exon 14 mutations in five individuals, including a pair of monozygotic twins. In total, six distinct frameshift mutations were found in eight subjects, and all were heterozygous truncating variants within the penultimate exon of DVL1. In five families in which samples from unaffected parents were available, the variants were demonstrated to represent de novo mutations. All variant alleles are predicted to result in a premature termination codon within the last exon, escape nonsense-mediated decay (NMD), and most likely generate a C-terminally truncated protein with a distinct -1 reading-frame terminus. Study of the transcripts extracted from affected subjects' leukocytes confirmed expression of both wild-type and variant alleles, supporting the hypothesis that mutant mRNA escapes NMD. Genomic variants identified in our study suggest that truncation of the C-terminal domain of DVL1, a protein hypothesized to have a downstream role in the Wnt-5a non-canonical pathway, is a common cause of DRS.
Keywords: Adaptor Proteins, Signal Transducing; Amino Acid Sequence; Base Sequence; Craniofacial Abnormalities; Dishevelled Proteins; DNA Primers; Dwarfism; Exome; Exons; Frameshift Mutation; Gene Components; Humans; Limb Deformities, Congenital; Molecular Sequence Data; Phosphoproteins; Sequence Analysis, DNA; Urogenital Abnormalities

Epigenome-wide association study (EWAS) of BMI, BMI change and waist circumference in African American adults identifies multiple replicated loci. - Demerath, Ellen W; Guan, Weihua; Grove, Megan L; Aslibekyan, Stella; Mendelson, Michael; Zhou, Yi-Hui; Hedman, Åsa K; Sandling, Johanna K; Li, Li-An; Irvin, Marguerite R; Zhi, Degui; Deloukas, Panos; et al. (Hum Mol Genet, 2015)
Obesity is an important component of the pathophysiology of chronic diseases. Identifying epigenetic modifications associated with elevated adiposity, including DNA methylation variation, may point to genomic pathways that are dysregulated in numerous conditions. The Illumina 450K Bead Chip array was used to assay DNA methylation in leukocyte DNA obtained from 2097 African American adults in the Atherosclerosis Risk in Communities (ARIC) study. Mixed-effects regression models were used to test the association of methylation beta value with concurrent body mass index (BMI) and waist circumference (WC), and BMI change, adjusting for batch effects and potential confounders. Replication using whole-blood DNA from 2377 White adults in the Framingham Heart Study and CD4+ T cell DNA from 991 Whites in the Genetics of Lipid Lowering Drugs and Diet Network Study was followed by testing using adipose tissue DNA from 648 women in the Multiple Tissue Human Expression Resource cohort. Seventy-six BMI-related probes, 164 WC-related probes and 8 BMI change-related probes passed the threshold for significance in ARIC (P < 1 × 10(-7); Bonferroni), including probes in the recently reported HIF3A, CPT1A and ABCG1 regions. Replication using blood DNA was achieved for 37 BMI probes and 1 additional WC probe. Sixteen of these also replicated in adipose tissue, including 15 novel methylation findings near genes involved in lipid metabolism, immune response/cytokine signaling and other diverse pathways, including LGALS3BP, KDM2B, PBX1 and BBS2, among others. Adiposity traits are associated with DNA methylation at numerous CpG sites that replicate across studies despite variation in tissue type, ethnicity and analytic approaches.
Keywords: Aged; Atherosclerosis; Black or African American; Body Mass Index; DNA Methylation; Epigenesis, Genetic; Female; Genome-Wide Association Study; Humans; Lipid Metabolism; Male; Metabolic Networks and Pathways; Middle Aged; Obesity; Waist Circumference; White People

FBN1 contributing to familial congenital diaphragmatic hernia. - Beck, Tyler F; Campeau, Philippe M; Jhangiani, Shalini N; Gambin, Tomasz; Li, Alexander H; Abo-Zahrah, Reem; Jordan, Valerie K; Hernandez-Garcia, Andres; Wiszniewski, Wojciech K; Muzny, Donna; Gibbs, Richard A; Boerwinkle, Eric; et al. (Am J Med Genet A, 2015)
Congenital diaphragmatic hernia (CDH) is a relatively common, life--threatening birth defect. We present a family with recurrent CDH--paraesophageal and central--for whom exome sequencing (ES) revealed a frameshift mutation (c.4969_4970insA, p.Ile1657Asnfs*30) in the fibrillin 1 gene (FBN1) that causes Marfan syndrome. A diagnosis of Marfan syndrome had not been considered previously in this family. However, a review of the literature demonstrated that FBN1 mutations have an unusual pattern of CDH in which paraesophageal hernias are particularly common. Subsequent clinical evaluations revealed evidence for ectopia lentis in affected family members supporting a clinical diagnosis of Marfan syndrome. Since only two other cases of familial CDH have been described in association with FBN1 mutations, we investigated an oligogenic hypothesis by examining ES data for deleterious sequence changes in other CDH-related genes. This search revealed putatively deleterious sequence changes in four other genes that have been shown to cause diaphragm defects in humans and/or mice--FREM1, DES, PAX3 and MET. It is unclear whether these changes, alone or in aggregate, are contributing to the development of CDH in this family. However, their individual contribution is likely to be small compared to that of the frameshift mutation in FBN1. We conclude that ES can be used to identify both major and minor genetic factors that may contribute to CDH. These results also suggest that ES should be considered in the diagnostic evaluation of individuals and families with CDH, particularly when other diagnostic modalities have failed to reveal a molecular etiology.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Exome; Female; Fibrillin-1; Fibrillins; Frameshift Mutation; Genetic Association Studies; Hernias, Diaphragmatic, Congenital; Humans; Male; Marfan Syndrome; Microfilament Proteins; Pedigree

FlyVar: a database for genetic variation in Drosophila melanogaster. - Wang, Fei; Jiang, Lichun; Chen, Yong; Haelterman, Nele A; Bellen, Hugo J; Chen, Rui (Database (Oxford), 2015)
FlyVar is a publicly and freely available platform that addresses the increasing need of next generation sequencing data analysis in the Drosophila research community. It is composed of three parts. First, a database that contains 5.94 million DNA polymorphisms found in Drosophila melanogaster derived from whole genome shotgun sequencing of 612 genomes of D. melanogaster. In addition, a list of 1094 dispensable genes has been identified. Second, a graphical user interface (GUI) has been implemented to allow easy and flexible queries of the database. Third, a set of interactive online tools enables filtering and annotation of genomic sequences obtained from individual D. melanogaster strains to identify candidate mutations. FlyVar permits the analysis of next generation sequencing data without the need of extensive computational training or resources. Database URL: www.iipl.fudan.edu.cn/FlyVar.
Keywords: Animals; Databases, Genetic; Drosophila melanogaster; Genes, Insect; Molecular Sequence Annotation; Polymorphism, Genetic; User-Computer Interface

FOXO1 is required for binding of PR on IRF4, novel transcriptional regulator of endometrial stromal decidualization. - Vasquez, Yasmin M; Mazur, Erik C; Li, Xilong; Kommagani, Ramakrishna; Jiang, Lichun; Chen, Rui; Lanz, Rainer B; Kovanci, Ertug; Gibbons, William E; DeMayo, Francesco J (Mol Endocrinol, 2015)
The forkhead box O1A (FOXO1) is an early-induced target of the protein kinase A pathway during the decidualization of human endometrial stromal cells (HESCs). In this study we identified the cistrome and transcriptome of FOXO1 and its role as a transcriptional regulator of the progesterone receptor (PR). Direct targets of FOXO1 were identified by integrating RNA sequencing with chromatin immunoprecipitation followed by deep sequencing. Gene ontology analysis demonstrated that FOXO1 regulates a subset of genes in decidualization such as those involved in cancer, p53 signaling, focal adhesions, and Wnt signaling. An overlap of the FOXO1 and PR chromatin immunoprecipitation followed by deep sequencing intervals revealed the co-occupancy of FOXO1 in more than 75% of PR binding intervals. Among these intervals were highly enriched motifs for the interferon regulatory factor member 4 (IRF4). IRF4 was determined to be a genomic target of both FOXO1 and PR and also to be differentially regulated in HESCs treated with small interfering RNA targeting FOXO1 or PR prior to decidualization stimulus. Ablation of FOXO1 was found to abolish binding of PR to the shared binding interval downstream of the IRF4 gene. Finally, small interfering RNA-mediated ablation of IRF4 was shown to compromise morphological transformation of decidualized HESCs and to attenuate the expression of the decidual markers IGFBP1, PRL, and WNT4. These results provide the first evidence that FOXO1 is functionally required for the binding of PR to genomic targets. Most notably, FOXO1 and PR are required for the regulation of IRF4, a novel transcriptional regulator of decidualization in HESCs.
Keywords: Base Sequence; Binding Sites; Chromatin Immunoprecipitation; Decidua; Female; Forkhead Box Protein O1; Forkhead Transcription Factors; Gene Expression Regulation; Genome, Human; Humans; Interferon Regulatory Factors; Molecular Sequence Data; Nucleotide Motifs; Protein Binding; Receptors, Progesterone; Reproducibility of Results; RNA, Small Interfering; Sequence Analysis, RNA; Software; Stromal Cells; Transcription, Genetic

The GABA transaminase, ABAT, is essential for mitochondrial nucleoside metabolism. - Besse, Arnaud; Wu, Ping; Bruni, Francesco; Donti, Taraka; Graham, Brett H; Craigen, William J; McFarland, Robert; Moretti, Paolo; Lalani, Seema; Scott, Kenneth L; Taylor, Robert W; Bonnen, Penelope E (Cell Metab, 2015)
ABAT is a key enzyme responsible for catabolism of principal inhibitory neurotransmitter γ-aminobutyric acid (GABA). We report an essential role for ABAT in a seemingly unrelated pathway, mitochondrial nucleoside salvage, and demonstrate that mutations in this enzyme cause an autosomal recessive neurometabolic disorder and mtDNA depletion syndrome (MDS). We describe a family with encephalomyopathic MDS caused by a homozygous missense mutation in ABAT that results in elevated GABA in subjects' brains as well as decreased mtDNA levels in subjects' fibroblasts. Nucleoside rescue and co-IP experiments pinpoint that ABAT functions in the mitochondrial nucleoside salvage pathway to facilitate conversion of dNDPs to dNTPs. Pharmacological inhibition of ABAT through the irreversible inhibitor Vigabatrin caused depletion of mtDNA in photoreceptor cells that was prevented through addition of dNTPs in cell culture media. This work reveals ABAT as a connection between GABA metabolism and nucleoside metabolism and defines a neurometabolic disorder that includes MDS.
Keywords: 4-Aminobutyrate Transaminase; Brain; DNA, Mitochondrial; Fibroblasts; gamma-Aminobutyric Acid; Humans; Mitochondria; Mutation, Missense; Nucleosides

Generation and characterization of antibodies against Asian elephant (Elephas maximus) IgG, IgM, and IgA. - Humphreys, Alan F; Tan, Jie; Peng, Rongsheng; Benton, Susan M; Qin, Xiang; Worley, Kim C; Mikulski, Rose L; Chow, Dar-Chone; Palzkill, Timothy G; Ling, Paul D (PLoS One, 2015)
Asian elephant (Elephas maximus) immunity is poorly characterized and understood. This gap in knowledge is particularly concerning as Asian elephants are an endangered species threatened by a newly discovered herpesvirus known as elephant endotheliotropic herpesvirus (EEHV), which is the leading cause of death for captive Asian elephants born after 1980 in North America. While reliable diagnostic assays have been developed to detect EEHV DNA, serological assays to evaluate elephant anti-EEHV antibody responses are lacking and will be needed for surveillance and epidemiological studies and also for evaluating potential treatments or vaccines against lethal EEHV infection. Previous studies have shown that Asian elephants produce IgG in serum, but they failed to detect IgM and IgA, further hampering development of informative serological assays for this species. To begin to address this issue, we determined the constant region genomic sequence of Asian elephant IgM and obtained some limited protein sequence information for putative serum IgA. The information was used to generate or identify specific commercial antisera reactive against IgM and IgA isotypes. In addition, we generated a monoclonal antibody against Asian elephant IgG. These three reagents were used to demonstrate that all three immunoglobulin isotypes are found in Asian elephant serum and milk and to detect antibody responses following tetanus toxoid booster vaccination or antibodies against a putative EEHV structural protein. The results indicate that these new reagents will be useful for developing sensitive and specific assays to detect and characterize elephant antibody responses for any pathogen or vaccine, including EEHV.
Keywords: Animals; Antibodies, Anti-Idiotypic; Base Sequence; Betaherpesvirinae; Chromatography, Gel; DNA Primers; Electrophoresis, Polyacrylamide Gel; Elephants; Endangered Species; Enzyme-Linked Immunosorbent Assay; Herpesviridae Infections; Immunoglobulin A; Immunoglobulin G; Immunoglobulin M; Molecular Sequence Data; Polymerase Chain Reaction; Sequence Analysis, DNA; Tandem Mass Spectrometry

Genes that Affect Brain Structure and Function Identified by Rare Variant Analyses of Mendelian Neurologic Disease. - Karaca, Ender; Harel, Tamar; Pehlivan, Davut; Jhangiani, Shalini N; Gambin, Tomasz; Coban Akdemir, Zeynep; Gonzaga-Jauregui, Claudia; Erdin, Serkan; Bayram, Yavuz; Campbell, Ian M; Hunter, Jill V; Atik, Mehmed M; et al. (Neuron, 2015)
Development of the human nervous system involves complex interactions among fundamental cellular processes and requires a multitude of genes, many of which remain to be associated with human disease. We applied whole exome sequencing to 128 mostly consanguineous families with neurogenetic disorders that often included brain malformations. Rare variant analyses for both single nucleotide variant (SNV) and copy number variant (CNV) alleles allowed for identification of 45 novel variants in 43 known disease genes, 41 candidate genes, and CNVs in 10 families, with an overall potential molecular cause identified in >85% of families studied. Among the candidate genes identified, we found PRUNE, VARS, and DHX37 in multiple families and homozygous loss-of-function variants in AGBL2, SLC18A2, SMARCA1, UBQLN1, and CPLX1. Neuroimaging and in silico analysis of functional and expression proximity between candidate and known disease genes allowed for further understanding of genetic networks underlying specific types of brain malformations.
Keywords: Brain; Cohort Studies; Databases, Genetic; Female; Gene Regulatory Networks; Genetic Association Studies; Genetic Variation; Humans; Male; Mendelian Randomization Analysis; Nervous System Diseases; Pedigree

Genetic fine mapping and genomic annotation defines causal mechanisms at type 2 diabetes susceptibility loci. - Gaulton, Kyle J; Ferreira, Teresa; Lee, Yeji; Raimondo, Anne; Mägi, Reedik; Reschen, Michael E; Mahajan, Anubha; Locke, Adam; Rayner, N William; Robertson, Neil; Scott, Robert A; Prokopenko, Inga; et al. (Nat Genet, 2015)
We performed fine mapping of 39 established type 2 diabetes (T2D) loci in 27,206 cases and 57,574 controls of European ancestry. We identified 49 distinct association signals at these loci, including five mapping in or near KCNQ1. 'Credible sets' of the variants most likely to drive each distinct signal mapped predominantly to noncoding sequence, implying that association with T2D is mediated through gene regulation. Credible set variants were enriched for overlap with FOXA2 chromatin immunoprecipitation binding sites in human islet and liver cells, including at MTNR1B, where fine mapping implicated rs10830963 as driving T2D association. We confirmed that the T2D risk allele for this SNP increases FOXA2-bound enhancer activity in islet- and liver-derived cells. We observed allele-specific differences in NEUROD1 binding in islet-derived cells, consistent with evidence that the T2D risk allele increases islet MTNR1B expression. Our study demonstrates how integration of genetic and genomic information can define molecular mechanisms through which variants underlying association signals exert their effects on disease.
Keywords: Binding Sites; Case-Control Studies; Chromatin Immunoprecipitation; Chromosome Mapping; Diabetes Mellitus, Type 2; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Hepatocyte Nuclear Factor 3-beta; Humans; Islets of Langerhans; Liver; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Receptor, Melatonin, MT2

Genetic overlap between diagnostic subtypes of ischemic stroke. - Holliday, Elizabeth G; Traylor, Matthew; Malik, Rainer; Bevan, Steve; Falcone, Guido; Hopewell, Jemma C; Cheng, Yu-Ching; Cotlarciuc, Ioana; Bis, Joshua C; Boerwinkle, Eric; Boncoraglio, Giorgio B; Clarke, Robert; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: Despite moderate heritability, the phenotypic heterogeneity of ischemic stroke has hampered gene discovery, motivating analyses of diagnostic subtypes with reduced sample sizes. We assessed evidence for a shared genetic basis among the 3 major subtypes: large artery atherosclerosis (LAA), cardioembolism, and small vessel disease (SVD), to inform potential cross-subtype analyses. METHODS: Analyses used genome-wide summary data for 12 389 ischemic stroke cases (including 2167 LAA, 2405 cardioembolism, and 1854 SVD) and 62 004 controls from the Metastroke consortium. For 4561 cases and 7094 controls, individual-level genotype data were also available. Genetic correlations between subtypes were estimated using linear mixed models and polygenic profile scores. Meta-analysis of a combined LAA-SVD phenotype (4021 cases and 51 976 controls) was performed to identify shared risk alleles. RESULTS: High genetic correlation was identified between LAA and SVD using linear mixed models (rg=0.96, SE=0.47, P=9×10(-4)) and profile scores (rg=0.72; 95% confidence interval, 0.52-0.93). Between LAA and cardioembolism and SVD and cardioembolism, correlation was moderate using linear mixed models but not significantly different from zero for profile scoring. Joint meta-analysis of LAA and SVD identified strong association (P=1×10(-7)) for single nucleotide polymorphisms near the opioid receptor μ1 (OPRM1) gene. CONCLUSIONS: Our results suggest that LAA and SVD, which have been hitherto treated as genetically distinct, may share a substantial genetic component. Combined analyses of LAA and SVD may increase power to identify small-effect alleles influencing shared pathophysiological processes.
Keywords: Alleles; Atherosclerosis; Cerebral Small Vessel Diseases; Cohort Studies; Data Interpretation, Statistical; Embolism; Genome-Wide Association Study; Genotype; Humans; Ischemia; Linear Models; Meta-Analysis as Topic; Phenotype; Polymorphism, Single Nucleotide; Stroke

The genomes of two key bumblebee species with primitive eusocial organization. - Sadd, Ben M; Barribeau, Seth M; Bloch, Guy; de Graaf, Dirk C; Dearden, Peter; Elsik, Christine G; Gadau, Jürgen; Grimmelikhuijzen, Cornelis J P; Hasselmann, Martin; Lozier, Jeffrey D; Robertson, Hugh M; Smagghe, Guy; et al. (Genome Biol, 2015)
BACKGROUND: The shift from solitary to social behavior is one of the major evolutionary transitions. Primitively eusocial bumblebees are uniquely placed to illuminate the evolution of highly eusocial insect societies. Bumblebees are also invaluable natural and agricultural pollinators, and there is widespread concern over recent population declines in some species. High-quality genomic data will inform key aspects of bumblebee biology, including susceptibility to implicated population viability threats. RESULTS: We report the high quality draft genome sequences of Bombus terrestris and Bombus impatiens, two ecologically dominant bumblebees and widely utilized study species. Comparing these new genomes to those of the highly eusocial honeybee Apis mellifera and other Hymenoptera, we identify deeply conserved similarities, as well as novelties key to the biology of these organisms. Some honeybee genome features thought to underpin advanced eusociality are also present in bumblebees, indicating an earlier evolution in the bee lineage. Xenobiotic detoxification and immune genes are similarly depauperate in bumblebees and honeybees, and multiple categories of genes linked to social organization, including development and behavior, show high conservation. Key differences identified include a bias in bumblebee chemoreception towards gustation from olfaction, and striking differences in microRNAs, potentially responsible for gene regulation underlying social and other traits. CONCLUSIONS: These two bumblebee genomes provide a foundation for post-genomic research on these key pollinators and insect societies. Overall, gene repertoires suggest that the route to advanced eusociality in bees was mediated by many small changes in many genes and processes, and not by notable expansion or depauperation.
Keywords: Animals; Bee Venoms; Bees; Behavior, Animal; Chemoreceptor Cells; Chromosome Mapping; Databases, Genetic; Evolution, Molecular; Female; Gene Expression Regulation; Gene Rearrangement; Genes, Insect; Genomics; Interspersed Repetitive Sequences; Male; Open Reading Frames; Polymorphism, Single Nucleotide; Selenoproteins; Sequence Analysis, DNA; Social Behavior; Species Specificity; Synteny

Genomic profiling guides the choice of molecular targeted therapy of pancreatic cancer. - Frank, Thomas S; Sun, Xiaotian; Zhang, Yuqing; Yang, Jingxuan; Fisher, William E; Gingras, Marie-Claude; Li, Min (Cancer Lett, 2015)
Pancreatic cancer has the worst five-year survival rate of all malignancies due to its aggressive progression and resistance to therapy. Current therapies are limited to gemcitabine-based chemotherapeutics, surgery, and radiation. The current trend toward "personalized genomic medicine" has the potential to improve the treatment options for pancreatic cancer. Gene identification and genetic alterations like single nucleotide polymorphisms and mutations will allow physicians to predict the efficacy and toxicity of drugs, which could help diagnose pancreatic cancer, guide neoadjuvant or adjuvant treatment, and evaluate patients' prognosis. This article reviews the multifaceted roles of genomics and pharmacogenomics in pancreatic cancer.
Keywords: Animals; Antineoplastic Agents; Biomarkers, Tumor; Drug Resistance, Neoplasm; Gene Expression Profiling; Genetic Predisposition to Disease; Genomics; Humans; Molecular Targeted Therapy; Pancreatic Neoplasms; Patient Selection; Pharmacogenetics; Phenotype; Precision Medicine; Predictive Value of Tests; Signal Transduction

Genomic signatures of cooperation and conflict in the social amoeba. - Ostrowski, Elizabeth A; Shen, Yufeng; Tian, Xiangjun; Sucgang, Richard; Jiang, Huaiyang; Qu, Jiaxin; Katoh-Kurasawa, Mariko; Brock, Debra A; Dinh, Christopher; Lara-Garduno, Fremiet; Lee, Sandra L; Kovar, Christie L; et al. (Curr Biol, 2015)
Cooperative systems are susceptible to invasion by selfish individuals that profit from receiving the social benefits but fail to contribute. These so-called "cheaters" can have a fitness advantage in the laboratory, but it is unclear whether cheating provides an important selective advantage in nature. We used a population genomic approach to examine the history of genes involved in cheating behaviors in the social amoeba Dictyostelium discoideum, testing whether these genes experience rapid evolutionary change as a result of conflict over spore-stalk fate. Candidate genes and surrounding regions showed elevated polymorphism, unusual patterns of linkage disequilibrium, and lower levels of population differentiation, but they did not show greater between-species divergence. The signatures were most consistent with frequency-dependent selection acting to maintain multiple alleles, suggesting that conflict may lead to stalemate rather than an escalating arms race. Our results reveal the evolutionary dynamics of cooperation and cheating and underscore how sequence-based approaches can be used to elucidate the history of conflicts that are difficult to observe directly.
Keywords: Dictyostelium; Evolution, Molecular; Genome, Protozoan; Genomics; Polymorphism, Genetic; Selection, Genetic

Germline PRKACA amplification causes variable phenotypes that may depend on the extent of the genomic defect: molecular mechanisms and clinical presentations. - Lodish, Maya B; Bo Yuan; Levy, Isaac; Braunstein, Glenn D; Lyssikatos, Charalampos; Salpea, Paraskevi; Szarek, Eva; Karageorgiadis, Alexander S; Belyavskaya, Elena; Raygada, Margarita; Faucz, Fabio Rueda; Izzat, Louise; et al. (Eur J Endocrinol, 2015)
OBJECTIVE: We have recently reported five patients with bilateral adrenocortical hyperplasia (BAH) and Cushing's syndrome (CS) caused by constitutive activation of the catalytic subunit of protein kinase A (PRKACA). By doing new in-depth analysis of their cytogenetic abnormality, we attempted a better genotype-phenotype correlation of their PRKACA amplification. DESIGN: This study is a case series. METHODS: Molecular cytogenetic, genomic, clinical, and histopathological analyses were performed in five patients with CS. RESULTS: Reinvestigation of the defects of previously described patients by state-of-the-art molecular cytogenetics showed complex genomic rearrangements in the chromosome 19p13.2p13.12 locus, resulting in copy number gains encompassing the entire PRKACA gene; three patients (one sporadic case and two related cases) were observed with gains consistent with duplications, while two sporadic patients were observed with gains consistent with triplications. Although all five patients presented with ACTH-independent CS, the three sporadic patients had micronodular BAH and underwent bilateral adrenalectomy in early childhood, whereas the two related patients, a mother and a son, presented with macronodular BAH as adults. In at least one patient, PRKACA triplication was associated with a more severe phenotype. CONCLUSIONS: Constitutional chromosomal PRKACA gene amplification is a recently identified genetic defect associated with CS, a trait that may be inherited in an autosomal dominant manner or occur de novo. Genomic rearrangements can be complex and can result in different copy number states of dosage-sensitive genes, e.g., duplication and triplication. PRKACA amplification can lead to variable phenotypes clinically and pathologically, both micro- and macro-nodular BAH, the latter of which we speculate may depend on the extent of amplification.
Keywords: Adrenal Glands; Adrenalectomy; Adult; Child; Child, Preschool; Cushing Syndrome; Cyclic AMP-Dependent Protein Kinase Catalytic Subunits; DNA Copy Number Variations; Female; Gene Amplification; Humans; Hyperplasia; Male; Phenotype; Young Adult

Global transcriptional disturbances underlie Cornelia de Lange syndrome and related phenotypes. - Yuan, Bo; Pehlivan, Davut; Karaca, Ender; Patel, Nisha; Charng, Wu-Lin; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Sutton, V Reid; Yesil, Gozde; Bozdogan, Sevcan Tug; Tos, Tulay; Koparir, Asuman; et al. (J Clin Invest, 2015)
Cornelia de Lange syndrome (CdLS) is a genetically heterogeneous disorder that presents with extensive phenotypic variability, including facial dysmorphism, developmental delay/intellectual disability (DD/ID), abnormal extremities, and hirsutism. About 65% of patients harbor mutations in genes that encode subunits or regulators of the cohesin complex, including NIPBL, SMC1A, SMC3, RAD21, and HDAC8. Wiedemann-Steiner syndrome (WDSTS), which shares CdLS phenotypic features, is caused by mutations in lysine-specific methyltransferase 2A (KMT2A). Here, we performed whole-exome sequencing (WES) of 2 male siblings clinically diagnosed with WDSTS; this revealed a hemizygous, missense mutation in SMC1A that was predicted to be deleterious. Extensive clinical evaluation and WES of 32 Turkish patients clinically diagnosed with CdLS revealed the presence of a de novo heterozygous nonsense KMT2A mutation in 1 patient without characteristic WDSTS features. We also identified de novo heterozygous mutations in SMC3 or SMC1A that affected RNA splicing in 2 independent patients with combined CdLS and WDSTS features. Furthermore, in families from 2 separate world populations segregating an autosomal-recessive disorder with CdLS-like features, we identified homozygous mutations in TAF6, which encodes a core transcriptional regulatory pathway component. Together, our data, along with recent transcriptome studies, suggest that CdLS and related phenotypes may be "transcriptomopathies" rather than cohesinopathies.
Keywords: Adolescent; Adult; Cell Cycle Proteins; Child; Child, Preschool; Chondroitin Sulfate Proteoglycans; Chromosomal Proteins, Non-Histone; Codon, Nonsense; De Lange Syndrome; Exome; Exonucleases; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Heterozygote; Histone Deacetylases; Histone-Lysine N-Methyltransferase; Humans; Infant; Male; Myeloid-Lymphoid Leukemia Protein; Phenotype; Proteins; Repressor Proteins; Transcriptome

Human adipose tissue as a reservoir for memory CD4+ T cells and HIV. - Couturier, Jacob; Suliburk, James W; Brown, Jeremy M; Luke, David J; Agarwal, Neeti; Yu, Xiaoying; Nguyen, Chi; Iyer, Dinakar; Kozinetz, Claudia A; Overbeek, Paul A; Metzker, Michael L; Balasubramanyam, Ashok; et al. (AIDS, 2015)
OBJECTIVE: The objective of this study is to determine whether adipose tissue functions as a reservoir for HIV-1. DESIGN: We examined memory CD4(+) T cells and HIV DNA in adipose tissue-stromal vascular fraction (AT-SVF) of five patients [four antiretroviral therapy (ART)-treated and one untreated]. To determine whether adipocytes stimulate CD4(+) T cells and regulate HIV production, primary human adipose cells were cocultured with HIV-infected CD4(+) T cells. METHODS: AT-SVF T cells were studied by flow cytometry, and AT-SVF HIV DNA (Gag and Env) was examined by nested PCR and sequence analyses. CD4(+) T-cell activation and HIV production were measured by flow cytometry and ELISA. RESULTS: AT-SVF CD3(+) T cells were activated (>60% CD69(+)) memory CD4(+) and CD8(+) T cells in uninfected and HIV-infected persons, but the AT-SVF CD4(+)/CD8(+) ratio was lower in HIV patients. HIV DNA (Gag and Env) was detected in AT-SVF of all five patients examined by nested PCR, comparably to other tissues [peripheral blood mononuclear cell (PBMC), lymph node or thymus]. In coculture experiments, adipocytes increased CD4(+) T-cell activation and HIV production approximately two to three-fold in synergy with gamma-chain cytokines interleukin (IL)-2, IL7 or IL15. These effects were mitigated by neutralizing antibodies against IL6 and integrin-α1β1. Adipocytes also enhanced T-cell viability. CONCLUSION: Adipose tissues of ART-treated patients harbour activated memory CD4(+) T cells and HIV DNA. Adipocytes promote CD4(+) T-cell activation and HIV production in concert with intrinsic adipose factors. Adipose tissue may be an important reservoir for HIV.
Keywords: Adipocytes; Adipose Tissue; CD4-Positive T-Lymphocytes; Cells, Cultured; Coculture Techniques; DNA, Viral; Enzyme-Linked Immunosorbent Assay; Flow Cytometry; HIV; Humans; Lymphocyte Activation; T-Lymphocyte Subsets

Identification of Variant-Specific Functions of PIK3CA by Rapid Phenotyping of Rare Mutations. - Dogruluk, Turgut; Tsang, Yiu Huen; Espitia, Maribel; Chen, Fengju; Chen, Tenghui; Chong, Zechen; Appadurai, Vivek; Dogruluk, Armel; Eterovic, Agna Karina; Bonnen, Penelope E; Creighton, Chad J; Chen, Ken; et al. (Cancer Res, 2015)
Large-scale sequencing efforts are uncovering the complexity of cancer genomes, which are composed of causal "driver" mutations that promote tumor progression along with many more pathologically neutral "passenger" events. The majority of mutations, both in known cancer drivers and uncharacterized genes, are generally of low occurrence, highlighting the need to functionally annotate the long tail of infrequent mutations present in heterogeneous cancers. Here we describe a mutation assessment pipeline enabled by high-throughput engineering of molecularly barcoded gene variant expression clones identified by tumor sequencing. We first used this platform to functionally assess tail mutations observed in PIK3CA, which encodes the catalytic subunit alpha of the phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) frequently mutated in cancer. Orthogonal screening for PIK3CA variant activity using in vitro and in vivo cell growth and transformation assays differentiated driver from passenger mutations, revealing that PIK3CA variant activity correlates imperfectly with its mutation frequency across breast cancer populations. Although PIK3CA mutations with frequencies above 5% were significantly more oncogenic than wild-type in all assays, mutations occurring at 0.07% to 5.0% included those with and without oncogenic activities that ranged from weak to strong in at least one assay. Proteomic profiling coupled with therapeutic sensitivity assays on PIK3CA variant-expressing cell models revealed variant-specific activation of PI3K signaling as well as other pathways that include the MEK1/2 module of mitogen-activated protein kinase pathway. Our data indicate that cancer treatments will need to increasingly consider the functional relevance of specific mutations in driver genes rather than considering all mutations in drivers as equivalent.
Keywords: Animals; Breast Neoplasms; Cell Line, Tumor; Class I Phosphatidylinositol 3-Kinases; DNA Mutational Analysis; Female; Heterografts; High-Throughput Nucleotide Sequencing; Humans; Immunoblotting; Mice; Mice, Nude; Mutagenesis, Site-Directed; Phenotype; Phosphatidylinositol 3-Kinases; Polymerase Chain Reaction; Transduction, Genetic

Identifying gene disruptions in novel balanced de novo constitutional translocations in childhood cancer patients by whole-genome sequencing. - Ritter, Deborah I; Haines, Katherine; Cheung, Hannah; Davis, Caleb F; Lau, Ching C; Berg, Jonathan S; Brown, Chester W; Thompson, Patrick A; Gibbs, Richard; Wheeler, David A; Plon, Sharon E (Genet Med, 2015)
PURPOSE: We applied whole-genome sequencing (WGS) to children diagnosed with neoplasms and found to carry apparently balanced constitutional translocations to discover novel genic disruptions. METHODS: We applied the structural variation (SV) calling programs CREST, BreakDancer, SV-STAT, and CGAP-CNV, and we developed an annotative filtering strategy to achieve nucleotide resolution at the translocations. RESULTS: We identified the breakpoints for t(6;12)(p21.1;q24.31), disrupting HNF1A in a patient diagnosed with hepatic adenomas and maturity-onset diabetes of the young (MODY). Translocation as the disruptive event of HNF1A, a gene known to be involved in MODY3, has not been previously reported. In a subject with Hodgkin lymphoma and subsequent low-grade glioma, we identified t(5;18)(q35.1;q21.2), disrupting both SLIT3 and DCC, genes previously implicated in both glioma and lymphoma. CONCLUSION: These examples suggest that implementing clinical WGS in the diagnostic workup of patients with novel but apparently balanced translocations may reveal unanticipated disruption of disease-associated genes and aid in prediction of the clinical phenotype.
Keywords: Adenoma; Adult; Age Factors; Base Sequence; Child; Child, Preschool; Chromosome Breakpoints; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 18; Chromosomes, Human, Pair 5; Chromosomes, Human, Pair 6; DCC Receptor; Diabetes Mellitus, Type 2; DNA Copy Number Variations; Female; Genetic Association Studies; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; INDEL Mutation; Liver Neoplasms; Male; Membrane Proteins; Molecular Sequence Data; Neoplasms; Polymorphism, Single Nucleotide; Receptors, Cell Surface; Translocation, Genetic; Tumor Suppressor Proteins

Initial testing (stage 1) of the PARP inhibitor BMN 673 by the pediatric preclinical testing program: PALB2 mutation predicts exceptional in vivo response to BMN 673. - Smith, Malcolm A; Hampton, Oliver A; Reynolds, C Patrick; Kang, Min H; Maris, John M; Gorlick, Richard; Kolb, E Anders; Lock, Richard; Carol, Hernan; Keir, Stephen T; Wu, Jianrong; Kurmasheva, Raushan T; et al. (Pediatr Blood Cancer, 2015)
BACKGROUND: BMN 673 is a potent inhibitor of poly-ADP ribose polymerase (PARP) that is in clinical testing with a primary focus on BRCA-mutated cancers. BMN 673 is active both through inhibiting PARP catalytic activity and by tightly trapping PARP to DNA at sites of single strand breaks. PROCEDURE: BMN 673 was tested in vitro at concentrations ranging from 0.1 nM to 1 μM and in vivo at a daily dose of 0.33 mg/kg administered orally twice daily (Mon-Fri) and once daily on weekends (solid tumors) for 28 days. RESULTS: The median relative IC50 (rIC50 ) concentration against the PPTP cell lines was 25.8 nM. The median rIC50 for the Ewing cell lines was lower than for the remaining cell lines (6.4 vs. 31.1 nM, respectively). In vivo BMN 673 induced statistically significant differences in EFS distribution in 17/43 (39.5%) xenograft models. Three objective regressions were observed: a complete response (CR) in a medulloblastoma line (BT-45), a maintained CR in a Wilms tumor line (KT-10), and a maintained CR in an ependymoma line (BT-41). BMN 673 maintained its high level of activity against KT-10 with a threefold reduction in dose. KT-10 possesses a truncating mutation in PALB2 analogous to PALB2 mutations associated with hereditary breast and ovarian cancer that abrogate homologous recombination (HR) repair. CONCLUSIONS: The PPTP results suggest that single agent BMN 673 may have limited clinical activity against pediatric cancers. Single agent activity is more likely for patients whose tumors have defects in HR repair.
Keywords: Animals; Bone Neoplasms; Drug Evaluation, Preclinical; Enzyme Inhibitors; Fanconi Anemia Complementation Group N Protein; Female; Glioblastoma; Humans; Mice; Mutation; Neuroblastoma; Nuclear Proteins; Phthalazines; Poly(ADP-ribose) Polymerase Inhibitors; Rhabdomyosarcoma; Sarcoma, Ewing; Tumor Suppressor Proteins

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.
Keywords: Adult; Age Factors; Aging; BRCA1 Protein; Breast Neoplasms; DNA Repair; Female; Gene Regulatory Networks; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genomics; Genotype; Humans; Hypothalamus; Menopause; Middle Aged; Models, Genetic; Phenotype; Reproduction; Signal Transduction

Lipoprotein associated phospholipase A2 activity, apolipoprotein C3 loss-of-function variants and cardiovascular disease: The Atherosclerosis Risk In Communities Study. - Pokharel, Yashashwi; Sun, Wensheng; Polfus, Linda M; Folsom, Aaron R; Heiss, Gerardo; Sharrett, A Richey; Boerwinkle, Eric; Ballantyne, Christie M; Hoogeveen, Ron C (Atherosclerosis, 2015)
OBJECTIVE: Lipoprotein-associated phospholipase A2 (LpPLA2) activity was associated with higher CHD risk in a meta-analysis, which was partly dependent on circulating lipid levels. Apolipoprotein C3 loss-of-function (ApoC3 LOF) mutations were related with reduced postprandial lipemia and CHD risk. However, the association of LpPLA2 activity with ApoC3 LOF is not known. METHODS: We examined the association of LpPLA2 activity and ApoC3 LOF mutations and incident cardiovascular disease (CVD) (defined as coronary heart disease [CHD] plus ischemic stroke) and all-cause mortality in the biracial longitudinal Atherosclerosis Risk In Communities (ARIC) study. RESULTS: The mean LpPLA2 activity was 229.3 nmol/min/mL and was higher in men and whites. LpPLA2 activity correlated positively with atherogenic dyslipidemia. ApoC3 LOF carriers had lower LpPLA2 activity levels compared to non-carriers, and there was inverse association between LpPLA2 activity and ApoC3 LOF mutations in whites. In a fully adjusted model, greater LpPLA2 activity was independently associated with incident CVD (HR 1.35, 1.09-1.68 for highest vs. lowest quintile), which was mainly explained by its association with CHD, and was also associated with all-cause mortality (HR 1.65, 1.38-1.98). CONCLUSIONS: Greater LpPLA2 activity was associated with increased CHD and all-cause mortality in both whites and African-Americans in the ARIC study. The inverse relation between LpPLA2 activity and ApoC3 LOF mutations suggests that delayed lipoprotein clearance may at least in part explain the observed association of LpPLA2 activity with increased CVD risk.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Alleles; Apolipoprotein C-III; Atherosclerosis; Cardiovascular Diseases; Dyslipidemias; Female; Humans; Lipoprotein Lipase; Male; Middle Aged; Mutation; Postprandial Period; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; United States

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: Black People; Blood Glucose; Diabetes Mellitus, Type 2; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; White People

Lucilia cuprina genome unlocks parasitic fly biology to underpin future interventions. - Anstead, Clare A; Korhonen, Pasi K; Young, Neil D; Hall, Ross S; Jex, Aaron R; Murali, Shwetha C; Hughes, Daniel S T; Lee, Siu F; Perry, Trent; Stroehlein, Andreas J; Ansell, Brendan R E; Breugelmans, Bert; et al. (Nat Commun, 2015)
Lucilia cuprina is a parasitic fly of major economic importance worldwide. Larvae of this fly invade their animal host, feed on tissues and excretions and progressively cause severe skin disease (myiasis). Here we report the sequence and annotation of the 458-megabase draft genome of Lucilia cuprina. Analyses of this genome and the 14,544 predicted protein-encoding genes provide unique insights into the fly's molecular biology, interactions with the host animal and insecticide resistance. These insights have broad implications for designing new methods for the prevention and control of myiasis.
Keywords: Animals; Diptera; Female; Gene Expression Regulation; Genome, Insect; Insect Proteins; Insecticide Resistance; Insecticides; Larva; Male; Transcriptome

A massive expansion of effector genes underlies gall-formation in the wheat pest Mayetiola destructor. - Zhao, Chaoyang; Escalante, Lucio Navarro; Chen, Hang; Benatti, Thiago R; Qu, Jiaxin; Chellapilla, Sanjay; Waterhouse, Robert M; Wheeler, David; Andersson, Martin N; Bao, Riyue; Batterton, Matthew; Behura, Susanta K; et al. (Curr Biol, 2015)
Gall-forming arthropods are highly specialized herbivores that, in combination with their hosts, produce extended phenotypes with unique morphologies [1]. Many are economically important, and others have improved our understanding of ecology and adaptive radiation [2]. However, the mechanisms that these arthropods use to induce plant galls are poorly understood. We sequenced the genome of the Hessian fly (Mayetiola destructor; Diptera: Cecidomyiidae), a plant parasitic gall midge and a pest of wheat (Triticum spp.), with the aim of identifying genic modifications that contribute to its plant-parasitic lifestyle. Among several adaptive modifications, we discovered an expansive reservoir of potential effector proteins. Nearly 5% of the 20,163 predicted gene models matched putative effector gene transcripts present in the M. destructor larval salivary gland. Another 466 putative effectors were discovered among the genes that have no sequence similarities in other organisms. The largest known arthropod gene family (family SSGP-71) was also discovered within the effector reservoir. SSGP-71 proteins lack sequence homologies to other proteins, but their structures resemble both ubiquitin E3 ligases in plants and E3-ligase-mimicking effectors in plant pathogenic bacteria. SSGP-71 proteins and wheat Skp proteins interact in vivo. Mutations in different SSGP-71 genes avoid the effector-triggered immunity that is directed by the wheat resistance genes H6 and H9. Results point to effectors as the agents responsible for arthropod-induced plant gall formation.
Keywords: Adaptation, Biological; Amino Acid Sequence; Animals; Base Sequence; Chromosomes; Diptera; Larva; Models, Genetic; Molecular Sequence Data; Multigene Family; Phylogeny; Plant Tumors; Sequence Analysis, DNA; Sequence Homology; Sexual Behavior, Animal; Triticum; Two-Hybrid System Techniques; Ubiquitin-Protein Ligases

The Matchmaker Exchange: a platform for rare disease gene discovery. - Philippakis, Anthony A; Azzariti, Danielle R; Beltran, Sergi; Brookes, Anthony J; Brownstein, Catherine A; Brudno, Michael; Brunner, Han G; Buske, Orion J; Carey, Knox; Doll, Cassie; Dumitriu, Sergiu; Dyke, Stephanie O M; et al. (Hum Mutat, 2015)
There are few better examples of the need for data sharing than in the rare disease community, where patients, physicians, and researchers must search for "the needle in a haystack" to uncover rare, novel causes of disease within the genome. Impeding the pace of discovery has been the existence of many small siloed datasets within individual research or clinical laboratory databases and/or disease-specific organizations, hoping for serendipitous occasions when two distant investigators happen to learn they have a rare phenotype in common and can "match" these cases to build evidence for causality. However, serendipity has never proven to be a reliable or scalable approach in science. As such, the Matchmaker Exchange (MME) was launched to provide a robust and systematic approach to rare disease gene discovery through the creation of a federated network connecting databases of genotypes and rare phenotypes using a common application programming interface (API). The core building blocks of the MME have been defined and assembled. Three MME services have now been connected through the API and are available for community use. Additional databases that support internal matching are anticipated to join the MME network as it continues to grow.
Keywords: Database Management Systems; Databases, Genetic; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Information Dissemination; Rare Diseases; Software

Mutations in PNPLA6 are linked to photoreceptor degeneration and various forms of childhood blindness. - Kmoch, S; Majewski, J; Ramamurthy, V; Cao, S; Fahiminiya, S; Ren, H; MacDonald, I M; Lopez, I; Sun, V; Keser, V; Khan, A; Stránecký, V; et al. (Nat Commun, 2015)
Blindness due to retinal degeneration affects millions of people worldwide, but many disease-causing mutations remain unknown. PNPLA6 encodes the patatin-like phospholipase domain containing protein 6, also known as neuropathy target esterase (NTE), which is the target of toxic organophosphates that induce human paralysis due to severe axonopathy of large neurons. Mutations in PNPLA6 also cause human spastic paraplegia characterized by motor neuron degeneration. Here we identify PNPLA6 mutations in childhood blindness in seven families with retinal degeneration, including Leber congenital amaurosis and Oliver McFarlane syndrome. PNPLA6 localizes mostly at the inner segment plasma membrane in photoreceptors and mutations in Drosophila PNPLA6 lead to photoreceptor cell death. We also report that lysophosphatidylcholine and lysophosphatidic acid levels are elevated in mutant Drosophila. These findings show a role for PNPLA6 in photoreceptor survival and identify phospholipid metabolism as a potential therapeutic target for some forms of blindness.
Keywords: Amino Acid Sequence; Animals; Blindness; Child; Child, Preschool; Drosophila; Female; Humans; Male; Mice; Mice, Inbred C57BL; Microscopy, Fluorescence; Molecular Sequence Data; Mutation; Pedigree; Phenotype; Phospholipases; Phospholipids; Retina; Retinal Degeneration; Sequence Analysis, DNA; Sequence Homology, Amino Acid; Spectrometry, Mass, Electrospray Ionization

New mutations in the RAB28 gene in 2 Spanish families with cone-rod dystrophy. - Riveiro-Álvarez, Rosa; Xie, Yajing Angela; López-Martínez, Miguel-Ángel; Gambin, Tomasz; Pérez-Carro, Raquel; Ávila-Fernández, Almudena; López-Molina, María-Isabel; Zernant, Jana; Jhangiani, Shalini; Muzny, Donna; Yuan, Bo; Boerwinkle, Eric; et al. (JAMA Ophthalmol, 2015)
IMPORTANCE: The families evaluated in this study represent the second report of cone-rod dystrophy (CRD) cases caused by mutations in RAB28, a recently discovered gene associated with CRD. OBJECTIVE: To determine the disease-causing gene in 2 families of Spanish descent presenting with CRD who do not have ABCA4 mutations. DESIGN, SETTING, AND PARTICIPANTS: Molecular genetics and observational case studies of 2 families, each with 1 affected proband with CRD and 3 or 5 unaffected family members. The affected individual from each family received a complete ophthalmic examination including assessment of refractive errors and best-corrected visual acuity, biomicroscopy, color fundus photography, electroretinography analysis, and visual-evoked potential analysis. After complete sequencing of the ABCA4 gene with negative results, the screening for disease-causing mutations was performed by whole-exome sequencing. Possible disease-associated variants were determined by filtering based on minor allele frequency, predicted pathogenicity, and segregation analysis in all family members. MAIN OUTCOMES AND MEASURES: The appearance of the macula was evaluated by clinical examination, fundus photography, and fundus autofluorescence imaging, and visual function was assessed by electroretinography. Disease-causing mutations were assessed by sequence analyses. RESULTS: Ophthalmologic findings included markedly reduced visual acuity, bull's eye maculopathy, foveal hyperpigmentation, peripapillary atrophy, dyschromatopsia, extinguished photopic responses, and reduced scotopic responses observed on electroretinography consistent with the CRD phenotype often associated with ABCA4 mutations. Although no ABCA4 mutations were detected in either patient, whole-exome sequencing analysis identified 2 new homozygous mutations in the recently described RAB28 gene, the c.172 + 1G>C splice site variant in IVS2 and the missense c.T651G:p.C217W substitution. Both variants were determined as deleterious by predictive programs and were segregated with the disease in both families. Sequencing of 107 additional patients of Spanish descent with CRD did not reveal other cases with RAB28 mutations. CONCLUSIONS AND RELEVANCE: Deleterious mutations in RAB28 result in a classic CRD phenotype and are an infrequent cause of CRD in the Spanish population.
Keywords: Adolescent; Adult; Child; Diagnosis, Differential; DNA Mutational Analysis; Female; Follow-Up Studies; Genetic Predisposition to Disease; Hispanic or Latino; Humans; Male; Microscopy, Acoustic; Mutation; Pedigree; Phenotype; rab GTP-Binding Proteins; Retinitis Pigmentosa; Retrospective Studies; Young Adult

Next-generation sequencing and novel variant determination in a cohort of 92 familial exudative vitreoretinopathy patients. - Salvo, Jason; Lyubasyuk, Vera; Xu, Mingchu; Wang, Hui; Wang, Feng; Nguyen, Duy; Wang, Keqing; Luo, Hongrong; Wen, Cindy; Shi, Catherine; Lin, Danni; Zhang, Kang; et al. (Invest Ophthalmol Vis Sci, 2015)
PURPOSE: Familial exudative vitreoretinopathy (FEVR) is a developmental disease that can cause visual impairment and retinal detachment at a young age. Four genes involved in the Wnt signaling pathway were previously linked to this disease: NDP, FDZ4, LRP5, and TSPAN12. Identification of novel disease-causing alleles allows for a deeper understanding of the disease, better molecular diagnosis, and improved treatment. METHODS: Sequencing libraries from 92 FEVR patients were generated using a custom capture panel to enrich for 163 known retinal disease-causing genes in humans. Samples were processed using next generation sequencing (NGS) techniques followed by data analysis to identify and classify single nucleotide variants and small insertions and deletions. Sanger validation and segregation testing were used to verify suspected variants. RESULTS: Of the cohort of 92, 45 patients were potentially solved (48.9%). Solved cases resulted from the determination of 49 unique mutations, 41 of which are novel. Of the novel variants discovered, 13 were highly likely to cause FEVR due to the nature of these variants (frameshifting indels, splicing mutations, and nonsense variants types). To our knowledge, this is the largest study of a FEVR cohort using NGS. CONCLUSIONS: We were able to determine probable disease-causing variants in a large number of FEVR patients, the majority of which were novel. Knowledge of these variants will help to further characterize and diagnose FEVR.
Keywords: Cohort Studies; DNA Mutational Analysis; DNA-Binding Proteins; Eye Diseases, Hereditary; Eye Proteins; Familial Exudative Vitreoretinopathies; Female; Frizzled Receptors; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Low Density Lipoprotein Receptor-Related Protein-5; Male; Mutation; Nerve Tissue Proteins; Retinal Diseases; Sequence Analysis, DNA; Tetraspanins; Transcription Factors

Non-coding genetic variants in human disease. - Zhang, Feng; Lupski, James R (Hum Mol Genet, 2015)
Genetic variants, including single-nucleotide variants (SNVs) and copy number variants (CNVs), in the non-coding regions of the human genome can play an important role in human traits and complex diseases. Most of the genome-wide association study (GWAS) signals map to non-coding regions and potentially point to non-coding variants, whereas their functional interpretation is challenging. In this review, we discuss the human non-coding variants and their contributions to human diseases in the following four parts. (i) Functional annotations of non-coding SNPs mapped by GWAS: we discuss recent progress revealing some of the molecular mechanisms for GWAS signals affecting gene function. (ii) Technical progress in interpretation of non-coding variants: we briefly describe some of the technologies for functional annotations of non-coding variants, including the methods for genome-wide mapping of chromatin interaction, computational tools for functional predictions and the new genome editing technologies useful for dissecting potential functional consequences of non-coding variants. (iii) Non-coding CNVs in human diseases: we review our emerging understanding the role of non-coding CNVs in human disease. (iv) Compound inheritance of large genomic deletions and non-coding variants: compound inheritance at a locus consisting of coding variants plus non-coding ones is described.
Keywords: Animals; Disease; DNA Copy Number Variations; Genetic Variation; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Regulatory Sequences, Nucleic Acid

Pediatric Cancer Genetics Research and an Evolving Preventive Ethics Approach for Return of Results after Death of the Subject. - Scollon, Sarah; Bergstrom, Katie; McCullough, Laurence B; McGuire, Amy L; Gutierrez, Stephanie; Kerstein, Robin; Parsons, D Williams; Plon, Sharon E (J Law Med Ethics, 2015)
The return of genetic research results after death in the pediatric setting comes with unique complexities. Researchers must determine which results and through which processes results are returned. This paper discusses the experience over 15 years in pediatric cancer genetics research of returning research results after the death of a child and proposes a preventive ethics approach to protocol development in order to improve the quality of return of results in pediatric genomic settings.
Keywords: Adult; Child; Child, Preschool; Death; Disclosure; Genetic Research; Genomics; Humans; Neoplasms; Research Subjects

Population genomic analysis of 962 whole genome sequences of humans reveals natural selection in non-coding regions. - Yu, Fuli; Lu, Jian; Liu, Xiaoming; Gazave, Elodie; Chang, Diana; Raj, Srilakshmi; Hunter-Zinck, Haley; Blekhman, Ran; Arbiza, Leonardo; Van Hout, Cris; Morrison, Alanna; Johnson, Andrew D; et al. (PLoS One, 2015)
Whole genome analysis in large samples from a single population is needed to provide adequate power to assess relative strengths of natural selection across different functional components of the genome. In this study, we analyzed next-generation sequencing data from 962 European Americans, and found that as expected approximately 60% of the top 1% of positive selection signals lie in intergenic regions, 33% in intronic regions, and slightly over 1% in coding regions. Several detailed functional annotation categories in intergenic regions showed statistically significant enrichment in positively selected loci when compared to the null distribution of the genomic span of ENCODE categories. There was a significant enrichment of purifying selection signals detected in enhancers, transcription factor binding sites, microRNAs and target sites, but not on lincRNA or piRNAs, suggesting different evolutionary constraints for these domains. Loci in "repressed or low activity regions" and loci near or overlapping the transcription start site were the most significantly over-represented annotations among the top 1% of signals for positive selection.
Keywords: DNA, Intergenic; Genetic Loci; Humans; Metagenomics; Open Reading Frames; Polymorphism, Single Nucleotide

Rise and fall of subclones from diagnosis to relapse in pediatric B-acute lymphoblastic leukaemia. - Ma, Xiaotu; Edmonson, Michael; Yergeau, Donald; Muzny, Donna M; Hampton, Oliver A; Rusch, Michael; Song, Guangchun; Easton, John; Harvey, Richard C; Wheeler, David A; Ma, Jing; Doddapaneni, Harshavardhan; et al. (Nat Commun, 2015)
There is incomplete understanding of genetic heterogeneity and clonal evolution during cancer progression. Here we use deep whole-exome sequencing to describe the clonal architecture and evolution of 20 pediatric B-acute lymphoblastic leukaemias from diagnosis to relapse. We show that clonal diversity is comparable at diagnosis and relapse and clonal survival from diagnosis to relapse is not associated with mutation burden. Six pathways were frequently mutated, with NT5C2, CREBBP, WHSC1, TP53, USH2A, NRAS and IKZF1 mutations enriched at relapse. Half of the leukaemias had multiple subclonal mutations in a pathway or gene at diagnosis, but mostly with only one, usually minor clone, surviving therapy to acquire additional mutations and become the relapse founder clone. Relapse-specific mutations in NT5C2 were found in nine cases, with mutations in four cases being in descendants of the relapse founder clone. These results provide important insights into the genetic basis of treatment failure in ALL and have implications for the early detection of mutations driving relapse.
Keywords: 5'-Nucleotidase; Child; Clonal Evolution; Clone Cells; CREB-Binding Protein; Disease Progression; DNA Copy Number Variations; Exome; Extracellular Matrix Proteins; Female; GTP Phosphohydrolases; Histone-Lysine N-Methyltransferase; Humans; Ikaros Transcription Factor; Male; Membrane Proteins; Mutation; Neoplasm Recurrence, Local; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Repressor Proteins; Tumor Suppressor Protein p53

Roger et al. respond to "future of population studies". - Roger, Véronique L; Boerwinkle, Eric; Crapo, James D; Douglas, Pamela S; Epstein, Jonathan A; Granger, Christopher B; Greenland, Philip; Kohane, Isaac; Psaty, Bruce M (Am J Epidemiol, 2015)
Keywords: Data Collection; Epidemiologic Research Design; Epidemiologic Studies; Humans; Research

Spata7 is a retinal ciliopathy gene critical for correct RPGRIP1 localization and protein trafficking in the retina. - Eblimit, Aiden; Nguyen, Thanh-Minh T; Chen, Yiyun; Esteve-Rudd, Julian; Zhong, Hua; Letteboer, Stef; van Reeuwijk, Jeroen; Simons, David L; Ding, Qian; Wu, Ka Man; Li, Yumei; Van Beersum, Sylvia; et al. (Hum Mol Genet, 2015)
Leber congenital amaurosis (LCA) and juvenile retinitis pigmentosa (RP) are severe hereditary diseases that causes visual impairment in infants and children. SPATA7 has recently been identified as the LCA3 and juvenile RP gene in humans, whose function in the retina remains elusive. Here, we show that SPATA7 localizes at the primary cilium of cells and at the connecting cilium (CC) of photoreceptor cells, indicating that SPATA7 is a ciliary protein. In addition, SPATA7 directly interacts with the retinitis pigmentosa GTPase regulator interacting protein 1 (RPGRIP1), a key connecting cilium protein that has also been linked to LCA. In the retina of Spata7 null mutant mice, a substantial reduction of RPGRIP1 levels at the CC of photoreceptor cells is observed, suggesting that SPATA7 is required for the stable assembly and localization of the ciliary RPGRIP1 protein complex. Furthermore, our results pinpoint a role of this complex in protein trafficking across the CC to the outer segments, as we identified that rhodopsin accumulates in the inner segments and around the nucleus of photoreceptors. This accumulation then likely triggers the apoptosis of rod photoreceptors that was observed. Loss of Spata7 function in mice indeed results in a juvenile RP-like phenotype, characterized by progressive degeneration of photoreceptor cells and a strongly decreased light response. Together, these results indicate that SPATA7 functions as a key member of a retinal ciliopathy-associated protein complex, and that apoptosis of rod photoreceptor cells triggered by protein mislocalization is likely the mechanism of disease progression in LCA3/ juvenile RP patients.
Keywords: Animals; Apoptosis; Cattle; Cytoskeletal Proteins; DNA-Binding Proteins; Gene Deletion; Humans; Mice; Mice, Mutant Strains; Photoreceptor Connecting Cilium; Protein Transport; Proteins; Retinal Cone Photoreceptor Cells; Retinal Rod Photoreceptor Cells; Rhodopsin

Structure and function of the healthy pre-adolescent pediatric gut microbiome. - Hollister, Emily B; Riehle, Kevin; Luna, Ruth Ann; Weidler, Erica M; Rubio-Gonzales, Michelle; Mistretta, Toni-Ann; Raza, Sabeen; Doddapaneni, Harsha V; Metcalf, Ginger A; Muzny, Donna M; Gibbs, Richard A; Petrosino, Joseph F; et al. (Microbiome, 2015)
BACKGROUND: The gut microbiome influences myriad host functions, including nutrient acquisition, immune modulation, brain development, and behavior. Although human gut microbiota are recognized to change as we age, information regarding the structure and function of the gut microbiome during childhood is limited. Using 16S rRNA gene and shotgun metagenomic sequencing, we characterized the structure, function, and variation of the healthy pediatric gut microbiome in a cohort of school-aged, pre-adolescent children (ages 7-12 years). We compared the healthy pediatric gut microbiome with that of healthy adults previously recruited from the same region (Houston, TX, USA). RESULTS: Although healthy children and adults harbored similar numbers of taxa and functional genes, their composition and functional potential differed significantly. Children were enriched in Bifidobacterium spp., Faecalibacterium spp., and members of the Lachnospiraceae, while adults harbored greater abundances of Bacteroides spp. From a functional perspective, significant differences were detected with respect to the relative abundances of genes involved in vitamin synthesis, amino acid degradation, oxidative phosphorylation, and triggering mucosal inflammation. Children's gut communities were enriched in functions which may support ongoing development, while adult communities were enriched in functions associated with inflammation, obesity, and increased risk of adiposity. CONCLUSIONS: Previous studies suggest that the human gut microbiome is relatively stable and adult-like after the first 1 to 3 years of life. Our results suggest that the healthy pediatric gut microbiome harbors compositional and functional qualities that differ from those of healthy adults and that the gut microbiome may undergo a more prolonged development than previously suspected.
Keywords: Adult; Age Factors; Biodiversity; Child; Cluster Analysis; DNA Barcoding, Taxonomic; Female; Gastrointestinal Microbiome; Healthy Volunteers; Humans; Male; Metagenome; RNA, Ribosomal, 16S

TET2 and CSMD1 genes affect SBP response to hydrochlorothiazide in never-treated essential hypertensives. - Chittani, Martina; Zaninello, Roberta; Lanzani, Chiara; Frau, Francesca; Ortu, Maria F; Salvi, Erika; Fresu, Giovanni; Citterio, Lorena; Braga, Daniele; Piras, Daniela A; Carpini, Simona Delli; Velayutham, Dinesh; et al. (J Hypertens, 2015)
BACKGROUND: Thiazide diuretics have been recommended as a first-line antihypertensive treatment, although the choice of 'the right drug in the individual essential hypertensive patient' remains still empirical. Essential hypertension is a complex, polygenic disease derived from the interaction of patient's genetic background with the environment. Pharmacogenomics could be a useful tool to pinpoint gene variants involved in antihypertensive drug response, thus optimizing therapeutic advantages and minimizing side effects. METHODS AND RESULTS: We looked for variants associated with blood pressure response to hydrochlorothiazide over an 8-week follow-up by means of a genome-wide association analysis in two Italian cohorts of never-treated essential hypertensive patients: 343 samples from Sardinia and 142 from Milan. TET2 and CSMD1 as plausible candidate genes to affect SBP response to hydrochlorothiazide were identified. The specificity of our findings for hydrochlorothiazide was confirmed in an independent cohort of essential hypertensive patients treated with losartan. Our best findings were also tested for replication in four independent hypertensive samples of European Ancestry, such as GENetics of drug RESponsiveness in essential hypertension, Genetic Epidemiology of Responses to Antihypertensives, NORdic DILtiazem intervention, Pharmacogenomics Evaluation of Antihypertensive Responses, and Campania Salute Network-StayOnDiur. We validated a polymorphism in CSMD1 and UGGT2. CONCLUSION: This exploratory study reports two plausible loci associated with SBP response to hydrochlorothiazide: TET2, an aldosterone-responsive mediator of αENaC gene transcription; and CSMD1, previously described as associated with hypertension in a case-control study.
Keywords: Adult; Aged; Aldosterone; Antihypertensive Agents; Blood Pressure; Case-Control Studies; Dioxygenases; DNA-Binding Proteins; Essential Hypertension; Genome-Wide Association Study; Humans; Hydrochlorothiazide; Hypertension; Italy; Losartan; Male; Membrane Proteins; Middle Aged; Pharmacogenetics; Proto-Oncogene Proteins; Sodium Chloride Symporter Inhibitors; Systole; Tumor Suppressor Proteins; White People

Tissue-specific transcriptome sequencing analysis expands the non-human primate reference transcriptome resource (NHPRTR). - Peng, Xinxia; Thierry-Mieg, Jean; Thierry-Mieg, Danielle; Nishida, Andrew; Pipes, Lenore; Bozinoski, Marjan; Thomas, Matthew J; Kelly, Sara; Weiss, Jeffrey M; Raveendran, Muthuswamy; Muzny, Donna; Gibbs, Richard A; et al. (Nucleic Acids Res, 2015)
The non-human primate reference transcriptome resource (NHPRTR, available online at http://nhprtr.org/) aims to generate comprehensive RNA-seq data from a wide variety of non-human primates (NHPs), from lemurs to hominids. In the 2012 Phase I of the NHPRTR project, 19 billion fragments or 3.8 terabases of transcriptome sequences were collected from pools of ∼ 20 tissues in 15 species and subspecies. Here we describe a major expansion of NHPRTR by adding 10.1 billion fragments of tissue-specific RNA-seq data. For this effort, we selected 11 of the original 15 NHP species and subspecies and constructed total RNA libraries for the same ∼ 15 tissues in each. The sequence quality is such that 88% of the reads align to human reference sequences, allowing us to compute the full list of expression abundance across all tissues for each species, using the reads mapped to human genes. This update also includes improved transcript annotations derived from RNA-seq data for rhesus and cynomolgus macaques, two of the most commonly used NHP models and additional RNA-seq data compiled from related projects. Together, these comprehensive reference transcriptomes from multiple primates serve as a valuable community resource for genome annotation, gene dynamics and comparative functional analysis.
Keywords: Animals; Databases, Genetic; Gene Expression Profiling; Internet; Macaca; Molecular Sequence Annotation; Organ Specificity; Primates; Reference Standards; Sequence Alignment; Sequence Analysis, RNA

The Alu-rich genomic architecture of SPAST predisposes to diverse and functionally distinct disease-associated CNV alleles. - Boone, Philip M; Bo Yuan; Campbell, Ian M; Scull, Jennifer C; Withers, Marjorie A; Baggett, Brett C; Beck, Christine R; Shaw, Christine J; Stankiewicz, Pawel; Moretti, Paolo; Goodwin, Wendy E; Hein, Nichole; et al. (Am J Hum Genet, 2014)
Intragenic copy-number variants (CNVs) contribute to the allelic spectrum of both Mendelian and complex disorders. Although pathogenic deletions and duplications in SPAST (mutations in which cause autosomal-dominant spastic paraplegia 4 [SPG4]) have been described, their origins and molecular consequences remain obscure. We mapped breakpoint junctions of 54 SPAST CNVs at nucleotide resolution. Diverse combinations of exons are deleted or duplicated, highlighting the importance of particular exons for spastin function. Of the 54 CNVs, 38 (70%) appear to be mediated by an Alu-based mechanism, suggesting that the Alu-rich genomic architecture of SPAST renders this locus susceptible to various genome rearrangements. Analysis of breakpoint Alus further informs a model of Alu-mediated CNV formation characterized by small CNV size and potential involvement of mechanisms other than homologous recombination. Twelve deletions (22%) overlap part of SPAST and a portion of a nearby, directly oriented gene, predicting novel chimeric genes in these subjects' genomes. cDNA from a subject with a SPAST final exon deletion contained multiple SPAST:SLC30A6 fusion transcripts, indicating that SPAST CNVs can have transcriptional effects beyond the gene itself. SLC30A6 has been implicated in Alzheimer disease, so these fusion gene data could explain a report of spastic paraplegia and dementia cosegregating in a family with deletion of the final exon of SPAST. Our findings provide evidence that the Alu genomic architecture of SPAST predisposes to diverse CNV alleles with distinct transcriptional--and possibly phenotypic--consequences. Moreover, we provide further mechanistic insights into Alu-mediated copy-number change that are extendable to other loci.
Keywords: Adenosine Triphosphatases; Alu Elements; Base Sequence; Cation Transport Proteins; Cell Line, Transformed; DNA Copy Number Variations; Genotype; Humans; Protein Isoforms; Recombinant Fusion Proteins; Sequence Analysis, DNA; Sequence Deletion; Spastic Paraplegia, Hereditary; Spastin

Association of levels of fasting glucose and insulin with rare variants at the chromosome 11p11.2-MADD locus: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Cornes, Belinda K; Brody, Jennifer A; Nikpoor, Naghmeh; Morrison, Alanna C; Chu, Huan; Ahn, Byung Soo; Wang, Shuai; Dauriz, Marco; Barzilay, Joshua I; Dupuis, Josée; Florez, Jose C; Coresh, Josef; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Common variation at the 11p11.2 locus, encompassing MADD, ACP2, NR1H3, MYBPC3, and SPI1, has been associated in genome-wide association studies with fasting glucose and insulin (FI). In the Cohorts for Heart and Aging Research in Genomic Epidemiology Targeted Sequencing Study, we sequenced 5 gene regions at 11p11.2 to identify rare, potentially functional variants influencing fasting glucose or FI levels. METHODS AND RESULTS: Sequencing (mean depth, 38×) across 16.1 kb in 3566 individuals without diabetes mellitus identified 653 variants, 79.9% of which were rare (minor allele frequency <1%) and novel. We analyzed rare variants in 5 gene regions with FI or fasting glucose using the sequence kernel association test. At NR1H3, 53 rare variants were jointly associated with FI (P=2.73×10(-3)); of these, 7 were predicted to have regulatory function and showed association with FI (P=1.28×10(-3)). Conditioning on 2 previously associated variants at MADD (rs7944584, rs10838687) did not attenuate this association, suggesting that there are >2 independent signals at 11p11.2. One predicted regulatory variant, chr11:47227430 (hg18; minor allele frequency=0.00068), contributed 20.6% to the overall sequence kernel association test score at NR1H3, lies in intron 2 of NR1H3, and is a predicted binding site for forkhead box A1 (FOXA1), a transcription factor associated with insulin regulation. In human HepG2 hepatoma cells, the rare chr11:47227430 A allele disrupted FOXA1 binding and reduced FOXA1-dependent transcriptional activity. CONCLUSIONS: Sequencing at 11p11.2-NR1H3 identified rare variation associated with FI. One variant, chr11:47227430, seems to be functional, with the rare A allele reducing transcription factor FOXA1 binding and FOXA1-dependent transcriptional activity.
Keywords: Aged; Aged, 80 and over; Aging; Blood Glucose; Chromosomes, Human, Pair 11; Cohort Studies; Death Domain Receptor Signaling Adaptor Proteins; Diabetes Mellitus, Type 2; Fasting; Female; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Genomics; Guanine Nucleotide Exchange Factors; Heart Diseases; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Blood lead concentrations in Jamaican children with and without autism spectrum disorder. - Rahbar, Mohammad H; Samms-Vaughan, Maureen; Dickerson, Aisha S; Loveland, Katherine A; Ardjomand-Hessabi, Manouchehr; Bressler, Jan; Shakespeare-Pellington, Sydonnie; Grove, Megan L; Pearson, Deborah A; Boerwinkle, Eric (Int J Environ Res Public Health, 2014)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder manifesting by early childhood. Lead is a toxic metal shown to cause neurodevelopmental disorders in children. Several studies have investigated the possible association between exposure to lead and ASD, but their findings are conflicting. Using data from 100 ASD cases (2-8 years of age) and their age- and sex-matched typically developing controls, we investigated the association between blood lead concentrations (BLC) and ASD in Jamaican children. We administered a questionnaire to assess demographic and socioeconomic information as well as exposure to potential lead sources. We used General Linear Models (GLM) to assess the association of BLC with ASD status as well as with sources of exposure to lead. In univariable GLM, we found a significant difference between geometric mean blood lead concentrations of ASD cases and controls (2.25 μg/dL cases vs. 2.73 μg/dL controls, p < 0.05). However, after controlling for potential confounders, there were no significant differences between adjusted geometric mean blood lead concentrations of ASD cases and controls (2.55 μg/dL vs. 2.72 μg/dL, p = 0.64). Our results do not support an association between BLC and ASD in Jamaican children. We have identified significant confounders when assessing an association between ASD and BLC.
Keywords: Case-Control Studies; Child; Child Development Disorders, Pervasive; Child, Preschool; Diet; Environmental Pollutants; Female; Humans; Jamaica; Lead; Male; Socioeconomic Factors; Surveys and Questionnaires

Characterization of HPV and host genome interactions in primary head and neck cancers. - Parfenov, Michael; Pedamallu, Chandra Sekhar; Gehlenborg, Nils; Freeman, Samuel S; Danilova, Ludmila; Bristow, Christopher A; Lee, Semin; Hadjipanayis, Angela G; Ivanova, Elena V; Wilkerson, Matthew D; Protopopov, Alexei; Yang, Lixing; et al. (Proc Natl Acad Sci U S A, 2014)
Previous studies have established that a subset of head and neck tumors contains human papillomavirus (HPV) sequences and that HPV-driven head and neck cancers display distinct biological and clinical features. HPV is known to drive cancer by the actions of the E6 and E7 oncoproteins, but the molecular architecture of HPV infection and its interaction with the host genome in head and neck cancers have not been comprehensively described. We profiled a cohort of 279 head and neck cancers with next generation RNA and DNA sequencing and show that 35 (12.5%) tumors displayed evidence of high-risk HPV types 16, 33, or 35. Twenty-five cases had integration of the viral genome into one or more locations in the human genome with statistical enrichment for genic regions. Integrations had a marked impact on the human genome and were associated with alterations in DNA copy number, mRNA transcript abundance and splicing, and both inter- and intrachromosomal rearrangements. Many of these events involved genes with documented roles in cancer. Cancers with integrated vs. nonintegrated HPV displayed different patterns of DNA methylation and both human and viral gene expressions. Together, these data provide insight into the mechanisms by which HPV interacts with the human genome beyond expression of viral oncoproteins and suggest that specific integration events are an integral component of viral oncogenesis.
Keywords: Base Sequence; DNA Methylation; Gene Expression Regulation, Neoplastic; Genes, Neoplasm; Genome, Human; Head and Neck Neoplasms; Host-Pathogen Interactions; Humans; Molecular Sequence Data; Papillomaviridae; Virus Integration

Comparative validation of the D. melanogaster modENCODE transcriptome annotation. - Chen, Zhen-Xia; Sturgill, David; Qu, Jiaxin; Jiang, Huaiyang; Park, Soo; Boley, Nathan; Suzuki, Ana Maria; Fletcher, Anthony R; Plachetzki, David C; FitzGerald, Peter C; Artieri, Carlo G; Atallah, Joel; et al. (Genome Res, 2014)
Accurate gene model annotation of reference genomes is critical for making them useful. The modENCODE project has improved the D. melanogaster genome annotation by using deep and diverse high-throughput data. Since transcriptional activity that has been evolutionarily conserved is likely to have an advantageous function, we have performed large-scale interspecific comparisons to increase confidence in predicted annotations. To support comparative genomics, we filled in divergence gaps in the Drosophila phylogeny by generating draft genomes for eight new species. For comparative transcriptome analysis, we generated mRNA expression profiles on 81 samples from multiple tissues and developmental stages of 15 Drosophila species, and we performed cap analysis of gene expression in D. melanogaster and D. pseudoobscura. We also describe conservation of four distinct core promoter structures composed of combinations of elements at three positions. Overall, each type of genomic feature shows a characteristic divergence rate relative to neutral models, highlighting the value of multispecies alignment in annotating a target genome that should prove useful in the annotation of other high priority genomes, especially human and other mammalian genomes that are rich in noncoding sequences. We report that the vast majority of elements in the annotation are evolutionarily conserved, indicating that the annotation will be an important springboard for functional genetic testing by the Drosophila community.
Keywords: Animals; Cluster Analysis; Computational Biology; Drosophila melanogaster; Evolution, Molecular; Exons; Female; Gene Expression Profiling; Genome, Insect; Humans; Male; Molecular Sequence Annotation; Nucleotide Motifs; Phylogeny; Position-Specific Scoring Matrices; Promoter Regions, Genetic; Reproducibility of Results; RNA Editing; RNA Splice Sites; RNA Splicing; Transcription Initiation Site; Transcriptome

De novo truncating mutations in AHDC1 in individuals with syndromic expressive language delay, hypotonia, and sleep apnea. - Xia, Fan; Bainbridge, Matthew N; Tan, Tiong Yang; Wangler, Michael F; Scheuerle, Angela E; Zackai, Elaine H; Harr, Margaret H; Sutton, V Reid; Nalam, Roopa L; Zhu, Wenmiao; Nash, Margot; Ryan, Monique M; et al. (Am J Hum Genet, 2014)
Clinical whole-exome sequencing (WES) for identification of mutations leading to Mendelian disease has been offered to the medical community since 2011. Clinically undiagnosed neurological disorders are the most frequent basis for test referral, and currently, approximately 25% of such cases are diagnosed at the molecular level. To date, there are approximately 4,000 "known" disease-associated loci, and many are associated with striking dysmorphic features, making genotype-phenotype correlations relatively straightforward. A significant fraction of cases, however, lack characteristic dysmorphism or clinical pathognomonic traits and are dependent upon molecular tests for definitive diagnoses. Further, many molecular diagnoses are guided by recent gene-disease association discoveries. Hence, there is a critical interplay between clinical testing and research leading to gene-disease association discovery. Here, we describe four probands, all of whom presented with hypotonia, intellectual disability, global developmental delay, and mildly dysmorphic facial features. Three of the four also had sleep apnea. Each was a simplex case without a remarkable family history. Using WES, we identified AHDC1 de novo truncating mutations that most likely cause this genetic syndrome.
Keywords: Child; Child, Preschool; DNA-Binding Proteins; Exome; Female; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Muscle Hypotonia; Mutation; Sleep Apnea Syndromes; Syndrome

Design and anticipated outcomes of the eMERGE-PGx project: a multicenter pilot for preemptive pharmacogenomics in electronic health record systems. - Rasmussen-Torvik, L J; Stallings, S C; Gordon, A S; Almoguera, B; Basford, M A; Bielinski, S J; Brautbar, A; Brilliant, M H; Carrell, D S; Connolly, J J; Crosslin, D R; Doheny, K F; et al. (Clin Pharmacol Ther, 2014)
We describe here the design and initial implementation of the eMERGE-PGx project. eMERGE-PGx, a partnership of the Electronic Medical Records and Genomics Network and the Pharmacogenomics Research Network, has three objectives: (i) to deploy PGRNseq, a next-generation sequencing platform assessing sequence variation in 84 proposed pharmacogenes, in nearly 9,000 patients likely to be prescribed drugs of interest in a 1- to 3-year time frame across several clinical sites; (ii) to integrate well-established clinically validated pharmacogenetic genotypes into the electronic health record with associated clinical decision support and to assess process and clinical outcomes of implementation; and (iii) to develop a repository of pharmacogenetic variants of unknown significance linked to a repository of electronic health record-based clinical phenotype data for ongoing pharmacogenomics discovery. We describe site-specific project implementation and anticipated products, including genetic variant and phenotype data repositories, novel variant association studies, clinical decision support modules, clinical and process outcomes, approaches to managing incidental findings, and patient and clinician education methods.
Keywords: Adolescent; Aged; Child; Databases, Genetic; Drug Therapy; Electronic Health Records; Female; Genetic Association Studies; Genetic Variation; Genotype; Humans; Knowledge Bases; Male; Middle Aged; Pharmacogenetics; Phenotype; Pilot Projects; Sequence Analysis, DNA; Young Adult

Drosophila eyes absent is required for normal cone and pigment cell development. - Karandikar, Umesh C; Jin, Meng; Jusiak, Barbara; Kwak, SuJin; Chen, Rui; Mardon, Graeme (PLoS One, 2014)
In Drosophila, development of the compound eye is orchestrated by a network of highly conserved transcriptional regulators known as the retinal determination (RD) network. The retinal determination gene eyes absent (eya) is expressed in most cells within the developing eye field, from undifferentiated retinal progenitors to photoreceptor cells whose differentiation begins at the morphogenetic furrow (MF). Loss of eya expression leads to an early block in retinal development, making it impossible to study the role of eya expression during later steps of retinal differentiation. We have identified two new regulatory regions that control eya expression during retinal development. These two enhancers are necessary to maintain eya expression anterior to the MF (eya-IAM) and in photoreceptors (eya-PSE), respectively. We find that deleting these enhancers affects developmental events anterior to the MF as well as retinal differentiation posterior to the MF. In line with previous results, we find that reducing eya expression anterior to the MF affects several early steps during early retinal differentiation, including cell cycle arrest and expression of the proneural gene ato. Consistent with previous observations that suggest a role for eya in cell proliferation during early development we find that deletion of eya-IAM leads to a marked reduction in the size of the adult retinal field. On the other hand, deletion of eya-PSE leads to defects in cone and pigment cell development. In addition we find that eya expression is necessary to activate expression of the cone cell marker Cut and to regulate levels of the Hedgehog pathway effector Ci. In summary, our study uncovers novel aspects of eya-mediated regulation of eye development. The genetic tools generated in this study will allow for a detailed study of how the RD network regulates key steps in eye formation.
Keywords: Animals; Basic Helix-Loop-Helix Transcription Factors; Cell Cycle Checkpoints; Cell Differentiation; DNA-Binding Proteins; Drosophila melanogaster; Drosophila Proteins; Enhancer Elements, Genetic; Eye Proteins; Gene Expression Regulation, Developmental; Homeodomain Proteins; Larva; Nerve Tissue Proteins; Nuclear Proteins; Organogenesis; Retinal Cone Photoreceptor Cells; Retinal Pigment Epithelium; Transcription Factors

A drosophila genetic resource of mutants to study mechanisms underlying human genetic diseases. - Yamamoto, Shinya; Jaiswal, Manish; Charng, Wu-Lin; Gambin, Tomasz; Karaca, Ender; Mirzaa, Ghayda; Wiszniewski, Wojciech; Sandoval, Hector; Haelterman, Nele A; Xiong, Bo; Zhang, Ke; Bayat, Vafa; et al. (Cell, 2014)
Invertebrate model systems are powerful tools for studying human disease owing to their genetic tractability and ease of screening. We conducted a mosaic genetic screen of lethal mutations on the Drosophila X chromosome to identify genes required for the development, function, and maintenance of the nervous system. We identified 165 genes, most of whose function has not been studied in vivo. In parallel, we investigated rare variant alleles in 1,929 human exomes from families with unsolved Mendelian disease. Genes that are essential in flies and have multiple human homologs were found to be likely to be associated with human diseases. Merging the human data sets with the fly genes allowed us to identify disease-associated mutations in six families and to provide insights into microcephaly associated with brain dysgenesis. This bidirectional synergism between fly genetics and human genomics facilitates the functional annotation of evolutionarily conserved genes involved in human health.
Keywords: Animals; Disease; Disease Models, Animal; Drosophila melanogaster; Genetic Testing; Humans; Inheritance Patterns; RNA Interference; X Chromosome

The effect of dietary fat intake on hepatic gene expression in LG/J AND SM/J mice. - Partridge, Charlyn G; Fawcett, Gloria L; Wang, Bing; Semenkovich, Clay F; Cheverud, James M (BMC Genomics, 2014)
BACKGROUND: The liver plays a major role in regulating metabolic homeostasis and is vital for nutrient metabolism. Identifying the genetic factors regulating these processes could lead to a greater understanding of how liver function responds to a high-fat diet and how that response may influence susceptibilities to obesity and metabolic syndrome. In this study we examine differences in hepatic gene expression between the LG/J and SM/J inbred mouse strains and how gene expression in these strains is affected by high-fat diet. LG/J and SM/J are known to differ in their responses to a high-fat diet for a variety of obesity- and diabetes-related traits, with the SM/J strain exhibiting a stronger phenotypic response to diet. RESULTS: Dietary intake had a significant effect on gene expression in both inbred lines. Genes up-regulated by a high-fat diet were involved in biological processes such as lipid and carbohydrate metabolism; protein and amino acid metabolic processes were down regulated on a high-fat diet. A total of 259 unique transcripts exhibited a significant diet-by-strain interaction. These genes tended to be associated with immune function. In addition, genes involved in biochemical processes related to non-alcoholic fatty liver disease (NAFLD) manifested different responses to diet between the two strains. For most of these genes, SM/J had a stronger response to the high-fat diet than LG/J. CONCLUSIONS: These data show that dietary fat impacts gene expression levels in SM/J relative to LG/J, with SM/J exhibiting a stronger response. This supports previous data showing that SM/J has a stronger phenotypic response to high-fat diet. Based upon these findings, we suggest that SM/J and its cross with the LG/J strain provide a good model for examining non-alcoholic fatty liver disease and its role in metabolic syndrome.
Keywords: Animals; Diabetes Mellitus; Diet, High-Fat; Down-Regulation; Female; Liver; Male; Mice; Mice, Inbred Strains; Non-alcoholic Fatty Liver Disease; Obesity; Quantitative Trait Loci; Up-Regulation

Evidence for stabilizing selection on codon usage in chromosomal rearrangements of Drosophila pseudoobscura. - Fuller, Zachary L; Haynes, Gwilym D; Zhu, Dianhui; Batterton, Matthew; Chao, Hsu; Dugan, Shannon; Javaid, Mehwish; Jayaseelan, Joy C; Lee, Sandra; Li, Mingmei; Ongeri, Fiona; Qi, Sulan; et al. (G3 (Bethesda), 2014)
There has been a renewed interest in investigating the role of stabilizing selection acting on genome-wide traits such as codon usage bias. Codon bias, when synonymous codons are used at unequal frequencies, occurs in a wide variety of taxa. Standard evolutionary models explain the maintenance of codon bias through a balance of genetic drift, mutation and weak purifying selection. The efficacy of selection is expected to be reduced in regions of suppressed recombination. Contrary to observations in Drosophila melanogaster, some recent studies have failed to detect a relationship between the recombination rate, intensity of selection acting at synonymous sites, and the magnitude of codon bias as predicted under these standard models. Here, we examined codon bias in 2798 protein coding loci on the third chromosome of D. pseudoobscura using whole-genome sequences of 47 individuals, representing five common third chromosome gene arrangements. Fine-scale recombination maps were constructed using more than 1 million segregating sites. As expected, recombination was demonstrated to be significantly suppressed between chromosome arrangements, allowing for a direct examination of the relationship between recombination, selection, and codon bias. As with other Drosophila species, we observe a strong mutational bias away from the most frequently used codons. We find the rate of synonymous and nonsynonymous polymorphism is variable between different amino acids. However, we do not observe a reduction in codon bias or the strength of selection in regions of suppressed recombination as expected. Instead, we find that the interaction between weak stabilizing selection and mutational bias likely plays a role in shaping the composition of synonymous codons across the third chromosome in D. pseudoobscura.
Keywords: Animals; Chromosomes; Codon; Drosophila; High-Throughput Nucleotide Sequencing; Polymorphism, Single Nucleotide; Recombination, Genetic; Selection, Genetic; Sequence Analysis, DNA

Exome sequencing identifies a novel homozygous mutation in the phosphate transporter SLC34A1 in hypophosphatemia and nephrocalcinosis. - Rajagopal, Abbhirami; Braslavsky, Débora; Lu, James T; Kleppe, Soledad; Clément, Florencia; Cassinelli, Hamilton; Liu, David S; Liern, Jose Miguel; Vallejo, Graciela; Bergadá, Ignacio; Gibbs, Richard A; Campeau, Phillipe M; et al. (J Clin Endocrinol Metab, 2014)
CONTEXT: Two Argentinean siblings (a boy and a girl) from a nonconsanguineous family presented with hypercalcemia, hypercalciuria, hypophosphatemia, low parathyroid hormone (PTH), and nephrocalcinosis. OBJECTIVE: The goal of this study was to identify genetic causes of the clinical findings in the two siblings. DESIGN: Whole exome sequencing was performed to identify disease-causing mutations in the youngest sibling, and a candidate variant was screened in other family members by Sanger sequencing. In vitro experiments were conducted to determine the effects of the mutation that was identified. PATIENTS AND OTHER PARTICIPANTS: Affected siblings (2 y.o. female and 10 y.o male) and their parents were included in the study. Informed consent was obtained for genetic studies. RESULTS: A novel homozygous mutation in the gene encoding the renal sodium-dependent phosphate transporter SLC34A1 was identified in both siblings (c.1484G>A, p.Arg495His). In vitro studies showed that the p.Arg495His mutation resulted in decreased phosphate uptake when compared to wild-type SLC34A1. CONCLUSIONS: The homozygous G>A transition that results in the substitution of histidine for arginine at position 495 of the renal sodium-dependent phosphate transporter, SLC34A1, is involved in disease pathogenesis in these patients. Our report of the second family with two mutated SLC34A1 alleles expands the known phenotype of this rare condition.
Keywords: Child; Child, Preschool; DNA Mutational Analysis; Exome; Female; Humans; Hypercalcemia; Hypercalciuria; Hypophosphatemia; Male; Mutation; Nephrocalcinosis; Parathyroid Hormone; Pedigree; Phenotype; Sodium-Phosphate Cotransporter Proteins, Type IIa

Exonic duplication CNV of NDRG1 associated with autosomal-recessive HMSN-Lom/CMT4D. - Okamoto, Yuji; Goksungur, Meryem Tuba; Pehlivan, Davut; Beck, Christine R; Gonzaga-Jauregui, Claudia; Muzny, Donna M; Atik, Mehmed M; Carvalho, Claudia M B; Matur, Zeliha; Bayraktar, Serife; Boone, Philip M; Akyuz, Kaya; et al. (Genet Med, 2014)
PURPOSE: Copy-number variations as a mutational mechanism contribute significantly to human disease. Approximately one-half of the patients with Charcot-Marie-Tooth (CMT) disease have a 1.4 Mb duplication copy-number variation as the cause of their neuropathy. However, non-CMT1A neuropathy patients rarely have causative copy-number variations, and to date, autosomal-recessive disease has not been associated with copy-number variation as a mutational mechanism. METHODS: We performed Agilent 8 × 60 K array comparative genomic hybridization on DNA from 12 recessive Turkish families with CMT disease. Additional molecular studies were conducted to detect breakpoint junctions and to evaluate gene expression levels in a family in which we detected an intragenic duplication copy-number variation. RESULTS: We detected an ~6.25 kb homozygous intragenic duplication in NDRG1, a gene known to be causative for recessive HMSNL/CMT4D, in three individuals from a Turkish family with CMT neuropathy. Further studies showed that this intragenic copy-number variation resulted in a homozygous duplication of exons 6-8 that caused decreased mRNA expression of NDRG1. CONCLUSION: Exon-focused high-resolution array comparative genomic hybridization enables the detection of copy-number variation carrier states in recessive genes, particularly small copy-number variations encompassing or disrupting single genes. In families for whom a molecular diagnosis has not been elucidated by conventional clinical assays, an assessment for copy-number variations in known CMT genes might be considered.
Keywords: Adult; Base Sequence; Cell Cycle Proteins; Charcot-Marie-Tooth Disease; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Duplication; Gene Expression; Genes, Recessive; Humans; Intracellular Signaling Peptides and Proteins; Male; Mutation; Refsum Disease; Sequence Analysis, DNA; Turkey; Young Adult

Exonuclease mutations in DNA polymerase epsilon reveal replication strand specific mutation patterns and human origins of replication. - Shinbrot, Eve; Henninger, Erin E; Weinhold, Nils; Covington, Kyle R; Göksenin, A Yasemin; Schultz, Nikolaus; Chao, Hsu; Doddapaneni, Harshavardhan; Muzny, Donna M; Gibbs, Richard A; Sander, Chris; Pursell, Zachary F; et al. (Genome Res, 2014)
Tumors with somatic mutations in the proofreading exonuclease domain of DNA polymerase epsilon (POLE-exo*) exhibit a novel mutator phenotype, with markedly elevated TCT→TAT and TCG→TTG mutations and overall mutation frequencies often exceeding 100 mutations/Mb. Here, we identify POLE-exo* tumors in numerous cancers and classify them into two groups, A and B, according to their mutational properties. Group A mutants are found only in POLE, whereas Group B mutants are found in POLE and POLD1 and appear to be nonfunctional. In Group A, cell-free polymerase assays confirm that mutations in the exonuclease domain result in high mutation frequencies with a preference for C→A mutation. We describe the patterns of amino acid substitutions caused by POLE-exo* and compare them to other tumor types. The nucleotide preference of POLE-exo* leads to increased frequencies of recurrent nonsense mutations in key tumor suppressors such as TP53, ATM, and PIK3R1. We further demonstrate that strand-specific mutation patterns arise from some of these POLE-exo* mutants during genome duplication. This is the first direct proof of leading strand-specific replication by human POLE, which has only been demonstrated in yeast so far. Taken together, the extremely high mutation frequency and strand specificity of mutations provide a unique identifier of eukaryotic origins of replication.
Keywords: Ataxia Telangiectasia Mutated Proteins; Class Ia Phosphatidylinositol 3-Kinase; Codon, Nonsense; Databases, Genetic; DNA Mutational Analysis; DNA Polymerase II; DNA Polymerase III; DNA Replication; Exonucleases; Genome-Wide Association Study; Humans; Microsatellite Instability; Models, Molecular; Mutation, Missense; Neoplasms; Phosphatidylinositol 3-Kinases; Protein Structure, Tertiary; Replication Origin; Tumor Suppressor Protein p53

The first myriapod genome sequence reveals conservative arthropod gene content and genome organisation in the centipede Strigamia maritima. - Chipman, Ariel D; Ferrier, David E K; Brena, Carlo; Qu, Jiaxin; Hughes, Daniel S T; Schröder, Reinhard; Torres-Oliva, Montserrat; Znassi, Nadia; Jiang, Huaiyang; Almeida, Francisca C; Alonso, Claudio R; Apostolou, Zivkos; et al. (PLoS Biol, 2014)
Myriapods (e.g., centipedes and millipedes) display a simple homonomous body plan relative to other arthropods. All members of the class are terrestrial, but they attained terrestriality independently of insects. Myriapoda is the only arthropod class not represented by a sequenced genome. We present an analysis of the genome of the centipede Strigamia maritima. It retains a compact genome that has undergone less gene loss and shuffling than previously sequenced arthropods, and many orthologues of genes conserved from the bilaterian ancestor that have been lost in insects. Our analysis locates many genes in conserved macro-synteny contexts, and many small-scale examples of gene clustering. We describe several examples where S. maritima shows different solutions from insects to similar problems. The insect olfactory receptor gene family is absent from S. maritima, and olfaction in air is likely effected by expansion of other receptor gene families. For some genes S. maritima has evolved paralogues to generate coding sequence diversity, where insects use alternate splicing. This is most striking for the Dscam gene, which in Drosophila generates more than 100,000 alternate splice forms, but in S. maritima is encoded by over 100 paralogues. We see an intriguing linkage between the absence of any known photosensory proteins in a blind organism and the additional absence of canonical circadian clock genes. The phylogenetic position of myriapods allows us to identify where in arthropod phylogeny several particular molecular mechanisms and traits emerged. For example, we conclude that juvenile hormone signalling evolved with the emergence of the exoskeleton in the arthropods and that RR-1 containing cuticle proteins evolved in the lineage leading to Mandibulata. We also identify when various gene expansions and losses occurred. The genome of S. maritima offers us a unique glimpse into the ancestral arthropod genome, while also displaying many adaptations to its specific life history.
Keywords: Animals; Arthropods; Circadian Rhythm Signaling Peptides and Proteins; DNA Methylation; Evolution, Molecular; Female; Genome; Genome, Mitochondrial; Hormones; Male; Multigene Family; Phylogeny; Polymorphism, Genetic; Protein Kinases; Receptors, Odorant; RNA, Untranslated; Selenoproteins; Sex Chromosomes; Synteny; Transcription Factors

Functional analysis of miR-34c as a putative tumor suppressor in high-grade serous ovarian cancer. - Yu, Zhifeng; Kim, Jaeyeon; He, Lin; Creighton, Chad J; Gunaratne, Preethi H; Hawkins, Shannon M; Matzuk, Martin M (Biol Reprod, 2014)
Altered microRNA expression patterns are implicated in the formation of many human diseases, including ovarian cancer. Our laboratory previously created Dicer(fl/fl)/Pten(fl/fl)/Amhr2(cre/+) mice, which developed high-grade serous carcinomas originating from mouse fallopian tubes, while neither Dicer(fl/fl)/Amhr2(cre/+) nor Pten(fl/fl)/Amhr2(cre/+) mice developed tumors. To explore miRNAs involved in the tumorigenesis in the double-knockout (DKO) mice, tumor cell lines were established from mouse primary tumors, and the most abundant miRNAs present in mouse normal fallopian tubes, let-7b and miR-34c, were expressed in these cell lines. We found that miR-34c had a more dramatic effect on inhibiting tumor cell viability than let-7b. The action of miR-34c induced tumor cell cycle arrest in G1 phase and apoptosis, and was accompanied with the regulation of key genes involved in cell proliferation and cell cycle G1/S transition. miR-34c suppressed the expression of Ezh2 and Mybl2, which may transcriptionally and functionally activate Cdkn1c. Furthermore, miR-34c levels are extremely low in human serous adenocarcinomas compared with human normal fallopian tubes. Expression of miR-34c in human ovarian cancer cells phenocopied its effects in DKO mouse tumor cells. However, miR-34b/c(-/-)/Pten(fl/fl)/Amhr2(cre/+) mice failed to develop high-grade serous carcinomas, implicating a combination of miRNAs in the tumorigenesis process. Thus, while miR-34c is a putative tumor suppressor in high-grade serous ovarian carcinoma with potential therapeutic advantages, screening of additional miRNAs for their effects alone and in combination with miR-34c is highly warranted to uncover miRNAs that synergize with miR-34c against cancer.
Keywords: Animals; Cell Line, Tumor; Cystadenocarcinoma, Serous; DEAD-box RNA Helicases; Fallopian Tubes; Female; Gene Expression Regulation, Neoplastic; Genes, Tumor Suppressor; Humans; Mice; Mice, Knockout; MicroRNAs; Neoplasm Grading; Ovarian Neoplasms; PTEN Phosphohydrolase; Ribonuclease III

Gene-specific function prediction for non-synonymous mutations in monogenic diabetes genes. - Li, Quan; Liu, Xiaoming; Gibbs, Richard A; Boerwinkle, Eric; Polychronakos, Constantin; Qu, Hui-Qi (PLoS One, 2014)
The rapid progress of genomic technologies has been providing new opportunities to address the need of maturity-onset diabetes of the young (MODY) molecular diagnosis. However, whether a new mutation causes MODY can be questionable. A number of in silico methods have been developed to predict functional effects of rare human mutations. The purpose of this study is to compare the performance of different bioinformatics methods in the functional prediction of nonsynonymous mutations in each MODY gene, and provides reference matrices to assist the molecular diagnosis of MODY. Our study showed that the prediction scores by different methods of the diabetes mutations were highly correlated, but were more complimentary than replacement to each other. The available in silico methods for the prediction of diabetes mutations had varied performances across different genes. Applying gene-specific thresholds defined by this study may be able to increase the performance of in silico prediction of disease-causing mutations.
Keywords: Adolescent; Apoptosis Regulatory Proteins; Basic Helix-Loop-Helix Transcription Factors; Cell Cycle Proteins; Child; Computational Biology; Diabetes Mellitus, Type 2; Hepatocyte Nuclear Factor 1-alpha; Hepatocyte Nuclear Factor 1-beta; Hepatocyte Nuclear Factor 4; Homeodomain Proteins; Humans; Lipase; Mutation, Missense; Paired Box Transcription Factors; Potassium Channels, Inwardly Rectifying; Repressor Proteins; src-Family Kinases; Sulfonylurea Receptors; Trans-Activators; Young Adult

Genetic and clinical analysis of ABCA4-associated disease in African American patients. - Zernant, Jana; Collison, Frederick T; Lee, Winston; Fishman, Gerald A; Nõupuu, Kalev; Bo Yuan; Cai, Carolyn; James R Lupski; Yannuzzi, Lawrence A; Tsang, Stephen H; Allikmets, Rando (Hum Mutat, 2014)
Autosomal recessive Stargardt disease (STGD1) is caused by hundreds of mutations in the ABCA4 gene, which are often specific to racial and ethnic groups. Here, we investigated the ABCA4 variation and their phenotypic expression in a cohort of 44 patients of African American descent, a previously under-characterized racial group. Patients were screened for mutations in ABCA4 by next-generation sequencing and array-comparative genomic hybridization (aCGH), followed by analyses for pathogenicity by in silico programs. Thorough ophthalmic examination was performed on all patients. At least two (expected) disease-causing alleles in the ABCA4 gene were identified in 27 (61.4%) patients, one allele in 11 (25%) patients, and no ABCA4 mutations were found in six (13.6%) patients. Altogether, 39 different disease-causing ABCA4 variants, including seven new, were identified on 65 (74%) chromosomes, most of which were unique for this racial group. The most frequent ABCA4 mutation in this cohort was c.6320G>A (p.(R2107H)), representing 19.3% of all disease-associated alleles. No large copy number variants were identified in any patient. Most patients reported later onset of symptoms. In summary, the ABCA4 mutation spectrum in patients of West African descent differs significantly from that in patients of European descent, resulting in a later onset and "milder" disease.
Keywords: Adult; African Americans; ATP-Binding Cassette Transporters; Comparative Genomic Hybridization; DNA Mutational Analysis; Electroretinography; Female; Genetic Predisposition to Disease; Humans; Macular Degeneration; Male; Middle Aged; Mutation; Stargardt Disease; United States; Whites

Genetic determinants influencing human serum metabolome among African Americans. - Yu, Bing; Zheng, Yan; Alexander, Danny; Morrison, Alanna C; Coresh, Josef; Boerwinkle, Eric (PLoS Genet, 2014)
Phenotypes proximal to gene action generally reflect larger genetic effect sizes than those that are distant. The human metabolome, a result of multiple cellular and biological processes, are functional intermediate phenotypes proximal to gene action. Here, we present a genome-wide association study of 308 untargeted metabolite levels among African Americans from the Atherosclerosis Risk in Communities (ARIC) Study. Nineteen significant common variant-metabolite associations were identified, including 13 novel loci (p<1.6 × 10(-10)). These loci were associated with 7-50% of the difference in metabolite levels per allele, and the variance explained ranged from 4% to 20%. Fourteen genes were identified within the nineteen loci, and four of them contained non-synonymous substitutions in four enzyme-encoding genes (KLKB1, SIAE, CPS1, and NAT8); the other significant loci consist of eight other enzyme-encoding genes (ACE, GATM, ACY3, ACSM2B, THEM4, ADH4, UGT1A, TREH), a transporter gene (SLC6A13) and a polycystin protein gene (PKD2L1). In addition, four potential disease-associated paths were identified, including two direct longitudinal predictive relationships: NAT8 with N-acetylornithine, N-acetyl-1-methylhistidine and incident chronic kidney disease, and TREH with trehalose and incident diabetes. These results highlight the value of using endophenotypes proximal to gene function to discover new insights into biology and disease pathology.
Keywords: Acetyltransferases; Alleles; Atherosclerosis; Black or African American; Diabetes Mellitus; Genome-Wide Association Study; Humans; Metabolome; Phenotype; Polymorphism, Single Nucleotide; Trehalose

Genome typing of nonhuman primate models: implications for biomedical research. - Haus, Tanja; Ferguson, Betsy; Jeffrey Rogers; Doxiadis, Gaby; Certa, Ulrich; Rose, Nicola J; Teepe, Robert; Weinbauer, Gerhard F; Roos, Christian (Trends Genet, 2014)
The success of personalized medicine rests on understanding the genetic variation between individuals. Thus, as medical practice evolves and variation among individuals becomes a fundamental aspect of clinical medicine, a thorough consideration of the genetic and genomic information concerning the animals used as models in biomedical research also becomes critical. In particular, nonhuman primates (NHPs) offer great promise as models for many aspects of human health and disease. These are outbred species exhibiting substantial levels of genetic variation; however, understanding of the contribution of this variation to phenotypes is lagging behind in NHP species. Thus, there is a pivotal need to address this gap and define strategies for characterizing both genomic content and variability within primate models of human disease. Here, we discuss the current state of genomics of NHP models and offer guidelines for future work to ensure continued improvement and utility of this line of biomedical research.
Keywords: Animals; Biomedical Research; Disease Models, Animal; Genetic Variation; Genome-Wide Association Study; Genomics; Humans; Precision Medicine; Primates; Sequence Analysis, DNA

Genomic and proteomic analysis of transcription factor TFII-I reveals insight into the response to cellular stress. - Fan, Alex Xiucheng; Papadopoulos, Giorgio L; Hossain, Mir A; Lin, I-Ju; Hu, Jianhong; Tang, Tommy Ming; Kilberg, Michael S; Renne, Rolf; Strouboulis, John; Bungert, Jörg (Nucleic Acids Res, 2014)
The ubiquitously expressed transcription factor TFII-I exerts both positive and negative effects on transcription. Using biotinylation tagging technology and high-throughput sequencing, we determined sites of chromatin interactions for TFII-I in the human erythroleukemia cell line K562. This analysis revealed that TFII-I binds upstream of the transcription start site of expressed genes, both upstream and downstream of the transcription start site of repressed genes, and downstream of RNA polymerase II peaks at the ATF3 and other stress responsive genes. At the ATF3 gene, TFII-I binds immediately downstream of a Pol II peak located 5 kb upstream of exon 1. Induction of ATF3 expression increases transcription throughout the ATF3 gene locus which requires TFII-I and correlates with increased association of Pol II and Elongin A. Pull-down assays demonstrated that TFII-I interacts with Elongin A. Partial depletion of TFII-I expression caused a reduction in the association of Elongin A with and transcription of the DNMT1 and EFR3A genes without a decrease in Pol II recruitment. The data reveal different interaction patterns of TFII-I at active, repressed, or inducible genes, identify novel TFII-I interacting proteins, implicate TFII-I in the regulation of transcription elongation and provide insight into the role of TFII-I during the response to cellular stress.
Keywords: Activating Transcription Factor 3; Binding Sites; Biotinylation; Carbon-Nitrogen Ligases; DNA Topoisomerases, Type II; Elongin; Escherichia coli Proteins; Genomics; Humans; K562 Cells; Nuclear Proteins; Proteomics; Repressor Proteins; RNA Polymerase II; Stress, Physiological; TATA-Binding Protein Associated Factors; Transcription Factors; Transcription Factors, TFII; Transcription Initiation Site

Genomic encyclopedia of bacteria and archaea: sequencing a myriad of type strains. - Kyrpides, Nikos C; Hugenholtz, Philip; Eisen, Jonathan A; Woyke, Tanja; Göker, Markus; Parker, Charles T; Amann, Rudolf; Beck, Brian J; Chain, Patrick S G; Chun, Jongsik; Colwell, Rita R; Danchin, Antoine; et al. (PLoS Biol, 2014)
Microbes hold the key to life. They hold the secrets to our past (as the descendants of the earliest forms of life) and the prospects for our future (as we mine their genes for solutions to some of the planet's most pressing problems, from global warming to antibiotic resistance). However, the piecemeal approach that has defined efforts to study microbial genetic diversity for over 20 years and in over 30,000 genome projects risks squandering that promise. These efforts have covered less than 20% of the diversity of the cultured archaeal and bacterial species, which represent just 15% of the overall known prokaryotic diversity. Here we call for the funding of a systematic effort to produce a comprehensive genomic catalog of all cultured Bacteria and Archaea by sequencing, where available, the type strain of each species with a validly published name (currently∼11,000). This effort will provide an unprecedented level of coverage of our planet's genetic diversity, allow for the large-scale discovery of novel genes and functions, and lead to an improved understanding of microbial evolution and function in the environment.
Keywords: Archaea; Bacteria; Databases, Genetic; Genome, Archaeal; Genome, Bacterial; Genomics; Phylogeny; Sequence Analysis, DNA

A homozygous missense mutation in NEUROD1 is associated with nonsyndromic autosomal recessive retinitis pigmentosa. - Wang, Feng; Li, Huajin; Xu, Mingchu; Li, Hui; Zhao, Li; Yang, Lizhu; Zaneveld, Jacques E; Wang, Keqing; Li, Yumei; Sui, Ruifang; Chen, Rui (Invest Ophthalmol Vis Sci, 2014)
PURPOSE: Mutations in the same gene can lead to different clinical phenotypes. In this study, we aim to identify novel genotype-phenotype correlations and novel disease genes by analyzing an unsolved autosomal recessive retinitis pigmentosa (ARRP) Han Chinese family. METHODS: Whole exome sequencing was performed for one proband from the consanguineous ARRP family. Stringent variants filtering and prioritizations were applied to identify the causative mutation. RESULTS: A homozygous missense variant, c.724G>A; p.V242I, in NEUROD1 was identified as the most likely cause of disease. This allele perfectly segregates in the family and affects an amino acid, which is highly conserved among mammals. A previous study showed that a homozygous null allele in NEUROD1 causes severe syndromic disease with neonatal diabetes, systematic neurological abnormalities, and early-onset retinal dystrophy. Consistent with these results, our patients who are homozygous for a less severe missense allele presented only late-onset retinal degeneration without any syndromic symptoms. CONCLUSIONS: We identified a potential novel genotype-phenotype correlation between NEUROD1 and nonsyndromic ARRP. Our study supports the idea that NEUROD1 is important for maintenance of the retina function and partial loss-of-function mutation in NEUROD1 is likely a rare cause of nonsyndromic ARRP.
Keywords: Adult; Basic Helix-Loop-Helix Transcription Factors; DNA; DNA Mutational Analysis; Female; Genes, Recessive; Homozygote; Humans; Male; Mutation, Missense; Pedigree; Phenotype; Retinitis Pigmentosa

Human metabolome associates with dietary intake habits among African Americans in the atherosclerosis risk in communities study. - Zheng, Yan; Yu, Bing; Alexander, Danny; Steffen, Lyn M; Boerwinkle, Eric (Am J Epidemiol, 2014)
The human metabolome is a measurable outcome of interactions among an individual's inherited genome, microbiome, and dietary intake. We explored the relationship between dietary intake and serum untargeted metabolomic profiles in a subsample of 1,977 African Americans from the Atherosclerosis Risk in Communities (ARIC) Study in 1987-1989. For each metabolite, we conducted linear regression to estimate its relationships with each food group and food category. Potential confounding factors included age, sex, body mass index (weight (kg)/height (m)(2)), energy intake, kidney function, and food groups. We used a modified Bonferroni correction to determine statistical significance. In total, 48 pairs of diet-metabolite associations were identified, including multiple novel associations. The food group "sugar-rich foods and beverages" was inversely associated with 5 metabolites in the 2-hydroxybutyrate-related subpathway and positively associated with 5 γ-glutamyl dipeptides. The hypothesized mechanism of these associations may be through oxidative stress. "Sugar-rich foods and beverages" were also inversely associated with 7 unsaturated long-chain fatty acids. These findings suggest that the contribution of a sugar-rich dietary pattern to increased cardiovascular disease risk may be partially attributed to oxidative stress and disordered lipid profiles. Metabolomics may reveal novel metabolic biomarkers of dietary intake and provide insight into biochemical pathways underlying nutritional effects on disease development.
Keywords: Atherosclerosis; Biomarkers; Black or African American; Diet; Feeding Behavior; Female; Humans; Male; Metabolome; Middle Aged; Overweight; Risk Factors

Intrapopulation genome size variation in D. melanogaster reflects life history variation and plasticity. - Ellis, Lisa L; Huang, Wen; Quinn, Andrew M; Ahuja, Astha; Alfrejd, Ben; Gomez, Francisco E; Hjelmen, Carl E; Moore, Kristi L; Mackay, Trudy F C; Johnston, J Spencer; Tarone, Aaron M (PLoS Genet, 2014)
We determined female genome sizes using flow cytometry for 211 Drosophila melanogaster sequenced inbred strains from the Drosophila Genetic Reference Panel, and found significant conspecific and intrapopulation variation in genome size. We also compared several life history traits for 25 lines with large and 25 lines with small genomes in three thermal environments, and found that genome size as well as genome size by temperature interactions significantly correlated with survival to pupation and adulthood, time to pupation, female pupal mass, and female eclosion rates. Genome size accounted for up to 23% of the variation in developmental phenotypes, but the contribution of genome size to variation in life history traits was plastic and varied according to the thermal environment. Expression data implicate differences in metabolism that correspond to genome size variation. These results indicate that significant genome size variation exists within D. melanogaster and this variation may impact the evolutionary ecology of the species. Genome size variation accounts for a significant portion of life history variation in an environmentally dependent manner, suggesting that potential fitness effects associated with genome size variation also depend on environmental conditions.
Keywords: Adaptation, Physiological; Animals; Biological Evolution; Drosophila melanogaster; Environment; Female; Genetic Variation; Genome Size; Genome, Insect; Insect Hormones

Lactobacillus reuteri strain combination in Helicobacter pylori infection: a randomized, double-blind, placebo-controlled study. - Francavilla, Ruggiero; Polimeno, Lorenzo; Demichina, Antonella; Maurogiovanni, Giovanni; Principi, Beatrice; Scaccianoce, Giuseppe; Ierardi, Enzo; Russo, Francesco; Riezzo, Giuseppe; Di Leo, Alfredo; Cavallo, Luciano; Francavilla, Antonio; et al. (J Clin Gastroenterol, 2014)
GOALS: The goals of this study were to investigate the role of a new probiotic preparation (Lactobacillus reuteri DSM 17938 and L. reuteri ATCC PTA 6475) in Helicobacter pylori infection. BACKGROUND: Specific probiotic strains play a role in H. pylori infection for their ability to decrease bacterial load and gastritis, prevent antibiotic-associated side effects, and increase the eradication rate. STUDY: This is a prospective, double-blind, randomized, placebo-controlled study in a tertiary care setting. A total of 100 H. pylori-positive naive patients received either L. reuteri combination (2×10 Colony Forming Units) or placebo during a 3-phase study (pre-eradication, eradication, and follow-up). All underwent C urea breath test (C-UBT), blood assessments of gastrin-17 (G17), endoscopy, and the Gastrointestinal Symptom Rating Scale. Eradication was confirmed by C-UBT 8 weeks after the completion of therapy. RESULTS: Fifty patients were allocated in each group. During pre-eradication period, C-UBT δ decreased by 13% in L. reuteri combination as compared with a 4% increase in placebo (-13.2±34% vs. 4.3±27%; P<0.03). During eradication, GSRS increased significantly in placebo as compared with L. reuteri combination (6.8±2.9 vs. 4±3.1; P<0.01). Significantly less patients in L. reuteri combination as compared with placebo-reported side effects (40.9% vs. 62.8%; P<0.04). An abnormal G17 value was found in patients receiving placebo as compared with L. reuteri combination (28% vs. 12%; P<0.02). Eradication rate was 75% in L. reuteri combination and 65.9% in placebo (P=NS). L. reuteri combination increased eradication rate by 9.1% (odds ratio: 1.5). CONCLUSIONS: L. reuteri combination alone is able to exert an inhibitory effect on H. pylori growth, and when administered with eradication therapy, it determines a significant reduction in antibiotic-associated side effects. Moreover, L. reuteri combination was able to decrease serum G17 levels and to (not significantly) increase the H. pylori-eradication rate.
Keywords: Adolescent; Adult; Aged; Anti-Bacterial Agents; Breath Tests; Double-Blind Method; Drug Therapy, Combination; Female; Follow-Up Studies; Gastrins; Helicobacter Infections; Helicobacter pylori; Humans; Limosilactobacillus reuteri; Male; Middle Aged; Probiotics; Prospective Studies; Treatment Outcome; Young Adult

Large conserved domains of low DNA methylation maintained by Dnmt3a. - Jeong, Mira; Sun, Deqiang; Luo, Min; Huang, Yun; Challen, Grant A; Rodriguez, Benjamin; Zhang, Xiaotian; Chavez, Lukas; Wang, Hui; Hannah, Rebecca; Kim, Sang-Bae; Yang, Liubin; et al. (Nat Genet, 2014)
Gains and losses in DNA methylation are prominent features of mammalian cell types. To gain insight into the mechanisms that promote shifts in DNA methylation and contribute to changes in cell fate, including malignant transformation, we performed genome-wide mapping of 5-methylcytosine and 5-hydroxymethylcytosine in purified mouse hematopoietic stem cells. We discovered extended regions of low methylation (canyons) that span conserved domains frequently containing transcription factors and are distinct from CpG islands and shores. About half of the genes in these methylation canyons are coated with repressive histone marks, whereas the remainder are covered by activating histone marks and are highly expressed in hematopoietic stem cells (HSCs). Canyon borders are demarked by 5-hydroxymethylcytosine and become eroded in the absence of DNA methyltransferase 3a (Dnmt3a). Genes dysregulated in human leukemias are enriched for canyon-associated genes. The new epigenetic landscape we describe may provide a mechanism for the regulation of hematopoiesis and may contribute to leukemia development.
Keywords: 5-Methylcytosine; Animals; Base Sequence; Conserved Sequence; CpG Islands; Cytosine; Databases, Genetic; DNA (Cytosine-5-)-Methyltransferases; DNA Methylation; DNA Methyltransferase 3A; Epigenesis, Genetic; Gene Expression Regulation; Hematopoietic Stem Cells; Histones; Humans; Leukemia; Male; Mice; Mice, Inbred C57BL; Mice, Mutant Strains

Large-scale identification of chemically induced mutations in Drosophila melanogaster. - Haelterman, Nele A; Jiang, Lichun; Li, Yumei; Bayat, Vafa; Sandoval, Hector; Ugur, Berrak; Tan, Kai Li; Zhang, Ke; Bei, Danqing; Xiong, Bo; Charng, Wu-Lin; Busby, Theodore; et al. (Genome Res, 2014)
Forward genetic screens using chemical mutagens have been successful in defining the function of thousands of genes in eukaryotic model organisms. The main drawback of this strategy is the time-consuming identification of the molecular lesions causative of the phenotypes of interest. With whole-genome sequencing (WGS), it is now possible to sequence hundreds of strains, but determining which mutations are causative among thousands of polymorphisms remains challenging. We have sequenced 394 mutant strains, generated in a chemical mutagenesis screen, for essential genes on the Drosophila X chromosome and describe strategies to reduce the number of candidate mutations from an average of -3500 to 35 single-nucleotide variants per chromosome. By combining WGS with a rough mapping method based on large duplications, we were able to map 274 (-70%) mutations. We show that these mutations are causative, using small 80-kb duplications that rescue lethality. Hence, our findings demonstrate that combining rough mapping with WGS dramatically expands the toolkit necessary for assigning function to genes.
Keywords: Animals; Chromosome Mapping; Drosophila melanogaster; Ethyl Methanesulfonate; Female; Genes, Essential; Genes, Insect; Male; Molecular Sequence Data; Mutagenesis; Mutagens; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; X Chromosome

Mammalian Y chromosomes retain widely expressed dosage-sensitive regulators. - Bellott, Daniel W; Hughes, Jennifer F; Skaletsky, Helen; Brown, Laura G; Pyntikova, Tatyana; Cho, Ting-Jan; Koutseva, Natalia; Zaghlul, Sara; Graves, Tina; Rock, Susie; Kremitzki, Colin; Fulton, Robert S; et al. (Nature, 2014)
The human X and Y chromosomes evolved from an ordinary pair of autosomes, but millions of years ago genetic decay ravaged the Y chromosome, and only three per cent of its ancestral genes survived. We reconstructed the evolution of the Y chromosome across eight mammals to identify biases in gene content and the selective pressures that preserved the surviving ancestral genes. Our findings indicate that survival was nonrandom, and in two cases, convergent across placental and marsupial mammals. We conclude that the gene content of the Y chromosome became specialized through selection to maintain the ancestral dosage of homologous X-Y gene pairs that function as broadly expressed regulators of transcription, translation and protein stability. We propose that beyond its roles in testis determination and spermatogenesis, the Y chromosome is essential for male viability, and has unappreciated roles in Turner's syndrome and in phenotypic differences between the sexes in health and disease.
Keywords: Animals; Chromosomes, Human, X; Chromosomes, Human, Y; Disease; Evolution, Molecular; Female; Gene Dosage; Gene Expression Regulation; Health; Humans; Male; Mammals; Marsupialia; Molecular Sequence Annotation; Molecular Sequence Data; Protein Biosynthesis; Protein Stability; Selection, Genetic; Sequence Homology; Sex Characteristics; Spermatogenesis; Testis; Transcription, Genetic; Turner Syndrome; X Chromosome; Y Chromosome

Mechanism, prevalence, and more severe neuropathy phenotype of the Charcot-Marie-Tooth type 1A triplication. - Liu, Pengfei; Gelowani, Violet; Zhang, Feng; Drory, Vivian E; Ben-Shachar, Shay; Roney, Erin; Medeiros, Adam C; Moore, Rebecca J; DiVincenzo, Christina; Burnette, William B; Higgins, Joseph J; Li, Jun; et al. (Am J Hum Genet, 2014)
Copy-number variations cause genomic disorders. Triplications, unlike deletions and duplications, are poorly understood because of challenges in molecular identification, the choice of a proper model system for study, and awareness of their phenotypic consequences. We investigated the genomic disorder Charcot-Marie-Tooth disease type 1A (CMT1A), a dominant peripheral neuropathy caused by a 1.4 Mb recurrent duplication occurring by nonallelic homologous recombination. We identified CMT1A triplications in families in which the duplication segregates. The triplications arose de novo from maternally transmitted duplications and caused a more severe distal symmetric polyneuropathy phenotype. The recombination that generated the triplication occurred between sister chromatids on the duplication-bearing chromosome and could accompany gene conversions with the homologous chromosome. Diagnostic testing for CMT1A (n = 20,661 individuals) identified 13% (n = 2,752 individuals) with duplication and 0.024% (n = 5 individuals) with segmental tetrasomy, suggesting that triplications emerge from duplications at a rate as high as ~1:550, which is more frequent than the rate of de novo duplication. We propose that individuals with duplications are predisposed to acquiring triplications and that the population prevalence of triplication is underascertained.
Keywords: Alleles; Charcot-Marie-Tooth Disease; DNA Copy Number Variations; Female; Gene Dosage; Gene Duplication; Humans; Male; Microsatellite Repeats; Muscular Atrophy; Nucleic Acid Hybridization; Pedigree; Phenotype; Polyneuropathies; Recombination, Genetic

A missense mutation in HK1 leads to autosomal dominant retinitis pigmentosa. - Wang, Feng; Wang, Yandong; Zhang, Bin; Zhao, Li; Lyubasyuk, Vera; Wang, Keqing; Xu, Mingchu; Li, Yumei; Wu, Frances; Wen, Cindy; Bernstein, Paul S; Lin, Danni; et al. (Invest Ophthalmol Vis Sci, 2014)
PURPOSE: Retinitis pigmentosa (RP) is a genetically heterogeneous disease with over 60 causative genes known to date. Nevertheless, approximately 40% of RP cases remain genetically unsolved, suggesting that many novel disease-causing genes are yet to be identified. In this study, we aimed to identify the causative mutation for a large autosomal dominant RP (adRP) family with negative results from known retinal disease gene screening. METHODS: Linkage analysis followed by whole-exome sequencing was performed. Stringent variant filtering and prioritization was carried out to identify the causative mutation. RESULTS: Linkage analysis identified a minimal disease region of 8 Mb on chromosome 10 with a peak parametric logarithm (base 10) of odds (LOD) score of 3.500. Further whole-exome sequencing identified a heterozygous missense mutation (NM_000188.2:c.2539G>A, p.E847K) in hexokinase 1 (HK1) that segregated with the disease phenotype in the family. Biochemical assays showed that the E847K mutation does not affect hexokinase enzymatic activity or the protein stability, suggesting that the mutation may impact other uncharacterized function or result in a gain of function of HK1. CONCLUSIONS: Here, we identified HK1 as a novel causative gene for adRP. This is the first report that associates the glucose metabolic pathway with human retinal degenerative disease, suggesting a potential new disease mechanism.
Keywords: Adolescent; Child; Child, Preschool; DNA; DNA Mutational Analysis; Female; Genes, Dominant; Genetic Linkage; Genetic Predisposition to Disease; Heterozygote; Hexokinase; Humans; Male; Mutation, Missense; Pedigree; Phenotype; Retinitis Pigmentosa; Young Adult

Multilayer-omics analysis of renal cell carcinoma, including the whole exome, methylome and transcriptome. - Arai, Eri; Sakamoto, Hiromi; Ichikawa, Hitoshi; Totsuka, Hirohiko; Chiku, Suenori; Gotoh, Masahiro; Mori, Taisuke; Nakatani, Tamao; Ohnami, Sumiko; Nakagawa, Tohru; Fujimoto, Hiroyuki; Wang, Linghua; et al. (Int J Cancer, 2014)
The aim of this study was to identify pathways that have a significant impact during renal carcinogenesis. Sixty-seven paired samples of both noncancerous renal cortex tissue and cancerous tissue from patients with clear cell renal cell carcinomas (RCCs) were subjected to whole-exome, methylome and transcriptome analyses using Agilent SureSelect All Exon capture followed by sequencing on an Illumina HiSeq 2000 platform, Illumina Infinium HumanMethylation27 BeadArray and Agilent SurePrint Human Gene Expression microarray, respectively. Sanger sequencing and quantitative reverse transcription-PCR were performed for technical verification. MetaCore software was used for pathway analysis. Somatic nonsynonymous single-nucleotide mutations, insertions/deletions and intragenic breaks of 2,153, 359 and 8 genes were detected, respectively. Mutations of GCN1L1, MED12 and CCNC, which are members of CDK8 mediator complex directly regulating β-catenin-driven transcription, were identified in 16% of the RCCs. Mutations of MACF1, which functions in the Wnt/β-catenin signaling pathway, were identified in 4% of the RCCs. A combination of methylome and transcriptome analyses further highlighted the significant role of the Wnt/β-catenin signaling pathway in renal carcinogenesis. Genetic aberrations and reduced expression of ERC2 and ABCA13 were frequent in RCCs, and MTOR mutations were identified as one of the major disrupters of cell signaling during renal carcinogenesis. Our results confirm that multilayer-omics analysis can be a powerful tool for revealing pathways that play a significant role in carcinogenesis.
Keywords: Carcinoma, Renal Cell; DNA Methylation; Exome; Gene Expression Regulation, Neoplastic; Humans; Kidney Neoplasms; Polymorphism, Single Nucleotide; RNA, Messenger; Transcriptome

Mutational landscape of aggressive cutaneous squamous cell carcinoma. - Pickering, Curtis R; Zhou, Jane H; Lee, J Jack; Drummond, Jennifer A; Peng, S Andrew; Saade, Rami E; Tsai, Kenneth Y; Curry, Jonathan L; Tetzlaff, Michael T; Lai, Stephen Y; Yu, Jun; Muzny, Donna M; et al. (Clin Cancer Res, 2014)
PURPOSE: Aggressive cutaneous squamous cell carcinoma (cSCC) is often a disfiguring and lethal disease. Very little is currently known about the mutations that drive aggressive cSCC. EXPERIMENTAL DESIGN: Whole-exome sequencing was performed on 39 cases of aggressive cSCC to identify driver genes and novel therapeutic targets. Significantly, mutated genes were identified with MutSig or complementary methods developed to specifically identify candidate tumor suppressors based upon their inactivating mutation bias. RESULTS: Despite the very high-mutational background caused by UV exposure, 23 candidate drivers were identified, including the well-known cancer-associated genes TP53, CDKN2A, NOTCH1, AJUBA, HRAS, CASP8, FAT1, and KMT2C (MLL3). Three novel candidate tumor suppressors with putative links to cancer or differentiation, NOTCH2, PARD3, and RASA1, were also identified as possible drivers in cSCC. KMT2C mutations were associated with poor outcome and increased bone invasion. CONCLUSIONS: The mutational spectrum of cSCC is similar to that of head and neck squamous cell carcinoma and dominated by tumor-suppressor genes. These results improve the foundation for understanding this disease and should aid in identifying and treating aggressive cSCC.
Keywords: Carcinoma, Squamous Cell; Cluster Analysis; Computational Biology; Disease Progression; DNA Copy Number Variations; Exome; Genomics; High-Throughput Nucleotide Sequencing; Humans; Mutation; Prognosis; Skin Neoplasms

Mutations in NGLY1 cause an inherited disorder of the endoplasmic reticulum-associated degradation pathway. - Enns, Gregory M; Shashi, Vandana; Bainbridge, Matthew; Gambello, Michael J; Zahir, Farah R; Bast, Thomas; Crimian, Rebecca; Schoch, Kelly; Platt, Julia; Cox, Rachel; Bernstein, Jonathan A; Scavina, Mena; et al. (Genet Med, 2014)
PURPOSE: The endoplasmic reticulum-associated degradation pathway is responsible for the translocation of misfolded proteins across the endoplasmic reticulum membrane into the cytosol for subsequent degradation by the proteasome. To define the phenotype associated with a novel inherited disorder of cytosolic endoplasmic reticulum-associated degradation pathway dysfunction, we studied a series of eight patients with deficiency of N-glycanase 1. METHODS: Whole-genome, whole-exome, or standard Sanger sequencing techniques were employed. Retrospective chart reviews were performed in order to obtain clinical data. RESULTS: All patients had global developmental delay, a movement disorder, and hypotonia. Other common findings included hypolacrima or alacrima (7/8), elevated liver transaminases (6/7), microcephaly (6/8), diminished reflexes (6/8), hepatocyte cytoplasmic storage material or vacuolization (5/6), and seizures (4/8). The nonsense mutation c.1201A>T (p.R401X) was the most common deleterious allele. CONCLUSION: NGLY1 deficiency is a novel autosomal recessive disorder of the endoplasmic reticulum-associated degradation pathway associated with neurological dysfunction, abnormal tear production, and liver disease. The majority of patients detected to date carry a specific nonsense mutation that appears to be associated with severe disease. The phenotypic spectrum is likely to enlarge as cases with a broader range of mutations are detected.
Keywords: Abnormalities, Multiple; Adolescent; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Exome; Family Health; Fatal Outcome; Female; Genome-Wide Association Study; Humans; Infant; Male; Microcephaly; Movement Disorders; Muscle Hypotonia; Mutation; Pedigree; Peptide-N4-(N-acetyl-beta-glucosaminyl) Asparagine Amidase; Retrospective Studies; Seizures; Sequence Analysis, DNA; Signal Transduction; Young Adult

Mutations in PURA cause profound neonatal hypotonia, seizures, and encephalopathy in 5q31.3 microdeletion syndrome. - Lalani, Seema R; Zhang, Jing; Schaaf, Christian P; Brown, Chester W; Magoulas, Pilar; Tsai, Anne Chun-Hui; El-Gharbawy, Areeg; Wierenga, Klaas J; Bartholomew, Dennis; Fong, Chin-To; Barbaro-Dieber, Tina; Kukolich, Mary K; et al. (Am J Hum Genet, 2014)
5q31.3 microdeletion syndrome is characterized by neonatal hypotonia, encephalopathy with or without epilepsy, and severe developmental delay, and the minimal critical deletion interval harbors three genes. We describe 11 individuals with clinical features of 5q31.3 microdeletion syndrome and de novo mutations in PURA, encoding transcriptional activator protein Pur-α, within the critical region. These data implicate causative PURA mutations responsible for the severe neurological phenotypes observed in this syndrome.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Caenorhabditis elegans; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, Pair 5; DNA-Binding Proteins; Humans; Molecular Sequence Data; Muscle Hypotonia; Mutation; Seizures; Sequence Analysis, DNA; Syndrome; Transcription Factors

Mutually exclusive recurrent somatic mutations in MAP2K1 and BRAF support a central role for ERK activation in LCH pathogenesis. - Chakraborty, Rikhia; Hampton, Oliver A; Shen, Xiaoyun; Simko, Stephen J; Shih, Albert; Abhyankar, Harshal; Lim, Karen Phaik Har; Covington, Kyle R; Treviño, Lisa; Dewal, Ninad; Muzny, Donna M; Doddapaneni, Harshavardhan; et al. (Blood, 2014)
Langerhans cell histiocytosis (LCH) is a myeloproliferative disorder characterized by lesions composed of pathological CD207(+) dendritic cells with an inflammatory infiltrate. BRAFV600E remains the only recurrent mutation reported in LCH. In order to evaluate the spectrum of somatic mutations in LCH, whole exome sequencing was performed on matched LCH and normal tissue samples obtained from 41 patients. Lesions from other histiocytic disorders, juvenile xanthogranuloma, Erdheim-Chester disease, and Rosai-Dorfman disease were also evaluated. All of the lesions from histiocytic disorders were characterized by an extremely low overall rate of somatic mutations. Notably, 33% (7/21) of LCH cases with wild-type BRAF and none (0/20) with BRAFV600E harbored somatic mutations in MAP2K1 (6 in-frame deletions and 1 missense mutation) that induced extracellular signal-regulated kinase (ERK) phosphorylation in vitro. Single cases of somatic mutations of the mitogen-activated protein kinase (MAPK) pathway genes ARAF and ERBB3 were also detected. The ability of MAPK pathway inhibitors to suppress MAPK kinase and ERK phosphorylation in cell culture and primary tumor models was dependent on the specific LCH mutation. The findings of this study support a model in which ERK activation is a universal end point in LCH arising from pathological activation of upstream signaling proteins.
Keywords: Dendritic Cells; Disease Progression; Erdheim-Chester Disease; HEK293 Cells; Histiocytosis, Langerhans-Cell; Histiocytosis, Sinus; Humans; MAP Kinase Kinase 1; MAP Kinase Signaling System; Mutation, Missense; Proto-Oncogene Proteins B-raf; Xanthogranuloma, Juvenile

Natural variation in genome architecture among 205 Drosophila melanogaster Genetic Reference Panel lines. - Huang, Wen; Massouras, Andreas; Inoue, Yutaka; Peiffer, Jason; Ràmia, Miquel; Tarone, Aaron M; Turlapati, Lavanya; Zichner, Thomas; Zhu, Dianhui; Lyman, Richard F; Magwire, Michael M; Blankenburg, Kerstin; et al. (Genome Res, 2014)
The Drosophila melanogaster Genetic Reference Panel (DGRP) is a community resource of 205 sequenced inbred lines, derived to improve our understanding of the effects of naturally occurring genetic variation on molecular and organismal phenotypes. We used an integrated genotyping strategy to identify 4,853,802 single nucleotide polymorphisms (SNPs) and 1,296,080 non-SNP variants. Our molecular population genomic analyses show higher deletion than insertion mutation rates and stronger purifying selection on deletions. Weaker selection on insertions than deletions is consistent with our observed distribution of genome size determined by flow cytometry, which is skewed toward larger genomes. Insertion/deletion and single nucleotide polymorphisms are positively correlated with each other and with local recombination, suggesting that their nonrandom distributions are due to hitchhiking and background selection. Our cytogenetic analysis identified 16 polymorphic inversions in the DGRP. Common inverted and standard karyotypes are genetically divergent and account for most of the variation in relatedness among the DGRP lines. Intriguingly, variation in genome size and many quantitative traits are significantly associated with inversions. Approximately 50% of the DGRP lines are infected with Wolbachia, and four lines have germline insertions of Wolbachia sequences, but effects of Wolbachia infection on quantitative traits are rarely significant. The DGRP complements ongoing efforts to functionally annotate the Drosophila genome. Indeed, 15% of all D. melanogaster genes segregate for potentially damaged proteins in the DGRP, and genome-wide analyses of quantitative traits identify novel candidate genes. The DGRP lines, sequence data, genotypes, quality scores, phenotypes, and analysis and visualization tools are publicly available.
Keywords: Animals; Chromatin; Drosophila melanogaster; Female; Genetic Linkage; Genetic Variation; Genome Size; Genome, Insect; Genome-Wide Association Study; Genotype; Genotyping Techniques; High-Throughput Nucleotide Sequencing; INDEL Mutation; Linkage Disequilibrium; Male; Molecular Sequence Annotation; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Reproducibility of Results

NR2F1 mutations cause optic atrophy with intellectual disability. - Bosch, Daniëlle G M; Boonstra, F Nienke; Gonzaga-Jauregui, Claudia; Xu, Mafei; de Ligt, Joep; Jhangiani, Shalini; Wiszniewski, Wojciech; Muzny, Donna M; Yntema, Helger G; Pfundt, Rolph; Vissers, Lisenka E L M; Spruijt, Liesbeth; et al. (Am J Hum Genet, 2014)
Optic nerve atrophy and hypoplasia can be primary disorders or can result from trans-synaptic degeneration arising from cerebral visual impairment (CVI). Here we report six individuals with CVI and/or optic nerve abnormalities, born after an uneventful pregnancy and delivery, who have either de novo heterozygous missense mutations in NR2F1, also known as COUP-TFI, or deletions encompassing NR2F1. All affected individuals show mild to moderate intellectual impairment. NR2F1 encodes a nuclear receptor protein that regulates transcription. A reporter assay showed that missense mutations in the zinc-finger DNA-binding domain and the putative ligand-binding domain decrease NR2F1 transcriptional activity. These findings indicate that NR2F1 plays an important role in the neurodevelopment of the visual system and that its disruption can lead to optic atrophy with intellectual disability.
Keywords: Adolescent; Adult; Amino Acid Sequence; Child; Child, Preschool; COUP Transcription Factor I; DNA-Binding Proteins; Female; Genotype; Humans; Intellectual Disability; Male; Molecular Sequence Data; Mutation, Missense; Optic Atrophy; Phenotype; Young Adult; Zinc Fingers

Onset of atonal expression in Drosophila retinal progenitors involves redundant and synergistic contributions of Ey/Pax6 and So binding sites within two distant enhancers. - Zhou, Qingxiang; Zhang, Tianyi; Jemc, Jennifer C; Chen, Yiyun; Chen, Rui; Rebay, Ilaria; Pignoni, Francesca (Dev Biol, 2014)
Proneural transcription factors drive the generation of specialized neurons during nervous system development, and their dynamic expression pattern is critical to their function. The activation of the proneural gene atonal (ato) in the Drosophila eye disc epithelium represents a critical step in the transition from retinal progenitor cell to developing photoreceptor neuron. We show here that the onset of ato transcription depends on two distant enhancers that function differently in subsets of retinal progenitor cells. A detailed analysis of the crosstalk between these enhancers identifies a critical role for three binding sites for the Retinal Determination factors Eyeless (Ey) and Sine oculis (So). We show how these sites interact to induce ato expression in distinct regions of the eye field and confirm them to be occupied by endogenous Ey and So proteins in vivo. Our study suggests that Ey and So operate differently through the same 3' cis-regulatory sites in distinct populations of retinal progenitors.
Keywords: Animals; Basic Helix-Loop-Helix Transcription Factors; Binding Sites; DNA-Binding Proteins; Drosophila; Drosophila Proteins; Enhancer Elements, Genetic; Eye Proteins; Gene Expression Regulation, Developmental; Green Fluorescent Proteins; Homeodomain Proteins; In Situ Hybridization; Nerve Tissue Proteins; Nervous System; Neurons; Paired Box Transcription Factors; PAX6 Transcription Factor; Repressor Proteins; Retina; Stem Cells; Transcription, Genetic

Parent of origin, mosaicism, and recurrence risk: probabilistic modeling explains the broken symmetry of transmission genetics. - Campbell, Ian M; Stewart, Jonathan R; James, Regis A; Lupski, James R; Stankiewicz, Paweł; Olofsson, Peter; Shaw, Chad A (Am J Hum Genet, 2014)
Most new mutations are observed to arise in fathers, and increasing paternal age positively correlates with the risk of new variants. Interestingly, new mutations in X-linked recessive disease show elevated familial recurrence rates. In male offspring, these mutations must be inherited from mothers. We previously developed a simulation model to consider parental mosaicism as a source of transmitted mutations. In this paper, we extend and formalize the model to provide analytical results and flexible formulas. The results implicate parent of origin and parental mosaicism as central variables in recurrence risk. Consistent with empirical data, our model predicts that more transmitted mutations arise in fathers and that this tendency increases as fathers age. Notably, the lack of expansion later in the male germline determines relatively lower variance in the proportion of mutants, which decreases with paternal age. Subsequently, observation of a transmitted mutation has less impact on the expected risk for future offspring. Conversely, for the female germline, which arrests after clonal expansion in early development, variance in the mutant proportion is higher, and observation of a transmitted mutation dramatically increases the expected risk of recurrence in another pregnancy. Parental somatic mosaicism considerably elevates risk for both parents. These findings have important implications for genetic counseling and for understanding patterns of recurrence in transmission genetics. We provide a convenient online tool and source code implementing our analytical results. These tools permit varying the underlying parameters that influence recurrence risk and could be useful for analyzing risk in diverse family structures.
Keywords: Adult; Aged; Aged, 80 and over; Chromosome Aberrations; DNA Copy Number Variations; Fathers; Female; Gametogenesis; Genetic Diseases, Inborn; Genomics; Germ Cells; Germ-Line Mutation; Humans; Inheritance Patterns; Male; Middle Aged; Models, Theoretical; Mosaicism; Mothers; Pregnancy; Recurrence; Risk Factors; Young Adult

Parental somatic mosaicism is underrecognized and influences recurrence risk of genomic disorders. - Campbell, Ian M; Yuan, Bo; Robberecht, Caroline; Pfundt, Rolph; Szafranski, Przemyslaw; McEntagart, Meriel E; Nagamani, Sandesh C S; Erez, Ayelet; Bartnik, Magdalena; Wiśniowiecka-Kowalnik, Barbara; Plunkett, Katie S; Pursley, Amber N; et al. (Am J Hum Genet, 2014)
New human mutations are thought to originate in germ cells, thus making a recurrence of the same mutation in a sibling exceedingly rare. However, increasing sensitivity of genomic technologies has anecdotally revealed mosaicism for mutations in somatic tissues of apparently healthy parents. Such somatically mosaic parents might also have germline mosaicism that can potentially cause unexpected intergenerational recurrences. Here, we show that somatic mosaicism for transmitted mutations among parents of children with simplex genetic disease is more common than currently appreciated. Using the sensitivity of individual-specific breakpoint PCR, we prospectively screened 100 families with children affected by genomic disorders due to rare deletion copy-number variants (CNVs) determined to be de novo by clinical analysis of parental DNA. Surprisingly, we identified four cases of low-level somatic mosaicism for the transmitted CNV in DNA isolated from parental blood. Integrated probabilistic modeling of gametogenesis developed in response to our observations predicts that mutations in parental blood increase recurrence risk substantially more than parental mutations confined to the germline. Moreover, despite the fact that maternally transmitted mutations are the minority of alleles, our model suggests that sexual dimorphisms in gametogenesis result in a greater proportion of somatically mosaic transmitting mothers who are thus at increased risk of recurrence. Therefore, somatic mosaicism together with sexual differences in gametogenesis might explain a considerable fraction of unexpected recurrences of X-linked recessive disease. Overall, our results underscore an important role for somatic mosaicism and mitotic replicative mutational mechanisms in transmission genetics.
Keywords: Cell Division; DNA Copy Number Variations; Female; Gametogenesis; Genetic Diseases, Inborn; Genomics; Germ Cells; Germ-Line Mutation; Humans; Male; Models, Genetic; Mosaicism; Mutation; Pedigree; Prospective Studies; Recurrence; Risk; Sex Characteristics; Smith-Magenis Syndrome

Passage number is a major contributor to genomic structural variations in mouse iPSCs. - Liu, Pengfei; Kaplan, Anna; Bo Yuan; Hanna, Jacob H; James R Lupski; Reiner, Orly (Stem Cells, 2014)
Emergence of genomic instability is a practical issue in preparing neural stem cells (NSCs) and induced pluripotent stem cells (iPSCs). However, it is still not fully understood what the origins and mechanisms for formation are for the genomic alternations observed. Here, we studied the extent of genomic variation on the scale of individual cells originating from the same animal. We used mouse NSCs grown from embryonic cells and iPSCs generated from embryonic brain cells, B cells or fibroblasts, and performed comparative analysis with cultures of fibroblasts from the same mouse. In the first passage of these cell lines, aneuploidies were only observed for chromosomes 6, 11, 12, 19, and Y, which is overall at a rate lower than previously reported; de novo copy number variations (CNVs) were observed in 4.3% of neural iPSCs, 29% of B cell iPSCs, 10% of fibroblast iPSCs, and 1.3% of neurospheres. In contrast, propagation of these first passage cells to a later passage induced additional aneuploidies and CNVs. Breakpoint sequencing analysis suggested that the majority of the detected CNVs arose by replicative mechanisms. Interestingly, we detected identical de novo CNVs in different single cell colonies that appeared to have arisen independently from each other, which suggests a novel CNV formation mechanism in these cells. Our findings provide insights into mechanisms of CNV formation during reprogramming and suggest that replicative mechanisms for CNV formation accompany mitotic divisions.
Keywords: Aneuploidy; Animals; Base Sequence; Cell Proliferation; Chromosome Breakage; Clone Cells; Comparative Genomic Hybridization; DNA Copy Number Variations; Genetic Loci; Genomic Instability; Genomic Structural Variation; Induced Pluripotent Stem Cells; Mice; Molecular Sequence Data; Neural Stem Cells; Spheroids, Cellular

Possible race and gender divergence in association of genetic variations with plasma von Willebrand factor: a study of ARIC and 1000 genome cohorts. - Zhou, Zhou; Yu, Fuli; Buchanan, Ashley; Fu, Yuanyuan; Campos, Marco; Wu, Kenneth K; Chambless, Lloyd E; Folsom, Aaron R; Boerwinkle, Eric; Dong, Jing-fei (PLoS One, 2014)
The synthesis, secretion and clearance of von Willebrand factor (VWF) are regulated by genetic variations in coding and promoter regions of the VWF gene. We have previously identified 19 single nucleotide polymorphisms (SNPs), primarily in introns that are associated with VWF antigen levels in subjects of European descent. In this study, we conducted race by gender analyses to compare the association of VWF SNPs with VWF antigen among 10,434 healthy Americans of European (EA) or African (AA) descent from the Atherosclerosis Risk in Communities (ARIC) study. Among 75 SNPs analyzed, 13 and 10 SNPs were associated with VWF antigen levels in EA male and EA female subjects, respectively. However, only one SNP (RS1063857) was significantly associated with VWF antigen in AA females and none was in AA males. Haplotype analysis of the ARIC samples and studying racial diversities in the VWF gene from the 1000 genomes database suggest a greater degree of variations in the VWF gene in AA subjects as compared to EA subjects. Together, these data suggest potential race and gender divergence in regulating VWF expression by genetic variations.
Keywords: Atherosclerosis; Black People; Cohort Studies; Demography; Female; Gene Frequency; Genetic Variation; Genome, Human; Haplotypes; Humans; Male; Polymorphism, Single Nucleotide; Sex Characteristics; von Willebrand Factor; White People

Recurrent CNVs and SNVs at the NPHP1 locus contribute pathogenic alleles to Bardet-Biedl syndrome. - Lindstrand, Anna; Davis, Erica E; Carvalho, Claudia M B; Pehlivan, Davut; Willer, Jason R; Tsai, I-Chun; Ramanathan, Subhadra; Zuppan, Craig; Sabo, Aniko; Muzny, Donna; Gibbs, Richard; Liu, Pengfei; et al. (Am J Hum Genet, 2014)
Homozygosity for a recurrent 290 kb deletion of NPHP1 is the most frequent cause of isolated nephronophthisis (NPHP) in humans. A deletion of the same genomic interval has also been detected in individuals with Joubert syndrome (JBTS), and in the mouse, Nphp1 interacts genetically with Ahi1, a known JBTS locus. Given these observations, we investigated the contribution of NPHP1 in Bardet-Biedl syndrome (BBS), a ciliopathy of intermediate severity. By using a combination of array-comparative genomic hybridization, TaqMan copy number assays, and sequencing, we studied 200 families affected by BBS. We report a homozygous NPHP1 deletion CNV in a family with classical BBS that is transmitted with autosomal-recessive inheritance. Further, we identified heterozygous NPHP1 deletions in two more unrelated persons with BBS who bear primary mutations at another BBS locus. In parallel, we identified five families harboring an SNV in NPHP1 resulting in a conserved missense change, c.14G>T (p.Arg5Leu), that is enriched in our Hispanic pedigrees; in each case, affected individuals carried additional bona fide pathogenic alleles in another BBS gene. In vivo functional modeling in zebrafish embryos demonstrated that c.14G>T is a loss-of-function variant, and suppression of nphp1 in concert with each of the primary BBS loci found in our NPHP1-positive pedigrees exacerbated the severity of the phenotype. These results suggest that NPHP1 mutations are probably rare primary causes of BBS that contribute to the mutational burden of the disorder.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Bardet-Biedl Syndrome; Cytoskeletal Proteins; DNA Copy Number Variations; Gastrulation; Genetic Loci; Heterozygote; Homozygote; Humans; Kidney; Membrane Proteins; Mice; Pedigree; Sequence Deletion; Zebrafish

Regulation of Drosophila eye development by the transcription factor Sine oculis. - Jusiak, Barbara; Karandikar, Umesh C; Kwak, Su-Jin; Wang, Feng; Wang, Hui; Chen, Rui; Mardon, Graeme (PLoS One, 2014)
Homeodomain transcription factors of the Sine oculis (SIX) family direct multiple regulatory processes throughout the metazoans. Sine oculis (So) was first characterized in the fruit fly Drosophila melanogaster, where it is both necessary and sufficient for eye development, regulating cell survival, proliferation, and differentiation. Despite its key role in development, only a few direct targets of So have been described previously. In the current study, we aim to expand our knowledge of So-mediated transcriptional regulation in the developing Drosophila eye using ChIP-seq to map So binding regions throughout the genome. We find 7,566 So enriched regions (peaks), estimated to map to 5,952 genes. Using overlap between the So ChIP-seq peak set and genes that are differentially regulated in response to loss or gain of so, we identify putative direct targets of So. We find So binding enrichment in genes not previously known to be regulated by So, including genes that encode cell junction proteins and signaling pathway components. In addition, we analyze a subset of So-bound novel genes in the eye, and find eight genes that have previously uncharacterized eye phenotypes and may be novel direct targets of So. Our study presents a greatly expanded list of candidate So targets and serves as basis for future studies of So-mediated gene regulation in the eye.
Keywords: Animals; Drosophila melanogaster; Eye; Gene Expression Regulation, Developmental; Homeodomain Proteins; Optic Disk; Organogenesis; Transcription Factors

Serum metabolomic profiling and incident CKD among African Americans. - Yu, Bing; Zheng, Yan; Nettleton, Jennifer A; Alexander, Danny; Coresh, Josef; Boerwinkle, Eric (Clin J Am Soc Nephrol, 2014)
BACKGROUND AND OBJECTIVES: Novel biomarkers that more accurately reflect kidney function and predict future CKD are needed. The human metabolome is the product of multiple physiologic or pathophysiologic processes and may provide novel insight into disease etiology and progression. This study investigated whether estimated kidney function would be associated with multiple metabolites and whether selected metabolomic factors would be independent risk factors for incident CKD. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: In total, 1921 African Americans free of CKD with a median of 19.6 years follow-up among the Atherosclerosis Risk in Communities Study were included. A total of 204 serum metabolites quantified by untargeted gas chromatography-mass spectrometry and liquid chromatography-mass spectrometry was analyzed by both linear regression for the cross-sectional associations with eGFR (specified by the Chronic Kidney Disease Epidemiology Collaboration equation) and Cox proportional hazards model for the longitudinal associations with incident CKD. RESULTS: Forty named and 34 unnamed metabolites were found to be associated with eGFR specified by the Chronic Kidney Disease Epidemiology Collaboration equation with creatine and 3-indoxyl sulfate showing the strongest positive (2.8 ml/min per 1.73 m(2) per +1 SD; 95% confidence interval, 2.1 to 3.5) and negative association (-14.2 ml/min per 1.73 m(2) per +1 SD; 95% confidence interval, -17.0 to -11.3), respectively. Two hundred four incident CKD events with a median follow-up time of 19.6 years were included in the survival analyses. Higher levels of 5-oxoproline (hazard ratio, 0.70; 95% confidence interval, 0.60 to 0.82) and 1,5-anhydroglucitol (hazard ratio, 0.68; 95% confidence interval, 0.58 to 0.80) were significantly related to lower risk of incident CKD, and the associations did not appreciably change when mutually adjusted. CONCLUSIONS: These data identify a large number of metabolites associated with kidney function as well as two metabolites that are candidate risk factors for CKD and may provide new insights into CKD biomarker identification.
Keywords: Biomarkers; Black or African American; Chromatography, Liquid; Creatine; Cross-Sectional Studies; Deoxyglucose; Female; Gas Chromatography-Mass Spectrometry; Humans; Incidence; Indican; Kidney; Linear Models; Longitudinal Studies; Male; Metabolomics; Middle Aged; Proportional Hazards Models; Pyrrolidonecarboxylic Acid; Renal Insufficiency, Chronic; Risk Factors; Time Factors; United States

The somatic genomic landscape of chromophobe renal cell carcinoma. - Davis, Caleb F; Ricketts, Christopher J; Wang, Min; Yang, Lixing; Cherniack, Andrew D; Shen, Hui; Buhay, Christian; Kang, Hyojin; Kim, Sang Cheol; Fahey, Catherine C; Hacker, Kathryn E; Bhanot, Gyan; et al. (Cancer Cell, 2014)
We describe the landscape of somatic genomic alterations of 66 chromophobe renal cell carcinomas (ChRCCs) on the basis of multidimensional and comprehensive characterization, including mtDNA and whole-genome sequencing. The result is consistent that ChRCC originates from the distal nephron compared with other kidney cancers with more proximal origins. Combined mtDNA and gene expression analysis implicates changes in mitochondrial function as a component of the disease biology, while suggesting alternative roles for mtDNA mutations in cancers relying on oxidative phosphorylation. Genomic rearrangements lead to recurrent structural breakpoints within TERT promoter region, which correlates with highly elevated TERT expression and manifestation of kataegis, representing a mechanism of TERT upregulation in cancer distinct from previously observed amplifications and point mutations.
Keywords: Base Sequence; Carcinoma, Renal Cell; Chromosome Breakpoints; Chromosome Deletion; Chromosomes, Human; DNA Copy Number Variations; DNA Methylation; DNA Mutational Analysis; DNA, Mitochondrial; Exome; Genome, Human; Humans; Kidney Neoplasms; Molecular Sequence Data; Promoter Regions, Genetic; Telomerase; Transcriptome

Squamous cell carcinoma of the oral tongue in young non-smokers is genomically similar to tumors in older smokers. - Pickering, Curtis R; Zhang, Jiexin; Neskey, David M; Zhao, Mei; Jasser, Samar A; Wang, Jiping; Ward, Alexandra; Tsai, C Jillian; Ortega Alves, Marcus V; Zhou, Jane H; Drummond, Jennifer; El-Naggar, Adel K; et al. (Clin Cancer Res, 2014)
PURPOSE: Epidemiologic studies have identified an increasing incidence of squamous cell carcinoma of the oral tongue (SCCOT) in younger patients. EXPERIMENTAL DESIGN: DNA isolated from tongue tumors of young (<45 years, non-smokers) and old (>45 years) patients at was subjected to whole-exome sequencing and copy-number analysis. These data were compared with data from similar patients in the TCGA (The Cancer Genome Atlas) project. RESULTS: In this study, we found that gene-specific mutation and copy-number alteration frequencies were similar between young and old patients with SCCOT in two independent cohorts. Likewise, the types of base changes observed in the young cohort were similar to those in the old cohort even though they differed in smoking history. TCGA data also demonstrate that the genomic effects of smoking are tumor site-specific, and we find that smoking has only a minor impact on the types of mutations observed in SCCOT. CONCLUSIONS: Overall, tumors from young patients with SCCOT appear genomically similar to those of older patients with SCCOT, and the cause for the increasing incidence of young SCCOT remains unknown. These data indicate that the functional impact of smoking on carcinogenesis in SCCOT is still poorly understood.
Keywords: Adult; Age Factors; Carcinoma, Squamous Cell; DNA Copy Number Variations; DNA Mutational Analysis; Female; Humans; Male; Middle Aged; Mutation; Prognosis; Smoking; Tongue Neoplasms

Trans-ancestry mutational landscape of hepatocellular carcinoma genomes. - Totoki, Yasushi; Tatsuno, Kenji; Covington, Kyle R; Ueda, Hiroki; Creighton, Chad J; Kato, Mamoru; Tsuji, Shingo; Donehower, Lawrence A; Slagle, Betty L; Nakamura, Hiromi; Yamamoto, Shogo; Shinbrot, Eve; et al. (Nat Genet, 2014)
Diverse epidemiological factors are associated with hepatocellular carcinoma (HCC) prevalence in different populations. However, the global landscape of the genetic changes in HCC genomes underpinning different epidemiological and ancestral backgrounds still remains uncharted. Here a collection of data from 503 liver cancer genomes from different populations uncovered 30 candidate driver genes and 11 core pathway modules. Furthermore, a collaboration of two large-scale cancer genome projects comparatively analyzed the trans-ancestry substitution signatures in 608 liver cancer cases and identified unique mutational signatures that predominantly contribute to Asian cases. This work elucidates previously unexplored ancestry-associated mutational processes in HCC development. A combination of hotspot TERT promoter mutation, TERT focal amplification and viral genome integration occurs in more than 68% of cases, implicating TERT as a central and ancestry-independent node of hepatocarcinogenesis. Newly identified alterations in genes encoding metabolic enzymes, chromatin remodelers and a high proportion of mTOR pathway activations offer potential therapeutic and diagnostic opportunities.
Keywords: Algorithms; Asian People; Carcinoma, Hepatocellular; CpG Islands; DNA Mutational Analysis; Exome; Gene Expression Regulation, Neoplastic; Genome, Human; Genome, Viral; Hepacivirus; Hepatitis B virus; Humans; Japan; Liver Neoplasms; Models, Statistical; Mutation; Principal Component Analysis; Telomerase; TOR Serine-Threonine Kinases; United States; White People

Whole exome sequencing identifies novel genes for fetal hemoglobin response to hydroxyurea in children with sickle cell anemia. - Sheehan, Vivien A; Crosby, Jacy R; Sabo, Aniko; Mortier, Nicole A; Howard, Thad A; Muzny, Donna M; Dugan-Perez, Shannon; Aygun, Banu; Nottage, Kerri A; Boerwinkle, Eric; Gibbs, Richard A; Ware, Russell E; et al. (PLoS One, 2014)
Hydroxyurea has proven efficacy in children and adults with sickle cell anemia (SCA), but with considerable inter-individual variability in the amount of fetal hemoglobin (HbF) produced. Sibling and twin studies indicate that some of that drug response variation is heritable. To test the hypothesis that genetic modifiers influence pharmacological induction of HbF, we investigated phenotype-genotype associations using whole exome sequencing of children with SCA treated prospectively with hydroxyurea to maximum tolerated dose (MTD). We analyzed 171 unrelated patients enrolled in two prospective clinical trials, all treated with dose escalation to MTD. We examined two MTD drug response phenotypes: HbF (final %HbF minus baseline %HbF), and final %HbF. Analyzing individual genetic variants, we identified multiple low frequency and common variants associated with HbF induction by hydroxyurea. A validation cohort of 130 pediatric sickle cell patients treated to MTD with hydroxyurea was genotyped for 13 non-synonymous variants with the strongest association with HbF response to hydroxyurea in the discovery cohort. A coding variant in Spalt-like transcription factor, or SALL2, was associated with higher final HbF in this second independent replication sample and SALL2 represents an outstanding novel candidate gene for further investigation. These findings may help focus future functional studies and provide new insights into the pharmacological HbF upregulation by hydroxyurea in patients with SCA.
Keywords: Anemia, Sickle Cell; Child; Cohort Studies; DNA-Binding Proteins; Dose-Response Relationship, Drug; Exome; Fetal Hemoglobin; Genomics; Humans; Hydroxyurea; Maximum Tolerated Dose; Open Reading Frames; Phenotype; Prospective Studies; Sequence Analysis, DNA; Transcription Factors; Treatment Outcome

Whole exome sequencing identifies three novel mutations in ANTXR1 in families with GAPO syndrome. - Bayram, Yavuz; Pehlivan, Davut; Karaca, Ender; Gambin, Tomasz; Jhangiani, Shalini N; Erdin, Serkan; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; Muzny, Donna; Elcioglu, Nursel H; Yildirim, M Selman; Bozkurt, Banu; et al. (Am J Med Genet A, 2014)
GAPO syndrome (OMIM#230740) is the acronym for growth retardation, alopecia, pseudoanodontia, and optic atrophy. About 35 cases have been reported, making it among one of the rarest recessive conditions. Distinctive craniofacial features including alopecia, rarefaction of eyebrows and eyelashes, frontal bossing, high forehead, mid-facial hypoplasia, hypertelorism, and thickened eyelids and lips make GAPO syndrome a clinically recognizable phenotype. While this genomic study was in progress mutations in ANTXR1 were reported to cause GAPO syndrome. In our study we performed whole exome sequencing (WES) for five affected individuals from three Turkish kindreds segregating the GAPO trait. Exome sequencing analysis identified three novel homozygous mutations including; one frame-shift (c.1220_1221insT; p.Ala408Cysfs*2), one splice site (c.411A>G; p.Gln137Gln), and one non-synonymous (c.1150G>A; p.Gly384Ser) mutation in the ANTXR1 gene. Our studies expand the allelic spectrum in this rare condition and potentially provide insight into the role of ANTXR1 in the regulation of the extracellular matrix.
Keywords: Adolescent; Adult; Alopecia; Anodontia; Base Sequence; Child; Chromosome Segregation; DNA Mutational Analysis; Exome; Facies; Family; Female; Growth Disorders; Humans; Male; Microfilament Proteins; Molecular Sequence Data; Mutation; Neoplasm Proteins; Optic Atrophies, Hereditary; Pedigree; Protein Structure, Tertiary; Receptors, Cell Surface

Whole-exome sequencing of polycythemia vera revealed novel driver genes and somatic mutation shared by T cells and granulocytes. - Wang, L; Swierczek, S I; Drummond, J; Hickman, K; Kim, S J; Walker, K; Doddapaneni, H; Muzny, D M; Gibbs, R A; Wheeler, D A; Prchal, J T (Leukemia, 2014)
To better understand the underlying molecular basis of polycythemia vera (PV), we performed whole-exome sequencing and DNA copy-number analysis of 31 -positive patients and further investigated the evolution of somatic mutations using longitudinal samples. In addition to and 9pUPD, we identified frequent recurrent somatic mutation in , and . Forty two percent of patients had a somatic mutation in at least one epigenetic modifier gene. In 4 of 31 patients, variant allele abundance suggested mutation of was preceded by other somatic mutations including , and . Strikingly, in 7 patients, apparent germline variants were detected at COSMIC codons in one or more PV-related genes in which we had also discovered somatic mutations across the cohort, suggesting that some pre- mutations contribute to substantial T-lymphocyte progeny. This study contributes to novel understanding of the complexity of PV pathogenesis.
Keywords: DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; Exome; Granulocytes; Humans; Janus Kinase 2; Mutation; Polycythemia Vera; Repressor Proteins; Sequence Analysis, DNA; T-Lymphocytes

Why primate models matter. - Phillips, Kimberley A; Bales, Karen L; Capitanio, John P; Conley, Alan; Czoty, Paul W; 't Hart, Bert A; Hopkins, William D; Hu, Shiu-Lok; Miller, Lisa A; Nader, Michael A; Nathanielsz, Peter W; Rogers, Jeffrey; et al. (Am J Primatol, 2014)
Research involving nonhuman primates (NHPs) has played a vital role in many of the medical and scientific advances of the past century. NHPs are used because of their similarity to humans in physiology, neuroanatomy, reproduction, development, cognition, and social complexity-yet it is these very similarities that make the use of NHPs in biomedical research a considered decision. As primate researchers, we feel an obligation and responsibility to present the facts concerning why primates are used in various areas of biomedical research. Recent decisions in the United States, including the phasing out of chimpanzees in research by the National Institutes of Health and the pending closure of the New England Primate Research Center, illustrate to us the critical importance of conveying why continued research with primates is needed. Here, we review key areas in biomedicine where primate models have been, and continue to be, essential for advancing fundamental knowledge in biomedical and biological research.
Keywords: Animal Experimentation; Animals; Disease Models, Animal; Humans; Primates; United States

Adverse outcomes in clear cell renal cell carcinoma with mutations of 3p21 epigenetic regulators BAP1 and SETD2: a report by MSKCC and the KIRC TCGA research network. - Hakimi, A Ari; Ostrovnaya, Irina; Reva, Boris; Schultz, Nikolaus; Chen, Ying-Bei; Gonen, Mithat; Liu, Han; Takeda, Shugaku; Voss, Martin H; Tickoo, Satish K; Reuter, Victor E; Russo, Paul; et al. (Clin Cancer Res, 2013)
PURPOSE: To investigate the impact of newly identified chromosome 3p21 epigenetic tumor suppressors PBRM1, SETD2, and BAP1 on cancer-specific survival (CSS) of 609 patients with clear cell renal cell carcinoma (ccRCC) from 2 distinct cohorts. EXPERIMENTAL DESIGN: Select sequencing on 3p tumor suppressors of 188 patients who underwent resection of primary ccRCC at the Memorial Sloan-Kettering Cancer Center (MSKCC) was conducted to interrogate the genotype-phenotype associations. These findings were compared with analyses of the genomic and clinical dataset from our nonoverlapping The Cancer Genome Atlas (TCGA) cohort of 421 patients with primary ccRCC. RESULTS: 3p21 tumor suppressors are frequently mutated in both the MSKCC (PBRM1, 30.3%; SETD2, 7.4%; BAP1, 6.4%) and the TCGA (PBRM1, 33.5%; SETD2, 11.6%; BAP1, 9.7%) cohorts. BAP1 mutations are associated with worse CSS in both cohorts [MSKCC, P = 0.002; HR 7.71; 95% confidence interval (CI)2.08-28.6; TCGA, P = 0.002; HR 2.21; 95% CI 1.35-3.63]. SETD2 are associated with worse CSS in the TCGA cohort (P = 0.036; HR 1.68; 95% CI 1.04-2.73). On the contrary, PBRM1 mutations, the second most common gene mutations of ccRCC, have no impact on CSS. CONCLUSION: The chromosome 3p21 locus harbors 3 frequently mutated ccRCC tumor suppressor genes. BAP1 and SETD2 mutations (6%-12%) are associated with worse CSS, suggesting their roles in disease progression. PBRM1 mutations (30%-34%) do not impact CSS, implicating its principal role in the tumor initiation. Future efforts should focus on therapeutic interventions and further clinical, pathologic, and molecular interrogation of this novel class of tumor suppressors.
Keywords: Aged; Carcinoma, Renal Cell; Cell Transformation, Neoplastic; Chromosomes, Human, Pair 3; Clinical Trials as Topic; Disease-Free Survival; DNA-Binding Proteins; Epigenesis, Genetic; Female; Gene Expression Regulation, Neoplastic; Histone-Lysine N-Methyltransferase; Humans; Kidney Neoplasms; Male; Middle Aged; Mutation; Neoplasm Staging; Nuclear Proteins; Transcription Factors; Tumor Suppressor Proteins; Ubiquitin Thiolesterase

ARMC4 mutations cause primary ciliary dyskinesia with randomization of left/right body asymmetry. - Hjeij, Rim; Lindstrand, Anna; Francis, Richard; Zariwala, Maimoona A; Liu, Xiaoqin; Li, You; Damerla, Rama; Dougherty, Gerard W; Abouhamed, Marouan; Olbrich, Heike; Loges, Niki T; Pennekamp, Petra; et al. (Am J Hum Genet, 2013)
The motive forces for ciliary movement are generated by large multiprotein complexes referred to as outer dynein arms (ODAs), which are preassembled in the cytoplasm prior to transport to the ciliary axonemal compartment. In humans, defects in structural components, docking complexes, or cytoplasmic assembly factors can cause primary ciliary dyskinesia (PCD), a disorder characterized by chronic airway disease and defects in laterality. By using combined high resolution copy-number variant and mutation analysis, we identified ARMC4 mutations in twelve PCD individuals whose cells showed reduced numbers of ODAs and severely impaired ciliary beating. Transient suppression in zebrafish and analysis of an ENU mouse mutant confirmed in both model organisms that ARMC4 is critical for left-right patterning. We demonstrate that ARMC4 is an axonemal protein that is necessary for proper targeting and anchoring of ODAs.
Keywords: Amino Acid Sequence; Animals; Armadillo Domain Proteins; Axoneme; Body Patterning; Cilia; DNA Copy Number Variations; DNA Mutational Analysis; Dyneins; Gene Expression Regulation; Humans; Kartagener Syndrome; Mice; Microtubule-Associated Proteins; Molecular Sequence Data; Mutation; Respiratory System; Zebrafish

Associations between metabolomic compounds and incident heart failure among African Americans: the ARIC Study. - Zheng, Yan; Yu, Bing; Alexander, Danny; Manolio, Teri A; Aguilar, David; Coresh, Josef; Heiss, Gerardo; Boerwinkle, Eric; Nettleton, Jennifer A (Am J Epidemiol, 2013)
Heart failure is more prevalent among African Americans than in the general population. Metabolomic studies among African Americans may efficiently identify novel biomarkers of heart failure. We used untargeted methods to measure 204 stable serum metabolites and evaluated their associations with incident heart failure hospitalization (n = 276) after a median follow-up of 20 years (1987-2008) by using Cox regression in data from 1,744 African Americans aged 45-64 years without heart failure at baseline from the Jackson, Mississippi, field center of the Atherosclerosis Risk in Communities (ARIC) Study. After adjustment for established risk factors, we found that 16 metabolites (6 named with known structural identities and 10 unnamed with unknown structural identities, the latter denoted by using the format X-12345) were associated with incident heart failure (P < 0.0004 based on a modified Bonferroni procedure). Of the 6 named metabolites, 4 are involved in amino acid metabolism, 1 (prolylhydroxyproline) is a dipeptide, and 1 (erythritol) is a sugar alcohol. After additional adjustment for kidney function, 2 metabolites remained associated with incident heart failure (for metabolite X-11308, hazard ratio = 0.75, 95% confidence interval: 0.65, 0.86; for metabolite X-11787, hazard ratio = 1.23, 95% confidence interval: 1.10, 1.37). Further structural analysis revealed X-11308 to be a dihydroxy docosatrienoic acid and X-11787 to be an isoform of either hydroxyleucine or hydroxyisoleucine. Our metabolomic analysis revealed novel biomarkers associated with incident heart failure independent of traditional risk factors.
Keywords: Age Distribution; Atherosclerosis; Biomarkers; Black or African American; Comorbidity; Diabetes Mellitus; Female; Follow-Up Studies; Heart Failure; Humans; Hypertension; Kidney Diseases; Male; Metabolomics; Middle Aged; Mississippi; Obesity; Proportional Hazards Models; Sedentary Behavior

Bacterial discrimination by dictyostelid amoebae reveals the complexity of ancient interspecies interactions. - Nasser, Waleed; Santhanam, Balaji; Miranda, Edward Roshan; Parikh, Anup; Juneja, Kavina; Rot, Gregor; Dinh, Chris; Chen, Rui; Zupan, Blaz; Shaulsky, Gad; Kuspa, Adam (Curr Biol, 2013)
BACKGROUND: Amoebae and bacteria interact within predator-prey and host-pathogen relationships, but the general response of amoeba to bacteria is not well understood. The amoeba Dictyostelium discoideum feeds on, and is colonized by, diverse bacterial species, including Gram-positive [Gram(+)] and Gram-negative [Gram(-)] bacteria, two major groups of bacteria that differ in structure and macromolecular composition. RESULTS: Transcriptional profiling of D. discoideum revealed sets of genes whose expression is enriched in amoebae interacting with different species of bacteria, including sets that appear specific to amoebae interacting with Gram(+) or with Gram(-) bacteria. In a genetic screen utilizing the growth of mutant amoebae on a variety of bacteria as a phenotypic readout, we identified amoebal genes that are only required for growth on Gram(+) bacteria, including one that encodes the cell-surface protein gp130, as well as several genes that are only required for growth on Gram(-) bacteria, including one that encodes a putative lysozyme, AlyL. These genes are required for parts of the transcriptional response of wild-type amoebae, and this allowed their classification into potential response pathways. CONCLUSIONS: We have defined genes that are critical for amoebal survival during feeding on Gram(+), or Gram(-), bacteria that we propose form part of a regulatory network that allows D. discoideum to elicit specific cellular responses to different species of bacteria in order to optimize survival.
Keywords: Dictyostelium; Gene Expression Profiling; Genes, Bacterial; Genes, Protozoan; Gram-Negative Bacteria; Gram-Positive Bacteria; Host-Pathogen Interactions; Mutation; Transcription, Genetic

Bioactivity and bioavailability of ginsenosides are dependent on the glycosidase activities of the A/J mouse intestinal microbiome defined by pyrosequencing. - Niu, Tao; Smith, Diane L; Yang, Zhen; Gao, Song; Yin, Taijun; Jiang, Zhi-Hong; You, Ming; Gibbs, Richard A; Petrosino, Joseph F; Hu, Ming (Pharm Res, 2013)
PURPOSE: To investigate the ability of bacteria in the intestinal microbiome to convert naturally occurring primary ginsenosides in red ginseng extract to active secondary ginsenosides. METHODS: Anti-proliferative ginsenoside activity was tested using mouse lung cancer LM1 cells. Permeabilities were evaluated in Caco-2 cell monolayers. Systemic exposure of secondary ginsenosides was determined in A/J mice. 16S rRNA gene pyrosequencing was used to determine membership and abundance of bacteria in intestinal microbiome. RESULTS: Secondary ginsenoside C-K exhibited higher anti-proliferative activity and permeability than primary ginsenosides. Significant amounts of secondary ginsenosides (F2 and C-K) were found in blood of A/J mice following oral administration of primary ginsenoside Rb1. Because mammalian cells did not hydrolyze ginsenoside, we determined the ability of bacteria to hydrolyze ginsenosides and found that Rb1 underwent stepwise hydrolysis to Rd, F2, and then C-K. Formation of F2 from Rd was the rate-limiting step in the biotransformation of Rb1 to C-K. CONCLUSION: Conversion to F2 is the rate-limiting step in bioactivation of primary ginsenosides by A/J mouse intestinal microbiome, whose characterization reveals the presence of certain bacterial families capable of enabling the formation of F2 and C-K in vivo.
Keywords: Animals; Antineoplastic Agents, Phytogenic; Bacteria; Biological Availability; Biotransformation; Caco-2 Cells; Cell Line, Tumor; Cell Proliferation; Drugs, Chinese Herbal; Ginsenosides; Glycoside Hydrolases; Humans; Hydrolysis; Intestinal Mucosa; Intestines; Male; Metagenome; Mice; Neoplasms; Panax; RNA, Bacterial

Characterizing polymorphisms and allelic diversity of von Willebrand factor gene in the 1000 Genomes. - Wang, Q Y; Song, J; Gibbs, R A; Boerwinkle, E; Dong, J F; Yu, F L (J Thromb Haemost, 2013)
BACKGROUND: The von Willebrand factor (VWF) gene is highly polymorphic, with variants correlated with VWF antigen levels, adhesion activity, clearance and factor VIII binding. VWF mutations are detected in patients with von Willebrand disease (VWD), whereas polymorphic variants could be associated with thrombosis. However, information on the ethnic diversity of VWF variants and their association with diseases is limited. OBJECTIVES: To characterize novel VWF variants from different ethnicities in the general population. PATIENTS/METHODS: We analyzed samples from 1092 subjects of 14 ethnicities available in the 1000 Genomes database for VWF variants and their potential functional impacts. RESULTS: We identified 2728 SNPs and 91 insertions and deletions that had a high level of ethnic diversity, with Africans having the highest number of variants. The highest level of diversity was found in the D' and D2 domains. Among 94 non-synonymous variants, 31 were predicted to be deleterious, including 19 that were previously associated with VWD. Most of these 'VWD variants' had allele frequencies consistent with disease incidence in European subjects, but some had a significantly higher frequency in other ethnicities. The mutations R2185Q, H817Q and M740I associated with type 1 and type 2N VWD were present in more than 13% of African subjects. CONCLUSIONS: These results highlight the complexity of VWF variations in different ethnic groups and emphasize the importance of interrogating variations on multiple ethnic backgrounds for associations with bleeding and thrombosis.
Keywords: Asian People; Black or African American; Black People; Databases, Genetic; DNA Mutational Analysis; Ethnicity; Gene Frequency; Genetic Predisposition to Disease; Hemostasis; Human Genome Project; Humans; Incidence; Mutation; Phenotype; Polymorphism, Single Nucleotide; von Willebrand Diseases; von Willebrand Factor; White People

Comprehensive molecular characterization of clear cell renal cell carcinoma. (Nature, 2013)
Genetic changes underlying clear cell renal cell carcinoma (ccRCC) include alterations in genes controlling cellular oxygen sensing (for example, VHL) and the maintenance of chromatin states (for example, PBRM1). We surveyed more than 400 tumours using different genomic platforms and identified 19 significantly mutated genes. The PI(3)K/AKT pathway was recurrently mutated, suggesting this pathway as a potential therapeutic target. Widespread DNA hypomethylation was associated with mutation of the H3K36 methyltransferase SETD2, and integrative analysis suggested that mutations involving the SWI/SNF chromatin remodelling complex (PBRM1, ARID1A, SMARCA4) could have far-reaching effects on other pathways. Aggressive cancers demonstrated evidence of a metabolic shift, involving downregulation of genes involved in the TCA cycle, decreased AMPK and PTEN protein levels, upregulation of the pentose phosphate pathway and the glutamine transporter genes, increased acetyl-CoA carboxylase protein, and altered promoter methylation of miR-21 (also known as MIR21) and GRB10. Remodelling cellular metabolism thus constitutes a recurrent pattern in ccRCC that correlates with tumour stage and severity and offers new views on the opportunities for disease treatment.
Keywords: Acetyl-CoA Carboxylase; AMP-Activated Protein Kinases; Carcinoma, Renal Cell; Chromatin; Chromatin Assembly and Disassembly; Citric Acid Cycle; DNA Methylation; DNA Mutational Analysis; Epigenesis, Genetic; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Genome, Human; Genomics; GRB10 Adaptor Protein; Histone-Lysine N-Methyltransferase; Humans; Metabolic Networks and Pathways; MicroRNAs; Mutation; Pentose Phosphate Pathway; Phosphatidylinositol 3-Kinases; Proto-Oncogene Proteins c-akt; PTEN Phosphohydrolase; RNA, Neoplasm; Signal Transduction; Survival Analysis

CRHR1 genotypes, neural circuits and the diathesis for anxiety and depression. - Rogers, J; Raveendran, M; Fawcett, G L; Fox, A S; Shelton, S E; Oler, J A; Cheverud, J; Muzny, D M; Gibbs, R A; Davidson, R J; Kalin, N H (Mol Psychiatry, 2013)
The corticotrophin-releasing hormone (CRH) system integrates the stress response and is associated with stress-related psychopathology. Previous reports have identified interactions between childhood trauma and sequence variation in the CRH receptor 1 gene (CRHR1) that increase risk for affective disorders. However, the underlying mechanisms that connect variation in CRHR1 to psychopathology are unknown. To explore potential mechanisms, we used a validated rhesus macaque model to investigate association between genetic variation in CRHR1, anxious temperament (AT) and brain metabolic activity. In young rhesus monkeys, AT is analogous to the childhood risk phenotype that predicts the development of human anxiety and depressive disorders. Regional brain metabolism was assessed with (18)F-labeled fluoro-2-deoxyglucose (FDG) positron emission tomography in 236 young, normally reared macaques that were also characterized for AT. We show that single nucleotide polymorphisms (SNPs) affecting exon 6 of CRHR1 influence both AT and metabolic activity in the anterior hippocampus and amygdala, components of the neural circuit underlying AT. We also find evidence for association between SNPs in CRHR1 and metabolism in the intraparietal sulcus and precuneus. These translational data suggest that genetic variation in CRHR1 affects the risk for affective disorders by influencing the function of the neural circuit underlying AT and that differences in gene expression or the protein sequence involving exon 6 may be important. These results suggest that variation in CRHR1 may influence brain function before any childhood adversity and may be a diathesis for the interaction between CRHR1 genotypes and childhood trauma reported to affect human psychopathology.
Keywords: Animals; Anxiety; Brain; Depression; Disease Models, Animal; Female; Fluorodeoxyglucose F18; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Macaca mulatta; Male; Polymorphism, Single Nucleotide; Positron-Emission Tomography; Receptors, Corticotropin-Releasing Hormone

DANPOS: dynamic analysis of nucleosome position and occupancy by sequencing. - Chen, Kaifu; Xi, Yuanxin; Pan, Xuewen; Li, Zhaoyu; Kaestner, Klaus; Tyler, Jessica; Dent, Sharon; He, Xiangwei; Li, Wei (Genome Res, 2013)
Recent developments in next-generation sequencing have enabled whole-genome profiling of nucleosome organizations. Although several algorithms for inferring nucleosome position from a single experimental condition have been available, it remains a challenge to accurately define dynamic nucleosomes associated with environmental changes. Here, we report a comprehensive bioinformatics pipeline, DANPOS, explicitly designed for dynamic nucleosome analysis at single-nucleotide resolution. Using both simulated and real nucleosome data, we demonstrated that bias correction in preliminary data processing and optimal statistical testing significantly enhances the functional interpretation of dynamic nucleosomes. The single-nucleotide resolution analysis of DANPOS allows us to detect all three categories of nucleosome dynamics, such as position shift, fuzziness change, and occupancy change, using a uniform statistical framework. Pathway analysis indicates that each category is involved in distinct biological functions. We also analyzed the influence of sequencing depth and suggest that even 200-fold coverage is probably not enough to identify all the dynamic nucleosomes. Finally, based on nucleosome data from the human hematopoietic stem cells (HSCs) and mouse embryonic stem cells (ESCs), we demonstrated that DANPOS is also robust in defining functional dynamic nucleosomes, not only in promoters, but also in distal regulatory regions in the mammalian genome.
Keywords: Algorithms; Animals; Computational Biology; Computer Simulation; Databases, Genetic; DNA; High-Throughput Nucleotide Sequencing; Humans; Mice; Nucleosomes; Promoter Regions, Genetic; Protein Binding; ROC Curve

Dawn of ocular gene therapy: implications for molecular diagnosis in retinal disease. - Zaneveld, Jacques; Wang, Feng; Wang, Xia; Chen, Rui (Sci China Life Sci, 2013)
Personalized medicine aims to utilize genomic information about patients to tailor treatment. Gene replacement therapy for rare genetic disorders is perhaps the most extreme form of personalized medicine, in that the patients' genome wholly determines their treatment regimen. Gene therapy for retinal disorders is poised to become a clinical reality. The eye is an optimal site for gene therapy due to the relative ease of precise vector delivery, immune system isolation, and availability for monitoring of any potential damage or side effects. Due to these advantages, clinical trials for gene therapy of retinal diseases are currently underway. A necessary precursor to such gene therapies is accurate molecular diagnosis of the mutation(s) underlying disease. In this review, we discuss the application of Next Generation Sequencing (NGS) to obtain such a diagnosis and identify disease causing genes, using retinal disorders as a case study. After reviewing ocular gene therapy, we discuss the application of NGS to the identification of novel Mendelian disease genes. We then compare current, array based mutation detection methods against next NGS-based methods in three retinal diseases: Leber's Congenital Amaurosis, Retinitis Pigmentosa, and Stargardt's disease. We conclude that next-generation sequencing based diagnosis offers several advantages over array based methods, including a higher rate of successful diagnosis and the ability to more deeply and efficiently assay a broad spectrum of mutations. However, the relative difficulty of interpreting sequence results and the development of standardized, reliable bioinformatic tools remain outstanding concerns. In this review, recent advances NGS based molecular diagnoses are discussed, as well as their implications for the development of personalized medicine.
Keywords: Animals; DNA Mutational Analysis; Genetic Therapy; Genetic Vectors; High-Throughput Nucleotide Sequencing; Humans; Leber Congenital Amaurosis; Macular Degeneration; Molecular Diagnostic Techniques; Precision Medicine; Retinal Diseases; Retinitis Pigmentosa

dbNSFP v2.0: a database of human non-synonymous SNVs and their functional predictions and annotations. - Liu, Xiaoming; Jian, Xueqiu; Boerwinkle, Eric (Hum Mutat, 2013)
dbNSFP is a database developed for functional prediction and annotation of all potential non-synonymous single-nucleotide variants (nsSNVs) in the human genome. This database significantly facilitates the process of querying predictions and annotations from different databases/web-servers for large amounts of nsSNVs discovered in exome-sequencing studies. Here we report a recent major update of the database to version 2.0. We have rebuilt the SNV collection based on GENCODE 9 and currently the database includes 87,347,043 nsSNVs and 2,270,742 essential splice site SNVs (an 18% increase compared to dbNSFP v1.0). For each nsSNV dbNSFP v2.0 has added two prediction scores (MutationAssessor and FATHMM) and two conservation scores (GERP++ and SiPhy). The original five prediction and conservation scores in v1.0 (SIFT, Polyphen2, LRT, MutationTaster and PhyloP) have been updated. Rich functional annotations for SNVs and genes have also been added into the new version, including allele frequencies observed in the 1000 Genomes Project phase 1 data and the NHLBI Exome Sequencing Project, various gene IDs from different databases, functional descriptions of genes, gene expression and gene interaction information, among others. dbNSFP v2.0 is freely available for download at http://sites.google.com/site/jpopgen/dbNSFP.
Keywords: Computational Biology; Databases, Nucleic Acid; Exome; Gene Frequency; Genome, Human; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Software

Deletions of recessive disease genes: CNV contribution to carrier states and disease-causing alleles. - Boone, Philip M; Campbell, Ian M; Baggett, Brett C; Soens, Zachry T; Rao, Mitchell M; Hixson, Patricia M; Patel, Ankita; Bi, Weimin; Cheung, Sau Wai; Lalani, Seema R; Beaudet, Arthur L; Stankiewicz, Pawel; et al. (Genome Res, 2013)
Over 1200 recessive disease genes have been described in humans. The prevalence, allelic architecture, and per-genome load of pathogenic alleles in these genes remain to be fully elucidated, as does the contribution of DNA copy-number variants (CNVs) to carrier status and recessive disease. We mined CNV data from 21,470 individuals obtained by array-comparative genomic hybridization in a clinical diagnostic setting to identify deletions encompassing or disrupting recessive disease genes. We identified 3212 heterozygous potential carrier deletions affecting 419 unique recessive disease genes. Deletion frequency of these genes ranged from one occurrence to 1.5%. When compared with recessive disease genes never deleted in our cohort, the 419 recessive disease genes affected by at least one carrier deletion were longer and located farther from known dominant disease genes, suggesting that the formation and/or prevalence of carrier CNVs may be affected by both local and adjacent genomic features and by selection. Some subjects had multiple carrier CNVs (307 subjects) and/or carrier deletions encompassing more than one recessive disease gene (206 deletions). Heterozygous deletions spanning multiple recessive disease genes may confer carrier status for multiple single-gene disorders, for complex syndromes resulting from the combination of two or more recessive conditions, or may potentially cause clinical phenotypes due to a multiply heterozygous state. In addition to carrier mutations, we identified homozygous and hemizygous deletions potentially causative for recessive disease. We provide further evidence that CNVs contribute to the allelic architecture of both carrier and recessive disease-causing mutations. Thus, a complete recessive carrier screening method or diagnostic test should detect CNV alleles.
Keywords: Alleles; Comparative Genomic Hybridization; Databases, Genetic; DNA Copy Number Variations; Gene Deletion; Gene Frequency; Genes, Dominant; Genes, Recessive; Genetic Diseases, Inborn; Homozygote; Humans

Detection of clinically relevant copy number variants with whole-exome sequencing. - de Ligt, Joep; Boone, Philip M; Pfundt, Rolph; Vissers, Lisenka E L M; Richmond, Todd; Geoghegan, Joel; O'Moore, Kathleen; de Leeuw, Nicole; Shaw, Christine; Brunner, Han G; Lupski, James R; Veltman, Joris A; et al. (Hum Mutat, 2013)
Copy number variation (CNV) is a common source of genetic variation that has been implicated in many genomic disorders. This has resulted in the widespread application of genomic microarrays as a first-tier diagnostic tool for CNV detection. More recently, whole-exome sequencing (WES) has been proven successful for the detection of clinically relevant point mutations and small insertion-deletions exome wide. We evaluate the utility of short-read WES (SOLiD 5500xl) to detect clinically relevant CNVs in DNA from 10 patients with intellectual disability and compare these results to data from two independent high-resolution microarrays. Eleven of the 12 clinically relevant CNVs were detected via read-depth analysis of WES data; a heterozygous single-exon deletion remained undetected by all algorithms evaluated. Although the detection power of WES for small CNVs currently does not match that of high-resolution microarray platforms, we show that the majority (88%) of rare coding CNVs containing three or more exons are successfully identified by WES. These results show that the CNV detection resolution of WES is comparable to that of medium-resolution genomic microarrays commonly used as clinical assays. The combined detection of point mutations, indels, and CNVs makes WES a very attractive first-tier diagnostic test for genetically heterogeneous disorders.
Keywords: Algorithms; DNA Copy Number Variations; Exome; Genetic Testing; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Intellectual Disability; Reproducibility of Results

Evidence for replicative mechanism in a CHD7 rearrangement in a patient with CHARGE syndrome. - Vatta, Matteo; Niu, Zhiyv; Lupski, James R; Putnam, Philip; Spoonamore, Katherine G; Fang, Ping; Eng, Christine M; Willis, Alecia S (Am J Med Genet A, 2013)
Haploinsufficiency of CHD7 (OMIM# 608892) is known to cause CHARGE syndrome (OMIM# 214800). Molecular testing supports a definitive diagnosis in approximately 65-70% of cases. Most CHD7 mutations arise de novo, and no mutations affecting exon-7 have been reported to date. We report on an 8-year-old girl diagnosed with CHARGE syndrome that was referred to our laboratory for comprehensive CHD7 gene screening. Genomic DNA from the subject with a suspected diagnosis of CHARGE was isolated from peripheral blood lymphocytes and comprehensive Sanger sequencing, along with deletion/duplication analysis of the CHD7 gene using multiplex ligation-dependent probe amplification (MLPA), was performed. MLPA analysis identified a reduced single probe signal for exon-7 of the CHD7 gene consistent with potential heterozygous deletion. Long-range PCR breakpoint analysis identified a complex genomic rearrangement (CGR) leading to the deletion of exon-7 and breakpoints consistent with a replicative mechanism such as fork stalling and template switching (FoSTeS) or microhomology-mediated break-induced replication (MMBIR). Taken together this represents the first evidence for a CHD7 intragenic CGR in a patient with CHARGE syndrome leading to what appears to be also the first report of a mutation specifically disrupting exon-7. Although likely rare, CGR may represent an overlooked mechanism in subjects with CHARGE syndrome that can be missed by current sequencing and dosage assays.
Keywords: Abnormalities, Multiple; CHARGE Syndrome; Child; DNA Helicases; DNA Replication; DNA-Binding Proteins; Exons; Female; Gene Deletion; Haploinsufficiency; Humans; Mutation

Exome sequencing of a patient with suspected mitochondrial disease reveals a likely multigenic etiology. - Craigen, William J; Graham, Brett H; Wong, Lee-Jun; Scaglia, Fernando; Lewis, Richard Alan; Bonnen, Penelope E (BMC Med Genet, 2013)
BACKGROUND: The clinical features of mitochondrial disease are complex and highly variable, leading to challenges in establishing a specific diagnosis. Despite being one of the most commonly occurring inherited genetic diseases with an incidence of 1/5000, ~90% of these complex patients remain without a DNA-based diagnosis. We report our efforts to identify the pathogenetic cause for a patient with typical features of mitochondrial disease including infantile cataracts, CPEO, ptosis, progressive distal muscle weakness, and ataxia who carried a diagnosis of mitochondrial disease for over a decade. METHODS: Whole exome sequencing and bioinformatic analysis of these data were conducted on the proband. RESULTS: Exome sequencing studies showed a homozygous splice site mutation in SETX, which is known to cause Spinocerebellar Ataxia, Autosomal Recessive 1 (SCAR1). Additionally a missense mutation was identified in a highly conserved position of the OCRL gene, which causes Lowe Syndrome and Dent Disease 2. CONCLUSIONS: This patient's complex phenotype reflects a complex genetic etiology in which no single gene explained the complete clinical presentation. These genetic studies reveal that this patient does not have mitochondrial disease but rather a genocopy caused by more than one mutant locus. This study demonstrates the benefit of exome sequencing in providing molecular diagnosis to individuals with complex clinical presentations.
Keywords: Adult; Computational Biology; DNA Helicases; Exome; Genetic Diseases, X-Linked; Genetic Loci; Homozygote; Humans; Male; Mitochondrial Diseases; Multifunctional Enzymes; Mutation, Missense; Nephrolithiasis; Oculocerebrorenal Syndrome; Pedigree; Phenotype; Phosphoric Monoester Hydrolases; RNA Helicases; RNA, Ribosomal, 16S; Sequence Analysis, DNA; Spinocerebellar Ataxias; Spinocerebellar Degenerations

A functional variomics tool for discovering drug-resistance genes and drug targets. - Huang, Zhiwei; Chen, Kaifu; Zhang, Jianhuai; Li, Yongxiang; Wang, Hui; Cui, Dandan; Tang, Jiangwu; Liu, Yong; Shi, Xiaomin; Li, Wei; Liu, Dan; Chen, Rui; et al. (Cell Rep, 2013)
Comprehensive discovery of genetic mechanisms of drug resistance and identification of in vivo drug targets represent significant challenges. Here we present a functional variomics technology in the model organism Saccharomyces cerevisiae. This tool analyzes numerous genetic variants and effectively tackles both problems simultaneously. Using this tool, we discovered almost all genes that, due to mutations or modest overexpression, confer resistance to rapamycin, cycloheximide, and amphotericin B. Most significant among the resistance genes were drug targets, including multiple targets of a given drug. With amphotericin B, we discovered the highly conserved membrane protein Pmp3 as a potent resistance factor and a possible target. Widespread application of this tool should allow rapid identification of conserved resistance mechanisms and targets of many more compounds. New genes and alleles that confer resistance to other stresses can also be discovered. Similar tools in other systems, such as human cell lines, will also be useful.
Keywords: Alleles; Amphotericin B; Antifungal Agents; Cell Cycle Proteins; Cycloheximide; Drug Resistance, Microbial; Mutation; Phosphatidylinositol 3-Kinases; Phosphoinositide-3 Kinase Inhibitors; Proteolipids; Ribosomal Proteins; Saccharomyces cerevisiae; Saccharomyces cerevisiae Proteins; Sirolimus

Incidental copy-number variants identified by routine genome testing in a clinical population. - Boone, Philip M; Soens, Zachry T; Campbell, Ian M; Stankiewicz, Pawel; Cheung, Sau Wai; Patel, Ankita; Beaudet, Arthur L; Plon, Sharon E; Shaw, Chad A; McGuire, Amy L; Lupski, James R (Genet Med, 2013)
PURPOSE: Mutational load of susceptibility variants has not been studied on a genomic scale in a clinical population, nor has the potential to identify these mutations as incidental findings during clinical testing been systematically ascertained. METHODS: Array comparative genomic hybridization, a method for genome-wide detection of DNA copy-number variants, was performed clinically on DNA from 9,005 individuals. Copy-number variants encompassing or disrupting single genes were identified and analyzed for their potential to confer predisposition to dominant, adult-onset disease. Multigene copy-number variants affecting dominant, adult-onset cancer syndrome genes were also assessed. RESULTS: In our cohort, 83 single-gene copy-number variants affected 40 unique genes associated with dominant, adult-onset disorders and unrelated to the patients' referring diagnoses (i.e., incidental) were found. Fourteen of these copy-number variants are likely disease-predisposing, 25 are likely benign, and 44 are of unknown clinical consequence. When incidental copy-number variants spanning up to 20 genes were considered, 27 copy-number variants affected 17 unique genes associated with dominant, adult-onset cancer predisposition. CONCLUSION: Copy-number variants potentially conferring susceptibility to adult-onset disease can be identified as incidental findings during routine genome-wide testing. Some of these mutations may be medically actionable, enabling disease surveillance or prevention; however, most incidentally observed single-gene copy-number variants are currently of unclear significance to the patient.
Keywords: Age of Onset; Base Sequence; Chromosome Mapping; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Order; Genetic Predisposition to Disease; Humans; Inheritance Patterns; Male; Reproducibility of Results

Integrated genomic characterization of endometrial carcinoma. - Kandoth, Cyriac; Schultz, Nikolaus; Cherniack, Andrew D; Akbani, Rehan; Liu, Yuexin; Shen, Hui; Robertson, A Gordon; Pashtan, Itai; Shen, Ronglai; Benz, Christopher C; Yau, Christina; Laird, Peter W; et al. (Nature, 2013)
We performed an integrated genomic, transcriptomic and proteomic characterization of 373 endometrial carcinomas using array- and sequencing-based technologies. Uterine serous tumours and ∼25% of high-grade endometrioid tumours had extensive copy number alterations, few DNA methylation changes, low oestrogen receptor/progesterone receptor levels, and frequent TP53 mutations. Most endometrioid tumours had few copy number alterations or TP53 mutations, but frequent mutations in PTEN, CTNNB1, PIK3CA, ARID1A and KRAS and novel mutations in the SWI/SNF chromatin remodelling complex gene ARID5B. A subset of endometrioid tumours that we identified had a markedly increased transversion mutation frequency and newly identified hotspot mutations in POLE. Our results classified endometrial cancers into four categories: POLE ultramutated, microsatellite instability hypermutated, copy-number low, and copy-number high. Uterine serous carcinomas share genomic features with ovarian serous and basal-like breast carcinomas. We demonstrated that the genomic features of endometrial carcinomas permit a reclassification that may affect post-surgical adjuvant treatment for women with aggressive tumours.
Keywords: Breast Neoplasms; Chromosome Aberrations; DNA Copy Number Variations; DNA Mutational Analysis; DNA Polymerase II; DNA-Binding Proteins; Endometrial Neoplasms; Exome; Female; Gene Expression Regulation, Neoplastic; Genome, Human; Genomics; Humans; Ovarian Neoplasms; Poly-ADP-Ribose Binding Proteins; Signal Transduction; Transcription Factors

Integrative genomic characterization of oral squamous cell carcinoma identifies frequent somatic drivers. - Pickering, Curtis R; Zhang, Jiexin; Yoo, Suk Young; Bengtsson, Linnea; Moorthy, Shhyam; Neskey, David M; Zhao, Mei; Ortega Alves, Marcus V; Chang, Kyle; Drummond, Jennifer; Cortez, Elsa; Xie, Tong-Xin; et al. (Cancer Discov, 2013)
The survival of patients with oral squamous cell carcinoma (OSCC) has not changed significantly in several decades, leading clinicians and investigators to search for promising molecular targets. To this end, we conducted comprehensive genomic analysis of gene expression, copy number, methylation, and point mutations in OSCC. Integrated analysis revealed more somatic events than previously reported, identifying four major driver pathways (mitogenic signaling, Notch, cell cycle, and TP53) and two additional key genes (FAT1, CASP8). The Notch pathway was defective in 66% of patients, and in follow-up studies of mechanism, functional NOTCH1 signaling inhibited proliferation of OSCC cell lines. Frequent mutation of caspase-8 (CASP8) defines a new molecular subtype of OSCC with few copy number changes. Although genomic alterations are dominated by loss of tumor suppressor genes, 80% of patients harbored at least one genomic alteration in a targetable gene, suggesting that novel approaches to treatment may be possible for this debilitating subset of head and neck cancers.
Keywords: Carcinoma, Squamous Cell; Caspase 8; Cell Line, Tumor; DNA Copy Number Variations; DNA Methylation; Gene Expression Regulation, Neoplastic; Genomics; Humans; Mouth Neoplasms; Point Mutation; Receptors, Notch

Longitudinal study shows increasing obesity and hyperglycemia in micronesia. - Murdock, David; Salit, Jacqueline; Stoffel, Markus; Friedman, Jeffrey M; Pe'er, Itsik; Breslow, Jan L; Bonnen, Penelope E (Obesity (Silver Spring), 2013)
OBJECTIVE: Obesity and diabetes are particularly high in indigenous populations exposed to a Western diet and lifestyle. The prevalence of obesity, diabetes, hyperglycemia, dyslipidemia, and hypertension in one such population, the Micronesian island of Kosrae was described. DESIGN AND METHODS: Longitudinal screenings for metabolic traits were conducted on adult Kosraens ≥ 20 years of age in 1994 and again in 2001. Data was obtained on 3,106 Kosraens, comprising ∼80% of the adult population. Diabetes was diagnosed using World Health Organization guidelines. Prevalences of obesity, hyperglycemia, dyslipidemia, and hypertension were assessed. RESULTS: The overall age-adjusted prevalence of diabetes increased from 14 to 21%. The most significant change observed in the population was increases in obesity and hyperglycemia, especially among young Kosraens and women. Obesity age-adjusted prevalence increased from 45 to 62%, and hyperglycemia age-adjusted prevalence increased from 19 to 44%. Of note, Kosraens as a group had unusually low high density lipoprotein (HDL) levels with 80% classified as low HDL by NCEP-ATPIII criteria, despite lacking the usually accompanying increase in triglycerides. Comparison to reports from other populations shows that Kosrae experiences one of the highest rates of obesity, hyperglycemia, and low HDL globally while maintaining relatively healthy levels of triglycerides. CONCLUSION: Our study shows a dramatic increase in obesity and hyperglycemia in Kosrae in just 7 years and forebodes significantly increased health risks for this part of the world.
Keywords: Adult; Aged; Cholesterol, HDL; Diabetes Mellitus; Dyslipidemias; Female; Humans; Hyperglycemia; Hypertension; Longitudinal Studies; Male; Micronesia; Middle Aged; Obesity; Prevalence; Sex Factors; Triglycerides; Young Adult

Mutations in FBXL4 cause mitochondrial encephalopathy and a disorder of mitochondrial DNA maintenance. - Bonnen, Penelope E; Yarham, John W; Besse, Arnaud; Wu, Ping; Faqeih, Eissa A; Al-Asmari, Ali Mohammad; Saleh, Mohammad A M; Eyaid, Wafaa; Hadeel, Alrukban; He, Langping; Smith, Frances; Yau, Shu; et al. (Am J Hum Genet, 2013)
Nuclear genetic disorders causing mitochondrial DNA (mtDNA) depletion are clinically and genetically heterogeneous, and the molecular etiology remains undiagnosed in the majority of cases. Through whole-exome sequencing, we identified recessive nonsense and splicing mutations in FBXL4 segregating in three unrelated consanguineous kindreds in which affected children present with a fatal encephalopathy, lactic acidosis, and severe mtDNA depletion in muscle. We show that FBXL4 is an F-box protein that colocalizes with mitochondria and that loss-of-function and splice mutations in this protein result in a severe respiratory chain deficiency, loss of mitochondrial membrane potential, and a disturbance of the dynamic mitochondrial network and nucleoid distribution in fibroblasts from affected individuals. Expression of the wild-type FBXL4 transcript in cell lines from two subjects fully rescued the levels of mtDNA copy number, leading to a correction of the mitochondrial biochemical deficit. Together our data demonstrate that mutations in FBXL4 are disease causing and establish FBXL4 as a mitochondrial protein with a possible role in maintaining mtDNA integrity and stability.
Keywords: Acidosis, Lactic; Base Sequence; Child; Child, Preschool; Chromosome Segregation; DNA, Mitochondrial; Electron Transport; F-Box Proteins; Female; Fibroblasts; Gene Dosage; Genes, Recessive; Genetic Predisposition to Disease; Humans; Infant; Infant, Newborn; Male; Mitochondrial Encephalomyopathies; Molecular Sequence Data; Muscle, Skeletal; Mutation; Oxidative Phosphorylation; Pedigree; Protein Transport; Ubiquitin-Protein Ligases

Mutations in VRK1 associated with complex motor and sensory axonal neuropathy plus microcephaly. - Gonzaga-Jauregui, Claudia; Lotze, Timothy; Jamal, Leila; Penney, Samantha; Campbell, Ian M; Pehlivan, Davut; Hunter, Jill V; Woodbury, Suzanne L; Raymond, Gerald; Adesina, Adekunle M; Jhangiani, Shalini N; Reid, Jeffrey G; et al. (JAMA Neurol, 2013)
IMPORTANCE: Patients with rare diseases and complex clinical presentations represent a challenge for clinical diagnostics. Genomic approaches are allowing the identification of novel variants in genes for very rare disorders, enabling a molecular diagnosis. Genomics is also revealing a phenotypic expansion whereby the full spectrum of clinical expression conveyed by mutant alleles at a locus can be better appreciated. OBJECTIVE: To elucidate the molecular cause of a complex neuropathy phenotype in 3 patients by applying genomic sequencing strategies. DESIGN, SETTING, AND PARTICIPANTS: Three affected individuals from 2 unrelated families presented with a complex neuropathy phenotype characterized by axonal sensorimotor neuropathy and microcephaly. They were recruited into the Centers for Mendelian Genomics research program to identify the molecular cause of their phenotype. Whole-genome, targeted whole-exome sequencing, and high-resolution single-nucleotide polymorphism arrays were performed in genetics clinics of tertiary care pediatric hospitals and biomedical research institutions. MAIN OUTCOMES AND MEASURES: Whole-genome and whole-exome sequencing identified the variants responsible for the patients' clinical phenotype. RESULTS: We identified compound heterozygous alleles in 2 affected siblings from 1 family and a homozygous nonsense variant in the third unrelated patient in the vaccinia-related kinase 1 gene (VRK1). In the latter subject, we found a common haplotype on which the nonsense mutation occurred and that segregates in the Ashkenazi Jewish population. CONCLUSIONS AND RELEVANCE: We report the identification of disease-causing alleles in 3 children from 2 unrelated families with a previously uncharacterized complex axonal motor and sensory neuropathy accompanied by severe nonprogressive microcephaly and cerebral dysgenesis. Our data raise the question of whether VRK1 mutations disturb cell cycle progression and may result in apoptosis of cells in the nervous system. The application of unbiased genomic approaches allows the identification of potentially pathogenic mutations in unsuspected genes in highly genetically heterogeneous and uncharacterized neurological diseases.
Keywords: Child; Child, Preschool; DNA Mutational Analysis; Female; Genotype; Hereditary Sensory and Motor Neuropathy; Humans; Infant; Intracellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Microcephaly; Mutation; Neural Conduction; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases

OikoBase: a genomics and developmental transcriptomics resource for the urochordate Oikopleura dioica. - Danks, Gemma; Campsteijn, Coen; Parida, Mrutyunjaya; Butcher, Stephen; Doddapaneni, Harsha; Fu, Bolei; Petrin, Raul; Metpally, Raghu; Lenhard, Boris; Wincker, Patrick; Chourrout, Daniel; Thompson, Eric M; et al. (Nucleic Acids Res, 2013)
We report the development of OikoBase (http://oikoarrays.biology.uiowa.edu/Oiko/), a tiling array-based genome browser resource for Oikopleura dioica, a metazoan belonging to the urochordates, the closest extant group to vertebrates. OikoBase facilitates retrieval and mining of a variety of useful genomics information. First, it includes a genome browser which interrogates 1260 genomic sequence scaffolds and features gene, transcript and CDS annotation tracks. Second, we annotated gene models with gene ontology (GO) terms and InterPro domains which are directly accessible in the browser with links to their entries in the GO (http://www.geneontology.org/) and InterPro (http://www.ebi.ac.uk/interpro/) databases, and we provide transcript and peptide links for sequence downloads. Third, we introduce the transcriptomics of a comprehensive set of developmental stages of O. dioica at high resolution and provide downloadable gene expression data for all developmental stages. Fourth, we incorporate a BLAST tool to identify homologs of genes and proteins. Finally, we include a tutorial that describes how to use OikoBase as well as a link to detailed methods, explaining the data generation and analysis pipeline. OikoBase will provide a valuable resource for research in chordate development, genome evolution and plasticity and the molecular ecology of this important marine planktonic organism.
Keywords: Animals; Data Mining; Databases, Genetic; Gene Expression Profiling; Genomics; Internet; Molecular Sequence Annotation; Oligonucleotide Array Sequence Analysis; Transcriptome; Urochordata

Persistent human herpesvirus-6 infection in patients with an inherited form of the virus. - Pantry, Shara N; Medveczky, Maria M; Arbuckle, Jesse H; Luka, Janos; Montoya, Jose G; Hu, Jianhong; Renne, Rolf; Peterson, Daniel; Pritchett, Joshua C; Ablashi, Dharam V; Medveczky, Peter G (J Med Virol, 2013)
Human herpesvirus-6 (HHV-6)A and 6B are ubiquitous betaherpesviruses viruses with lymphotropic and neurotropic potential. As reported earlier, these viruses establish latency by integration into the telomeres of host chromosomes. Chromosomally integrated HHV-6 (CIHHV-6) can be transmitted vertically from parent to child. Some CIHHV-6 patients are suffering from neurological symptoms, while others remain asymptomatic. Four patients with CIHHV-6 and CNS dysfunction were treated with valganciclovir or foscarnet. HHV-6 replication was detected by reverse transcriptase polymerase chain reaction amplification of a late envelope glycoprotein. In this study we also compared the inherited and persistent HHV-6 viruses by DNA sequencing. The prevalence of CIHHV-6 in this cohort of adult patients from the USA suffering from a wide range of neurological symptoms including long-term fatigue were found significantly greater than the reported 0.8% in the general population. Long-term antiviral therapy inhibited HHV-6 replication as documented by loss of viral mRNA production. Sequence comparison of the mRNA and the inherited viral genome revealed that the transcript is produced by an exogenous virus. In conclusion, the data presented here document that some individuals with CIHHV-6 are infected persistently with exogenous HHV-6 strains that lead to a wide range of neurological symptoms; the proposed name for this condition is inherited herpesvirus 6 syndrome or IHS.
Keywords: Adult; Antiviral Agents; Cohort Studies; DNA, Viral; Foscarnet; Ganciclovir; Herpesvirus 6, Human; Humans; Infectious Disease Transmission, Vertical; Prevalence; RNA, Viral; Roseolovirus Infections; Sequence Analysis, DNA; Treatment Outcome; United States; Valganciclovir; Virus Replication

PhenoDB: a new web-based tool for the collection, storage, and analysis of phenotypic features. - Hamosh, Ada; Sobreira, Nara; Hoover-Fong, Julie; Sutton, V Reid; Boehm, Corinne; Schiettecatte, François; Valle, David (Hum Mutat, 2013)
To interpret whole exome/genome sequence data for clinical and research purposes, comprehensive phenotypic information, knowledge of pedigree structure, and results of previous clinical testing are essential. With these requirements in mind and to meet the needs of the Centers for Mendelian Genomics project, we have developed PhenoDB (http://phenodb.net), a secure, Web-based portal for entry, storage, and analysis of phenotypic and other clinical information. The phenotypic features are organized hierarchically according to the major headings and subheadings of the Online Mendelian Inheritance in Man (OMIM®) clinical synopses, with further subdivisions according to structure and function. Every string allows for a free-text entry. All of the approximately 2,900 features use the preferred term from Elements of Morphology and are fully searchable and mapped to the Human Phenotype Ontology and Elements of Morphology. The PhenoDB allows for ascertainment of relevant information from a case in a family or cohort, which is then searchable by family, OMIM number, phenotypic feature, mode of inheritance, genes screened, and so on. The database can also be used to format phenotypic data for submission to dbGaP for appropriately consented individuals. PhenoDB was built using Django, an open source Web development tool, and is freely available through the Johns Hopkins McKusick-Nathans Institute of Genetic Medicine (http://phenodb.net).
Keywords: Databases, Factual; Genomics; Humans; Internet; Medical Informatics; Phenotype; Software

Rare complete knockouts in humans: population distribution and significant role in autism spectrum disorders. - Lim, Elaine T; Raychaudhuri, Soumya; Sanders, Stephan J; Stevens, Christine; Sabo, Aniko; MacArthur, Daniel G; Neale, Benjamin M; Kirby, Andrew; Ruderfer, Douglas M; Fromer, Menachem; Lek, Monkol; Liu, Li; et al. (Neuron, 2013)
To characterize the role of rare complete human knockouts in autism spectrum disorders (ASDs), we identify genes with homozygous or compound heterozygous loss-of-function (LoF) variants (defined as nonsense and essential splice sites) from exome sequencing of 933 cases and 869 controls. We identify a 2-fold increase in complete knockouts of autosomal genes with low rates of LoF variation (≤ 5% frequency) in cases and estimate a 3% contribution to ASD risk by these events, confirming this observation in an independent set of 563 probands and 4,605 controls. Outside the pseudoautosomal regions on the X chromosome, we similarly observe a significant 1.5-fold increase in rare hemizygous knockouts in males, contributing to another 2% of ASDs in males. Taken together, these results provide compelling evidence that rare autosomal and X chromosome complete gene knockouts are important inherited risk factors for ASD.
Keywords: Case-Control Studies; Child Development Disorders, Pervasive; Child, Preschool; Chromosomes, Human, X; Demography; Female; Gene Deletion; Genetic Variation; Homozygote; Humans; Linkage Disequilibrium; Loss of Heterozygosity; Male; Risk Factors

Replicative mechanisms for CNV formation are error prone. - Carvalho, Claudia M B; Pehlivan, Davut; Ramocki, Melissa B; Fang, Ping; Alleva, Benjamin; Franco, Luis M; Belmont, John W; Hastings, P J; Lupski, James R (Nat Genet, 2013)
We investigated 67 breakpoint junctions of gene copy number gains in 31 unrelated subjects. We observed a strikingly high frequency of small deletions and insertions (29%) apparently originating from polymerase slippage events, in addition to frameshifts and point mutations in homonucleotide runs (13%), at or flanking the breakpoint junctions of complex copy number variants. These single-nucleotide variants were generated concomitantly with the de novo complex genomic rearrangement (CGR) event. Our findings implicate low-fidelity, error-prone DNA polymerase activity in synthesis associated with DNA repair mechanisms as the cause of local increase in point mutation burden associated with human CGR.
Keywords: Base Sequence; DNA Breaks; DNA Copy Number Variations; DNA Repair; DNA Replication; Frameshift Mutation; Gene Rearrangement; Genetic Variation; Genotype; Humans; Sequence Analysis, DNA; Sequence Deletion

Reporting genomic sequencing results to ordering clinicians: incidental, but not exceptional. - Green, Robert C; Lupski, James R; Biesecker, Leslie G (JAMA, 2013)
Keywords: Disclosure; Genetic Predisposition to Disease; Genetic Testing; Humans; Incidental Findings; Mandatory Reporting; Mutation; Personal Autonomy; Risk; Sequence Analysis, DNA

RNA interference knockdown of DNA methyl-transferase 3 affects gene alternative splicing in the honey bee. - Li-Byarlay, Hongmei; Li, Yang; Stroud, Hume; Feng, Suhua; Newman, Thomas C; Kaneda, Megan; Hou, Kirk K; Worley, Kim C; Elsik, Christine G; Wickline, Samuel A; Jacobsen, Steven E; Ma, Jian; et al. (Proc Natl Acad Sci U S A, 2013)
Studies of DNA methylation from fungi, plants, and animals indicate that gene body methylation is ancient and highly conserved in eukaryotic genomes, but its role has not been clearly defined. It has been postulated that regulation of alternative splicing of transcripts was an original function of DNA methylation, but a direct experimental test of the effect of methylation on alternative slicing at the whole genome level has never been performed. To do this, we developed a unique method to administer RNA interference (RNAi) in a high-throughput and noninvasive manner and then used it to knock down the expression of DNA methyl-transferase 3 (dnmt3), which is required for de novo DNA methylation. We chose the honey bee (Apis mellifera) for this test because it has recently emerged as an important model organism for studying the effects of DNA methylation on development and social behavior, and DNA methylation in honey bees is predominantly on gene bodies. Here we show that dnmt3 RNAi decreased global genomic methylation level as expected and in addition caused widespread and diverse changes in alternative splicing in fat tissue. Four different types of splicing events were affected by dnmt3 gene knockdown, and change in two types, exon skipping and intron retention, was directly related to decreased methylation. These results demonstrate that one function of gene body DNA methylation is to regulate alternative splicing.
Keywords: Alternative Splicing; Animals; Bees; Behavior, Animal; DNA (Cytosine-5-)-Methyltransferases; DNA Methylation; Gene Knockdown Techniques; Insect Proteins; RNA Interference; Social Behavior

Whole-genome sequence-based analysis of high-density lipoprotein cholesterol. - Morrison, Alanna C; Voorman, Arend; Johnson, Andrew D; Liu, Xiaoming; Yu, Jin; Li, Alexander; Muzny, Donna; Yu, Fuli; Rice, Kenneth; Zhu, Chengsong; Bis, Joshua; Heiss, Gerardo; et al. (Nat Genet, 2013)
We describe initial steps for interrogating whole-genome sequence data to characterize the genetic architecture of a complex trait, levels of high-density lipoprotein cholesterol (HDL-C). We report whole-genome sequencing and analysis of 962 individuals from the Cohorts for Heart and Aging Research in Genetic Epidemiology (CHARGE) studies. From this analysis, we estimate that common variation contributes more to heritability of HDL-C levels than rare variation, and screening for mendelian variants for dyslipidemia identified individuals with extreme HDL-C levels. Whole-genome sequencing analyses highlight the value of regulatory and non-protein-coding regions of the genome in addition to protein-coding regions.
Keywords: Cholesterol, HDL; Computational Biology; Databases, Genetic; Genetic Variation; Genome, Human; Genome-Wide Association Study; Genomics; Heterozygote; Humans; Open Reading Frames

The 1000 Genomes Project: data management and community access. - Clarke, Laura; Zheng-Bradley, Xiangqun; Smith, Richard; Kulesha, Eugene; Xiao, Chunlin; Toneva, Iliana; Vaughan, Brendan; Preuss, Don; Leinonen, Rasko; Shumway, Martin; Sherry, Stephen; Flicek, Paul (Nat Methods, 2012)
The 1000 Genomes Project was launched as one of the largest distributed data collection and analysis projects ever undertaken in biology. In addition to the primary scientific goals of creating both a deep catalog of human genetic variation and extensive methods to accurately discover and characterize variation using new sequencing technologies, the project makes all of its data publicly available. Members of the project data coordination center have developed and deployed several tools to enable widespread data access.
Keywords: Computational Biology; Databases, Genetic; Genetic Variation; Genome, Human; Genomics; Humans; Sequence Analysis, DNA

Advanced methylome analysis after bisulfite deep sequencing: an example in Arabidopsis. - Dinh, Huy Q; Dubin, Manu; Fritz J Sedlazeck; Lettner, Nicole; Mittelsten Scheid, Ortrun; von Haeseler, Arndt (PLoS One, 2012)
Deep sequencing after bisulfite conversion (BS-Seq) is the method of choice to generate whole genome maps of cytosine methylation at single base-pair resolution. Its application to genomic DNA of Arabidopsis flower bud tissue resulted in the first complete methylome, determining a methylation rate of 6.7% in this tissue. BS-Seq reads were mapped onto an in silico converted reference genome, applying the so-called 3-letter genome method. Here, we present BiSS (Bisufite Sequencing Scorer), a new method applying Smith-Waterman alignment to map bisulfite-converted reads to a reference genome. In addition, we introduce a comprehensive adaptive error estimate that accounts for sequencing errors, erroneous bisulfite conversion and also wrongly mapped reads. The re-analysis of the Arabidopsis methylome data with BiSS mapped substantially more reads to the genome. As a result, it determines the methylation status of an extra 10% of cytosines and estimates the methylation rate to be 7.7%. We validated the results by individual traditional bisulfite sequencing for selected genomic regions. In addition to predicting the methylation status of each cytosine, BiSS also provides an estimate of the methylation degree at each genomic site. Thus, BiSS explores BS-Seq data more extensively and provides more information for downstream analysis.
Keywords: Arabidopsis; Base Sequence; Cytosine; DNA Methylation; Genome, Plant; High-Throughput Nucleotide Sequencing; Reference Standards; Reproducibility of Results; Sequence Alignment; Sequence Analysis, DNA; Sulfites

Analysis of microsatellite variation in Drosophila melanogaster with population-scale genome sequencing. - Fondon, John W; Martin, Andy; Richards, Stephen; Gibbs, Richard A; Mittelman, David (PLoS One, 2012)
Genome sequencing technologies promise to revolutionize our understanding of genetics, evolution, and disease by making it feasible to survey a broad spectrum of sequence variation on a population scale. However, this potential can only be realized to the extent that methods for extracting and interpreting distinct forms of variation can be established. The error profiles and read length limitations of early versions of next-generation sequencing technologies rendered them ineffective for some sequence variant types, particularly microsatellites and other tandem repeats, and fostered the general misconception that such variants are inherently inaccessible to these platforms. At the same time, tandem repeats have emerged as important sources of functional variation. Tandem repeats are often located in and around genes, and frequent mutations in their lengths exert quantitative effects on gene function and phenotype, rapidly degrading linkage disequilibrium between markers and traits. Sensitive identification of these variants in large-scale next-gen sequencing efforts will enable more comprehensive association studies capable of revealing previously invisible associations. We present a population-scale analysis of microsatellite repeats using whole-genome data from 158 inbred isolates from the Drosophila Genetics Reference Panel, a collection of over 200 extensively phenotypically characterized isolates from a single natural population, to uncover processes underlying repeat mutation and to enable associations with behavioral, morphological, and life-history traits. Analysis of repeat variation from next-generation sequence data will also enhance studies of genome stability and neurodegenerative diseases.
Keywords: Animals; Drosophila melanogaster; Genetic Variation; Genetics, Population; Genome; Genotype; Microsatellite Repeats; Mutation

Androgen receptor CAG repeat polymorphism in males of six non-human primate species. - Mubiru, James N; Cavazos, Nicole; Hemmat, Peggah; Garcia-Forey, Magdalena; Shade, Robert E; Rogers, Jeffrey (J Med Primatol, 2012)
BACKGROUND: Androgen receptor [CAG](n) microsatellite has been linked to human diseases. METHODS: Six non-human primates were genotyped for the [CAG](n) microsatellite. RESULTS: Marmosets and macaques are monomorphic, while mangabeys, baboons, and chimpanzees are polymorphic. CONCLUSIONS: Non-human primates that are polymorphic for the microsatellite are candidate animal models for CAG-related diseases.
Keywords: Animals; DNA; Male; Pan troglodytes; Polymerase Chain Reaction; Polymorphism, Genetic; Primates; Receptors, Androgen; Trinucleotide Repeats

Atlas2 Cloud: a framework for personal genome analysis in the cloud. - Evani, Uday S; Challis, Danny; Yu, Jin; Jackson, Andrew R; Paithankar, Sameer; Bainbridge, Matthew N; Jakkamsetti, Adinarayana; Pham, Peter; Coarfa, Cristian; Milosavljevic, Aleksandar; Yu, Fuli (BMC Genomics, 2012)
BACKGROUND: Until recently, sequencing has primarily been carried out in large genome centers which have invested heavily in developing the computational infrastructure that enables genomic sequence analysis. The recent advancements in next generation sequencing (NGS) have led to a wide dissemination of sequencing technologies and data, to highly diverse research groups. It is expected that clinical sequencing will become part of diagnostic routines shortly. However, limited accessibility to computational infrastructure and high quality bioinformatic tools, and the demand for personnel skilled in data analysis and interpretation remains a serious bottleneck. To this end, the cloud computing and Software-as-a-Service (SaaS) technologies can help address these issues. RESULTS: We successfully enabled the Atlas2 Cloud pipeline for personal genome analysis on two different cloud service platforms: a community cloud via the Genboree Workbench, and a commercial cloud via the Amazon Web Services using Software-as-a-Service model. We report a case study of personal genome analysis using our Atlas2 Genboree pipeline. We also outline a detailed cost structure for running Atlas2 Amazon on whole exome capture data, providing cost projections in terms of storage, compute and I/O when running Atlas2 Amazon on a large data set. CONCLUSIONS: We find that providing a web interface and an optimized pipeline clearly facilitates usage of cloud computing for personal genome analysis, but for it to be routinely used for large scale projects there needs to be a paradigm shift in the way we develop tools, in standard operating procedures, and in funding mechanisms.
Keywords: Databases, Genetic; Genome, Human; Humans; Internet; Software; User-Computer Interface

Brain copy number variants and neuropsychiatric traits. - Lupski, James R (Biol Psychiatry, 2012)
Keywords: Brain; DNA Copy Number Variations; Genetic Predisposition to Disease; Humans; Mental Disorders; Nervous System Diseases; Phenotype

Complete genome sequence of Enterococcus faecium strain TX16 and comparative genomic analysis of Enterococcus faecium genomes. - Qin, Xiang; Galloway-Peña, Jessica R; Sillanpaa, Jouko; Roh, Jung Hyeob; Nallapareddy, Sreedhar R; Chowdhury, Shahreen; Bourgogne, Agathe; Choudhury, Tina; Muzny, Donna M; Buhay, Christian J; Ding, Yan; Dugan-Rocha, Shannon; et al. (BMC Microbiol, 2012)
BACKGROUND: Enterococci are among the leading causes of hospital-acquired infections in the United States and Europe, with Enterococcus faecalis and Enterococcus faecium being the two most common species isolated from enterococcal infections. In the last decade, the proportion of enterococcal infections caused by E. faecium has steadily increased compared to other Enterococcus species. Although the underlying mechanism for the gradual replacement of E. faecalis by E. faecium in the hospital environment is not yet understood, many studies using genotyping and phylogenetic analysis have shown the emergence of a globally dispersed polyclonal subcluster of E. faecium strains in clinical environments. Systematic study of the molecular epidemiology and pathogenesis of E. faecium has been hindered by the lack of closed, complete E. faecium genomes that can be used as references. RESULTS: In this study, we report the complete genome sequence of the E. faecium strain TX16, also known as DO, which belongs to multilocus sequence type (ST) 18, and was the first E. faecium strain ever sequenced. Whole genome comparison of the TX16 genome with 21 E. faecium draft genomes confirmed that most clinical, outbreak, and hospital-associated (HA) strains (including STs 16, 17, 18, and 78), in addition to strains of non-hospital origin, group in the same clade (referred to as the HA clade) and are evolutionally considerably more closely related to each other by phylogenetic and gene content similarity analyses than to isolates in the community-associated (CA) clade with approximately a 3-4% average nucleotide sequence difference between the two clades at the core genome level. Our study also revealed that many genomic loci in the TX16 genome are unique to the HA clade. 380 ORFs in TX16 are HA-clade specific and antibiotic resistance genes are enriched in HA-clade strains. Mobile elements such as IS16 and transposons were also found almost exclusively in HA strains, as previously reported. CONCLUSIONS: Our findings along with other studies show that HA clonal lineages harbor specific genetic elements as well as sequence differences in the core genome which may confer selection advantages over the more heterogeneous CA E. faecium isolates. Which of these differences are important for the success of specific E. faecium lineages in the hospital environment remain(s) to be determined.
Keywords: DNA, Bacterial; Enterococcus faecium; Genome, Bacterial; Humans; Molecular Sequence Data; Sequence Analysis, DNA

Comprehensive molecular characterization of human colon and rectal cancer. (Nature, 2012)
To characterize somatic alterations in colorectal carcinoma, we conducted a genome-scale analysis of 276 samples, analysing exome sequence, DNA copy number, promoter methylation and messenger RNA and microRNA expression. A subset of these samples (97) underwent low-depth-of-coverage whole-genome sequencing. In total, 16% of colorectal carcinomas were found to be hypermutated: three-quarters of these had the expected high microsatellite instability, usually with hypermethylation and MLH1 silencing, and one-quarter had somatic mismatch-repair gene and polymerase ε (POLE) mutations. Excluding the hypermutated cancers, colon and rectum cancers were found to have considerably similar patterns of genomic alteration. Twenty-four genes were significantly mutated, and in addition to the expected APC, TP53, SMAD4, PIK3CA and KRAS mutations, we found frequent mutations in ARID1A, SOX9 and FAM123B. Recurrent copy-number alterations include potentially drug-targetable amplifications of ERBB2 and newly discovered amplification of IGF2. Recurrent chromosomal translocations include the fusion of NAV2 and WNT pathway member TCF7L1. Integrative analyses suggest new markers for aggressive colorectal carcinoma and an important role for MYC-directed transcriptional activation and repression.
Keywords: Colonic Neoplasms; DNA Copy Number Variations; DNA Methylation; Exome; Gene Expression Profiling; Humans; Mutation; Mutation Rate; Polymorphism, Single Nucleotide; Rectal Neoplasms; Sequence Analysis, DNA

Deep sequencing of systematic combinatorial libraries reveals β-lactamase sequence constraints at high resolution. - Deng, Zhifeng; Huang, Wanzhi; Bakkalbasi, Erol; Brown, Nicholas G; Adamski, Carolyn J; Rice, Kacie; Muzny, Donna; Gibbs, Richard A; Palzkill, Timothy (J Mol Biol, 2012)
In this study, combinatorial libraries were used in conjunction with ultrahigh-throughput sequencing to comprehensively determine the impact of each of the 19 possible amino acid substitutions at each residue position in the TEM-1 β-lactamase enzyme. The libraries were introduced into Escherichiacoli, and mutants were selected for ampicillin resistance. The selected colonies were pooled and subjected to ultrahigh-throughput sequencing to reveal the sequence preferences at each position. The depth of sequencing provided a clear, statistically significant picture of what amino acids are favored for ampicillin hydrolysis for all 263 positions of the enzyme in one experiment. Although the enzyme is generally tolerant of amino acid substitutions, several surface positions far from the active site are sensitive to substitutions suggesting a role for these residues in enzyme stability, solubility, or catalysis. In addition, information on the frequency of substitutions was used to identify mutations that increase enzyme thermodynamic stability. Finally, a comparison of sequence requirements based on the mutagenesis results versus those inferred from sequence conservation in an alignment of 156 class A β-lactamases reveals significant differences in that several residues in TEM-1 do not tolerate substitutions and yet extensive variation is observed in the alignment and vice versa. An analysis of the TEM-1 and other class A structures suggests that residues that vary in the alignment may nevertheless make unique, but important, interactions within individual enzymes.
Keywords: Amino Acid Sequence; Amino Acid Substitution; Ampicillin; Ampicillin Resistance; Base Sequence; beta-Lactamases; DNA Mutational Analysis; Enzyme Stability; Escherichia coli; Gene Library; High-Throughput Nucleotide Sequencing; Hydrolysis; Models, Molecular; Mutant Proteins; Mutation Rate; Selection, Genetic; Solubility; Thermodynamics

The Drosophila melanogaster Genetic Reference Panel. - Mackay, Trudy F C; Richards, Stephen; Stone, Eric A; Barbadilla, Antonio; Ayroles, Julien F; Zhu, Dianhui; Casillas, Sònia; Han, Yi; Magwire, Michael M; Cridland, Julie M; Richardson, Mark F; Anholt, Robert R H; et al. (Nature, 2012)
A major challenge of biology is understanding the relationship between molecular genetic variation and variation in quantitative traits, including fitness. This relationship determines our ability to predict phenotypes from genotypes and to understand how evolutionary forces shape variation within and between species. Previous efforts to dissect the genotype-phenotype map were based on incomplete genotypic information. Here, we describe the Drosophila melanogaster Genetic Reference Panel (DGRP), a community resource for analysis of population genomics and quantitative traits. The DGRP consists of fully sequenced inbred lines derived from a natural population. Population genomic analyses reveal reduced polymorphism in centromeric autosomal regions and the X chromosome, evidence for positive and negative selection, and rapid evolution of the X chromosome. Many variants in novel genes, most at low frequency, are associated with quantitative traits and explain a large fraction of the phenotypic variance. The DGRP facilitates genotype-phenotype mapping using the power of Drosophila genetics.
Keywords: Alleles; Animals; Centromere; Chromosomes, Insect; Drosophila melanogaster; Genome-Wide Association Study; Genomics; Genotype; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Selection, Genetic; Starvation; Telomere; X Chromosome

Epistasis dominates the genetic architecture of Drosophila quantitative traits. - Huang, Wen; Richards, Stephen; Carbone, Mary Anna; Zhu, Dianhui; Anholt, Robert R H; Ayroles, Julien F; Duncan, Laura; Jordan, Katherine W; Lawrence, Faye; Magwire, Michael M; Warner, Crystal B; Blankenburg, Kerstin; et al. (Proc Natl Acad Sci U S A, 2012)
Epistasis-nonlinear genetic interactions between polymorphic loci-is the genetic basis of canalization and speciation, and epistatic interactions can be used to infer genetic networks affecting quantitative traits. However, the role that epistasis plays in the genetic architecture of quantitative traits is controversial. Here, we compared the genetic architecture of three Drosophila life history traits in the sequenced inbred lines of the Drosophila melanogaster Genetic Reference Panel (DGRP) and a large outbred, advanced intercross population derived from 40 DGRP lines (Flyland). We assessed allele frequency changes between pools of individuals at the extremes of the distribution for each trait in the Flyland population by deep DNA sequencing. The genetic architecture of all traits was highly polygenic in both analyses. Surprisingly, none of the SNPs associated with the traits in Flyland replicated in the DGRP and vice versa. However, the majority of these SNPs participated in at least one epistatic interaction in the DGRP. Despite apparent additive effects at largely distinct loci in the two populations, the epistatic interactions perturbed common, biologically plausible, and highly connected genetic networks. Our analysis underscores the importance of epistasis as a principal factor that determines variation for quantitative traits and provides a means to uncover genetic networks affecting these traits. Knowledge of epistatic networks will contribute to our understanding of the genetic basis of evolutionarily and clinically important traits and enhance predictive ability at an individualized level in medicine and agriculture.
Keywords: Animals; Drosophila melanogaster; Epistasis, Genetic; Genes, Insect; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Exome capture reveals ZNF423 and CEP164 mutations, linking renal ciliopathies to DNA damage response signaling. - Chaki, Moumita; Airik, Rannar; Ghosh, Amiya K; Giles, Rachel H; Chen, Rui; Slaats, Gisela G; Wang, Hui; Hurd, Toby W; Zhou, Weibin; Cluckey, Andrew; Gee, Heon Yung; Ramaswami, Gokul; et al. (Cell, 2012)
Nephronophthisis-related ciliopathies (NPHP-RC) are degenerative recessive diseases that affect kidney, retina, and brain. Genetic defects in NPHP gene products that localize to cilia and centrosomes defined them as "ciliopathies." However, disease mechanisms remain poorly understood. Here, we identify by whole-exome resequencing, mutations of MRE11, ZNF423, and CEP164 as causing NPHP-RC. All three genes function within the DNA damage response (DDR) pathway. We demonstrate that, upon induced DNA damage, the NPHP-RC proteins ZNF423, CEP164, and NPHP10 colocalize to nuclear foci positive for TIP60, known to activate ATM at sites of DNA damage. We show that knockdown of CEP164 or ZNF423 causes sensitivity to DNA damaging agents and that cep164 knockdown in zebrafish results in dysregulated DDR and an NPHP-RC phenotype. Our findings link degenerative diseases of the kidney and retina, disorders of increasing prevalence, to mechanisms of DDR.
Keywords: Animals; Cilia; DNA Damage; DNA-Binding Proteins; Exome; Gene Knockdown Techniques; Genes, Recessive; Humans; Kidney Diseases, Cystic; Mice; Microtubule Proteins; MRE11 Homologue Protein; Proteins; Signal Transduction; Zebrafish

Gene structure in the sea urchin Strongylocentrotus purpuratus based on transcriptome analysis. - Tu, Qiang; Cameron, R Andrew; Worley, Kim C; Gibbs, Richard A; Davidson, Eric H (Genome Res, 2012)
A comprehensive transcriptome analysis has been performed on protein-coding RNAs of Strongylocentrotus purpuratus, including 10 different embryonic stages, six feeding larval and metamorphosed juvenile stages, and six adult tissues. In this study, we pooled the transcriptomes from all of these sources and focused on the insights they provide for gene structure in the genome of this recently sequenced model system. The genome had initially been annotated by use of computational gene model prediction algorithms. A large fraction of these predicted genes were recovered in the transcriptome when the reads were mapped to the genome and appropriately filtered and analyzed. However, in a manually curated subset, we discovered that more than half the computational gene model predictions were imperfect, containing errors such as missing exons, prediction of nonexistent exons, erroneous intron/exon boundaries, fusion of adjacent genes, and prediction of multiple genes from single genes. The transcriptome data have been used to provide a systematic upgrade of the gene model predictions throughout the genome, very greatly improving the research usability of the genomic sequence. We have constructed new public databases that incorporate information from the transcriptome analyses. The transcript-based gene model data were used to define average structural parameters for S. purpuratus protein-coding genes. In addition, we constructed a custom sea urchin gene ontology, and assigned about 7000 different annotated transcripts to 24 functional classes. Strong correlations became evident between given functional ontology classes and structural properties, including gene size, exon number, and exon and intron size.
Keywords: Animals; Computational Biology; Databases, Nucleic Acid; Exons; Female; Gene Expression Profiling; Genome; Introns; Male; Models, Genetic; Molecular Sequence Annotation; Molecular Sequence Data; Open Reading Frames; RNA, Spliced Leader; Strongylocentrotus purpuratus; Trans-Splicing; Transcriptome

Genome-wide single nucleotide polymorphism arrays as a diagnostic tool in patients with synchronous endometrial and ovarian cancer. - Ikeda, Yuji; Oda, Katsutoshi; Nakagawa, Shunsuke; Murayama-Hosokawa, Satsuki; Yamamoto, Shogo; Ishikawa, Shumpei; Wang, Linghua; Takazawa, Yutaka; Maeda, Daichi; Wada-Hiraike, Osamu; Kawana, Kei; Fukayama, Masashi; et al. (Int J Gynecol Cancer, 2012)
OBJECTIVE: Synchronous carcinomas in the endometrium and ovaries can be a single primary tumor with metastasis (SPM) or dual primary tumors (DP). Although the prognosis of DP without any metastases is significantly better than that of SPM, pathological diagnosis is difficult in tumors with similar histological features. MATERIALS AND METHODS: In 10 tumors from 5 patients with synchronous endometrial and ovarian carcinomas, 250K single nucleotide polymorphism arrays were performed. The patients were genetically diagnosed according to the pattern of copy number alterations (CNAs), in addition to microsatellite status and mutational analysis of PIK3CA, PTEN, K-Ras, and CTNNB1. RESULTS: Of the 5 patients, 3 exhibited identical CNA patterns, including type, loci, and degree of each alteration in the endometrial and ovarian carcinomas. The other 2 exhibited CNAs only in either endometrial or ovarian carcinoma. All 5 tumors had 1 or more genetic mutations in the genes examined. One patient exhibited mutations both in PIK3CA and PTEN at discordant sites between endometrial and ovarian carcinomas, whereas the other 4 exhibited concordant mutations. Overall, 4 of the 5 patients were genetically diagnosed with SPM, and the remaining 1 with DP. The pathological diagnosis was not in agreement with the genetic diagnosis in 4 of the 5 patients. CONCLUSIONS: Genome-wide genotyping diagnosis may represent a useful approach for distinguishing between SPM and DP in synchronous endometrial and ovarian carcinomas.
Keywords: Adult; beta Catenin; Biomarkers, Tumor; Class I Phosphatidylinositol 3-Kinases; DNA Copy Number Variations; Endometrial Neoplasms; Female; Genome, Human; Genotype; Humans; Immunoenzyme Techniques; Microsatellite Repeats; Middle Aged; Mutation; Neoplasm Grading; Neoplasm Staging; Neoplasms, Multiple Primary; Oligonucleotide Array Sequence Analysis; Ovarian Neoplasms; Phosphatidylinositol 3-Kinases; Polymorphism, Single Nucleotide; Prognosis; Proto-Oncogene Proteins; Proto-Oncogene Proteins p21(ras); PTEN Phosphohydrolase; ras Proteins

Genomic and SNP analyses demonstrate a distant separation of the hospital and community-associated clades of Enterococcus faecium. - Galloway-Peña, Jessica; Roh, Jung Hyeob; Latorre, Mauricio; Qin, Xiang; Murray, Barbara E (PLoS One, 2012)
Recent studies have pointed to the existence of two subpopulations of Enterococcus faecium, one containing primarily commensal/community-associated (CA) strains and one that contains most clinical or hospital-associated (HA) strains, including those classified by multi-locus sequence typing (MLST) as belonging to the CC17 group. The HA subpopulation more frequently has IS16, pathogenicity island(s), and plasmids or genes associated with antibiotic resistance, colonization, and/or virulence. Supporting the two clades concept, we previously found a 3-10% difference between four genes from HA-clade strains vs. CA-clade strains, including 5% difference between pbp5-R of ampicillin-resistant, HA strains and pbp5-S of ampicillin-sensitive, CA strains. To further investigate the core genome of these subpopulations, we studied 100 genes from 21 E. faecium genome sequences; our analyses of concatenated sequences, SNPs, and individual genes all identified two distinct groups. With the concatenated sequence, HA-clade strains differed by 0-1% from one another while CA clade strains differed from each other by 0-1.1%, with 3.5-4.2% difference between the two clades. While many strains had a few genes that grouped in one clade with most of their genes in the other clade, one strain had 28% of its genes in the CA clade and 72% in the HA clade, consistent with the predicted role of recombination in the evolution of E. faecium. Using estimates for Escherichia coli, molecular clock calculations using sSNP analysis indicate that these two clades may have diverged ≥1 million years ago or, using the higher mutation rate for Bacillus anthracis, ∼300,000 years ago. These data confirm the existence of two clades of E. faecium and show that the differences between the HA and CA clades occur at the core genomic level and long preceded the modern antibiotic era.
Keywords: Community-Acquired Infections; Cross Infection; DNA, Bacterial; Enterococcus faecium; Evolution, Molecular; Genetic Speciation; Genome, Bacterial; Gram-Positive Bacterial Infections; Hospitals; Humans; Models, Genetic; Phylogeny; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

High throughput sequencing methods for microbiome profiling: application to food animal systems. - Highlander, Sarah K (Anim Health Res Rev, 2012)
Analysis of microbial communities using high throughput sequencing methods began in the mid 2000s permitting the production of 1000s to 10,000s of sequence reads per sample and megabases of data per sequence run. This then unprecedented depth of sequencing allowed, for the first time, the discovery of the 'rare biosphere' in environmental samples. The technology was quickly applied to studies in several human subjects. Perhaps these early studies served as a reminder that though the microbes that inhabit mammals are known to outnumber host cells by an order of magnitude or more, most of these are unknown members of our second genome, or microbiome (as coined by Joshua Lederberg), because of our inability to culture them. High throughput methods for microbial 16S ribosomal RNA gene and whole genome shotgun (WGS) sequencing have now begun to reveal the composition and identity of archaeal, bacterial and viral communities at many sites, in and on the human body. Surveys of the microbiota of food production animals have been published in the past few years and future studies should benefit from protocols and tools developed from large-scale human microbiome studies. Nevertheless, production animal-related resources, such as improved host genome assemblies and increased numbers and diversity of host-specific microbial reference genome sequences, will be needed to permit meaningful and robust analysis of 16S rDNA and WGS sequence data.
Keywords: Animals; Animals, Domestic; Archaea; Bacteria; DNA, Ribosomal; Genes, rRNA; High-Throughput Nucleotide Sequencing; Humans; Meat; Metagenome; Metagenomics; RNA, Ribosomal, 16S; Sequence Analysis, RNA; Viruses

Identification of a single-stranded DNA virus associated with citrus chlorotic dwarf disease, a new member in the family Geminiviridae. - Loconsole, Giuliana; Saldarelli, Pasquale; Harshavardhan Doddapaneni; Savino, Vito; Martelli, Giovanni P; Saponari, Maria (Virology, 2012)
In the attempt to identify the causal agent of Citrus chlorotic dwarf disease (CCDD), a virus-like disorder of citrus, the small RNA fraction and total DNA from symptomatic citrus plants were subjected to high-throughput sequencing. DNA fragments deriving from an apparently new geminivirus-like agent were found and assembled by NGS to re-construct the entire viral genome. The newly identified virus has a circular single-stranded DNA genome comprising five open reading frames (ORFs) with sequence homologies with those encoded by geminiviruses. PCR and qPCR assays were successfully used for determining its presence in the CCDD-affected plants obtained by graft propagation. The larger genome size (3.64 vs. 2.5-3.0 kb) and a number of differences in its structural organization, identified this virus as a highly divergent member of the family Geminiviridae, to which the provisional name of Citrus chlorotic dwarf-associated virus (CCDaV) is assigned.
Keywords: Citrus; DNA, Single-Stranded; DNA, Viral; Geminiviridae; Genome, Viral; Molecular Sequence Data; Open Reading Frames; Plant Diseases; Sequence Analysis, DNA

Identity and function of a large gene network underlying mutagenic repair of DNA breaks. - Al Mamun, Abu Amar M; Lombardo, Mary-Jane; Shee, Chandan; Lisewski, Andreas M; Gonzalez, Caleb; Lin, Dongxu; Nehring, Ralf B; Saint-Ruf, Claude; Gibson, Janet L; Frisch, Ryan L; Lichtarge, Olivier; Hastings, P J; et al. (Science, 2012)
Mechanisms of DNA repair and mutagenesis are defined on the basis of relatively few proteins acting on DNA, yet the identities and functions of all proteins required are unknown. Here, we identify the network that underlies mutagenic repair of DNA breaks in stressed Escherichia coli and define functions for much of it. Using a comprehensive screen, we identified a network of ≥93 genes that function in mutation. Most operate upstream of activation of three required stress responses (RpoS, RpoE, and SOS, key network hubs), apparently sensing stress. The results reveal how a network integrates mutagenic repair into the biology of the cell, show specific pathways of environmental sensing, demonstrate the centrality of stress responses, and imply that these responses are attractive as potential drug targets for blocking the evolution of pathogens.
Keywords: Bacterial Proteins; DNA Breaks, Double-Stranded; DNA Repair; Escherichia coli; Gene Expression Regulation, Bacterial; Gene Regulatory Networks; Mutagenesis; Sigma Factor; SOS Response, Genetics; Stress, Physiological

Integrated analyses of microRNAs demonstrate their widespread influence on gene expression in high-grade serous ovarian carcinoma. - Creighton, Chad J; Hernandez-Herrera, Anadulce; Jacobsen, Anders; Levine, Douglas A; Mankoo, Parminder; Schultz, Nikolaus; Du, Ying; Zhang, Yiqun; Larsson, Erik; Sheridan, Robert; Xiao, Weimin; Spellman, Paul T; et al. (PLoS One, 2012)
BACKGROUND: The Cancer Genome Atlas (TCGA) Network recently comprehensively catalogued the molecular aberrations in 487 high-grade serous ovarian cancers, with much remaining to be elucidated regarding the microRNAs (miRNAs). Here, using TCGA ovarian data, we surveyed the miRNAs, in the context of their predicted gene targets. METHODS AND RESULTS: Integration of miRNA and gene patterns yielded evidence that proximal pairs of miRNAs are processed from polycistronic primary transcripts, and that intronic miRNAs and their host gene mRNAs derive from common transcripts. Patterns of miRNA expression revealed multiple tumor subtypes and a set of 34 miRNAs predictive of overall patient survival. In a global analysis, miRNA:mRNA pairs anti-correlated in expression across tumors showed a higher frequency of in silico predicted target sites in the mRNA 3'-untranslated region (with less frequency observed for coding sequence and 5'-untranslated regions). The miR-29 family and predicted target genes were among the most strongly anti-correlated miRNA:mRNA pairs; over-expression of miR-29a in vitro repressed several anti-correlated genes (including DNMT3A and DNMT3B) and substantially decreased ovarian cancer cell viability. CONCLUSIONS: This study establishes miRNAs as having a widespread impact on gene expression programs in ovarian cancer, further strengthening our understanding of miRNA biology as it applies to human cancer. As with gene transcripts, miRNAs exhibit high diversity reflecting the genomic heterogeneity within a clinically homogeneous disease population. Putative miRNA:mRNA interactions, as identified using integrative analysis, can be validated. TCGA data are a valuable resource for the identification of novel tumor suppressive miRNAs in ovarian as well as other cancers.
Keywords: 3' Untranslated Regions; Breast; Cell Line, Tumor; DNA Copy Number Variations; Female; Gene Expression Regulation, Neoplastic; Humans; MicroRNAs; Neoplasms, Cystic, Mucinous, and Serous; Ovarian Neoplasms

The KAT6B-related disorders genitopatellar syndrome and Ohdo/SBBYS syndrome have distinct clinical features reflecting distinct molecular mechanisms. - Campeau, Philippe M; Lu, James T; Dawson, Brian C; Fokkema, Ivo F A C; Robertson, Stephen P; Gibbs, Richard A; Lee, Brendan H (Hum Mutat, 2012)
Genitopatellar syndrome (GPS) and Say-Barber-Biesecker-Young-Simpson syndrome (SBBYSS or Ohdo syndrome) have both recently been shown to be caused by distinct mutations in the histone acetyltransferase KAT6B (a.k.a. MYST4/MORF). All variants are de novo dominant mutations that lead to protein truncation. Mutations leading to GPS occur in the proximal portion of the last exon and lead to the expression of a protein without a C-terminal domain. Mutations leading to SBBYSS occur either throughout the gene, leading to nonsense-mediated decay, or more distally in the last exon. Features present only in GPS are contractures, anomalies of the spine, ribs and pelvis, renal cysts, hydronephrosis, and agenesis of the corpus callosum. Features present only in SBBYSS include long thumbs and long great toes and lacrimal duct abnormalities. Several features occur in both, such as intellectual disability, congenital heart defects, and genital and patellar anomalies. We propose that haploinsufficiency or loss of a function mediated by the C-terminal domain causes the common features, whereas gain-of-function activities would explain the features unique to GPS. Further molecular studies and the compilation of mutations in a database for genotype-phenotype correlations (www.LOVD.nl/KAT6B) might help tease out answers to these questions and understand the developmental programs dysregulated by the different truncations.
Keywords: Abnormalities, Multiple; Base Sequence; Blepharophimosis; Blepharoptosis; Craniofacial Abnormalities; Databases, Nucleic Acid; DNA; Female; Genetic Association Studies; Haploinsufficiency; Heart Defects, Congenital; Histone Acetyltransferases; Humans; Intellectual Disability; Kidney; Male; Molecular Sequence Data; Mutation; Patella; Psychomotor Disorders; Scrotum; Sequence Deletion; Urogenital Abnormalities

Landscape of somatic retrotransposition in human cancers. - Lee, Eunjung; Iskow, Rebecca; Yang, Lixing; Gokcumen, Omer; Haseley, Psalm; Luquette, Lovelace J; Lohr, Jens G; Harris, Christopher C; Ding, Li; Wilson, Richard K; Wheeler, David A; Gibbs, Richard A; et al. (Science, 2012)
Transposable elements (TEs) are abundant in the human genome, and some are capable of generating new insertions through RNA intermediates. In cancer, the disruption of cellular mechanisms that normally suppress TE activity may facilitate mutagenic retrotranspositions. We performed single-nucleotide resolution analysis of TE insertions in 43 high-coverage whole-genome sequencing data sets from five cancer types. We identified 194 high-confidence somatic TE insertions, as well as thousands of polymorphic TE insertions in matched normal genomes. Somatic insertions were present in epithelial tumors but not in blood or brain cancers. Somatic L1 insertions tend to occur in genes that are commonly mutated in cancer, disrupt the expression of the target genes, and are biased toward regions of cancer-specific DNA hypomethylation, highlighting their potential impact in tumorigenesis.
Keywords: Base Sequence; Cell Transformation, Neoplastic; Colorectal Neoplasms; DNA Methylation; Female; Gene Expression Regulation, Neoplastic; Genes, Neoplasm; Genome, Human; Glioblastoma; Humans; Long Interspersed Nucleotide Elements; Male; Microsatellite Instability; Molecular Sequence Annotation; Molecular Sequence Data; Multiple Myeloma; Mutagenesis, Insertional; Mutation; Ovarian Neoplasms; Prostatic Neoplasms; Retroelements; Sequence Analysis, DNA

Loss-of-function mutations in TGFB2 cause a syndromic presentation of thoracic aortic aneurysm. - Lindsay, Mark E; Schepers, Dorien; Bolar, Nikhita Ajit; Doyle, Jefferson J; Gallo, Elena; Fert-Bober, Justyna; Kempers, Marlies J E; Fishman, Elliot K; Chen, Yichun; Myers, Loretha; Bjeda, Djahita; Oswald, Gretchen; et al. (Nat Genet, 2012)
Loeys-Dietz syndrome (LDS) associates with a tissue signature for high transforming growth factor (TGF)-β signaling but is often caused by heterozygous mutations in genes encoding positive effectors of TGF-β signaling, including either subunit of the TGF-β receptor or SMAD3, thereby engendering controversy regarding the mechanism of disease. Here, we report heterozygous mutations or deletions in the gene encoding the TGF-β2 ligand for a phenotype within the LDS spectrum and show upregulation of TGF-β signaling in aortic tissue from affected individuals. Furthermore, haploinsufficient Tgfb2(+/-) mice have aortic root aneurysm and biochemical evidence of increased canonical and noncanonical TGF-β signaling. Mice that harbor both a mutant Marfan syndrome (MFS) allele (Fbn1(C1039G/+)) and Tgfb2 haploinsufficiency show increased TGF-β signaling and phenotypic worsening in association with normalization of TGF-β2 expression and high expression of TGF-β1. Taken together, these data support the hypothesis that compensatory autocrine and/or paracrine events contribute to the pathogenesis of TGF-β-mediated vasculopathies.
Keywords: Animals; Aortic Aneurysm, Thoracic; Disease Models, Animal; Female; Fibrillin-1; Fibrillins; Haploinsufficiency; Humans; Loeys-Dietz Syndrome; Male; Marfan Syndrome; Mice; Mice, Knockout; Mice, Mutant Strains; Microfilament Proteins; Mutation; Pedigree; Phenotype; Signal Transduction; Syndrome; Transforming Growth Factor beta2

MAPK target sites of eyes absent are not required for eye development or survival in Drosophila. - Jusiak, Barbara; Abulimiti, Abuduaini; Haelterman, Nele; Chen, Rui; Mardon, Graeme (PLoS One, 2012)
Eyes absent (Eya) is a highly conserved transcription cofactor and protein phosphatase that plays an essential role in eye development and survival in Drosophila. Ectopic eye induction assays using cDNA transgenes have suggested that mitogen activated protein kinase (MAPK) activates Eya by phosphorylating it on two consensus target sites, S402 and S407, and that this activation potentiates the ability of Eya to drive eye formation. However, this mechanism has never been tested in normal eye development. In the current study, we generated a series of genomic rescue transgenes to investigate how loss- and gain-of-function mutations at these two MAPK target sites within Eya affect Drosophila survival and normal eye formation: eya(+)GR, the wild-type control; eya(SA)GR, which lacks phosphorylation at the two target residues; and eya(SDE)GR, which contains phosphomimetic amino acids at the same two residues. Contrary to the previous studies in ectopic eye development, all eya genomic transgenes tested rescue both eye formation and survival equally effectively. We conclude that, in contrast to ectopic eye formation, MAPK-mediated phosphorylation of Eya on S402 and S407 does not play a role in normal development. This is the first study in Drosophila to evaluate the difference in outcomes between genomic rescue and ectopic cDNA-based overexpression of the same gene. These findings indicate similar genomic rescue strategies may prove useful for re-evaluating other long-standing Drosophila developmental models.
Keywords: Animals; Compound Eye, Arthropod; Drosophila; Drosophila Proteins; Eye Proteins; Gene Expression Regulation, Developmental; Mitogen-Activated Protein Kinases; Mutation; Phenotype; Phosphorylation; Signal Transduction

Microarray-based capture of novel expressed cell type-specific transfrags (CoNECT) to annotate tissue-specific transcription in Drosophila melanogaster. - Hong, X; Doddapaneni, H; Comeron, J M; Rodesch, M J; Halvensleben, H A; Nien, C Y; Bolei, F; Metpally, R; Richmond, T A; Albert, T J; Manak, J R (G3 (Bethesda), 2012)
Faithful annotation of tissue-specific transcript isoforms is important not only to understand how genes are organized and regulated but also to identify potential novel, unannotated exons of genes, which may be additional targets of mutation in disease states or while performing mutagenic screens. We have developed a microarray enrichment methodology followed by long-read, next-generation sequencing for identification of unannotated transcript isoforms expressed in two Drosophila tissues, the ovary and the testis. Even with limited sequencing, these studies have identified a large number of novel transcription units, including 5' exons and extensions, 3' exons and extensions, internal exons and exon extensions, gene fusions, and both germline-specific splicing events and promoters. Additionally, comparing our capture dataset with tiling array and traditional RNA-seq analysis, we demonstrate that our enrichment strategy is able to capture low-abundance transcripts that cannot readily be identified by the other strategies. Finally, we show that our methodology can help identify transcriptional signatures of minority cell types within the ovary that would otherwise be difficult to reveal without the CoNECT enrichment strategy. These studies introduce an efficient methodology for cataloging tissue-specific transcriptomes in which specific classes of genes or transcripts can be targeted for capture and sequence, thus reducing the significant sequencing depth normally required for accurate annotation. Ovary and testis isotigs over 200 bp have been deposited with the GenBank Transcriptome Shotgun Assembly Sequence Database as bioproject no.PRJNA89451 (accession nos. JV208106–JV230865).
Keywords: Animals; Databases, Genetic; Drosophila melanogaster; Drosophila Proteins; Exons; Female; Male; Oligonucleotide Array Sequence Analysis; Ovary; Promoter Regions, Genetic; Protein Isoforms; RNA Splicing; Testis; Transcriptome

Mind the gap: upgrading genomes with Pacific Biosciences RS long-read sequencing technology. - English, Adam C; Richards, Stephen; Han, Yi; Wang, Min; Vee, Vanesa; Qu, Jiaxin; Qin, Xiang; Muzny, Donna M; Reid, Jeffrey G; Worley, Kim C; Gibbs, Richard A (PLoS One, 2012)
Many genomes have been sequenced to high-quality draft status using Sanger capillary electrophoresis and/or newer short-read sequence data and whole genome assembly techniques. However, even the best draft genomes contain gaps and other imperfections due to limitations in the input data and the techniques used to build draft assemblies. Sequencing biases, repetitive genomic features, genomic polymorphism, and other complicating factors all come together to make some regions difficult or impossible to assemble. Traditionally, draft genomes were upgraded to "phase 3 finished" status using time-consuming and expensive Sanger-based manual finishing processes. For more facile assembly and automated finishing of draft genomes, we present here an automated approach to finishing using long-reads from the Pacific Biosciences RS (PacBio) platform. Our algorithm and associated software tool, PBJelly, (publicly available at https://sourceforge.net/projects/pb-jelly/) automates the finishing process using long sequence reads in a reference-guided assembly process. PBJelly also provides "lift-over" co-ordinate tables to easily port existing annotations to the upgraded assembly. Using PBJelly and long PacBio reads, we upgraded the draft genome sequences of a simulated Drosophila melanogaster, the version 2 draft Drosophila pseudoobscura, an assembly of the Assemblathon 2.0 budgerigar dataset, and a preliminary assembly of the Sooty mangabey. With 24× mapped coverage of PacBio long-reads, we addressed 99% of gaps and were able to close 69% and improve 12% of all gaps in D. pseudoobscura. With 4× mapped coverage of PacBio long-reads we saw reads address 63% of gaps in our budgerigar assembly, of which 32% were closed and 63% improved. With 6.8× mapped coverage of mangabey PacBio long-reads we addressed 97% of gaps and closed 66% of addressed gaps and improved 19%. The accuracy of gap closure was validated by comparison to Sanger sequencing on gaps from the original D. pseudoobscura draft assembly and shown to be dependent on initial reference quality.
Keywords: Animals; Base Sequence; Cercocebus atys; Databases, Genetic; Decision Making; Drosophila; Genome; Melopsittacus; Reproducibility of Results; Sequence Analysis, DNA; Software

Mutations in the TGF-β repressor SKI cause Shprintzen-Goldberg syndrome with aortic aneurysm. - Doyle, Alexander J; Doyle, Jefferson J; Bessling, Seneca L; Maragh, Samantha; Lindsay, Mark E; Schepers, Dorien; Gillis, Elisabeth; Mortier, Geert; Homfray, Tessa; Sauls, Kimberly; Norris, Russell A; Huso, Nicholas D; et al. (Nat Genet, 2012)
Elevated transforming growth factor (TGF)-β signaling has been implicated in the pathogenesis of syndromic presentations of aortic aneurysm, including Marfan syndrome (MFS) and Loeys-Dietz syndrome (LDS). However, the location and character of many of the causal mutations in LDS intuitively imply diminished TGF-β signaling. Taken together, these data have engendered controversy regarding the specific role of TGF-β in disease pathogenesis. Shprintzen-Goldberg syndrome (SGS) has considerable phenotypic overlap with MFS and LDS, including aortic aneurysm. We identified causative variation in ten individuals with SGS in the proto-oncogene SKI, a known repressor of TGF-β activity. Cultured dermal fibroblasts from affected individuals showed enhanced activation of TGF-β signaling cascades and higher expression of TGF-β-responsive genes relative to control cells. Morpholino-induced silencing of SKI paralogs in zebrafish recapitulated abnormalities seen in humans with SGS. These data support the conclusions that increased TGF-β signaling is the mechanism underlying SGS and that high signaling contributes to multiple syndromic presentations of aortic aneurysm.
Keywords: Animals; Aortic Aneurysm; Arachnodactyly; Cells, Cultured; Craniosynostoses; DNA-Binding Proteins; Fibroblasts; Humans; Loeys-Dietz Syndrome; Marfan Syndrome; Mice; Mutation; Phenotype; Phosphorylation; Proto-Oncogene Mas; Proto-Oncogene Proteins; Signal Transduction; Transforming Growth Factor beta; Zebrafish

Patterns and rates of exonic de novo mutations in autism spectrum disorders. - Neale, Benjamin M; Kou, Yan; Liu, Li; Ma'ayan, Avi; Samocha, Kaitlin E; Sabo, Aniko; Lin, Chiao-Feng; Stevens, Christine; Wang, Li-San; Makarov, Vladimir; Polak, Paz; Yoon, Seungtai; et al. (Nature, 2012)
Autism spectrum disorders (ASD) are believed to have genetic and environmental origins, yet in only a modest fraction of individuals can specific causes be identified. To identify further genetic risk factors, here we assess the role of de novo mutations in ASD by sequencing the exomes of ASD cases and their parents (n = 175 trios). Fewer than half of the cases (46.3%) carry a missense or nonsense de novo variant, and the overall rate of mutation is only modestly higher than the expected rate. In contrast, the proteins encoded by genes that harboured de novo missense or nonsense mutations showed a higher degree of connectivity among themselves and to previous ASD genes as indexed by protein-protein interaction screens. The small increase in the rate of de novo events, when taken together with the protein interaction results, are consistent with an important but limited role for de novo point mutations in ASD, similar to that documented for de novo copy number variants. Genetic models incorporating these data indicate that most of the observed de novo events are unconnected to ASD; those that do confer risk are distributed across many genes and are incompletely penetrant (that is, not necessarily sufficient for disease). Our results support polygenic models in which spontaneous coding mutations in any of a large number of genes increases risk by 5- to 20-fold. Despite the challenge posed by such models, results from de novo events and a large parallel case-control study provide strong evidence in favour of CHD8 and KATNAL2 as genuine autism risk factors.
Keywords: Autistic Disorder; Case-Control Studies; DNA-Binding Proteins; Exome; Exons; Family Health; Genetic Predisposition to Disease; Humans; Models, Genetic; Multifactorial Inheritance; Mutation; Phenotype; Poisson Distribution; Protein Interaction Maps; Transcription Factors

PDX-1 is a therapeutic target for pancreatic cancer, insulinoma and islet neoplasia using a novel RNA interference platform. - Liu, Shi-He; Rao, Donald D; Nemunaitis, John; Senzer, Neil; Zhou, Guisheng; Dawson, David; Gingras, Marie-Claude; Wang, Zhaohui; Gibbs, Richard; Norman, Michael; Templeton, Nancy S; DeMayo, Francesco J; et al. (PLoS One, 2012)
Pancreatic and duodenal homeobox-1 (PDX-1) is a transcription factor that regulates insulin expression and islet maintenance in the adult pancreas. Our recent studies demonstrate that PDX-1 is an oncogene for pancreatic cancer and is overexpressed in pancreatic cancer. The purpose of this study was to demonstrate that PDX-1 is a therapeutic target for both hormonal symptoms and tumor volume in mouse models of pancreatic cancer, insulinoma and islet neoplasia. Immunohistochemistry of human pancreatic and islet neoplasia specimens revealed marked PDX-1 overexpression, suggesting PDX-1 as a "drugable" target within these diseases. To do so, a novel RNA interference effector platform, bifunctional shRNA(PDX-1), was developed and studied in mouse and human cell lines as well as in mouse models of pancreatic cancer, insulinoma and islet neoplasia. Systemic delivery of bi-shRNA(humanPDX-1) lipoplexes resulted in marked reduction of tumor volume and improved survival in a human pancreatic cancer xenograft mouse model. bi-shRNA(mousePDX-1) lipoplexes prevented death from hyperinsulinemia and hypoglycemia in an insulinoma mouse model. shRNA(mousePDX-1) lipoplexes reversed hyperinsulinemia and hypoglycemia in an immune-competent mouse model of islet neoplasia. PDX-1 was overexpressed in pancreatic neuroendocrine tumors and nesidioblastosis. These data demonstrate that PDX-1 RNAi therapy controls hormonal symptoms and tumor volume in mouse models of pancreatic cancer, insulinoma and islet neoplasia, therefore, PDX-1 is a potential therapeutic target for these pancreatic diseases.
Keywords: Animals; Cell Line, Tumor; Cell Proliferation; Disease Models, Animal; Glucose Tolerance Test; Homeodomain Proteins; Humans; Immunohistochemistry; In Situ Nick-End Labeling; Insulin; Insulinoma; Islets of Langerhans; Male; Mice; Mice, SCID; Neoplasm Transplantation; Pancreas; Pancreatic Neoplasms; RNA Interference; Trans-Activators

Phosphorylated and sumoylation-deficient progesterone receptors drive proliferative gene signatures during breast cancer progression. - Knutson, Todd P; Daniel, Andrea R; Fan, Danhua; Silverstein, Kevin At; Covington, Kyle R; Fuqua, Suzanne Aw; Lange, Carol A (Breast Cancer Res, 2012)
INTRODUCTION: Progesterone receptors (PR) are emerging as important breast cancer drivers. Phosphorylation events common to breast cancer cells impact PR transcriptional activity, in part by direct phosphorylation. PR-B but not PR-A isoforms are phosphorylated on Ser294 by mitogen activated protein kinase (MAPK) and cyclin dependent kinase 2 (CDK2). Phospho-Ser294 PRs are resistant to ligand-dependent Lys388 SUMOylation (that is, a repressive modification). Antagonism of PR small ubiquitin-like modifier (SUMO)ylation by mitogenic protein kinases suggests a mechanism for derepression (that is, transcriptional activation) of target genes. As a broad range of PR protein expression is observed clinically, a PR gene signature would provide a valuable marker of PR contribution to early breast cancer progression. METHODS: Global gene expression patterns were measured in T47D and MCF-7 breast cancer cells expressing either wild-type (SUMOylation-capable) or K388R (SUMOylation-deficient) PRs and subjected to pathway analysis. Gene sets were validated by RT-qPCR. Recruitment of coregulators and histone methylation levels were determined by chromatin immunoprecipitation. Changes in cell proliferation and survival were determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays and western blotting. Finally, human breast tumor cohort datasets were probed to identify PR-associated gene signatures; metagene analysis was employed to define survival rates in patients whose tumors express a PR gene signature. RESULTS: 'SUMO-sensitive' PR target genes primarily include genes required for proliferative and pro-survival signaling. DeSUMOylated K388R receptors are preferentially recruited to enhancer regions of derepressed genes (that is, MSX2, RGS2, MAP1A, and PDK4) with the steroid receptor coactivator, CREB-(cAMP-response element-binding protein)-binding protein (CBP), and mixed lineage leukemia 2 (MLL2), a histone methyltransferase mediator of nucleosome remodeling. PR SUMOylation blocks these events, suggesting that SUMO modification of PR prevents interactions with mediators of early chromatin remodeling at 'closed' enhancer regions. SUMO-deficient (phospho-Ser294) PR gene signatures are significantly associated with human epidermal growth factor 2 (ERBB2)-positive luminal breast tumors and predictive of early metastasis and shortened survival. Treatment with antiprogestin or MEK inhibitor abrogated expression of SUMO-sensitive PR target-genes and inhibited proliferation in BT-474 (estrogen receptor (ER)+/PR+/ERBB2+) breast cancer cells. CONCLUSIONS: We conclude that reversible PR SUMOylation/deSUMOylation profoundly alters target gene selection in breast cancer cells. Phosphorylation-induced PR deSUMOylation favors a permissive chromatin environment via recruitment of CBP and MLL2. Patients whose ER+/PR+ tumors are driven by hyperactive (that is, derepressed) phospho-PRs may benefit from endocrine (antiestrogen) therapies that contain an antiprogestin.
Keywords: Apoptosis; Breast Neoplasms; Cell Line, Tumor; Cell Proliferation; Cell Survival; Cyclic AMP Response Element-Binding Protein; Cyclin-Dependent Kinase 2; Disease Progression; DNA-Binding Proteins; Female; Gene Expression Profiling; Humans; MCF-7 Cells; Mitogen-Activated Protein Kinases; Neoplasm Proteins; Phosphorylation; Promoter Regions, Genetic; Receptor, ErbB-2; Receptors, Progesterone; Signal Transduction; Small Ubiquitin-Related Modifier Proteins; Sumoylation; Transcriptional Activation; Transcriptome

Quantitative trait loci affecting liver fat content in mice. - Minkina, Olga; Cheverud, James M; Fawcett, Gloria; Semenkovich, Clay F; Kenney-Hunt, Jane P (G3 (Bethesda), 2012)
Nonalcoholic fatty liver disease, a condition in which excess fat accumulates in the liver, is strongly associated with the metabolic syndrome, including obesity and other related conditions. This disease has the potential to progress from steatosis to steatohepatitis, fibrosis, and cirrhosis. The recent increase in the prevalence of the metabolic syndrome is largely driven by changes in diet and activity levels. Individual variation in the response to this obesogenic environment, however, is attributable in part to genetic variation between individuals, but very few mammalian genetic loci have been identified with effects on fat accumulation in the liver. To study the genetic basis for variation in liver fat content in response to dietary fat, liver fat proportion was determined using quantitative magnetic resonance imaging in 478 mice from 16 LG/J X SM/J recombinant inbred strains fed either a high-fat (42% kcal from fat) or low-fat (15% kcal from fat) diet. An analysis of variance confirmed that there is a genetic basis for variation in liver fat content within the population with significant effects of sex and diet. Three quantitative trail loci that contribute to liver fat content also were mapped.
Keywords: Animals; Diabetes Mellitus; Diet, Fat-Restricted; Diet, High-Fat; Fats; Fatty Liver; Female; Liver; Male; Mice; Non-alcoholic Fatty Liver Disease; Obesity; Quantitative Trait Loci

REGγ is associated with multiple oncogenic pathways in human cancers. - He, Jing; Cui, Long; Zeng, Yu; Wang, Guangqiang; Zhou, Ping; Yang, Yuanyuan; Ji, Lei; Zhao, Yanyan; Chen, Jiwu; Wang, Zhuo; Shi, Tieliu; Zhang, Pei; et al. (BMC Cancer, 2012)
BACKGROUND: Recent studies suggest a role of the proteasome activator, REGγ, in cancer progression. Since there are limited numbers of known REGγ targets, it is not known which cancers and pathways are associated with REGγ. METHODS: REGγ protein expressions in four different cancers were investigated by immunohistochemistry (IHC) analysis. Following NCBI Gene Expression Omnibus (GEO) database search, microarray platform validation, differential expressions of REGγ in corresponding cancers were statistically analyzed. Genes highly correlated with REGγ were defined based on Pearson's correlation coefficient. Functional links were estimated by Ingenuity Core analysis. Finally, validation was performed by RT-PCR analysis in established cancer cell lines and IHC in human colon cancer tissues RESULTS: Here, we demonstrate overexpression of REGγ in four different cancer types by micro-tissue array analysis. Using meta-analysis of publicly available microarray databases and biological studies, we verified elevated REGγ gene expression in the four types of cancers and identified genes significantly correlated with REGγ expression, including genes in p53, Myc pathways, and multiple other cancer-related pathways. The predicted correlations were largely consistent with quantitative RT-PCR analysis. CONCLUSIONS: This study provides us novel insights in REGγ gene expression profiles and its link to multiple cancer-related pathways in cancers. Our results indicate potentially important pathogenic roles of REGγ in multiple cancer types and implicate REGγ as a putative cancer marker.
Keywords: Antigens, Neoplasm; Autoantigens; Colonic Neoplasms; Disease Progression; Gene Expression Profiling; Humans; Immunohistochemistry; Liver Neoplasms; Lung Neoplasms; Microarray Analysis; Neoplasms; Proteasome Endopeptidase Complex; Thyroid Neoplasms; Tumor Cells, Cultured

Residual plasmatic activity of ADAMTS13 is correlated with phenotype severity in congenital thrombotic thrombocytopenic purpura. - Lotta, Luca A; Wu, Haifeng M; Mackie, Ian J; Noris, Marina; Veyradier, Agnes; Scully, Marie A; Remuzzi, Giuseppe; Coppo, Paul; Liesner, Ri; Donadelli, Roberta; Loirat, Chantal; Gibbs, Richard A; et al. (Blood, 2012)
The quantification of residual plasmatic ADAMTS13 activity in congenital thrombotic thrombocytopenic purpura (TTP) patients is constrained by limitations in sensitivity and reproducibility of commonly used assays at low levels of ADAMTS13 activity, blunting efforts to establish genotype-phenotype correlations. In the present study, the residual plasmatic activity of ADAMTS13 was measured centrally by surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (limit of detection = 0.5%) in 29 congenital TTP patients. The results were used to study correlations among ADAMTS13 genotype, residual plasmatic activity, and clinical phenotype severity. An ADAMTS13 activity above 0.5% was measured in 26 (90%) patients and lower levels of activity were associated with earlier age at first TTP episode requiring plasma infusion, more frequent recurrences, and prescription of fresh-frozen plasma prophylaxis. Receiver operating characteristic curve analysis showed that activity levels of less than 2.74% and 1.61% were discriminative of age at first TTP episode requiring plasma infusion < 18 years, annual rate of TTP episodes > 1, and use of prophylaxis. Mutations affecting the highly conserved N-terminal domains of the protein were associated with lower residual ADAMTS13 activity and a more severe phenotype in an allelic-dose dependent manner. The results of the present study show that residual ADAMTS13 activity is associated with the severity of clinical phenotype in congenital TTP and provide insights into genotype-phenotype correlations.
Keywords: ADAM Proteins; ADAMTS13 Protein; Adolescent; Adult; Age Factors; Aged; Blood Chemical Analysis; Blood Transfusion; Child; Child, Preschool; DNA Mutational Analysis; Female; Genetic Association Studies; Humans; Male; Middle Aged; Mutation; Plasma; Purpura, Thrombotic Thrombocytopenic; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Young Adult

The role of drinking water sources, consumption of vegetables and seafood in relation to blood arsenic concentrations of Jamaican children with and without Autism Spectrum Disorders. - Rahbar, Mohammad H; Samms-Vaughan, Maureen; Ardjomand-Hessabi, Manouchehr; Loveland, Katherine A; Dickerson, Aisha S; Chen, Zhongxue; Bressler, Jan; Shakespeare-Pellington, Sydonnie; Grove, Megan L; Bloom, Kari; Wirth, Julie; Pearson, Deborah A; et al. (Sci Total Environ, 2012)
Arsenic is a toxic metal with harmful effects on human health, particularly on cognitive function. Autism Spectrum Disorders (ASDs) are lifelong neurodevelopmental and behavioral disorders manifesting in infancy or early childhood. We used data from 130 children between 2 and 8 years (65 pairs of ASD cases with age- and sex-matched control), to compare the mean total blood arsenic concentrations in children with and without ASDs in Kingston, Jamaica. Based on univariable analysis, we observed a significant difference between ASD cases and controls (4.03 μg/L for cases vs. 4.48 μg/L for controls, P<0.01). In the final multivariable General Linear Model (GLM), after controlling for car ownership, maternal age, parental education levels, source of drinking water, consumption of "yam, sweet potato, or dasheen", "carrot or pumpkin", "callaloo, broccoli, or pak choi", cabbage, avocado, and the frequency of seafood consumption per week, we did not find a significant association between blood arsenic concentrations and ASD status (4.36 μg/L for cases vs. 4.65 μg/L for controls, P=0.23). Likewise, in a separate final multivariable GLM, we found that source of drinking water, eating avocado, and eating "callaloo, broccoli, or pak choi" was significantly associated with higher blood arsenic concentrations (all three P<0.05). Based on our findings, we recommend assessment of arsenic levels in water, fruits, and vegetables, as well as increased awareness among the Jamaican population regarding potential risks for various exposures to arsenic.
Keywords: Arsenic; Case-Control Studies; Child; Child Development Disorders, Pervasive; Drinking Water; Humans; Jamaica; Seafood; Vegetables

Serum prostate specific antigen changes in cynomolgus monkeys (Macaca fascicularis) on a high sugar high fat diet. - Mubiru, James N; Garcia-Forey, Magdalena; Cavazos, Nicole; Hemmat, Peggah; Dick, Edward J; Owston, Michael A; Bauer, Cassondra A; Shade, Robert E; Rogers, Jeffrey (Prostate, 2012)
BACKGROUND: An inverse relationship between serum prostate specific antigen (PSA) levels and body mass index (BMI) has been reported in men but not in any animal model. METHODS: Serum PSA in a colony of cynomolgus monkeys was assayed and correlated to body weight, prostate weight, and age. In addition, 15 animals were selected and fed a high sugar high fat (HSHF) diet for 49 weeks to increase their BMI and correlate it to PSA RESULTS: Serum PSA levels were positively correlated to prostate weight (r = 0.515, P = 0.025) and age (r = 0.548, P = 0.00072) but was not significantly correlated to body weight (r = -0.032, P = 0.419). For the animals on the HSHF diet, body weight, lean mass, fat mass, and BMI were significantly higher at 49 weeks than at baseline (P < 0.01). PSA was not significantly correlated to body weight and insulin at both baseline and 49 weeks. PSA was negatively correlated to BMI and insulin resistance (HOMA-IR) at 49 weeks but not at baseline. In addition, we observed hepatic steatosis and increases in serum liver enzymes. CONCLUSIONS: Increases in BMI in cynomolgus monkeys as a result of consuming a HSHF diet resulted in PSA changes similar to those in humans with increased BMI. Cynomolgus monkeys are a useful model for investigating the relationship between obesity, diabetes, and PSA changes resulting from prostate gland pathology.
Keywords: Absorptiometry, Photon; Animals; Blood Glucose; Body Mass Index; Body Weight; Dietary Carbohydrates; Dietary Fats; Disease Models, Animal; Insulin; Insulin Resistance; Macaca fascicularis; Male; Obesity; Organ Size; Prostate; Prostate-Specific Antigen

SINE retrotransposons cause epigenetic reprogramming of adjacent gene promoters. - Estécio, Marcos R H; Gallegos, Juan; Dekmezian, Mhair; Lu, Yue; Liang, Shoudan; Issa, Jean-Pierre J (Mol Cancer Res, 2012)
Almost half of the human genome and as much as 40% of the mouse genome is composed of repetitive DNA sequences. The majority of these repeats are retrotransposons of the SINE and LINE families, and such repeats are generally repressed by epigenetic mechanisms. It has been proposed that these elements can act as methylation centers from which DNA methylation spreads into gene promoters in cancer. Contradictory to a methylation center function, we have found that retrotransposons are enriched near promoter CpG islands that stay methylation-free in cancer. Clearly, it is important to determine which influence, if any, these repetitive elements have on nearby gene promoters. Using an in vitro system, we confirm here that SINE B1 elements can influence the activity of downstream gene promoters, with acquisition of DNA methylation and loss of activating histone marks, thus resulting in a repressed state. SINE sequences themselves did not immediately acquire DNA methylation but were marked by H3K9me2 and H3K27me3. Moreover, our bisulfite sequencing data did not support that gain of DNA methylation in gene promoters occurred by methylation spreading from SINE B1 repeats. Genome-wide analysis of SINE repeats distribution showed that their enrichment is directly correlated with the presence of USF1, USF2, and CTCF binding, proteins with insulator function. In summary, our work supports the concept that SINE repeats interfere negatively with gene expression and that their presence near gene promoters is counter-selected, except when the promoter is protected by an insulator element.
Keywords: Adaptor Proteins, Signal Transducing; Alu Elements; Animals; Antigens, CD; Cadherins; Cellular Reprogramming; Chromatin; Cyclin-Dependent Kinase Inhibitor p19; DNA Methylation; Epigenesis, Genetic; Gene Silencing; Genes; Humans; Insulator Elements; Long Interspersed Nucleotide Elements; Mice; MutL Protein Homolog 1; NIH 3T3 Cells; Nuclear Proteins; Promoter Regions, Genetic; Protein Binding; Short Interspersed Nucleotide Elements; Transcription Initiation Site; Transcription, Genetic; Tumor Suppressor Protein p14ARF

A systematic survey of loss-of-function variants in human protein-coding genes. - MacArthur, Daniel G; Balasubramanian, Suganthi; Frankish, Adam; Huang, Ni; Morris, James; Walter, Klaudia; Jostins, Luke; Habegger, Lukas; Pickrell, Joseph K; Montgomery, Stephen B; Albers, Cornelis A; Zhang, Zhengdong D; et al. (Science, 2012)
Genome-sequencing studies indicate that all humans carry many genetic variants predicted to cause loss of function (LoF) of protein-coding genes, suggesting unexpected redundancy in the human genome. Here we apply stringent filters to 2951 putative LoF variants obtained from 185 human genomes to determine their true prevalence and properties. We estimate that human genomes typically contain ~100 genuine LoF variants with ~20 genes completely inactivated. We identify rare and likely deleterious LoF alleles, including 26 known and 21 predicted severe disease-causing variants, as well as common LoF variants in nonessential genes. We describe functional and evolutionary differences between LoF-tolerant and recessive disease genes and a method for using these differences to prioritize candidate genes found in clinical sequencing studies.
Keywords: Disease; Gene Expression; Gene Frequency; Genetic Variation; Genome, Human; Humans; Phenotype; Polymorphism, Single Nucleotide; Proteins; Selection, Genetic

Treponema pallidum infection in the wild baboons of East Africa: distribution and genetic characterization of the strains responsible. - Harper, Kristin N; Fyumagwa, Robert D; Hoare, Richard; Wambura, Philemon N; Coppenhaver, Dorian H; Sapolsky, Robert M; Alberts, Susan C; Tung, Jenny; Rogers, Jeffrey; Kilewo, Morris; Batamuzi, Emmanuel K; Leendertz, Fabian H; et al. (PLoS One, 2012)
It has been known for decades that wild baboons are naturally infected with Treponema pallidum, the bacterium that causes the diseases syphilis (subsp. pallidum), yaws (subsp. pertenue), and bejel (subsp. endemicum) in humans. Recently, a form of T. pallidum infection associated with severe genital lesions has been described in wild baboons at Lake Manyara National Park in Tanzania. In this study, we investigated ten additional sites in Tanzania and Kenya using a combination of macroscopic observation and serology, in order to determine whether the infection was present in each area. In addition, we obtained genetic sequence data from six polymorphic regions using T. pallidum strains collected from baboons at two different Tanzanian sites. We report that lesions consistent with T. pallidum infection were present at four of the five Tanzanian sites examined, and serology was used to confirm treponemal infection at three of these. By contrast, no signs of treponemal infection were observed at the six Kenyan sites, and serology indicated T. pallidum was present at only one of them. A survey of sexually mature baboons at Lake Manyara National Park in 2006 carried out as part of this study indicated that roughly ten percent displayed T. pallidum-associated lesions severe enough to cause major structural damage to the genitalia. Finally, we found that T. pallidum strains from Lake Manyara National Park and Serengeti National Park were genetically distinct, and a phylogeny suggested that baboon strains may have diverged prior to the clade containing human strains. We conclude that T. pallidum infection associated with genital lesions appears to be common in the wild baboons of the regions studied in Tanzania. Further study is needed to elucidate the infection's transmission mode, its associated morbidity and mortality, and the relationship between baboon and human strains.
Keywords: Africa, Eastern; Animals; Antibodies, Bacterial; DNA, Bacterial; Evolution, Molecular; Female; Humans; Male; Monkey Diseases; Papio; Phylogeny; Sequence Analysis, DNA; Species Specificity; Syphilis; Treponema pallidum

Using whole-genome sequence data to predict quantitative trait phenotypes in Drosophila melanogaster. - Ober, Ulrike; Ayroles, Julien F; Stone, Eric A; Richards, Stephen; Zhu, Dianhui; Gibbs, Richard A; Stricker, Christian; Gianola, Daniel; Schlather, Martin; Mackay, Trudy F C; Simianer, Henner (PLoS Genet, 2012)
Predicting organismal phenotypes from genotype data is important for plant and animal breeding, medicine, and evolutionary biology. Genomic-based phenotype prediction has been applied for single-nucleotide polymorphism (SNP) genotyping platforms, but not using complete genome sequences. Here, we report genomic prediction for starvation stress resistance and startle response in Drosophila melanogaster, using ∼2.5 million SNPs determined by sequencing the Drosophila Genetic Reference Panel population of inbred lines. We constructed a genomic relationship matrix from the SNP data and used it in a genomic best linear unbiased prediction (GBLUP) model. We assessed predictive ability as the correlation between predicted genetic values and observed phenotypes by cross-validation, and found a predictive ability of 0.239±0.008 (0.230±0.012) for starvation resistance (startle response). The predictive ability of BayesB, a Bayesian method with internal SNP selection, was not greater than GBLUP. Selection of the 5% SNPs with either the highest absolute effect or variance explained did not improve predictive ability. Predictive ability decreased only when fewer than 150,000 SNPs were used to construct the genomic relationship matrix. We hypothesize that predictive power in this population stems from the SNP-based modeling of the subtle relationship structure caused by long-range linkage disequilibrium and not from population structure or SNPs in linkage disequilibrium with causal variants. We discuss the implications of these results for genomic prediction in other organisms.
Keywords: Animals; Bayes Theorem; Chromosome Mapping; Drosophila melanogaster; Genetics, Population; Genome, Insect; Genotype; Linkage Disequilibrium; Models, Genetic; Models, Theoretical; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Selection, Genetic; Sequence Analysis, DNA

Whole genome sequence of Treponema pallidum ssp. pallidum, strain Mexico A, suggests recombination between yaws and syphilis strains. - Pětrošová, Helena; Zobaníková, Marie; Čejková, Darina; Mikalová, Lenka; Pospíšilová, Petra; Strouhal, Michal; Chen, Lei; Qin, Xiang; Muzny, Donna M; Weinstock, George M; Smajs, David (PLoS Negl Trop Dis, 2012)
BACKGROUND: Treponema pallidum ssp. pallidum (TPA), the causative agent of syphilis, and Treponema pallidum ssp. pertenue (TPE), the causative agent of yaws, are closely related spirochetes causing diseases with distinct clinical manifestations. The TPA Mexico A strain was isolated in 1953 from male, with primary syphilis, living in Mexico. Attempts to cultivate TPA Mexico A strain under in vitro conditions have revealed lower growth potential compared to other tested TPA strains. METHODOLOGY/PRINCIPAL FINDINGS: The complete genome sequence of the TPA Mexico A strain was determined using the Illumina sequencing technique. The genome sequence assembly was verified using the whole genome fingerprinting technique and the final sequence was annotated. The genome size of the Mexico A strain was determined to be 1,140,038 bp with 1,035 predicted ORFs. The Mexico A genome sequence was compared to the whole genome sequences of three TPA (Nichols, SS14 and Chicago) and three TPE (CDC-2, Samoa D and Gauthier) strains. No large rearrangements in the Mexico A genome were found and the identified nucleotide changes occurred most frequently in genes encoding putative virulence factors. Nevertheless, the genome of the Mexico A strain, revealed two genes (TPAMA_0326 (tp92) and TPAMA_0488 (mcp2-1)) which combine TPA- and TPE- specific nucleotide sequences. Both genes were found to be under positive selection within TPA strains and also between TPA and TPE strains. CONCLUSIONS/SIGNIFICANCE: The observed mosaic character of the TPAMA_0326 and TPAMA_0488 loci is likely a result of inter-strain recombination between TPA and TPE strains during simultaneous infection of a single host suggesting horizontal gene transfer between treponemal subspecies.
Keywords: DNA, Bacterial; Genome, Bacterial; Humans; Male; Mexico; Molecular Sequence Data; Open Reading Frames; Recombination, Genetic; Sequence Analysis, DNA; Synteny; Syphilis; Treponema pallidum; Yaws

Whole genome sequences of three Treponema pallidum ssp. pertenue strains: yaws and syphilis treponemes differ in less than 0.2% of the genome sequence. - Čejková, Darina; Zobaníková, Marie; Chen, Lei; Pospíšilová, Petra; Strouhal, Michal; Qin, Xiang; Mikalová, Lenka; Norris, Steven J; Muzny, Donna M; Gibbs, Richard A; Fulton, Lucinda L; Sodergren, Erica; et al. (PLoS Negl Trop Dis, 2012)
BACKGROUND: The yaws treponemes, Treponema pallidum ssp. pertenue (TPE) strains, are closely related to syphilis causing strains of Treponema pallidum ssp. pallidum (TPA). Both yaws and syphilis are distinguished on the basis of epidemiological characteristics, clinical symptoms, and several genetic signatures of the corresponding causative agents. METHODOLOGY/PRINCIPAL FINDINGS: To precisely define genetic differences between TPA and TPE, high-quality whole genome sequences of three TPE strains (Samoa D, CDC-2, Gauthier) were determined using next-generation sequencing techniques. TPE genome sequences were compared to four genomes of TPA strains (Nichols, DAL-1, SS14, Chicago). The genome structure was identical in all three TPE strains with similar length ranging between 1,139,330 bp and 1,139,744 bp. No major genome rearrangements were found when compared to the four TPA genomes. The whole genome nucleotide divergence (d(A)) between TPA and TPE subspecies was 4.7 and 4.8 times higher than the observed nucleotide diversity (π) among TPA and TPE strains, respectively, corresponding to 99.8% identity between TPA and TPE genomes. A set of 97 (9.9%) TPE genes encoded proteins containing two or more amino acid replacements or other major sequence changes. The TPE divergent genes were mostly from the group encoding potential virulence factors and genes encoding proteins with unknown function. CONCLUSIONS/SIGNIFICANCE: Hypothetical genes, with genetic differences, consistently found between TPE and TPA strains are candidates for syphilitic treponemes virulence factors. Seventeen TPE genes were predicted under positive selection, and eleven of them coded either for predicted exported proteins or membrane proteins suggesting their possible association with the cell surface. Sequence changes between TPE and TPA strains and changes specific to individual strains represent suitable targets for subspecies- and strain-specific molecular diagnostics.
Keywords: DNA, Bacterial; Gene Order; Genetic Variation; Genome, Bacterial; Humans; Molecular Sequence Data; Sequence Analysis, DNA; Synteny; Syphilis; Treponema pallidum; Yaws

Association studies for next-generation sequencing. - Luo, Li; Boerwinkle, Eric; Xiong, Momiao (Genome Res, 2011)
Genome-wide association studies (GWAS) have become the primary approach for identifying genes with common variants influencing complex diseases. Despite considerable progress, the common variations identified by GWAS account for only a small fraction of disease heritability and are unlikely to explain the majority of phenotypic variations of common diseases. A potential source of the missing heritability is the contribution of rare variants. Next-generation sequencing technologies will detect millions of novel rare variants, but these technologies have three defining features: identification of a large number of rare variants, a high proportion of sequence errors, and a large proportion of missing data. These features raise challenges for testing the association of rare variants with phenotypes of interest. In this study, we use a genome continuum model and functional principal components as a general principle for developing novel and powerful association analysis methods designed for resequencing data. We use simulations to calculate the type I error rates and the power of nine alternative statistics: two functional principal component analysis (FPCA)-based statistics, the multivariate principal component analysis (MPCA)-based statistic, the weighted sum (WSS), the variable-threshold (VT) method, the generalized T(2), the collapsing method, the CMC method, and individual tests. We also examined the impact of sequence errors on their type I error rates. Finally, we apply the nine statistics to the published resequencing data set from ANGPTL4 in the Dallas Heart Study. We report that FPCA-based statistics have a higher power to detect association of rare variants and a stronger ability to filter sequence errors than the other seven methods.
Keywords: Angiopoietin-Like Protein 4; Angiopoietins; Computational Biology; Computer Simulation; Databases, Genetic; Genetic Variation; Genetics, Population; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Models, Biological; Models, Statistical; Multivariate Analysis; Phenotype; Sequence Analysis, DNA

Building a comprehensive genomic program for hepatocellular carcinoma. - Harring, Theresa R; Guiteau, Jacfranz J; Nguyen, N Thao T; Cotton, Ron T; Gingras, Marie-Claude; Wheeler, David A; O'Mahony, Christine A; Gibbs, Richard A; Brunicardi, F Charles; Goss, John A (World J Surg, 2011)
BACKGROUND: Hepatocellular carcinoma (HCC) is the most common primary liver cancer, causing approximately 660,000 deaths worldwide annually. The preferred treatment of HCC is surgical resection or orthotopic liver transplantation (OLT) for patients meeting specific criteria. For patients outside these criteria, options are limited and include medical therapy, radiofrequency ablation, chemoembolization, or palliative measures, and these result in poor outcomes. Various centers at Baylor are elucidating the genomics of HCC to improve treatment options, with a focus on three etiologies: hepatitis C virus, hepatitis B virus, and non-viral. METHODS: Through collaborative efforts, we have established an effective specimen biobanking protocol, and we are using several techniques to analyze HCC, including whole genome sequencing, whole exome sequencing, gene-specific analysis, gene expression, and epigenetic analysis. RESULTS: We have completed whole genome sequencing on two patient samples, whole exome sequencing on 47 patient samples, gene-specific analysis on 94 patient samples, gene expression on 4 patient samples, and epigenetic analysis on 1 patient sample. CONCLUSIONS: We hope to use these results to define novel genetic therapeutic strategies that may work in conjunction with surgical approaches to improve long-term patient and graft survival rates in patients with HCC. We also aim to provide a functional framework of a comprehensive program for genomic analysis that may be imitated by other institutions and for other tumors in the global quest toward personalized genomic medicine.
Keywords: Carcinoma, Hepatocellular; Cell Transformation, Neoplastic; Databases, Nucleic Acid; Disease Progression; Epigenomics; Exome; Forecasting; Gene Expression Regulation, Neoplastic; Genome, Human; Genome-Wide Association Study; Humans; Liver Neoplasms; Precision Medicine; Tissue Banks

The complete genome sequence of 'Candidatus Liberibacter solanacearum', the bacterium associated with potato zebra chip disease. - Lin, Hong; Lou, Binghai; Glynn, Jonathan M; Doddapaneni, Harshavardhan; Civerolo, Edwin L; Chen, Chuanwu; Duan, Yongping; Zhou, Lijuan; Vahling, Cheryl M (PLoS One, 2011)
Zebra Chip (ZC) is an emerging plant disease that causes aboveground decline of potato shoots and generally results in unusable tubers. This disease has led to multi-million dollar losses for growers in the central and western United States over the past decade and impacts the livelihood of potato farmers in Mexico and New Zealand. ZC is associated with 'Candidatus Liberibacter solanacearum', a fastidious alpha-proteobacterium that is transmitted by a phloem-feeding psyllid vector, Bactericera cockerelli Sulc. Research on this disease has been hampered by a lack of robust culture methods and paucity of genome sequence information for 'Ca. L. solanacearum'. Here we present the sequence of the 1.26 Mbp metagenome of 'Ca. L. solanacearum', based on DNA isolated from potato psyllids. The coding inventory of the 'Ca. L. solanacearum' genome was analyzed and compared to related Rhizobiaceae to better understand 'Ca. L. solanacearum' physiology and identify potential targets to develop improved treatment strategies. This analysis revealed a number of unique transporters and pathways, all potentially contributing to ZC pathogenesis. Some of these factors may have been acquired through horizontal gene transfer. Taxonomically, 'Ca. L. solanacearum' is related to 'Ca. L. asiaticus', a suspected causative agent of citrus huanglongbing, yet many genome rearrangements and several gene gains/losses are evident when comparing these two Liberibacter. species. Relative to 'Ca. L. asiaticus', 'Ca. L. solanacearum' probably has reduced capacity for nucleic acid modification, increased amino acid and vitamin biosynthesis functionalities, and gained a high-affinity iron transport system characteristic of several pathogenic microbes.
Keywords: Amino Acids; Biological Transport; Carbohydrate Metabolism; Cell Division; Cell Proliferation; Citrus; DNA Replication; DNA, Bacterial; Energy Metabolism; Genome, Bacterial; Genomics; Nitrogen; Nucleotides; Plant Diseases; Prophages; Proteobacteria; Solanum tuberosum; Sulfur; Vitamins

Copy number variation detection in whole-genome sequencing data using the Bayesian information criterion. - Xi, Ruibin; Hadjipanayis, Angela G; Luquette, Lovelace J; Kim, Tae-Min; Lee, Eunjung; Zhang, Jianhua; Johnson, Mark D; Muzny, Donna M; Wheeler, David A; Gibbs, Richard A; Kucherlapati, Raju; Park, Peter J (Proc Natl Acad Sci U S A, 2011)
DNA copy number variations (CNVs) play an important role in the pathogenesis and progression of cancer and confer susceptibility to a variety of human disorders. Array comparative genomic hybridization has been used widely to identify CNVs genome wide, but the next-generation sequencing technology provides an opportunity to characterize CNVs genome wide with unprecedented resolution. In this study, we developed an algorithm to detect CNVs from whole-genome sequencing data and applied it to a newly sequenced glioblastoma genome with a matched control. This read-depth algorithm, called BIC-seq, can accurately and efficiently identify CNVs via minimizing the Bayesian information criterion. Using BIC-seq, we identified hundreds of CNVs as small as 40 bp in the cancer genome sequenced at 10× coverage, whereas we could only detect large CNVs (> 15 kb) in the array comparative genomic hybridization profiles for the same genome. Eighty percent (14/16) of the small variants tested (110 bp to 14 kb) were experimentally validated by quantitative PCR, demonstrating high sensitivity and true positive rate of the algorithm. We also extended the algorithm to detect recurrent CNVs in multiple samples as well as deriving error bars for breakpoints using a Gibbs sampling approach. We propose this statistical approach as a principled yet practical and efficient method to estimate CNVs in whole-genome sequencing data.
Keywords: Algorithms; Bayes Theorem; Brain Neoplasms; Comparative Genomic Hybridization; Computer Simulation; DNA Copy Number Variations; Female; Gene Dosage; Genome; Genome, Human; Glioblastoma; Humans; Models, Genetic; Models, Statistical; Sequence Analysis, DNA

Cortical sulcal areas in baboons (Papio hamadryas spp.) with generalized interictal epileptic discharges on scalp EEG. - Szabó, C A; Kochunov, P; Knape, K D; McCoy, K J M; Leland, M M; Lancaster, J L; Fox, P T; Williams, J T; Rogers, J (Epilepsy Res, 2011)
Brain MRI studies in people with idiopathic generalized epilepsies demonstrate regional morphometric differences, though variable in magnitude and location. As the baboon provides an excellent electroclinical and neuroimaging model for photosensitive generalized epilepsy in humans, this study evaluated MRI volumetric and morphometric differences between baboons with interictal epileptic discharges (IEDs) on scalp EEG and baboons with normal EEG studies. Seventy-seven baboons underwent high-resolution brain MRI and scalp EEG studies. The scans were acquired using an 8-channel primate head coil (Siemens TRIO 3T scanner, Erlangen, Germany). After spatial normalization, sulcal measurements were obtained by object-based-morphology methods. One-hour scalp EEG studies were performed in animals sedated with ketamine. Thirty-eight (22F/16M) baboons had normal EEGs (IED-), while 39 (22F/17M) had generalized IEDs (IED+). The two groups were compared for age, total brain volume, and sulcal areas (Hotelling's Trace) as well as between-subjects comparison of 11 individual sulcal areas (averaged between left and right hemispheres). There were no differences between IED- and IED+ groups with respect to age or total brain (gray or white matter) volume, and multivariate tests demonstrated a marginally significant decrease of sulcal areas in IED+ baboons (p=0.075). Tests of between-subjects effects showed statistically significant decreases in the intraparietal (p=0.002), central (p=0.03) and cingulate sulci (p=0.02), and marginal decreases involving the lunate (p=0.07) and superior temporal sulci (p=0.08). Differences in sulcal areas in IED+ baboons may reflect global developmental abnormalities, while decreases of areas of specific sulci reflect anatomical markers for potential generators or cortical nodes of the networks underlying spontaneous seizures and photosensitivity in the baboon.
Keywords: Animals; Brain; Cerebral Cortex; Data Interpretation, Statistical; Electroencephalography; Epilepsy; Female; Functional Laterality; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Papio; Parietal Lobe; Seizures

dbNSFP: a lightweight database of human nonsynonymous SNPs and their functional predictions. - Liu, Xiaoming; Jian, Xueqiu; Eric Boerwinkle (Hum Mutat, 2011)
With the advance of sequencing technologies, whole exome sequencing has increasingly been used to identify mutations that cause human diseases, especially rare Mendelian diseases. Among the analysis steps, functional prediction (of being deleterious) plays an important role in filtering or prioritizing nonsynonymous SNP (NS) for further analysis. Unfortunately, different prediction algorithms use different information and each has its own strength and weakness. It has been suggested that investigators should use predictions from multiple algorithms instead of relying on a single one. However, querying predictions from different databases/Web-servers for different algorithms is both tedious and time consuming, especially when dealing with a huge number of NSs identified by exome sequencing. To facilitate the process, we developed dbNSFP (database for nonsynonymous SNPs' functional predictions). It compiles prediction scores from four new and popular algorithms (SIFT, Polyphen2, LRT, and MutationTaster), along with a conservation score (PhyloP) and other related information, for every potential NS in the human genome (a total of 75,931,005). It is the first integrated database of functional predictions from multiple algorithms for the comprehensive collection of human NSs. dbNSFP is freely available for download at http://sites.google.com/site/jpopgen/dbNSFP.
Keywords: Algorithms; Computational Biology; Databases, Nucleic Acid; Genetic Association Studies; Humans; Internet; Polymorphism, Single Nucleotide; Software

Demographic history and rare allele sharing among human populations. - Gravel, Simon; Henn, Brenna M; Gutenkunst, Ryan N; Indap, Amit R; Marth, Gabor T; Clark, Andrew G; Yu, Fuli; Gibbs, Richard A; Bustamante, Carlos D (Proc Natl Acad Sci U S A, 2011)
High-throughput sequencing technology enables population-level surveys of human genomic variation. Here, we examine the joint allele frequency distributions across continental human populations and present an approach for combining complementary aspects of whole-genome, low-coverage data and targeted high-coverage data. We apply this approach to data generated by the pilot phase of the Thousand Genomes Project, including whole-genome 2-4× coverage data for 179 samples from HapMap European, Asian, and African panels as well as high-coverage target sequencing of the exons of 800 genes from 697 individuals in seven populations. We use the site frequency spectra obtained from these data to infer demographic parameters for an Out-of-Africa model for populations of African, European, and Asian descent and to predict, by a jackknife-based approach, the amount of genetic diversity that will be discovered as sample sizes are increased. We predict that the number of discovered nonsynonymous coding variants will reach 100,000 in each population after ∼1,000 sequenced chromosomes per population, whereas ∼2,500 chromosomes will be needed for the same number of synonymous variants. Beyond this point, the number of segregating sites in the European and Asian panel populations is expected to overcome that of the African panel because of faster recent population growth. Overall, we find that the majority of human genomic variable sites are rare and exhibit little sharing among diverged populations. Our results emphasize that replication of disease association for specific rare genetic variants across diverged populations must overcome both reduced statistical power because of rarity and higher population divergence.
Keywords: Demography; Evolution, Molecular; Gene Frequency; Genes; Genetic Drift; Genetic Variation; Genetics, Population; Genomics; Humans; Models, Genetic; Racial Groups; Sequence Analysis, DNA

Dicer-mediated upregulation of BCRP confers tamoxifen resistance in human breast cancer cells. - Selever, Jennifer; Gu, Guowei; Lewis, Michael T; Beyer, Amanda; Herynk, Matthew H; Covington, Kyle R; Tsimelzon, Anna; Dontu, Gabriela; Provost, Patrick; Di Pietro, Attilio; Boumendjel, Ahcène; Albain, Kathy; et al. (Clin Cancer Res, 2011)
PURPOSE: Tamoxifen (Tam) is the most prescribed hormonal agent for treatment of estrogen receptor α (ERα)-positive breast cancer patients. Using microarray analysis, we observed that metastatic breast tumors resistant to Tam therapy had elevated levels of Dicer. EXPERIMENTAL DESIGN: We overexpressed Dicer in ERα-positive MCF-7 human breast cancer cells and observed a concomitant increase in expression of the breast cancer resistance protein (BCRP). We thus hypothesized that Tam resistance associated with Dicer overexpression in ERα-positive breast cancer cells may involve BCRP. We analyzed BCRP function in Dicer-overexpressing cells using growth in soft agar and mammosphere formation and evaluated intracellular Tam efflux. RESULTS: In the presence of Tam, Dicer-overexpressing cells formed resistant colonies in soft agar, and treatment with BCRP inhibitors restored Tam sensitivity. Tumor xenograft studies confirmed that Dicer-overexpressing cells were resistant to Tam in vivo. Tumors and distant metastases could be initiated with as few as five mammosphere cells from both vector and Dicer-overexpressing cells, indicating that the mammosphere assay selected for cells with enhanced tumor-initiating and metastatic capacity. Dicer-overexpressing cells with elevated levels of BCRP effluxed Tam more efficiently than control cells, and BCRP inhibitors were able to inhibit efflux. CONCLUSION: Dicer-overexpressing breast cancer cells enriched for cells with enhanced BCRP function. We hypothesize that it is this population which may be involved in the emergence of Tam-resistant growth. BCRP may be a novel clinical target to restore Tam sensitivity.
Keywords: Animals; Antineoplastic Agents, Hormonal; ATP Binding Cassette Transporter, Subfamily G, Member 2; ATP-Binding Cassette Transporters; Breast Neoplasms; Cell Line, Tumor; DEAD-box RNA Helicases; Disease Models, Animal; Drug Resistance, Neoplasm; Estrogen Antagonists; Estrogen Receptor alpha; Female; Humans; Mice; Mice, Nude; Neoplasm Proteins; Neoplasms, Hormone-Dependent; Ribonuclease III; Tamoxifen; Up-Regulation

Diet-dependent genetic and genomic imprinting effects on obesity in mice. - Cheverud, James M; Lawson, Heather A; Fawcett, Gloria L; Wang, Bing; Pletscher, L Susan; R Fox, Ashley; Maxwell, Taylor J; Ehrich, Thomas H; Kenney-Hunt, Jane P; Wolf, Jason B; Semenkovich, Clay F (Obesity (Silver Spring), 2011)
Although the current obesity epidemic is of environmental origin, there is substantial genetic variation in individual response to an obesogenic environment. In this study, we perform a genome-wide scan for quantitative trait loci (QTLs) affecting obesity per se, or an obese response to a high-fat diet in mice from the LG/J by SM/J Advanced Intercross (AI) Line (Wustl:LG,SM-G16). A total of 1,002 animals from 78 F₁₆ full sibships were weaned at 3 weeks of age and half of each litter placed on high- and low-fat diets. Animals remained on the diet until 20 weeks of age when they were necropsied and the weights of the reproductive, kidney, mesenteric, and inguinal fat depots were recorded. Effects on these phenotypes, along with total fat depot weight and carcass weight at necropsy, were mapped across the genome using 1,402 autosomal single-nucleotide polymorphism (SNP) markers. Haplotypes were reconstructed and additive, dominance, and imprinting genotype scores were derived every 1 cM along the F₁₆ map. Analysis was performed using a mixed model with additive, dominance, and imprinting genotype scores, their interactions with sex, diet, and with sex-by-diet as fixed effects and with family and its interaction with sex, diet, and sex-by-diet as random effects. We discovered 95 trait-specific QTLs mapping to 40 locations. Most QTLs had additive effects with dominance and imprinting effects occurring at two-thirds of the loci. Nearly every locus interacted with sex and/or diet in important ways demonstrating that gene effects are primarily context dependent, changing depending on sex and/or diet.
Keywords: Adipose Tissue; Adiposity; Animals; Body Weight; Diet; Epigenesis, Genetic; Female; Genome-Wide Association Study; Genomic Imprinting; Male; Mice; Obesity; Organ Size; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Disruptive TP53 mutation is associated with aggressive disease characteristics in an orthotopic murine model of oral tongue cancer. - Sano, Daisuke; Xie, Tong-Xin; Ow, Thomas J; Zhao, Mei; Pickering, Curtis R; Zhou, Ge; Sandulache, Vlad C; Wheeler, David A; Gibbs, Richard A; Caulin, Carlos; Myers, Jeffrey N (Clin Cancer Res, 2011)
PURPOSE: To characterize tumor growth and metastatic potential in head and neck squamous cell carcinoma (HNSCC) cell lines in an orthotopic murine model of oral tongue cancer and to correlate TP53 mutation status with these findings. EXPERIMENTAL DESIGN: Cells from each of 48 HNSCC cell lines were orthotopically injected into the oral tongues of nude mice. Tumor volume, cervical lymph node metastasis, and mouse survival were recorded. Direct sequencing of the TP53 gene and Western blot analysis for the p53 protein after induction with 5-fluorouracil was conducted. Cell lines were categorized as either mutant TP53 or wild-type TP53, and lines with TP53 mutation were further categorized on the basis of type of mutation (disruptive or nondisruptive) and level of p53 protein expression. The behavior of tumors in these different groups was compared. RESULTS: These 48 HNSCC cell lines showed a wide range of behavior from highly aggressive and metastatic to no tumor formation. Mice injected with cells harboring disruptive TP53 mutations had faster tumor growth, greater incidence of cervical lymph node metastasis, and shorter survival than mice injected with cells lacking these mutations. CONCLUSIONS: HNSCC cell lines display a wide spectrum of behavior in an orthotopic model of oral cancer. Cell lines with disruptive TP53 mutations are more aggressive in this system, corroborating clinical reports that have linked these mutations to poor patient outcome.
Keywords: Animals; Carcinoma, Squamous Cell; Cell Line, Tumor; Disease Models, Animal; Genes, p53; Head and Neck Neoplasms; Humans; Male; Mice; Mice, Nude; Mutation; Squamous Cell Carcinoma of Head and Neck; Tongue Neoplasms; Transplantation, Heterologous; Tumor Suppressor Protein p53

The Drosophila melanogaster transcriptome by paired-end RNA sequencing. - Daines, Bryce; Wang, Hui; Wang, Liguo; Li, Yumei; Han, Yi; Emmert, David; Gelbart, William; Wang, Xia; Li, Wei; Gibbs, Richard; Chen, Rui (Genome Res, 2011)
RNA-seq was used to generate an extensive map of the Drosophila melanogaster transcriptome by broad sampling of 10 developmental stages. In total, 142.2 million uniquely mapped 64-100-bp paired-end reads were generated on the Illumina GA II yielding 356× sequencing coverage. More than 95% of FlyBase genes and 90% of splicing junctions were observed. Modifications to 30% of FlyBase gene models were made by extension of untranslated regions, inclusion of novel exons, and identification of novel splicing events. A total of 319 novel transcripts were identified, representing a 2% increase over the current annotation. Alternate splicing was observed in 31% of D. melanogaster genes, a 38% increase over previous estimations, but significantly less than that observed in higher organisms. Much of this splicing is subtle such as tandem alternate splice sites.
Keywords: Alternative Splicing; Animals; Drosophila melanogaster; Female; Gene Expression Profiling; Genes, Y-Linked; Male; Molecular Sequence Annotation; Molecular Sequence Data; Oligonucleotide Array Sequence Analysis; Sequence Analysis, RNA

Familial thoracic aortic aneurysms and dissections: identification of a novel locus for stable aneurysms with a low risk for progression to aortic dissection. - Guo, Dong-chuan; Regalado, Ellen S; Minn, Charles; Tran-Fadulu, Van; Coney, Joshua; Cao, Jiumei; Wang, Min; Yu, Robert K; Estrera, Anthony L; Safi, Hazim J; Shete, Sanjay S; Milewicz, Dianna M (Circ Cardiovasc Genet, 2011)
BACKGROUND: Thoracic aortic aneurysms leading to acute aortic dissections are the major diseases that affect the thoracic aorta. Approximately 20% of patients with thoracic aortic aneurysms and dissections (TAAD) have a family history of TAAD, and these patients present younger with more rapidly enlarging aneurysms than patients without a family history of aortic disease. METHODS AND RESULTS: A large family with multiple members with TAAD inherited in an autosomal-dominant manner was identified. The ascending aortic aneurysms were associated with slow enlargement, a low risk of dissection, and decreased penetrance in women. Genome-wide linkage analysis was performed, and a novel locus on chromosome 12 was identified for the mutant gene causing disease in this family. Of the 12 male members who carry the disease-linked microsatellite haplotype, 9 had ascending aortic aneurysms with an average diameter of 4.7 cm at an average age of 52.4 years (range, 32 to 76 years) at the time of diagnosis; only 1 individual had progressed to acute aortic dissection, and no other members with aortic dissections were identified. Women harboring the disease-linked haplotype did not have thoracic aortic disease, including 1 aged 84 years. Sequencing of 9 genes within the critical interval at the chromosome 12 locus did not identify the mutant gene. CONCLUSIONS: Mapping a locus for ascending thoracic aortic aneurysms associated with a low risk of aortic dissection supports our hypothesis that genes leading to familial disease can be associated with less-aggressive thoracic aortic disease.
Keywords: Adult; Aged; Aged, 80 and over; Aorta; Aortic Aneurysm, Thoracic; Aortic Dissection; Chromosomes, Human, Pair 12; Disease Progression; Family; Female; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Haplotypes; Humans; Lod Score; Male; Middle Aged; Pedigree; Risk Factors; Sequence Analysis, DNA

Gastrointestinal microbiome signatures of pediatric patients with irritable bowel syndrome. - Saulnier, Delphine M; Riehle, Kevin; Mistretta, Toni-Ann; Diaz, Maria-Alejandra; Mandal, Debasmita; Raza, Sabeen; Weidler, Erica M; Qin, Xiang; Coarfa, Cristian; Milosavljevic, Aleksandar; Petrosino, Joseph F; Highlander, Sarah; et al. (Gastroenterology, 2011)
BACKGROUND & AIMS: The intestinal microbiomes of healthy children and pediatric patients with irritable bowel syndrome (IBS) are not well defined. Studies in adults have indicated that the gastrointestinal microbiota could be involved in IBS. METHODS: We analyzed 71 samples from 22 children with IBS (pediatric Rome III criteria) and 22 healthy children, ages 7-12 years, by 16S ribosomal RNA gene sequencing, with an average of 54,287 reads/stool sample (average 454 read length = 503 bases). Data were analyzed using phylogenetic-based clustering (Unifrac), or an operational taxonomic unit (OTU) approach using a supervised machine learning tool (randomForest). Most samples were also hybridized to a microarray that can detect 8741 bacterial taxa (16S rRNA PhyloChip). RESULTS: Microbiomes associated with pediatric IBS were characterized by a significantly greater percentage of the class γ-proteobacteria (0.07% vs 0.89% of total bacteria, respectively; P < .05); 1 prominent component of this group was Haemophilus parainfluenzae. Differences highlighted by 454 sequencing were confirmed by high-resolution PhyloChip analysis. Using supervised learning techniques, we were able to classify different subtypes of IBS with a success rate of 98.5%, using limited sets of discriminant bacterial species. A novel Ruminococcus-like microbe was associated with IBS, indicating the potential utility of microbe discovery for gastrointestinal disorders. A greater frequency of pain correlated with an increased abundance of several bacterial taxa from the genus Alistipes. CONCLUSIONS: Using 16S metagenomics by PhyloChip DNA hybridization and deep 454 pyrosequencing, we associated specific microbiome signatures with pediatric IBS. These findings indicate the important association between gastrointestinal microbes and IBS in children; these approaches might be used in diagnosis of functional bowel disorders in pediatric patients.
Keywords: Abdominal Pain; Case-Control Studies; Child; DNA Probes; Female; Gastrointestinal Tract; Haemophilus parainfluenzae; Humans; Incidence; Irritable Bowel Syndrome; Male; Metagenome; Phenotype; Phylogeny; RNA, Ribosomal, 16S; Ruminococcus

Genetic basis for in vivo daptomycin resistance in enterococci. - Arias, Cesar A; Panesso, Diana; McGrath, Danielle M; Qin, Xiang; Mojica, Maria F; Miller, Corwin; Diaz, Lorena; Tran, Truc T; Rincon, Sandra; Barbu, E Magda; Reyes, Jinnethe; Roh, Jung H; et al. (N Engl J Med, 2011)
BACKGROUND: Daptomycin is a lipopeptide with bactericidal activity that acts on the cell membrane of enterococci and is often used off-label to treat patients infected with vancomycin-resistant enterococci. However, the emergence of resistance to daptomycin during therapy threatens its usefulness. METHODS: We performed whole-genome sequencing and characterization of the cell envelope of a clinical pair of vancomycin-resistant Enterococcus faecalis isolates from the blood of a patient with fatal bacteremia; one isolate (S613) was from blood drawn before treatment and the other isolate (R712) was from blood drawn after treatment with daptomycin. The minimal inhibitory concentrations (MICs) of these two isolates were 1 and 12 μg per milliliter, respectively. Gene replacements were made to exchange the alleles found in isolate S613 with those in isolate R712. RESULTS: Isolate R712 had in-frame deletions in three genes. Two genes encoded putative enzymes involved in phospholipid metabolism, GdpD (which denotes glycerophosphoryl diester phosphodiesterase) and Cls (which denotes cardiolipin synthetase), and one gene encoded a putative membrane protein, LiaF (which denotes lipid II cycle-interfering antibiotics protein but whose exact function is not known). LiaF is predicted to be a member of a three-component regulatory system (LiaFSR) involved in the stress-sensing response of the cell envelope to antibiotics. Replacement of the liaF allele of isolate S613 with the liaF allele from isolate R712 quadrupled the MIC of daptomycin, whereas replacement of the gdpD allele had no effect on MIC. Replacement of both the liaF and gdpD alleles of isolate S613 with the liaF and gdpD alleles of isolate R712 raised the daptomycin MIC for isolate S613 to 12 μg per milliliter. As compared with isolate S613, isolate R712--the daptomycin-resistant isolate--had changes in the structure of the cell envelope and alterations in membrane permeability and membrane potential. CONCLUSIONS: Mutations in genes encoding LiaF and a GdpD-family protein were necessary and sufficient for the development of resistance to daptomycin during the treatment of vancomycin-resistant enterococci. (Funded by the National Institute of Allergy and Infectious Diseases and the National Institutes of Health.).
Keywords: Anti-Bacterial Agents; Bacteremia; Daptomycin; Drug Resistance, Bacterial; Enterococcus faecalis; Genes, Bacterial; Genome, Bacterial; Gram-Positive Bacterial Infections; Humans; Microbial Sensitivity Tests; Microscopy, Electron, Transmission; Mutation; Sequence Analysis, DNA; Vancomycin Resistance

Genetical genomics of Th1 and Th2 immune response in a baboon model of atherosclerosis risk factors. - Vinson, A; Curran, J E; Johnson, M P; Dyer, T D; Moses, E K; Blangero, J; Cox, L A; Rogers, J; Havill, L M; VandeBerg, J L; Mahaney, M C (Atherosclerosis, 2011)
OBJECTIVE: CD4(+) T-cells mediate inflammation in atherosclerosis, but additive genetic effects on associated pathways of Th1 and Th2 immune response have not been described. We sought to characterize heritability, pleiotropy, and QTL effects on the expression of genes implicated in Th1 and Th2 immune response in a baboon model of risk factors for atherosclerosis. METHODS: We employed a maximum likelihood-based variance decomposition approach to estimate additive genetic effects on transcript levels generated from a gene expression profile of lymphocytes in 499 pedigreed baboons maintained on a basal diet. Transcript levels for 57 genes implicated in Th1 and Th2 immune response were selected for analysis based on significant heritability in this profile. Multipoint whole genome scans were conducted on heritable transcript levels to localize QTLs influencing these measures. To evaluate pleiotropic effects on transcript levels, we estimated genetic and phenotypic correlations among transcript measures, and assessed their correspondence using a Mantel test. Network analysis using GeneGo's MetaCore™ software was conducted to characterize known interaction among coded proteins. RESULTS: Heritabilities for candidate gene transcript levels ranged from 0.092-0.786 (median h(2)=0.278, P=4.72×10(-4)). Linkage analyses yielded significant evidence (LOD≥2.73) for 14 eQTLs (LOD score range 2.76-14.87, genome-wide P=4.9×10(-2)-1.03×10(-14)). Estimates of genetic correlation supported shared additive genetic effects incorporating all 57 transcripts (null hypothesis of ρ(G)=0 rejected at FDR≤0.05 for 522 of 1596 estimates), and accounted for most of the observed phenotypic correlation among transcripts (Mantel test, r([ρP],)([ρG])=0.781, P<0.0001). Network analysis revealed direct interactions among 54 of the 57 coded proteins. CONCLUSIONS: We conclude that major genetic effects influence expression levels of multiple genes implicated in Th1 and Th2 immune response. Additionally, we find that expression levels of these candidate genes are characterized by extensive pleiotropy, consistent with known interaction among their coded proteins, many of which are independently associated with atherosclerosis.
Keywords: Animals; Atherosclerosis; Disease Models, Animal; Female; Gene Expression Profiling; Gene Regulatory Networks; Genetic Pleiotropy; Genetic Predisposition to Disease; Heredity; Inflammation; Male; Models, Genetic; Papio hamadryas; Phenotype; Quantitative Trait Loci; Risk Assessment; Risk Factors; Th1 Cells; Th2 Cells; Transcription, Genetic

Global DNA methylation and risk of subclinical atherosclerosis in young adults: the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) study. - Bressler, Jan; Shimmin, Lawrence C; Boerwinkle, Eric; Hixson, James E (Atherosclerosis, 2011)
OBJECTIVE: The association between hepatic global DNA methylation measured using pyrosequencing technology and the risk of subclinical atherosclerosis was examined in the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) study. PDAY is a bi-racial investigation of the natural history of atherosclerosis and its risk factors involving 3013 individuals aged 15-34 years who underwent autopsy after dying of unrelated causes in 1987-1994. METHODS: Raised atherosclerotic lesions were defined as the sum of the percentages of intimal surface area detected in the right coronary artery and left half of the abdominal and thoracic aorta harboring fibrous plaques, complicated lesions, and calcified lesions during a postmortem pathological examination. To conduct the case-control study, 300 cases selected with the highest raised lesion scores were paired with 300 controls without raised lesions after matching for age, race, and gender. RESULTS: Global DNA methylation was not associated with disease risk in the study population considered as a whole using conditional logistic regression models to analyze matched pairs. Since the estimation of the risk of atherosclerosis associated with inter-individual variation in DNA methylation was similar if unconditional logistic regression was used, subgroup analyses were carried out after adjusting for matching variables. A modest association with methylation levels below the median value was found in white but not in African-American study participants (odds ratio = 1.59, 95% confidence interval = 1.02-2.49, p = 0.04). CONCLUSIONS: Hepatic global DNA methylation does not appear to be a definitive determinant of atherosclerosis burden in a postmortem sample of young adults.
Keywords: Adolescent; Adult; Age Factors; Aorta, Abdominal; Aorta, Thoracic; Aortic Diseases; Asymptomatic Diseases; Atherosclerosis; Autopsy; Black or African American; Case-Control Studies; Coronary Artery Disease; Coronary Vessels; DNA; DNA Methylation; Female; Humans; Liver; Logistic Models; Male; Matched-Pair Analysis; Odds Ratio; Plaque, Atherosclerotic; Risk Assessment; Risk Factors; Texas; White People; Young Adult

Heritability of alveolar bone loss from periodontal disease in a baboon population: a pilot study. - Miley, D Douglas; Baumgartner, Mark H; Cheverud, James M; Roseman, Charles C; Rogers, Jeffrey; McLeod, Dwight E; Reyes, Elio; Hildebolt, Charles F (J Periodontol, 2011)
BACKGROUND: Reports from studies of twins, disease aggregation in families, animal models for periodontal disease, and various genetic-analysis studies have determined that genetics plays a role in the susceptibility to periodontal disease. The purpose of this pilot study is to evaluate the effect of genetics on periodontal disease by evaluating the heritability of alveolar bone loss in a captive baboon population. METHODS: A collection of baboon skulls from a pedigreed colony (for which scientists and veterinarians maintain complete genealogic and veterinary records) was obtained from the Southwest National Primate Research Center, San Antonio, Texas and used in this pilot study. Measurements of alveolar bone loss were performed on 390 dry baboon skulls. A periodontal probe was used to measure alveolar bone loss. Maximum likelihood methods (designed to handle complex genealogies) were used to determine the heritability of alveolar bone loss. This software used known pedigrees in the captive baboon sample and tested the relationship between pairwise kinship and alveolar bone loss data to determine the heritability of alveolar bone loss from periodontal disease. RESULTS: Genetic data were available for 347 of the 390 specimens. Using age and sex as covariates, genetic analysis indicated a heritability of 35% (standard error = 20%; P = 0.01). Although gender was not a significant factor in periodontal disease (P = 0.96), age was highly significantly associated with periodontal disease (P <0.0001). CONCLUSIONS: In this pilot study, analysis of alveolar bone loss measurements from captive baboons indicates that bone loss increases with age and that a portion of periodontal disease risk may be caused by genetic variance. These findings provide evidence that periodontal disease is heritable in captive baboons and indicate that a larger, more-detailed study is warranted.
Keywords: Age Factors; Alveolar Bone Loss; Animals; Disease Models, Animal; Female; Genetic Predisposition to Disease; Male; Mandible; Papio; Periodontal Diseases; Pilot Projects

A high-resolution map of human evolutionary constraint using 29 mammals. - Lindblad-Toh, Kerstin; Garber, Manuel; Zuk, Or; Lin, Michael F; Parker, Brian J; Washietl, Stefan; Kheradpour, Pouya; Ernst, Jason; Jordan, Gregory; Mauceli, Evan; Ward, Lucas D; Lowe, Craig B; et al. (Nature, 2011)
The comparison of related genomes has emerged as a powerful lens for genome interpretation. Here we report the sequencing and comparative analysis of 29 eutherian genomes. We confirm that at least 5.5% of the human genome has undergone purifying selection, and locate constrained elements covering ∼4.2% of the genome. We use evolutionary signatures and comparisons with experimental data sets to suggest candidate functions for ∼60% of constrained bases. These elements reveal a small number of new coding exons, candidate stop codon readthrough events and over 10,000 regions of overlapping synonymous constraint within protein-coding exons. We find 220 candidate RNA structural families, and nearly a million elements overlapping potential promoter, enhancer and insulator regions. We report specific amino acid residues that have undergone positive selection, 280,000 non-coding elements exapted from mobile elements and more than 1,000 primate- and human-accelerated elements. Overlap with disease-associated variants indicates that our findings will be relevant for studies of human biology, health and disease.
Keywords: Animals; Disease; Evolution, Molecular; Exons; Genome; Genome, Human; Genomics; Health; Humans; Mammals; Molecular Sequence Annotation; Phylogeny; RNA; Selection, Genetic; Sequence Alignment; Sequence Analysis, DNA

Identification of genetic susceptibility to childhood cancer through analysis of genes in parallel. - Plon, Sharon E; Wheeler, David A; Strong, Louise C; Tomlinson, Gail E; Pirics, Michael; Meng, Qingchang; Cheung, Hannah C; Begin, Phyllis R; Muzny, Donna M; Lewis, Lora; Biegel, Jaclyn A; Gibbs, Richard A (Cancer Genet, 2011)
Clinical cancer genetic susceptibility analysis typically proceeds sequentially, beginning with the most likely causative gene. The process is time consuming and the yield is low, particularly for families with unusual patterns of cancer. We determined the results of in parallel mutation analysis of a large cancer-associated gene panel. We performed deletion analysis and sequenced the coding regions of 45 genes (8 oncogenes and 37 tumor suppressor or DNA repair genes) in 48 childhood cancer patients who also (i) were diagnosed with a second malignancy under age 30, (ii) have a sibling diagnosed with cancer under age 30, and/or (iii) have a major congenital anomaly or developmental delay. Deleterious mutations were identified in 6 of 48 (13%) families, 4 of which met the sibling criteria. Mutations were identified in genes previously implicated in both dominant and recessive childhood syndromes, including SMARCB1, PMS2, and TP53. No pathogenic deletions were identified. This approach has provided efficient identification of childhood cancer susceptibility mutations and will have greater utility as additional cancer susceptibility genes are identified. Integrating parallel analysis of large gene panels into clinical testing will speed results and increase diagnostic yield. The failure to detect mutations in 87% of families highlights that a number of childhood cancer susceptibility genes remain to be discovered.
Keywords: Adolescent; Adult; Algorithms; Child; DNA Mutational Analysis; DNA Repair; Gene Dosage; Genes, Dominant; Genes, Recessive; Genes, Tumor Suppressor; Genetic Predisposition to Disease; Humans; Immunoprecipitation; Models, Genetic; Mutation; Neoplasms; Oncogenes; Reverse Transcriptase Polymerase Chain Reaction; Rhabdoid Tumor

The importance of context to the genetic architecture of diabetes-related traits is revealed in a genome-wide scan of a LG/J × SM/J murine model. - Lawson, Heather A; Lee, Arthur; Fawcett, Gloria L; Wang, Bing; Pletscher, L Susan; Maxwell, Taylor J; Ehrich, Thomas H; Kenney-Hunt, Jane P; Wolf, Jason B; Semenkovich, Clay F; Cheverud, James M (Mamm Genome, 2011)
Variations in diabetic phenotypes are caused by complex interactions of genetic effects, environmental factors, and the interplay between the two. We tease apart these complex interactions by examining genome-wide genetic and epigenetic effects on diabetes-related traits among different sex, diet, and sex-by-diet cohorts in a Mus musculus model. We conducted a genome-wide scan for quantitative trait loci that affect serum glucose and insulin levels and response to glucose stress in an F(16) Advanced Intercross Line of the LG/J and SM/J intercross (Wustl:LG,SM-G16). Half of each sibship was fed a high-fat diet and half was fed a relatively low-fat diet. Context-dependent genetic (additive and dominance) and epigenetic (parent-of-origin imprinting) effects were characterized by partitioning animals into sex, diet, and sex-by-diet cohorts. We found that different cohorts often have unique genetic effects at the same loci, and that genetic signals can be masked or erroneously assigned to specific cohorts if they are not considered individually. Our data demonstrate that the effects of genes on complex trait variation are highly context-dependent and that the same genomic sequence can affect traits differently depending on an individual's sex and/or dietary environment. Our results have important implications for studies of complex traits in humans.
Keywords: Animals; Animals, Outbred Strains; Blood Glucose; Diabetes Mellitus, Type 2; Disease Models, Animal; Female; Genome-Wide Association Study; Humans; Hybridization, Genetic; Insulin; Male; Mice; Quantitative Trait Loci

Integrated genomic analyses of ovarian carcinoma. (Nature, 2011)
A catalogue of molecular aberrations that cause ovarian cancer is critical for developing and deploying therapies that will improve patients' lives. The Cancer Genome Atlas project has analysed messenger RNA expression, microRNA expression, promoter methylation and DNA copy number in 489 high-grade serous ovarian adenocarcinomas and the DNA sequences of exons from coding genes in 316 of these tumours. Here we report that high-grade serous ovarian cancer is characterized by TP53 mutations in almost all tumours (96%); low prevalence but statistically recurrent somatic mutations in nine further genes including NF1, BRCA1, BRCA2, RB1 and CDK12; 113 significant focal DNA copy number aberrations; and promoter methylation events involving 168 genes. Analyses delineated four ovarian cancer transcriptional subtypes, three microRNA subtypes, four promoter methylation subtypes and a transcriptional signature associated with survival duration, and shed new light on the impact that tumours with BRCA1/2 (BRCA1 or BRCA2) and CCNE1 aberrations have on survival. Pathway analyses suggested that homologous recombination is defective in about half of the tumours analysed, and that NOTCH and FOXM1 signalling are involved in serous ovarian cancer pathophysiology.
Keywords: Aged; Carcinoma; DNA Methylation; Female; Gene Dosage; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Genomics; Humans; MicroRNAs; Middle Aged; Mutation; Ovarian Neoplasms; RNA, Messenger

Kinda baboons (Papio kindae) and grayfoot chacma baboons (P. ursinus griseipes) hybridize in the Kafue river valley, Zambia. - Jolly, C J; Burrell, A S; Phillips-Conroy, J E; Bergey, C; Rogers, J (Am J Primatol, 2011)
The ranges of small kinda (Papio kindae) and much larger grayfooted chacma (P. ursinus griseipes) baboons adjoin in the Kafue National Park, Zambia. In a visual survey of baboons at 48 sites in the Kafue River drainage we found that, contrary to previous reports, groups at the species interface near the town of Ngoma are phenotypically diverse and presumably formed by multigenerational hybridization. Mitochondrial and/or Y-chromosome genetic markers from fecal samples (N=164) collected at 29 sites support this conclusion. Groups with phenotypic signs of a history of hybridization also had taxon-specific mitochondria and Y-haplotypes from both parental species. Although the distribution of mitochondrial haplotypes largely mirrored that of external phenotypes, a significant proportion of male specimens from grayfoot as well as hybrid groups carried kinda Y-chromosomes, and kinda Y-chromosomes were involved in all observed cases of mitochondrial/Y-chromosome discordance. These observations are consistent with, though they do not prove, a population history in which the range of chacmas and the hybrid zone have advanced at the expense of the kinda range. They also suggest that, unexpectedly, kinda male×chacma female matings are much more common than the reciprocal cross in the ancestry of hybrids. We suggest that distinctive male kinda behavior and the "juvenile" appearance of kinda baboons of both sexes, perhaps combined with obstetric difficulties of a small kinda female carrying the large offspring of a chacma male, may account for this bias.
Keywords: Animals; Animals, Wild; DNA, Mitochondrial; Female; Genes, Y-Linked; Genetic Markers; Genetic Variation; Haplotypes; Hybridization, Genetic; Male; Papio; Papio ursinus; Phenotype; Sexual Behavior, Animal; Zambia

Long-range massively parallel mate pair sequencing detects distinct mutations and similar patterns of structural mutability in two breast cancer cell lines. - Hampton, Oliver A; Koriabine, Maxim; Miller, Christopher A; Coarfa, Cristian; Li, Jian; Den Hollander, Petra; Schoenherr, Caroline; Carbone, Lucia; Nefedov, Mikhail; Ten Hallers, Boudewijn F H; Lee, Adrian V; De Jong, Pieter J; et al. (Cancer Genet, 2011)
Cancer genomes frequently undergo genomic instability resulting in accumulation of chromosomal rearrangement. To date, one of the main challenges has been to confidently and accurately identify these rearrangements by using short-read massively parallel sequencing. We were able to improve cancer rearrangement detection by combining two distinct massively parallel sequencing strategies: fosmid-sized (36 kb on average) and standard 5 kb mate pair libraries. We applied this combined strategy to map rearrangements in two breast cancer cell lines, MCF7 and HCC1954. We detected and validated a total of 91 somatic rearrangements in MCF7 and 25 in HCC1954, including genomic alterations corresponding to previously reported transcript aberrations in these two cell lines. Each of the genomes contains two types of breakpoints: clustered and dispersed. In both cell lines, the dispersed breakpoints show enrichment for low copy repeats, while the clustered breakpoints associate with high copy number amplifications. Comparing the two genomes, we observed highly similar structural mutational spectra affecting different sets of genes, pointing to similar histories of genomic instability against the background of very different gene network perturbations.
Keywords: Breast Neoplasms; Cell Line, Tumor; Chromosome Aberrations; Chromosome Mapping; DNA, Neoplasm; Female; Genome, Human; Genomic Instability; High-Throughput Nucleotide Sequencing; Humans; Mutation; Polymerase Chain Reaction; Sequence Analysis, DNA

Loss of Rho GDIα and resistance to tamoxifen via effects on estrogen receptor α. - Barone, Ines; Brusco, Lauren; Gu, Guowei; Selever, Jennifer; Beyer, Amanda; Covington, Kyle R; Tsimelzon, Anna; Wang, Tao; Hilsenbeck, Susan G; Chamness, Gary C; Andò, Sebastiano; Fuqua, Suzanne A W (J Natl Cancer Inst, 2011)
BACKGROUND: Estrogen receptor (ER) α is a successful therapeutic target in breast cancer, but patients eventually develop resistance to antiestrogens such as tamoxifen. METHODS: To identify genes whose expression was associated with the development of tamoxifen resistance and metastasis, we used microarrays to compare gene expression in four primary tumors from tamoxifen-treated patients whose breast cancers did not recur vs five metastatic tumors from patients whose cancers progressed during adjuvant tamoxifen treatment. Because Rho guanine dissociation inhibitor (GDI) α was underexpressed in the tamoxifen-resistant group, we stably transfected ERα-positive MCF-7 breast cancer cells with a plasmid encoding a short hairpin (sh) RNA to silence Rho GDIα expression. We used immunoblots and transcription assays to examine the role of Rho GDIα in ER-related signaling and growth of cells in vitro and as xenografts in treated nude mice (n = 8-9 per group) to examine the effects of Rho GDIα blockade on hormone responsiveness and metastatic behavior. The time to tumor tripling as the time in weeks from randomization to a threefold increase in total tumor volume over baseline was examined in treated mice. The associations of Rho GDIα and MTA2 levels with tamoxifen resistance were examined in microarray data from patients. All statistical tests were two-sided. RESULTS: Rho GDIα was expressed at lower levels in ERα-positive tumors that recurred during tamoxifen treatment than in ERα-positive tamoxifen-sensitive primary tumors. MCF-7 breast cancer cells in which Rho GDIα expression had been silenced were tamoxifen-resistant, had increased Rho GTPase and p21-activated kinase 1 activity, increased phosphorylation of ERα at serine 305, and enhanced tamoxifen-induced ERα transcriptional activity compared with control cells. MCF-7 cells in which Rho GDIα expression was silenced metastasized with high frequency when grown as tumor xenografts. When mice were treated with estrogen or estrogen withdrawal, tripling times for xenografts from cells with Rho GDIα silencing were similar to those from vector-containing control cells; however, tripling times were statistically significantly faster than control when mice were treated with tamoxifen (median tripling time for tumors with Rho GDIα small interfering RNA = 2.34 weeks; for control tumors = not reached, hazard ratio = 4.13, 95% confidence interval = 1.07 to 15.96, P = .040 [adjusted for multiple comparisons, P = .119]). Levels of the metastasis-associated protein MTA2 were also increased upon Rho GDIα silencing, and combined Rho GDIα and MTA2 levels were associated with recurrence in 250 tamoxifen-treated patients. CONCLUSION: Loss of Rho GDIα enhances metastasis and resistance to tamoxifen via effects on both ERα and MTA2 in models of ERα-positive breast cancer and in tumors of tamoxifen-treated patients.
Keywords: Animals; Antineoplastic Agents, Hormonal; Breast Neoplasms; Cell Line, Tumor; Down-Regulation; Drug Resistance, Neoplasm; Enzyme Activation; Estrogen Antagonists; Estrogen Receptor alpha; Female; Gene Expression Regulation, Neoplastic; Gene Silencing; Genome-Wide Association Study; Guanine Nucleotide Dissociation Inhibitors; Histone Deacetylases; Humans; Immunoblotting; Immunohistochemistry; Immunoprecipitation; Mice; Mice, Nude; Neoplasm Recurrence, Local; Odds Ratio; Phenotype; Plasmids; Protein Array Analysis; Random Allocation; Repressor Proteins; Retrospective Studies; rho GTP-Binding Proteins; rho Guanine Nucleotide Dissociation Inhibitor alpha; rho-Specific Guanine Nucleotide Dissociation Inhibitors; RNA, Small Interfering; Secondary Prevention; Selective Estrogen Receptor Modulators; Signal Transduction; Tamoxifen; Time Factors; Transcriptional Activation; Transplantation, Heterologous; Tumor Stem Cell Assay

Minimum information about a marker gene sequence (MIMARKS) and minimum information about any (x) sequence (MIxS) specifications. - Yilmaz, Pelin; Kottmann, Renzo; Field, Dawn; Knight, Rob; Cole, James R; Amaral-Zettler, Linda; Gilbert, Jack A; Karsch-Mizrachi, Ilene; Johnston, Anjanette; Cochrane, Guy; Vaughan, Robert; Hunter, Christopher; et al. (Nat Biotechnol, 2011)
Here we present a standard developed by the Genomic Standards Consortium (GSC) for reporting marker gene sequences--the minimum information about a marker gene sequence (MIMARKS). We also introduce a system for describing the environment from which a biological sample originates. The 'environmental packages' apply to any genome sequence of known origin and can be used in combination with MIMARKS and other GSC checklists. Finally, to establish a unified standard for describing sequence data and to provide a single point of entry for the scientific community to access and learn about GSC checklists, we present the minimum information about any (x) sequence (MIxS). Adoption of MIxS will enhance our ability to analyze natural genetic diversity documented by massive DNA sequencing efforts from myriad ecosystems in our ever-changing biosphere.
Keywords: Biomarkers; Checklist; Databases, Genetic; Environment; Genes, rRNA; Genetic Variation; Humans; Information Storage and Retrieval; Internet; Metagenomics; Programming Languages; Sequence Analysis, DNA; Software

A preliminary report on the feeding of cynomolgus monkeys (Macaca fascicularis) with a high-sugar high-fat diet for 33 weeks. - Mubiru, James N; Garcia-Forey, Magdalena; Higgins, Paul B; Hemmat, Peggah; Cavazos, Nicole E; Dick, Edward J; Owston, Michael A; Bauer, Cassondra A; Shade, Robert E; Comuzzie, Anthony G; Rogers, Jeffrey (J Med Primatol, 2011)
BACKGROUND: The metabolic syndrome is common in populations exposed to a typical Western diet. There is a lack of an animal model that mimics this condition. METHODS: We fed 15 cynomolgus monkeys ad libitum a high-sugar high-fat (HSHF) diet for 33 weeks. Body weight, body composition, serum lipids, and insulin were measured at baseline and at 33 weeks. RESULTS: The animals tolerated the HSHF diet very well. In the intervention group, total serum cholesterol and low-density lipoprotein cholesterol were 3- and 5-fold higher, respectively, at 33 weeks as compared with their baseline levels. Serum high-density lipoprotein cholesterol and triglycerides were not significantly affected. Dual-energy X-ray absorptiometry (DXA) analysis of the intervention group indicated that the trunk fat mass increased by 187% during this period. CONCLUSIONS: Cynomolgus monkeys should be a useful model for investigating the interactions of diet and other factors such as genetics in the development of the metabolic syndrome.
Keywords: Absorptiometry, Photon; Animals; Biomarkers; Blood Glucose; Body Composition; Body Weight; Cholesterol; Dietary Carbohydrates; Dietary Fats; Energy Metabolism; Insulin; Macaca fascicularis; Male; Metabolic Syndrome; Models, Animal; Triglycerides

A primer on a hepatocellular carcinoma bioresource bank using the cancer genome atlas guidelines: practical issues and pitfalls. - Nguyen, N Thao T; Cotton, Ron T; Harring, Theresa R; Guiteau, Jacfranz J; Gingras, Marie-Claude; Wheeler, David A; O'Mahony, Christine A; Gibbs, Richard A; Brunicardi, F Charles; Goss, John A (World J Surg, 2011)
BACKGROUND: Since the advent of the human genome, the era of personalized genomic medicine is indisputably in progress. METHODS: In an effort to contribute to the evolving knowledge of genomic medicine, we have aimed directly at building a bioresource bank for hepatocellular carcinoma. This tumor bank is based on the rigorous guidelines set forth by the National Cancer Institute, and it offers analytes to help elucidate the mechanisms of progression from cirrhosis to malignancy, risk factors for recurrence, and applicability of current treatment options to a diverse group of people. CONCLUSIONS: Surgeons have a privileged position between patients (and their cancer) and the benches of basic science. Thus, we offer a primer based on our own experiences, from which surgeons may take elements to build their own bioresource bank for use in collaboration with others. We highlight some practicalities and pitfalls that could be overlooked, as well as a discussion of possible solutions.
Keywords: Carcinoma, Hepatocellular; Cell Transformation, Neoplastic; Cooperative Behavior; Databases, Genetic; Databases, Nucleic Acid; Disease Progression; Forecasting; Genetic Predisposition to Disease; Genome, Human; Guidelines as Topic; Humans; Interdisciplinary Communication; Liver; Liver Cirrhosis; Liver Neoplasms; National Cancer Institute (U.S.); Neoplasm Invasiveness; Neoplasm Recurrence, Local; Precision Medicine; Tissue Banks; United States

The promise of a personalized genomic approach to pancreatic cancer and why targeted therapies have missed the mark. - Fisher, William E (World J Surg, 2011)
Pancreatic cancer (PC) carries the highest mortality rate of any cancer type. Although minor advances in chemotherapy have been made, the mortality rate has remained the same over the last several decades. Clinical trials examining therapies targeting the epidermal growth factor (EGFR), vascular endothelial growth factor (VEGF), specific mutated proteins such as K-ras, immunotherapy employing tumor-associated antigens, and biologic therapy such as TNFerade (GenVec, Inc., Gaithersburg, MD) have all failed to substantially improve survival. Pancreatic cancer is likely a heterogeneous disease; therefore, a personalized genomic approach offers the possibility to tailor treatment to the unique characteristics of individual patients and their tumors. Rapid advances in sequencing technology are decreasing the time and cost of obtaining this information to a clinically useful level. However, many challenges remain to be faced in applying this technology in the field of PC. Even if patients with PC could be identified early in the course of the disease, localizing the disease and treating it in a minimally invasive fashion will remain problematic. Ethical issues including patient discrimination and access to care will be particularly important in PC. As the field advances, validation, education of clinicians, and determining the true value and source of funding will be difficult. Although the era of personalized genomic medicine has arrived, it will certainly take many years to begin to realize its potential. It is to be hoped that this new approach will result in a significant improvement in the survival curve for patients with PC.
Keywords: Antimetabolites, Antineoplastic; Antineoplastic Combined Chemotherapy Protocols; Combined Modality Therapy; Deoxycytidine; Drug Delivery Systems; Forecasting; Gemcitabine; Genetic Association Studies; Human Genome Project; Humans; Molecular Targeted Therapy; Pancreatic Neoplasms; Precision Medicine; Risk Factors; Sequence Analysis, DNA; Survival Rate; Treatment Failure

Resequencing of IRS2 reveals rare variants for obesity but not fasting glucose homeostasis in Hispanic children. - Butte, Nancy F; Voruganti, V Saroja; Cole, Shelley A; Haack, Karin; Comuzzie, Anthony G; Muzny, Donna M; Wheeler, David A; Chang, Kyle; Hawes, Alicia; Gibbs, Richard A (Physiol Genomics, 2011)
Our objective was to resequence insulin receptor substrate 2 (IRS2) to identify variants associated with obesity- and diabetes-related traits in Hispanic children. Exonic and intronic segments, 5' and 3' flanking regions of IRS2 (∼14.5 kb), were bidirectionally sequenced for single nucleotide polymorphism (SNP) discovery in 934 Hispanic children using 3730XL DNA Sequencers. Additionally, 15 SNPs derived from Illumina HumanOmni1-Quad BeadChips were analyzed. Measured genotype analysis tested associations between SNPs and obesity and diabetes-related traits. Bayesian quantitative trait nucleotide analysis was used to statistically infer the most likely functional polymorphisms. A total of 140 SNPs were identified with minor allele frequencies (MAF) ranging from 0.001 to 0.47. Forty-two of the 70 coding SNPs result in nonsynonymous amino acid substitutions relative to the consensus sequence; 28 SNPs were detected in the promoter, 12 in introns, 28 in the 3'-UTR, and 2 in the 5'-UTR. Two insertion/deletions (indels) were detected. Ten independent rare SNPs (MAF = 0.001-0.009) were associated with obesity-related traits (P = 0.01-0.00002). SNP 10510452_139 in the promoter region was shown to have a high posterior probability (P = 0.77-0.86) of influencing BMI, fat mass, and waist circumference in Hispanic children. SNP 10510452_139 contributed between 2 and 4% of the population variance in body weight and composition. None of the SNPs or indels were associated with diabetes-related traits or accounted for a previously identified quantitative trait locus on chromosome 13 for fasting serum glucose. Rare but not common IRS2 variants may play a role in the regulation of body weight but not an essential role in fasting glucose homeostasis in Hispanic children.
Keywords: Bayes Theorem; Child; Diabetes Mellitus; Fasting; Genetic Predisposition to Disease; Genotyping Techniques; Glucose; Hispanic or Latino; Homeostasis; Humans; Insulin Receptor Substrate Proteins; Linkage Disequilibrium; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Sequence Analysis, DNA

Systems biology data analysis methodology in pharmacogenomics. - Rodin, Andrei S; Gogoshin, Grigoriy; Boerwinkle, Eric (Pharmacogenomics, 2011)
Pharmacogenetics aims to elucidate the genetic factors underlying the individual's response to pharmacotherapy. Coupled with the recent (and ongoing) progress in high-throughput genotyping, sequencing and other genomic technologies, pharmacogenetics is rapidly transforming into pharmacogenomics, while pursuing the primary goals of identifying and studying the genetic contribution to drug therapy response and adverse effects, and existing drug characterization and new drug discovery. Accomplishment of both of these goals hinges on gaining a better understanding of the underlying biological systems; however, reverse-engineering biological system models from the massive datasets generated by the large-scale genetic epidemiology studies presents a formidable data analysis challenge. In this article, we review the recent progress made in developing such data analysis methodology within the paradigm of systems biology research that broadly aims to gain a 'holistic', or 'mechanistic' understanding of biological systems by attempting to capture the entirety of interactions between the components (genetic and otherwise) of the system.
Keywords: Artificial Intelligence; Drug Discovery; Drug-Related Side Effects and Adverse Reactions; Epistasis, Genetic; Genotype; Humans; Molecular Epidemiology; Pharmacogenetics; Research Design; Statistics as Topic; Systems Biology

Whole-exome sequencing identifies ALMS1, IQCB1, CNGA3, and MYO7A mutations in patients with Leber congenital amaurosis. - Wang, Xia; Wang, Hui; Cao, Ming; Li, Zhe; Chen, Xianfeng; Patenia, Claire; Gore, Athurva; Abboud, Emad B; Al-Rajhi, Ali A; Lewis, Richard A; Lupski, James R; Mardon, Graeme; et al. (Hum Mutat, 2011)
It has been well documented that mutations in the same retinal disease gene can result in different clinical phenotypes due to difference in the mutant allele and/or genetic background. To evaluate this, a set of consanguineous patient families with Leber congenital amaurosis (LCA) that do not carry mutations in known LCA disease genes was characterized through homozygosity mapping followed by targeted exon/whole-exome sequencing to identify genetic variations. Among these families, a total of five putative disease-causing mutations, including four novel alleles, were found for six families. These five mutations are located in four genes, ALMS1, IQCB1, CNGA3, and MYO7A. Therefore, in our LCA collection from Saudi Arabia, three of the 37 unassigned families carry mutations in retinal disease genes ALMS1, CNGA3, and MYO7A, which have not been previously associated with LCA, and 3 of the 37 carry novel mutations in IQCB1, which has been recently associated with LCA. Together with other reports, our results emphasize that the molecular heterogeneity underlying LCA, and likely other retinal diseases, may be highly complex. Thus, to obtain accurate diagnosis and gain a complete picture of the disease, it is essential to sequence a larger set of retinal disease genes and combine the clinical phenotype with molecular diagnosis.
Keywords: Calmodulin-Binding Proteins; Cell Cycle Proteins; Child, Preschool; Chromosome Mapping; Consanguinity; Cyclic Nucleotide-Gated Cation Channels; DNA Mutational Analysis; Exome; Family; Homozygote; Humans; Leber Congenital Amaurosis; Mutation; Myosin VIIa; Myosins; Pedigree; Proteins; Saudi Arabia; Sequence Analysis, DNA

Whole-genome sequencing for optimized patient management. - Bainbridge, Matthew N; Wiszniewski, Wojciech; Murdock, David R; Friedman, Jennifer; Gonzaga-Jauregui, Claudia; Newsham, Irene; Reid, Jeffrey G; Fink, John K; Morgan, Margaret B; Gingras, Marie-Claude; Muzny, Donna M; Hoang, Linh D; et al. (Sci Transl Med, 2011)
Whole-genome sequencing of patient DNA can facilitate diagnosis of a disease, but its potential for guiding treatment has been under-realized. We interrogated the complete genome sequences of a 14-year-old fraternal twin pair diagnosed with dopa (3,4-dihydroxyphenylalanine)-responsive dystonia (DRD; Mendelian Inheritance in Man #128230). DRD is a genetically heterogeneous and clinically complex movement disorder that is usually treated with l-dopa, a precursor of the neurotransmitter dopamine. Whole-genome sequencing identified compound heterozygous mutations in the SPR gene encoding sepiapterin reductase. Disruption of SPR causes a decrease in tetrahydrobiopterin, a cofactor required for the hydroxylase enzymes that synthesize the neurotransmitters dopamine and serotonin. Supplementation of l-dopa therapy with 5-hydroxytryptophan, a serotonin precursor, resulted in clinical improvements in both twins.
Keywords: Adolescent; Decision Making; Dystonic Disorders; Female; Genome, Human; Humans; Levodopa; Male; Patient Care; Pedigree; Sequence Analysis, DNA; Treatment Outcome; Twins, Dizygotic

Amygdalar and hippocampal substrates of anxious temperament differ in their heritability. - Oler, Jonathan A; Fox, Andrew S; Shelton, Steven E; Rogers, Jeffrey; Dyer, Thomas D; Davidson, Richard J; Shelledy, Wendy; Oakes, Terrence R; Blangero, John; Kalin, Ned H (Nature, 2010)
Anxious temperament (AT) in human and non-human primates is a trait-like phenotype evident early in life that is characterized by increased behavioural and physiological reactivity to mildly threatening stimuli. Studies in children demonstrate that AT is an important risk factor for the later development of anxiety disorders, depression and comorbid substance abuse. Despite its importance as an early predictor of psychopathology, little is known about the factors that predispose vulnerable children to develop AT and the brain systems that underlie its expression. To characterize the neural circuitry associated with AT and the extent to which the function of this circuit is heritable, we studied a large sample of rhesus monkeys phenotyped for AT. Using 238 young monkeys from a multigenerational single-family pedigree, we simultaneously assessed brain metabolic activity and AT while monkeys were exposed to the relevant ethological condition that elicits the phenotype. High-resolution (18)F-labelled deoxyglucose positron-emission tomography (FDG-PET) was selected as the imaging modality because it provides semi-quantitative indices of absolute glucose metabolic rate, allows for simultaneous measurement of behaviour and brain activity, and has a time course suited for assessing temperament-associated sustained brain responses. Here we demonstrate that the central nucleus region of the amygdala and the anterior hippocampus are key components of the neural circuit predictive of AT. We also show significant heritability of the AT phenotype by using quantitative genetic analysis. Additionally, using voxelwise analyses, we reveal significant heritability of metabolic activity in AT-associated hippocampal regions. However, activity in the amygdala region predictive of AT is not significantly heritable. Furthermore, the heritabilities of the hippocampal and amygdala regions significantly differ from each other. Even though these structures are closely linked, the results suggest differential influences of genes and environment on how these brain regions mediate AT and the ongoing risk of developing anxiety and depression.
Keywords: Amygdala; Animals; Anxiety; Depression; Female; Freezing Reaction, Cataleptic; Genetic Predisposition to Disease; Glucose; Heredity; Hippocampus; Macaca mulatta; Male; Models, Animal; Neural Pathways; Pedigree; Phenotype; Positron-Emission Tomography; Stress, Psychological; Temperament; Temporal Lobe; Vocalization, Animal

Association of glycemic index and glycemic load with risk of incident coronary heart disease among Whites and African Americans with and without type 2 diabetes: the Atherosclerosis Risk in Communities study. - Hardy, Dale S; Hoelscher, Deanna M; Aragaki, Corinne; Stevens, June; Steffen, Lyn M; Pankow, James S; Boerwinkle, Eric (Ann Epidemiol, 2010)
PURPOSE: In this study we examined whether high glycemic index (GI) and glycemic load (GL) diets are associated with increased risk of developing coronary heart disease (CHD) in Whites and African Americans with and without type 2 diabetes. METHODS: Data on 13,051 patients ages 45 to 64 years from the Atherosclerosis Risk in Communities study were analyzed. The ARIC food frequency questionnaire baseline data provided GI and GL indices. A propensity score was created to estimate the effect of a patient's covariates on energy-adjusted GI or GL. During a maximum of 17 years of follow-up, 1683 cases of CHD (371 with diabetes and 1312 without diabetes) were recorded. RESULTS: For every 5-units increase in GI, there was a 1.16-fold (95% confidence interval [95% CI], 1.01-1.33) increased risk of incident CHD in African Americans. For every 30-units increase in GL, there was a 1.11-fold (95% CI, 1.01-1.21) increased risk of incident CHD in Whites. High GL was an especially important CHD risk factor for Whites without diabetes (per 30-units increase; hazard ratio, 1.14; 95% CI, 1.02-1.26). However, these relationships were not seen in individuals with diabetes. CONCLUSIONS: Nutritional advice to reduce the GI and GL in diets of African Americans and Whites subjects (without diabetes) may play a role in reducing CHD risk.
Keywords: Black or African American; Coronary Disease; Diabetes Mellitus, Type 2; Diet; Female; Follow-Up Studies; Glycemic Index; Humans; Male; Middle Aged; Risk Assessment; Surveys and Questionnaires; White People

Associations between dietary patterns and flow cytometry-measured biomarkers of inflammation and cellular activation in the Atherosclerosis Risk in Communities (ARIC) Carotid Artery MRI Study. - Nettleton, Jennifer A; Matijevic, Nena; Follis, Jack L; Folsom, Aaron R; Boerwinkle, Eric (Atherosclerosis, 2010)
BACKGROUND: Specific foods and overall dietary patterns are associated with soluble biomarkers of systemic inflammation and endothelial activation. However, no large epidemiological studies have evaluated relationships between such dietary factors and cell-specific markers of activation and inflammation as measured by flow cytometry. METHODS: Cell aggregates and multiple platelet and leukocyte markers were quantified by flow cytometry in fresh whole blood from 1101 white adults participating in the Carotid Artery MRI Study, a subset of the larger Atherosclerosis Risk in Communities (ARIC) Study. Two dietary patterns ("Healthy" and "Western") were empirically derived via principal components analysis using data collected by food frequency questionnaire. Cross-sectional associations between dietary patterns and flow cytometry-measured biomarkers were evaluated, adjusting for demographics and lifestyle factors, including medications use. RESULTS: After multivariable adjustment, monocyte lipopolysaccharide receptor (CD14), monocyte toll-like receptor-2, and platelet glycoprotein IIb (CD41) showed inverse associations with the Healthy dietary pattern (p=0.01, 0.04, and 0.01, respectively). In contrast, the Western dietary pattern was positively associated with CD41 and platelet-granulocyte aggregates (p=0.01 and 0.04, respectively). Independent of other dietary factors, alcohol consumption was inversely associated with levels of pan-leukocyte marker (CD45), P-selectin (CD62P) on PLA1 and on PLA2 platelets, and platelet-monocyte, platelet-granulocyte, and platelet-lymphocyte aggregates. CONCLUSION: Dietary patterns and alcohol intake were each cross-sectionally associated with select markers of cellular activation and inflammation measured by flow cytometry. These data are consistent with the hypothesis that holistic measures of dietary intake are associated with inflammation.
Keywords: Aged; Alcohol Drinking; Biomarkers; Carotid Arteries; Carotid Artery Diseases; Cross-Sectional Studies; Diet Records; Feeding Behavior; Female; Flow Cytometry; Humans; Inflammation; Inflammation Mediators; Leukocyte Common Antigens; Life Style; Linear Models; Lipopolysaccharide Receptors; Magnetic Resonance Angiography; Male; P-Selectin; Platelet Membrane Glycoprotein IIb; Principal Component Analysis; Risk Assessment; Risk Factors; Surveys and Questionnaires; Toll-Like Receptor 2; United States

A catalog of reference genomes from the human microbiome. - Nelson, Karen E; Weinstock, George M; Highlander, Sarah K; Worley, Kim C; Creasy, Heather Huot; Wortman, Jennifer Russo; Rusch, Douglas B; Mitreva, Makedonka; Sodergren, Erica; Chinwalla, Asif T; Feldgarden, Michael; Gevers, Dirk; et al. (Science, 2010)
The human microbiome refers to the community of microorganisms, including prokaryotes, viruses, and microbial eukaryotes, that populate the human body. The National Institutes of Health launched an initiative that focuses on describing the diversity of microbial species that are associated with health and disease. The first phase of this initiative includes the sequencing of hundreds of microbial reference genomes, coupled to metagenomic sequencing from multiple body sites. Here we present results from an initial reference genome sequencing of 178 microbial genomes. From 547,968 predicted polypeptides that correspond to the gene complement of these strains, previously unidentified ("novel") polypeptides that had both unmasked sequence length greater than 100 amino acids and no BLASTP match to any nonreference entry in the nonredundant subset were defined. This analysis resulted in a set of 30,867 polypeptides, of which 29,987 (approximately 97%) were unique. In addition, this set of microbial genomes allows for approximately 40% of random sequences from the microbiome of the gastrointestinal tract to be associated with organisms based on the match criteria used. Insights into pan-genome analysis suggest that we are still far from saturating microbial species genetic data sets. In addition, the associated metrics and standards used by our group for quality assurance are presented.
Keywords: Bacteria; Bacterial Proteins; Biodiversity; Computational Biology; Databases, Genetic; Gastrointestinal Tract; Genes, Bacterial; Genetic Variation; Genome, Archaeal; Genome, Bacterial; Humans; Metagenome; Metagenomics; Mouth; Peptides; Phylogeny; Respiratory System; Sequence Analysis, DNA; Skin; Urogenital System

Diabetes genes and prostate cancer in the Atherosclerosis Risk in Communities study. - Meyer, Tamra E; Boerwinkle, Eric; Morrison, Alanna C; Volcik, Kelly A; Sanderson, Maureen; Coker, Ann L; Pankow, James S; Folsom, Aaron R (Cancer Epidemiol Biomarkers Prev, 2010)
There is a known inverse association between type 2 diabetes (T2D) and prostate cancer (PrCa) that is poorly understood. Genetic studies of the T2D-PrCa association may provide insight into the underlying mechanisms of this association. We evaluated associations in the Atherosclerosis Risk in Communities study between PrCa and nine T2D single nucleotide polymorphisms from genome-wide association studies of T2D (in CDKAL1, CDKN2A/B, FTO, HHEX, IGF2BP2, KCNJ11, PPARG, SLC30A8, and TCF7L2) and four T2D single nucleotide polymorphisms from pre-genome-wide association studies (in ADRB2, CAPN10, SLC2A2, and UCP2). From 1987 to 2000, there were 397 incident PrCa cases among 6,642 men ages 45 to 64 years at baseline. We used race-adjusted Cox proportional hazards models to estimate associations between PrCa and increasing number of T2D risk-raising alleles. PrCa was positively associated with the CAPN10 rs3792267 G allele [hazard ratio (HR) 1.20; 95% confidence interval (CI), 1.00-1.44] and inversely associated with the SLC2A2 rs5400 Thr110 allele (HR, 0.85; 95% CI, 0.72, 1.00), the UCP2 rs660339 Val55 allele (HR, 0.84; 95% CI, 0.73, 0.97) and the IGF2BP2 rs4402960 T allele (HR, 0.79; 95% CI, 0.61-1.02; blacks only). The TCF7L2 rs7903146 T allele was inversely associated with PrCa using a dominant genetic model (HR, 0.79; 95% CI, 0.65-0.97). Further knowledge of T2D gene-PrCa mechanisms may improve understanding of PrCa etiology.
Keywords: Atherosclerosis; Calpain; Cohort Studies; Diabetes Mellitus, Type 2; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Transporter Type 2; Humans; Ion Channels; Male; Middle Aged; Mitochondrial Proteins; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prostatic Neoplasms; RNA-Binding Proteins; TCF Transcription Factors; Transcription Factor 7-Like 2 Protein; Uncoupling Protein 2

Discovery of novel microRNAs in female reproductive tract using next generation sequencing. - Creighton, Chad J; Benham, Ashley L; Zhu, Huifeng; Khan, Mahjabeen F; Reid, Jeffrey G; Nagaraja, Ankur K; Fountain, Michael D; Dziadek, Olivia; Han, Derek; Ma, Lang; Kim, Jong; Hawkins, Shannon M; et al. (PLoS One, 2010)
MicroRNAs (miRNAs) are small non-coding RNAs that mediate post-transcriptional gene silencing. Over 700 human miRNAs have currently been identified, many of which are mutated or de-regulated in diseases. Here we report the identification of novel miRNAs through deep sequencing the small RNAome (<30 nt) of over 100 tissues or cell lines derived from human female reproductive organs in both normal and disease states. These specimens include ovarian epithelium and ovarian cancer, endometrium and endometriomas, and uterine myometrium and uterine smooth muscle tumors. Sequence reads not aligning with known miRNAs were each mapped to the genome to extract flanking sequences. These extended sequence regions were folded in silico to identify RNA hairpins. Sequences demonstrating the ability to form a stem loop structure with low minimum free energy (<-25 kcal) and predicted Drosha and Dicer cut sites yielding a mature miRNA sequence matching the actual sequence were considered putative novel miRNAs. Additional confidence was achieved when putative novel hairpins assembled a collection of sequences highly similar to the putative mature miRNA but with heterogeneous 3'-ends. A confirmed novel miRNA fulfilled these criteria and had its "star" sequence in our collection. We found 7 distinct confirmed novel miRNAs, and 51 additional novel miRNAs that represented highly confident predictions but without detectable star sequences. Our novel miRNAs were detectable in multiple samples, but expressed at low levels and not specific to any one tissue or cell type. To date, this study represents the largest set of samples analyzed together to identify novel miRNAs.
Keywords: Cell Line; DNA, Complementary; Female; Genetic Techniques; Genitalia, Female; Humans; MicroRNAs; Nucleic Acid Conformation; Ovarian Neoplasms; Ovary; Polymerase Chain Reaction; Ribonuclease III; Sequence Analysis, DNA; Tissue Distribution

European admixture on the Micronesian island of Kosrae: lessons from complete genetic information. - Bonnen, Penelope E; Lowe, Jennifer K; Altshuler, David M; Breslow, Jan L; Stoffel, Markus; Friedman, Jeffrey M; Pe'er, Itsik (Eur J Hum Genet, 2010)
The architecture of natural variation present in a contemporary population is a result of multiple population genetic forces, including population bottleneck and expansion, selection, drift, and admixture. We seek to untangle the contribution of admixture to genetic diversity on the Micronesian island of Kosrae. Toward this goal, we used a complete genetic approach by combining a dense genome-wide map of 100,000 single-nucleotide polymorphisms (SNPs) with data from uniparental markers from the mitochondrial genome and the nonrecombining portion of the Y chromosome. These markers were typed in approximately 3200 individuals from Kosrae, representing 80% of the adult population of the island. We developed novel software that uses SNP data to delineate ancestry for individual segments of the genome. Through this analysis, we determined that 39% of Kosraens have some European ancestry. However, the vast majority of admixed individuals (77%) have European alleles spanning less than 10% of their genomes. Data from uniparental markers show most of this admixture to be male, introduced in the late nineteenth century. Furthermore, pedigree analysis shows that the majority of European admixture on Kosrae is because of the contribution of one individual. This approach shows the benefit of combining information from autosomal and uniparental polymorphisms and provides new methodology for determining ancestry in a population.
Keywords: Chromosomes, Human, Y; DNA, Mitochondrial; Europe; Female; Gene Pool; Genetic Markers; Genetics, Population; Genome, Human; Geography; Haplotypes; Humans; Inheritance Patterns; Male; Micronesia; Pedigree; Phylogeny; Software; Time Factors

A full-length cDNA resource for the pea aphid, Acyrthosiphon pisum. - Shigenobu, S; Richards, S; Cree, A G; Morioka, M; Fukatsu, T; Kudo, T; Miyagishima, S; Gibbs, R A; Stern, D L; Nakabachi, A (Insect Mol Biol, 2010)
Large collections of full-length cDNAs are important resources for genome annotation and functional genomics. We report the creation of a collection of 50 599 full-length cDNA clones from the pea aphid, Acyrthosiphon pisum. Sequencing from 5' and 3' ends of the clones generated 97 828 high-quality expressed sequence tags, representing approximately 9000 genes. These sequences were imported to AphidBase and are shown to play crucial roles in both automatic gene prediction and manual annotation. Our detailed analyses demonstrated that the full-length cDNAs can further improve gene models and can even identify novel genes that are not included in the current version of the official gene set. This full-length cDNA collection can be utilized for a wide variety of functional studies, serving as a community resource for the study of the functional genomics of the pea aphid.
Keywords: 3' Untranslated Regions; 5' Untranslated Regions; Animals; Aphids; Base Sequence; DNA Primers; DNA, Complementary; Expressed Sequence Tags; Gene Library; Genome, Insect; Host-Pathogen Interactions; Models, Genetic; Pisum sativum

Functional and evolutionary insights from the genomes of three parasitoid Nasonia species. - Werren, John H; Richards, Stephen; Desjardins, Christopher A; Niehuis, Oliver; Gadau, Jürgen; Colbourne, John K; Werren, John H; Richards, Stephen; Desjardins, Christopher A; Niehuis, Oliver; Gadau, Jürgen; Colbourne, John K; et al. (Science, 2010)
We report here genome sequences and comparative analyses of three closely related parasitoid wasps: Nasonia vitripennis, N. giraulti, and N. longicornis. Parasitoids are important regulators of arthropod populations, including major agricultural pests and disease vectors, and Nasonia is an emerging genetic model, particularly for evolutionary and developmental genetics. Key findings include the identification of a functional DNA methylation tool kit; hymenopteran-specific genes including diverse venoms; lateral gene transfers among Pox viruses, Wolbachia, and Nasonia; and the rapid evolution of genes involved in nuclear-mitochondrial interactions that are implicated in speciation. Newly developed genome resources advance Nasonia for genetic research, accelerate mapping and cloning of quantitative trait loci, and will ultimately provide tools and knowledge for further increasing the utility of parasitoids as pest insect-control agents.
Keywords: Animals; Arthropods; Biological Evolution; DNA Methylation; DNA Transposable Elements; Female; Gene Transfer, Horizontal; Genes, Insect; Genetic Speciation; Genetic Variation; Genome, Insect; Host-Parasite Interactions; Insect Proteins; Insect Viruses; Insecta; Male; Molecular Sequence Data; Quantitative Trait Loci; Recombination, Genetic; Sequence Analysis, DNA; Wasp Venoms; Wasps; Wolbachia

Genetic diversity in India and the inference of Eurasian population expansion. - Xing, Jinchuan; Watkins, W Scott; Hu, Ya; Huff, Chad D; Sabo, Aniko; Muzny, Donna M; Bamshad, Michael J; Gibbs, Richard A; Jorde, Lynn B; Yu, Fuli (Genome Biol, 2010)
BACKGROUND: Genetic studies of populations from the Indian subcontinent are of great interest because of India's large population size, complex demographic history, and unique social structure. Despite recent large-scale efforts in discovering human genetic variation, India's vast reservoir of genetic diversity remains largely unexplored. RESULTS: To analyze an unbiased sample of genetic diversity in India and to investigate human migration history in Eurasia, we resequenced one 100-kb ENCODE region in 92 samples collected from three castes and one tribal group from the state of Andhra Pradesh in south India. Analyses of the four Indian populations, along with eight HapMap populations (692 samples), showed that 30% of all SNPs in the south Indian populations are not seen in HapMap populations. Several Indian populations, such as the Yadava, Mala/Madiga, and Irula, have nucleotide diversity levels as high as those of HapMap African populations. Using unbiased allele-frequency spectra, we investigated the expansion of human populations into Eurasia. The divergence time estimates among the major population groups suggest that Eurasian populations in this study diverged from Africans during the same time frame (approximately 90 to 110 thousand years ago). The divergence among different Eurasian populations occurred more than 40,000 years after their divergence with Africans. CONCLUSIONS: Our results show that Indian populations harbor large amounts of genetic variation that have not been surveyed adequately by public SNP discovery efforts. Our data also support a delayed expansion hypothesis in which an ancestral Eurasian founding population remained isolated long after the out-of-Africa diaspora, before expanding throughout Eurasia.
Keywords: DNA, Mitochondrial; Ethnicity; Gene Frequency; Genetic Variation; Genetics, Population; Geography; Humans; India; Polymorphism, Single Nucleotide; Population Density; Population Dynamics; Sequence Analysis, DNA

Genetic, epigenetic, and gene-by-diet interaction effects underlie variation in serum lipids in a LG/JxSM/J murine model. - Lawson, Heather A; Zelle, Kathleen M; Fawcett, Gloria L; Wang, Bing; Pletscher, L Susan; Maxwell, Taylor J; Ehrich, Thomas H; Kenney-Hunt, Jane P; Wolf, Jason B; Semenkovich, Clay F; Cheverud, James M (J Lipid Res, 2010)
Variation in serum cholesterol, free-fatty acids, and triglycerides is associated with cardiovascular disease (CVD) risk factors. There is great interest in characterizing the underlying genetic architecture of these risk factors, because they vary greatly within and among human populations and between the sexes. We present results of a genome-wide scan for quantitative trait loci (QTL) affecting serum cholesterol, free-fatty acids, and triglycerides in an F(16) advanced intercross line of LG/J and SM/J (Wustl:LG,SM-G16). Half of the population was fed a high-fat diet and half was fed a relatively low-fat diet. Context-dependent genetic (additive and dominance) and epigenetic (imprinting) effects were characterized by partitioning animals into sex, diet, and sex-by-diet cohorts. Here we examine genetic, environmental, and genetic-by-environmental interactions of QTL overlapping previously identified loci associated with CVD risk factors, and we add to the serum lipid QTL landscape by identifying new loci.
Keywords: Animals; Cardiovascular Diseases; Crosses, Genetic; Diet; Epigenesis, Genetic; Genetic Variation; Humans; Lipids; Mice; Models, Animal; Quantitative Trait Loci

The importance of being cis: evolution of orthologous fish and mammalian enhancer activity. - Ritter, Deborah I; Li, Qiang; Kostka, Dennis; Pollard, Katherine S; Guo, Su; Chuang, Jeffrey H (Mol Biol Evol, 2010)
Conserved noncoding elements (CNEs) in vertebrate genomes often act as developmental enhancers, but a critical issue is how well orthologous CNE sequences retain the same activity in their respective species, a characteristic important for generalization of model organism studies. To quantify how well CNE enhancer activity has been preserved, we compared the anatomy-specific activities of 41 zebra fish CNEs in zebra fish embryos with the activities of orthologous human CNEs in mouse embryos. We found that 13/41 (∼30%) of the orthologous CNE pairs exhibit conserved positive activity in zebra fish and mouse. Conserved positive activity is only weakly associated with either sequence conservation or the absence of bases undergoing accelerated evolution. A stronger effect is that disparate activity is associated with transcription factor binding site divergence. To distinguish the contributions of cis- versus trans-regulatory changes, we analyzed 13 CNEs in a three-way experimental comparison: human CNE tested in zebra fish, human CNE tested in mouse, and orthologous zebra fish CNE tested in zebra fish. Both cis- and trans-changes affect a significant fraction of CNEs, although human and zebra fish sequences exhibit disparate activity in zebra fish (indicating cis regulatory changes) twice as often as human sequences show disparate activity when tested in mouse and zebra fish (indicating trans regulatory changes). In all four cases where the zebra fish and human CNE display a similar expression pattern in zebra fish, the human CNE also displays a similar expression pattern in mouse. This suggests that the endogenous enhancer activity of ∼30% of human CNEs can be determined from experiments in zebra fish alone, and to identify these CNEs, both the zebra fish and the human sequences should be tested.
Keywords: Animals; Conserved Sequence; DNA, Intergenic; Enhancer Elements, Genetic; Evolution, Molecular; Gene Expression Profiling; Gene Regulatory Networks; Humans; Mice; ROC Curve; Transcription Factors; Zebrafish

Integrating common and rare genetic variation in diverse human populations. - Altshuler, David M; Gibbs, Richard A; Peltonen, Leena; Altshuler, David M; Gibbs, Richard A; Peltonen, Leena; Dermitzakis, Emmanouil; Schaffner, Stephen F; Yu, Fuli; Peltonen, Leena; Dermitzakis, Emmanouil; Bonnen, Penelope E; et al. (Nature, 2010)
Despite great progress in identifying genetic variants that influence human disease, most inherited risk remains unexplained. A more complete understanding requires genome-wide studies that fully examine less common alleles in populations with a wide range of ancestry. To inform the design and interpretation of such studies, we genotyped 1.6 million common single nucleotide polymorphisms (SNPs) in 1,184 reference individuals from 11 global populations, and sequenced ten 100-kilobase regions in 692 of these individuals. This integrated data set of common and rare alleles, called 'HapMap 3', includes both SNPs and copy number polymorphisms (CNPs). We characterized population-specific differences among low-frequency variants, measured the improvement in imputation accuracy afforded by the larger reference panel, especially in imputing SNPs with a minor allele frequency of <or=5%, and demonstrated the feasibility of imputing newly discovered CNPs and SNPs. This expanded public resource of genome variants in global populations supports deeper interrogation of genomic variation and its role in human disease, and serves as a step towards a high-resolution map of the landscape of human genetic variation.
Keywords: DNA Copy Number Variations; Genome, Human; Human Genome Project; Humans; Polymorphism, Single Nucleotide; Population Groups

A map of human genome variation from population-scale sequencing. - Abecasis, Gonçalo R; Altshuler, David; Auton, Adam; Brooks, Lisa D; Durbin, Richard M; Gibbs, Richard A; Hurles, Matt E; McVean, Gil A (Nature, 2010)
The 1000 Genomes Project aims to provide a deep characterization of human genome sequence variation as a foundation for investigating the relationship between genotype and phenotype. Here we present results of the pilot phase of the project, designed to develop and compare different strategies for genome-wide sequencing with high-throughput platforms. We undertook three projects: low-coverage whole-genome sequencing of 179 individuals from four populations; high-coverage sequencing of two mother-father-child trios; and exon-targeted sequencing of 697 individuals from seven populations. We describe the location, allele frequency and local haplotype structure of approximately 15 million single nucleotide polymorphisms, 1 million short insertions and deletions, and 20,000 structural variants, most of which were previously undescribed. We show that, because we have catalogued the vast majority of common variation, over 95% of the currently accessible variants found in any individual are present in this data set. On average, each person is found to carry approximately 250 to 300 loss-of-function variants in annotated genes and 50 to 100 variants previously implicated in inherited disorders. We demonstrate how these results can be used to inform association and functional studies. From the two trios, we directly estimate the rate of de novo germline base substitution mutations to be approximately 10(-8) per base pair per generation. We explore the data with regard to signatures of natural selection, and identify a marked reduction of genetic variation in the neighbourhood of genes, due to selection at linked sites. These methods and public data will support the next phase of human genetic research.
Keywords: Calibration; Chromosomes, Human, Y; Computational Biology; DNA Mutational Analysis; DNA, Mitochondrial; Evolution, Molecular; Female; Genetic Association Studies; Genetic Variation; Genetics, Population; Genome, Human; Genome-Wide Association Study; Genomics; Genotype; Haplotypes; Humans; Male; Mutation; Pilot Projects; Polymorphism, Single Nucleotide; Recombination, Genetic; Sample Size; Selection, Genetic; Sequence Alignment; Sequence Analysis, DNA

Mutational analysis of the latency-associated nuclear antigen DNA-binding domain of Kaposi's sarcoma-associated herpesvirus reveals structural conservation among gammaherpesvirus origin-binding proteins. - Han, Soo-Jin; Hu, Jianhong; Pierce, Brian; Weng, Zhiping; Renne, Rolf (J Gen Virol, 2010)
The latency-associated nuclear antigen (LANA) of Kaposi's sarcoma-associated herpesvirus functions as an origin-binding protein (OBP) and transcriptional regulator. LANA binds the terminal repeats via the C-terminal DNA-binding domain (DBD) to support latent DNA replication. To date, the structure of LANA has not been solved. Sequence alignments among OBPs of gammaherpesviruses have revealed that the C terminus of LANA is structurally related to EBNA1, the OBP of Epstein-Barr virus. Based on secondary structure predictions for LANA(DBD) and published structures of EBNA1(DBD), this study used bioinformatics tools to model a putative structure for LANA(DBD) bound to DNA. To validate the predicted model, 38 mutants targeting the most conserved motifs, namely three alpha-helices and a conserved proline loop, were constructed and functionally tested. In agreement with data for EBNA1, residues in helices 1 and 2 mainly contributed to sequence-specific DNA binding and replication activity, whilst mutations in helix 3 affected replication activity and multimer formation. Additionally, several mutants were isolated with discordant phenotypes, which may aid further studies into LANA function. In summary, these data suggest that the secondary and tertiary structures of LANA and EBNA1 DBDs are conserved and are critical for (i) sequence-specific DNA binding, (ii) multimer formation, (iii) LANA-dependent transcriptional repression, and (iv) DNA replication.
Keywords: Amino Acid Sequence; Amino Acid Substitution; Animals; Antigens, Viral; Binding Sites; Cell Line; Chlorocebus aethiops; Conserved Sequence; DNA Replication; DNA, Viral; Electrophoretic Mobility Shift Assay; Epstein-Barr Virus Nuclear Antigens; Evolution, Molecular; Gammaherpesvirinae; Herpesvirus 8, Human; Humans; Models, Molecular; Molecular Sequence Data; Mutant Proteins; Mutation; Nuclear Proteins; Protein Multimerization; Protein Structure, Quaternary; Protein Structure, Tertiary; Sequence Homology, Amino Acid; Structural Homology, Protein

A new diagnostic system for ultra-sensitive and specific detection and quantification of Candidatus Liberibacter asiaticus, the bacterium associated with citrus Huanglongbing. - Lin, Hong; Chen, Chuanwu; Harshavardhan Doddapaneni; Duan, Yongping; Civerolo, Edwin L; Bai, Xianjin; Zhao, Xiaolong (J Microbiol Methods, 2010)
An ultra-sensitive and quantitative diagnostic system by combining nested PCR and TaqMan PCR in a single tube was developed for detection of "Candidatus Liberibacter asiaticus". The procedure involves two PCR steps using the species-specific outer and inner primer pairs. Different annealing temperatures allow both the first and the second rounds of PCR to be performed sequentially in the same closed tube. The first PCR with outer primers was performed at a higher annealing temperature and with limited amount of primers to prevent interference with the inner primers during the second round of PCR. The specificity of the dual primer TaqMan is high because the fluorescent signal can only be generated from the TaqMan probes that are homologous to the product amplified by the outer and inner primers. This new detection system can reliably detect as few as single copies of target DNA. The sensitivity of the dual primer system is comparable to the conventional two-tube nested PCR, but it eliminates the potential risk of cross contamination commonly associated with conventional nested PCR. This one-tube dual primer TaqMan PCR method is gel-free with reduced handling time and is cost effective. At the same time, this system provides significantly increased sensitivity, improved reliability and high through-put capability suitable for routine, large scale diagnoses of clinical plant tissue and insect samples. The technique described here is generic and can be applied to the detection of other plant pathogenic bacteria.
Keywords: Citrus; DNA Primers; Oligonucleotide Probes; Polymerase Chain Reaction; Rhizobiaceae; Sensitivity and Specificity

P450 redox enzymes in the white rot fungus Phanerochaete chrysosporium: gene transcription, heterologous expression, and activity analysis on the purified proteins. - Subramanian, Venkataramanan; Doddapaneni, Harshavardhan; Syed, Khajamohiddin; Yadav, Jagjit S (Curr Microbiol, 2010)
With an aim to understand the cytochrome P450 enzyme system in the white rot fungus Phanerochaete chrysosporium, here we report molecular characterization of its P450 redox proteins including the primary P450 oxidoreductase (POR) and two alternate P450 redox proteins cytochrome b5 (cyt b5) and cytochrome b5 reductase (cyt b5r) in terms of transcriptional regulation and heterologous expression. The transcript abundance followed the order POR > cyt b5r > cyt b5. Interestingly, the three genes showed an overall higher expression in the defined carbon-limited cultures with low nitrogen (LN) or high nitrogen (HN) versus the carbon-rich malt extract (ME) cultures. cDNA cloning and analysis revealed the following deduced protein characteristics: cyt b5 (238 amino acids, 25.38 kDa) and cyt b5r (321 amino acids, 35.52 kDa). Phylogenetic analysis revealed that the cloned cyt b5 belongs to a novel class of fungal cyt b5-like proteins. The two proteins cyt b5 and cyt b5r were heterologously expressed in E. coli and purified using affinity-based purification in an active form. The POR was heterologously expressed in Saccharomyces cerevisiae and was also purified in active form as evidenced by its cytochrome c reduction activity. This is the first report on cloning, heterologous expression, and purification of the alternate redox proteins cyt b5 and cyt b5r in E. coli and on yeast expression of POR from this model white rot fungus.
Keywords: Carbon; Cloning, Molecular; Culture Media; Cytochrome P-450 Enzyme System; Cytochrome-B(5) Reductase; Cytochromes b5; DNA, Complementary; Environmental Pollutants; Escherichia coli; Fungal Proteins; Gene Duplication; Gene Expression; Genome, Fungal; Lignin; Molecular Sequence Data; NADPH-Ferrihemoprotein Reductase; Nitrogen; Oxidation-Reduction; Phanerochaete; Phylogeny; Polymerase Chain Reaction; Recombinant Proteins; Saccharomyces cerevisiae; Transcription, Genetic

Personal genome research : what should the participant be told? - McGuire, Amy L; Lupski, James R (Trends Genet, 2010)
Should the results of whole genome sequencing research be disclosed to participants, in particular when the results have uncertain or indeterminate phenotypic consequences? This controversial question is considered in light of one author's (J.L.) experience as a geneticist who recently had his own genome sequenced.
Keywords: Data Interpretation, Statistical; Genetic Variation; Genome, Human; Humans; Sequence Analysis, DNA; Truth Disclosure

Phosphorylation of the mutant K303R estrogen receptor alpha at serine 305 affects aromatase inhibitor sensitivity. - Barone, I; Iacopetta, D; Covington, K R; Cui, Y; Tsimelzon, A; Beyer, A; Andò, S; Fuqua, S A W (Oncogene, 2010)
We earlier identified a lysine to arginine transition at residue 303 (K303R) in estrogen receptor alpha (ERalpha) in invasive breast cancers, which confers resistance to the aromatase inhibitor (AI) anastrozole (Ana) when expressed in MCF-7 breast cancer cells. Here, we show that AI resistance arises through an enhanced cross talk of the insulin-like growth factor receptor-1 (IGF-1R)/insulin receptor substrate (IRS)-1/Akt pathway with ERalpha, and the serine (S) residue 305 adjacent to the K303R mutation has a key function in mediating this cross talk. The ERalpha S305 residue is an important site that modifies response to tamoxifen; thus, we questioned whether this site could also influence AI response. We generated stable transfectants-expressing wild-type, K303R ERalpha or a double K303R/S305A mutant receptor, and found that the AI-resistant phenotype associated with expression of the K303R mutation was dependent on activation of S305 within the receptor. Ana significantly reduced growth in K303R/S305A-expressing cells. Preventing S305 phosphorylation with a blocking peptide inhibited IGF-1R/IRS-1/Akt activation and also restored AI sensitivity. Our data suggest that the K303R mutation and the S305 ERalpha residue may be a novel determinant of AI response in breast cancer, and blockade of S305 phosphorylation represents a new therapeutic strategy for treating tumors resistant to hormone therapy.
Keywords: Aromatase Inhibitors; Breast Neoplasms; Cell Line, Tumor; Drug Resistance, Neoplasm; Estrogen Receptor alpha; Female; Humans; Insulin Receptor Substrate Proteins; Mutation; Phosphorylation; Proto-Oncogene Proteins c-akt; Receptor Cross-Talk; Receptor, IGF Type 1; Serine

Pretranscriptional regulation of Tgf-beta1 by PI polyamide prevents scarring and accelerates wound healing of the cornea after exposure to alkali. - Chen, Min; Matsuda, Hiroyuki; Wang, Linghua; Watanabe, Takayoshi; Kimura, Makoto T; Igarashi, Jun; Wang, Xiaofei; Sakimoto, Tohru; Fukuda, Noboru; Sawa, Mitsuru; Nagase, Hiroki (Mol Ther, 2010)
Corneal alkali burns are a serious clinical problem that often leads to permanent visual impairment. In this process, transforming growth factor (Tgf)-beta1 is upregulated and involved in the response to corneal injury and the process of corneal stromal scarring. To develop an efficient compound to inhibit Tgf-beta1 in the cornea, we designed GB1201, a pyrrole-imidazole (PI) polyamide targeting rat Tgf-beta1 gene promoter to the activator protein-1 (AP-1) binding site. GB1201 showed a high binding affinity to the target DNA sequence in the gel mobility shift and Biacore assays. GB1201 significantly inhibited the rat Tgf-beta1 gene promoter activity in HEK (human embryonic kidney) 293 cells in a concentration-dependent manner. Topically administrated GB1201 was distributed immediately to the nuclei of all cell layers of the cornea and remained for 24 hours. A corneal alkali burn model in rats was used to evaluate the therapeutic efficacy of GB1201. GB1201 suppressed the upregulation of Tgf-beta1 in the burned cornea, both in the mRNA and protein levels. Moreover, daily treatment with GB1201 for a week significantly improved the corneal tissue wound healing, reduced corneal stromal scarring, and prevented corneal haze formation. Our data suggest that PI polyamide may open new opportunities for therapeutic intervention in the treatment of chemically burned corneas.
Keywords: Animals; Binding Sites; Cicatrix; Cornea; Dose-Response Relationship, Drug; Gene Expression Regulation; Humans; Imidazoles; Nylons; Promoter Regions, Genetic; Pyrroles; Rats; RNA, Messenger; Transforming Growth Factor beta1; Wound Healing

Rapid identification of heterozygous mutations in Drosophila melanogaster using genomic capture sequencing. - Wang, Hui; Chattopadhyay, Abanti; Li, Zhe; Daines, Bryce; Li, Yumei; Gao, Chunxu; Gibbs, Richard; Zhang, Kun; Chen, Rui (Genome Res, 2010)
One of the key advantages of using Drosophila melanogaster as a genetic model organism is the ability to conduct saturation mutagenesis screens to identify genes and pathways underlying a given phenotype. Despite the large number of genetic tools developed to facilitate downstream cloning of mutations obtained from such screens, the current procedure remains labor intensive, time consuming, and costly. To address this issue, we designed an efficient strategy for rapid identification of heterozygous mutations in the fly genome by combining rough genetic mapping, targeted DNA capture, and second generation sequencing technology. We first tested this method on heterozygous flies carrying either a previously characterized dac(5) or sens(E2) mutation. Targeted amplification of genomic regions near these two loci was used to enrich DNA for sequencing, and both point mutations were successfully identified. When this method was applied to uncharacterized twr mutant flies, the underlying mutation was identified as a single-base mutation in the gene Spase18-21. This targeted-genome-sequencing method reduces time and effort required for mutation cloning by up to 80% compared with the current approach and lowers the cost to <$1000 for each mutant. Introduction of this and other sequencing-based methods for mutation cloning will enable broader usage of forward genetics screens and have significant impacts in the field of model organisms such as Drosophila.
Keywords: Animals; Animals, Genetically Modified; Base Sequence; Cost-Benefit Analysis; DNA Mutational Analysis; Drosophila melanogaster; Genetic Carrier Screening; Genome, Insect; Heterozygote; Models, Biological; Molecular Sequence Data; Point Mutation; Sequence Homology, Nucleic Acid; Time Factors

Risk of type 2 diabetes and obesity is differentially associated with variation in FTO in whites and African-Americans in the ARIC study. - Bressler, Jan; Kao, W H Linda; Pankow, James S; Boerwinkle, Eric (PLoS One, 2010)
Single nucleotide polymorphisms (SNPs) in the fat mass and obesity associated (FTO) gene are associated with body mass index (BMI) in populations of European descent. The FTO rs9939609 variant, first detected in a genome-wide association study of diabetes, conferred an increased disease risk that was abolished after adjustment for BMI, suggesting that the association may be due to variation in adiposity. The relationship between diabetes, four previously identified FTO polymorphisms that span a 19.6-kb genomic region, and obesity was therefore evaluated in the biracial population-based Atherosclerosis Risk in Communities Study with the goal of further refining the association by comparing results between the two ethnic groups. The prevalence of diabetes and obesity (BMI > or = 30 kg/m(2)) was established at baseline, and diabetes was determined by either self-report, a fasting glucose level > or = 126 mg/dL, or non-fasting glucose > or = 200 mg/dL. There were 1,004 diabetes cases and 10,038 non-cases in whites, and 670 cases and 2,780 non-cases in African-Americans. Differences in mean BMI were assessed by a general linear model, and multivariable logistic regression was used to predict the risk of diabetes and obesity. For white participants, the FTO rs9939609 A allele was associated with an increased risk of diabetes (odds ratio (OR) = 1.19, p<0.001) and obesity (OR = 1.22, p<0.001) under an additive genetic model that was similar for all of the SNPs analyzed. In African-Americans, only the rs1421085 C allele was a determinant of obesity risk (OR = 1.17, p = 0.05), but was found to be protective against diabetes (OR = 0.79, p = 0.03). Adjustment for BMI did not eliminate any of the observed associations with diabetes. Significant statistical interaction between race and the FTO variants suggests that the effect on diabetes susceptibility may be context dependent.
Keywords: Alleles; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Atherosclerosis; Black or African American; Body Mass Index; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins; Quantitative Trait, Heritable; White People

Source identification in two criminal cases using phylogenetic analysis of HIV-1 DNA sequences. - Scaduto, Diane I; Brown, Jeremy M; Haaland, Wade C; Zwickl, Derrick J; Hillis, David M; Metzker, Michael L (Proc Natl Acad Sci U S A, 2010)
Phylogenetic analysis has been widely used to test the a priori hypothesis of epidemiological clustering in suspected transmission chains of HIV-1. Among studies showing strong support for relatedness between HIV samples obtained from infected individuals, evidence for the direction of transmission between epidemiologically related pairs has been lacking. During transmission of HIV, a genetic bottleneck occurs, resulting in the paraphyly of source viruses with respect to those of the recipient. This paraphyly establishes the direction of transmission, from which the source can then be inferred. Here, we present methods and results from two criminal cases, State of Washington v Anthony Eugene Whitfield, case number 04-1-0617-5 (Superior Court of the State of Washington, Thurston County, 2004) and State of Texas v Philippe Padieu, case numbers 219-82276-07, 219-82277-07, 219-82278-07, 219-82279-07, 219-82280-07, and 219-82705-07 (219th Judicial District Court, Collin County, TX, 2009), which provided evidence that direction can be established from blinded case samples. The observed paraphyly from each case study led to the identification of an inferred source (i.e., index case), whose identity was revealed at trial to be that of the defendant.
Keywords: Criminal Law; Databases, Genetic; DNA, Viral; Forensic Genetics; HIV Infections; HIV-1; Humans; Molecular Sequence Data; Phylogeny; Sequence Analysis, DNA; Texas; Washington

A systematic approach to identify functional motifs within vertebrate developmental enhancers. - Li, Qiang; Ritter, Deborah; Yang, Nan; Dong, Zhiqiang; Li, Hao; Chuang, Jeffrey H; Guo, Su (Dev Biol, 2010)
Uncovering the cis-regulatory logic of developmental enhancers is critical to understanding the role of non-coding DNA in development. However, it is cumbersome to identify functional motifs within enhancers, and thus few vertebrate enhancers have their core functional motifs revealed. Here we report a combined experimental and computational approach for discovering regulatory motifs in developmental enhancers. Making use of the zebrafish gene expression database, we computationally identified conserved non-coding elements (CNEs) likely to have a desired tissue-specificity based on the expression of nearby genes. Through a high throughput and robust enhancer assay, we tested the activity of approximately 100 such CNEs and efficiently uncovered developmental enhancers with desired spatial and temporal expression patterns in the zebrafish brain. Application of de novo motif prediction algorithms on a group of forebrain enhancers identified five top-ranked motifs, all of which were experimentally validated as critical for forebrain enhancer activity. These results demonstrate a systematic approach to discover important regulatory motifs in vertebrate developmental enhancers. Moreover, this dataset provides a useful resource for further dissection of vertebrate brain development and function.
Keywords: Animals; Base Sequence; Brain; Computational Biology; Conserved Sequence; Databases, Genetic; DNA, Intergenic; Enhancer Elements, Genetic; Gene Expression Regulation, Developmental; Molecular Sequence Data; Mutation; Organ Specificity; Reproducibility of Results; Time Factors; Zebrafish

Taking DNA from the dead. - McGuire, Amy L; Majumder, Mary A; Halpern, Scott D; Swindell, J S; Yaeger, Laura V; Gibbs, Richard A; Wheeler, Thomas M (Nat Rev Genet, 2010)
Keywords: Cadaver; DNA; Ethics, Medical; Informed Consent

Whole exome capture in solution with 3 Gbp of data. - Bainbridge, Matthew N; Wang, Min; Burgess, Daniel L; Kovar, Christie; Rodesch, Matthew J; D'Ascenzo, Mark; Kitzman, Jacob; Wu, Yuan-Qing; Newsham, Irene; Richmond, Todd A; Jeddeloh, Jeffrey A; Muzny, Donna; et al. (Genome Biol, 2010)
We have developed a solution-based method for targeted DNA capture-sequencing that is directed to the complete human exome. Using this approach allows the discovery of greater than 95% of all expected heterozygous singe base variants, requires as little as 3 Gbp of raw sequence data and constitutes an effective tool for identifying rare coding alleles in large scale genomic studies.
Keywords: Base Pairing; Databases, Nucleic Acid; Exons; Gene Library; Haplotypes; Humans; Polymorphism, Single Nucleotide; Reproducibility of Results; Sequence Alignment; Sequence Analysis, DNA; Solutions

A-beta-subtype of ketosis-prone diabetes is not predominantly a monogenic diabetic syndrome. - Haaland, Wade C; Scaduto, Diane I; Maldonado, Mario R; Mansouri, Dena L; Nalini, Ramaswami; Iyer, Dinakar; Patel, Sanjeet; Guthikonda, Anu; Hampe, Christiane S; Balasubramanyam, Ashok; Metzker, Michael L (Diabetes Care, 2009)
OBJECTIVE: Ketosis-prone diabetes (KPD) is an emerging syndrome that encompasses several distinct phenotypic subgroups that share a predisposition to diabetic ketoacidosis. We investigated whether the A-beta- subgroup of KPD, characterized by complete insulin dependence, absent beta-cell functional reserve, lack of islet cell autoantibodies, and strong family history of type 2 diabetes, represents a monogenic form of diabetes. RESEARCH DESIGN AND METHODS: Over 8 years, 37 patients with an A-beta- phenotype were identified in our longitudinally followed cohort of KPD patients. Seven genes, including hepatocyte nuclear factor 4A (HNF4A), glucokinase (GCK), HNF1A, pancreas duodenal homeobox 1 (PDX1), HNF1B, neurogenic differentiation 1 (NEUROD1), and PAX4, were directly sequenced in all patients. Selected gene regions were also sequenced in healthy, unrelated ethnically matched control subjects, consisting of 84 African American, 96 Caucasian, and 95 Hispanic subjects. RESULTS: The majority (70%) of the A-beta- KPD patients had no significant causal polymorphisms in either the proximal promoter or coding regions of the seven genes. The combination of six potentially significant low-frequency, heterozygous sequence variants in HNF-1 alpha (A174V or G574S), PDX1 (putative 5'-untranslated region CCAAT box, P33T, or P239Q), or PAX4 (R133W) were found in 27% (10/37) of patients, with one additional patient revealing two variants, PDX1 P33T and PAX4 R133W. The A174V variant has not been previously reported. CONCLUSIONS: Despite its well-circumscribed, robust, and distinctive phenotype of severe, nonautoimmune-mediated beta-cell dysfunction, A-beta- KPD is most likely not a predominantly monogenic diabetic syndrome. Several A-beta- KPD patients have low-frequency variants in HNF1A, PDX1, or PAX4 genes, which may be of functional significance in their pathophysiology.
Keywords: Adult; Autoantibodies; Basic Helix-Loop-Helix Transcription Factors; Diabetes Mellitus, Type 1; Diabetes Mellitus, Type 2; Female; Genetic Variation; Glucokinase; Glycated Hemoglobin; Hepatocyte Nuclear Factor 1-beta; Hepatocyte Nuclear Factor 4; Homeodomain Proteins; Humans; Insulin; Insulin-Secreting Cells; Islets of Langerhans; Male; Middle Aged; Paired Box Transcription Factors; Trans-Activators

Apoptosis, autophagy, accelerated senescence and reactive oxygen in the response of human breast tumor cells to adriamycin. - Di, Xu; Shiu, Robert P; Newsham, Irene F; Gewirtz, David A (Biochem Pharmacol, 2009)
Although the primary response to Adriamycin (doxorubicin) in p53 mutant MDA-MB231 and p53 null MCF-7/E6 breast tumor cells is apoptotic cell death, the residual surviving population appears to be in a state of senescence, based on cell morphology, beta galactosidase staining, induction of p21(waf1/cip1) and down regulation of cdc2/cdk1. Suppression of apoptosis in MDA-MB231 and MCF-7/E6 cells treated with Adriamycin using the broad spectrum caspase inhibitor, zvad-Fmk, results in substantial induction of autophagy. Overall sensitivity to Adriamycin, measured by clonogenic survival, is not altered in the cells undergoing autophagy, consistent with autophagy contributing to cell death in response to Adriamycin. The free radical scavengers, glutathione and N-acetyl cysteine attenuate the accelerated senescence response to Adriamycin in MCF-7 cells as well as in MDA-MB231 and MCF-7/E6 cells, but protect primarily the MCF-7 cells, indicating that reactive oxygen is unlikely to be directly responsible for Adriamycin toxicity in breast tumor cells. Expression of caspase 3 or induced expression of c-myc in MCF-7 cells fails to abrogate accelerated senescence induced by Adriamycin. Taken together, these studies suggest that accelerated senescence induced by Adriamycin is similar in cells with wild type p53 and in cells lacking functional p53 with regard to the upregulation of p21(waf1/cip1), down regulation of cdc2 and the involvement of reactive oxygen species. Furthermore, accelerated senescence, autophagy and apoptosis all appear to be effective in suppressing self-renewal capacity in breast tumor cells exposed to Adriamycin.
Keywords: Apoptosis; Autophagy; Breast Neoplasms; Cell Line, Tumor; Cellular Senescence; Doxorubicin; Humans; Reactive Oxygen Species

Basic principles and technologies for deciphering the genetic map of cancer. - Voidonikolas, Georgios; Kreml, Stephanie S; Chen, Changyi; Fisher, William E; Brunicardi, F Charles; Gibbs, Richard A; Gingras, Marie-Claude (World J Surg, 2009)
The progress achieved in the field of genomics in recent years is leading medicine to adopt a personalized model in which the knowledge of individual DNA alterations will allow a targeted approach to cancer. Using pancreatic cancer as a model, we discuss herein the fundamentals that need to be considered for the high throughput and global identification of mutations. These include patient-related issues, sample collection, DNA isolation, gene selection, primer design, and sequencing techniques. We also describe the possible applications of the discovery of DNA changes to the approach of this disease and cite preliminary efforts where the knowledge has been translated into the clinical or preclinical setting.
Keywords: Adenocarcinoma; DNA Fragmentation; Genes, Neoplasm; Genetic Techniques; Humans; Neoplasms; Nucleic Acid Amplification Techniques; Pancreatic Neoplasms; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins; Proto-Oncogene Proteins p21(ras); ras Proteins; Sequence Analysis, DNA

Carbohydrate intake modifies associations between ANGPTL4[E40K] genotype and HDL-cholesterol concentrations in White men from the Atherosclerosis Risk in Communities (ARIC) study. - Nettleton, Jennifer A; Volcik, Kelly A; Hoogeveen, Ron C; Boerwinkle, Eric (Atherosclerosis, 2009)
BACKGROUND: Common allelic variation in the angiopoietin-like 4 gene (ANGPTL4[E40K]) has been associated with low triglyceride (TG) and high HDL-C. OBJECTIVE: We examined whether dietary macronutrient intake modified associations between ANGPTL4[E40K] variation and TG and HDL-C in White men and women from the Atherosclerosis Risk in Communities study. DESIGN: Diet was assessed by food frequency questionnaire. Intake of fat (total fat [TF], saturated fat [SF], monounsaturated fat [MUFA], polyunsaturated fat [PUFA], and n-3 PUFA) and carbohydrate were expressed as percentage of total energy intake. ANGPTL4 A allele carriers (n=148 in men, 200 in women) were compared to non-carriers (n=3667 in men, 4496 in women). Interactions were tested separately in men and women, adjusting for study center, age, smoking, physical activity, BMI, and alcohol intake. RESULTS: ANGPTL4 A allele carriers had significantly greater HDL-C and lower TG than non-carriers (p<or=0.001). In all participants, carbohydrate intake was inversely associated with HDL-C and positively associated with TG, whereas TF, SF, and MUFA showed opposite associations with TG and HDL-C (p<0.001). These relations were uniform between sex-specific genotype groups, with one exception. In men, but not women, the inverse association between carbohydrate and HDL-C was stronger in A allele carriers (beta+/-S.E. -1.80+/-0.54) than non-carriers (beta+/-S.E. -0.54+/-0.11, p(interaction)=0.04 in men and 0.69 in women; p 3-way interaction=0.14). CONCLUSIONS: These data suggest that ANGPTL4 variation and relative contributions of dietary fat and carbohydrate influence TG and HDL-C concentrations. In men, ANGPTL4 variation and dietary carbohydrate may interactively influence HDL-C.
Keywords: Alleles; Angiopoietin-Like Protein 4; Angiopoietins; Atherosclerosis; Cholesterol; Cholesterol, HDL; Community Health Services; Diet; Female; Genetic Variation; Genotype; Humans; Male; Middle Aged; Nutritional Sciences; Risk; Sex Factors; Triglycerides; White People

The completion of the Mammalian Gene Collection (MGC). - Temple, Gary; Gerhard, Daniela S; Rasooly, Rebekah; Feingold, Elise A; Good, Peter J; Robinson, Cristen; Mandich, Allison; Derge, Jeffrey G; Lewis, Jeanne; Shoaf, Debonny; Collins, Francis S; Jang, Wonhee; et al. (Genome Res, 2009)
Since its start, the Mammalian Gene Collection (MGC) has sought to provide at least one full-protein-coding sequence cDNA clone for every human and mouse gene with a RefSeq transcript, and at least 6200 rat genes. The MGC cloning effort initially relied on random expressed sequence tag screening of cDNA libraries. Here, we summarize our recent progress using directed RT-PCR cloning and DNA synthesis. The MGC now contains clones with the entire protein-coding sequence for 92% of human and 89% of mouse genes with curated RefSeq (NM-accession) transcripts, and for 97% of human and 96% of mouse genes with curated RefSeq transcripts that have one or more PubMed publications, in addition to clones for more than 6300 rat genes. These high-quality MGC clones and their sequences are accessible without restriction to researchers worldwide.
Keywords: Animals; Cloning, Molecular; Computational Biology; DNA; DNA, Complementary; Gene Library; Genes; Humans; Mammals; Mice; National Institutes of Health (U.S.); Rats; Reverse Transcriptase Polymerase Chain Reaction; United States

Copy number variation of CCL3-like genes affects rate of progression to simian-AIDS in Rhesus Macaques (Macaca mulatta). - Degenhardt, Jeremiah D; de Candia, Paola; Chabot, Adrien; Schwartz, Stuart; Henderson, Les; Ling, Binhua; Hunter, Meredith; Jiang, Zhaoshi; Palermo, Robert E; Katze, Michael; Eichler, Evan E; Ventura, Mario; et al. (PLoS Genet, 2009)
Variation in genes underlying host immunity can lead to marked differences in susceptibility to HIV infection among humans. Despite heavy reliance on non-human primates as models for HIV/AIDS, little is known about which host factors are shared and which are unique to a given primate lineage. Here, we investigate whether copy number variation (CNV) at CCL3-like genes (CCL3L), a key genetic host factor for HIV/AIDS susceptibility and cell-mediated immune response in humans, is also a determinant of time until onset of simian-AIDS in rhesus macaques. Using a retrospective study of 57 rhesus macaques experimentally infected with SIVmac, we find that CCL3L CNV explains approximately 18% of the variance in time to simian-AIDS (p<0.001) with lower CCL3L copy number associating with more rapid disease course. We also find that CCL3L copy number varies significantly (p<10(-6)) among rhesus subpopulations, with Indian-origin macaques having, on average, half as many CCL3L gene copies as Chinese-origin macaques. Lastly, we confirm that CCL3L shows variable copy number in humans and chimpanzees and report on CCL3L CNV within and among three additional primate species. On the basis of our findings we suggest that (1) the difference in population level copy number may explain previously reported observations of longer post-infection survivorship of Chinese-origin rhesus macaques, (2) stratification by CCL3L copy number in rhesus SIV vaccine trials will increase power and reduce noise due to non-vaccine-related differences in survival, and (3) CCL3L CNV is an ancestral component of the primate immune response and, therefore, copy number variation has not been driven by HIV or SIV per se.
Keywords: Animals; Calibration; Chemokine CCL3; Disease Progression; DNA Primers; Gene Dosage; Genetics, Population; Immune System; Likelihood Functions; Macaca mulatta; Microsatellite Repeats; Models, Statistical; Proportional Hazards Models; Reverse Transcriptase Polymerase Chain Reaction; Simian Acquired Immunodeficiency Syndrome

Developing a tissue resource to characterize the genome of pancreatic cancer. - Voidonikolas, Georgios; Gingras, Marie-Claude; Hodges, Sally; McGuire, Amy L; Chen, Changyi; Gibbs, Richard A; Brunicardi, F Charles; Fisher, William E (World J Surg, 2009)
With recent advances in DNA sequencing technology, medicine is entering an era in which a personalized genomic approach to diagnosis and treatment of disease is feasible. However, discovering the role of altered DNA sequences in various disease states will be a challenging task. The genomic approach offers great promise for diseases, such as pancreatic cancer, in which the effect of current diagnostic and treatment modalities is disappointing. To facilitate the characterization of the genome of pancreatic cancer, high-quality and well-annotated tissue repositories are needed. This article summarizes the basic principles that guide the creation of such a repository, including sample processing and preservation techniques, sample size and composition, and collection of clinical data elements.
Keywords: Adenocarcinoma; Computational Biology; Confidentiality; Databases, Genetic; Genomics; Humans; Informed Consent; Organ Preservation Solutions; Pancreatic Neoplasms; Prevalence; Quality Control; Specimen Handling; Tissue Banks; United States

Endometriosis is associated with progesterone resistance in the baboon (Papio anubis) oviduct: evidence based on the localization of oviductal glycoprotein 1 (OVGP1). - Wang, Chaohua; Mavrogianis, Patricia A; Fazleabas, Asgerally T (Biol Reprod, 2009)
Endometriosis has been associated with a reduced response to progesterone in both the eutopic and ectopic endometrium. In this study we evaluated OVGP1 and steroid receptor expression in oviducts of baboons with endometriosis during the midsecretory phase and determined whether progesterone resistance associated with endometriosis also occurs in the oviduct. Oviducts obtained during the window of uterine receptivity (Day 10 postovulation [PO]) from animals with induced and spontaneous disease were compared to control animals during the proliferative stage and in the implantation window as well as animals treated with the progesterone receptor (PGR) antagonist ZK 137.299 (ZK). OVGP1 was significantly higher in animals with endometriosis compared with Day 10 PO controls and was similar to that seen in the late proliferative phase and in ZK-treated animals. Baboons with spontaneous endometriosis also showed a similar persistence of OVGP1, which was correlated with the maintenance of estrogen receptor 1 (ESR1) in the epithelial cells of animals with endometriosis. However, epithelial cell height and the percentage of ciliation were not affected by endometriosis. These data imply that the normal antagonism of progesterone on ESR and OVGP1, which results in their downregulation during the window of implantation, is absent in animals with endometriosis. This was confirmed further when the action of PGR was antagonized in animals without disease, which also resulted in the persistence of ESR1 and OVGP1. These studies suggest that an aberrant oviductal environment may be an additive factor that contributes to endometriosis-associated infertility.
Keywords: Animals; Drug Resistance; Endometriosis; Endometrium; Estrogen Receptor alpha; Fallopian Tubes; Female; Glycoproteins; Papio anubis; Peritoneal Diseases; Progesterone; Receptors, Progesterone; Tissue Distribution

Genome-wide identification of allelic expression in hypertensive rats. - Dmitrieva, Renata I; Hinojos, Cruz A; Grove, Megan L; Bell, Rebecca J; Boerwinkle, Eric; Fornage, Myriam; Doris, Peter A (Circ Cardiovasc Genet, 2009)
BACKGROUND: Identification of genes involved in complex cardiovascular disease traits has proven challenging. Inbred animal models can facilitate genetic studies of disease traits. The spontaneously hypertensive rat (SHR) is an inbred model of hypertension that exists in several closely related but genetically distinct lines. METHODS AND RESULTS: We used renal gene-expression profiling across 3 distinct SHR lines to identify genes that show different expression in SHR than in the genetically related normotensive control strain, Wistar-Kyoto. To ensure robust discovery of genes showing SHR-specific expression differences, we considered only those genes in which differential expression is replicated in multiple animals of each of multiple hypertensive rat lines at multiple time points during the ontogeny of hypertension. Mutation analysis was performed on the identified genes to uncover allelic variation. We identified those genes in which all SHR lines share a single allele of the gene when normotensive controls (Wistar-Kyoto) have fixed the alternative allele. We then identified which of the differentially expressed genes show expression that is controlled by the alleleic variation present in and around the gene. Allelic expression was demonstrated by observing the effect on gene expression of alleles inherited in the freely segregating F(2) progeny of a cross between SHR and Wistar-Kyoto animals. CONCLUSIONS: The result of these studies is the identification of several genes (Ptprj, Ela1, Dapk-2, and Gstt2) in which each of 4 SHR lines examined have fixed the same allele and in which each of 2 Wistar-Kyoto lines have a contrasting allele for which the inherited allele influences the level of gene expression. We further show that alleles of these genes lie in extensive haplotype blocks that have been inherited identical by descent in the hypertensive lines.
Keywords: Alleles; Animals; Blood Pressure; Disease Models, Animal; Female; Gene Expression Profiling; Genome-Wide Association Study; Humans; Hypertension; Kidney; Male; Pedigree; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR; Rats, Inbred WKY

Genomics. Genome project standards in a new era of sequencing. - Chain, P S G; Grafham, D V; Fulton, R S; Fitzgerald, M G; Hostetler, J; Muzny, D; Ali, J; Birren, B; Bruce, D C; Buhay, C; Cole, J R; Ding, Y; et al. (Science, 2009)
More detailed sequence standards that keep up with revolutionary sequencing technologies will aid the research community in evaluating data.
Keywords: Computational Biology; Databases, Nucleic Acid; Genome; Genomics; Sequence Analysis, DNA

High-quality genomic DNA extraction from formalin-fixed and paraffin-embedded samples deparaffinized using mineral oil. - Lin, Jianghai; Kennedy, Stephen H; Svarovsky, Therese; Rogers, Jeffrey; Kemnitz, Joseph W; Xu, Anlong; Zondervan, Krina T (Anal Biochem, 2009)
Extracting DNA from formalin-fixed and paraffin-embedded (FFPE) tissue remains a challenge, despite numerous attempts to develop a more effective method. Polymerase chain reaction (PCR) success rates with DNA extracted using current methods remain low. We extracted DNA from 140 long-term archived FFPE samples using a simple but effective deparaffinization method, removing the wax with mineral oil, and a commercially available DNA extraction kit. DNA quality was subsequently tested in a genotyping experiment with 14 microsatellite markers. High-quality DNA was obtained with a mean PCR success rate of 97% (range: 88-100%) across markers. The results suggested that DNA extracted using this novel method is likely to be suitable for genetic studies involving DNA fragments <200 bp.
Keywords: DNA; Fixatives; Formaldehyde; Mineral Oil; Paraffin Embedding; Polymerase Chain Reaction; Time Factors

High-throughput multiplex sequencing to discover copy number variants in Drosophila. - Daines, Bryce; Wang, Hui; Li, Yumei; Han, Yi; Gibbs, Richard; Chen, Rui (Genetics, 2009)
Copy number variation (CNV) contributes in phenotypically relevant ways to the genetic variability of many organisms. Cost-effective genomewide methods for identifying copy number variation are necessary to elucidate the contribution that these structural variants make to the genomes of model organisms. We have developed a novel approach for the identification of copy number variation by next generation sequencing. As a proof of concept our method has been applied to map the deletions of three Drosophila deficiency strains. We demonstrate that low sequence coverage is sufficient for identifying and mapping large deletions at kilobase resolution, suggesting that data generated from high-throughput sequencing experiments are sufficient for simultaneously analyzing many strains. Genomic DNA from two Drosophila deficiency stocks was barcoded and sequenced in multiplex, and the breakpoints associated with each deletion were successfully identified. The approach we describe is immediately applicable to the systematic exploration of copy number variation in model organisms and humans.
Keywords: Animals; DNA Copy Number Variations; Drosophila melanogaster; Genome, Insect; Methods; Sequence Analysis, DNA; Sequence Deletion

Involvement of SSRP1 in latent replication of Kaposi's sarcoma-associated herpesvirus. - Hu, Jianhong; Liu, Eugene; Renne, Rolf (J Virol, 2009)
Kaposi's sarcoma-associated herpesvirus (also named human herpesvirus 8) is a gamma-herpesvirus that undergoes both lytic and latent infection. During latent infection, two viral elements are required: latency-associated nuclear antigen (LANA), which functions as an origin binding protein, and the latent origin, which resides within the terminal repeats (TRs) of the viral genome. Previously, we identified two cis-elements within the TRs which are required for latent DNA replication: two LANA binding sites (LBS1 and LBS2 [LBS1/2]) and a GC-rich replication element (RE) upstream of LBS1/2. To further characterize the RE, we constructed a 71-bp minimal replicon (MR) and performed a detailed mutational analysis. Our data indicate that the first 8 nucleotides within the RE are critical for replication. Moreover, both the position and the distance between the RE and LBS1/2 can affect origin replication activity, suggesting that the RE may function as a loading pad for cellular proteins involved in replication. Using biotinylated DNA fragments of wild-type or mutant MRs as probes, we identified 30 proteins that preferentially bind to the origin. Among these proteins, structure-specific recognition protein 1 (SSRP1), a subunit of the FACT complex, and telomeric repeat binding factor 2 (TRF2) formed complexes with LANA at the MR region. Furthermore, the small interfering RNA-based knockdown of SSRP1, but not the dominant-negative-based knockdown of TRF2, significantly decreased the efficiency of LANA-dependent DNA replication. These results indicate that SSRP1 is a novel cellular protein involved in LANA-dependent DNA replication.
Keywords: Animals; Antigens, Viral; Binding Sites; Cell Line; DNA Replication; DNA, Viral; DNA-Binding Proteins; Genome, Viral; Herpesviridae Infections; Herpesvirus 8, Human; High Mobility Group Proteins; Humans; Molecular Sequence Data; Nuclear Proteins; RNA, Small Interfering; Terminal Repeat Sequences; Transcriptional Elongation Factors; Virus Latency; Virus Replication

Localization of multiple pleiotropic genes for lipoprotein metabolism in baboons. - Rainwater, David L; Cox, Laura A; Rogers, Jeffrey; VandeBerg, John L; Mahaney, Michael C (J Lipid Res, 2009)
We employed a novel approach to identify the key loci that harbor genes influencing lipoprotein metabolism in approximately 2,000 pedigreed baboons fed various diets differing in levels of fat and cholesterol. In this study, 126 overlapping traits related to both LDL and HDL metabolism were normalized and subjected to genome-wide linkage screening. As was expected, the traits were highly, but not completely, correlated. We exploited the information in these correlated traits by focusing on those genomic regions harboring quantitative trait loci (QTL) for multiple traits, reasoning that the more influential genes would impact a larger number of traits. This study identified five major QTL clusters (each with at least two significant logarithm of the odds scores >4.7), two of which had not been previously reported in baboons. One of these mapped to the baboon ortholog of human chromosome 1p32-p34 and influenced concentrations of LDL-cholesterol on Basal and high-fat, low-cholesterol diets. The other novel QTL cluster mapped to the baboon ortholog of human chromosome 12q13.13-q14.1 and influenced LDL size properties on high-fat, low-cholesterol and high-fat, high-cholesterol, but not Basal, diets. Confirming the value of this approach, three of the QTL clusters replicated published linkage findings for the same or similar traits.
Keywords: Animals; Chromosomes, Mammalian; Diet; Gene Expression Regulation; Genetic Linkage; Genotype; Humans; Lipid Metabolism; Lipids; Lipoproteins; Lod Score; Multigene Family; Papio; Quantitative Trait Loci

Low frequency of MLL3 mutations in colorectal carcinoma. - Vakoc, Christopher R; Wen, Yu-Ye; Gibbs, Richard A; Johnstone, Cameron N; Rustgi, Anil K; Blobel, Gerd A (Cancer Genet Cytogenet, 2009)
Keywords: Carcinoma; Case-Control Studies; Colorectal Neoplasms; DNA-Binding Proteins; Gene Frequency; Genetic Testing; Humans; Mutation; Polymorphism, Single Nucleotide

Metagenomic pyrosequencing and microbial identification. - Petrosino, Joseph F; Highlander, Sarah; Luna, Ruth Ann; Gibbs, Richard A; Versalovic, James (Clin Chem, 2009)
BACKGROUND: The Human Microbiome Project has ushered in a new era for human metagenomics and high-throughput next-generation sequencing strategies. CONTENT: This review describes evolving strategies in metagenomics, with a special emphasis on the core technology of DNA pyrosequencing. The challenges of microbial identification in the context of microbial populations are discussed. The development of next-generation pyrosequencing strategies and the technical hurdles confronting these methodologies are addressed. Bioinformatics-related topics include taxonomic systems, sequence databases, sequence-alignment tools, and classifiers. DNA sequencing based on 16S rRNA genes or entire genomes is summarized with respect to potential pyrosequencing applications. SUMMARY: Both the approach of 16S rDNA amplicon sequencing and the whole-genome sequencing approach may be useful for human metagenomics, and numerous bioinformatics tools are being deployed to tackle such vast amounts of microbiological sequence diversity. Metagenomics, or genetic studies of microbial communities, may ultimately contribute to a more comprehensive understanding of human health, disease susceptibilities, and the pathophysiology of infectious and immune-mediated diseases.
Keywords: Computational Biology; DNA, Bacterial; Genomics; Humans; Metagenome; RNA, Ribosomal, 16S; Sequence Analysis, DNA

Microarray analysis of somatostatin receptor 5-regulated gene expression profiles in murine pancreas. - Patel, Sanjeet G; Zhou, Guisheng; Liu, Shi-He; Li, Min; Jeong, Jae-Wook; DeMayo, Francesco J; Marie-Claude Gingras; Richard A Gibbs; Fisher, William E; Brunicardi, F Charles (World J Surg, 2009)
BACKGROUND: We previously demonstrated that somatostatin receptor type 5 (SSTR5) gene ablation results in alterations in insulin secretion and glucose metabolism, accompanied by morphologic alterations in the islets of Langerhans. The underlying mechanism(s) by which SSTR5 exerts its cellular functions remain(s) unknown. We hypothesized that SSTR5 mediates the inhibitory effect of somatostatin (SST) on insulin secretion and islet proliferation by regulating a specific set of pancreatic genes. METHODS: To identify SSTR5-regulated pancreatic genes, gene expression microarray analysis was performed on the whole pancreas of 1- and 3-month-old wild-type (WT) and SSTR5 knockout (SSTR5-/-) male mice. Real-time RT-PCR and immunofluorescence were performed to validate selected differentially expressed genes. RESULTS: A set of 143 probes were identified to be differentially expressed in the pancreas of 1-month-old SSTR5-/- mice, 72 of which were downregulated and 71 upregulated. At 3 months of age, SSTR5 gene ablation resulted in downregulation of a set of 30 probes and upregulation of a set of 37 probes. Among these differentially expressed genes, there were 15 and 5 genes that were upregulated and downregulated, respectively, in mice at both 1 and 3 months of age. Three genes, PAP/INGAP, ANG, and TDE1, were selected to be validated by real-time RT-PCR and immunofluorescence. CONCLUSIONS: A specific set of genes linked to a wide range of cellular functions such as islet proliferation, apoptosis, angiogenesis, and tumorigenesis were either upregulated or downregulated in SSTR5-deficient male mice compared with their expression in wild-type mice. Therefore, these genes are potential SSTR5-regulated genes during normal pancreatic development and functional maintenance.
Keywords: Animals; Apoptosis; Cell Proliferation; Down-Regulation; Fluorescent Antibody Technique; Gene Expression Profiling; Islets of Langerhans; Male; Mice; Mice, Knockout; Neoplasm Proteins; Neovascularization, Pathologic; Oligonucleotide Array Sequence Analysis; Pancreas; Pancreatitis-Associated Proteins; Proteins; Receptors, Cell Surface; Receptors, Somatostatin; Reverse Transcriptase Polymerase Chain Reaction; Ribonuclease, Pancreatic; Up-Regulation

Mutation survey of known LCA genes and loci in the Saudi Arabian population. - Li, Yumei; Wang, Hui; Peng, Jianlan; Gibbs, Richard A; Lewis, Richard Alan; Lupski, James R; Mardon, Graeme; Chen, Rui (Invest Ophthalmol Vis Sci, 2009)
PURPOSE: The purpose of this study was to perform a comprehensive survey of all known Leber congenital amaurosis (LCA) genes and loci in a collection of 37 consanguineous LCA families from Saudi Arabia. METHODS: Direct PCR and sequencing were used to screen 13 known LCA genes (GUCY2D, CRX, RPE65, TULP1, AIPL1, CRB1, RPGRIP1, LRAT, RDH12, IMPDH1, CEP290, RD3, LCA5). In addition, families without mutations identified were further screened with STR markers around these 13 known LCA genes and two loci. RESULTS: Disease-causing mutations were identified in nine of the 37 families: five in TULP1, two in CRB1, one in RPE65, and one in GUCY2D. Mutations in known genes only accounted for 24% of the Saudi families--much less than what has been observed in the European population (65%). Phenotype-genotype analysis was carried out to investigate the LCA disease penetrance for all families whose mutations identified. All identified mutations were found to segregate perfectly with the disease phenotype. On the other hand, severity of the disease varies for different patients carrying the same mutation and even within the same family. Furthermore, based on homozygosity mapping with both STR and SNP markers, one family is likely to map to the LCA3 locus. CONCLUSIONS: These results underscore the importance of studying LCA disease families from different ethnic backgrounds to identify additional novel LCA disease genes. Furthermore, perfect segregation between mutation and disease indicates that LCA is fully penetrant. However, phenotypic variations among patients carrying the same mutation suggest that at least some of the variations in the clinical phenotype is due to modification from the genetic background, environment, or other factors.
Keywords: Blindness; Carrier Proteins; cis-trans-Isomerases; Consanguinity; DNA Mutational Analysis; Eye Proteins; Female; Genes; Genotype; Guanylate Cyclase; Humans; Male; Membrane Proteins; Microsatellite Repeats; Mutation; Nerve Tissue Proteins; Pedigree; Phenotype; Polymerase Chain Reaction; Receptors, Cell Surface; Retinal Degeneration; Saudi Arabia

Mutations in SPATA7 cause Leber congenital amaurosis and juvenile retinitis pigmentosa. - Wang, Hui; den Hollander, Anneke I; Moayedi, Yalda; Abulimiti, Abuduaini; Li, Yumei; Collin, Rob W J; Hoyng, Carel B; Lopez, Irma; Abboud, Emad B; Al-Rajhi, Ali A; Bray, Molly; Lewis, Richard Alan; et al. (Am J Hum Genet, 2009)
Leber congenital amaurosis (LCA) and juvenile retinitis pigmentosa (RP) are the most common hereditary causes of visual impairment in infants and children. Using homozygosity mapping, we narrowed down the critical region of the LCA3 locus to 3.8 Mb between markers D14S1022 and D14S1005. By direct Sanger sequencing of all genes within this region, we found a homozygous nonsense mutation in the SPATA7 gene in Saudi Arabian family KKESH-060. Three other loss-of-function mutations were subsequently discovered in patients with LCA or juvenile RP from distinct populations. Furthermore, we determined that Spata7 is expressed in the mature mouse retina. Our findings reveal another human visual-disease gene that causes LCA and juvenile RP.
Keywords: Animals; Child; Codon, Nonsense; DNA-Binding Proteins; Homozygote; Humans; Mice; Middle Aged; Pedigree; Retina; Retinal Diseases; Retinitis Pigmentosa

Personalized copy number and segmental duplication maps using next-generation sequencing. - Alkan, Can; Kidd, Jeffrey M; Marques-Bonet, Tomas; Aksay, Gozde; Antonacci, Francesca; Hormozdiari, Fereydoun; Kitzman, Jacob O; Baker, Carl; Malig, Maika; Mutlu, Onur; Sahinalp, S Cenk; Gibbs, Richard A; et al. (Nat Genet, 2009)
Despite their importance in gene innovation and phenotypic variation, duplicated regions have remained largely intractable owing to difficulties in accurately resolving their structure, copy number and sequence content. We present an algorithm (mrFAST) to comprehensively map next-generation sequence reads, which allows for the prediction of absolute copy-number variation of duplicated segments and genes. We examine three human genomes and experimentally validate genome-wide copy number differences. We estimate that, on average, 73-87 genes vary in copy number between any two individuals and find that these genic differences overwhelmingly correspond to segmental duplications (odds ratio = 135; P < 2.2 x 10(-16)). Our method can distinguish between different copies of highly identical genes, providing a more accurate assessment of gene content and insight into functional constraint without the limitations of array-based technology.
Keywords: Algorithms; Chromosome Mapping; DNA; Gene Dosage; Gene Duplication; Genome, Human; Genomic Library; Humans; Polymorphism, Genetic; Sequence Analysis, DNA

The prolonged effect of repeated maternal glucocorticoid exposure on the maternal and fetal leptin/insulin-like growth factor axis in Papio species. - Schlabritz-Loutsevitch, Natalia E; Lopez-Alvarenga, Juan C; Comuzzie, Anthony G; Miller, Myrna M; Ford, Stephen P; Li, Cun; Hubbard, Gene B; Ferry, Robert J; Nathanielsz, Peter W (Reprod Sci, 2009)
BACKGROUND: Maternal obesity represents a risk factor for pregnancy-related complications. Glucocorticoids are known to promote obesity in adults. METHODS: We evaluated maternal and fetal metabolic changes during and after 3 weekly courses of betamethasone administered to pregnant baboons (Papio subspecies) at doses equivalent to those given to pregnant women. RESULTS: Betamethasone administration during the second half of pregnancy increased maternal weight but neither maternal food intake nor fetal weight, as assessed at the end of gestation. Betamethasone increased maternal serum glucose concentration, the ratio of insulin-like growth factor-I and insulin-like growth factor binding protein-3, and serum leptin during treatment (normalized by 17, 35, and 45 days posttreatment, respectively, for each parameter). Maternal and fetal serum leptin concentrations did not differ between groups at the end of gestation. CONCLUSION: Prolonged maternal hyperleptinemia caused by betamethasone administration in the second half of gestation did not change fetal metabolic parameters measured and placental leptin distribution at the end of gestation.
Keywords: Animals; Betamethasone; Blood Glucose; Body Weight; Cesarean Section; Cholesterol; Drug Administration Schedule; Eating; Female; Fetal Blood; Fetal Weight; Fetus; Gestational Age; Glucocorticoids; Hydrocortisone; Injections, Intramuscular; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Insulin-Like Growth Factor II; Leptin; Maternal-Fetal Exchange; Papio cynocephalus; Placenta; Pregnancy

Replication of long-bone length QTL in the F9-F10 LG,SM advanced intercross. - Norgard, Elizabeth A; Jarvis, Joseph P; Roseman, Charles C; Maxwell, Taylor J; Kenney-Hunt, Jane P; Samocha, Kaitlin E; Pletscher, L Susan; Wang, Bing; Fawcett, Gloria L; Leatherwood, Christopher J; Wolf, Jason B; Cheverud, James M (Mamm Genome, 2009)
Quantitative trait locus (QTL) mapping techniques are frequently used to identify genomic regions associated with variation in phenotypes of interest. However, the F(2) intercross and congenic strain populations usually employed have limited genetic resolution resulting in relatively large confidence intervals that greatly inhibit functional confirmation of statistical results. Here we use the increased resolution of the combined F(9) and F(10) generations (n = 1455) of the LG,SM advanced intercross to fine-map previously identified QTL associated with the lengths of the humerus, ulna, femur, and tibia. We detected 81 QTL affecting long-bone lengths. Of these, 49 were previously identified in the combined F(2)-F(3) population of this intercross, while 32 represent novel contributors to trait variance. Pleiotropy analysis suggests that most QTL affect three to four long bones or serially homologous limb segments. We also identified 72 epistatic interactions involving 38 QTL and 88 novel regions. This analysis shows that using later generations of an advanced intercross greatly facilitates fine-mapping of confidence intervals, resolving three F(2)-F(3) QTL into multiple linked loci and narrowing confidence intervals of other loci, as well as allowing identification of additional QTL. Further characterization of the biological bases of these QTL will help provide a better understanding of the genetics of small variations in long-bone length.
Keywords: Animals; Bone and Bones; Crosses, Genetic; DNA Replication; Female; Hybridization, Genetic; Male; Mice; Organ Size; Quantitative Trait Loci

A sequence-level map of chromosomal breakpoints in the MCF-7 breast cancer cell line yields insights into the evolution of a cancer genome. - Hampton, Oliver A; Den Hollander, Petra; Miller, Christopher A; Delgado, David A; Li, Jian; Coarfa, Cristian; Harris, Ronald A; Richards, Stephen; Scherer, Steven E; Muzny, Donna M; Gibbs, Richard A; Lee, Adrian V; et al. (Genome Res, 2009)
By applying a method that combines end-sequence profiling and massively parallel sequencing, we obtained a sequence-level map of chromosomal aberrations in the genome of the MCF-7 breast cancer cell line. A total of 157 distinct somatic breakpoints of two distinct types, dispersed and clustered, were identified. A total of 89 breakpoints are evenly dispersed across the genome. A majority of dispersed breakpoints are in regions of low copy repeats (LCRs), indicating a possible role for LCRs in chromosome breakage. The remaining 68 breakpoints form four distinct clusters of closely spaced breakpoints that coincide with the four highly amplified regions in MCF-7 detected by array CGH located in the 1p13.1-p21.1, 3p14.1-p14.2, 17q22-q24.3, and 20q12-q13.33 chromosomal cytobands. The clustered breakpoints are not significantly associated with LCRs. Sequences flanking most (95%) breakpoint junctions are consistent with double-stranded DNA break repair by nonhomologous end-joining or template switching. A total of 79 known or predicted genes are involved in rearrangement events, including 10 fusions of coding exons from different genes and 77 other rearrangements. Four fusions result in novel expressed chimeric mRNA transcripts. One of the four expressed fusion products (RAD51C-ATXN7) and one gene truncation (BRIP1 or BACH1) involve genes coding for members of protein complexes responsible for homology-driven repair of double-stranded DNA breaks. Another one of the four expressed fusion products (ARFGEF2-SULF2) involves SULF2, a regulator of cell growth and angiogenesis. We show that knock-down of SULF2 in cell lines causes tumorigenic phenotypes, including increased proliferation, enhanced survival, and increased anchorage-independent growth.
Keywords: Breast Neoplasms; Cell Line, Tumor; Chromosome Breakage; Chromosome Mapping; Chromosomes, Artificial, Bacterial; DNA Repair; Evolution, Molecular; Gene Expression Profiling; Genes, Neoplasm; Genome, Human; Humans; Locus Control Region; Models, Biological; Mutant Chimeric Proteins; Sequence Analysis, DNA

A simple and evolutional approach proven to recanalise the nasolacrimal duct obstruction. - Chen, D; Ge, J; Wang, L; Gao, Q; Ma, P; Li, N; Li, D-Q; Wang, Z (Br J Ophthalmol, 2009)
AIM: To evaluate a new approach of recanalisation of nasolacrimal duct obstruction (RC-NLDO) in the treatment of the nasolacrimal duct obstruction (NLDO) and chronic dacryocystitis. METHODS: 583 patients with 641 eyes suffering from NLDO and chronic dacryocystitis were enrolled in this study. The RC-NLDO was performed in 506 eyes, with 135 eyes undergoing external dacryocystorhinostomy (EX-DCR) as controls. Patient follow-up for 54 months was evaluated by symptoms, dye disappearance test, lacrimal irrigation and digital subtraction dacryocystogram. The RC-NLDO was also performed in 12 rhesus monkeys for histopathological examination. RESULTS: The clinical success rates were 93.1% in 506 cases of RC-NLDO and 91.11% in 135 cases of EX-DCR. The success rates for second surgery were achieved in 85.19% on RC-NLDO and 40.0% on EX-DCR. No major intra- or postoperative complications were observed in the RC-NLDO group. The mean operative duration was 12.5 min for RC-NLDO and 40.3 min for EX-DCR (p<0.001). A pathological study in rhesus monkeys demonstrated that the RC-NLDO wounded epithelium in nasolacrimal duct healed completely within 1 month without granulation tissue formation. CONCLUSION: The findings demonstrate that the RC-NLDO is a simple and effective approach proven to recanalise the obstructed nasolacrimal duct with a comparable success rate to EX-DCR.
Keywords: Animals; Catheterization; Dacryocystorhinostomy; Equipment Design; Female; Humans; Lacrimal Duct Obstruction; Macaca mulatta; Male; Middle Aged; Nasolacrimal Duct; Postoperative Care; Wound Healing

Spontaneous mutagenesis is elevated in protease-defective cells. - Al Mamun, Abu Amar M; Humayun, M Zafri (Mol Microbiol, 2009)
As a first step towards describing the role of proteolysis in maintaining genomic integrity, we have determined the effect of the loss of ClpXP, a major energy-dependent cytoplasmic protease that degrades truncated proteins as well as a number of regulatory proteins, on spontaneous mutagenesis. In a rifampicin-sensitive to rifampicin-resistance assay that detects base substitution mutations in the essential rpoB gene, there is a modest, but appreciable increase in mutagenesis in Delta(clpP-clpX) cells relative to wild-type cells. A colony papillation analysis using a set of lacZ strains revealed that genetic -1 frameshift mutations are strongly elevated in Clp-defective cells. A quantitative analysis using a valine-sensitive to valine-resistance assay that detects frameshift mutations showed that mutagenesis is elevated 50-fold in Clp-defective cells. Elevated frameshift mutagenesis observed in Clp-deficient cells is essentially abolished in lexA1[Ind(-)] (SOS-uninducible) cells, and in cells deleted for the SOS gene dinB, which codes for DNA polymerase IV. In contrast, mutagenesis is unaffected or stimulated in cells deleted for umuC or umuD, which code for critical components of DNA polymerase V. Loss of rpoS, which codes for a stress-response sigma factor known to upregulate dinB expression in stationary phase, does not affect mutagenesis. We propose that elevated DinB expression, as well as stabilization of UmuD/UmuD' heterodimers in Delta(clpP-clpX) cells, contributes to elevated mutagenesis. These findings suggest that in normal cells, Clp-mediated proteolysis plays an important role in preventing gratuitous mutagenesis.
Keywords: DNA Polymerase beta; DNA-Directed DNA Polymerase; Endopeptidase Clp; Escherichia coli; Escherichia coli Proteins; Frameshift Mutation; Genes, Bacterial; Mutagenesis

Unlocking the bovine genome. - Tellam, Ross L; Lemay, Danielle G; Van Tassell, Curtis P; Lewin, Harris A; Worley, Kim C; Elsik, Christine G (BMC Genomics, 2009)
The draft genome sequence of cattle (Bos taurus) has now been analyzed by the Bovine Genome Sequencing and Analysis Consortium and the Bovine HapMap Consortium, which together represent an extensive collaboration involving more than 300 scientists from 25 different countries.
Keywords: Animals; Cattle; Chromosome Mapping; Chromosomes, Mammalian; Databases, Genetic; Evolution, Molecular; Genome; Internet; Sequence Analysis, DNA

Use of wrapper algorithms coupled with a random forests classifier for variable selection in large-scale genomic association studies. - Rodin, Andrei S; Litvinenko, Anatoliy; Klos, Kathy; Morrison, Alanna C; Woodage, Trevor; Coresh, Josef; Boerwinkle, Eric (J Comput Biol, 2009)
Modern large-scale genetic association studies generate increasingly high-dimensional datasets. Therefore, some variable selection procedure should be performed before the application of traditional data analysis methods, for reasons of both computational efficiency and problems related to overfitting. We describe here a "wrapper" strategy (SIZEFIT) for variable selection that uses a Random Forests classifier, coupled with various local search/optimization algorithms. We apply it to a large dataset consisting of 2,425 African-American and non-Hispanic white individuals genotyped for 4,869 single-nucleotide polymorphisms (SNPs) in a coronary heart disease (CHD) case-cohort association study (Atherosclerosis Risk in Communities), using incident CHD and plasma low-density lipoprotein (LDL) cholesterol levels as the dependent variables. We show that most SNPs can be safely removed from the dataset without compromising the predictive (classification) accuracy, with only a small number of SNPs (sometimes less than 100) containing any predictive signal. A statistical (SUMSTAT) approach is also applied to the dataset for comparison purposes. We describe a novel method for refining the subset of signal-containing SNPs (FIXFIT), based on an Extremal Optimization algorithm. Finally, we compare the top SNP rankings obtained by different methods and devise practical guidelines for researchers trying to generate a compact subset of predictive SNPs from genome-wide association datasets. Interestingly, there is a significant amount of overlap between seemingly very heterogeneous rankings. We conclude by constructing compact optimal predictive SNP subsets for CHD (less than 150 SNPs) and LDL (less than 300 SNPs) phenotypes, and by comparing various rankings for two well-known positive control SNPs for LDL in the apolipoprotein E gene.
Keywords: Algorithms; Apolipoproteins E; Atherosclerosis; Black or African American; Databases, Genetic; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Models, Genetic

Acquisition of uncharacterized sequences from Candidatus liberibacter, an unculturable bacterium, using an improved genomic walking method. - Lin, Hong; Harshavardhan Doddapaneni; Bai, Xianjing; Yao, Jiqiang; Zhao, Xiaolong; Civerolo, Edwin L (Mol Cell Probes, 2008)
An effective PCR-based genomic walking approach is described to discover previously unknown flanking genomic DNA sequences from Candidatus Liberibacter asiaticus, an unculturable, phloem-limited bacterium. Using this technique, 8564bp of new DNA sequences were obtained from three genomic loci; tufB-secE-nusG-rplKAJL-rpoBC gene cluster, omp gene (outer membrane protein, Omp) and 16/23S rRNA gene in Ca. L. asiaticus. These, together with publicly available Ca. Liberibacter sequences, are clustered into five contigs and two singlets representing 24,477 non-redundant base pairs. BLAST annotation predicts 12 full-length genes, two partial genes and one pseudogene among these sequences. The sequences obtained in this study provide new genome information about Ca. Liberibacter that will facilitate development of new genome-based detection tools. The technique described here can also be employed to acquire new genomic information for other unculturable or fastidious organisms for which available sequences are limited or for filling sequence gaps between known flanking genomic DNA sequences.
Keywords: Bacterial Outer Membrane Proteins; Base Sequence; Chromosome Walking; Citrus; DNA, Ribosomal; Genes, Bacterial; Genome, Bacterial; Multigene Family; Polymerase Chain Reaction; Reproducibility of Results; Rhizobiaceae

Analysis of transcriptome data in the red flour beetle, Tribolium castaneum. - Park, Yoonseong; Aikins, Jamie; Wang, L J; Beeman, Richard W; Oppert, Brenda; Lord, Jeffrey C; Brown, Susan J; Lorenzen, Marcé D; Richards, Stephen; Weinstock, George M; Gibbs, Richard A (Insect Biochem Mol Biol, 2008)
The whole genome sequence of Tribolium castaneum, a worldwide coleopteran pest of stored products, has recently been determined. In order to facilitate accurate annotation and detailed functional analysis of this genome, we have compiled and analyzed all available expressed sequence tag (EST) data. The raw data consist of 61,228 ESTs, including 10,704 obtained from NCBI and an additional 50,524 derived from 32,544 clones generated in our laboratories. These sequences were amassed from cDNA libraries representing six different tissues or stages, namely: whole embryos, whole larvae, larval hindguts and Malpighian tubules, larval fat bodies and carcasses, adult ovaries, and adult heads. Assembly of the 61,228 sequences collapsed into 12,269 clusters (groups of overlapping ESTs representing single genes), of which 10,134 mapped onto 6,463 (39%) of the 16,422 GLEAN gene models (i.e. official Tribolium gene list). Approximately 1,600 clusters (13% of the total) lack corresponding GLEAN models, despite high matches to the genome, suggesting that a considerable number of transcribed sequences were missed by the gene prediction programs or were removed by GLEAN. We conservatively estimate that the current EST set represents more than 7,500 transcription units.
Keywords: Animals; Databases, Nucleic Acid; Expressed Sequence Tags; Gene Expression Profiling; Gene Library; Tribolium

cneViewer: a database of conserved non-coding elements for studies of tissue-specific gene regulation. - Persampieri, Jason; Ritter, Deborah I; Lees, Daniel; Lehoczky, Jessica; Li, Qiang; Guo, Su; Chuang, Jeffrey H (Bioinformatics, 2008)
There are thousands of strongly conserved non-coding elements (CNEs) in vertebrate genomes, and their functions remain largely unknown. However, without biologically relevant criteria for prioritizing them, selecting a particular CNE sequences to study can be haphazard. To address this problem, we present cneViewer-a database and webtool that systematizes information on conserved non-coding DNA elements in zebrafish. A key feature here is the ability to search for CNEs that may be relevant to tissue-specific gene regulation, based on known developmental expression patterns of nearby genes. cneViewer provides this and other organizing features that significantly facilitate experimental design and CNE analysis.
Keywords: Animals; Base Sequence; Computational Biology; Conserved Sequence; Databases, Genetic; DNA; Gene Expression Regulation; Humans; Internet; Molecular Sequence Data; Regulatory Sequences, Nucleic Acid; Software; Zebrafish

Complete genome sequence of Treponema pallidum ssp. pallidum strain SS14 determined with oligonucleotide arrays. - Matejková, Petra; Strouhal, Michal; Smajs, David; Norris, Steven J; Palzkill, Timothy; Petrosino, Joseph F; Sodergren, Erica; Norton, Jason E; Singh, Jaz; Richmond, Todd A; Molla, Michael N; Albert, Thomas J; et al. (BMC Microbiol, 2008)
BACKGROUND: Syphilis spirochete Treponema pallidum ssp. pallidum remains the enigmatic pathogen, since no virulence factors have been identified and the pathogenesis of the disease is poorly understood. Increasing rates of new syphilis cases per year have been observed recently. RESULTS: The genome of the SS14 strain was sequenced to high accuracy by an oligonucleotide array strategy requiring hybridization to only three arrays (Comparative Genome Sequencing, CGS). Gaps in the resulting sequence were filled with targeted dideoxy-terminators (DDT) sequencing and the sequence was confirmed by whole genome fingerprinting (WGF). When compared to the Nichols strain, 327 single nucleotide substitutions (224 transitions, 103 transversions), 14 deletions, and 18 insertions were found. On the proteome level, the highest frequency of amino acid-altering substitution polymorphisms was in novel genes, while the lowest was in housekeeping genes, as expected by their evolutionary conservation. Evidence was also found for hypervariable regions and multiple regions showing intrastrain heterogeneity in the T. pallidum chromosome. CONCLUSION: The observed genetic changes do not have influence on the ability of Treponema pallidum to cause syphilitic infection, since both SS14 and Nichols are virulent in rabbit. However, this is the first assessment of the degree of variation between the two syphilis pathogens and paves the way for phylogenetic studies of this fascinating organism.
Keywords: Animals; Chromosome Mapping; DNA Fingerprinting; Genome, Bacterial; Humans; Molecular Sequence Data; Oligonucleotide Array Sequence Analysis; Open Reading Frames; Polymorphism, Single Nucleotide; Rabbits; Reproducibility of Results; Sequence Analysis, DNA; Syphilis; Treponema pallidum

Comprehensive genomic characterization defines human glioblastoma genes and core pathways. (Nature, 2008)
Human cancer cells typically harbour multiple chromosomal aberrations, nucleotide substitutions and epigenetic modifications that drive malignant transformation. The Cancer Genome Atlas (TCGA) pilot project aims to assess the value of large-scale multi-dimensional analysis of these molecular characteristics in human cancer and to provide the data rapidly to the research community. Here we report the interim integrative analysis of DNA copy number, gene expression and DNA methylation aberrations in 206 glioblastomas--the most common type of adult brain cancer--and nucleotide sequence aberrations in 91 of the 206 glioblastomas. This analysis provides new insights into the roles of ERBB2, NF1 and TP53, uncovers frequent mutations of the phosphatidylinositol-3-OH kinase regulatory subunit gene PIK3R1, and provides a network view of the pathways altered in the development of glioblastoma. Furthermore, integration of mutation, DNA methylation and clinical treatment data reveals a link between MGMT promoter methylation and a hypermutator phenotype consequent to mismatch repair deficiency in treated glioblastomas, an observation with potential clinical implications. Together, these findings establish the feasibility and power of TCGA, demonstrating that it can rapidly expand knowledge of the molecular basis of cancer.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Brain Neoplasms; DNA Methylation; DNA Modification Methylases; DNA Repair; DNA Repair Enzymes; Female; Gene Dosage; Gene Expression Regulation, Neoplastic; Genes, erbB-1; Genes, Tumor Suppressor; Genome, Human; Genomics; Glioblastoma; Humans; Male; Middle Aged; Models, Molecular; Mutation; Neurofibromin 1; Phosphatidylinositol 3-Kinases; Protein Structure, Tertiary; Retrospective Studies; Signal Transduction; Tumor Suppressor Proteins

Genetic architecture of adiposity and organ weight using combined generation QTL analysis. - Fawcett, Gloria L; Roseman, Charles C; Jarvis, Joseph P; Wang, Bing; Wolf, Jason B; Cheverud, James M (Obesity (Silver Spring), 2008)
We present here a detailed study of the genetic contributions to adult body size and adiposity in the LG,SM advanced intercross line (AIL), an obesity model. This study represents a first step in fine-mapping obesity quantitative trait loci (QTLs) in an AIL. QTLs for adiposity in this model were previously isolated to chromosomes 1, 6, 7, 8, 9, 12, 13, and 18. This study focuses on heritable contributions and the genetic architecture of fatpad and organ weights. We analyzed both the F(2) and F(3) generations of the LG,SM AIL population single-nucleotide polymorphism (SNP) genotyped with a marker density of approximately 4 cM. We replicate 88% of the previously identified obesity QTLs and identify 13 new obesity QTLs. Nearly half of the single-trait QTLs were sex-specific. Several broad QTL regions were resolved into multiple, narrower peaks. The 113 single-trait QTLs for organs and body weight clustered into 27 pleiotropic loci. A large number of epistatic interactions are described which begin to elucidate potential interacting molecular networks. We present a relatively rapid means to obtain fine-mapping details from AILs using dense marker maps and consecutive generations. Analysis of the complex genetic architecture underlying fatpad and organ weights in this model may eventually help to elucidate not only heritable contributions to obesity but also common gene sets for obesity and its comorbidities.
Keywords: Adipose Tissue; Adiposity; Animals; Disease Models, Animal; Epistasis, Genetic; Female; Kidney; Liver; Male; Mice; Mice, Inbred Strains; Myocardium; Obesity; Organ Size; Quantitative Trait Loci; Sex Characteristics; Spleen

Genetic influences on behavioral inhibition and anxiety in juvenile rhesus macaques. - Rogers, J; Shelton, S E; Shelledy, W; Garcia, R; Kalin, N H (Genes Brain Behav, 2008)
In humans and other animals, behavioral responses to threatening stimuli are an important component of temperament. Among children, extreme behavioral inhibition elicited by novel situations or strangers predicts the subsequent development of anxiety disorders and depression. Genetic differences among children are known to affect risk of developing behavioral inhibition and anxiety, but a more detailed understanding of genetic influences on susceptibility is needed. Nonhuman primates provide valuable models for studying the mechanisms underlying human behavior. Individual differences in threat-induced behavioral inhibition (freezing behavior) in young rhesus monkeys are stable over time and reflect individual levels of anxiety. This study used the well-established human intruder paradigm to elicit threat-induced freezing behavior and other behavioral responses in 285 young pedigreed rhesus monkeys. We examined the overall influence of quantitative genetic variation and tested the specific effect of the serotonin transporter promoter repeat polymorphism. Quantitative genetic analyses indicated that the residual heritability of freezing duration (behavioral inhibition) is h(2) = 0.384 (P = 0.012) and of 'orienting to the intruder' (vigilance) is h(2) = 0.908 (P = 0.00001). Duration of locomotion and hostility and frequency of cooing were not significantly heritable. The serotonin transporter polymorphism showed no significant effect on either freezing or orienting to the intruder. Our results suggest that this species could be used for detailed studies of genetic mechanisms influencing extreme behavioral inhibition, including the identification of specific genes that are involved in predisposing individuals to such behavior.
Keywords: Animals; Anxiety Disorders; Behavior, Animal; Brain; Brain Chemistry; Disease Models, Animal; Fear; Female; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Genetic Variation; Inhibition, Psychological; Macaca mulatta; Male; Neural Inhibition; Polymorphism, Single Nucleotide; Serotonin; Serotonin Plasma Membrane Transport Proteins; Social Behavior

The genome of the model beetle and pest Tribolium castaneum. - Stephen Richards; Richard A Gibbs; Weinstock, George M; Brown, Susan J; Denell, Robin; Beeman, Richard W; Richard A Gibbs; Beeman, Richard W; Brown, Susan J; Bucher, Gregor; Friedrich, Markus; Grimmelikhuijzen, Cornelis J P; et al. (Nature, 2008)
Tribolium castaneum is a member of the most species-rich eukaryotic order, a powerful model organism for the study of generalized insect development, and an important pest of stored agricultural products. We describe its genome sequence here. This omnivorous beetle has evolved the ability to interact with a diverse chemical environment, as shown by large expansions in odorant and gustatory receptors, as well as P450 and other detoxification enzymes. Development in Tribolium is more representative of other insects than is Drosophila, a fact reflected in gene content and function. For example, Tribolium has retained more ancestral genes involved in cell-cell communication than Drosophila, some being expressed in the growth zone crucial for axial elongation in short-germ development. Systemic RNA interference in T. castaneum functions differently from that in Caenorhabditis elegans, but nevertheless offers similar power for the elucidation of gene function and identification of targets for selective insect control.
Keywords: Animals; Base Composition; Body Patterning; Cytochrome P-450 Enzyme System; DNA Transposable Elements; Genes, Insect; Genome, Insect; Growth and Development; Humans; Insecticides; Neurotransmitter Agents; Oogenesis; Phylogeny; Proteome; Receptors, G-Protein-Coupled; Receptors, Odorant; Repetitive Sequences, Nucleic Acid; RNA Interference; Taste; Telomere; Tribolium; Vision, Ocular

Genotype-by-diet effects on co-variation in Lp-PLA2 activity and LDL-cholesterol concentration in baboons fed an atherogenic diet. - Vinson, Amanda; Mahaney, Michael C; Diego, Vince P; Cox, Laura A; Rogers, Jeffrey; VandeBerg, John L; Rainwater, David L (J Lipid Res, 2008)
Both lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) activity, a biomarker of inflammation, and concentration of its primary associated lipoprotein, LDL, are correlated with adverse coronary outcomes. We previously reported a quantitative trait locus (QTL) corresponding to HSA2p24.3-p23.2 with pleiotropic effects on Lp-PLA(2) activity and LDL-cholesterol (LDL-C) concentration in baboons fed a basal diet. Here, our goal was to locate pleiotropic QTLs influencing both traits in the same baboons fed a high-cholesterol, high-fat (HCHF) diet, and to assess whether shared genetic effects on these traits differ between diets. We assayed Lp-PLA(2) activity and LDL-C concentration in 683 baboons fed the HCHF diet. We used a bivariate maximum likelihood-based variance components approach in whole-genome linkage screens to locate a QTL [logarithm of odds (LOD) = 3.13, genome-wide P = 0.019] corresponding to HSA19q12-q13.2 with pleiotropic effects on Lp-PLA(2) activity and LDL-C levels in the HCHF diet. We additionally found significant evidence of genetic variance in response to diet for Lp-PLA(2) activity (P = 0.0017) and for LDL-C concentration (P = 0.00001), revealing a contribution of genotype-by-diet interaction to covariation in these two traits. We conclude that the pleiotropic QTLs detected at 2p24.3-p23.2 and 19q12-q13.2 on the basal and HCHF diets, respectively, exert diet-specific effects on covariation in Lp-PLA(2) activity and LDL-C concentration.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Animals; Cholesterol, LDL; Dietary Fats; Female; Genetic Predisposition to Disease; Genotype; Male; Papio; Quantitative Trait Loci; Risk Factors

Identification and phenotypic characterization of a second collagen adhesin, Scm, and genome-based identification and analysis of 13 other predicted MSCRAMMs, including four distinct pilus loci, in Enterococcus faecium. - Sillanpaa, Jouko; Nallapareddy, Sreedhar R; Prakash, Vittal P; Qin, Xiang; Höök, Magnus; Weinstock, George M; Murray, Barbara E (Microbiology (Reading), 2008)
Attention has recently been drawn to Enterococcus faecium because of an increasing number of nosocomial infections caused by this species and its resistance to multiple antibacterial agents. However, relatively little is known about the pathogenic determinants of this organism. We have previously identified a cell-wall-anchored collagen adhesin, Acm, produced by some isolates of E. faecium, and a secreted antigen, SagA, exhibiting broad-spectrum binding to extracellular matrix proteins. Here, we analysed the draft genome of strain TX0016 for potential microbial surface components recognizing adhesive matrix molecules (MSCRAMMs). Genome-based bioinformatics identified 22 predicted cell-wall-anchored E. faecium surface proteins (Fms), of which 15 (including Acm) had characteristics typical of MSCRAMMs, including predicted folding into a modular architecture with multiple immunoglobulin-like domains. Functional characterization of one [Fms10; redesignated second collagen adhesin of E. faecium (Scm)] revealed that recombinant Scm(65) (A- and B-domains) and Scm(36) (A-domain) bound to collagen type V efficiently in a concentration-dependent manner, bound considerably less to collagen type I and fibrinogen, and differed from Acm in their binding specificities to collagen types IV and V. Results from far-UV circular dichroism measurements of recombinant Scm(36) and of Acm(37) indicated that these proteins were rich in beta-sheets, supporting our folding predictions. Whole-cell ELISA and FACS analyses unambiguously demonstrated surface expression of Scm in most E. faecium isolates. Strikingly, 11 of the 15 predicted MSCRAMMs clustered in four loci, each with a class C sortase gene; nine of these showed similarity to Enterococcus faecalis Ebp pilus subunits and also contained motifs essential for pilus assembly. Antibodies against one of the predicted major pilus proteins, Fms9 (redesignated EbpC(fm)), detected a 'ladder' pattern of high-molecular-mass protein bands in a Western blot analysis of cell surface extracts from E. faecium, suggesting that EbpC(fm) is polymerized into a pilus structure. Further analysis of the transcripts of the corresponding gene cluster indicated that fms1 (ebpA(fm)), fms5 (ebpB(fm)) and ebpC(fm) are co-transcribed, a result consistent with those for pilus-encoding gene clusters of other Gram-positive bacteria. All 15 genes occurred frequently in 30 clinically derived diverse E. faecium isolates tested. The common occurrence of MSCRAMM- and pilus-encoding genes and the presence of a second collagen-binding protein may have important implications for our understanding of this emerging pathogen.
Keywords: Adhesins, Bacterial; Bacterial Adhesion; Circular Dichroism; Collagen; DNA, Bacterial; Enterococcus faecium; Enzyme-Linked Immunosorbent Assay; Fimbriae, Bacterial; Flow Cytometry; Genes, Bacterial; Genome, Bacterial; Multigene Family; Phenotype; Protein Binding; Protein Conformation; Recombinant Proteins; Reverse Transcriptase Polymerase Chain Reaction; RNA, Bacterial; Substrate Specificity

Large scale variation in Enterococcus faecalis illustrated by the genome analysis of strain OG1RF. - Bourgogne, Agathe; Garsin, Danielle A; Qin, Xiang; Singh, Kavindra V; Sillanpaa, Jouko; Yerrapragada, Shailaja; Ding, Yan; Dugan-Rocha, Shannon; Buhay, Christian; Shen, Hua; Chen, Guan; Williams, Gabrielle; et al. (Genome Biol, 2008)
BACKGROUND: Enterococcus faecalis has emerged as a major hospital pathogen. To explore its diversity, we sequenced E. faecalis strain OG1RF, which is commonly used for molecular manipulation and virulence studies. RESULTS: The 2,739,625 base pair chromosome of OG1RF was found to contain approximately 232 kilobases unique to this strain compared to V583, the only publicly available sequenced strain. Almost no mobile genetic elements were found in OG1RF. The 64 areas of divergence were classified into three categories. First, OG1RF carries 39 unique regions, including 2 CRISPR loci and a new WxL locus. Second, we found nine replacements where a sequence specific to V583 was substituted by a sequence specific to OG1RF. For example, the iol operon of OG1RF replaces a possible prophage and the vanB transposon in V583. Finally, we found 16 regions that were present in V583 but missing from OG1RF, including the proposed pathogenicity island, several probable prophages, and the cpsCDEFGHIJK capsular polysaccharide operon. OG1RF was more rapidly but less frequently lethal than V583 in the mouse peritonitis model and considerably outcompeted V583 in a murine model of urinary tract infections. CONCLUSION: E. faecalis OG1RF carries a number of unique loci compared to V583, but the almost complete lack of mobile genetic elements demonstrates that this is not a defining feature of the species. Additionally, OG1RF's effects in experimental models suggest that mediators of virulence may be diverse between different E. faecalis strains and that virulence is not dependent on the presence of mobile genetic elements.
Keywords: Animals; Anti-Bacterial Agents; Bacterial Proteins; Biofilms; DNA, Bacterial; Drug Resistance, Bacterial; Enterococcus faecalis; Fusidic Acid; Genetic Variation; Genome, Bacterial; Genomics; Interspersed Repetitive Sequences; Membrane Proteins; Mice; Operon; Repetitive Sequences, Nucleic Acid; Rifampin; Sequence Homology, Nucleic Acid

Mouse let-7 miRNA populations exhibit RNA editing that is constrained in the 5'-seed/ cleavage/anchor regions and stabilize predicted mmu-let-7a:mRNA duplexes. - Reid, Jeffrey G; Nagaraja, Ankur K; Lynn, Francis C; Drabek, Rafal B; Muzny, Donna M; Shaw, Chad A; Weiss, Michelle K; Naghavi, Arash O; Khan, Mahjabeen; Zhu, Huifeng; Tennakoon, Jayantha; Gunaratne, Gemunu H; et al. (Genome Res, 2008)
Massively parallel sequencing of millions of < 30-nt RNAs expressed in mouse ovary, embryonic pancreas (E14.5), and insulin-secreting beta-cells (betaTC-3) reveals that approximately 50% of the mature miRNAs representing mostly the mmu-let-7 family display internal insertion/deletions and substitutions when compared to precursor miRNA and the mouse genome reference sequences. Approximately, 12%-20% of species associated with mmu-let-7 populations exhibit sequence discrepancies that are dramatically reduced in nucleotides 3-7 (5'-seed) and 10-15 (cleavage and anchor sites). This observation is inconsistent with sequencing error and leads us to propose that the changes arise predominantly from post-transcriptional RNA-editing activity operating on miRNA:target mRNA complexes. Internal nucleotide modifications are most enriched at the ninth nucleotide position. A common ninth base edit of U-to-G results in a significant increase in stability of down-regulated let-7a targets in inhibin-deficient mice (Inha-/-). An excess of U-insertions (14.8%) over U-deletions (1.5%) and the presence of cleaved intermediates suggest that a mammalian TUTase (terminal uridylyl transferase) mediated dUTP-dependent U-insertion/U-deletion cycle may be a possible mechanism. We speculate that mRNA target site-directed editing of mmu-let-7a duplex-bulges stabilizes "loose" miRNA:mRNA target associations and functions to expand the target repertoire and/or enhance mRNA decay over translational repression. Our results also demonstrate that the systematic study of sequence variation within specific RNA classes in a given cell type from millions of sequences generated by next-generation sequencing (NGS) technologies ("intranomics") can be used broadly to infer functional constraints on specific parts of completely uncharacterized RNAs.
Keywords: Animals; Base Sequence; Cells, Cultured; Deoxyuracil Nucleotides; Embryo, Mammalian; Female; Mice; MicroRNAs; Molecular Sequence Data; Nucleic Acid Conformation; RNA Editing; RNA Nucleotidyltransferases; RNA Stability; RNA, Messenger; RNA, Small Untranslated

Nonhuman primates as models for studies of prostate specific antigen and prostatic diseases. - Mubiru, James N; Hubbard, Gene B; Dick, Edward J; Furman, Jaime; Troyer, Dean A; Rogers, Jeffrey (Prostate, 2008)
BACKGROUND: Because prostate specific antigen (PSA) is released at increased levels into the blood early in the development of prostate cancer, benign prostatic hyperplasia (BPH) and prostatitis, it is widely used as a marker for these diseases. However, PSA has clinical limitations as a screen for prostatic diseases due to its low sensitivity and specificity. There is a strong need to better understand the biology of PSA and factors affecting its serum levels. METHODS: We evaluated cynomolgus macaques, rhesus macaques, baboons, and marmosets for their suitability as models for the study of PSA biology and prostatic diseases. RESULTS: Prostates of several nonhuman primates are anatomically similar to the human counterpart. Anti-human PSA antibody detected PSA antigens in all the Old World monkeys (cynomolgus macaques, rhesus macaques, and baboons) but not in marmosets. Of the Old World monkeys, cynomolgus macaques have the highest serum PSA levels; baboons have the lowest. Serum PSA levels from macaques includes a number of outlier samples with unusually high values. We also report two cases of abnormal pathologies in macaques accompanied by high serum PSA levels. One case consisted of prostatic hyperplasia involving both glandular and basal cells in a cynomolgus macaque and another of glandular hyperplasia and atrophy in a rhesus macaque. The finding that pathological changes in the prostate of macaques may lead to increases in serum PSA is worthy of further exploration. CONCLUSION: Cynomolgus macaques and rhesus macaques are promising animal models for PSA biology studies.
Keywords: Animals; Body Weight; Callithrix; Disease Models, Animal; Haplorhini; Immunoblotting; Macaca fascicularis; Macaca mulatta; Male; Organ Size; Papio; Prostate-Specific Antigen; Prostatic Hyperplasia; Prostatic Neoplasms; Racemases and Epimerases; Reverse Transcriptase Polymerase Chain Reaction; RNA

Pash 2.0: scaleable sequence anchoring for next-generation sequencing technologies. - Coarfa, Cristian; Milosavljevic, Aleksandar (Pac Symp Biocomput, 2008)
Many applications of next-generation sequencing technologies involve anchoring of a sequence fragment or a tag onto a corresponding position on a reference genome assembly. Positional Hashing method, implemented in the Pash 2.0 program, is specifically designed for the task of high-volume anchoring. In this article we present multi-diagonal gapped kmer collation and other improvements introduced in Pash 2.0 that further improve accuracy and speed of Positional Hashing. The goal of this article is to show that gapped kmer matching with cross-diagonal collation suffices for anchoring across close evolutionary distances and for the purpose of human resequencing. We propose a benchmark for evaluating the performance of anchoring programs that captures key parameters in specific applications, including duplicative structure of genomes of humans and other species. We demonstrate speedups of up to tenfold in large-scale anchoring experiments achieved by PASH 2.0 when compared to BLAT, another similarity search program frequently used for anchoring.
Keywords: Algorithms; Animals; Computational Biology; Databases, Genetic; Evolution, Molecular; Genome, Human; Humans; Sensitivity and Specificity; Sequence Alignment; Software

Peroxisome proliferator-activated receptor [alpha] genetic variation interacts with n-6 and long-chain n-3 fatty acid intake to affect total cholesterol and LDL-cholesterol concentrations in the Atherosclerosis Risk in Communities Study. - Volcik, Kelly A; Nettleton, Jennifer A; Ballantyne, Christie M; Boerwinkle, Eric (Am J Clin Nutr, 2008)
BACKGROUND: Peroxisome proliferator-activated receptor-alpha (PPARA) regulates the expression of genes involved in lipid metabolism. The binding of polyunsaturated fatty acids (PUFAs) to PPARA results in rapid changes in the expression of genes involved in lipid oxidation, with long-chain n-3 fatty acids being potent activators of PPARA. OBJECTIVE: We evaluated the potential effect modification of PPARA genetic variation on the association between PUFA intake, specifically n-6 and long-chain n-3 fatty acid intakes, and multiple lipid measures in the large biethnic Atherosclerosis Risk in Communities (ARIC) Study. DESIGN: Study participants (10 134 whites and 3480 African Americans) were selected from the ARIC Study--a prospective investigation of atherosclerosis and its clinical sequelae. Multiple linear regression models were used to assess the relation between PPARA genotypes, as well as dietary fatty acid intake, and baseline lipid measures. PPARA-specific effects of variation were assessed by including genotype-by-fatty acid interaction terms in each statistical model. RESULTS: PPARA genotype frequencies were significantly different between whites and African Americans. No significant associations between lipid measures and PPARA genotype were observed in either whites or African Americans. Significant genotype-by-n-6 fatty acid intake interactions were observed only in whites for the 3'untranslated region (UTR) G-->A single nucleotide polymorphism (SNP) and total cholesterol (P = 0.03) and LDL cholesterol (P = 0.03). Significant genotype-by-long-chain n-3 fatty acid intake interactions were observed only in African Americans for the 3'UTR C-->T SNP and total cholesterol (P = 0.03) and LDL cholesterol (P = 0.02). CONCLUSIONS: Findings from the current study suggest that PPARA 3'UTR SNPs modulate the association between lipid concentrations and dietary n-6 fatty acid intake (in whites) and long-chain n-3 fatty acid intake (in African Americans) such that persons with homozygous variant genotypes have significantly lower total cholesterol and LDL-cholesterol measures when consuming higher quantities of n-6 or long-chain n-3 fatty acids.
Keywords: 3' Untranslated Regions; Atherosclerosis; Black People; Cholesterol; Cholesterol, LDL; Dietary Fats; Fatty Acids, Omega-3; Fatty Acids, Omega-6; Female; Gene Frequency; Genetic Variation; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; PPAR alpha; Risk Factors; United States; White People

A pleiotropic QTL on 2p influences serum Lp-PLA2 activity and LDL cholesterol concentration in a baboon model for the genetics of atherosclerosis risk factors. - Vinson, A; Mahaney, M C; Cox, L A; Rogers, J; VandeBerg, J L; Rainwater, D L (Atherosclerosis, 2008)
Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)), the major portion of which is bound to low-density lipoprotein, is an independent biomarker of cardiovascular disease risk. To search for common genetic determinants of variation in both Lp-PLA(2) activity and LDL cholesterol (LDL-C) concentration, we assayed these substances in serum from 679 pedigreed baboons. Using a maximum likelihood-based variance components approach, we detected significant evidence for a QTL affecting Lp-PLA(2) activity (LOD=2.79, genome-wide P=0.039) and suggestive evidence for a QTL affecting LDL-C levels (LOD=2.16) at the same location on the baboon ortholog of human chromosome 2p. Because we also found a significant genetic correlation between the two traits (rho(G)=0.50, P<0.00001), we conducted bivariate linkage analyses of Lp-PLA(2) activity and LDL-C concentration. These bivariate analyses improved the evidence (LOD=3.19, genome-wide P=0.015) for a QTL at the same location on 2p, corresponding to the human cytogenetic region 2p24.3-p23.2. The QTL-specific correlation between the traits (rho(Q)=0.62) was significantly different from both zero and 1 (P[rho(Q)=0]=0.047; P[rho(Q)=1]=0.022), rejecting the hypothesis of co-incident linkage and consistent with incomplete pleiotropy at this locus. We conclude that polymorphisms at the QTL described in this study exert some genetic effects that are shared between Lp-PLA(2) activity and LDL-C concentration.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Animals; Atherosclerosis; Cholesterol, LDL; Disease Models, Animal; Female; Male; Multivariate Analysis; Papio hamadryas; Quantitative Trait Loci; Risk Factors

PrimerSNP: a web tool for whole-genome selection of allele-specific and common primers of phylogenetically-related bacterial genomic sequences. - Yao, Jiqiang; Lin, Hong; Van Deynze, Allen; Doddapaneni, Harshavardhan; Francis, Martha; Lemos, Eliana Gertrudes Macedo; Civerolo, Edwin L (BMC Microbiol, 2008)
BACKGROUND: The increasing number of genomic sequences of bacteria makes it possible to select unique SNPs of a particular strain/species at the whole genome level and thus design specific primers based on the SNPs. The high similarity of genomic sequences among phylogenetically-related bacteria requires the identification of the few loci in the genome that can serve as unique markers for strain differentiation. PrimerSNP attempts to identify reliable strain-specific markers, on which specific primers are designed for pathogen detection purpose. RESULTS: PrimerSNP is an online tool to design primers based on strain specific SNPs for multiple strains/species of microorganisms at the whole genome level. The allele-specific primers could distinguish query sequences of one strain from other homologous sequences by standard PCR reaction. Additionally, PrimerSNP provides a feature for designing common primers that can amplify all the homologous sequences of multiple strains/species of microorganisms. PrimerSNP is freely available at http://cropdisease.ars.usda.gov/~primer. CONCLUSION: PrimerSNP is a high-throughput specific primer generation tool for the differentiation of phylogenetically-related strains/species. Experimental validation showed that this software had a successful prediction rate of 80.4 - 100% for strain specific primer design.
Keywords: Alleles; Bacteria; Computational Biology; DNA Primers; Genome, Bacterial; Internet; Polymorphism, Single Nucleotide; Sensitivity and Specificity; Sequence Alignment; Software

Progress and prospects in rat genetics: a community view. - Aitman, Timothy J; Critser, John K; Cuppen, Edwin; Dominiczak, Anna; Fernandez-Suarez, Xose M; Flint, Jonathan; Gauguier, Dominique; Geurts, Aron M; Gould, Michael; Harris, Peter C; Holmdahl, Rikard; Hübner, Norbert; et al. (Nat Genet, 2008)
The rat is an important system for modeling human disease. Four years ago, the rich 150-year history of rat research was transformed by the sequencing of the rat genome, ushering in an era of exceptional opportunity for identifying genes and pathways underlying disease phenotypes. Genome-wide association studies in human populations have recently provided a direct approach for finding robust genetic associations in common diseases, but identifying the precise genes and their mechanisms of action remains problematic. In the context of significant progress in rat genomic resources over the past decade, we outline achievements in rat gene discovery to date, show how these findings have been translated to human disease, and document an increasing pace of discovery of new disease genes, pathways and mechanisms. Finally, we present a set of principles that justify continuing and strengthening genetic studies in the rat model, and further development of genomic infrastructure for rat research.
Keywords: Animals; Animals, Genetically Modified; Chromosome Mapping; Disease Models, Animal; Gene Targeting; Genetic Diseases, Inborn; Genome; Genomics; Humans; Rats

Quantitative monitoring of adenocarcinoma development in rodents by magnetic resonance imaging. - Garbow, Joel R; Wang, Min; Wang, Yian; Lubet, Ronald A; You, Ming (Clin Cancer Res, 2008)
PURPOSE: Accurately following the time course of tumor progression and response to therapy in animal models of cancer is key to the development of better chemopreventive and chemotherapeutic agents. The goal of this work was to monitor quantitatively the development and progression of adenocarcinoma in a time course study of mice treated with the carcinogen urethane using in vivo small-animal magnetic resonance imaging (MRI). EXPERIMENTAL DESIGN: Mice treated with a single dose of urethane were imaged at four time points beginning 8 months after treatment. High-resolution images of mouse lung were obtained in vivo using respiratory-gated MRI methods. Individual tumors were manually segmented and their volumes calculated. At the end of the study, mice were euthanized and MRI tumor quantification was validated by histology and histopathology. RESULTS: Tumors as small as 0.4 mm in diameter can be detected and quantitatively measured in mice by in vivo MRI. Total tumor burden increased consistently in all mice studied, whereas the growth rate of individual tumors varied widely. The positions and diameters of individual tumors as measured by MRI correlated well with histology results. Histologic study of large, rapidly growing tumors showed that these were adenocarcinomas, whereas small, slowly growing lesions were predominantly adenomas. CONCLUSIONS: Longitudinal in vivo MRI is a powerful modality that can be of great aid in elucidating the factors that control the onset of lung tumors and can serve as a platform for the development and preclinical testing of novel therapies having a high likelihood of efficacy in human clinical trials.
Keywords: Adenocarcinoma; Animals; Carcinogens; Disease Models, Animal; Image Interpretation, Computer-Assisted; Image Processing, Computer-Assisted; Lung Neoplasms; Magnetic Resonance Imaging; Male; Mice; Mice, Inbred A; Urethane

The serotonin transporter genotype is associated with intermediate brain phenotypes that depend on the context of eliciting stressor. - Kalin, N H; Shelton, S E; Fox, A S; Rogers, J; Oakes, T R; Davidson, R J (Mol Psychiatry, 2008)
A variant allele in the promoter region of the serotonin transporter gene, SLC6A4, the s allele, is associated with increased vulnerability to develop anxiety-related traits and depression. Furthermore, functional magnetic resonance imaging (fMRI) studies reveal that s carriers have increased amygdala reactivity in response to aversive stimuli, which is thought to be an intermediate phenotype mediating the influences of the s allele on emotionality. We used high-resolution microPET [18F]fluoro-2-deoxy-D-glucose (FDG) scanning to assess regional brain metabolic activity in rhesus monkeys to further explore s allele-related intermediate phenotypes. Rhesus monkeys provide an excellent model to understand mechanisms underlying human anxiety, and FDG microPET allows for the assessment of brain activity associated with naturalistic environments outside the scanner. During FDG uptake, monkeys were exposed to different ethologically relevant stressful situations (relocation and threat) as well as to the less stressful familiar environment of their home cage. The s carriers displayed increased orbitofrontal cortex activity in response to both relocation and threat. However, during relocation they displayed increased amygdala reactivity and in response to threat they displayed increased reactivity of the bed nucleus of the stria terminalis. No increase in the activity of any of these regions occurred when the animals were administered FDG in their home cages. These findings demonstrate context-dependent intermediate phenotypes in s carriers that provide a framework for understanding the mechanisms underlying the vulnerabilities of s-allele carriers exposed to different types of stressors.
Keywords: Animals; Behavior, Animal; Brain; Brain Mapping; Disease Models, Animal; Female; Fluorodeoxyglucose F18; Genotype; Macaca mulatta; Male; Phenotype; Polymorphism, Genetic; Positron-Emission Tomography; Serotonin Plasma Membrane Transport Proteins; Stress, Psychological

VitisExpDB: a database resource for grape functional genomics. - Doddapaneni, Harshavardhan; Lin, Hong; Walker, M Andrew; Yao, Jiqiang; Civerolo, Edwin L (BMC Plant Biol, 2008)
BACKGROUND: The family Vitaceae consists of many different grape species that grow in a range of climatic conditions. In the past few years, several studies have generated functional genomic information on different Vitis species and cultivars, including the European grape vine, Vitis vinifera. Our goal is to develop a comprehensive web data source for Vitaceae. DESCRIPTION: VitisExpDB is an online MySQL-PHP driven relational database that houses annotated EST and gene expression data for V. vinifera and non-vinifera grape species and varieties. Currently, the database stores approximately 320,000 EST sequences derived from 8 species/hybrids, their annotation (BLAST top match) details and Gene Ontology based structured vocabulary. Putative homologs for each EST in other species and varieties along with information on their percent nucleotide identities, phylogenetic relationship and common primers can be retrieved. The database also includes information on probe sequence and annotation features of the high density 60-mer gene expression chip consisting of approximately 20,000 non-redundant set of ESTs. Finally, the database includes 14 processed global microarray expression profile sets. Data from 12 of these expression profile sets have been mapped onto metabolic pathways. A user-friendly web interface with multiple search indices and extensively hyperlinked result features that permit efficient data retrieval has been developed. Several online bioinformatics tools that interact with the database along with other sequence analysis tools have been added. In addition, users can submit their ESTs to the database. CONCLUSION: The developed database provides genomic resource to grape community for functional analysis of genes in the collection and for the grape genome annotation and gene function identification. The VitisExpDB database is available through our website http://cropdisease.ars.usda.gov/vitis_at/main-page.htm.
Keywords: Computational Biology; Databases, Genetic; Expressed Sequence Tags; Genomics; Internet; Vitis

What everybody should know about the rat genome and its online resources. - Twigger, Simon N; Pruitt, Kim D; Fernandez-Suarez, Xose M; Karolchik, Donna; Worley, Kim C; Maglott, Donna R; Brown, Garth; Weinstock, George; Gibbs, Richard A; Kent, Jim; Birney, Ewan; Jacob, Howard J (Nat Genet, 2008)
It has been four years since the original publication of the draft sequence of the rat genome. Five groups are now working together to assemble, annotate and release an updated version of the rat genome. As the prevailing model for physiology, complex disease and pharmacological studies, there is an acute need for the rat's genomic resources to keep pace with the rat's prominence in the laboratory. In this commentary, we describe the current status of the rat genome sequence and the plans for its impending 'upgrade'. We then cover the key online resources providing access to the rat genome, including the new SNP views at Ensembl, the RefSeq and Genes databases at the US National Center for Biotechnology Information, Genome Browser at the University of California Santa Cruz and the disease portals for cardiovascular disease and obesity at the Rat Genome Database.
Keywords: Animals; Computational Biology; Databases, Genetic; Disease Models, Animal; Genetic Diseases, Inborn; Genetic Variation; Genome; Genomics; Haplotypes; Humans; Internet; Polymorphism, Single Nucleotide; Rats; Rats, Mutant Strains; Sequence Analysis, DNA

28-way vertebrate alignment and conservation track in the UCSC Genome Browser. - Miller, Webb; Rosenbloom, Kate; Hardison, Ross C; Hou, Minmei; Taylor, James; Raney, Brian; Burhans, Richard; King, David C; Baertsch, Robert; Blankenberg, Daniel; Kosakovsky Pond, Sergei L; Nekrutenko, Anton; et al. (Genome Res, 2007)
This article describes a set of alignments of 28 vertebrate genome sequences that is provided by the UCSC Genome Browser. The alignments can be viewed on the Human Genome Browser (March 2006 assembly) at http://genome.ucsc.edu, downloaded in bulk by anonymous FTP from http://hgdownload.cse.ucsc.edu/goldenPath/hg18/multiz28way, or analyzed with the Galaxy server at http://g2.bx.psu.edu. This article illustrates the power of this resource for exploring vertebrate and mammalian evolution, using three examples. First, we present several vignettes involving insertions and deletions within protein-coding regions, including a look at some human-specific indels. Then we study the extent to which start codons and stop codons in the human sequence are conserved in other species, showing that start codons are in general more poorly conserved than stop codons. Finally, an investigation of the phylogenetic depth of conservation for several classes of functional elements in the human genome reveals striking differences in the rates and modes of decay in alignability. Each functional class has a distinctive period of stringent constraint, followed by decays that allow (for the case of regulatory regions) or reject (for coding regions and ultraconserved elements) insertions and deletions.
Keywords: Animals; Base Sequence; Cats; Cattle; Codon, Initiator; Codon, Terminator; Conserved Sequence; Databases, Genetic; Dogs; Genome, Human; Guinea Pigs; Humans; Mice; Molecular Sequence Data; Mutagenesis, Insertional; Rabbits; Rats; Sequence Alignment; Sequence Deletion

Comparative analysis of ESTs involved in grape responses to Xylella fastidiosa infection. - Lin, Hong; Doddapaneni, Harshavardhan; Takahashi, Yuri; Walker, M Andrew (BMC Plant Biol, 2007)
BACKGROUND: The gram-negative bacterium Xylella fastidiosa (Xf) is the causal agent of Pierce's disease (PD) in grape as well as diseases of many fruit and ornamental plants. The current molecular breeding efforts have identified genetic basis of PD resistance in grapes. However, the transcriptome level characterization of the host response to this pathogen is lacking. RESULTS: Twelve tissue specific subtractive suppression hybridization (SSH) cDNA libraries derived from a time course sampling scheme were constructed from stems, leaves and shoots of PD resistant and susceptible sibling genotypes (V. rupestris x V. arizonica) in response to Xf infection. A total of 5,794 sequences were obtained from these cDNA libraries from which 993 contigs and 949 singletons were derived. Using Gene Ontology (GO) hierarchy, the non-redundant sequences were classified into the three principal categories: molecular function (30%), cellular components (9%) and biological processes (7%). Comparative analysis found variations in EST expression pattern between infected and non-infected PD resistant and PD susceptible grape genotypes. Among the three tissues, libraries from stem tissues showed significant differences in transcript quality suggesting their important role in grape-Xylella interaction. CONCLUSION: This study constitutes the first attempt to characterize the Vitis differential transcriptome associated with host-pathogen interactions from different explants and genotypes. All the generated ESTs have been submitted to GenBank and are also available through our website for further functional studies.
Keywords: Cluster Analysis; DNA, Complementary; Expressed Sequence Tags; Gene Expression Regulation, Plant; Gene Library; Molecular Sequence Data; Nucleic Acid Hybridization; Plant Diseases; Plant Leaves; Plant Shoots; Plant Stems; Reverse Transcriptase Polymerase Chain Reaction; Sequence Analysis, DNA; Time Factors; Vitis; Xylella

Demographic histories and patterns of linkage disequilibrium in Chinese and Indian rhesus macaques. - Hernandez, Ryan D; Hubisz, Melissa J; David A Wheeler; Smith, David G; Ferguson, Betsy; Jeffrey Rogers; Nazareth, Lynne; Indap, Amit; Bourquin, Traci; McPherson, John; Donna M Muzny; Richard A Gibbs; et al. (Science, 2007)
To understand the demographic history of rhesus macaques (Macaca mulatta) and document the extent of linkage disequilibrium (LD) in the genome, we partially resequenced five Encyclopedia of DNA Elements regions in 9 Chinese and 38 captive-born Indian rhesus macaques. Population genetic analyses of the 1467 single-nucleotide polymorphisms discovered suggest that the two populations separated about 162,000 years ago, with the Chinese population tripling in size since then and the Indian population eventually shrinking by a factor of four. Using coalescent simulations, we confirmed that these inferred demographic events explain a much faster decay of LD in Chinese (r(2) approximately 0.15 at 10 kilobases) versus Indian (r(2) approximately 0.52 at 10 kilobases) macaque populations.
Keywords: Animals; China; Demography; DNA, Mitochondrial; Genetics, Medical; Humans; India; Linkage Disequilibrium; Macaca mulatta; Polymorphism, Single Nucleotide

EGFR-T790M is a rare lung cancer susceptibility allele with enhanced kinase activity. - Vikis, Haris; Sato, Mitsuo; James, Michael; Wang, Daolong; Wang, Yian; Wang, Min; Jia, Dongmei; Liu, Yan; Bailey-Wilson, Joan E; Amos, Christopher I; Pinney, Susan M; Petersen, Gloria M; et al. (Cancer Res, 2007)
The use of tyrosine kinase inhibitors (TKI) has yielded great success in treatment of lung adenocarcinomas. However, patients who develop resistance to TKI treatment often acquire a somatic resistance mutation (T790M) located in the catalytic cleft of the epidermal growth factor receptor (EGFR) enzyme. Recently, a report describing EGFR-T790M as a germ-line mutation suggested that this mutation may be associated with inherited susceptibility to lung cancer. Contrary to previous reports, our analysis indicates that the T790M mutation confers increased Y992 and Y1068 phosphorylation levels. In a human bronchial epithelial cell line, overexpression of EGFR-T790M displayed a growth advantage over wild-type (WT) EGFR. We also screened 237 lung cancer family probands, in addition to 45 bronchoalveolar tumors, and found that none of them contained the EGFR-T790M mutation. Our observations show that EGFR-T790M provides a proliferative advantage with respect to WT EGFR and suggest that the enhanced kinase activity of this mutant is the basis for rare cases of inherited susceptibility to lung cancer.
Keywords: Alleles; Animals; Chlorocebus aethiops; COS Cells; DNA, Neoplasm; ErbB Receptors; Genes, erbB-1; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Lung Neoplasms; Pedigree; Phosphorylation

Elevated expression of DNA polymerase II increases spontaneous mutagenesis in Escherichia coli. - Al Mamun, Abu Amar M (Mutat Res, 2007)
Escherichia coli DNA polymerase II (Pol-II), encoded by the SOS-regulated polB gene, belongs to the highly conserved group B (alpha-like) family of "high-fidelity" DNA polymerases. Elevated expression of polB gene was recently shown to result in a significant elevation of translesion DNA synthesis at 3, N(4)-ethenocytosine lesion with concomitant increase in mutagenesis. Here, I show that elevated expression of Pol-II leads to an approximately 100-fold increase in spontaneous mutagenesis in a manner that is independent of SOS, umuDC, dinB, recA, uvrA and mutS functions. Cells grow slowly and filament with elevated expression of Pol-II. Introduction of carboxy terminus ("beta interaction domain") mutations in polB eliminates elevated spontaneous mutagenesis, as well as defects in cell growth and morphology, suggesting that these abilities require the interaction of Pol-II with the beta processivity subunit of DNA polymerase III. Introduction of a mutation in the proofreading exo motif of polB elevates mutagenesis by a further 180-fold, suggesting that Pol-II can effectively compete with DNA polymerase III for DNA synthesis. Thus, Pol-II can contribute to spontaneous mutagenesis when its expression is elevated.
Keywords: Base Sequence; DNA Polymerase II; DNA, Bacterial; Drug Resistance, Bacterial; Escherichia coli; Escherichia coli Proteins; Gene Expression; Genes, Bacterial; Mutagenesis; Mutation; Mutation, Missense; Plasmids; Rifampin

Genome sequence of Fusobacterium nucleatum subspecies polymorphum - a genetically tractable fusobacterium. - Karpathy, Sandor E; Qin, Xiang; Gioia, Jason; Jiang, Huaiyang; Liu, Yamei; Petrosino, Joseph F; Yerrapragada, Shailaja; Fox, George E; Haake, Susan Kinder; Weinstock, George M; Highlander, Sarah K (PLoS One, 2007)
Fusobacterium nucleatum is a prominent member of the oral microbiota and is a common cause of human infection. F. nucleatum includes five subspecies: polymorphum, nucleatum, vincentii, fusiforme, and animalis. F. nucleatum subsp. polymorphum ATCC 10953 has been well characterized phenotypically and, in contrast to previously sequenced strains, is amenable to gene transfer. We sequenced and annotated the 2,429,698 bp genome of F. nucleatum subsp. polymorphum ATCC 10953. Plasmid pFN3 from the strain was also sequenced and analyzed. When compared to the other two available fusobacterial genomes (F. nucleatum subsp. nucleatum, and F. nucleatum subsp. vincentii) 627 open reading frames unique to F. nucleatum subsp. polymorphum ATCC 10953 were identified. A large percentage of these mapped within one of 28 regions or islands containing five or more genes. Seventeen percent of the clustered proteins that demonstrated similarity were most similar to proteins from the clostridia, with others being most similar to proteins from other gram-positive organisms such as Bacillus and Streptococcus. A ten kilobase region homologous to the Salmonella typhimurium propanediol utilization locus was identified, as was a prophage and integrated conjugal plasmid. The genome contains five composite ribozyme/transposons, similar to the CdISt IStrons described in Clostridium difficile. IStrons are not present in the other fusobacterial genomes. These findings indicate that F. nucleatum subsp. polymorphum is proficient at horizontal gene transfer and that exchange with the Firmicutes, particularly the Clostridia, is common.
Keywords: Amino Acids; Base Sequence; Clostridium; DNA, Bacterial; Evolution, Molecular; Fusobacterium nucleatum; Gene Transfer Techniques; Genome, Bacterial; Humans; Infections; Introns; Multigene Family; Open Reading Frames; Peptides; Plasmids; Polymorphism, Genetic; Repetitive Sequences, Nucleic Acid

A genomewide admixture map for Latino populations. - Price, Alkes L; Patterson, Nick; Yu, Fuli; Cox, David R; Waliszewska, Alicja; McDonald, Gavin J; Tandon, Arti; Schirmer, Christine; Neubauer, Julie; Bedoya, Gabriel; Duque, Constanza; Villegas, Alberto; et al. (Am J Hum Genet, 2007)
Admixture mapping is an economical and powerful approach for localizing disease genes in populations of recently mixed ancestry and has proven successful in African Americans. The method holds equal promise for Latinos, who typically inherit a mix of European, Native American, and African ancestry. However, admixture mapping in Latinos has not been practical because of the lack of a map of ancestry-informative markers validated in Native American and other populations. To address this, we screened multiple databases, containing millions of markers, to identify 4,186 markers that were putatively informative for determining the ancestry of chromosomal segments in Latino populations. We experimentally validated each of these markers in at least 232 new Latino, European, Native American, and African samples, and we selected a subset of 1,649 markers to form an admixture map. An advantage of our strategy is that we focused our map on markers distinguishing Native American from other ancestries and restricted it to markers with very similar frequencies in Europeans and Africans, which decreased the number of markers needed and minimized the possibility of false disease associations. We evaluated the effectiveness of our map for localizing disease genes in four Latino populations from both North and South America.
Keywords: Alleles; Black People; Case-Control Studies; Chromosome Mapping; Chromosomes, Human; Computer Simulation; Databases, Genetic; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genetics, Population; Genome, Human; Hispanic or Latino; Humans; Indians, North American; Reproducibility of Results; White People

A genome-wide linkage scan for diabetic retinopathy susceptibility genes in Mexican Americans with type 2 diabetes from Starr County, Texas. - Hallman, D Michael; Eric Boerwinkle; Gonzalez, Victor H; Klein, Barbara E K; Klein, Ronald; Hanis, Craig L (Diabetes, 2007)
We conducted a genome-wide linkage scan for genes contributing to retinopathy risk using 794 diabetes case subjects from 393 Mexican-American families from Starr County, Texas, having at least two diabetic siblings. The sample included 567 retinopathy case subjects comprising 282 affected sibling pairs. Retinopathy was classified as none, early nonproliferative, moderate-to-severe nonproliferative, or proliferative. Using 360 polymorphic markers (average spacing 9.4 cM), we conducted nonparametric linkage analysis followed by ordered-subset analysis (OSA) ranking families by average age of diabetes diagnosis. For any retinopathy, the highest LOD scores including all families were on chromosomes 3 (2.41 at 117 cM) and 12 (2.47 at 15.5). OSA logarithm of odds (LOD) scores >2 for any retinopathy occurred on chromosomes 12 (4.47 at 13.2 cM), 15 (3.65 at 100.6), and 20 (2.67 at 54.1). Scores >2 for either moderate-to-severe nonproliferative or proliferative retinopathy occurred on chromosomes 5 (2.53 at 11.2 cM), 6 (2.28 at 30.6), and 19 (2.21 at 100.6). Thus, unconditional linkage analysis revealed suggestive evidence of linkage with retinopathy on two chromosomes, whereas OSA revealed strong evidence of linkage on two chromosomes, and suggestive evidence on four. Candidate genes were identified in most implicated regions.
Keywords: Adult; Age of Onset; Body Mass Index; Diabetes Mellitus, Type 2; Diabetic Retinopathy; Family; Female; Genetic Predisposition to Disease; Genome, Human; Humans; Lod Score; Male; Mexican Americans; Middle Aged; Retinal Diseases; Siblings; Texas

Identification and analysis of functional elements in 1% of the human genome by the ENCODE pilot project. - Birney, Ewan; Stamatoyannopoulos, John A; Dutta, Anindya; Guigó, Roderic; Gingeras, Thomas R; Margulies, Elliott H; Weng, Zhiping; Snyder, Michael; Dermitzakis, Emmanouil T; Thurman, Robert E; Kuehn, Michael S; Taylor, Christopher M; et al. (Nature, 2007)
We report the generation and analysis of functional data from multiple, diverse experiments performed on a targeted 1% of the human genome as part of the pilot phase of the ENCODE Project. These data have been further integrated and augmented by a number of evolutionary and computational analyses. Together, our results advance the collective knowledge about human genome function in several major areas. First, our studies provide convincing evidence that the genome is pervasively transcribed, such that the majority of its bases can be found in primary transcripts, including non-protein-coding transcripts, and those that extensively overlap one another. Second, systematic examination of transcriptional regulation has yielded new understanding about transcription start sites, including their relationship to specific regulatory sequences and features of chromatin accessibility and histone modification. Third, a more sophisticated view of chromatin structure has emerged, including its inter-relationship with DNA replication and transcriptional regulation. Finally, integration of these new sources of information, in particular with respect to mammalian evolution based on inter- and intra-species sequence comparisons, has yielded new mechanistic and evolutionary insights concerning the functional landscape of the human genome. Together, these studies are defining a path for pursuit of a more comprehensive characterization of human genome function.
Keywords: Chromatin; Chromatin Immunoprecipitation; Conserved Sequence; DNA Replication; Evolution, Molecular; Exons; Genetic Variation; Genome, Human; Genomics; Heterozygote; Histones; Humans; Pilot Projects; Protein Binding; Regulatory Sequences, Nucleic Acid; RNA, Messenger; RNA, Untranslated; Transcription Factors; Transcription Initiation Site; Transcription, Genetic

MYH11 mutations result in a distinct vascular pathology driven by insulin-like growth factor 1 and angiotensin II. - Pannu, Hariyadarshi; Tran-Fadulu, Van; Papke, Christina L; Scherer, Steve; Liu, Yaozhong; Presley, Caroline; Guo, Dongchuan; Estrera, Anthony L; Safi, Hazim J; Brasier, Allan R; Vick, G Wesley; Marian, A J; et al. (Hum Mol Genet, 2007)
Non-syndromic thoracic aortic aneurysms and dissections (TAADs) are inherited in an autosomal dominant manner in approximately 20% of cases. Familial TAAD is genetically heterogeneous and four loci have been mapped for this disease to date, including a locus at 16p for TAAD associated with patent ductus arteriosus (PDA). The defective gene at the 16p locus has recently been identified as the smooth muscle cell (SMC)-specific myosin heavy chain gene (MYH11). On sequencing MYH11 in 93 families with TAAD alone and three families with TAAD/PDA, we identified novel mutations in two families with TAAD/PDA, but none in families with TAAD alone. Histopathological analysis of aortic sections from two individuals with MYH11 mutations revealed SMC disarray and focal hyperplasia of SMCs in the aortic media. SMC hyperplasia leading to significant lumen narrowing in some of the vessels of the adventitia was also observed. Insulin-like growth factor-1 (IGF-1) was upregulated in mutant aortas as well as explanted SMCs, but no increase in transforming growth factor-beta expression or downstream targets was observed. Enhanced expression of angiotensin-converting enzyme and markers of Angiotensin II (Ang II) vascular inflammation (macrophage inflammatory protein-1alpha and beta) were also found. These data suggest that MYH11 mutations are likely to be specific to the phenotype of TAAD/PDA and result in a distinct aortic and occlusive vascular pathology potentially driven by IGF-1 and Ang II.
Keywords: Adult; Amino Acid Sequence; Angiotensin II; Aortic Aneurysm, Thoracic; Child, Preschool; Ductus Arteriosus, Patent; Female; Genetic Testing; Humans; Insulin-Like Growth Factor I; Male; Middle Aged; Models, Molecular; Molecular Sequence Data; Mutation; Myosin Heavy Chains; Pedigree; Sequence Homology, Amino Acid; Vascular Diseases

nWayComp: a genome-wide sequence comparison tool for multiple strains/species of phylogenetically related microorganisms. - Yao, Jiqiang; Lin, Hong; Harshavardhan Doddapaneni; Civerolo, Edwin L (In Silico Biol, 2007)
The increasing number of whole genomic sequences of microorganisms has led to the complexity of genome-wide annotation and gene sequence comparison among multiple microorganisms. To address this problem, we have developed nWayComp software that compares DNA and protein sequences of phylogenetically-related microorganisms. This package integrates a series of bioinformatics tools such as BLAST, ClustalW, ALIGN, PHYLIP and PRIMER3 for sequence comparison. It searches for homologous sequences among multiple organisms and identifies genes that are unique to a particular organism. The homologous gene sets are then ranked in the descending order of the sequence similarity. For each set of homologous sequences, a table of sequence identity among homologous genes along with sequence variations such as SNPs and INDELS is developed, and a phylogenetic tree is constructed. In addition, a common set of primers that can amplify all the homologous sequences are generated. The nWayComp package provides users with a quick and convenient tool to compare genomic sequences among multiple organisms at the whole-genome level.
Keywords: Computational Biology; Databases, Genetic; Genes, Bacterial; Genome, Bacterial; Multigene Family; Phylogeny; Sequence Alignment; Sequence Homology; Software; Xanthomonas

Paradoxical DNA repair and peroxide resistance gene conservation in Bacillus pumilus SAFR-032. - Gioia, Jason; Yerrapragada, Shailaja; Qin, Xiang; Jiang, Huaiyang; Igboeli, Okezie C; Muzny, Donna; Dugan-Rocha, Shannon; Ding, Yan; Hawes, Alicia; Liu, Wen; Perez, Lesette; Kovar, Christie; et al. (PLoS One, 2007)
BACKGROUND: Bacillus spores are notoriously resistant to unfavorable conditions such as UV radiation, gamma-radiation, H2O2, desiccation, chemical disinfection, or starvation. Bacillus pumilus SAFR-032 survives standard decontamination procedures of the Jet Propulsion Lab spacecraft assembly facility, and both spores and vegetative cells of this strain exhibit elevated resistance to UV radiation and H2O2 compared to other Bacillus species. PRINCIPAL FINDINGS: The genome of B. pumilus SAFR-032 was sequenced and annotated. Lists of genes relevant to DNA repair and the oxidative stress response were generated and compared to B. subtilis and B. licheniformis. Differences in conservation of genes, gene order, and protein sequences are highlighted because they potentially explain the extreme resistance phenotype of B. pumilus. The B. pumilus genome includes genes not found in B. subtilis or B. licheniformis and conserved genes with sequence divergence, but paradoxically lacks several genes that function in UV or H2O2 resistance in other Bacillus species. SIGNIFICANCE: This study identifies several candidate genes for further research into UV and H2O2 resistance. These findings will help explain the resistance of B. pumilus and are applicable to understanding sterilization survival strategies of microbes.
Keywords: Bacillus; DNA Repair; Drug Resistance, Bacterial; Gamma Rays; Genes, Bacterial; Genome, Bacterial; Hydrogen Peroxide; Oxidative Stress; Sequence Analysis, DNA; Spores, Bacterial; Ultraviolet Rays

A preliminary study of the baboon prostate pathophysiology. - Mubiru, James N; Hubbard, Gene B; Dick, Edward J; Butler, Stephanie D; Valente, Anthony J; Troyer, Dean A; Jeffrey Rogers (Prostate, 2007)
BACKGROUND: Prostate cancer, benign prostatic hyperplasia, and prostatitis frequently affect men worldwide. At present there are no suitable animal models for these diseases. This study explores the potential use of the baboon as a model for prostatic diseases. METHODS: Prostates of 48 baboons of different ages were studied. Prostate specific antigen (PSA) and alpha-methyl-acyl-CoA racemase (AMACR) were localized in the different lobes of the prostate by Western blotting and immunohistochemistry. PSA in baboon serum was demonstrated by radioimmunoassay and western blotting. Baboon AMACR cDNA was cloned and its expression assayed in baboon tissues. RESULTS: The baboon prostate is anatomically and histologically similar to its human counterpart, with cranial and caudal lobes corresponding to central and peripheral zones of the human prostate. We found lymphocytic infiltration (91%), and sclerosing/atrophic lesions (34%). PSA tissue immunostaining intensity and alpha-methyl-acyl-CoA racemase (AMACR) gene expression levels differed between the cranial and caudal lobes of the prostate. The cloned baboon AMACR cDNA showed 96% homology with its human counterpart. Anti-human AMACR, PSA and basal keratin antibodies stained intracellular and basement membrane structures in the baboon prostate. The sclerosing/atrophic lesions were comparable to their human counterparts. CONCLUSIONS: The similarity of baboon prostate to its human counterpart and the fact that human antibodies (AMACR, PSA, basal keratin) are reactive to baboon prostatic proteins indicates that the baboon is a promising model for human prostatic diseases.
Keywords: Animals; Cloning, Molecular; Disease Models, Animal; Immunoblotting; Immunohistochemistry; Male; Papio hamadryas; Pilot Projects; Prostate; Prostate-Specific Antigen; Prostatic Diseases; Racemases and Epimerases; Reverse Transcriptase Polymerase Chain Reaction; RNA

Termination of DNA synthesis by N6-alkylated, not 3'-O-alkylated, photocleavable 2'-deoxyadenosine triphosphates. - Wu, Weidong; Stupi, Brian P; Litosh, Vladislav A; Mansouri, Dena; Farley, Demetra; Morris, Sidney; Metzker, Sherry; Metzker, Michael L (Nucleic Acids Res, 2007)
The Human Genome Project has facilitated the sequencing of many species, yet the current Sanger method is too expensive, labor intensive and time consuming to accomplish medical resequencing of human genomes en masse. Of the 'next-generation' technologies, cyclic reversible termination (CRT) is a promising method with the goal of producing accurate sequence information at a fraction of the cost and effort. The foundation of this approach is the reversible terminator (RT), its chemical and biological properties of which directly impact the performance of the sequencing technology. Here, we have discovered a novel paradigm in RT chemistry, the attachment of a photocleavable, 2-nitrobenzyl group to the N(6)-position of 2'-deoxyadenosine triphosphate (dATP), which, upon incorporation, terminates DNA synthesis. The 3'-OH group of the N(6)-(2-nitrobenzyl)-dATP remains unblocked, providing favorable incorporation and termination properties for several commercially available DNA polymerases while maintaining good discrimination against mismatch incorporations. Upon removal of the 2-nitrobenzyl group with UV light, the natural nucleotide is restored without molecular scarring. A five-base experiment, illustrating the exquisite, stepwise addition through a homopolymer repeat, demonstrates the applicability of the N(6)-(2-nitrobenzyl)-dATP as an ideal RT for CRT sequencing.
Keywords: Alkylation; Base Pair Mismatch; Deoxyadenine Nucleotides; Deoxyadenosines; DNA; DNA-Directed DNA Polymerase; Photochemistry; Sequence Analysis, DNA; Ultraviolet Rays

Trisomy 17 in a baboon (Papio hamadryas) with polydactyly, patent foramen ovale and pyelectasis. - Moore, Charleen M; Hubbard, Gene B; Dick, Edward; Dunn, Betty G; Raveendran, Muthuswamy; Jeffrey Rogers; Williams, Vick; Gomez, Jeremiah J; Butler, Stephanie D; Leland, M Michelle; Schlabritz-Loutsevitch, Natalia E (Am J Primatol, 2007)
Trisomy 13 in humans is the third most common autosomal abnormality at birth, after trisomy 21 and trisomy 18. It has a reported incidence of between 1:5,000 and 1:30,000 live births. It is associated with multiple abnormalities, many of which shorten lifespan. We describe here the first reported case of a baboon (Papio hamadryas) with trisomy of chromosome 17, which is homologous to human chromosome 13. The trisomic infant was born to a consanguineous pair of baboons and had morphological characteristics similar to those observed in human trisomy 13, including bilateral polydactyly in the upper limbs, a patent foramen ovale, and pyelectasis. Molecular DNA analysis using human chromosome 13 markers was consistent with the affected infant inheriting two copies of chromosome 17 derived from the same parental chromosome. This trisomy was, therefore, due to either an error in meiosis II or the result of postzygotic nondisjunction. The parental origin, however, could not be determined.
Keywords: Animals; Arm; Chromosomes, Mammalian; Dilatation, Pathologic; Female; Heart Atria; Heart Septal Defects, Atrial; Humans; Inbreeding; Kidney Pelvis; Male; Papio hamadryas; Polydactyly; Trisomy

Widespread lateral gene transfer from intracellular bacteria to multicellular eukaryotes. - Dunning Hotopp, Julie C; Clark, Michael E; Oliveira, Deodoro C S G; Foster, Jeremy M; Fischer, Peter; Muñoz Torres, Mónica C; Giebel, Jonathan D; Kumar, Nikhil; Ishmael, Nadeeza; Wang, Shiliang; Ingram, Jessica; Nene, Rahul V; et al. (Science, 2007)
Although common among bacteria, lateral gene transfer-the movement of genes between distantly related organisms-is thought to occur only rarely between bacteria and multicellular eukaryotes. However, the presence of endosymbionts, such as Wolbachia pipientis, within some eukaryotic germlines may facilitate bacterial gene transfers to eukaryotic host genomes. We therefore examined host genomes for evidence of gene transfer events from Wolbachia bacteria to their hosts. We found and confirmed transfers into the genomes of four insect and four nematode species that range from nearly the entire Wolbachia genome (>1 megabase) to short (<500 base pairs) insertions. Potential Wolbachia-to-host transfers were also detected computationally in three additional sequenced insect genomes. We also show that some of these inserted Wolbachia genes are transcribed within eukaryotic cells lacking endosymbionts. Therefore, heritable lateral gene transfer occurs into eukaryotic hosts from their prokaryote symbionts, potentially providing a mechanism for acquisition of new genes and functions.
Keywords: Animals; Chromosome Mapping; Crosses, Genetic; DNA, Bacterial; Drosophila; Female; Gene Transfer, Horizontal; Genes, Bacterial; In Situ Hybridization, Fluorescence; Insecta; Male; Molecular Sequence Data; Nematoda; Retroelements; Reverse Transcriptase Polymerase Chain Reaction; Sequence Analysis, DNA; Symbiosis; Wolbachia

Analysis of the genome-wide variations among multiple strains of the plant pathogenic bacterium Xylella fastidiosa. - Doddapaneni, Harshavardhan; Yao, Jiqiang; Lin, Hong; Walker, M Andrew; Civerolo, Edwin L (BMC Genomics, 2006)
BACKGROUND: The Gram-negative, xylem-limited phytopathogenic bacterium Xylella fastidiosa is responsible for causing economically important diseases in grapevine, citrus and many other plant species. Despite its economic impact, relatively little is known about the genomic variations among strains isolated from different hosts and their influence on the population genetics of this pathogen. With the availability of genome sequence information for four strains, it is now possible to perform genome-wide analyses to identify and categorize such DNA variations and to understand their influence on strain functional divergence. RESULTS: There are 1,579 genes and 194 non-coding homologous sequences present in the genomes of all four strains, representing a 76. 2% conservation of the sequenced genome. About 60% of the X. fastidiosa unique sequences exist as tandem gene clusters of 6 or more genes. Multiple alignments identified 12,754 SNPs and 14,449 INDELs in the 1528 common genes and 20,779 SNPs and 10,075 INDELs in the 194 non-coding sequences. The average SNP frequency was 1.08 x 10(-2) per base pair of DNA and the average INDEL frequency was 2.06 x 10(-2) per base pair of DNA. On an average, 60.33% of the SNPs were synonymous type while 39.67% were non-synonymous type. The mutation frequency, primarily in the form of external INDELs was the main type of sequence variation. The relative similarity between the strains was discussed according to the INDEL and SNP differences. The number of genes unique to each strain were 60 (9a5c), 54 (Dixon), 83 (Ann1) and 9 (Temecula-1). A sub-set of the strain specific genes showed significant differences in terms of their codon usage and GC composition from the native genes suggesting their xenologous origin. Tandem repeat analysis of the genomic sequences of the four strains identified associations of repeat sequences with hypothetical and phage related functions. CONCLUSION: INDELs and strain specific genes have been identified as the main source of variations among strains, with individual strains showing different rates of genome evolution. Based on these genome comparisons, it appears that the Pierce's disease strain Temecula-1 genome represents the ancestral genome of the X. fastidiosa. Results of this analysis are publicly available in the form of a web database.
Keywords: Analysis of Variance; Computational Biology; Databases, Genetic; Fimbriae, Bacterial; Genes, Bacterial; Genome, Bacterial; Multigene Family; Mutation; Plant Diseases; Plants; Polymorphism, Single Nucleotide; Species Specificity; Xylella

Chromosome rearrangement and diversification of Francisella tularensis revealed by the type B (OSU18) genome sequence. - Petrosino, Joseph F; Xiang, Qin; Karpathy, Sandor E; Jiang, Huaiyang; Yerrapragada, Shailaja; Liu, Yamei; Gioia, Jason; Hemphill, Lisa; Gonzalez, Arely; Raghavan, T M; Uzman, Akif; Fox, George E; et al. (J Bacteriol, 2006)
The gamma-proteobacterium Francisella tularensis is one of the most infectious human pathogens, and the highly virulent organism F. tularensis subsp. tularensis (type A) and less virulent organism F. tularensis subsp. holarctica (type B) are most commonly associated with significant disease in humans and animals. Here we report the complete genome sequence and annotation for a low-passage type B strain (OSU18) isolated from a dead beaver found near Red Rock, Okla., in 1978. A comparison of the F. tularensis subsp. holarctica sequence with that of F. tularensis subsp. tularensis strain Schu4 (P. Larsson et al., Nat. Genet. 37:153-159, 2005) highlighted genetic differences that may underlie different pathogenicity phenotypes and the evolutionary relationship between type A and type B strains. Despite extensive DNA sequence identity, the most significant difference between type A and type B isolates is the striking amount of genomic rearrangement that exists between the strains. All but two rearrangements can be attributed to homologous recombination occurring between two prominent insertion elements, ISFtu1 and ISFtu2. Numerous pseudogenes have been found in the genomes and are likely contributors to the difference in virulence between the strains. In contrast, no rearrangements have been observed between the OSU18 genome and the genome of the type B live vaccine strain (LVS), and only 448 polymorphisms have been found within non-transposase-coding sequences whose homologs are intact in OSU18. Nonconservative differences between the two strains likely include the LVS attenuating mutation(s).
Keywords: Chromosomes, Bacterial; DNA Transposable Elements; DNA, Bacterial; Evolution, Molecular; Francisella tularensis; Gene Rearrangement; Genome, Bacterial; Molecular Sequence Data; Polymorphism, Genetic; Pseudogenes; Recombination, Genetic; Sequence Analysis, DNA; Sequence Homology; Virulence

Community annotation: procedures, protocols, and supporting tools. - Elsik, Christine G; Worley, Kim C; Zhang, Lan; Milshina, Natalia V; Jiang, Huaiyang; Reese, Justin T; Childs, Kevin L; Venkatraman, Anand; Dickens, C Michael; Weinstock, George M; Richard A Gibbs (Genome Res, 2006)
Investigators at the Baylor College of Medicine Human Genome Sequencing Center (BCM-HGSC) and BeeBase organized a community-wide effort to manually annotate the honey bee (Apis mellifera) genome. Although various strategies for manual annotation have been used in the past, the value of dispersed community annotation has not yet been demonstrated. Here we make a case for the merit of dispersed community annotation. We present annotation procedures, standard protocols, and tools used for sequence analysis, data submission, and data management. We also report lessons learned from this dispersed community annotation effort for a metazoan genome.
Keywords: Animals; Bees; Databases, Genetic; Genome, Human; Genomics; Humans; Models, Genetic; Molecular Sequence Data; Sequence Analysis

Complete nucleotide sequence of a P2 family lysogenic bacteriophage, varphiMhaA1-PHL101, from Mannheimia haemolytica serotype A1. - Highlander, Sarah K; Weissenberger, Sarah; Alvarez, Laura E; Weinstock, George M; Berget, Peter B (Virology, 2006)
The 34,525 nucleotide sequence of a double-stranded DNA bacteriophage (phiMhaA1-PHL101) from Mannheimia haemolytica serotype A1 has been determined. The phage encodes 50 open reading frames. Twenty-three of the proteins are similar to proteins of the P2 family of phages. Other protein sequences are most similar to possible prophage sequences from the draft genome of Histophilus somni 2336. Fourteen open reading frames encode proteins with no known homolog. The P2 orthologues are collinear in phiMhaA1-PHL101, with the exception of the phage tail protein gene T, which maps in a unique location between the S and V genes. The phage ORFs can be arranged into 17 possible transcriptional units and many of the genes are predicted to be translationally coupled. Southern blot analysis revealed phiMhaA1-PHL101 sequences in other A1 isolates as well as in serotype A5, A6, A9, and A12 strains of M. haemolytica, but not in the related organisms, Mannheimia glucosida or Pasteurella trehalosi.
Keywords: Bacteriophages; Base Composition; Base Sequence; DNA Replication; DNA Viruses; DNA, Viral; Gene Expression Regulation, Viral; Mannheimia haemolytica; Transcription, Genetic; Viral Proteins

Desmosomal dysfunction due to mutations in desmoplakin causes arrhythmogenic right ventricular dysplasia/cardiomyopathy. - Yang, Zhao; Bowles, Neil E; Steven E Scherer; Taylor, Michael D; Kearney, Debra L; Ge, Shuping; Nadvoretskiy, Vyacheslav V; DeFreitas, Gilberto; Carabello, Blasé; Brandon, Lois I; Godsel, Lisa M; Green, Kathleen J; et al. (Circ Res, 2006)
Arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) is characterized by progressive degeneration of the right ventricular myocardium, ventricular arrhythmias, fibrous-fatty replacement, and increased risk of sudden death. Mutations in 6 genes, including 4 encoding desmosomal proteins (Junctional plakoglobin (JUP), Desmoplakin (DSP), Plakophilin 2, and Desmoglein 2), have been identified in patients with ARVD/C. Mutation analysis of 66 probands identified 4 variants in DSP; V30M, Q90R, W233X, and R2834H. To establish a cause and effect relationship between those DSP missense mutations and ARVD/C, we performed in vitro and in vivo analyses of the mutated proteins. Unlike wild-type (WT) DSP, the N-terminal mutants (V30M and Q90R) failed to localize to the cell membrane in desomosome-forming cell line and failed to bind to and coimmunoprecipitate JUP. Multiple attempts to generate N-terminal DSP (V30M and Q90R) cardiac-specific transgenes have failed: analysis of embryos revealed evidence of profound ventricular dilation, which likely resulted in embryonic lethality. We were able to develop transgenic (Tg) mice with cardiac-restricted overexpression of the C-terminal mutant (R2834H) or WT DSP. Whereas mice overexpressing WT DSP had no detectable histologic, morphological, or functional cardiac changes, the R2834H-Tg mice had increased cardiomyocyte apoptosis, cardiac fibrosis, and lipid accumulation, along with ventricular enlargement and cardiac dysfunction in both ventricles. These mice also displayed interruption of DSP-desmin interaction at intercalated discs (IDs) and marked ultra-structural changes of IDs. These data suggest DSP expression in cardiomyocytes is crucial for maintaining cardiac tissue integrity, and DSP abnormalities result in ARVD/C by cardiomyocyte death, changes in lipid metabolism, and defects in cardiac development.
Keywords: Animals; Apoptosis; Arrhythmogenic Right Ventricular Dysplasia; Cardiomyopathies; Cell Communication; Cell Line, Tumor; Desmoplakins; Desmosomes; DNA Mutational Analysis; Embryo, Mammalian; Heart; Humans; Intercellular Junctions; Lipid Metabolism; Mice; Mice, Transgenic; Mutation, Missense; Myocytes, Cardiac

The DNA sequence, annotation and analysis of human chromosome 3. - Donna M Muzny; Steven E Scherer; Kaul, Rajinder; Wang, Jing; Yu, Jun; Sudbrak, Ralf; Buhay, Christian J; Rui Chen; Cree, Andrew; Ding, Yan; Dugan-Rocha, Shannon; Gill, Rachel; et al. (Nature, 2006)
After the completion of a draft human genome sequence, the International Human Genome Sequencing Consortium has proceeded to finish and annotate each of the 24 chromosomes comprising the human genome. Here we describe the sequencing and analysis of human chromosome 3, one of the largest human chromosomes. Chromosome 3 comprises just four contigs, one of which currently represents the longest unbroken stretch of finished DNA sequence known so far. The chromosome is remarkable in having the lowest rate of segmental duplication in the genome. It also includes a chemokine receptor gene cluster as well as numerous loci involved in multiple human cancers such as the gene encoding FHIT, which contains the most common constitutive fragile site in the genome, FRA3B. Using genomic sequence from chimpanzee and rhesus macaque, we were able to characterize the breakpoints defining a large pericentric inversion that occurred some time after the split of Homininae from Ponginae, and propose an evolutionary history of the inversion.
Keywords: Animals; Base Sequence; Chromosome Breakage; Chromosome Inversion; Chromosomes, Human, Pair 3; Contig Mapping; CpG Islands; DNA, Complementary; Evolution, Molecular; Expressed Sequence Tags; Human Genome Project; Humans; Macaca mulatta; Molecular Sequence Data; Pan troglodytes; Sequence Analysis, DNA; Synteny

Escherichia coli DNA polymerase II can efficiently bypass 3,N(4)-ethenocytosine lesions in vitro and in vivo. - Al Mamun, Abu Amar M; Humayun, M Zafri (Mutat Res, 2006)
Escherichia coli DNA polymerase II (pol-II) is a highly conserved protein that appears to have a role in replication restart, as well as in translesion synthesis across specific DNA adducts under some conditions. Here, we have investigated the effects of elevated expression of pol-II (without concomitant SOS induction) on translesion DNA synthesis and mutagenesis at 3,N(4)-ethenocytosine (varepsilonC), a highly mutagenic DNA lesion induced by oxidative stress as well as by exposure to industrial chemicals such as vinyl chloride. In normal cells, survival of transfected M13 single-stranded DNA bearing a single varepsilonC residue (varepsilonC-ssDNA) is about 20% of that of control DNA, with about 5% of the progeny phage bearing a mutation at the lesion site. Most mutations are C-->A and C-->T, with a slight predominance of transversions over transitions. In contrast, in cells expressing elevated levels of pol-II, survival of varepsilonC-ssDNA is close to 100%, with a concomitant mutation frequency of almost 99% suggesting highly efficient translesion DNA synthesis. Furthermore, an overwhelming majority of mutations at varepsilonC are C-->T transitions. Purified pol-II efficiently catalyzes translesion synthesis at varepsilonC in vitro, accompanied by high levels of mutagenesis with the same specificity. These results suggest that the observed in vivo effects in pol-II over-expressing cells are due to pol-II-mediated DNA synthesis. Introduction of mutations in the carboxy terminus region (beta interaction domain) of polB eliminates in vivo translesion synthesis at varepsilonC, suggesting that the ability of pol-II to compete with pol-III requires interaction with the beta processivity subunit of pol-III. Thus, pol-II can compete with pol-III for translesion synthesis.
Keywords: Animals; Base Sequence; Cattle; Cytosine; DNA Polymerase II; DNA Primers; Escherichia coli; Mutagenesis

Evidence for alternative candidate genes near RB1 involved in clonal expansion of in situ urothelial neoplasia. - Kim, Mi-Sook; Jeong, Joon; Majewski, Tadeusz; Kram, Andrzej; Yoon, Dong-Sup; Zhang, Ruo-Dan; Li, Jun-Zhi; Ptaszynski, Konrad; Kuang, Tang C; Zhou, Jain-Hua; Sathyanarayana, Ubaradka G; Tuziak, Tomasz; et al. (Lab Invest, 2006)
In this paper, we present whole-organ histologic and genetic mapping studies using hypervariable DNA markers on chromosome 13 and then integrate the recombination- and single-nucleotide polymorphic sites (SNPs)-based deletion maps with the annotated genome sequence. Using bladders resected from patients with invasive urothelial carcinoma, we studied allelic patterns of 40 microsatellite markers mapping to all regions of chromosome 13 and 79 SNPs located within the 13q14 region containing the RB1 gene. A whole-organ histologic and genetic mapping strategy was used to identify the evolution of allelic losses on chromosome 13 during the progression of bladder neoplasia. Markers mapping to chromosomal regions involved in clonal expansion of preneoplastic intraurothelial lesions were subsequently tested in 25 tumors and 21 voided urine samples of patients with bladder cancer. Four clusters of allelic losses mapping to distinct regions of chromosome 13 were identified. Markers mapping to the 13q14 region that is flanked by D13S263 and D13S276, which contains the RB1 gene, showed allelic losses associated with early clonal expansion of intraurothelial neoplasia. Such losses could be identified in approximately 32% bladder tumor tissue samples and 38% of voided urines from patients with bladder cancer. The integration of distribution patterns of clonal allelic losses revealed by the microsatellite markers with those obtained by genotyping of SNPs disclosed that the loss within an approximately 4-Mb segment centered around RB1 may represent an incipient event in bladder neoplasia. However, the inactivation of RB1 occurred later and was associated with the onset of severe dysplasia/carcinoma in situ. Our studies provide evidence for the presence of critical alternative candidate genes mapping to the 13q14 region that are involved in clonal expansion of neoplasia within the bladder antecedent to the inactivation of the RB1 gene.
Keywords: Aged; Aged, 80 and over; Alleles; Chromosome Mapping; Chromosomes, Human, Pair 13; DNA Methylation; Humans; Immunohistochemistry; Middle Aged; Polymerase Chain Reaction; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Recombination, Genetic; Retinoblastoma Protein; Urinary Bladder Neoplasms

The generation of a conditional Fmr1 knock out mouse model to study Fmrp function in vivo. - Mientjes, E J; Nieuwenhuizen, I; Kirkpatrick, L; Zu, T; Hoogeveen-Westerveld, M; Severijnen, L; Rifé, M; Willemsen, R; Nelson, D L; Oostra, B A (Neurobiol Dis, 2006)
The FMR1 gene, mutated in Fragile X syndrome patients, has been modeled in mice with a neomycin cassette inserted in exon 5 of the mouse Fmr1 gene creating an Fmr1 knockout (Fmr1 KO) allele. This results in animals lacking Fmr1 protein (Fmrp) expression in all tissues. We have created a new, more versatile Fmr1 in vivo KO model (Fmr1 KO2) and generated conditional Fmr1 KO (CKO) mice by flanking the promoter and first exon of Fmr1 with lox P sites. This enables us to create a null allele in specific cell types and at specific time points by crossing Fmr1 CKO mice with tissue specific or inducible cre-recombinase expressing mice. The new Fmr1 KO2 line does not express any Fmrp and also lacks detectable Fmr1 transcripts. Crossing the Fmr1 CKO line with a Purkinje cell-specific cre-recombinase expresser produces mice that are null for Fmr1 in Purkinje neurons but wild type in all other cell types.
Keywords: Animals; Blotting, Western; Disease Models, Animal; Fragile X Mental Retardation Protein; Fragile X Syndrome; Immunohistochemistry; Mice; Mice, Knockout; Purkinje Cells; Reverse Transcriptase Polymerase Chain Reaction

Genetics. No longer de-identified. - McGuire, Amy L; Richard A Gibbs (Science, 2006)
Keywords: Access to Information; Databases, Genetic; Ethics Committees, Research; Genetic Privacy; Genetic Research; Health Insurance Portability and Accountability Act; Humans; Information Dissemination; Informed Consent; Polymorphism, Single Nucleotide; Research Subjects; Sequence Analysis, DNA; United States

The genome sequence of Mannheimia haemolytica A1: insights into virulence, natural competence, and Pasteurellaceae phylogeny. - Gioia, Jason; Qin, Xiang; Jiang, Huaiyang; Clinkenbeard, Kenneth; Lo, Reggie; Liu, Yamei; Fox, George E; Yerrapragada, Shailaja; McLeod, Michael P; McNeill, Thomas Z; Hemphill, Lisa; Sodergren, Erica; et al. (J Bacteriol, 2006)
The draft genome sequence of Mannheimia haemolytica A1, the causative agent of bovine respiratory disease complex (BRDC), is presented. Strain ATCC BAA-410, isolated from the lung of a calf with BRDC, was the DNA source. The annotated genome includes 2,839 coding sequences, 1,966 of which were assigned a function and 436 of which are unique to M. haemolytica. Through genome annotation many features of interest were identified, including bacteriophages and genes related to virulence, natural competence, and transcriptional regulation. In addition to previously described virulence factors, M. haemolytica encodes adhesins, including the filamentous hemagglutinin FhaB and two trimeric autotransporter adhesins. Two dual-function immunoglobulin-protease/adhesins are also present, as is a third immunoglobulin protease. Genes related to iron acquisition and drug resistance were identified and are likely important for survival in the host and virulence. Analysis of the genome indicates that M. haemolytica is naturally competent, as genes for natural competence and DNA uptake signal sequences (USS) are present. Comparison of competence loci and USS in other species in the family Pasteurellaceae indicates that M. haemolytica, Actinobacillus pleuropneumoniae, and Haemophilus ducreyi form a lineage distinct from other Pasteurellaceae. This observation was supported by a phylogenetic analysis using sequences of predicted housekeeping genes.
Keywords: Actinobacillus pleuropneumoniae; Adhesins, Bacterial; DNA, Bacterial; Gene Expression Regulation, Bacterial; Genome, Bacterial; Haemophilus ducreyi; Mannheimia haemolytica; Phylogeny; Prophages; Sequence Analysis, DNA; Transcription, Genetic; Transformation, Bacterial; Virulence

Genome-wide identification of direct targets of the Drosophila retinal determination protein Eyeless. - Ostrin, Edwin J; Li, Yumei; Hoffman, Kristi; Liu, Jing; Wang, Keqing; Zhang, Li; Mardon, Graeme; Chen, Rui (Genome Res, 2006)
The discovery of direct downstream targets of transcription factors (TFs) is necessary for understanding the genetic mechanisms underlying complex, highly regulated processes such as development. In this report, we have used a combinatorial strategy to conduct a genome-wide search for novel direct targets of Eyeless (Ey), a key transcription factor controlling early eye development in Drosophila. To overcome the lack of high-quality consensus binding site sequences, phylogenetic shadowing of known Ey binding sites in sine oculis (so) was used to construct a position weight matrix (PWM) of the Ey protein. This PWM was then used for in silico prediction of potential binding sites in the Drosophila melanogaster genome. To reduce the false positive rate, conservation of these potential binding sites was assessed by comparing the genomic sequences from seven Drosophila species. In parallel, microarray analysis of wild-type versus ectopic ey-expressing tissue, followed by microarray-based epistasis experiments in an atonal (ato) mutant background, identified 188 genes induced by ey. Intersection of in silico predicted conserved Ey binding sites with the candidate gene list produced through expression profiling yields a list of 20 putative ey-induced, eye-enriched, ato-independent, direct targets of Ey. The accuracy of this list of genes was confirmed using both in vitro and in vivo methods. Initial analysis reveals three genes, eyes absent, shifted, and Optix, as novel direct targets of Ey. These results suggest that the integrated strategy of computational biology, genomics, and genetics is a powerful approach to identify direct downstream targets for any transcription factor genome-wide.
Keywords: Animals; Chromosome Mapping; DNA-Binding Proteins; Drosophila; Drosophila Proteins; Gene Expression Profiling; Gene Expression Regulation; Genome, Insect; Oligonucleotide Array Sequence Analysis; Regulatory Elements, Transcriptional

Hypermutagenesis in mutA cells is mediated by mistranslational corruption of polymerase, and is accompanied by replication fork collapse. - Al Mamun, Abu Amar M; Gautam, Satyendra; Humayun, M Zafri (Mol Microbiol, 2006)
Elevated mistranslation induces a mutator response termed translational stress-induced mutagenesis (TSM) that is mediated by an unidentified modification of DNA polymerase III. Here we address two questions: (i) does TSM result from direct polymerase corruption, or from an indirect pathway triggered by increased protein turnover? (ii) Why are homologous recombination functions required for the expression of TSM under certain conditions, but not others? We show that replication of bacteriophage T4 in cells expressing the mutA allele of the glyVtRNA gene (Asp-Gly mistranslation), leads to both increased mutagenesis, and to an altered mutational specificity, results that strongly support mistranslational corruption of DNA polymerase. We also show that expression of mutA, which confers a recA-dependent mutator phenotype, leads to increased lambdoid prophage induction (selectable in vivo expression technology assay), suggesting that replication fork collapse occurs more frequently in mutA cells relative to control cells. No such increase in prophage induction is seen in cells expressing alaVGlu tRNA (Glu-->Ala mistranslation), in which the mutator phenotype is recA-independent. We propose that replication fork collapse accompanies episodic hypermutagenic replication cycles in mutA cells, requiring homologous recombination functions for fork recovery, and therefore, for mutation recovery. These findings highlight hitherto under-appreciated links among translation, replication and recombination, and suggest that translational fidelity, which is affected by genetic and environmental signals, is a key modulator of replication fidelity.
Keywords: Bacteriophage T4; Base Sequence; DNA Mutational Analysis; DNA Polymerase III; DNA Replication; DNA, Bacterial; Escherichia coli; Escherichia coli Proteins; Models, Genetic; Molecular Sequence Data; Mutagenesis; Nucleic Acid Conformation; Plasmids; Protein Biosynthesis; Rec A Recombinases; Sequence Analysis, DNA; SOS Response, Genetics

Meeting the growing demands of genetic research. - McGuire, Amy L; Richard A Gibbs (J Law Med Ethics, 2006)
Keywords: Databases, Genetic; Genetic Research; Genomics; Health Insurance Portability and Accountability Act; Humans; Informed Consent; United States

Mutant analysis of the Shal (Kv4) voltage-gated fast transient K+ channel in Caenorhabditis elegans. - Fawcett, Gloria L; Santi, Celia M; Butler, Alice; Harris, Thanawath; Covarrubias, Manuel; Salkoff, Lawrence (J Biol Chem, 2006)
Shal (Kv4) alpha-subunits are the most conserved among the family of voltage-gated potassium channels. Previous work has shown that the Shal potassium channel subfamily underlies the predominant fast transient outward current in Drosophila neurons (Tsunoda, S., and Salkoff, L. (1995) J. Neurosci. 15, 1741-1754) and the fast transient outward current in mouse heart muscle (Guo, W., Jung, W. E., Marionneau, C., Aimond, F., Xu, H., Yamada, K. A., Schwarz, T. L., Demolombe, S., and Nerbonne, J. M. (2005) Circ. Res. 97, 1342-1350). We show that Shal channels also play a role as the predominant transient outward current in Caenorhabditis elegans muscle. Green fluorescent protein promoter experiments also revealed SHL-1 expression in a subset of neurons as well as in C. elegans body wall muscle and in male-specific diagonal muscles. The shl-1 (ok1168) null mutant removed all fast transient outward current from muscle cells. SHL-1 currents strongly resembled Shal currents in other species except that they were active in a more depolarized voltage range. We also determined that the remaining delayed-rectifier current in cultured myocytes was carried by the Shaker ortholog SHK-1. In shl-1 (ok1168) mutants there was a significant compensatory increase in the SHK-1 current. Male shl-1 (ok1168) animals exhibited reduced mating efficiency resulting from an apparent difficulty in locating the hermaphrodite vulva. SHL-1 channels are apparently important in fine-tuning complex behaviors, such as mating, that play a crucial role in the survival and propagation of the species.
Keywords: Animals; Caenorhabditis elegans; DNA Mutational Analysis; Electrophysiology; Genes, Dominant; Green Fluorescent Proteins; Neurons; Oocytes; Phenotype; Promoter Regions, Genetic; RNA Interference; RNA, Complementary; Shal Potassium Channels; Xenopus

New technique for lacrimal system intubation. - Wang, Linghua; Chen, Dong; Wang, Zhichong (Am J Ophthalmol, 2006)
PURPOSE: To propose a new technique for silicone intubation in disorders of the lacrimal system in children and adults. DESIGN: Retrospective, noncomparative case series. METHODS: The surgery was performed in 513 eyes of 426 patients from March 2003 to July 2005 in our hospital. With the help of a so-called soft probe and intranasal endoscope, silicone tubes were inserted through both puncta into nasolacrimal duct and left in place for three to six months. RESULTS: The surgery was performed successfully in all cases. No intraoperative complications were found in the procedure. Tubes were removed between 2.1 and 5.3 months (mean 3.4 months) after surgery. Mean follow-up time after tube removal was 15.1 months (range 3.3 to 27.5 months). Tube displacement occurred in 11 cases (2.14%); no other complications associated with silicone tubes, such as granuloma formation or corneal erosion, occurred. All the tubes were removed successfully. No ophthalmic injuries occurred during tube removal. CONCLUSIONS: The technique proved to be effective in both children and adults. This technique, which is atraumatic, easy to perform, time-saving, and better tolerated, may be considered as an alternative method for lacrimal system intubation.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; Device Removal; Endoscopy; Female; Humans; Infant; Intraoperative Complications; Intubation; Lacrimal Duct Obstruction; Male; Middle Aged; Nasolacrimal Duct; Postoperative Complications; Retrospective Studies; Silicones; Time Factors

P-selectin Thr715Pro polymorphism predicts P-selectin levels but not risk of incident coronary heart disease or ischemic stroke in a cohort of 14595 participants: the Atherosclerosis Risk in Communities Study. - Volcik, Kelly A; Ballantyne, Christie M; Coresh, Josef; Folsom, Aaron R; Wu, Kenneth K; Eric Boerwinkle (Atherosclerosis, 2006)
OBJECTIVE: Inflammation, characterized by the recruitment/adhesion of circulating leukocytes by cellular adhesion molecules, plays an important role in the pathogenesis of atherosclerosis. Genetic analyses of P-selectin, a key adhesion molecule in the progression of atherosclerosis, have provided conflicting results regarding the role of variation within the P-selectin gene and risk for heart disease. No studies have examined the association of this polymorphism with stroke. Therefore, we examined the association of the P-selectin Thr715Pro polymorphism with incident coronary heart disease (CHD) and ischemic stroke among 14595 participants in the prospective cohort of the Atherosclerosis Risk in Communities (ARIC) Study. METHODS AND RESULTS: Incidences of ischemic stroke and CHD were determined through annual telephone calls and hospital and death certificate surveillance. Four hundred fifty-six validated ischemic stroke and 1533 CHD events were identified. P-selectin Pro715 allele frequency was determined in whites and African-Americans, respectively, for CHD cases (0.11, 0.02), CHD non-cases (0.11, 0.02), ischemic stroke cases (0.11, 0.02) and stroke non-cases (0.11, 0.02). The P-selectin Pro715 allele was not associated with risk of CHD or stroke in whites or African-Americans. P-selectin levels, however, were associated with the P-selectin Thr715Pro variant in whites, but not in African-Americans. CONCLUSIONS: Genotypes carrying the P-selectin Pro715 variant allele are associated with decreased P-selectin levels compared to the homozygous wild-type genotype in whites. The P-selectin Thr715Pro polymorphism is not associated with incident CHD or ischemic stroke in either whites or African-Americans.
Keywords: Alleles; Biomarkers; Coronary Artery Disease; Disease Progression; Female; Follow-Up Studies; Gene Frequency; Genotype; Humans; Incidence; Male; Middle Aged; P-Selectin; Polymorphism, Genetic; Prospective Studies; Risk Factors; Stroke; United States

Recurrent duplication-driven transposition of DNA during hominoid evolution. - Johnson, Matthew E; Cheng, Ze; Morrison, V Anne; Scherer, Steven; Ventura, Mario; Gibbs, Richard A; Green, Eric D; Eichler, Evan E (Proc Natl Acad Sci U S A, 2006)
The underlying mechanism by which the interspersed pattern of human segmental duplications has evolved is unknown. Based on a comparative analysis of primate genomes, we show that a particular segmental duplication (LCR16a) has been the source locus for the formation of the majority of intrachromosomal duplications blocks on human chromosome 16. We provide evidence that this particular segment has been active independently in each great ape and human lineage at different points during evolution. Euchromatic sequence that flanks sites of LCR16a integration are frequently lineage-specific duplications. This process has mobilized duplication blocks (15-200 kb in size) to new genomic locations in each species. Breakpoint analysis of lineage-specific insertions suggests coordinated deletion of repeat-rich DNA at the target site, in some cases deleting genes in that species. Our data support a model of duplication where the probability that a segment of DNA becomes duplicated is determined by its proximity to core duplicons, such as LCR16a.
Keywords: Animals; Base Sequence; Biological Evolution; Chromosomes, Human, Pair 16; DNA; DNA Transposable Elements; Evolution, Molecular; Gene Duplication; Hominidae; Humans; Molecular Sequence Data; Phylogeny; Sequence Alignment; Sequence Analysis, DNA

Shedding genomic light on Aristotle's lantern. - Sodergren, Erica; Shen, Yufeng; Song, Xingzhi; Zhang, Lan; Richard A Gibbs; Weinstock, George M (Dev Biol, 2006)
Sea urchins have proved fascinating to biologists since the time of Aristotle who compared the appearance of their bony mouth structure to a lantern in The History of Animals. Throughout modern times it has been a model system for research in developmental biology. Now, the genome of the sea urchin Strongylocentrotus purpuratus is the first echinoderm genome to be sequenced. A high quality draft sequence assembly was produced using the Atlas assembler to combine whole genome shotgun sequences with sequences from a collection of BACs selected to form a minimal tiling path along the genome. A formidable challenge was presented by the high degree of heterozygosity between the two haplotypes of the selected male representative of this marine organism. This was overcome by use of the BAC tiling path backbone, in which each BAC represents a single haplotype, as well as by improvements in the Atlas software. Another innovation introduced in this project was the sequencing of pools of tiling path BACs rather than individual BAC sequencing. The Clone-Array Pooled Shotgun Strategy greatly reduced the cost and time devoted to preparing shotgun libraries from BAC clones. The genome sequence was analyzed with several gene prediction methods to produce a comprehensive gene list that was then manually refined and annotated by a volunteer team of sea urchin experts. This latter annotation community edited over 9000 gene models and uncovered many unexpected aspects of the sea urchin genetic content impacting transcriptional regulation, immunology, sensory perception, and an organism's development. Analysis of the basic deuterostome genetic complement supports the sea urchin's role as a model system for deuterostome and, by extension, chordate development.
Keywords: Animals; Chromosomes, Artificial, Bacterial; DNA; Genome; Sea Urchins

Spectrum of CHD7 mutations in 110 individuals with CHARGE syndrome and genotype-phenotype correlation. - Lalani, Seema R; Safiullah, Arsalan M; Fernbach, Susan D; Harutyunyan, Karine G; Thaller, Christina; Peterson, Leif E; McPherson, John D; Gibbs, Richard A; White, Lisa D; Hefner, Margaret; Davenport, Sandra L H; Graham, John M; et al. (Am J Hum Genet, 2006)
CHARGE syndrome is a well-established multiple-malformation syndrome with distinctive consensus diagnostic criteria. Characteristic associated anomalies include ocular coloboma, choanal atresia, cranial nerve defects, distinctive external and inner ear abnormalities, hearing loss, cardiovascular malformations, urogenital anomalies, and growth retardation. Recently, mutations of the chromodomain helicase DNA-binding protein gene CHD7 were reported to be a major cause of CHARGE syndrome. We sequenced the CHD7 gene in 110 individuals who had received the clinical diagnosis of CHARGE syndrome, and we detected mutations in 64 (58%). Mutations were distributed throughout the coding exons and conserved splice sites of CHD7. Of the 64 mutations, 47 (73%) predicted premature truncation of the protein. These included nonsense and frameshift mutations, which most likely lead to haploinsufficiency. Phenotypically, the mutation-positive group was more likely to exhibit cardiovascular malformations (54 of 59 in the mutation-positive group vs. 30 of 42 in the mutation-negative group; P=.014), coloboma of the eye (55 of 62 in the mutation-positive group vs. 30 of 43 in the mutation-negative group; P=.022), and facial asymmetry, often caused by seventh cranial nerve abnormalities (36 of 56 in the mutation-positive group vs. 13 of 39 in the mutation-negative group; P=.004). Mouse embryo whole-mount and section in situ hybridization showed the expression of Chd7 in the outflow tract of the heart, optic vesicle, facio-acoustic preganglion complex, brain, olfactory pit, and mandibular component of the first branchial arch. Microarray gene-expression analysis showed a signature pattern of gene-expression differences that distinguished the individuals with CHARGE syndrome with CHD7 mutation from the controls. We conclude that cardiovascular malformations, coloboma, and facial asymmetry are common findings in CHARGE syndrome caused by CHD7 mutation.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Child; Child, Preschool; Coloboma; DNA Helicases; DNA Mutational Analysis; DNA-Binding Proteins; Embryo, Mammalian; Facial Asymmetry; Female; Genotype; Heart Defects, Congenital; Humans; In Situ Hybridization, Fluorescence; Male; Mice; Molecular Sequence Data; Mutation; Pedigree; Phenotype; RNA Splice Sites; RNA, Messenger; Syndrome

Targeting iCre expression to murine progesterone receptor cell-lineages using bacterial artificial chromosome transgenesis. - Mukherjee, Atish; Soyal, Selma M; David A Wheeler; Fernández-Valdivia, Rodrigo; Nguyen, Jonathan; DeMayo, Francesco J; Lydon, John P (Genesis, 2006)
Gene-targeting in embryonic stem cells has been the dominant genetic approach when engineering mouse models to query the physiologic importance of the progesterone receptor (PR). Although these models have been instrumental in disclosing the in vivo significance of the progesterone signaling pathway, generation of such mice exacts considerable expenditure of time, effort, and expense. Considering the growing list of new PR mouse models that are urgently required to address the next questions in progestin biology, bacterial artificial chromosome (BAC) recombineering in conjunction with transgenesis was evaluated as an alternative method to accelerate the creation of these models in the future. Using this approach, we describe the generation of three PR-BAC(iCre) transgenic lines in which improved Cre recombinase (iCre) was targeted in-frame, downstream, and under the control of the PR promoter contained within a BAC transgene. Crossing with the ROSA26R revealed that the PR-BAC(iCre) transgenic expresses active iCre only in cell-lineages that express the PR. The specificity of the PR-BAC(iCre) transgene not only underscores the importance of BAC-mediated transgenesis as a quick, easy, and affordable method by which to engineer the next generation of PR mouse models, but also provides a unique opportunity to investigate transcriptional control of PR expression as well as PR structure-function relationships in vivo.
Keywords: Animals; Cell Lineage; Chromosomes, Artificial, Bacterial; Computational Biology; DNA Primers; Gene Components; Gene Transfer Techniques; Integrases; Mice; Mice, Transgenic; Models, Animal; Promoter Regions, Genetic; Receptors, Progesterone

Zebrafish dax1 is required for development of the interrenal organ, the adrenal cortex equivalent. - Zhao, Y; Yang, Z; Phelan, J K; David A Wheeler; Lin, S; McCabe, E R B (Mol Endocrinol, 2006)
Mutations in the human nuclear receptor, DAX1, cause X-linked adrenal hypoplasia congenita (AHC). We report the isolation and characterization of a DAX1 homolog, dax1, in zebrafish. The dax1 cDNA encodes a protein of 264 amino acids, including the conserved carboxy-terminal ligand binding-like motif; but the amino-terminal region lacks the unusual repeats of the DNA binding-like domain in mammals. Genomic sequence analysis indicates that the dax1 gene structure is conserved also. Whole-mount in situ hybridization revealed the onset of dax1 expression in the developing hypothalamus at approximately 26 h post fertilization (hpf). Later, at about 28 hpf, a novel expression domain for dax1 appeared in the trunk. This bilateral dax1-expressing structure was located immediately above the yolk sac, between the otic vesicle and the pronephros. Interestingly, weak and transient expression of dax1 was observed in the interrenal glands (adrenal cortical equivalents) at approximately 31 hpf. This gene was also expressed in the liver after 3 dpf in the zebrafish larvae. Disruption of dax1 function by morpholino oligonucleotides (MO) down-regulated expression of steroidogenic genes, cyp11a and star, and led to severe phenotypes similar to ff1b (SF1) MO-injected embryos. Injection of dax1 MO did not affect ff1b expression, whereas ff1b MO abolished dax1 expression in the interrenal organ. Based on these results, we propose that dax1 is the mammalian DAX1 ortholog, functions downstream of ff1b in the regulatory cascades, and is required for normal development and function of the zebrafish interrenal organ.
Keywords: Adrenal Cortex; Amino Acid Sequence; Animals; Base Sequence; DAX-1 Orphan Nuclear Receptor; DNA-Binding Proteins; Embryo, Nonmammalian; Embryonic Development; Interrenal Gland; Molecular Sequence Data; Oligonucleotides, Antisense; Phylogeny; Receptors, Retinoic Acid; Repressor Proteins; Sequence Homology, Amino Acid; Transcription Factors; Water-Electrolyte Balance; Zebrafish; Zebrafish Proteins

The alpha-amino-3-hydroxyl-5-methyl-4-isoxazolepropionate receptor trafficking regulator "stargazin" is related to the claudin family of proteins by Its ability to mediate cell-cell adhesion. - Price, Maureen G; Davis, Caleb F; Deng, Fang; Burgess, Daniel L (J Biol Chem, 2005)
Mutations in the Cacng2 gene encoding the neuronal transmembrane protein stargazin result in recessively inherited epilepsy and ataxia in "stargazer" mice. Functional studies suggest a dual role for stargazin, both as a modulatory gamma subunit for voltage-dependent calcium channels and as a regulator of post-synaptic membrane targeting for alpha-amino-3-hydroxyl-5-methyl-4-isoxazolepropionate (AMPA)-type glutamate receptors. Co-immunoprecipitation experiments demonstrate that stargazin can bind proteins of either complex in vivo, but it remains unclear whether it can associate with both complexes simultaneously. Cacng2 is one of eight closely related genes (Cacng1-8) encoding proteins with four transmembrane segments, cytoplasmic termini, and molecular masses between 25 and 44 kDa. This group of Cacng genes constitutes only one branch of a larger monophyletic assembly dominated by over 20 genes encoding proteins known as claudins. Claudins regulate cell adhesion and paracellular permeability as fundamental components of non-neuronal tight junctions. Because stargazin is structurally similar to claudins, we hypothesized that it might also have retained claudin-like functions inherited from a common ancestor. Here, we report that expression of stargazin in mouse L-fibroblasts results in cell aggregation comparable with that produced by claudins, and present evidence that the interaction is heterotypic and calcium dependent. The data suggest that the cell adhesion function of stargazin preceded its current role in neurons as a regulator of either voltage-dependent calcium channels or AMPA receptors. We speculate these complexes may have co-opted the established presence of stargazin at sites of close cell-cell contact to facilitate their own evolving intercellular signaling functions.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Calcium Channels; Cell Adhesion; Cell Line; DNA; Humans; L Cells; Membrane Proteins; Mice; Microscopy, Electron; Molecular Sequence Data; Multigene Family; Mutation; Neurons; Phylogeny; Receptors, AMPA; Recombinant Proteins; Sequence Homology, Amino Acid; Signal Transduction; Transfection

Characterization of the minimal replicator of Kaposi's sarcoma-associated herpesvirus latent origin. - Hu, Jianhong; Renne, Rolf (J Virol, 2005)
The latency-associated nuclear antigen (LANA) of Kaposi's sarcoma-associated herpesvirus (KSHV) binds to two sites within the 801-bp-long terminal repeat (TR) and is the only viral protein required for episomal maintenance. While two or more copies of TR are required for long-term maintenance, a single TR confers LANA-dependent origin activity on plasmid DNA. Deletion mapping revealed a 71-bp-long minimal replicator containing two distinctive sequence elements: LANA binding sites (LBS1/2) and an adjacent 29- to 32-bp-long GC-rich sequence which we termed the replication element. Furthermore, the transcription factor Sp1 can bind to TR outside the minimal replicator and contributes to TR's previously reported enhancer activity.
Keywords: Antigens, Viral; DNA Replication; DNA, Viral; Enhancer Elements, Genetic; Herpesvirus 8, Human; Humans; Nuclear Proteins; Replication Origin; Sarcoma, Kaposi; Terminal Repeat Sequences; Virus Latency

Comparative genome sequencing of Drosophila pseudoobscura: chromosomal, gene, and cis-element evolution. - Richards, Stephen; Liu, Yue; Bettencourt, Brian R; Hradecky, Pavel; Letovsky, Stan; Nielsen, Rasmus; Thornton, Kevin; Hubisz, Melissa J; Chen, Rui; Meisel, Richard P; Couronne, Olivier; Hua, Sujun; et al. (Genome Res, 2005)
We have sequenced the genome of a second Drosophila species, Drosophila pseudoobscura, and compared this to the genome sequence of Drosophila melanogaster, a primary model organism. Throughout evolution the vast majority of Drosophila genes have remained on the same chromosome arm, but within each arm gene order has been extensively reshuffled, leading to a minimum of 921 syntenic blocks shared between the species. A repetitive sequence is found in the D. pseudoobscura genome at many junctions between adjacent syntenic blocks. Analysis of this novel repetitive element family suggests that recombination between offset elements may have given rise to many paracentric inversions, thereby contributing to the shuffling of gene order in the D. pseudoobscura lineage. Based on sequence similarity and synteny, 10,516 putative orthologs have been identified as a core gene set conserved over 25-55 million years (Myr) since the pseudoobscura/melanogaster divergence. Genes expressed in the testes had higher amino acid sequence divergence than the genome-wide average, consistent with the rapid evolution of sex-specific proteins. Cis-regulatory sequences are more conserved than random and nearby sequences between the species--but the difference is slight, suggesting that the evolution of cis-regulatory elements is flexible. Overall, a pattern of repeat-mediated chromosomal rearrangement, and high coadaptation of both male genes and cis-regulatory sequences emerges as important themes of genome divergence between these species of Drosophila.
Keywords: Animals; Chromosome Breakage; Chromosome Inversion; Chromosome Mapping; Chromosomes; Conserved Sequence; Drosophila; Drosophila melanogaster; Enhancer Elements, Genetic; Evolution, Molecular; Gene Rearrangement; Genes, Insect; Genetic Variation; Genome; Molecular Sequence Data; Predictive Value of Tests; Repetitive Sequences, Nucleic Acid; Sequence Analysis, DNA

Deletion of FMR1 in Purkinje cells enhances parallel fiber LTD, enlarges spines, and attenuates cerebellar eyelid conditioning in Fragile X syndrome. - Koekkoek, S K E; Yamaguchi, K; Milojkovic, B A; Dortland, B R; Ruigrok, T J H; Maex, R; De Graaf, W; Smit, A E; VanderWerf, F; Bakker, C E; Willemsen, R; Ikeda, T; et al. (Neuron, 2005)
Absence of functional FMRP causes Fragile X syndrome. Abnormalities in synaptic processes in the cerebral cortex and hippocampus contribute to cognitive deficits in Fragile X patients. So far, the potential roles of cerebellar deficits have not been investigated. Here, we demonstrate that both global and Purkinje cell-specific knockouts of Fmr1 show deficits in classical delay eye-blink conditioning in that the percentage of conditioned responses as well as their peak amplitude and peak velocity are reduced. Purkinje cells of these mice show elongated spines and enhanced LTD induction at the parallel fiber synapses that innervate these spines. Moreover, Fragile X patients display the same cerebellar deficits in eye-blink conditioning as the mutant mice. These data indicate that a lack of FMRP leads to cerebellar deficits at both the cellular and behavioral levels and raise the possibility that cerebellar dysfunctions can contribute to motor learning deficits in Fragile X patients.
Keywords: Animals; Cerebellum; Conditioning, Eyelid; Dendrites; Fragile X Mental Retardation Protein; Fragile X Syndrome; Gene Deletion; Humans; Long-Term Synaptic Depression; Male; Mice; Mice, Knockout; Mice, Mutant Strains; Models, Neurological; Nerve Fibers; Nerve Tissue Proteins; Purkinje Cells; Reflex, Startle; RNA-Binding Proteins

Demographic, environmental, and genetic predictors of metabolic side effects of hydrochlorothiazide treatment in hypertensive subjects. - Maitland-van der Zee, Anke-Hilse; Turner, Stephen T; Schwartz, Gary L; Chapman, Arlene B; Klungel, Olaf H; Eric Boerwinkle (Am J Hypertens, 2005)
BACKGROUND: Thiazide diuretics are recommended for first-line treatment of hypertension. Although considered safe and effective, their use is associated with dyslipidemia, hyperglycemia, and an increased risk of developing type 2 diabetes. The aim of this study was to characterize interindividual variation in glucose and lipid responses to hydrochlorothiazide and to identify demographic, environmental, and genetic predictors associated with this variation. METHODS: A community-based sample of 585 adults with essential hypertension (291 African Americans [150 women and 141 men] and 294 non-Hispanic whites [126 women and 168 men]) underwent monotherapy with hydrochlorothiazide for 4 weeks. Linear regression was used to construct prediction models for the changes in plasma total cholesterol, triglyceride, and glucose concentrations. RESULTS: The mean changes (+/- standard deviation) in response to hydrochlorothiazide were 6.13 +/- 22.8 mg/dL for total cholesterol, 17.21 +/- 70 mg/dL for triglycerides, and 3.5 +/- 9.5 mg/dL for plasma glucose. Ethnicity and baseline levels of the analytes were the only predictors that were significant for more than one response. Therefore, the mechanism for these metabolic effects are not entirely shared. CONCLUSIONS: Taken together, demographic, environmental, and genetic factors accounted for only 13% of the total variation in total cholesterol response, 17% of the variation in triglyceride response, and 11% of the variation in glucose response to hydrochlorothiazide, and less than half of this predicted variation in response was explained by measured genotypes.
Keywords: Adult; Black or African American; Blood Glucose; Blood Pressure; Cholesterol; Diuretics; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Hydrochlorothiazide; Hypertension; Logistic Models; Male; Middle Aged; Multivariate Analysis; Polymorphism, Genetic; Potassium; Predictive Value of Tests; Treatment Outcome; Triglycerides; White People

The DNA sequence of the human X chromosome. - Ross, Mark T; Grafham, Darren V; Coffey, Alison J; Scherer, Steven; McLay, Kirsten; Muzny, Donna; Platzer, Matthias; Howell, Gareth R; Burrows, Christine; Bird, Christine P; Frankish, Adam; Lovell, Frances L; et al. (Nature, 2005)
The human X chromosome has a unique biology that was shaped by its evolution as the sex chromosome shared by males and females. We have determined 99.3% of the euchromatic sequence of the X chromosome. Our analysis illustrates the autosomal origin of the mammalian sex chromosomes, the stepwise process that led to the progressive loss of recombination between X and Y, and the extent of subsequent degradation of the Y chromosome. LINE1 repeat elements cover one-third of the X chromosome, with a distribution that is consistent with their proposed role as way stations in the process of X-chromosome inactivation. We found 1,098 genes in the sequence, of which 99 encode proteins expressed in testis and in various tumour types. A disproportionately high number of mendelian diseases are documented for the X chromosome. Of this number, 168 have been explained by mutations in 113 X-linked genes, which in many cases were characterized with the aid of the DNA sequence.
Keywords: Animals; Antigens, Neoplasm; Centromere; Chromosomes, Human, X; Chromosomes, Human, Y; Contig Mapping; Crossing Over, Genetic; Dosage Compensation, Genetic; Evolution, Molecular; Female; Genetic Linkage; Genetics, Medical; Genomics; Humans; Male; Polymorphism, Single Nucleotide; Repetitive Sequences, Nucleic Acid; RNA; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Testis

Dual regulation and redundant function of two eye-specific enhancers of the Drosophila retinal determination gene dachshund. - Pappu, Kartik S; Ostrin, Edwin J; Middlebrooks, Brooke W; Sili, Beril Tavsanli; Rui Chen; Atkins, Mardelle R; Richard A Gibbs; Mardon, Graeme (Development, 2005)
Drosophila eye development is controlled by a conserved network of retinal determination (RD) genes. The RD genes encode nuclear proteins that form complexes and function in concert with extracellular signal-regulated transcription factors. Identification of the genomic regulatory elements that govern the eye-specific expression of the RD genes will allow us to better understand how spatial and temporal control of gene expression occurs during early eye development. We compared conserved non-coding sequences (CNCSs) between five Drosophilids along the approximately 40 kb genomic locus of the RD gene dachshund (dac). Our analysis uncovers two separate eye enhancers in intron eight and the 3' non-coding regions of the dac locus defined by clusters of highly conserved sequences. Loss- and gain-of-function analyses suggest that the 3' eye enhancer is synergistically activated by a combination of eya, so and dpp signaling, and only indirectly activated by ey, whereas the 5' eye enhancer is primarily regulated by ey, acting in concert with eya and so. Disrupting conserved So-binding sites in the 3' eye enhancer prevents reporter expression in vivo. Our results suggest that the two eye enhancers act redundantly and in concert with each other to integrate distinct upstream inputs and direct the eye-specific expression of dac.
Keywords: 3' Untranslated Regions; Animals; Base Sequence; DNA-Binding Proteins; Drosophila; Drosophila Proteins; Enhancer Elements, Genetic; Eye Proteins; Gene Expression Regulation, Developmental; Genome; Homeodomain Proteins; Homozygote; Introns; Molecular Sequence Data; Mutation; Nuclear Proteins; Organ Specificity; Response Elements; Retina

Emerging technologies in DNA sequencing. - Metzker, Michael L (Genome Res, 2005)
Demand for DNA sequence information has never been greater, yet current Sanger technology is too costly, time consuming, and labor intensive to meet this ongoing demand. Applications span numerous research interests, including sequence variation studies, comparative genomics and evolution, forensics, and diagnostic and applied therapeutics. Several emerging technologies show promise of delivering next-generation solutions for fast and affordable genome sequencing. In this review article, the DNA polymerase-dependent strategies of Sanger sequencing, single nucleotide addition, and cyclic reversible termination are discussed to highlight recent advances and potential challenges these technologies face in their development for ultrafast DNA sequencing.
Keywords: Animals; Base Sequence; DNA; DNA-Directed DNA Polymerase; Humans; Sequence Analysis, DNA

Evolutionarily conserved elements in vertebrate, insect, worm, and yeast genomes. - Siepel, Adam; Bejerano, Gill; Pedersen, Jakob S; Hinrichs, Angie S; Hou, Minmei; Rosenbloom, Kate; Clawson, Hiram; Spieth, John; Hillier, LaDeana W; Richards, Stephen; Weinstock, George M; Wilson, Richard K; et al. (Genome Res, 2005)
We have conducted a comprehensive search for conserved elements in vertebrate genomes, using genome-wide multiple alignments of five vertebrate species (human, mouse, rat, chicken, and Fugu rubripes). Parallel searches have been performed with multiple alignments of four insect species (three species of Drosophila and Anopheles gambiae), two species of Caenorhabditis, and seven species of Saccharomyces. Conserved elements were identified with a computer program called phastCons, which is based on a two-state phylogenetic hidden Markov model (phylo-HMM). PhastCons works by fitting a phylo-HMM to the data by maximum likelihood, subject to constraints designed to calibrate the model across species groups, and then predicting conserved elements based on this model. The predicted elements cover roughly 3%-8% of the human genome (depending on the details of the calibration procedure) and substantially higher fractions of the more compact Drosophila melanogaster (37%-53%), Caenorhabditis elegans (18%-37%), and Saccharaomyces cerevisiae (47%-68%) genomes. From yeasts to vertebrates, in order of increasing genome size and general biological complexity, increasing fractions of conserved bases are found to lie outside of the exons of known protein-coding genes. In all groups, the most highly conserved elements (HCEs), by log-odds score, are hundreds or thousands of bases long. These elements share certain properties with ultraconserved elements, but they tend to be longer and less perfectly conserved, and they overlap genes of somewhat different functional categories. In vertebrates, HCEs are associated with the 3' UTRs of regulatory genes, stable gene deserts, and megabase-sized regions rich in moderately conserved noncoding sequences. Noncoding HCEs also show strong statistical evidence of an enrichment for RNA secondary structure.
Keywords: 3' Untranslated Regions; Animals; Base Pairing; Base Sequence; Caenorhabditis elegans; Conserved Sequence; DNA, Intergenic; Evolution, Molecular; Genome; Humans; Insecta; Molecular Sequence Data; Saccharomyces; Vertebrates; Yeasts

G309D and W437OPA PINK1 mutations in Caucasian Parkinson's disease patients. - Deng, H; Le, W D; Zhang, X; Pan, T H; Jankovic, J (Acta Neurol Scand, 2005)
OBJECTIVE: To determine whether the G309D and W437OPA mutations in PINK1 gene are present in American Caucasian population of patients with Parkinson's disease (PD). METHODS: We searched for the G309D and W437OPA mutation by sequencing the regions of interest in the PINK1 gene in 237 unrelated Caucasian patients. RESULTS: None of the 237 samples showed the G309D or W437OPA mutations. CONCLUSIONS: The G309D and W437OPA mutations in PINK1 gene probably do not represent common causes of familial or sporadic PD in a Caucasian population.
Keywords: Adult; Amino Acid Substitution; DNA Mutational Analysis; Female; Genetic Testing; Genome, Human; Humans; Male; Middle Aged; Mutation; Parkinson Disease; Protein Kinases; United States; White People

Genetic diversity among type emm28 group A Streptococcus strains causing invasive infections and pharyngitis. - Green, Nicole M; Beres, Stephen B; Graviss, Edward A; Allison, James E; McGeer, Allison J; Vuopio-Varkila, Jaana; LeFebvre, Rance B; Musser, James M (J Clin Microbiol, 2005)
Genome sequencing of group A Streptococcus (GAS) has revealed that prophages account for the vast majority of gene content differences between strains. Serotype M28 strains are a leading cause of pharyngitis and invasive infections, but little is known about genetic diversity present in natural populations of these organisms. To study this issue, population-based samples of 568 strains from Ontario, Canada; Finland; and Houston, Texas, were analyzed. Special attention was given to analysis of variation in prophage-encoded virulence gene content by a PCR-based method. Thirty and 29 distinct prophage-encoded virulence gene profiles were identified among pharyngitis and invasive infection isolates. Thirteen profiles, representing the majority of the strains, were shared between these two classes of isolates. Significant differences were observed in the frequency of occurrence of certain prophage toxin gene profiles and infection type. M28 strains are highly diverse in prophage-encoded virulence gene content and integration site, supporting the key concept that prophages are critical contributors to GAS genetic diversity and population biology. Nucleotide sequence variation in the emm gene (encodes M protein) was also examined. Only three allelic variants were identified in the hypervariable portion of the emm28 gene. All but one strain had the same inferred amino acid sequence in the first 100 amino acids of the mature M28 protein. In contrast, size differences in the emm28 gene and inferred protein due to variable numbers of C-terminal repeats were common. The presence of macrolide resistance genes (mefA, ermB, and ermTR) was analyzed by PCR, and less than 2% of the strains were positive.
Keywords: Antigens, Bacterial; Bacterial Outer Membrane Proteins; Carrier Proteins; Chromosome Mapping; Drug Resistance, Bacterial; Genetic Variation; Humans; Macrolides; Pharyngitis; Prophages; Streptococcal Infections; Streptococcus pyogenes; Virulence

The genome of the social amoeba Dictyostelium discoideum. - Eichinger, L; Pachebat, J A; Glöckner, G; Rajandream, M-A; Sucgang, R; Berriman, M; Song, J; Olsen, R; Szafranski, K; Xu, Q; Tunggal, B; Kummerfeld, S; et al. (Nature, 2005)
The social amoebae are exceptional in their ability to alternate between unicellular and multicellular forms. Here we describe the genome of the best-studied member of this group, Dictyostelium discoideum. The gene-dense chromosomes of this organism encode approximately 12,500 predicted proteins, a high proportion of which have long, repetitive amino acid tracts. There are many genes for polyketide synthases and ABC transporters, suggesting an extensive secondary metabolism for producing and exporting small molecules. The genome is rich in complex repeats, one class of which is clustered and may serve as centromeres. Partial copies of the extrachromosomal ribosomal DNA (rDNA) element are found at the ends of each chromosome, suggesting a novel telomere structure and the use of a common mechanism to maintain both the rDNA and chromosomal termini. A proteome-based phylogeny shows that the amoebozoa diverged from the animal-fungal lineage after the plant-animal split, but Dictyostelium seems to have retained more of the diversity of the ancestral genome than have plants, animals or fungi.
Keywords: Animals; ATP-Binding Cassette Transporters; Base Composition; Cell Adhesion; Cell Movement; Centromere; Conserved Sequence; Dictyostelium; DNA Transposable Elements; DNA, Ribosomal; Eukaryotic Cells; Gene Duplication; Gene Transfer, Horizontal; Genome; Genomics; Humans; Molecular Sequence Data; Phylogeny; Proteome; Protozoan Proteins; Repetitive Sequences, Nucleic Acid; RNA, Transfer; Sequence Analysis, DNA; Signal Transduction; Social Behavior; Telomere

Genome-wide structural and evolutionary analysis of the P450 monooxygenase genes (P450ome) in the white rot fungus Phanerochaete chrysosporium: evidence for gene duplications and extensive gene clustering. - Doddapaneni, Harshavardhan; Chakraborty, Ranajit; Yadav, Jagjit S (BMC Genomics, 2005)
BACKGROUND: Phanerochaete chrysosporium, the model white rot basidiomycetous fungus, has the extraordinary ability to mineralize (to CO2) lignin and detoxify a variety of chemical pollutants. Its cytochrome P450 monooxygenases have recently been implied in several of these biotransformations. Our initial P450 cloning efforts in P. chrysosporium and its subsequent whole genome sequencing have revealed an extraordinary P450 repertoire ("P450ome") containing at least 150 P450 genes with yet unknown function. In order to understand the functional diversity and the evolutionary mechanisms and significance of these hemeproteins, here we report a genome-wide structural and evolutionary analysis of the P450ome of this fungus. RESULTS: Our analysis showed that P. chrysosporium P450ome could be classified into 12 families and 23 sub-families and is characterized by the presence of multigene families. A genome-level structural analysis revealed 16 organizationally homogeneous and heterogeneous clusters of tandem P450 genes. Analysis of our cloned cDNAs revealed structurally conserved characteristics (intron numbers and locations, and functional domains) among members of the two representative multigene P450 families CYP63 and CYP505 (P450foxy). Considering the unusually complex structural features of the P450 genes in this genome, including microexons (2-10 aa) and frequent small introns (45-55 bp), alternative splicing, as experimentally observed for CYP63, may be a more widespread event in the P450ome of this fungus. Clan-level phylogenetic comparison revealed that P. chrysosporium P450 families fall under 11 fungal clans and the majority of these multigene families appear to have evolved locally in this genome from their respective progenitor genes, as a result of extensive gene duplications and rearrangements. CONCLUSION: P. chrysosporium P450ome, the largest known to date among fungi, is characterized by tandem gene clusters and multigene families. This enormous P450 gene diversity has evolved by extensive gene duplications and intragenomic recombinations of the progenitor genes presumably to meet the exceptionally high metabolic demand of this biodegradative group of basidiomycetous fungi in ecological niches. In this context, alternative splicing appears to further contribute to the evolution of functional diversity of the P450ome in this fungus. The evolved P450 diversity is consistent with the known vast biotransformation potential of P. chrysosporium. The presented analysis will help design future P450 functional studies to understand the underlying mechanisms of secondary metabolism and oxidative biotransformation pathways in this model white rot fungus.
Keywords: Alternative Splicing; Amino Acid Sequence; Cloning, Molecular; Cluster Analysis; Cytochrome P-450 Enzyme System; DNA, Complementary; Evolution, Molecular; Gene Duplication; Genome, Fungal; Mixed Function Oxygenases; Models, Genetic; Molecular Sequence Data; Multigene Family; Oxygen; Phanerochaete; Phylogeny; Protein Structure, Tertiary; Sequence Homology, Amino Acid

A haplotype map of the human genome. (Nature, 2005)
Inherited genetic variation has a critical but as yet largely uncharacterized role in human disease. Here we report a public database of common variation in the human genome: more than one million single nucleotide polymorphisms (SNPs) for which accurate and complete genotypes have been obtained in 269 DNA samples from four populations, including ten 500-kilobase regions in which essentially all information about common DNA variation has been extracted. These data document the generality of recombination hotspots, a block-like structure of linkage disequilibrium and low haplotype diversity, leading to substantial correlations of SNPs with many of their neighbours. We show how the HapMap resource can guide the design and analysis of genetic association studies, shed light on structural variation and recombination, and identify loci that may have been subject to natural selection during human evolution.
Keywords: Chromosomes, Human, Y; DNA, Mitochondrial; Gene Frequency; Genome, Human; Haplotypes; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Recombination, Genetic; Selection, Genetic

Highly multiplexed molecular inversion probe genotyping: over 10,000 targeted SNPs genotyped in a single tube assay. - Hardenbol, Paul; Yu, Fuli; Belmont, John; Mackenzie, Jennifer; Bruckner, Carsten; Brundage, Tiffany; Boudreau, Andrew; Chow, Steve; Eberle, Jim; Erbilgin, Ayca; Falkowski, Mat; Fitzgerald, Ron; et al. (Genome Res, 2005)
Large-scale genetic studies are highly dependent on efficient and scalable multiplex SNP assays. In this study, we report the development of Molecular Inversion Probe technology with four-color, single array detection, applied to large-scale genotyping of up to 12,000 SNPs per reaction. While generating 38,429 SNP assays using this technology in a population of 30 trios from the Centre d'Etude Polymorphisme Humain family panel as part of the International HapMap project, we established SNP conversion rates of approximately 90% with concordance rates >99.6% and completeness levels >98% for assays multiplexed up to 12,000plex levels. Furthermore, these individual metrics can be "traded off" and, by sacrificing a small fraction of the conversion rate, the accuracy can be increased to very high levels. No loss of performance is seen when scaling from 6,000plex to 12,000plex assays, strongly validating the ability of the technology to suppress cross-reactivity at high multiplex levels. The results of this study demonstrate the suitability of this technology for comprehensive association studies that use targeted SNPs in indirect linkage disequilibrium studies or that directly screen for causative mutations.
Keywords: Chromosome Inversion; Cluster Analysis; DNA Probes; Gene Expression Profiling; Genome, Human; Genotype; Humans; Molecular Probe Techniques; Molecular Probes; Polymorphism, Single Nucleotide; Research Design

Identification of genetic polymorphisms through comparative DNA sequence analysis on the K-ras gene: implications for lung tumor susceptibility. - Wang, Min; Wang, Yian; You, Ming (Exp Lung Res, 2005)
In the present study, the authors performed a comparative sequence analysis of the K-ras gene. By comparing sequences from different mouse inbred strains, the authors have identified new nucleotide polymorphisms in the noncoding regions of mouse K-ras gene. They have also identified noncoding DNA segments evolutionarily conserved among the human, mouse, and rat. Computational analysis for transcription factor binding sites suggests that these polymorphic and conserved DNA sequences harbor potential cis-regulatory elements, which may contribute to the transcriptional regulation of the K-ras gene. Further studies on these potential regulatory sites may help to elucidate the fundamental mechanism underlying allele-specific activation and expression of K-ras gene in hybrid mouse lung tumors, which determines lung tumor susceptibility in mice.
Keywords: Animals; Base Sequence; Binding Sites; Conserved Sequence; DNA, Neoplasm; Gene Deletion; Genes, ras; Genetic Predisposition to Disease; Humans; Lung Neoplasms; Mice; Mice, Inbred Strains; Molecular Sequence Data; Polymorphism, Genetic; Promoter Regions, Genetic; Rats; Sequence Homology, Nucleic Acid; Transcription Factors

Keeping an eye on the fly genome. - Rui Chen; Mardon, Graeme (Dev Biol, 2005)
With its unique structure and dynamic development, the Drosophila eye has been a powerful genetic model system for studying molecular mechanisms of cell fate specification and differentiation. Hundreds of genes that function in a complex genetic network controlling this process have been identified during the past two decades. To further advance our understanding of the molecular mechanisms of eye development, it is increasingly important to place the current genetic pathway into a whole-genome perspective. Here, we review emerging technologies and strategies that will help to achieve this goal, including generation of a complete mutant set in Drosophila, genome-wide transcription factor target identification, and systematic studies of gene function aided by computational biology.
Keywords: Animals; Cell Differentiation; Computational Biology; Drosophila; Eye; Genome; Genomics; Mutation; Transcription Factors

Microarray-based global differential expression profiling of P450 monooxygenases and regulatory proteins for signal transduction pathways in the white rot fungus Phanerochaete chrysosporium. - Harshavardhan Doddapaneni; Yadav, J S (Mol Genet Genomics, 2005)
Whole genome sequencing of the model white rot basidiomycete Phanerochaete chrysosporium has revealed the largest P450 contingent known to date in fungi, along with related phase I and phase II metabolic genes and signaling cascade genes. As a part of their functional characterization, genome-wide expression profiling under physiologically distinct conditions, nutrient-limited (ligninolytic) and nutrient-rich (non-ligninolytic), was investigated using a custom-designed 70-mer oligonucleotide microarray developed based on 190 target genes and 23 control genes. All 150 P450 genes were found to be expressible under the test conditions, with 27 genes showing differential expression based on a >twofold arbitrary cut-off limit. Of these, 23 P450 genes were upregulated (twofold to ninefold) in defined high-nitrogen cultures whereas four genes were upregulated (twofold to twentyfold) in defined low-nitrogen cultures. Furthermore, tandem P450 member genes in ten of the 16 P450 genomic clusters showed nonassortative regulation of expression reflecting their functional diversity. Full-length cDNAs for two of the high-nitrogen upregulated genes pc-hn1 (CYP5035A1) and pc-hn2 (CYP5036A1) and partial cDNA for a low-nitrogen upregulated gene pc-ln1 (CYP5037A1) were cloned and characterized. The study provided first molecular evidence for the presence of active components of the cAMP- and MAP kinase-signaling pathways in a white rot fungus; four of these components (cpka and ste-12 of cAMP pathway and two MAP kinases, mps1 and sps1) were significantly upregulated (fourfold to eightfold) under nutrient-limited conditions, implying their likely role in the regulation of gene expression involved in secondary metabolism and biodegradation processes under these conditions.
Keywords: Base Sequence; Cytochrome P-450 Enzyme System; DNA Primers; DNA Probes; DNA, Complementary; Gene Expression Profiling; Nucleic Acid Hybridization; Oligonucleotide Array Sequence Analysis; Phanerochaete; Reverse Transcriptase Polymerase Chain Reaction; RNA, Fungal; Signal Transduction

Mining genetic epidemiology data with Bayesian networks application to APOE gene variation and plasma lipid levels. - Rodin, Andrei; Mosley, Thomas H; Clark, Andrew G; Sing, Charles F; Boerwinkle, Eric (J Comput Biol, 2005)
There is a critical need for data-mining methods that can identify SNPs that predict among individual variation in a phenotype of interest and reverse-engineer the biological network of relationships between SNPs, phenotypes, and other factors. This problem is both challenging and important in light of the large number of SNPs in many genes of interest and across the human genome. A potentially fruitful form of exploratory data analysis is the Bayesian or Belief network. A Bayesian or Belief network provides an analytic approach for identifying robust predictors of among-individual variation in a disease endpoints or risk factor levels. We have applied Belief networks to SNP variation in the human APOE gene and plasma apolipoprotein E levels from two samples: 702 African-Americans from Jackson, MS, and 854 non-Hispanic whites from Rochester, MN. Twenty variable sites in the APOE gene were genotyped in both samples. In Jackson, MS, SNPs 4036 and 4075 were identified to influence plasma apoE levels. In Rochester, MN, SNPs 3937 and 4075 were identified to influence plasma apoE levels. All three SNPs had been previously implicated in affecting measures of lipid and lipoprotein metabolism. Like all data-mining methods, Belief networks are meant to complement traditional hypothesis-driven methods of data analysis. These results document the utility of a Belief network approach for mining large scale genotype-phenotype association data.
Keywords: Apolipoproteins E; Bayes Theorem; Databases, Factual; Genetics, Population; Humans; Linkage Disequilibrium; Lipids; Models, Genetic; Polymorphism, Single Nucleotide

Mining genetic epidemiology data with Bayesian networks I: Bayesian networks and example application (plasma apoE levels). - Rodin, Andrei S; Boerwinkle, Eric (Bioinformatics, 2005)
MOTIVATION: The wealth of single nucleotide polymorphism (SNP) data within candidate genes and anticipated across the genome poses enormous analytical problems for studies of genotype-to-phenotype relationships, and modern data mining methods may be particularly well suited to meet the swelling challenges. In this paper, we introduce the method of Belief (Bayesian) networks to the domain of genotype-to-phenotype analyses and provide an example application. RESULTS: A Belief network is a graphical model of a probabilistic nature that represents a joint multivariate probability distribution and reflects conditional independences between variables. Given the data, optimal network topology can be estimated with the assistance of heuristic search algorithms and scoring criteria. Statistical significance of edge strengths can be evaluated using Bayesian methods and bootstrapping. As an example application, the method of Belief networks was applied to 20 SNPs in the apolipoprotein (apo) E gene and plasma apoE levels in a sample of 702 individuals from Jackson, MS. Plasma apoE level was the primary target variable. These analyses indicate that the edge between SNP 4075, coding for the well-known epsilon2 allele, and plasma apoE level was strong. Belief networks can effectively describe complex uncertain processes and can both learn from data and incorporate prior knowledge. AVAILABILITY: Various alternative and supplemental networks (not given in the text) as well as source code extensions, are available from the authors. SUPPLEMENTARY INFORMATION: http://bioinformatics.oxfordjournals.org.
Keywords: Apolipoproteins E; Bayes Theorem; Chromosome Mapping; Computer Simulation; Database Management Systems; Databases, Genetic; DNA Mutational Analysis; Epidemiologic Methods; Genotype; Humans; Information Storage and Retrieval; Models, Genetic; Models, Statistical; Polymorphism, Single Nucleotide

Molecular characterization of a widespread, pathogenic, and antibiotic resistance-receptive Enterococcus faecalis lineage and dissemination of its putative pathogenicity island. - Nallapareddy, Sreedhar R; Wenxiang, Huang; Weinstock, George M; Murray, Barbara E (J Bacteriol, 2005)
Enterococcus faecalis, a common cause of endocarditis and known for its capacity to transfer antibiotic resistance to other pathogens, has recently emerged as an important, multidrug-resistant nosocomial pathogen. However, knowledge of its lineages and the potential of particular clones of this species to disseminate and cause disease is limited. Using a nine-gene multilocus sequence typing (MLST) scheme, we identified an evolving and widespread clonal complex of E. faecalis that has caused outbreaks and life-threatening infections. Moreover, this unusual clonal complex was found to contain isolates of unexpected relatedness, including the first known U.S. vancomycin-resistant enterococcus (E. faecalis strain V583), the first known penicillinase-producing (Bla(+)) E. faecalis isolate, and the previously described widespread clone of penicillinase producers, a trait found in <0.1% of E. faecalis isolates. All members of this clonal cluster (designated as BVE for Bla(+) Van(r) endocarditis) were found to contain a previously described putative pathogenicity island (PAI). Further analysis of this PAI demonstrated its dissemination worldwide, albeit with considerable variability, confirmed its association with clinical isolates, and found a common insertion site in different clonal lineages. PAI deletions, MLST, and the uncommon resistances were used to predict the evolution of the BVE clonal cluster. The finding of a virulent and highly successful clonal complex of E. faecalis with different members resistant to the primary therapies of choice, ampicillin and vancomycin, has important implications for the evolution of virulence and successful lineages and for public health monitoring and control.
Keywords: Bacterial Proteins; Chromosomes, Bacterial; Drug Resistance, Bacterial; Endocarditis; Enterococcus faecalis; Genomic Islands; Gram-Positive Bacterial Infections; Humans; Virulence; Virulence Factors

Orphan nuclear receptor GCNF is required for the repression of pluripotency genes during retinoic acid-induced embryonic stem cell differentiation. - Gu, Peili; LeMenuet, Damien; Chung, Arthur C-K; Mancini, Michael; Wheeler, David A; Cooney, Austin J (Mol Cell Biol, 2005)
Embryonic stem (ES) cell pluripotency and differentiation are controlled by a network of transcription factors and signaling molecules. Transcription factors such as Oct4 and Nanog are required for self-renewal and maintain the undifferentiated state of ES cells. Decreases in the expression of these factors indicate the initiation of differentiation of ES cells. Inactivation of the gene encoding the orphan nuclear receptor GCNF showed that it plays an important role in the repression of Oct4 expression in somatic cells during early embryonic development. GCNF-/- ES cells were isolated to study the function of GCNF in the down-regulation of pluripotency genes during differentiation. Loss of repression of ES cell marker genes Oct4, Nanog, Sox2, FGF4, and Stella was observed upon treatment of GCNF-/- ES cells with retinoic acid. The loss of repression of pluripotency genes is either a direct or indirect consequence of loss of GCNF. Both the Oct4 and Nanog genes are direct targets of GCNF repression during ES cell differentiation and early mouse embryonic development. In contrast Sox2 and FGF4 are indirectly regulated by GCNF through Oct4. These findings establish a central role for GCNF in the repression of pluripotency gene expression during retinoic acid-induced ES cell differentiation.
Keywords: Animals; Blotting, Northern; Blotting, Western; Cell Differentiation; Cell Line; Cell Nucleus; Chromatin Immunoprecipitation; DNA-Binding Proteins; Down-Regulation; Embryo, Mammalian; Female; Fibroblast Growth Factor 4; Genotype; Homeodomain Proteins; In Situ Hybridization; Male; Mice; Mice, Transgenic; Microscopy, Fluorescence; Models, Genetic; Nanog Homeobox Protein; Nuclear Receptor Subfamily 6, Group A, Member 1; Octamer Transcription Factor-3; Phenotype; Plasmids; Protein Binding; Receptors, Cytoplasmic and Nuclear; Response Elements; Reverse Transcriptase Polymerase Chain Reaction; Signal Transduction; SOXB1 Transcription Factors; Stem Cells; Time Factors; Trans-Activators; Transfection; Tretinoin

Orphan nuclear receptor LRH-1 is required to maintain Oct4 expression at the epiblast stage of embryonic development. - Gu, Peili; Goodwin, Bryan; Chung, Arthur C-K; Xu, Xueping; Wheeler, David A; Price, Roger R; Galardi, Cristin; Peng, Li; Latour, Anne M; Koller, Beverly H; Gossen, Jan; Kliewer, Steven A; et al. (Mol Cell Biol, 2005)
Oct4 plays an essential role in maintaining the inner cell mass and pluripotence of embryonic stem (ES) cells. The expression of Oct4 is regulated by the proximal enhancer and promoter in the epiblast and by the distal enhancer and promoter at all other stages in the pluripotent cell lineage. Here we report that the orphan nuclear receptor LRH-1, which is expressed in undifferentiated ES cells, can bind to SF-1 response elements in the proximal promoter and proximal enhancer of the Oct4 gene and activate Oct4 reporter gene expression. LRH-1 is colocalized with Oct4 in the inner cell mass and the epiblast of embryos at early developmental stages. Disruption of the LRH-1 gene results in loss of Oct4 expression at the epiblast stage and early embryonic death. Using LRH-1(-/-) ES cells, we also show that LRH-1 is required to maintain Oct4 expression at early differentiation time points. In vitro and in vivo results show that LRH-1 plays an essential role in the maintenance of Oct4 expression in ES cells at the epiblast stage of embryonic development, thereby maintaining pluripotence at this crucial developmental stage prior to segregation of the primordial germ cell lineage at gastrulation.
Keywords: Animals; Blastocyst; Cell Differentiation; DNA-Binding Proteins; Down-Regulation; Embryo, Mammalian; Embryonic Development; Gene Expression Regulation, Developmental; Gene Silencing; Genes, Lethal; Mice; Octamer Transcription Factor-3; Receptors, Cytoplasmic and Nuclear; Response Elements; Stem Cells; Transcription Factors; Up-Regulation

Pas1c1 is a candidate for the mouse pulmonary adenoma susceptibility 1 locus. - Wang, Min; Futamura, Manabu; Wang, Yian; You, Ming (Oncogene, 2005)
Pas1 candidate 1 (Pas1c1) gene (also named Lmna-rs1) was found to encode two alternatively spliced mRNA transcripts (i.e. Pas1c1-Va and Pas1c1-Vb). In this study, we identified three additional mRNA transcripts encoded by the Pas1c1 gene, which were designated as Pas1c1-Vc, Pas1c1-Vd, and Pas1c1-Ve, respectively. Similar to Pas1c1-Vb, the newly identified transcripts were only expressed in mouse lung tissues from strains carrying the Pas1-susceptible (Pas1/s) allele. Pas1c1 transcripts were also detected in heart, testis, or brain but not in liver, spleen, or kidney. An 11-nucleotide polymorphism was found within the 3'-acceptor splice site of exon 8, which cosegregates with mouse strain Pas1 alleles and may underlie the strain-specific exon 8 skipping. We also found that ectopic expression of the Pas1c1-Va and Pas1c1-Vb in COS7 and NIH3T3 cells exhibited distinct intracellular distributions. These results support that Pas1c1 as a candidate for the Pas1 locus and the strain-specific isoforms may have differential effects on cell proliferation.
Keywords: Adenoma; Amino Acid Sequence; Animals; Base Sequence; DNA Primers; Exons; Genetic Predisposition to Disease; Lung Neoplasms; Mice; Molecular Sequence Data; Sequence Alignment; Sequence Homology, Amino Acid; Tumor Suppressor Proteins

Pooled genomic indexing of rhesus macaque. - Milosavljevic, Aleksandar; Harris, Ronald A; Sodergren, Erica J; Jackson, Andrew R; Kalafus, Ken J; Hodgson, Anne; Cree, Andrew; Dai, Weilie; Csuros, Miklos; Zhu, Baoli; De Jong, Pieter J; Weinstock, George M; et al. (Genome Res, 2005)
Pooled genomic indexing (PGI) is a method for mapping collections of bacterial artificial chromosome (BAC) clones between species by using a combination of clone pooling and DNA sequencing. PGI has been used to map a total of 3858 BAC clones covering approximately 24% of the rhesus macaque (Macaca mulatta) genome onto 4178 homologous loci in the human genome. A number of intrachromosomal rearrangements were detected by mapping multiple segments within the individual rhesus BACs onto multiple disjoined loci in the human genome. Transversal pooling designs involving shuffled BAC arrays were employed for robust mapping even with modest DNA sequence read coverage. A further innovation, short-tag pooled genomic indexing (ST-PGI), was also introduced to further improve the economy of mapping by sequencing multiple, short, mapable tags within a single sequencing reaction.
Keywords: Animals; Chromosome Aberrations; Chromosomes, Artificial, Bacterial; Contig Mapping; DNA; Genetic Markers; Genome; Genome, Human; Humans; Macaca mulatta; Sequence Alignment; Sequence Analysis, DNA

The beta(2)-adrenergic receptor Arg16-gly polymorphism and interactions involving beta(2)- and beta(3)-adrenergic receptor polymorphisms are associated with variations in longitudinal serum lipid profiles: the Bogalusa Heart Study. - Hallman, D Michael; Srinivasan, Sathanur R; Chen, Wei; Eric Boerwinkle; Berenson, Gerald S (Metabolism, 2004)
We examined the effects of combined genotypes of the beta(2)-adrenergic receptor (AR) Arg(16)-Gly and beta(3)-AR Trp(64)-Arg polymorphisms on longitudinal serum total (T-C) and low-density lipoprotein cholesterol (LDL-C) profiles in 1,198 subjects examined multiple times (6,488 observations) from 1973 to 1996 in the Bogalusa Heart Study, at ages from 4.5 to 38 years. Within 5-year age groups, T-C was significantly (P <.05) higher in beta(2)-AR Arg(16)/Arg(16) homozygotes than in Gly(16) carriers among those 4 to 8 (171.4 +/- 30.0 v 161.5 +/- 27.7 mg/dL), 9 to 13 (167.7 +/- 28.6 v 162.4 +/- 27.4 mg/dL), and 14 to 18 (158.8 +/- 29.6 v 154.7 +/- 27.5 mg/dL) years of age, but not in those 19 to 23, 24 to 28, 29 to 33, or 34 to 38 years of age. The beta(3)-AR polymorphism was not associated with variation in either T-C or LDL-C. In multilevel polynomial growth curve models, the combination of the beta(2)-AR Arg(16)/Arg(16) genotype with either the beta(3)-AR Arg(64)/Arg(64) or Trp(64)/Arg(64) genotypes, denoted AA/AX, was associated with variation in longitudinal T-C (P <.01) and LDL-C (P <.01) profiles. The association between combined beta(2)/beta(3)-AR genotype and lipid profiles differed among race/sex groups, being most marked in black females, in whom the AA/AX combination was associated with higher T-C and LDL-C profiles across all ages. In White males, the AA/AX combination was most strongly associated with higher lipids in adults. In black males and white females, lipid profiles differed little between genotype groups. Our findings suggest that the beta(2)-AR Arg(16)-Gly genotype influences T-C and LDL-C levels in an age-specific manner, that it may interact with beta(3)-AR Trp(64)-Arg genotypes to influence longitudinal T-C and LDL-C profiles, and that the effect of combined beta(2)/beta(3)-AR genotypes on T-C and LDL-C profiles may differ among race/sex groups.
Keywords: Age Factors; Algorithms; Amino Acid Substitution; Black People; Body Mass Index; Cardiovascular Diseases; Child; Cholesterol, LDL; DNA Primers; Female; Genotype; Humans; Lipids; Longitudinal Studies; Male; Polymorphism, Genetic; Receptors, Adrenergic, beta-2; Receptors, Adrenergic, beta-3; Reverse Transcriptase Polymerase Chain Reaction; Risk Factors; Sex Factors; Triglycerides; White People

Biochemical and genetic interaction between the fragile X mental retardation protein and the microRNA pathway. - Jin, Peng; Zarnescu, Daniela C; Ceman, Stephanie; Nakamoto, Mika; Mowrey, Julie; Jongens, Thomas A; Nelson, David L; Moses, Kevin; Warren, Stephen T (Nat Neurosci, 2004)
Fragile X syndrome is caused by a loss of expression of the fragile X mental retardation protein (FMRP). FMRP is a selective RNA-binding protein which forms a messenger ribonucleoprotein (mRNP) complex that associates with polyribosomes. Recently, mRNA ligands associated with FMRP have been identified. However, the mechanism by which FMRP regulates the translation of its mRNA ligands remains unclear. MicroRNAs are small noncoding RNAs involved in translational control. Here we show that in vivo mammalian FMRP interacts with microRNAs and the components of the microRNA pathways including Dicer and the mammalian ortholog of Argonaute 1 (AGO1). Using two different Drosophila melanogaster models, we show that AGO1 is critical for FMRP function in neural development and synaptogenesis. Our results suggest that FMRP may regulate neuronal translation via microRNAs and links microRNAs with human disease.
Keywords: Animals; Argonaute Proteins; Blotting, Western; Disease Models, Animal; Drosophila melanogaster; Drosophila Proteins; Eye; Fragile X Syndrome; HeLa Cells; Humans; Immunohistochemistry; Male; MicroRNAs; Microscopy, Electron, Scanning; Nerve Tissue Proteins; Neuromuscular Junction; Neuronal Plasticity; Precipitin Tests; Ribonuclease III; RNA-Induced Silencing Complex

Complete genome sequence of Rickettsia typhi and comparison with sequences of other rickettsiae. - McLeod, Michael P; Qin, Xiang; Karpathy, Sandor E; Gioia, Jason; Highlander, Sarah K; Fox, George E; McNeill, Thomas Z; Jiang, Huaiyang; Muzny, Donna; Jacob, Leni S; Hawes, Alicia C; Sodergren, Erica; et al. (J Bacteriol, 2004)
Rickettsia typhi, the causative agent of murine typhus, is an obligate intracellular bacterium with a life cycle involving both vertebrate and invertebrate hosts. Here we present the complete genome sequence of R. typhi (1,111,496 bp) and compare it to the two published rickettsial genome sequences: R. prowazekii and R. conorii. We identified 877 genes in R. typhi encoding 3 rRNAs, 33 tRNAs, 3 noncoding RNAs, and 838 proteins, 3 of which are frameshifts. In addition, we discovered more than 40 pseudogenes, including the entire cytochrome c oxidase system. The three rickettsial genomes share 775 genes: 23 are found only in R. prowazekii and R. typhi, 15 are found only in R. conorii and R. typhi, and 24 are unique to R. typhi. Although most of the genes are colinear, there is a 35-kb inversion in gene order, which is close to the replication terminus, in R. typhi, compared to R. prowazekii and R. conorii. In addition, we found a 124-kb R. typhi-specific inversion, starting 19 kb from the origin of replication, compared to R. prowazekii and R. conorii. Inversions in this region are also seen in the unpublished genome sequences of R. sibirica and R. rickettsii, indicating that this region is a hot spot for rearrangements. Genome comparisons also revealed a 12-kb insertion in the R. prowazekii genome, relative to R. typhi and R. conorii, which appears to have occurred after the typhus (R. prowazekii and R. typhi) and spotted fever (R. conorii) groups diverged. The three-way comparison allowed further in silico analysis of the SpoT split genes, leading us to propose that the stringent response system is still functional in these rickettsiae.
Keywords: Chromosome Inversion; DNA, Bacterial; Electron Transport Complex IV; Frameshifting, Ribosomal; Gene Expression Regulation, Bacterial; Gene Rearrangement; Genes, Bacterial; Genes, rRNA; Genome, Bacterial; Genomics; Molecular Sequence Data; Pseudogenes; Rickettsia; Rickettsia conorii; Rickettsia typhi; RNA, Transfer; RNA, Untranslated; Sequence Analysis, DNA; Sequence Homology; Synteny

Construction of small genome BAC library for functional and genomic applications. - Smajs, David; Norris, Steven J; Weinstock, George M (Methods Mol Biol, 2004)
Keywords: Base Sequence; Chromosomes, Artificial, Bacterial; DNA Primers; DNA, Bacterial; Electrophoresis, Gel, Pulsed-Field; Escherichia coli; Genetic Vectors; Genome, Bacterial; Genomic Library; Genomics; Restriction Mapping; Treponema pallidum

Dynamic building of a BAC clone tiling path for the Rat Genome Sequencing Project. - Chen, Rui; Sodergren, Erica; Weinstock, George M; Gibbs, Richard A (Genome Res, 2004)
CLONEPICKER is a software pipeline that integrates sequence data with BAC clone fingerprints to dynamically select a minimal overlapping clone set covering the whole genome. In the Rat Genome Sequencing Project (RGSP), a hybrid strategy of "clone by clone" and "whole genome shotgun" approaches was used to maximize the merits of both approaches. Like the "clone by clone" method, one key challenge for this strategy was to select a low-redundancy clone set that covered the whole genome while the sequencing is in progress. The CLONEPICKER pipeline met this challenge using restriction enzyme fingerprint data, BAC end sequence data, and sequences generated from individual BAC clones as well as WGS reads. In the RGSP, an average of 7.5 clones was identified from each side of a seed clone, and the minimal overlapping clones were reliably selected. Combined with the assembled BAC fingerprint map, a set of BAC clones that covered >97% of the genome was identified and used in the RGSP.
Keywords: Animals; Chromosomes, Artificial, Bacterial; Computational Biology; Contig Mapping; DNA Fingerprinting; Genome; Rats; Sequence Analysis, DNA; Software

Finishing the euchromatic sequence of the human genome. (Nature, 2004)
The sequence of the human genome encodes the genetic instructions for human physiology, as well as rich information about human evolution. In 2001, the International Human Genome Sequencing Consortium reported a draft sequence of the euchromatic portion of the human genome. Since then, the international collaboration has worked to convert this draft into a genome sequence with high accuracy and nearly complete coverage. Here, we report the result of this finishing process. The current genome sequence (Build 35) contains 2.85 billion nucleotides interrupted by only 341 gaps. It covers approximately 99% of the euchromatic genome and is accurate to an error rate of approximately 1 event per 100,000 bases. Many of the remaining euchromatic gaps are associated with segmental duplications and will require focused work with new methods. The near-complete sequence, the first for a vertebrate, greatly improves the precision of biological analyses of the human genome including studies of gene number, birth and death. Notably, the human genome seems to encode only 20,000-25,000 protein-coding genes. The genome sequence reported here should serve as a firm foundation for biomedical research in the decades ahead.
Keywords: Amino Acid Sequence; Base Sequence; Centromere; Chromosomes, Artificial, Bacterial; Chromosomes, Human; DNA, Complementary; Euchromatin; Gene Duplication; Genes; Genome, Human; Heterochromatin; Human Genome Project; Humans; Molecular Sequence Data; Multigene Family; Physical Chromosome Mapping; Plasmids; Pseudogenes; Research Design; Sensitivity and Specificity; Sequence Analysis, DNA; Telomere

Fosmid-based physical mapping of the Histoplasma capsulatum genome. - Magrini, Vincent; Warren, Wesley C; Wallis, John; Goldman, William E; Xu, Jian; Mardis, Elaine R; McPherson, John D (Genome Res, 2004)
A fosmid library representing 10-fold coverage of the Histoplasma capsulatum G217B genome was used to construct a restriction-based physical map. The data obtained from three restriction endonuclease fingerprints, generated from each clone using BamHI, HindIII, and PstI endonucleases, were combined and used in FPC for automatic and manual contig assembly builds. Concomitantly, a whole-genome shotgun (WGS) sequencing of paired-end reads from plasmids and fosmids were assembled with PCAP, providing a predicted genome size of up to 43.5 Mbp and 17% repetitive DNA. Fosmid paired-end sequences in the WGS assembly provide anchoring information to the physical map and result in joining of existing physical map contigs into 84 clusters containing 9551 fosmid clones. Here, we detail mapping the Histoplasma capsulatum genome comprehensively in fosmids, resulting in an efficient paradigm for de novo sequencing that uses a map-assisted whole genome shotgun approach.
Keywords: Contig Mapping; DNA Fingerprinting; Genetic Vectors; Genome, Fungal; Genomic Library; Histoplasma; Restriction Mapping

Genetics. The critical region in trisomy 21. - Nelson, David L; Richard A Gibbs (Science, 2004)
Keywords: Animals; Chromosome Deletion; Chromosomes, Human, Pair 21; Chromosomes, Mammalian; Craniofacial Abnormalities; Crosses, Genetic; Disease Models, Animal; Down Syndrome; Female; Gene Duplication; Humans; Male; Mice; Recombination, Genetic; Skull; Trisomy

Genome sequence of the Brown Norway rat yields insights into mammalian evolution. - Gibbs, Richard A; Weinstock, George M; Metzker, Michael L; Muzny, Donna M; Sodergren, Erica J; Scherer, Steven; Scott, Graham; Steffen, David; Worley, Kim C; Burch, Paula E; Okwuonu, Geoffrey; Hines, Sandra; et al. (Nature, 2004)
The laboratory rat (Rattus norvegicus) is an indispensable tool in experimental medicine and drug development, having made inestimable contributions to human health. We report here the genome sequence of the Brown Norway (BN) rat strain. The sequence represents a high-quality 'draft' covering over 90% of the genome. The BN rat sequence is the third complete mammalian genome to be deciphered, and three-way comparisons with the human and mouse genomes resolve details of mammalian evolution. This first comprehensive analysis includes genes and proteins and their relation to human disease, repeated sequences, comparative genome-wide studies of mammalian orthologous chromosomal regions and rearrangement breakpoints, reconstruction of ancestral karyotypes and the events leading to existing species, rates of variation, and lineage-specific and lineage-independent evolutionary events such as expansion of gene families, orthology relations and protein evolution.
Keywords: Animals; Base Composition; Centromere; Chromosomes, Mammalian; CpG Islands; DNA Transposable Elements; DNA, Mitochondrial; Evolution, Molecular; Gene Duplication; Genome; Genomics; Humans; Introns; Male; Mice; Models, Molecular; Mutagenesis; Polymorphism, Single Nucleotide; Rats; Rats, Inbred BN; Regulatory Sequences, Nucleic Acid; Retroelements; RNA Splice Sites; RNA, Untranslated; Sequence Analysis, DNA; Telomere

Genome-wide linkage disequilibrium and haplotype maps. - Belmont, John W; Richard A Gibbs (Am J Pharmacogenomics, 2004)
There is currently a broad effort to produce genome-wide high-density linkage disequilibrium (LD) maps with single nucleotide polymorphisms. The hope is that the resulting maps can be exploited to find genes that affect the onset and severity of at least some common human diseases. These maps may also be useful for identifying genes that affect drug response or the likelihood of drug toxicities. The goal of this review is to provide a broad overview of some of the key concerns motivating the design of a major international project called the International Haplotype Map Project. The process of map production requires the identification of very large numbers of polymorphic sites, implementation of facile, highly accurate and inexpensive genotyping production pipelines, and provision for public access to the genotype data. Great progress has been made recently in genotyping methods and these advances are allowing very large-scale data collection. A major goal of these efforts is to enable the selection of subsets of markers that capture useful genetic information in short genomic intervals, while optimally reducing the number of markers that must be genotyped. Standard measures of LD provide a starting point but may not fully capture the complexity of the information inherent in the data. Extremely dense genotype data in several broadly representative populations (European, Chinese, Japanese, and Yoruba) should yield important insights into the genetic structure of most genes. Further study is required to determine how broadly applicable the data will be to other population groups. Significant challenges lie ahead in determining the best methods for the selection of markers in disease/phenotype studies, large-scale genotyping, and analysis of the resulting genetic data.
Keywords: Animals; Chromosome Mapping; Databases, Genetic; Genetic Markers; Genome; Haplotypes; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Population; Quality Control

Genomic analysis of the nuclear receptor family: new insights into structure, regulation, and evolution from the rat genome. - Zhang, Zhengdong; Burch, Paula E; Cooney, Austin J; Lanz, Rainer B; Pereira, Fred A; Wu, Jiaqian; Gibbs, Richard A; Weinstock, George; Wheeler, David A (Genome Res, 2004)
Completion of the Rattus norvegicus genome sequence enabled a global inventory and analysis of the nuclear receptors (NRs) in three mammalian species. Forty-nine NR members were found in mouse, 48 in human. Forty-seven were found in the rat, with gaps at the locations expected for the other two. Pairwise comparisons of their distribution in rat, mouse, and human identified 11 syntenic NR gene blocks, including three small clusters of two or three closely related genes, each spanning 40 kb to 1700 kb. The exon structure of the ligand-binding domain suggests that exon shuffling has played a role in the evolution of this family. An invariant splice junction in all members of the NR family except LXRbeta suggests a functional role for the intron. The ligand-binding domains of PXR and CAR are among the most divergent in the family. Their higher nucleotide substitution rates may be related to the central role played by these two NRs in the metabolism of the foreign compounds and may have resulted from limited positive selection.
Keywords: Amino Acid Sequence; Animals; Chromosome Mapping; DNA; Evolution, Molecular; Exons; Genome; Genome, Human; Humans; Ligands; Mice; Molecular Sequence Data; Phylogeny; Protein Structure, Quaternary; Protein Structure, Tertiary; Rats; Receptors, Androgen; Receptors, Cytoplasmic and Nuclear; Receptors, Estrogen; Receptors, Glucocorticoid; Receptors, Progesterone

Integrated and sequence-ordered BAC- and YAC-based physical maps for the rat genome. - Krzywinski, Martin; Wallis, John; Gösele, Claudia; Bosdet, Ian; Chiu, Readman; Graves, Tina; Hummel, Oliver; Layman, Dan; Mathewson, Carrie; Wye, Natasja; Zhu, Baoli; Albracht, Derek; et al. (Genome Res, 2004)
As part of the effort to sequence the genome of Rattus norvegicus, we constructed a physical map comprised of fingerprinted bacterial artificial chromosome (BAC) clones from the CHORI-230 BAC library. These BAC clones provide approximately 13-fold redundant coverage of the genome and have been assembled into 376 fingerprint contigs. A yeast artificial chromosome (YAC) map was also constructed and aligned with the BAC map via fingerprinted BAC and P1 artificial chromosome clones (PACs) sharing interspersed repetitive sequence markers with the YAC-based physical map. We have annotated 95% of the fingerprint map clones in contigs with coordinates on the version 3.1 rat genome sequence assembly, using BAC-end sequences and in silico mapping methods. These coordinates have allowed anchoring 358 of the 376 fingerprint map contigs onto the sequence assembly. Of these, 324 contigs are anchored to rat genome sequences localized to chromosomes, and 34 contigs are anchored to unlocalized portions of the rat sequence assembly. The remaining 18 contigs, containing 54 clones, still require placement. The fingerprint map is a high-resolution integrative data resource that provides genome-ordered associations among BAC, YAC, and PAC clones and the assembled sequence of the rat genome.
Keywords: Animals; Automation; Chromosomes; Chromosomes, Artificial, Bacterial; Chromosomes, Artificial, Yeast; Cloning, Molecular; Computational Biology; Contig Mapping; DNA Fingerprinting; Genetic Markers; Genome; Physical Chromosome Mapping; Polymerase Chain Reaction; Rats; Sequence Analysis, DNA

Integrating ethics and science in the International HapMap Project. (Nat Rev Genet, 2004)
Genomics resources that use samples from identified populations raise scientific, social and ethical issues that are, in many ways, inextricably linked. Scientific decisions about which populations to sample to produce the HapMap, an international genetic variation resource, have raised questions about the relationships between the social identities used to recruit participants and the biological findings of studies that will use the HapMap. The sometimes problematic implications of those complex relationships have led to questions about how to conduct genetic variation research that uses identified populations in an ethical way, including how to involve members of a population in evaluating the risks and benefits posed for everyone who shares that identity. The ways in which these issues are linked is increasingly drawing the scientific and ethical spheres of genomics research closer together.
Keywords: Databases, Genetic; Genetic Privacy; Genetic Variation; Genome, Human; Genomics; Haplotypes; Humans; Informed Consent; International Cooperation; Population Groups; Sampling Studies

Large-scale RT-PCR recovery of full-length cDNA clones. - Wu, Jia Qian; Garcia, Angela M; Hulyk, Steven; Sneed, Anna; Kowis, Carla; Yuan, Ye; Steffen, David; McPherson, John D; Gunaratne, Preethi H; Richard A Gibbs (Biotechniques, 2004)
Pseudogenes, alternative transcripts, noncoding RNA, and polymorphisms each add extensive complexity to the mammalian transcriptome and confound estimation of the total number of genes. Despite advanced algorithms for gene prediction and several large-scale efforts to obtain cDNA clones for all human open reading frames (ORFs), no single collection is complete. To enhance this effort, we have developed a high-throughput pipeline for reverse transcription PCR (RT-PCR) gene recovery. Most importantly, novel molecular strategies for improving RT-PCR yield of transcripts that have been difficult to isolate by other means and computational strategies for clone sequence validation have been developed and optimized. This systematic gene recovery pipeline allows both rescue of predicted human and rat genes and provides insight into the complexity of the transcriptome through comparisons with existing data sets.
Keywords: Automation; Cloning, Molecular; DNA, Complementary; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Sequence Analysis, DNA

Levodopa-responsive aromatic L-amino acid decarboxylase deficiency. - Chang, Yuh Terng; Sharma, Radhakant; Marsh, J Lawrence; McPherson, John D; Bedell, Joey A; Knust, Andreas; Bräutigam, Christa; Hoffmann, Georg F; Hyland, Keith (Ann Neurol, 2004)
We report three siblings, who were treated empirically with levodopa combined with carbidopa. There was an immediate therapeutic response. Biochemical investigation surprisingly showed the clinical phenotype to be caused by aromatic L-amino acid decarboxylase deficiency. Molecular characterization showed a homozygous point mutation (c.387 G-->A) in exon 3. Kinetic studies showed the mutation to decrease the binding affinity for the substrate. This, combined with structural modeling suggesting alteration of active site configuration, provided an explanation for the therapeutic response to levodopa.
Keywords: Adolescent; Adult; Alanine; Antiparkinson Agents; Aromatic-L-Amino-Acid Decarboxylases; Binding Sites; Carbidopa; Chromatography, High Pressure Liquid; Developmental Disabilities; DNA Mutational Analysis; Drug Combinations; Electrochemistry; Family Health; Female; Glycine; Humans; Levodopa; Male; Models, Structural; Point Mutation; Protein Binding; Protein Conformation

Pash: efficient genome-scale sequence anchoring by Positional Hashing. - Kalafus, Ken J; Jackson, Andrew R; Milosavljevic, Aleksandar (Genome Res, 2004)
Pash is a computer program for efficient, parallel, all-against-all comparison of very long DNA sequences. Pash implements Positional Hashing, a novel parallelizable method for sequence comparison based on k-mer representation of sequences. The Positional Hashing method breaks the comparison problem in a unique way that avoids the quadratic penalty encountered with other sensitive methods and confers inherent low-level parallelism. Furthermore, Positional Hashing allows one to readily and predictably trade between sensitivity and speed. In a simulated comparison task, anchoring computationally mutated reads onto a genome, the sensitivity of Pash was equal to or greater than that of BLAST and BLAT, with Pash outperforming these programs as the reads became shorter and less similar to the genome. Using modest computing resources, we employed Pash for two large-scale sequence comparison tasks: comparison of three mammalian genomes, and anchoring millions of chimpanzee whole-genome shotgun sequencing reads onto the human genome. The results of these comparisons by Pash agree with those computed by other methods that use more than an order of magnitude more computing resources. These results confirm the sensitivity of Positional Hashing.
Keywords: Animals; Chromosome Mapping; Cluster Analysis; Computational Biology; DNA; Genome; Genome, Human; Humans; Mice; Pan troglodytes; Rats; Sensitivity and Specificity; Software

A physical map of the chicken genome. - Wallis, John W; Aerts, Jan; Groenen, Martien A M; Crooijmans, Richard P M A; Layman, Dan; Graves, Tina A; Scheer, Debra E; Kremitzki, Colin; Fedele, Mary J; Mudd, Nancy K; Cardenas, Marco; Higginbotham, Jamey; et al. (Nature, 2004)
Strategies for assembling large, complex genomes have evolved to include a combination of whole-genome shotgun sequencing and hierarchal map-assisted sequencing. Whole-genome maps of all types can aid genome assemblies, generally starting with low-resolution cytogenetic maps and ending with the highest resolution of sequence. Fingerprint clone maps are based upon complete restriction enzyme digests of clones representative of the target genome, and ultimately comprise a near-contiguous path of clones across the genome. Such clone-based maps are used to validate sequence assembly order, supply long-range linking information for assembled sequences, anchor sequences to the genetic map and provide templates for closing gaps. Fingerprint maps are also a critical resource for subsequent functional genomic studies, because they provide a redundant and ordered sampling of the genome with clones. In an accompanying paper we describe the draft genome sequence of the chicken, Gallus gallus, the first species sequenced that is both a model organism and a global food source. Here we present a clone-based physical map of the chicken genome at 20-fold coverage, containing 260 contigs of overlapping clones. This map represents approximately 91% of the chicken genome and enables identification of chicken clones aligned to positions in other sequenced genomes.
Keywords: Animals; Chickens; Chromosomes, Artificial, Bacterial; Cloning, Molecular; Contig Mapping; DNA Fingerprinting; Genetic Linkage; Genome; Genomics; Physical Chromosome Mapping; Sequence Tagged Sites

Pol iota is a candidate for the mouse pulmonary adenoma resistance 2 locus, a major modifier of chemically induced lung neoplasia. - Wang, Min; Devereux, Theodora R; Vikis, Haris G; McCulloch, Scott D; Holliday, Wanda; Anna, Colleen; Wang, Yian; Bebenek, Katarzyna; Kunkel, Thomas A; Guan, Kunliang; You, Ming (Cancer Res, 2004)
In this study, we performed systematic candidate gene analyses of the Pulmonary adenoma resistance 2 locus. Differential gene expression in lung tissues and nucleotide polymorphisms in coding regions between A/J and BALB/cJ mice were examined using reverse transcription-PCR and direct sequencing. Although not all genes in the interval were analyzed at this moment due to the recent database updating, we have found that the Pol iota gene, encoding the DNA polymerase iota, contains 25 nucleotide polymorphisms in its coding region between A/J and BALB/cJ mice, resulting in a total of ten amino acid changes. Primer extension assays with purified BALB/cJ and A/J proteins in vitro demonstrate that both forms of Pol iota are active but that they may differ in substrate discrimination, which may affect the formation of Kras2 mutations in mouse lung tumors. Altered expression of POL iota protein and an amino acid-changing nucleotide polymorphism were observed in human lung cancer cells, suggesting a possible role in the development of lung cancer. Thus, our data support the Pol iota gene as a modifier of lung tumorigenesis by altering DNA polymerase activity.
Keywords: Adenoma; Alternative Splicing; Amino Acid Sequence; Animals; DNA Polymerase iota; DNA-Directed DNA Polymerase; Gene Expression Regulation, Neoplastic; Humans; Immunity, Innate; Lung; Lung Neoplasms; Mice; Mice, Inbred A; Mice, Inbred BALB C; Molecular Sequence Data; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins; Proto-Oncogene Proteins p21(ras); ras Proteins; RNA, Messenger; Sequence Homology, Amino Acid; Tumor Cells, Cultured

Pooled Genomic Indexing (PGI): analysis and design of experiments. - Csuros, Miklos; Milosavljevic, Aleksandar (J Comput Biol, 2004)
Pooled Genomic Indexing (PGI) is a novel method for physical mapping of clones onto known sequences. PGI is carried out by pooling arrayed clones and generating shotgun sequence reads from the pools. The shotgun sequences are compared to a reference sequence. In the simplest case, clones are placed on an array and are pooled by rows and columns. If a shotgun sequence from a row pool and another shotgun sequence from a column pool match the reference sequence at a close distance, they are both assigned to the clone at the intersection of the two pools. Accordingly, the clone is mapped onto the region of the reference sequence between the two matches. A probabilistic model for PGI is developed, and several pooling designs are described and analyzed, including transversal designs and designs from linear codes. The probabilistic model and the pooling schemes are validated in simulated experiments where 625 rat bacterial artificial chromosome (BAC) clones and 207 mouse BAC clones are mapped onto homologous human sequence.
Keywords: Animals; Chromosomes, Artificial, Bacterial; Computational Biology; Data Interpretation, Statistical; Mice; Phylogeny; Physical Chromosome Mapping; Probability; Rats; Research Design

Preparation of BAC libraries from bacterial genomes by in vitro packaging. - Pal, Sangita; Mak, Solida; Weinstock, George M (Methods Mol Biol, 2004)
Keywords: Bacteriophage lambda; Base Sequence; Centrifugation, Density Gradient; Chromosomes, Artificial, Bacterial; DNA, Bacterial; Electrophoresis, Agar Gel; Escherichia coli; Genetic Vectors; Genome, Bacterial; Genomic Library; Treponema

Sequence and comparative analysis of the chicken genome provide unique perspectives on vertebrate evolution. (Nature, 2004)
We present here a draft genome sequence of the red jungle fowl, Gallus gallus. Because the chicken is a modern descendant of the dinosaurs and the first non-mammalian amniote to have its genome sequenced, the draft sequence of its genome--composed of approximately one billion base pairs of sequence and an estimated 20,000-23,000 genes--provides a new perspective on vertebrate genome evolution, while also improving the annotation of mammalian genomes. For example, the evolutionary distance between chicken and human provides high specificity in detecting functional elements, both non-coding and coding. Notably, many conserved non-coding sequences are far from genes and cannot be assigned to defined functional classes. In coding regions the evolutionary dynamics of protein domains and orthologous groups illustrate processes that distinguish the lineages leading to birds and mammals. The distinctive properties of avian microchromosomes, together with the inferred patterns of conserved synteny, provide additional insights into vertebrate chromosome architecture.
Keywords: Animals; Avian Proteins; Chickens; Conserved Sequence; DNA Transposable Elements; Evolution, Molecular; Gene Duplication; Genes; Genome; Genomics; Humans; Long Interspersed Nucleotide Elements; Multigene Family; Mutagenesis; Physical Chromosome Mapping; Pseudogenes; Retroviridae; RNA, Untranslated; Sequence Analysis, DNA; Short Interspersed Nucleotide Elements; Synteny; Vertebrates

Single nucleotide polymorphism (SNP) analysis of mouse quantitative trait loci for identification of candidate genes. - Yan, Y; Wang, M; Lemon, W J; You, M (J Med Genet, 2004)
Keywords: Acute Disease; Animals; Chromosomes, Mammalian; Disease Models, Animal; Disease Susceptibility; Genetic Predisposition to Disease; Lung; Lung Injury; Lung Neoplasms; Mice; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Seizures; Trypanosomiasis

Somatic and germline instability of the ATTCT repeat in spinocerebellar ataxia type 10. - Matsuura, Tohru; Fang, Ping; Lin, Xi; Khajavi, Mehrdad; Tsuji, Kuniko; Rasmussen, Astrid; Grewal, Raji P; Achari, Madhureeta; Alonso, Maria E; Pulst, Stefan M; Zoghbi, Huda Y; Nelson, David L; et al. (Am J Hum Genet, 2004)
Spinocerebellar ataxia type 10 (SCA10) is an autosomal dominant disorder characterized by ataxia, seizures, and anticipation. It is caused by an expanded ATTCT pentanucleotide repeat in intron 9 of a novel gene, designated "SCA10." The ATTCT expansion in SCA10 represents a novel class of microsatellite repeat and is one of the largest found to cause human diseases. The expanded ATTCT repeat is unstably transmitted from generation to generation, and an inverse correlation has been observed between size of repeat and age at onset. In this multifamily study, we investigated the intergenerational instability, somatic and germline mosaicism, and age-dependent repeat-size changes of the expanded ATTCT repeat. Our results showed that (1) the expanded ATTCT repeats are highly unstable when paternally transmitted, whereas maternal transmission resulted in significantly smaller changes in repeat size; (2) blood leukocytes, lymphoblastoid cells, buccal cells, and sperm have a variable degree of mosaicism in ATTCT expansion; (3) the length of the expanded repeat was not observed to change in individuals over a 5-year period; and (4) clinically determined anticipation is sometimes associated with intergenerational contraction rather than expansion of the ATTCT repeat.
Keywords: Age Distribution; Cell Line; Disease Transmission, Infectious; DNA; Female; Genes, Dominant; Germ Cells; Humans; Leukocytes; Male; Microsatellite Repeats; Mouth Mucosa; Pedigree; Repetitive Sequences, Nucleic Acid; Spermatozoa; Spinocerebellar Ataxias

The status, quality, and expansion of the NIH full-length cDNA project: the Mammalian Gene Collection (MGC). - Gerhard, Daniela S; Wagner, Lukas; Feingold, Elise A; Shenmen, Carolyn M; Grouse, Lynette H; Schuler, Greg; Klein, Steven L; Old, Susan; Rasooly, Rebekah; Good, Peter; Guyer, Mark; Peck, Allison M; et al. (Genome Res, 2004)
The National Institutes of Health's Mammalian Gene Collection (MGC) project was designed to generate and sequence a publicly accessible cDNA resource containing a complete open reading frame (ORF) for every human and mouse gene. The project initially used a random strategy to select clones from a large number of cDNA libraries from diverse tissues. Candidate clones were chosen based on 5'-EST sequences, and then fully sequenced to high accuracy and analyzed by algorithms developed for this project. Currently, more than 11,000 human and 10,000 mouse genes are represented in MGC by at least one clone with a full ORF. The random selection approach is now reaching a saturation point, and a transition to protocols targeted at the missing transcripts is now required to complete the mouse and human collections. Comparison of the sequence of the MGC clones to reference genome sequences reveals that most cDNA clones are of very high sequence quality, although it is likely that some cDNAs may carry missense variants as a consequence of experimental artifact, such as PCR, cloning, or reverse transcriptase errors. Recently, a rat cDNA component was added to the project, and ongoing frog (Xenopus) and zebrafish (Danio) cDNA projects were expanded to take advantage of the high-throughput MGC pipeline.
Keywords: Animals; Cloning, Molecular; Computational Biology; DNA Primers; DNA, Complementary; Gene Library; Humans; Mice; National Institutes of Health (U.S.); Open Reading Frames; Rats; United States; Xenopus laevis; Zebrafish

WormBase: a multi-species resource for nematode biology and genomics. - Harris, Todd W; Chen, Nansheng; Cunningham, Fiona; Tello-Ruiz, Marcela; Antoshechkin, Igor; Bastiani, Carol; Bieri, Tamberlyn; Blasiar, Darin; Bradnam, Keith; Chan, Juancarlos; Chen, Chao-Kung; Chen, Wen J; et al. (Nucleic Acids Res, 2004)
WormBase (http://www.wormbase.org/) is the central data repository for information about Caenorhabditis elegans and related nematodes. As a model organism database, WormBase extends beyond the genomic sequence, integrating experimental results with extensively annotated views of the genome. The WormBase Consortium continues to expand the biological scope and utility of WormBase with the inclusion of large-scale genomic analyses, through active data and literature curation, through new analysis and visualization tools, and through refinement of the user interface. Over the past year, the nearly complete genomic sequence and comparative analyses of the closely related species Caenorhabditis briggsae have been integrated into WormBase, including gene predictions, ortholog assignments and a new synteny viewer to display the relationships between the two species. Extensive site-wide refinement of the user interface now provides quick access to the most frequently accessed resources and a consistent browsing experience across the site. Unified single-page views now provide complete summaries of commonly accessed entries like genes. These advances continue to increase the utility of WormBase for C.elegans researchers, as well as for those researchers exploring problems in functional and comparative genomics in the context of a powerful genetic system.
Keywords: Animals; Caenorhabditis; Caenorhabditis elegans; Computational Biology; Databases, Genetic; Genomics; Information Storage and Retrieval; Internet; User-Computer Interface

Association of the T-cell regulatory gene CTLA4 with susceptibility to autoimmune disease. - Ueda, Hironori; Howson, Joanna M M; Esposito, Laura; Heward, Joanne; Snook, Hywel; Chamberlain, Giselle; Rainbow, Daniel B; Hunter, Kara M D; Smith, Annabel N; Di Genova, Gianfranco; Herr, Mathias H; Dahlman, Ingrid; et al. (Nature, 2003)
Genes and mechanisms involved in common complex diseases, such as the autoimmune disorders that affect approximately 5% of the population, remain obscure. Here we identify polymorphisms of the cytotoxic T lymphocyte antigen 4 gene (CTLA4)--which encodes a vital negative regulatory molecule of the immune system--as candidates for primary determinants of risk of the common autoimmune disorders Graves' disease, autoimmune hypothyroidism and type 1 diabetes. In humans, disease susceptibility was mapped to a non-coding 6.1 kb 3' region of CTLA4, the common allelic variation of which was correlated with lower messenger RNA levels of the soluble alternative splice form of CTLA4. In the mouse model of type 1 diabetes, susceptibility was also associated with variation in CTLA-4 gene splicing with reduced production of a splice form encoding a molecule lacking the CD80/CD86 ligand-binding domain. Genetic mapping of variants conferring a small disease risk can identify pathways in complex disorders, as exemplified by our discovery of inherited, quantitative alterations of CTLA4 contributing to autoimmune tissue destruction.
Keywords: Abatacept; Alternative Splicing; Animals; Antigens, CD; Antigens, Differentiation; Autoimmune Diseases; Base Sequence; CTLA-4 Antigen; Diabetes Mellitus, Type 1; Disease Models, Animal; Genetic Predisposition to Disease; Genotype; Graves Disease; Humans; Hypothyroidism; Immunoconjugates; Mice; Polymorphism, Single Nucleotide; Protein Isoforms; T-Lymphocytes

Clone-array pooled shotgun mapping and sequencing: design and analysis of experiments. - Csuros, Miklos; Li, Bingshan; Milosavljevic, Aleksandar (Genome Inform, 2003)
This paper studies sequencing and mapping methods that rely solely on pooling and shotgun sequencing of clones. First, we scrutinize and improve the recently proposed Clone-Array Pooled Shotgun Sequencing (CAPSS) method, which delivers a BAC-linked assembly of a whole genome sequence. Secondly, we introduce a novel physical mapping method, called Clone-Array Pooled Shotgun Mapping (CAPS-MAP), which computes the physical ordering of BACs in a random library. Both CAPSS and CAPS-MAP construct subclone libraries from pooled genomic BAC clones.
Keywords: Animals; Chromosomes, Artificial, Bacterial; Computational Biology; Computer Simulation; Drosophila melanogaster; Genome; Reproducibility of Results; Research Design; Sequence Alignment

Concatenation cDNA sequencing for transcriptome analysis. - Gunaratne, Preethi H; Wu, Jia Qian; Garcia, Angela M; Hulyk, Steven; Kim C Worley; Margolin, Judith F; Richard A Gibbs (C R Biol, 2003)
We describe a high-throughput cDNA sequencing pipeline (http://www.hgsc.bcm.tmc.edu/projects/cdna) built in response to the emerging need for rapid sequencing of large cDNA collections. Using this strategy cDNA inserts are purified and joined through concatenation into large molecules. These 'pseudo-BACs' are subjected to random shotgun sequencing whereby the majority of cDNA inserts in the pool are sequenced. Using this concatenation cDNA sequencing platform, we have contributed more than 13000 full-length cDNA sequences from human and mouse to the Mammalian Gene Collection (MGC).
Keywords: Cloning, Molecular; DNA, Complementary; DNA, Concatenated; Genetic Techniques; Humans; Sequence Analysis, DNA; Transcription, Genetic

Differentially expressed nucleolar TGF-beta1 target (DENTT) in mouse development. - Ozbun, Laurent L; Martínez, Alfredo; Angdisen, Jerry; Umphress, Sarah; Kang, Yang; Wang, Min; You, Ming; Jakowlew, Sonia B (Dev Dyn, 2003)
Differentially expressed nucleolar TGF-beta1 target (DENTT) is a recently identified gene whose mRNA is differentially affected by TGF-beta1 in TGF-beta1-responsive human lung cancer cells and who is a new member of the TSPY/TSPY-like/SET/NAP-1 (TTSN) protein superfamily. Here, we report that mouse DENTT mRNA contains a 2031-bp open reading frame that encodes a predicted polypeptide of 677-amino acids with a relative molecular mass of 77,671 Da. The mouse and human DENTT sequences show 77% and 78% homology at the nucleotide and amino acid level, respectively. Mouse DENTT is predicted to be a nuclear protein with two nuclear localization signals (NLS), two coiled-coil regions, and a domain that shows significant identity to a region that defines the TTSN superfamily. Green fluorescent protein (GFP)-tagged full-length mouse DENTT transfected into COS-7 cells showed localization predominantly in the nucleolus. Reverse transcription-polymerase chain reaction amplification, Northern hybridization, and Western blot analyses showed expression of mouse DENTT mRNA and protein throughout mouse embryogenesis. Immunohistochemical staining analysis showed that DENTT is expressed in multiple tissues in a defined spatiotemporal pattern during mouse embryogenesis. The heart and primitive brain were the first organs of the embryo that showed immunoreactivity for the DENTT antibody by day 8 of development (E8). In the developing mouse brain, the choroid plexus was intensely stained for DENTT in all stages of development. The spinal cord and dorsal root ganglia were also positive for DENTT staining beginning in the 11-day-old embryo (E11), where homogeneous immunostaining was observed throughout the developing neurons. By day 16 of development (E16), only a small subset of the neuronal population in the spinal cord and dorsal root ganglia was positively stained for DENTT. DENTT immunoreactivity increased steadily with maturation as the differentiation of cartilage and osteoblasts proceeded and reached a maximum in the growth plate during endochondral ossification. DENTT expression was also detected in multiple rodent cell types in vitro, including mouse F9 embryonal carcinoma (EC) cells. Addition of retinoic acid or sodium butyrate to F9 EC cells showed a rapid decrease in expression of DENTT protein occurring by 1 hr that continued to decrease to almost undetectable levels after 24 hr. Cotransfection of full-length mouse DENTT expression plasmid with 3TPLux or COL7A1Luc Luciferase reporter plasmids into F9 EC cells significantly increased the level of 3TPLux reporter transcription while decreasing the level of COL7A1Luc reporter transcription, suggesting that DENTT may play multiple roles in modulating transcriptional responses. These findings suggest new roles for the TTSN superfamily during embryogenesis and differentiation.
Keywords: 3T3 Cells; Animals; Base Sequence; Blotting, Northern; Blotting, Western; Bone and Bones; Cardiovascular System; Cell Cycle Proteins; Cell Differentiation; Cell Nucleolus; Chorion; Digestive System; DNA-Binding Proteins; Female; Gene Expression Regulation, Developmental; Genes, Reporter; Heart; Humans; Immunohistochemistry; Male; Mice; Mice, Inbred C57BL; Molecular Sequence Data; Nervous System; Nuclear Proteins; Placenta; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Sequence Homology, Amino Acid; Transcriptional Activation; Transforming Growth Factor beta; Transforming Growth Factor beta1

The DNA sequence and analysis of human chromosome 14. - Heilig, Roland; Eckenberg, Ralph; Petit, Jean-Louis; Fonknechten, Núria; Da Silva, Corinne; Cattolico, Laurence; Levy, Michaël; Barbe, Valérie; de Berardinis, Véronique; Ureta-Vidal, Abel; Pelletier, Eric; Vico, Virginie; et al. (Nature, 2003)
Chromosome 14 is one of five acrocentric chromosomes in the human genome. These chromosomes are characterized by a heterochromatic short arm that contains essentially ribosomal RNA genes, and a euchromatic long arm in which most, if not all, of the protein-coding genes are located. The finished sequence of human chromosome 14 comprises 87,410,661 base pairs, representing 100% of its euchromatic portion, in a single continuous segment covering the entire long arm with no gaps. Two loci of crucial importance for the immune system, as well as more than 60 disease genes, have been localized so far on chromosome 14. We identified 1,050 genes and gene fragments, and 393 pseudogenes. On the basis of comparisons with other vertebrate genomes, we estimate that more than 96% of the chromosome 14 genes have been annotated. From an analysis of the CpG island occurrences, we estimate that 70% of these annotated genes are complete at their 5' end.
Keywords: 5' Untranslated Regions; Animals; Base Composition; Chromosomes, Artificial; Chromosomes, Human, Pair 14; CpG Islands; DNA, Mitochondrial; DNA, Ribosomal; Genes; Genomics; Humans; Immunity; Mice; Microsatellite Repeats; Molecular Sequence Data; Open Reading Frames; Physical Chromosome Mapping; Pseudogenes; Reproducibility of Results; Sequence Analysis, DNA; Synteny

An Enterococcus faecium secreted antigen, SagA, exhibits broad-spectrum binding to extracellular matrix proteins and appears essential for E. faecium growth. - Teng, Fang; Kawalec, Magdalena; Weinstock, George M; Hryniewicz, Waleria; Murray, Barbara E (Infect Immun, 2003)
A gene encoding a major secreted antigen, SagA, was identified in Enterococcus faecium by screening an E. faecium genomic expression library with sera from patients with E. faecium-associated endocarditis. Recombinant SagA protein showed broad-spectrum binding to extracellular matrix (ECM) proteins, including fibrinogen, collagen type I, collagen type IV, fibronectin, and laminin. A fibrinogen-binding protein, purified from culture supernatants of an E. faecium clinical isolate, was found to match the N-terminal sequence of the predicted SagA protein and to react with the anti-SagA antibody, confirming that it was the SagA protein; this protein appeared as an 80- to 90-kDa smear on a Western blot that was sensitive to proteinase K and resistant to periodate treatment and glycoprotein staining. When overexpressed in E. faecium and Escherichia coli, the native and recombinant SagA proteins formed stable oligomers, apparently via their C-terminal domains. The SagA protein is composed of three domains: (i) a putative coiled-coil N-terminal domain that shows homology to the N-terminal domain of Streptococcus mutans SagA protein (42% similarity), previously shown to be involved in cell wall integrity and cell shape maintenance, and to the P45 protein of Listeria monocytogenes (41% similarity); (ii) a central domain containing direct repeats; and (iii) a C-terminal domain that is similar to that found in various proteins, including P45 (50% similarity) and P60 (52% similarity) of L. monocytogenes. The P45 and P60 proteins both have cell wall hydrolase activity, and the latter has also been shown to be involved in virulence, whereas cell wall hydrolase activity was not detected for SagA protein. The E. faecium sagA gene, like the S. mutans homologue, is located in a cluster of genes encoding proteins that appear to be involved in cell wall metabolism and could not be disrupted unless it was first transcomplemented, suggesting that the sagA gene is essential for E. faecium growth and may be involved in cell wall metabolism. In conclusion, the extracelluar E. faecium SagA protein is apparently essential for growth, shows broad-spectrum binding to ECM proteins, forms oligomers, and is antigenic during infection.
Keywords: Amino Acid Sequence; Antigens, Bacterial; Bacterial Proteins; Base Sequence; Chromosome Mapping; DNA, Bacterial; Enterococcus faecium; Extracellular Matrix Proteins; Fibrinogen; Genes, Bacterial; Humans; Molecular Sequence Data; Protein Binding; Recombinant Proteins; Virulence

FMR2 function: insight from a mouse knockout model. - Gu, Y; Nelson, D L (Cytogenet Genome Res, 2003)
The FMR2 gene is dysregulated by the fragile X E triplet repeat expansion in patients with FRAXE mental retardation syndrome. A CCG triplet, located in the 5' untranslated region of the FRAXE gene undergoes expansion and methylation in these patients, eliminating detectable gene transcription. FRAXE syndrome is distinct from fragile X syndrome, a more common genetic form of mental retardation caused by expansion and methylation of a similar repeat in the FMR1 gene located 600 kb proximal to FRAXE. FRAXE syndrome is rare, and patients' phenotypes are highly variable, leading to difficulties with predicting specific FMR2 functions based on the human disease. Recently, Lilliputian(Lilli), a Drosophila FMR2 orthologue, was identified; this gene has been linked with several signal transduction pathways, including the transforming growth factor-beta (TGF-beta) pathway, the Raf/MEK/MAP kinase (MAPK) pathway, and the P13K/PKB pathway. Mutation of Lilli shows defects in germinal band extension, cytoskeletal structure, cell growth, and organ development. The Lilli gene suggests possible functions for FMR2 (and related genes) in humans and mice, but cannot predict specific functions. Modeling FMR2 mutation in the mouse will be useful to understand specific functions of this gene in vertebrates. This review presents what has been learned thus far from the FMR2 knockout mouse model and suggests future studies on this model in order to compare it with the human FRAXE mental retardation disorder, Lilli mutants in Drosophila and other mouse models of genes in this family.
Keywords: Amino Acid Sequence; Animals; Disease Models, Animal; Fragile X Syndrome; Gene Expression Regulation, Developmental; Genes; Humans; Mental Retardation, X-Linked; Mice; Mice, Knockout; Molecular Sequence Data; Nuclear Proteins; Sequence Homology, Amino Acid; Trans-Activators; Trinucleotide Repeat Expansion

From vulnerable plaque to vulnerable patient: a call for new definitions and risk assessment strategies: Part I. - Naghavi, Morteza; Libby, Peter; Falk, Erling; Casscells, S Ward; Litovsky, Silvio; Rumberger, John; Badimon, Juan Jose; Stefanadis, Christodoulos; Moreno, Pedro; Pasterkamp, Gerard; Fayad, Zahi; Stone, Peter H; et al. (Circulation, 2003)
Atherosclerotic cardiovascular disease results in >19 million deaths annually, and coronary heart disease accounts for the majority of this toll. Despite major advances in treatment of coronary heart disease patients, a large number of victims of the disease who are apparently healthy die suddenly without prior symptoms. Available screening and diagnostic methods are insufficient to identify the victims before the event occurs. The recognition of the role of the vulnerable plaque has opened new avenues of opportunity in the field of cardiovascular medicine. This consensus document concludes the following. (1) Rupture-prone plaques are not the only vulnerable plaques. All types of atherosclerotic plaques with high likelihood of thrombotic complications and rapid progression should be considered as vulnerable plaques. We propose a classification for clinical as well as pathological evaluation of vulnerable plaques. (2) Vulnerable plaques are not the only culprit factors for the development of acute coronary syndromes, myocardial infarction, and sudden cardiac death. Vulnerable blood (prone to thrombosis) and vulnerable myocardium (prone to fatal arrhythmia) play an important role in the outcome. Therefore, the term "vulnerable patient" may be more appropriate and is proposed now for the identification of subjects with high likelihood of developing cardiac events in the near future. (3) A quantitative method for cumulative risk assessment of vulnerable patients needs to be developed that may include variables based on plaque, blood, and myocardial vulnerability. In Part I of this consensus document, we cover the new definition of vulnerable plaque and its relationship with vulnerable patients. Part II of this consensus document focuses on vulnerable blood and vulnerable myocardium and provide an outline of overall risk assessment of vulnerable patients. Parts I and II are meant to provide a general consensus and overviews the new field of vulnerable patient. Recently developed assays (eg, C-reactive protein), imaging techniques (eg, CT and MRI), noninvasive electrophysiological tests (for vulnerable myocardium), and emerging catheters (to localize and characterize vulnerable plaque) in combination with future genomic and proteomic techniques will guide us in the search for vulnerable patients. It will also lead to the development and deployment of new therapies and ultimately to reduce the incidence of acute coronary syndromes and sudden cardiac death. We encourage healthcare policy makers to promote translational research for screening and treatment of vulnerable patients.
Keywords: Acute Disease; Arteriosclerosis; Consensus; Coronary Disease; Death, Sudden, Cardiac; Disease Progression; Humans; Models, Cardiovascular; Risk Assessment; Syndrome; Terminology as Topic

From vulnerable plaque to vulnerable patient: a call for new definitions and risk assessment strategies: Part II. - Naghavi, Morteza; Libby, Peter; Falk, Erling; Casscells, S Ward; Litovsky, Silvio; Rumberger, John; Badimon, Juan Jose; Stefanadis, Christodoulos; Moreno, Pedro; Pasterkamp, Gerard; Fayad, Zahi; Stone, Peter H; et al. (Circulation, 2003)
Atherosclerotic cardiovascular disease results in >19 million deaths annually, and coronary heart disease accounts for the majority of this toll. Despite major advances in treatment of coronary heart disease patients, a large number of victims of the disease who are apparently healthy die suddenly without prior symptoms. Available screening and diagnostic methods are insufficient to identify the victims before the event occurs. The recognition of the role of the vulnerable plaque has opened new avenues of opportunity in the field of cardiovascular medicine. This consensus document concludes the following. (1) Rupture-prone plaques are not the only vulnerable plaques. All types of atherosclerotic plaques with high likelihood of thrombotic complications and rapid progression should be considered as vulnerable plaques. We propose a classification for clinical as well as pathological evaluation of vulnerable plaques. (2) Vulnerable plaques are not the only culprit factors for the development of acute coronary syndromes, myocardial infarction, and sudden cardiac death. Vulnerable blood (prone to thrombosis) and vulnerable myocardium (prone to fatal arrhythmia) play an important role in the outcome. Therefore, the term "vulnerable patient" may be more appropriate and is proposed now for the identification of subjects with high likelihood of developing cardiac events in the near future. (3) A quantitative method for cumulative risk assessment of vulnerable patients needs to be developed that may include variables based on plaque, blood, and myocardial vulnerability. In Part I of this consensus document, we cover the new definition of vulnerable plaque and its relationship with vulnerable patients. Part II of this consensus document will focus on vulnerable blood and vulnerable myocardium and provide an outline of overall risk assessment of vulnerable patients. Parts I and II are meant to provide a general consensus and overviews the new field of vulnerable patient. Recently developed assays (eg, C-reactive protein), imaging techniques (eg, CT and MRI), noninvasive electrophysiological tests (for vulnerable myocardium), and emerging catheters (to localize and characterize vulnerable plaque) in combination with future genomic and proteomic techniques will guide us in the search for vulnerable patients. It will also lead to the development and deployment of new therapies and ultimately to reduce the incidence of acute coronary syndromes and sudden cardiac death. We encourage healthcare policy makers to promote translational research for screening and treatment of vulnerable patients.
Keywords: Animals; Biomarkers; Coronary Artery Disease; Death, Sudden, Cardiac; Disease Susceptibility; Female; Humans; Male; Mass Screening; Myocardial Infarction; Myocardium; Risk Assessment; Severity of Illness Index; Swine; Thrombophilia

Genetic disruption of cortical interneuron development causes region- and GABA cell type-specific deficits, epilepsy, and behavioral dysfunction. - Powell, Elizabeth M; Campbell, Daniel B; Stanwood, Gregg D; Davis, Caleb; Noebels, Jeffrey L; Levitt, Pat (J Neurosci, 2003)
The generation of properly functioning circuits during brain development requires precise timing of cell migration and differentiation. Disruptions in the developmental plan may lead to neurological and psychiatric disorders. Neocortical circuits rely on inhibitory GABAergic interneurons, the majority of which migrate from subcortical sources. We have shown that the pleiotropic molecule hepatocyte growth factor/scatter factor (HGF/SF) mediates interneuron migration. Mice with a targeted mutation of the gene encoding urokinase plasminogen activator receptor (uPAR), a key component in HGF/SF activation and function, have decreased levels of HGF/SF and a 50% reduction in neocortical GABAergic interneurons at embryonic and perinatal ages. Disruption of interneuron development leads to early lethality in most models. Thus, the long-term consequences of such perturbations are unknown. Mice of the uPAR-/- strain survive until adulthood, and behavior testing demonstrates that they have an increased anxiety state. The uPAR-/- strain also exhibits spontaneous seizure activity and higher susceptibility to pharmacologically induced convulsions. The neocortex of the adult uPAR-/- mouse exhibits a dramatic region- and subtype-specific decrease in GABA-immunoreactive interneurons. Anterior cingulate and parietal cortical areas contain 50% fewer GABAergic interneurons compared with wild-type littermates. However, interneuron numbers in piriform and visual cortical areas do not differ from those of normal mice. Characterization of interneuron subpopulations reveals a near complete loss of the parvalbumin subtype, with other subclasses remaining intact. These data demonstrate that a single gene mutation can selectively alter the development of cortical interneurons in a region- and cell subtype-specific manner, with deficits leading to long-lasting changes in circuit organization and behavior.
Keywords: Animals; Anxiety; Behavior, Animal; Calcium-Binding Proteins; Cell Count; Darkness; Electroencephalography; Epilepsy; Exploratory Behavior; GABA Antagonists; gamma-Aminobutyric Acid; Genetic Predisposition to Disease; Interneurons; Light; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Neocortex; Receptors, Cell Surface; Receptors, Urokinase Plasminogen Activator; Spatial Behavior

Graded phenotypic response to partial and complete deficiency of a brain-specific transcript variant of the winged helix transcription factor RFX4. - Blackshear, Perry J; Graves, Joan P; Stumpo, Deborah J; Cobos, Inma; Rubenstein, John L R; Zeldin, Darryl C (Development, 2003)
One line of mice harboring a cardiac-specific epoxygenase transgene developed head swelling and rapid neurological decline in young adulthood, and had marked hydrocephalus of the lateral and third ventricles. The transgene was found to be inserted into an intron in the mouse Rfx4 locus. This insertion apparently prevented expression of a novel variant transcript of RFX4 (RFX4_v3), a member of the regulatory factor X family of winged helix transcription factors. Interruption of two alleles resulted in profound failure of dorsal midline brain structure formation and perinatal death, presumably by interfering with expression of downstream genes. Interruption of a single allele prevented formation of the subcommissural organ, a structure important for cerebrospinal fluid flow through the aqueduct of Sylvius, and resulted in congenital hydrocephalus. These data implicate the RFX4_v3 variant transcript as being crucial for early brain development, as well as for the genesis of the subcommissural organ. These findings may be relevant to human congenital hydrocephalus, a birth defect that affects approximately 0.6 per 1000 newborns.
Keywords: Alternative Splicing; Amino Acid Sequence; Animals; Brain; DNA-Binding Proteins; Embryo, Mammalian; Helix-Turn-Helix Motifs; Humans; Hydrocephalus; In Situ Hybridization; Mice; Mice, Transgenic; Molecular Sequence Data; Phenotype; Protein Isoforms; Regulatory Factor X Transcription Factors; Sequence Alignment; Tissue Distribution; Transcription Factors

Haplotype structure, LD blocks, and uneven recombination within the LRP5 gene. - Twells, Rebecca C J; Mein, Charles A; Phillips, Michael S; Hess, J Fred; Veijola, Riitta; Gilbey, Matthew; Bright, Matthew; Metzker, Michael; Lie, Benedicte A; Kingsnorth, Amanda; Gregory, Edward; Nakagawa, Yusuke; et al. (Genome Res, 2003)
Patterns of linkage disequilibrium (LD) in the human genome are beginning to be characterized, with a paucity of haplotype diversity in "LD blocks," interspersed by apparent "hot spots" of recombination. Previously, we cloned and physically characterized the low-density lipoprotein-receptor-related protein 5 (LRP5) gene. Here, we have extensively analysed both LRP5 and its flanking three genes, spanning 269 kb, for single nucleotide polymorphisms (SNPs), and we present a comprehensive SNP map comprising 95 polymorphisms. Analysis revealed high levels of recombination across LRP5, including a hot-spot region from intron 1 to intron 7 of LRP5, where there are 109 recombinants/Mb (4882 meioses), in contrast to flanking regions of 14.6 recombinants/Mb. This region of high recombination could be delineated into three to four hot spots, one within a 601-bp interval. For LRP5, three haplotype blocks were identified, flanked by the hot spots. Each LD block comprised over 80% common haplotypes, concurring with a previous study of 14 genes that showed that common haplotypes account for at least 80% of all haplotypes. The identification of hot spots in between these LD blocks provides additional evidence that LD blocks are separated by areas of higher recombination.
Keywords: 3' Flanking Region; 5' Flanking Region; Alleles; Chromosome Mapping; Chromosomes, Human, Pair 11; Diabetes Mellitus, Type 1; Gene Frequency; Genetic Markers; Genetics, Population; Genotype; Haplotypes; Humans; Introns; LDL-Receptor Related Proteins; Linkage Disequilibrium; Low Density Lipoprotein Receptor-Related Protein-5; Microsatellite Repeats; Nuclear Family; Polymorphism, Single Nucleotide; Receptors, LDL; Recombination, Genetic

How is the Drosophila research community making use of the genome sequence? - Richards, Stephen (Genome Biol, 2003)
A report on the 44th Annual Drosophila Research Conference, Chicago, USA, 5-9 March, 2003.
Keywords: Animals; Drosophila; Genome; Research; Research Design

The human genome: genes, pseudogenes, and variation on chromosome 7. - Waterston, R H; Hillier, L W; Fulton, L A; Fulton, R S; Graves, T A; Pepin, K H; Bork, P; Suyama, M; Torrents, D; Chinwalla, A T; Mardis, E R; McPherson, J D; et al. (Cold Spring Harb Symp Quant Biol, 2003)
Keywords: Base Sequence; Chromosome Mapping; Chromosomes, Human, Pair 7; DNA, Complementary; Genetic Variation; Genome, Human; History, 20th Century; History, 21st Century; Human Genome Project; Humans; Molecular Sequence Data; Pseudogenes; Research; Sequence Homology, Nucleic Acid

The International HapMap Project. (Nature, 2003)
The goal of the International HapMap Project is to determine the common patterns of DNA sequence variation in the human genome and to make this information freely available in the public domain. An international consortium is developing a map of these patterns across the genome by determining the genotypes of one million or more sequence variants, their frequencies and the degree of association between them, in DNA samples from populations with ancestry from parts of Africa, Asia and Europe. The HapMap will allow the discovery of sequence variants that affect common disease, will facilitate development of diagnostic tools, and will enhance our ability to choose targets for therapeutic intervention.
Keywords: Base Sequence; DNA; Gene Frequency; Genetic Variation; Genome, Human; Genomics; Haplotypes; Humans; International Cooperation; Polymorphism, Single Nucleotide; Public Sector; Racial Groups

Internet Contig Explorer (iCE)--a tool for visualizing clone fingerprint maps. - Fjell, Christopher D; Bosdet, Ian; Schein, Jacqueline E; Jones, Steven J M; Marra, Marco A (Genome Res, 2003)
Fingerprinted clone physical maps have proven useful in various applications, supporting both whole-genome and region-specific DNA sequencing as well as gene cloning studies. Fingerprint maps have been generated for several genomes, including those of human, mouse, rat, the nematodes Caenorhabditis elegans and Caenorhabditis briggsae, Arabidopsis thaliana and rice. Fingerprint maps of other genomes, including those of fungi, bacteria, poplar, and the cow, are being generated. The increasing use of fingerprint maps in genomic research has spawned a need in the research community for intuitive computer tools that facilitate viewing of the maps and the underlying fingerprint data. In this report we describe a new Java-based application called iCE (Internet Contig Explorer) that has been designed to provide views of fingerprint maps and associated data. Users can search for and display individual clones, contigs, clone fingerprints, clone insert sizes and markers. Users can also load into the software lists of particular clones of interest and view their fingerprints. iCE is being used at our Genome Centre to offer up to the research community views of the mouse, rat, bovine, C. briggsae, and several fungal genome bacterial artificial chromosome (BAC) fingerprint maps we have either completed or are currently constructing. We are also using iCE as part of the Rat Genome Sequencing Project to manage our provision of rat BAC clones for sequencing at the Human Genome Sequencing Center at the Baylor College of Medicine.
Keywords: Animals; Arabidopsis; Caenorhabditis; Caenorhabditis elegans; Cloning, Molecular; Contig Mapping; DNA Fingerprinting; DNA, Helminth; DNA, Plant; Humans; Internet; Mice; Oryza; Rats; Software

Investigating single nucleotide polymorphism (SNP) density in the human genome and its implications for molecular evolution. - Zhao, Zhongming; Fu, Yun-Xin; Hewett-Emmett, David; Eric Boerwinkle (Gene, 2003)
We investigated the single nucleotide polymorphism (SNP) density across the human genome and in different genic categories using two SNP databases: Celera's CgsSNP, which includes SNPs identified by comparing genomic sequences, and Celera's RefSNP, which includes SNPs from a variety of sources and is biased toward disease-associated genes. Based on CgsSNP, the average numbers of SNPs per 10 kb was 8.33, 8.44, and 8.09 in the human genome, in intergenic regions, and in genic regions, respectively. In genic regions, the SNP density in intronic, exonic and adjoining untranslated regions was 8.21, 5.28, and 7.51 SNPs per 10 kb, respectively. The pattern of SNP density based on RefSNP was different from that based on CgsSNP, emphasizing its utility for genotype-phenotype association studies but not for most population genetic studies. The number of SNPs per chromosome was correlated with chromosome length, but the density of SNPs estimated by CgsSNP was not significantly correlated with the GC content of the chromosome. Based on CgsSNP, the ratio of nonsense to missense mutations (0.027), the ratio of missense to silent mutations (1.15), and the ratio of non-synonymous to synonymous mutations (1.18) was less than half of that expected in a human protein coding sequence under the neutral mutation theory, reflecting a role for natural selection, especially purifying selection.
Keywords: Databases, Nucleic Acid; DNA, Intergenic; Evolution, Molecular; Exons; Gene Frequency; Genome, Human; Humans; Introns; Mutation; Polymorphism, Single Nucleotide

The male-specific region of the human Y chromosome is a mosaic of discrete sequence classes. - Skaletsky, Helen; Kuroda-Kawaguchi, Tomoko; Minx, Patrick J; Cordum, Holland S; Hillier, LaDeana; Brown, Laura G; Repping, Sjoerd; Pyntikova, Tatyana; Ali, Johar; Bieri, Tamberlyn; Chinwalla, Asif; Delehaunty, Andrew; et al. (Nature, 2003)
The male-specific region of the Y chromosome, the MSY, differentiates the sexes and comprises 95% of the chromosome's length. Here, we report that the MSY is a mosaic of heterochromatic sequences and three classes of euchromatic sequences: X-transposed, X-degenerate and ampliconic. These classes contain all 156 known transcription units, which include 78 protein-coding genes that collectively encode 27 distinct proteins. The X-transposed sequences exhibit 99% identity to the X chromosome. The X-degenerate sequences are remnants of ancient autosomes from which the modern X and Y chromosomes evolved. The ampliconic class includes large regions (about 30% of the MSY euchromatin) where sequence pairs show greater than 99.9% identity, which is maintained by frequent gene conversion (non-reciprocal transfer). The most prominent features here are eight massive palindromes, at least six of which contain testis genes.
Keywords: Chromosomes, Human, X; Chromosomes, Human, Y; Crossing Over, Genetic; DNA Transposable Elements; Euchromatin; Evolution, Molecular; Female; Gene Amplification; Gene Conversion; Genes; Heterochromatin; Humans; In Situ Hybridization, Fluorescence; Male; Models, Genetic; Multigene Family; Organ Specificity; Pseudogenes; Sequence Homology, Nucleic Acid; Sex Characteristics; Sex Determination Processes; Species Specificity; Testis; Transcription, Genetic; Transducin

Mapping a locus for familial thoracic aortic aneurysms and dissections (TAAD2) to 3p24-25. - Hasham, Sumera N; Willing, Marcia C; Guo, Dong-chuan; Muilenburg, Ann; He, Rumin; Tran, Van T; Steven E Scherer; Shete, Sanjay S; Milewicz, Dianna M (Circulation, 2003)
BACKGROUND: Familial thoracic aortic aneurysms and dissections (TAAD) occur as part of known syndromes such as Marfan syndrome but can also be inherited in families in an autosomal dominant manner as an isolated condition. Previous studies have mapped genes causing nonsyndromic familial TAAD to 5q13-15 (TAAD1) and 11q23.2-q24 (FAA1). Further genetic heterogeneity for the condition was evident by the presence of TAAD in some families not linked to these known loci. METHODS AND RESULTS: A 4-generation family with dominant mode of inheritance of TAAD was studied. Affected status was determined by dilation of the ascending aorta, surgical repair of an aneurysm or dissection, or death as the result of aortic dissection. None of the family members evaluated met the diagnostic criteria for Marfan syndrome. After exclusion of known loci for familial TAAD, a genome-wide scan was carried out to map the defective gene causing the disease in the family. A locus was mapped to a 25-cM region on 3p24-25 with a maximum multipoint logarithm of the odds score of 4.28. CONCLUSIONS: A third locus for nonsyndromic TAAD was mapped to 3p24-25 and termed the TAAD2 locus. This locus overlaps a previously mapped second locus for Marfan syndrome, termed the MFS2 locus. Future characterization of the TAAD2 gene will determine if TAAD2 is allelic to MFS2. In addition, identification of the TAAD2 gene will improve the presymptomatic diagnosis of individuals with this life-threatening genetic syndrome and provide information concerning the pathogenesis of the disease.
Keywords: Adolescent; Adult; Aortic Aneurysm, Thoracic; Aortic Dissection; Calcium-Binding Proteins; Child; Chromosome Mapping; Chromosomes, Human, Pair 3; Comorbidity; DNA Mutational Analysis; Echocardiography; Extracellular Matrix Proteins; Female; Genes, Dominant; Genetic Linkage; Genetic Markers; Genotype; Germany; Haplotypes; Humans; Lod Score; Male; Marfan Syndrome; Middle Aged; Pedigree; Penetrance; Switzerland

Mechanism of hedgehog signaling during Drosophila eye development. - Pappu, Kartik S; Rui Chen; Middlebrooks, Brooke W; Woo, Catherine; Heberlein, Ulrike; Mardon, Graeme (Development, 2003)
Although Hedgehog (Hh) signaling is essential for morphogenesis of the Drosophila eye, its exact link to the network of tissue-specific genes that regulate retinal determination has remained elusive. In this report, we demonstrate that the retinal determination gene eyes absent (eya) is the crucial link between the Hedgehog signaling pathway and photoreceptor differentiation. Specifically, we show that the mechanism by which Hh signaling controls initiation of photoreceptor differentiation is to alleviate repression of eya and decapentaplegic (dpp) expression by the zinc-finger transcription factor Cubitus interruptus (Ci(rep)). Furthermore, our results suggest that stabilized, full length Ci (Ci(act)) plays little or no role in Drosophila eye development. Moreover, while the effects of Hh are primarily concentration dependent in other tissues, hh signaling in the eye acts as a binary switch to initiate retinal morphogenesis by inducing expression of the tissue-specific factor Eya.
Keywords: Animals; Cell Differentiation; DNA-Binding Proteins; Drosophila melanogaster; Drosophila Proteins; Eye Proteins; Hedgehog Proteins; Models, Biological; Morphogenesis; Organisms, Genetically Modified; Photoreceptor Cells, Invertebrate; Signal Transduction; Transcription Factors; Wings, Animal

Novel potential ALL low-risk markers revealed by gene expression profiling with new high-throughput SSH-CCS-PCR. - Qiu, J; Gunaratne, P; Peterson, L E; Khurana, D; Walsham, N; Loulseged, H; Karni, R J; Roussel, E; Richard A Gibbs; Margolin, J F; Marie-Claude Gingras (Leukemia, 2003)
The current systems of risk grouping in pediatric acute lymphoblastic leukemia (ALL) fail to predict therapeutic success in 10-35% of patients. To identify better predictive markers of clinical behavior in ALL, we have developed an integrated approach for gene expression profiling that couples suppression subtractive hybridization, concatenated cDNA sequencing, and reverse transcriptase real-time quantitative PCR. Using this approach, a total of 600 differentially expressed genes were identified between t(4;11) ALL and pre-B ALL with no determinant chromosomal translocation. The expression of 67 genes was analyzed in different cytogenetic ALL subgroups and B lymphocytes isolated from healthy donors. Three genes, BACH1, TP53BPL, and H2B/S, were consistently expressed as a significant cluster associated with the low-risk ALL subgroups. A total of 42 genes were differentially expressed in ALL vs normal B lymphocytes, with no specific association with any particular ALL subgroups. The remaining 22 genes were part of a specific expression profile associated with the hyperdiploid, t(12;21), or t(4;11) subgroups. Using an unsupervised hierarchical cluster analysis, the discriminating power of these specific expression profiles allowed the clustering of patients according to their subgroups. These genes could help to understand the difference in treatment response and become therapeutical targets to improve ALL clinical outcomes.
Keywords: B-Lymphocytes; Biomarkers, Tumor; Case-Control Studies; DNA Primers; DNA, Complementary; DNA, Neoplasm; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Humans; Neoplasm Proteins; Nucleic Acid Hybridization; Oligonucleotide Array Sequence Analysis; Polymerase Chain Reaction; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Risk Factors; RNA, Messenger; RNA, Neoplasm; Subtraction Technique

Polymorphisms at the G72/G30 gene locus, on 13q33, are associated with bipolar disorder in two independent pedigree series. - Hattori, Eiji; Liu, Chunyu; Badner, Judith A; Bonner, Tom I; Christian, Susan L; Maheshwari, Manjula; Detera-Wadleigh, Sevilla D; Gibbs, Richard A; Gershon, Elliot S (Am J Hum Genet, 2003)
Linkage evidence suggests that chromosome 13 (13q32-33) contains susceptibility genes for both bipolar disorder and schizophrenia. Recently, genes called "G72" and "G30" were identified, and polymorphisms of these overlapping genes were reported to be associated with schizophrenia. We studied two series of pedigrees with bipolar disorder: the Clinical Neurogenetics (CNG) pedigrees (in which linkage to illness had been previously reported at 13q32-33), with 83 samples from 22 multiplex families, and the National Institute of Mental Health (NIMH) Genetics Initiative pedigrees, with 474 samples from 152 families. Sixteen single-nucleotide polymorphisms (SNPs) were genotyped at and around the G72/G30 locus, which covered a 157-kb region encompassing the entire complementary DNA sequences of G72 and G30. We performed transmission/disequilibrium testing (TDT) and haplotype analysis, since a linkage-disequilibrium block was present at this gene locus. In the CNG and NIMH data sets, the results of global TDT of the entire haplotype set were significant and consistent (P=.0004 and P=.008, respectively). In the CNG series, the associated genotypes divided the families into those with linkage and those without linkage (partitioned by the linkage evidence). Analysis of the decay of haplotype sharing gave a location estimate that included G72/G30 in its 95% confidence interval. Although statistically significant association was not detected for individual SNPs in the NIMH data set, the same haplotype was consistently overtransmitted in both series. These data suggest that a susceptibility variant for bipolar illness exists in the vicinity of the G72/G30 genes. Taken together with the earlier report, this is the first demonstration of a novel gene(s), discovered through a positional approach, independently associated with both bipolar illness and schizophrenia.
Keywords: Alternative Splicing; Bipolar Disorder; Carrier Proteins; Chromosomes, Human, Pair 13; DNA, Complementary; Gene Frequency; Genes; Genetic Linkage; Genetic Predisposition to Disease; Haplotypes; Humans; Intracellular Signaling Peptides and Proteins; Likelihood Functions; Linkage Disequilibrium; Molecular Sequence Data; Pedigree; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Positional cloning of the major quantitative trait locus underlying lung tumor susceptibility in mice. - Zhang, Zhongqiu; Futamura, Manabu; Vikis, Haris G; Wang, Min; Li, Jie; Wang, Yian; Guan, Kun-Liang; You, Ming (Proc Natl Acad Sci U S A, 2003)
Pulmonary adenoma susceptibility 1 (Pas1), located on chromosome 6, is the major locus affecting inherited predisposition to lung tumor development in mice. We have fine mapped the Pas1 locus to a region of approximately 0.5 megabases by using congenic strains of mice, constructed by placing the Pas1 region of chromosome 6 from A/J mice onto the genetic background of C57BL/6J mice. Systematic characterization of Pas1 candidates establishes the Las1 (lung adenoma susceptibility 1) and Kras2 (Kirsten rat sarcoma oncogene 2) genes as primary candidates for the Pas1 locus. Clearly, Kras2 affects lung tumor progression only, and Las1 is likely to affect lung tumor multiplicity.
Keywords: Adenoma; Amino Acid Sequence; Animals; Base Sequence; Blotting, Northern; Chromosome Mapping; Ciona intestinalis; Cloning, Molecular; DNA Primers; Genetic Markers; Genetic Predisposition to Disease; Humans; Lung Neoplasms; Male; Mice; Mice, Inbred A; Mice, Inbred C57BL; Mice, Nude; Microsatellite Repeats; Molecular Sequence Data; Proto-Oncogene Proteins; Proto-Oncogene Proteins p21(ras); Quantitative Trait Loci; ras Proteins; Reverse Transcriptase Polymerase Chain Reaction; Sequence Alignment; Sequence Homology, Amino Acid

Rigid, conjugated, fluoresceinated thymidine triphosphates: syntheses and polymerase mediated incorporation into DNA analogues. - Thoresen, Lars H; Jiao, Guan-Sheng; Haaland, Wade C; Metzker, Michael L; Burgess, Kevin (Chemistry, 2003)
Syntheses of a unique set of energy transfer dye labeled nucleoside triphosphates, compounds 1-3, are described. Attempts to prepare these compounds were only successful if the triphosphorylation reaction was performed before coupling the dye to the nucleobase, and not the other way around. Compounds were prepared as both the 2'-deoxy (a) and 2',3'-dideoxy- (b) forms. They feature progressively longer rigid conjugated linkers connecting the nucleobase and the hydroxyxanthone moiety. UV spectra of the parent nucleosides 12-14 show that as the length of the linker increases so does the absorption of the donor in the 320-330 nm region, but with relatively little red-shift of the maxima. Fluorescence spectra of the same compounds show that radiation in the 320-330 nm region results in predominant emission from the fluorescein. When the linker is irradiated at 320 nm, the only significant emission observed corresponds to the hydroxyxanthone part of the molecules at 520 nm; this corresponds to an effective Stokes' shift of 200 nm. As the absorption at 320-330 nm by the linker increases with length, so does the intensity of the fluorescein emission. A gel assay was used to gauge relative incorporation efficiencies of compounds 1-3, dTTP, ddTTP, and 6-TAMRA-ddTTP. Throughout, the thermostable polymerase TaqFS was used, as it is the one most widely applied in high throughput DNA sequencing. This assay showed that only compounds 3 were incorporated efficiently; these have the longest linkers. Of these, the 2'-deoxy nucleoside 3 a was incorporated and did not prevent the polymerase from extending the chain further. The 2',3'-dideoxy nucleoside 3 b was incorporated only about 430 times less efficiently than ddTTP under the same conditions, and caused chain termination. The implications of these studies on modified sequencing protocols are discussed.
Keywords: DNA; Fluoresceins; Spectrometry, Fluorescence; Spectrophotometry, Ultraviolet; Substrate Specificity; Taq Polymerase; Thymine Nucleotides

Sequence and structure of the extrachromosomal palindrome encoding the ribosomal RNA genes in Dictyostelium. - Sucgang, Richard; Chen, Guokai; Liu, Wen; Lindsay, Ryan; Lu, Jing; Muzny, Donna; Shaulsky, Gad; Loomis, William; Gibbs, Richard; Kuspa, Adam (Nucleic Acids Res, 2003)
Ribosomal RNAs (rRNAs) are encoded by multicopy families of identical genes. In Dictyostelium and other protists, the rDNA is carried on extrachromosomal palindromic elements that comprise up to 20% of the nuclear DNA. We present the sequence of the 88 kb Dictyostelium rDNA element, noting that the rRNA genes are likely to be the only transcribed regions. By interrogating a library of ordered YAC clones, we provide evidence for a chromosomal copy of the rDNA on chromosome 4. This locus may provide master copies for the stable transmission of the extrachromosomal elements. The extrachromosomal elements were also found to form chromosome-sized clusters of DNA within nuclei of nocodazole-treated cells arrested in mitosis. These clusters resemble true chromosomes and may allow the efficient segregation of the rDNA during mitosis. These rDNA clusters may also explain the cytological observations of a seventh chromosome in this organism.
Keywords: Animals; Chromosome Mapping; Dictyostelium; DNA, Protozoan; In Situ Hybridization, Fluorescence; Molecular Sequence Data; Plasmids; RNA, Ribosomal; Sequence Analysis, DNA

Software for automated analysis of DNA fingerprinting gels. - Fuhrmann, Daniel R; Krzywinski, Martin I; Chiu, Readman; Saeedi, Parvaneh; Schein, Jacqueline E; Bosdet, Ian E; Chinwalla, Asif; Hillier, LaDeana W; Waterston, Robert H; McPherson, John D; Jones, Steven J M; Marra, Marco A (Genome Res, 2003)
Here we describe software tools for the automated detection of DNA restriction fragments resolved on agarose fingerprinting gels. We present a mathematical model for the location and shape of the restriction fragments as a function of fragment size, with model parameters determined empirically from "marker" lanes containing molecular size standards. Automated identification of restriction fragments involves several steps, including: image preprocessing, to put the data in a form consistent with a linear model; marker lane analysis, for determination of the model parameters; and data lane analysis, a procedure for detecting restriction fragment multiplets while simultaneously determining the amplitude curve that describes restriction fragment amplitude as a function of mobility. In validation experiments conducted on fingerprinted and sequenced Bacterial Artificial Chromosome (BAC) clones, sensitivity and specificity of restriction fragment identification exceeded 96% on restriction fragments ranging in size from 600 base pairs (bp) to 30,000 bp. The integrated suite of software tools, written in MATLAB and collectively called BandLeader, is in use at the BC Cancer Agency Genome Sciences Centre (GSC) and the Washington University Genome Sequencing Center, and has been provided to the Wellcome Trust Sanger Institute and the Whitehead Institute. Employed in a production mode at the GSC, BandLeader has been used to perform automated restriction fragment identification for more than 850,000 BAC clones for mouse, rat, bovine, and poplar fingerprint mapping projects.
Keywords: Animals; Cattle; Chromosomes, Artificial, Bacterial; DNA; DNA Fingerprinting; Gels; Mice; Models, Chemical; Rats; Sepharose; Software

A computational/functional genomics approach for the enrichment of the retinal transcriptome and the identification of positional candidate retinopathy genes. - Katsanis, Nicholas; Worley, Kim C; Gonzalez, Guillermo; Ansley, Stephen J; Lupski, James R (Proc Natl Acad Sci U S A, 2002)
Grouping genes by virtue of their sequence similarity, functional association, or spatiotemporal distribution is an important first step in investigating function. Given the recent identification of >30,000 human genes either by analyses of genomic sequence or by derivation/assembly of ESTs, automated means of discerning gene function and association with disease are critical for the efficient processing of this large volume of data. We have designed a series of computational tools to manipulate the EST sequence database (dbEST) to predict EST clusters likely representing genes expressed exclusively or preferentially in a specific tissue. We implemented this tool by extracting 40,000 human retinal ESTs and performing in silico subtraction against 1.4 million human ESTs. This process yielded 925 ESTs likely to be specifically or preferentially expressed in the retina. We mapped all retinal-specific/predominant sequences in the human genome and produced a web-based searchable map of the retina transcriptome, onto which we overlaid the positions of all mapped but uncloned retinopathy genes. This resource has provided positional candidates for 42 of 51 uncloned retinopathies and may expedite substantially the identification of disease-associated genes. More importantly, the ability to systematically group ESTs according to their predicted expression profile is likely to be an important resource for studying gene function in a wide range of tissues and physiological systems and to identify positional candidate genes for human disorders whose phenotypic manifestations are restricted to specific tissues/organs/cell types.
Keywords: Databases, Nucleic Acid; Electronic Data Processing; Expressed Sequence Tags; Genome; Humans; Retina; Retinal Diseases; Transcription, Genetic

DNA polymerase III from Escherichia coli cells expressing mutA mistranslator tRNA is error-prone. - Al Mamun, Abu Amar M; Marians, Kenneth J; Humayun, M Zafri (J Biol Chem, 2002)
Translational stress-induced mutagenesis (TSM) refers to the elevated mutagenesis observed in Escherichia coli cells in which mistranslation has been increased as a result of mutations in tRNA genes (such as mutA) or by exposure to streptomycin. TSM does not require lexA-regulated SOS functions but is suppressed in cells defective for homologous recombination genes. Crude cell-free extracts from TSM-induced E. coli strains express an error-prone DNA polymerase. To determine whether DNA polymerase III is involved in the TSM phenotype, we first asked if the phenotype is expressed in cells defective for all four of the non-replicative DNA polymerases, namely polymerase I, II, IV, and V. By using a colony papillation assay based on the reversion of a lacZ mutant, we show that the TSM phenotype is expressed in such cells. Second, we asked if pol III from TSM-induced cells is error-prone. By purifying DNA polymerase III* from TSM-induced and control cells, and by testing its fidelity on templates bearing 3,N(4)-ethenocytosine (a mutagenic DNA lesion), as well as on undamaged DNA templates, we show here that polymerase III* purified from mutA cells is error-prone as compared with that from control cells. These findings suggest that DNA polymerase III is modified in TSM-induced cells.
Keywords: Base Sequence; DNA Polymerase III; DNA Replication; DNA, Bacterial; Escherichia coli; Genes, Bacterial; Molecular Sequence Data; Mutation; Protein Biosynthesis; RNA, Transfer

Efficient isolation of targeted Caenorhabditis elegans deletion strains using highly thermostable restriction endonucleases and PCR. - Wei, Aguan; Yuan, Alex; Fawcett, Gloria; Butler, Alice; Davis, Theodore; Xu, Shuang-yong; Salkoff, Lawrence (Nucleic Acids Res, 2002)
Reverse genetic approaches to understanding gene function would be greatly facilitated by increasing the efficiency of methods for isolating mutants without the reliance on a predicted phenotype. Established PCR-based methods of isolating deletion mutants are widely used for this purpose in Caenorhabditis elegans. However, these methods are inefficient at isolating small deletions. We report here a novel modification of PCR-based methods, employing thermostable restriction enzymes to block the synthesis of wild-type PCR product, so that only the deletion PCR product is amplified. This modification greatly increases the efficiency of isolating small targeted deletions in C.elegans. Using this method six new deletion strains were isolated from a small screen of approximately 400 000 haploid genomes, most with deletions <1.0 kb. Greater PCR detection sensitivity by this modification permitted approximately 10-fold greater pooling of DNA samples, reducing the effort and reagents required for screens. In addition, effective suppression of non-specific amplification allowed multiplexing with several independent primer pairs. The increased efficiency of this technique makes it more practical for small laboratories to undertake gene knock-out screens.
Keywords: Animals; Caenorhabditis elegans; Deoxyribonucleases, Type II Site-Specific; DNA Primers; DNA Restriction Enzymes; DNA, Helminth; Gene Targeting; Polymerase Chain Reaction; Sensitivity and Specificity; Sequence Deletion; Temperature

The Enterococcus faecalis fsrB gene, a key component of the fsr quorum-sensing system, is associated with virulence in the rabbit endophthalmitis model. - Mylonakis, Eleftherios; Engelbert, Michael; Qin, Xiang; Sifri, Costi D; Murray, Barbara E; Ausubel, Frederick M; Gilmore, Michael S; Calderwood, Stephen B (Infect Immun, 2002)
We used a rabbit endophthalmitis model to explore the role of fsrB, a gene required for the function of the fsr quorum-sensing system of Enterococcus faecalis, in pathogenicity. A nonpolar deletion mutant of fsrB had significantly reduced virulence compared to wild type. Complementation of mutation restored virulence. These data corroborate the role of fsrB in E. faecalis pathogenesis and suggest that the rabbit endophthalmitis model can be used to study the in vivo role of quorum sensing.
Keywords: Animals; Bacterial Proteins; Disease Models, Animal; Endophthalmitis; Enterococcus faecalis; Eye; Female; Genes, Bacterial; Gram-Positive Bacterial Infections; Rabbits; Retina; Virulence; Vision, Ocular

Finishing a whole-genome shotgun: release 3 of the Drosophila melanogaster euchromatic genome sequence. - Celniker, Susan E; Wheeler, David A; Kronmiller, Brent; Carlson, Joseph W; Halpern, Aaron; Patel, Sandeep; Adams, Mark; Champe, Mark; Dugan, Shannon P; Frise, Erwin; Hodgson, Ann; George, Reed A; et al. (Genome Biol, 2002)
BACKGROUND: The Drosophila melanogaster genome was the first metazoan genome to have been sequenced by the whole-genome shotgun (WGS) method. Two issues relating to this achievement were widely debated in the genomics community: how correct is the sequence with respect to base-pair (bp) accuracy and frequency of assembly errors? And, how difficult is it to bring a WGS sequence to the accepted standard for finished sequence? We are now in a position to answer these questions. RESULTS: Our finishing process was designed to close gaps, improve sequence quality and validate the assembly. Sequence traces derived from the WGS and draft sequencing of individual bacterial artificial chromosomes (BACs) were assembled into BAC-sized segments. These segments were brought to high quality, and then joined to constitute the sequence of each chromosome arm. Overall assembly was verified by comparison to a physical map of fingerprinted BAC clones. In the current version of the 116.9 Mb euchromatic genome, called Release 3, the six euchromatic chromosome arms are represented by 13 scaffolds with a total of 37 sequence gaps. We compared Release 3 to Release 2; in autosomal regions of unique sequence, the error rate of Release 2 was one in 20,000 bp. CONCLUSIONS: The WGS strategy can efficiently produce a high-quality sequence of a metazoan genome while generating the reagents required for sequence finishing. However, the initial method of repeat assembly was flawed. The sequence we report here, Release 3, is a reliable resource for molecular genetic experimentation and computational analysis.
Keywords: Animals; Drosophila melanogaster; Euchromatin; Genome; Physical Chromosome Mapping; Research Design; Sequence Analysis, DNA; X Chromosome

Generation and initial analysis of more than 15,000 full-length human and mouse cDNA sequences. - Strausberg, Robert L; Feingold, Elise A; Grouse, Lynette H; Derge, Jeffery G; Klausner, Richard D; Collins, Francis S; Wagner, Lukas; Shenmen, Carolyn M; Schuler, Gregory D; Altschul, Stephen F; Zeeberg, Barry; Buetow, Kenneth H; et al. (Proc Natl Acad Sci U S A, 2002)
The National Institutes of Health Mammalian Gene Collection (MGC) Program is a multiinstitutional effort to identify and sequence a cDNA clone containing a complete ORF for each human and mouse gene. ESTs were generated from libraries enriched for full-length cDNAs and analyzed to identify candidate full-ORF clones, which then were sequenced to high accuracy. The MGC has currently sequenced and verified the full ORF for a nonredundant set of >9,000 human and >6,000 mouse genes. Candidate full-ORF clones for an additional 7,800 human and 3,500 mouse genes also have been identified. All MGC sequences and clones are available without restriction through public databases and clone distribution networks (see http:mgc.nci.nih.gov).
Keywords: Algorithms; Animals; DNA, Complementary; Gene Library; Humans; Mice; Open Reading Frames; Sequence Analysis, DNA

Glass bead purification of plasmid template DNA for high throughput sequencing of mammalian genomes. - Dederich, Debra A; Okwuonu, Geoffrey; Garner, Toni; Denn, Amanda; Sutton, Angelica; Escotto, Michael; Martindale, Ashley; Delgado, Oliver; Muzny, Donna M; Gibbs, Richard A; Metzker, Michael L (Nucleic Acids Res, 2002)
To meet the new challenge of generating the draft sequences of mammalian genomes, we describe the development of a novel high throughput 96-well method for the purification of plasmid DNA template using size-fractionated, acid-washed glass beads. Unlike most previously described approaches, the current method has been designed and optimized to facilitate the direct binding of alcohol-precipitated plasmid DNA to glass beads from alkaline lysed bacterial cells containing the insoluble cellular aggregate material. Eliminating the tedious step of separating the cleared lysate significantly simplifies the method and improves throughput and reliability. During a 4 month period of 96-capillary DNA sequencing of the Rattus norvegicus genome at the Baylor College of Medicine Human Genome Sequencing Center, the average success rate and read length derived from >1 800 000 plasmid DNA templates prepared by the direct lysis/glass bead method were 82.2% and 516 bases, respectively. The cost of this direct lysis/glass bead method in September 2001 was approximately 10 cents per clone, which is a significant cost saving in high throughput genomic sequencing efforts.
Keywords: Animals; DNA; Genome; Glass; Microspheres; Plasmids; Rats; Reproducibility of Results; Sequence Analysis, DNA

Intron-size constraint as a mutational mechanism in Rothmund-Thomson syndrome. - Wang, Lisa L; Worley, Kim; Gannavarapu, Anu; Chintagumpala, Murali M; Levy, Moise L; Plon, Sharon E (Am J Hum Genet, 2002)
Rothmund-Thomson syndrome (RTS) is an autosomal recessive disorder caused by deleterious mutations in the RECQL4 gene on chromosome 8. The RECQL4 gene structure is unusual because it contains many small introns <100 bp. We describe a proband with RTS who has a novel 11-bp intronic deletion, and we show that this mutation results in a 66-bp intron too small for proper splicing. Constraint on intron size may represent a general mutational mechanism, since human-genome analysis reveals that approximately 15% of genes have introns <100 bp and are therefore susceptible to size constraint. Thus, monitoring of intron size may allow detection of mutations missed by exon-by-exon approaches.
Keywords: 3T3 Cells; Adenosine Triphosphatases; Animals; Base Sequence; DNA; DNA Helicases; Humans; Introns; Mice; Molecular Sequence Data; Mutation; RecQ Helicases; Reverse Transcriptase Polymerase Chain Reaction; RNA Splicing; Rothmund-Thomson Syndrome; Transfection

Latency-associated nuclear antigen (LANA) cooperatively binds to two sites within the terminal repeat, and both sites contribute to the ability of LANA to suppress transcription and to facilitate DNA replication. - Garber, Alexander C; Jianhong Hu; Renne, Rolf (J Biol Chem, 2002)
The latency-associated nuclear antigen (LANA) of Kaposi's sarcoma-associated herpesvirus is a multifunctional protein with important roles in both transcriptional regulation and episomal maintenance. LANA is also a DNA-binding protein and has been shown to specifically bind to a region within the terminal repeat. Here, we have performed a detailed analysis of the DNA-binding activity of LANA and show that it binds two sites separated by 22 bp. We used electrophoretic mobility shift assay to quantitatively analyze the binding sites and determined that the K(d) of the high affinity site is 1.51 +/- 0.16 nm. Examination of the contribution of nucleotides near the ends of the site showed that the core binding site consists of 16 bp, 13 of which are conserved between both sites. Analysis of the affinity of each site alone and in tandem revealed that the binding to the second site is primarily due to cooperativity with the first site. Using deletion and point mutations, we show that both sites contribute to the ability of LANA to suppress transcription and to facilitate DNA replication. In addition, we show that the ability of LANA to carry out these functions is directly proportional to its affinity for the sites in this region. The affinities, spacing, and cooperative binding between the two sites is similar to that of the Epstein-Barr virus dyad symmetry element oriP, suggesting a requirement for such an element in latent replication of these related DNA tumor viruses.
Keywords: Antigens, Viral; Base Sequence; Binding Sites; Chromatin; DNA; DNA-Binding Proteins; Dose-Response Relationship, Drug; Humans; Kinetics; Molecular Sequence Data; Mutation; Nuclear Proteins; Plasmids; Point Mutation; Protein Binding; Protein Structure, Tertiary; Transcription, Genetic; Transfection

The latency-associated nuclear antigen of Kaposi's sarcoma-associated herpesvirus supports latent DNA replication in dividing cells. - Hu, Jianhong; Garber, Alexander C; Renne, Rolf (J Virol, 2002)
Kaposi's sarcoma-associated herpesvirus (KSHV) is associated with Kaposi's sarcoma, primary effusion lymphoma, and multicentric Castleman's disease. The latency-associated nuclear antigen (LANA) is a multifunctional protein that is consistently expressed in all KSHV-associated malignancies. LANA interacts with a variety of cellular proteins, including the transcriptional cosuppressor complex mSin3 and the tumor suppressors p53 and Rb, thereby regulating viral and cellular gene expression. In addition, LANA is required for maintenance of the episomal viral DNA during latency in dividing cells. Colocalization studies suggest that LANA tethers the viral genome to chromosomes during mitosis. In support of this model, a specific LANA- binding site has recently been identified within the terminal repeat unit, and a chromatin interaction domain was mapped to a short amino acid stretch within the N-terminal domain of LANA. Epstein-Barr virus nuclear antigen 1 (EBNA-1), a functional homologue of LANA, is also required for genome segregation; in addition, EBNA-1 also supports efficient DNA replication of oriP-containing plasmids. By performing short-term replication assays, we demonstrate here for the first time that de novo synthesis of terminal-repeat (TR)-containing plasmids is highly dependent on the presence of LANA. We map the required cis-acting sequences within the TR to a 79-bp region and demonstrate that the DNA-binding domain of LANA is required for this DNA replication activity. Surprisingly, the 233-amino-acid C domain of LANA by itself partially supports replication. Our data show that LANA is a sequence-specific DNA-binding protein that, like EBNA-1, plays an important role in DNA replication and genome segregation. In addition, we show that all necessary cis elements for the origin of replication (ori) function are located within a single TR, suggesting that the putative ori of KSHV is different from those of other gammaherpesviruses, which all contain ori sequences within the unique long sequence outside of their TR. This notion is further strengthened by the unique modular structure of the KSHV TR element.
Keywords: Antigens, Viral; Base Sequence; Cell Line; DNA Replication; DNA, Viral; Enhancer Elements, Genetic; Herpesvirus 8, Human; Humans; Molecular Sequence Data; Nuclear Proteins; Plasmids; Replication Origin; Sarcoma, Kaposi; Terminal Repeat Sequences; Virus Latency

Molecular evidence of HIV-1 transmission in a criminal case. - Metzker, Michael L; Mindell, David P; Liu, Xiao-Mei; Ptak, Roger G; Gibbs, Richard A; Hillis, David M (Proc Natl Acad Sci U S A, 2002)
A gastroenterologist was convicted of attempted second-degree murder by injecting his former girlfriend with blood or blood-products obtained from an HIV type 1 (HIV-1)-infected patient under his care. Phylogenetic analyses of HIV-1 sequences were admitted and used as evidence in this case, representing the first use of phylogenetic analyses in a criminal court case in the United States. Phylogenetic analyses of HIV-1 reverse transcriptase and env DNA sequences isolated from the victim, the patient, and a local population sample of HIV-1-positive individuals showed the victim's HIV-1 sequences to be most closely related to and nested within a lineage comprised of the patient's HIV-1 sequences. This finding of paraphyly for the patient's sequences was consistent with the direction of transmission from the patient to the victim. Analysis of the victim's viral reverse transcriptase sequences revealed genotypes consistent with known mutations that confer resistance to AZT, similar to those genotypes found in the patient. A priori establishment of the patient and victim as a suspected transmission pair provided a clear hypothesis for phylogenetic testing. All phylogenetic models and both genes examined strongly supported the close relationship between the HIV-1 sequences of the patient and the victim. Resampling of blood from the suspected transmission pair and independent sequencing by different laboratories provided precaution against laboratory error.
Keywords: Base Sequence; Crime; Crime Victims; DNA, Viral; Female; Forensic Medicine; HIV Envelope Protein gp120; HIV Infections; HIV Reverse Transcriptase; HIV-1; Humans; Male; Molecular Sequence Data; Phylogeny; Sequence Analysis, DNA

PTPN11 mutations in Noonan syndrome type I: detection of recurrent mutations in exons 3 and 13. - Maheshwari, M; Belmont, J; Fernbach, S; Ho, T; Molinari, L; Yakub, I; Fuli Yu; Combes, A; Towbin, J; Craigen, W J; Richard A Gibbs (Hum Mutat, 2002)
We surveyed 16 subjects with the clinical diagnosis of Noonan Syndrome (NS1) from 12 families and their relevant family members for mutations in PTPN11/SHP2 using direct DNA sequencing. We found three different mutations among five families. Two unrelated subjects shared the same de novo missense substitution in exon 13 (S502T); an additional two unrelated families had a mutation in exon 3 (Y63C); and one subject had the amino acid substitution Y62D, also in exon 3. None of the three mutations were present in ethnically matched controls. In the mature protein model, the exon 3 mutants and the exon 13 mutant amino acids cluster at the interface between the N' SH2 domain and the phosphatase catalytic domain. Six of eight subjects with PTPN11/SHP2 mutations had pulmonary valve stenosis while no mutations were identified in those subjects (N = 4) with hypertrophic cardiomyopathy. An additional four subjects with possible Noonan syndrome were evaluated, but no mutations in PTPN11/SHP2 were identified. These results confirm that mutations in PTPN11/SHP2 underlie a common form of Noonan syndrome, and that the disease exhibits both allelic and locus heterogeneity. The observation of recurrent mutations supports the hypothesis that a special class of gain-of-function mutations in SHP2 give rise to Noonan syndrome.
Keywords: Catalytic Domain; DNA Mutational Analysis; Exons; Female; Humans; Intracellular Signaling Peptides and Proteins; Isoenzymes; Male; Mutation; Noonan Syndrome; Phenotype; Protein Structure, Quaternary; Protein Tyrosine Phosphatase, Non-Receptor Type 11; Protein Tyrosine Phosphatases; Recurrence; SH2 Domain-Containing Protein Tyrosine Phosphatases; src Homology Domains

Virulence effect of Enterococcus faecalis protease genes and the quorum-sensing locus fsr in Caenorhabditis elegans and mice. - Sifri, Costi D; Mylonakis, Eleftherios; Singh, Kavindra V; Qin, Xiang; Garsin, Danielle A; Murray, Barbara E; Ausubel, Frederick M; Calderwood, Stephen B (Infect Immun, 2002)
The expression of two Enterococcus faecalis extracellular virulence-related proteins, gelatinase (GelE) and serine protease (SprE), has been shown to be positively regulated by the fsr quorum-sensing system. We recently developed a novel system for studying E. faecalis pathogenicity that involves killing of the nematode worm Caenorhabditis elegans and showed that an E. faecalis fsrB mutant (strain TX5266) exhibited attenuated killing. We explore here the role of the fsr/gelE-sprE locus in pathogenicity by comparing results obtained in the nematode system with a mouse peritonitis model of E. faecalis infection. Insertion mutants of fsrA (TX5240) and fsrC (TX5242), like fsrB (TX5266), were attenuated in their ability to kill C. elegans. A deletion mutant of gelE (TX5264) and an insertion mutant of sprE (TX5243) were also attenuated in C. elegans killing, although to a lesser extent than the fsr mutants. Complementation of fsrB (TX5266) with a 6-kb fragment containing the entire fsr locus restored virulence in both the nematode and the mouse peritonitis models. The fsr mutants were not impaired in their ability to colonize the nematode intestine. These data show that extracellular proteases and the quorum-sensing fsr system are important for E. faecalis virulence in two highly divergent hosts: nematodes and mice.
Keywords: Animals; Bacterial Proteins; Caenorhabditis elegans; DNA-Binding Proteins; Enterococcus faecalis; Escherichia coli Proteins; Female; Gelatinases; Gene Expression Regulation, Bacterial; Genes, Bacterial; Genetic Complementation Test; Mice; Mice, Inbred ICR; Mutagenesis, Insertional; Sequence Deletion; Transcription Factors; Virulence

Characterization of the rat GRIK5 kainate receptor subunit gene promoter and its intragenic regions involved in neural cell specificity. - Chew, L J; Yuan, X; Steven E Scherer; Qie, L; Huang, F; Hayes, W P; Gallo, V (J Biol Chem, 2001)
The GRIK5 (glutamate receptor ionotropic kainate-5) gene encodes the kainate-preferring glutamate receptor subunit KA2. The GRIK5 promoter is TATA-less and GC-rich, with multiple consensus initiator sequences. Transgenic mouse lines carrying 4 kilobases of the GRIK5 5'-flanking sequence showed lacZ reporter expression predominantly in the nervous system. Reporter assays in central glial (CG-4) and non-neural cells indicated that a 1200-base pair (bp) 5'-flanking region could sustain neural cell-specific promoter activity. Transcriptional activity was associated with the formation of a transcription factor IID-containing complex on an initiator sequence located 1100 bp upstream of the first intron. In transfection studies, deletion of exonic sequences downstream of the promoter resulted in reporter gene activity that was no longer neural cell-specific. When placed downstream of the GRIK5 promoter, a 77-bp sequence from the deleted fragment completely silenced reporter expression in NIH3T3 fibroblasts while attenuating activity in CG-4 cells. Analysis of the 77-bp sequence revealed a functional SP1-binding site and a sequence resembling a neuron-restrictive silencer element. The latter sequence, however, did not display cell-specific binding of REST-like proteins. Our studies thus provide evidence for intragenic control of GRIK5 promoter activity and suggest that elements contributing to tissue-specific expression are contained within the first exon.
Keywords: 5' Flanking Region; Animals; Base Sequence; Cells, Cultured; Deoxyribonuclease I; Humans; Mice; Mice, Transgenic; Molecular Sequence Data; Neurons; Organ Specificity; Promoter Regions, Genetic; Protein Subunits; Rats; Receptors, Kainic Acid; Sp1 Transcription Factor

Comparing vertebrate whole-genome shotgun reads to the human genome. - Chen, R; Bouck, J B; Weinstock, G M; Gibbs, R A (Genome Res, 2001)
Multi-species sequence comparisons are a very efficient way to reveal conserved genes. Because sequence finishing is expensive and time consuming, many genome sequences are likely to stay incomplete. A challenge is to use these fragmented data for understanding the human genome. Methods for using cross-species whole-genome shotgun sequence (WGS) for genome annotation are described in this paper. About one-half million high-quality rat WGS reads (covering 7.5% of the rat genome) generated at the Baylor College of Medicine Human Genome Sequencing Center were compared with the human genome. Using computer-generated random reads as a negative control, a set of parameters was determined for reliable interpretation of BLAST search results. About 10% of the rat reads contain regions that are conserved in the human genomic sequence and about one-third of these include known gene-coding regions. Mapping the conserved regions to human chromosomes showed a 23-fold enrichment for coding regions compared with noncoding regions. This approach can also be applied to other mammalian genomes for gene finding. These data predicted approximately 42,500 genes in the human, slightly more than reported previously.
Keywords: Animals; Base Sequence; Computational Biology; Conserved Sequence; Databases, Genetic; Expressed Sequence Tags; Genome; Genome, Human; Heterochromatin; Humans; Mice; Molecular Sequence Data; Rats; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Species Specificity; Transcription, Genetic

DNA binding and modulation of gene expression by the latency-associated nuclear antigen of Kaposi's sarcoma-associated herpesvirus. - Garber, A C; Shu, M A; Hu, J; Renne, R (J Virol, 2001)
Kaposi's sarcoma-associated herpesvirus (KSHV) is associated with Kaposi's sarcoma, primary effusion lymphoma, and multicentric Castleman's disease. The latency-associated nuclear antigen (LANA) is highly expressed in these malignancies and has been shown to play an important role in episomal maintenance, presumably by binding to a putative oriP. In addition, LANA modulates cellular and viral gene expression and interacts with the cellular tumor suppressors p53 and retinoblastoma suppressor protein. Many of these features are reminiscent of Epstein-Barr virus nuclear antigens (EBNAs), a family of six proteins expressed during latency. EBNA-1 is required for episome maintenance, binds to oriP, and strongly activates transcription from two promoters, including its own. We have previously shown that LANA can transactivate its own promoter and therefore asked whether LANA, like EBNA-1, activates transcription by direct binding to DNA. By using recombinant LANA expressed from vaccinia virus vectors for electrophoretic mobility shift assays, we found that LANA does not bind to its own promoter. In contrast, LANA binds specifically to sequences containing an imperfect 20-bp palindrome in the terminal repeat (TR) of KSHV. We further show that the C-terminal domain of LANA is sufficient for site-specific DNA binding. Unlike EBNA-1, which activates transcription through binding of oriP, we found that LANA inhibits transcription from a single TR binding site. A multimerized TR as found in the viral genome results in strong transcriptional suppression when linked to a heterologous promoter. These data suggest that LANA, although fulfilling functions similar to those of EBNA-1, does so by very different mechanisms.
Keywords: Animals; Antigens, Viral; Binding Sites; Cell Line; DNA, Viral; DNA-Directed RNA Polymerases; Gene Expression Regulation, Viral; Genetic Vectors; Herpesvirus 8, Human; Humans; Nuclear Proteins; Promoter Regions, Genetic; Terminal Repeat Sequences; Transcription, Genetic; Transfection; Vaccinia virus; Viral Proteins

Evolution tunes the excitability of individual neurons. - Salkoff, L; Butler, A; Fawcett, G; Kunkel, M; McArdle, C; Paz-y-Mino, G; Nonet, M; Walton, N; Wang, Z W; Yuan, A; Wei, A (Neuroscience, 2001)
The relationship between the genome and the evolution of the nervous system may differ between an animal like C. elegans with 302 neurons, and mammals with tens of billions of neurons. Here we report that a class of nonconserved potassium channels highly expanded in C. elegans may play a special role in the evolution of its nervous system. The C. elegans genome contains an extended gene family of potassium channels whose members fall into two evolutionary divergent classes. One class constitutes an ancient conserved "set" of K+ channels with orthologues in both humans and Drosophila and a second larger class made up of rapidly evolving genes unique to C. elegans. Chief among this second class are novel potassium channels having four transmembrane domains per subunit that function as regulated leak conductances to modulate cell electrical excitability. This inventory of novel potassium channels is far larger in C. elegans than in humans or Drosophila. We found that, unlike conserved channel genes, the majority of these genes are expressed in very few cells. We also identified DNA enhancer elements associated with these genes that direct gene expression to individual neurons. We conclude that C. elegans may maintain an exceptionally large inventory of these channels (as well as ligand-gated channels) as an adaptive mechanism to "fine tune" individual neurons, making the most of its limited circuitry.
Keywords: Adaptation, Physiological; Animals; Base Sequence; Biological Evolution; Caenorhabditis; Caenorhabditis elegans; DNA; Enhancer Elements, Genetic; Gene Expression; Molecular Sequence Data; Multigene Family; Neurons; Potassium Channels; Protein Isoforms

Genetic mapping and DNA sequence-based analysis of deleted regions on chromosome 16 involved in progression of bladder cancer from occult preneoplastic conditions to invasive disease. - Yoon, D S; Li, L; Zhang, R D; Kram, A; Ro, J Y; Johnston, D; Grossman, H B; Scherer, S; Czerniak, B (Oncogene, 2001)
Histologic and genetic mapping with 30 hypervariable markers mapped to chromosome 16 were performed on 234 DNA samples of five cystectomy specimens from patients with invasive bladder cancer. Allelic losses of individual markers were related to microscopically identified precursor conditions in the entire bladder mucosa and invasive cancer. Their significance for the development and progression of neoplasia from in situ preneoplastic conditions to invasive disease was analysed by the nearest neighbor algorithm and binomial maximum likelihood analysis. Using this approach we identified five distinct regions of allelic losses defined by their flanking markers and predicted size as follows. p13.3(D16S418-D16S406, 1.2 cM), p13.1(D16S748-D16S287, 12.9 cM), q12 1(D16S409-D16S514, 24.0 cM), q22.1 (D16S496-D16S515, 5.4 cM), and q24 (D16S507-D16S511, 5.9 cM and D16S402-D16S413, 17.4 cM). The regions mapping to p13.1 and q24 were involved in early intraurothelial phases of bladder neoplasia such as mild to moderate dysplasia. On the other hand the deleted region mapping to p13.3 was involved in progression of severe dysplasia/carcinoma in situ to invasive bladder cancer. Testing of markers that exhibited statistically significant LOH in relation to progression of neoplasia from precursor conditions to invasive cancer on 28 tumors and voided urine samples from 25 patients with bladder cancer revealed that q12.1 showed LOH in 46.4% of tumor and 32.0% of voided urine samples. The LOH of a single marker D16S541 could be detected in approximately 28% of tumors and 20% of voided urine samples of patients with bladder cancer. These data imply that the deleted region centered around marker D16S541 spanning approximately 10 cM and flanked by D16S409 and D16S415 contains a novel putative tumor suppressor gene or genes playing an important role in the development of human bladder cancer. To facilitate more precise positional mapping and identification of pathogenetically relevant genes, we analysed of human genome contig and sequence databases spanning the deleted regions. Multiple known candidate genes and several smaller gene-rich areas mapping to the target regions of chromosome 16 were identified.
Keywords: Aged; Chromosome Mapping; Chromosomes, Human, Pair 16; Disease Progression; DNA, Neoplasm; Genes, Tumor Suppressor; Genetic Markers; Humans; Loss of Heterozygosity; Male; Middle Aged; Neoplasm Invasiveness; Precancerous Conditions; Sequence Deletion; Tissue Distribution; Urinary Bladder Neoplasms; Urine

Initial sequencing and analysis of the human genome. - Lander, E S; Linton, L M; Birren, B; Nusbaum, C; Zody, M C; Baldwin, J; Devon, K; Dewar, K; Doyle, M; FitzHugh, W; Funke, R; Gage, D; et al. (Nature, 2001)
The human genome holds an extraordinary trove of information about human development, physiology, medicine and evolution. Here we report the results of an international collaboration to produce and make freely available a draft sequence of the human genome. We also present an initial analysis of the data, describing some of the insights that can be gleaned from the sequence.
Keywords: Animals; Chromosome Mapping; Conserved Sequence; CpG Islands; Databases, Factual; DNA Transposable Elements; Drug Industry; Evolution, Molecular; Forecasting; GC Rich Sequence; Gene Duplication; Genes; Genetic Diseases, Inborn; Genetics, Medical; Genome, Human; Human Genome Project; Humans; Mutation; Private Sector; Proteins; Proteome; Public Sector; Repetitive Sequences, Nucleic Acid; RNA; Sequence Analysis, DNA; Species Specificity

A physical map of the human genome. - McPherson, J D; Marra, M; Hillier, L; Waterston, R H; Chinwalla, A; Wallis, J; Sekhon, M; Wylie, K; Mardis, E R; Wilson, R K; Fulton, R; Kucaba, T A; et al. (Nature, 2001)
The human genome is by far the largest genome to be sequenced, and its size and complexity present many challenges for sequence assembly. The International Human Genome Sequencing Consortium constructed a map of the whole genome to enable the selection of clones for sequencing and for the accurate assembly of the genome sequence. Here we report the construction of the whole-genome bacterial artificial chromosome (BAC) map and its integration with previous landmark maps and information from mapping efforts focused on specific chromosomal regions. We also describe the integration of sequence data with the map.
Keywords: Chromosomes, Artificial, Bacterial; Cloning, Molecular; Contig Mapping; DNA Fingerprinting; Gene Duplication; Genome, Human; Humans; In Situ Hybridization, Fluorescence; Repetitive Sequences, Nucleic Acid

A simple model host for identifying Gram-positive virulence factors. - Garsin, D A; Sifri, C D; Mylonakis, E; Qin, X; Singh, K V; Murray, B E; Calderwood, S B; Ausubel, F M (Proc Natl Acad Sci U S A, 2001)
We demonstrate the use of the nematode Caenorhabditis elegans as a facile and inexpensive model host for several Gram-positive human bacterial pathogens. Enterococcus faecalis, Streptococcus pneumoniae, and Staphylococcus aureus, but not Bacillus subtilis, Enterococcus faecium, or Streptococcus pyogenes, kill adult C. elegans. Focusing our studies on the enterococcal species, we found that both E. faecalis and E. faecium kill C. elegans eggs and hatchlings, although only E. faecalis kills the adults. In the case of adults, a low inoculum of E. faecalis grows to a high titer in the C. elegans intestine, resulting in a persistent infection that cannot be eradicated by prolonged feeding on E. faecium. Interestingly, a high titer of E. faecium also accumulates in the nematode gut, but does not affect the longevity of the worms. Two E. faecalis virulence-related factors that play an important role in mammalian models of infection, fsr, a putative quorum-sensing system, and cytolysin, are also important for nematode killing. We exploit the apparent parallels between Gram-positive infection in simple and more complex organisms by using the nematode to identify an E. faecalis virulence factor, ScrB, which is relevant to mammalian pathogenesis.
Keywords: Animals; Bacillus subtilis; Bacterial Proteins; Bacteriocins; Caenorhabditis elegans; Cytotoxins; Digestive System; Disease Models, Animal; Enterococcus faecalis; Enterococcus faecium; Gene Deletion; Gram-Positive Bacteria; Humans; Mice; Mice, Inbred ICR; Staphylococcus aureus; Streptococcus pneumoniae; Streptococcus pyogenes

A BAC-based physical map of the major autosomes of Drosophila melanogaster. - Hoskins, R A; Nelson, C R; Berman, B P; Laverty, T R; George, R A; Ciesiolka, L; Naeemuddin, M; Arenson, A D; Durbin, J; David, R G; Tabor, P E; Bailey, M R; et al. (Science, 2000)
We constructed a bacterial artificial chromosome (BAC)-based physical map of chromosomes 2 and 3 of Drosophila melanogaster, which constitute 81% of the genome. Sequence tagged site (STS) content, restriction fingerprinting, and polytene chromosome in situ hybridization approaches were integrated to produce a map spanning the euchromatin. Three of five remaining gaps are in repeat-rich regions near the centromeres. A tiling path of clones spanning this map and STS maps of chromosomes X and 4 was sequenced to low coverage; the maps and tiling path sequence were used to support and verify the whole-genome sequence assembly, and tiling path BACs were used as templates in sequence finishing.
Keywords: Animals; Centromere; Chromatin; Chromosomes, Bacterial; Cloning, Molecular; Contig Mapping; DNA Fingerprinting; Drosophila melanogaster; Euchromatin; Gene Library; Genes, Insect; Genetic Markers; Genetic Vectors; Genome; In Situ Hybridization; Repetitive Sequences, Nucleic Acid; Restriction Mapping; Sequence Analysis, DNA; Sequence Tagged Sites; Telomere

Construction of a high-resolution physical map of the chromosome 10q22-q23 dilated cardiomyopathy locus and analysis of candidate genes. - Bowles, K R; Abraham, S E; Brugada, R; Zintz, C; Comeaux, J; Sorajja, D; Tsubata, S; Li, H; Brandon, L; Richard A Gibbs; Steven E Scherer; Bowles, N E; et al. (Genomics, 2000)
Dilated cardiomyopathy (DCM) is a major cause of morbidity and mortality and a leading cause of cardiac transplantation worldwide. Multiple loci and three genes encoding cardiac actin, desmin, and lamin A/C have been described for autosomal dominant DCM. Using recombination analysis, we have narrowed the 10q21-q23 locus to a region of approximately 4.1 cM. In addition, we have constructed a BAC contig, composed of 199 clones, which was used to develop a high-resolution physical map that contains the DCM critical region (approximately 3.9 Mb long). Seven genes, including ANX11, PPIF, DLG5, RPC155, RPS24, SFTPA1, and KCNMA1, have been mapped to the region of interest. RPC155, RPS24, SFTPA1, and KCNMA1 were excluded from further analysis based on their known functions and tissue-specific expression patterns. Mutational analysis of ANX11, DLG5, and PPIF revealed no disease-associated mutations. Multiple ESTs have also been mapped to the critical region.
Keywords: Cardiomyopathy, Dilated; Chromosomes, Bacterial; Chromosomes, Human, Pair 10; DNA Mutational Analysis; Expressed Sequence Tags; Family Health; Female; Genetic Predisposition to Disease; Genomic Library; Humans; Male; Pedigree; Phenotype; Physical Chromosome Mapping; Sequence Analysis, DNA

Effects of Enterococcus faecalis fsr genes on production of gelatinase and a serine protease and virulence. - Qin, X; Singh, K V; Weinstock, G M; Murray, B E (Infect Immun, 2000)
Three agr-like genes (fsrA, fsrB, and fsrC, for Enterococcus faecalis regulator) were found upstream of the previously reported gelatinase gene (gelE) and a downstream putative serine protease gene (sprE; accession number Z12296) of Enterococcus faecalis OG1RF. The deduced amino acid sequence of fsrA shows 26% identity and 38% similarity to Staphylococcus aureus AgrA (the response regulator of the accessory gene regulator system in the agr locus), FsrB shows 23% identity and 41% similarity to S. aureus AgrB, and FsrC shows 23% identity and 36% similarity to S. aureus AgrC (the sensor transducer of Agr system). Northern blot analysis suggested that gelE and sprE are cotranscribed and that fsrB and fsrC are also cotranscribed in OG1RF. Northern blot analysis of fsrA, fsrB, fsrC, gelE, and sprE insertion mutants showed that fsrB, fsrC, gelE, and sprE are not expressed in fsrA, fsrB, and fsrC mutants, while insertion in an open reading frame further upstream of fsrA did not effect the expression of these genes, suggesting that agr-like genes may be autoregulated and that they regulate gelE and sprE expression, as further confirmed by complementation of fsr gene mutations with a 6-kb fragment which contains all three fsr genes in the shuttle vector, pAT18. Testing of 95 other isolates of E. faecalis showed that 62% produced gelatinase (Gel(+)), while 91% (including all Gel(+) strains) hybridized to a gelE probe; 71% (including all Gel(+) strains) hybridized to an fsr probe, corroborating the conclusion that both gelE and fsr are necessary for gelatinase production. Testing of fsrA, fsrB, and sprE mutants in a mouse peritonitis model showed that sprE and agr-like gene mutants resulted in highly significantly prolonged survival compared to the parent strain OG1RF, a finding similar to what we had previously shown for a gelE mutant. These results suggest that sprE and agr-like genes contribute to the virulence of E. faecalis OG1RF in this model.
Keywords: Amino Acid Sequence; Animals; Bacterial Proteins; Base Sequence; Blotting, Northern; Databases, Factual; Dihydropteridine Reductase; Disease Models, Animal; DNA, Bacterial; DNA-Binding Proteins; Enterococcus faecalis; Escherichia coli Proteins; Gelatinases; Genes, Bacterial; Genetic Complementation Test; Hemeproteins; Mice; Molecular Sequence Data; NADH, NADPH Oxidoreductases; Peritonitis; Phenotype; Reverse Transcriptase Polymerase Chain Reaction; Sequence Analysis, DNA; Serine Endopeptidases; Trans-Activators; Transcription Factors; Virulence

The Escherichia coli UVM response is accompanied by an SOS-independent error-prone DNA replication activity demonstrable in vitro. - al Mamun, A A; Yadava, R S; Ren, L; Humayun, M Z (Mol Microbiol, 2000)
UVM is an SOS-independent inducible response characterized by elevated mutagenesis at a site-specific 3, N4-ethenocytosine (epsilonC) residue borne on M13 single-stranded DNA transfected into Escherichia coli cells pretreated with DNA-damaging agents. By constructing and using E. coli strain AM124 (polA polB umuDC dinB lexA1[Ind-]), we show here that the UVM response is manifested in cells deficient for SOS induction, as well as for all four of the 'non-replicative' DNA polymerases, namely DNA polymerase I (polA), II (polB), IV (dinB) and V (umuDC). These results confirm that UVM represents a novel, previously unidentified cellular response to DNA-damaging agents. To address the question as to whether the UVM response is accompanied by an error-prone DNA replication activity, we applied a newly developed in vitro replication assay coupled to an in vitro mutation analysis system. In the assay, circular M13 single-stranded DNA bearing a site-specific lesion is converted to circular double-stranded replicative-form DNA in the presence of cell extracts and nucleotide precursors under conditions that closely mimic M13 replication in vivo. The newly synthesized (minus) DNA strand is selectively amplified by ligation-mediated polymerase chain reaction (LM-PCR), followed by a multiplex sequence analysis to determine the frequency and specificity of mutations. Replication of DNA bearing a site-specific epsilonC lesion by cell extracts from uninduced E. coli AM124 cells results in a mutation frequency of about 13%. Mutation frequency is elevated fivefold (to 58%) in cell extracts from UVM-induced AM124 cells, with C --> A mutations predominating over C --> T mutations, a specificity similar to that observed in vivo. These results, together with previously reported data, suggest that the UVM response is mediated through the induction of a transient error-prone DNA replication activity and that a modification of DNA polymerase III or the expression of a previously unidentified DNA polymerase may account for the UVM phenotype.
Keywords: Bacterial Proteins; Bacteriophage M13; Cytosine; DNA Polymerase beta; DNA Polymerase I; DNA Polymerase II; DNA Replication; DNA, Single-Stranded; DNA, Viral; DNA-Directed DNA Polymerase; Escherichia coli; Escherichia coli Proteins; Mutagenesis, Site-Directed; Mutagens; SOS Response, Genetics; Ultraviolet Rays

Fine mapping and characterization of candidate lung tumor resistance genes for the Par2 locus on mouse chromosome 18. - Zhang, Z; Lin, L; Liu, G; Wang, M; Hill, J; Wang, Y; You, M; Devereux, T R (Exp Lung Res, 2000)
In a number of recent studies, a lung tumor resistance locus designated either Par2 or Pas7 was mapped to distal chromosome 18 in crosses between susceptible A/J and more resistant BALB/c mice. This locus is important in that it accounts for as much as 60% of the difference in lung tumor susceptibility between the A/J and BALB/c mice, both of which contain the susceptible allele of Kras2, a marker and strong candidate for the major lung tumor susceptibility gene on mouse chromosome 6. We have now fine-mapped the Par2 locus by using congenic mice that were constructed by placing part of chromosome 18 from the susceptible A/J onto the genetic background of lung tumor-resistant BALB/c mice. After 7 generations of backcrossing, N7 mice that carried 28 cM of the A/J quantitative trait locus (QTL) region were crossed to the BALB/c to generate the N8 generation. Congenic strains (N8) that contain various QTL regions were generated. N9 mice, generated from N8 males x 3 BALB/c females, were genotyped in the region of the Par2 locus and treated with an initiating dose of urethane and allowed to form lung tumors over 6 months. The mice were killed and the lung tumors counted. With this cross the Par2 locus was narrowed to a 6-cM region. Potential candidate genes in this region include Smad4, Smad2, and Dcc. Previously, we excluded Smad4 and Smad2 as candidates for Par2 based on the lack of functional polymorphism(s) and differential expression in lungs from A/J and BALB/c mice. In this study, no polymorphism of the coding sequence of Dcc was observed between A/J and BALB/c mice. Further fine mapping and positional cloning are required for the identification of the Par2 gene.
Keywords: Adenoma; Animals; Animals, Congenic; Chromosome Mapping; Disease Models, Animal; DNA, Neoplasm; Female; Genetic Markers; Genetic Predisposition to Disease; Lung Neoplasms; Male; Mice; Mice, Inbred BALB C; Polymerase Chain Reaction; Polymorphism, Single-Stranded Conformational; Pregnancy; Sequence Analysis, DNA

The genome sequence of Drosophila melanogaster. - Adams, M D; Celniker, S E; Holt, R A; Evans, C A; Gocayne, J D; Amanatides, P G; Steven E Scherer; Li, P W; Hoskins, R A; Galle, R F; George, R A; Lewis, S E; et al. (Science, 2000)
The fly Drosophila melanogaster is one of the most intensively studied organisms in biology and serves as a model system for the investigation of many developmental and cellular processes common to higher eukaryotes, including humans. We have determined the nucleotide sequence of nearly all of the approximately 120-megabase euchromatic portion of the Drosophila genome using a whole-genome shotgun sequencing strategy supported by extensive clone-based sequence and a high-quality bacterial artificial chromosome physical map. Efforts are under way to close the remaining gaps; however, the sequence is of sufficient accuracy and contiguity to be declared substantially complete and to support an initial analysis of genome structure and preliminary gene annotation and interpretation. The genome encodes approximately 13,600 genes, somewhat fewer than the smaller Caenorhabditis elegans genome, but with comparable functional diversity.
Keywords: Animals; Biological Transport; Chromatin; Cloning, Molecular; Computational Biology; Contig Mapping; Cytochrome P-450 Enzyme System; DNA Repair; DNA Replication; Drosophila melanogaster; Euchromatin; Gene Library; Genes, Insect; Genome; Heterochromatin; Insect Proteins; Nuclear Proteins; Protein Biosynthesis; Sequence Analysis, DNA; Transcription, Genetic

Haplotypes at ATM identify coding-sequence variation and indicate a region of extensive linkage disequilibrium. - Bonnen, P E; Story, M D; Ashorn, C L; Buchholz, T A; Weil, M M; Nelson, D L (Am J Hum Genet, 2000)
Genetic variation in the human population may lead to functional variants of genes that contribute to risk for common chronic diseases such as cancer. In an effort to detect such possible predisposing variants, we constructed haplotypes for a candidate gene and tested their efficacy in association studies. We developed haplotypes consisting of 14 biallelic neutral-sequence variants that span 142 kb of the ATM locus. ATM is the gene responsible for the autosomal recessive disease ataxia-telangiectasia (AT). These ATM noncoding single-nucleotide polymorphisms (SNPs) were genotyped in nine CEPH families (89 individuals) and in 260 DNA samples from four different ethnic origins. Analysis of these data with an expectation-maximization algorithm revealed 22 haplotypes at this locus, with three major haplotypes having frequencies > or = .10. Tests for recombination and linkage disequilibrium (LD) show reduced recombination and extensive LD at the ATM locus, in all four ethnic groups studied. The most striking example was found in the study population of European ancestry, in which no evidence for recombination could be discerned. The potential of ATM haplotypes for detection of genetic variants through association studies was tested by analysis of 84 individuals carrying one of three ATM coding SNPs. Each coding SNP was detected by association with an ATM haplotype. We demonstrate that association studies with haplotypes for candidate genes have significant potential for the detection of genetic backgrounds that contribute to disease.
Keywords: Algorithms; Alleles; Animals; Ataxia Telangiectasia; Ataxia Telangiectasia Mutated Proteins; Case-Control Studies; Cell Cycle Proteins; Codon; DNA-Binding Proteins; Ethnicity; Europe; Gene Frequency; Genetic Variation; Haplotypes; Hominidae; Humans; Linkage Disequilibrium; Molecular Sequence Data; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases; Racial Groups; Recombination, Genetic; Tumor Suppressor Proteins

The human transcript database: a catalogue of full length cDNA inserts. - Bouck, J; McLeod, M P; Worley, K; Richard A Gibbs (Bioinformatics, 2000)
SUMMARY: Full length cDNA sequences are an important resource for the research community but are currently intermingled with other sequences. We have identified the human full length insert cDNA sequences in GenBank and placed them in a single location, the Human Transcript Database. AVAILIBILITY: The Human Transcript Database is available at http://www.hgsc.bcm.tms.edu/HTDB/. CONTACT: John Bouck: jbouck@bcm.tmc.edu
Keywords: Databases, Factual; DNA Transposable Elements; DNA, Complementary; Humans; RNA, Messenger

Intranasal immunization with HIV reverse transcriptase: effect of dose in the induction of helper T cell type 1 and 2 immunity. - Pacheco, S E; Richard A Gibbs; Ansari-Lari, A; Rogers, P (AIDS Res Hum Retroviruses, 2000)
HIV reverse transcriptase (RT) is immunologically recognized by the host after natural infection with HIV. To study the immune response to this nonenvelope protein and the effect of the antigen dose and the immunization route on the differential induction of cellular or humoral responses, CB6F1 mice were immunized intranasally with various doses of recombinant RT (0.025-25 microg/dose) in the presence of the mucosal adjuvant cholera toxin (CT). An antigen-specific, dose-dependent, in vitro proliferative response was observed in splenic cells from all mouse groups immunized with RT and CT. Proliferative responses in salivary gland-associated lymph node (SGALN) cells from the same mice were detected only with higher antigen dose immunizations (2.5, 25 microg/dose). IFN-gamma, a Th1-type cytokine, was detected in RT-stimulated culture supernatants from splenic and SGALN cells from all groups of mice immunized with RT and CT in a dose-dependent fashion. IL-4, a Th2-type cytokine, was detected in RT-stimulated culture supernatants from splenic and SGALN cells from mice immunized with higher doses of RT and CT. RT-specific IgG2a, a Th1-type-related antibody, was detected consistently in sera from all animals immunized with RT and CT and was predominant in mice immunized with lower antigen doses (0.025, 0.25 microg/dose). RT-specific IgG1, a Th2-type-related antibody, was detected consistently in mice immunized with higher antigen doses and was predominant in these groups. These studies demonstrate the immunogenicity of recombinant RT and the effect of the antigen dose in the induction of Th1-type and Th2-type immune responses after mucosal immunization.
Keywords: Administration, Intranasal; AIDS Vaccines; Animals; Cytokines; Dose-Response Relationship, Immunologic; Female; HIV Antibodies; HIV Reverse Transcriptase; Immunization; Immunoglobulin G; Lymph Nodes; Lymphocyte Activation; Mice; Recombinant Proteins; Salivary Glands; Spleen; Th1 Cells; Th2 Cells

Large expansion of the ATTCT pentanucleotide repeat in spinocerebellar ataxia type 10. - Matsuura, T; Yamagata, T; Burgess, D L; Rasmussen, A; Grewal, R P; Watase, K; Khajavi, M; McCall, A E; Davis, C F; Zu, L; Achari, M; Pulst, S M; et al. (Nat Genet, 2000)
Spinocerebellar ataxia type 10 (SCA10; MIM 603516; refs 1,2) is an autosomal dominant disorder characterized by cerebellar ataxia and seizures. The gene SCA10 maps to a 3.8-cM interval on human chromosome 22q13-qter (refs 1,2). Because several other SCA subtypes show trinucleotide repeat expansions, we examined microsatellites in this region. We found an expansion of a pentanucleotide (ATTCT) repeat in intron 9 of SCA10 in all patients in five Mexican SCA10 families. There was an inverse correlation between the expansion size, up to 22.5 kb larger than the normal allele, and the age of onset (r2=0.34, P=0.018). Analysis of 562 chromosomes from unaffected individuals of various ethnic origins (including 242 chromosomes from Mexican persons) showed a range of 10 to 22 ATTCT repeats with no evidence of expansions. Our data indicate that the new SCA10 intronic ATTCT pentanucleotide repeat in SCA10 patients is unstable and represents the largest microsatellite expansion found so far in the human genome.
Keywords: Animals; Asian People; Brain; Chromosome Mapping; Chromosomes, Human, Pair 22; DNA; Epilepsy; Female; Humans; Male; Mexican Americans; Mice; Mice, Inbred C57BL; Molecular Sequence Data; Pedigree; Polymorphism, Genetic; Repetitive Sequences, Nucleic Acid; Spinocerebellar Ataxias; United States; White People

PipMaker--a web server for aligning two genomic DNA sequences. - Schwartz, S; Zhang, Z; Frazer, K A; Smit, A; Riemer, C; Bouck, J; Gibbs, R; Hardison, R; Miller, W (Genome Res, 2000)
PipMaker (http://bio.cse.psu.edu) is a World-Wide Web site for comparing two long DNA sequences to identify conserved segments and for producing informative, high-resolution displays of the resulting alignments. One display is a percent identity plot (pip), which shows both the position in one sequence and the degree of similarity for each aligning segment between the two sequences in a compact and easily understandable form. Positions along the horizontal axis can be labeled with features such as exons of genes and repetitive elements, and colors can be used to clarify and enhance the display. The web site also provides a plot of the locations of those segments in both species (similar to a dot plot). PipMaker is appropriate for comparing genomic sequences from any two related species, although the types of information that can be inferred (e.g., protein-coding regions and cis-regulatory elements) depend on the level of conservation and the time and divergence rate since the separation of the species. Gene regulatory elements are often detectable as similar, noncoding sequences in species that diverged as much as 100-300 million years ago, such as humans and mice, Caenorhabditis elegans and C. briggsae, or Escherichia coli and Salmonella spp. PipMaker supports analysis of unfinished or "working draft" sequences by permitting one of the two sequences to be in unoriented and unordered contigs.
Keywords: Animals; Base Sequence; Caenorhabditis elegans; Computational Biology; DNA; Escherichia coli; Genes, Bacterial; Genes, Helminth; Genes, Protozoan; Humans; Internet; Mice; Molecular Sequence Data; Salmonella typhimurium; Sequence Alignment; Software

Requirement for homologous recombination functions for expression of the mutA mistranslator tRNA-induced mutator phenotype in Escherichia coli. - Ren, L; al Mamun, A A; Humayun, M Z (J Bacteriol, 2000)
Expression of the Escherichia coli mutA mutator phenotype requires recA, recB, recC, ruvA, and ruvC gene, but not recD, recF, recO, or recR genes. Thus, the recBCD-dependent homologous recombination system is a component of the signal pathway that activates an error-prone DNA polymerase in mutA cells.
Keywords: Bacterial Proteins; DNA Helicases; DNA-Binding Proteins; Endodeoxyribonucleases; Escherichia coli; Escherichia coli Proteins; Exodeoxyribonuclease V; Exodeoxyribonucleases; Gene Expression Regulation, Bacterial; Genes, Bacterial; Mutation; Phenotype; Rec A Recombinases; Recombination, Genetic; RNA, Transfer; Signal Transduction

An allylic/acyclic adenosine nucleoside triphosphate for termination of DNA synthesis by DNA template-dependent polymerases. - Martinez, C I; Thoresen, L H; Gibbs, R A; Burgess, K (Nucleic Acids Res, 1999)
An allylic adenosine triphosphate analog (AATP) was tested as a substrate for commercially available DNA polymerases. All but one of the enzymes assayed incorporated AATP opposite thymidine (T) with concomitant termination of the elongation reaction. A concentration of only 1 microM was sufficient for complete termination of the polymerization reaction for a short template mediated by Ampli Taq DNA polymerase FS (Taq FS). This result suggests that AATP could be used as a 2',3'-dideoxyadenosine-5'-triphosphate (ddA) surrogate. Kinetics of incorporation revealed that AATP was 48 times less efficiently incorporated than ddA. Furthermore, AATP was used in dye-primer sequencing as a substitute for ddA.
Keywords: Adenosine Triphosphate; Base Sequence; Boron Compounds; DNA; DNA Primers; DNA Replication; DNA-Directed DNA Polymerase; Fluorescent Dyes; Kinetics; Substrate Specificity; Templates, Genetic

Comparison of gene indexing databases. - Bouck, J; Yu, W; Richard A Gibbs; Kim C Worley (Trends Genet, 1999)
Keywords: Abstracting and Indexing; Alternative Splicing; Cluster Analysis; Databases, Factual; DNA, Complementary; Expressed Sequence Tags; Genome, Human; Humans

Escherichia coli cells bearing mutA, a mutant glyV tRNA gene, express a recA-dependent error-prone DNA replication activity. - al Mamun, A A; Rahman, M S; Humayun, M Z (Mol Microbiol, 1999)
A base substitution mutation (mutA) in the Escherichia coli glyV tRNA gene potentiates asp --> gly mistranslation and confers a strong mutator phenotype that is SOS independent, but requires recA, recB and recC genes. Here, we demonstrate that mutA cells express an error-prone DNA polymerase by using an in vitro experimental system based on the conversion of phage M13 single-stranded viral DNA bearing a model mutagenic lesion to the double-stranded replicative form. Amplification of the newly synthesized strand followed by multiplex DNA sequence analysis revealed that mutation fixation at 3, N4-ethenocytosine (varepsilonC) was approximately 3% when the DNA was replicated by normal cell extracts, approximately 48% when replicated by mutA cell extracts and approximately 3% when replicated by mutA recA double mutant cell extracts, in complete agreement with previous in vivo results. Mutagenesis at undamaged DNA sites was significantly elevated by mutA cell-free extracts in the M13 lacZ(alpha) forward mutagenesis system. Neither polA (DNA polymerase I) nor polB (DNA polymerase II) genes are required for the mutA phenotype, suggesting that the phenotype is mediated through a modification of DNA polymerase III or the activation of a previously unidentified DNA polymerase. These findings define the major features of a novel mutagenic pathway and imply the existence of previously unrecognized links between translation, recombination and replication.
Keywords: Animals; Bacteriophage M13; Cytosine; DNA Polymerase III; DNA Replication; DNA, Single-Stranded; DNA, Viral; Escherichia coli; Escherichia coli Proteins; Exodeoxyribonuclease V; Exodeoxyribonucleases; Genes, Bacterial; Genotype; Mutation; Rec A Recombinases; RNA, Transfer, Gly; Sequence Analysis, DNA

Sequence and organization of pXO1, the large Bacillus anthracis plasmid harboring the anthrax toxin genes. - Okinaka, R T; Cloud, K; Hampton, O; Hoffmaster, A R; Hill, K K; Keim, P; Koehler, T M; Lamke, G; Kumano, S; Mahillon, J; Manter, D; Martinez, Y; et al. (J Bacteriol, 1999)
The Bacillus anthracis Sterne plasmid pXO1 was sequenced by random, "shotgun" cloning. A circular sequence of 181,654 bp was generated. One hundred forty-three open reading frames (ORFs) were predicted using GeneMark and GeneMark.hmm, comprising only 61% (110,817 bp) of the pXO1 DNA sequence. The overall guanine-plus-cytosine content of the plasmid is 32.5%. The most recognizable feature of the plasmid is a "pathogenicity island," defined by a 44.8-kb region that is bordered by inverted IS1627 elements at each end. This region contains the three toxin genes (cya, lef, and pagA), regulatory elements controlling the toxin genes, three germination response genes, and 19 additional ORFs. Nearly 70% of the ORFs on pXO1 do not have significant similarity to sequences available in open databases. Absent from the pXO1 sequence are homologs to genes that are typically required to drive theta replication and to maintain stability of large plasmids in Bacillus spp. Among the ORFs with a high degree of similarity to known sequences are a collection of putative transposases, resolvases, and integrases, suggesting an evolution involving lateral movement of DNA among species. Among the remaining ORFs, there are three sequences that may encode enzymes responsible for the synthesis of a polysaccharide capsule usually associated with serotype-specific virulent streptococci.
Keywords: Antigens, Bacterial; Bacillus anthracis; Bacterial Toxins; DNA, Bacterial; Genes, Bacterial; Molecular Sequence Data; Open Reading Frames; Plasmids; Recombination, Genetic; Replication Origin; Restriction Mapping; Sequence Analysis, DNA; Sequence Homology

Somatic sequence variation at the Friedreich ataxia locus includes complete contraction of the expanded GAA triplet repeat, significant length variation in serially passaged lymphoblasts and enhanced mutagenesis in the flanking sequence. - Bidichandani, S I; Purandare, S M; Taylor, E E; Gumin, G; Machkhas, H; Harati, Y; Richard A Gibbs; Ashizawa, T; Patel, P I (Hum Mol Genet, 1999)
The vast majority of Friedreich ataxia patients are homozygous for large GAA triplet repeat expansions in intron 1 of the X25 gene. Instability of the expanded GAA repeat was examined in 23 chromosomes bearing 97-1250 triplets in lymphoblastoid cell lines passaged 20-39 times. Southern analyses revealed 18 events of significant changes in length ranging from 69 to 633 triplets, wherein the de novo allele gradually replaced the original over 1-6 passages. Contractions and expansions occurred with equal frequency and magnitude. This behavior is unique in comparison with other large, non-coding triplet repeat expansions [(CGG)(n)and (CTG)(n)] which remain relatively stable under similar conditions. We also report a rare patient who, having inherited two expanded alleles, showed evidence of contracted GAA repeats ranging from nine to 29 triplets in DNA from two independent peripheral blood samples. The GAA triplet repeat is known to adopt a triplex structure, and triplexes in transcribed templates cause enhanced mutagenesis. The poly(A) tract and a 135 bp sequence, both situated immediately upstream of the GAA triplet repeat, were therefore examined for somatic mutations. The poly(A) tract showed enhanced instability when in cis with the GAA expansion. The 135 bp upstream sequence was found to harbor a 3-fold excess of point mutations in DNA derived from individuals homozygous for the GAA triplet repeat expansion compared with normal controls. These data are likely to have important mechanistic and clinical implications.
Keywords: Base Sequence; Cells, Cultured; DNA Mutational Analysis; Frataxin; Friedreich Ataxia; Humans; Iron-Binding Proteins; Lymphocyte Activation; Lymphocytes; Molecular Sequence Data; Phosphotransferases (Alcohol Group Acceptor); Poly A; Trinucleotide Repeat Expansion

Association between serum insulin growth factor-I (IGF-I) and a simple sequence repeat in IGF-I gene: implications for genetic studies of bone mineral density. - Rosen, C J; Kurland, E S; Vereault, D; Adler, R A; Rackoff, P J; Craig, W Y; Witte, S; Rogers, J; Bilezikian, J P (J Clin Endocrinol Metab, 1998)
We recently demonstrated that insulin growth factor-I (IGF-I) cosegregates with bone mineral density (BMD) in progenitor crosses of two inbred strains of mice. Additionally, we reported that men with idiopathic osteoporosis (IOM) have low serum IGF-I levels, which can be related to BMD and bone turnover. In this study, we considered the possibility that serum IGF-I levels are influenced by molecular genetic variation in the IGF-I structural gene, and that a polymorphic microsatellite (CA repeat) in this locus can be used as a genetic marker for such comparisons. We studied 171 men and women, classified according to the trial in which they were participating. First, in 25 Caucasian men with IOM we noted a very high frequency (64%) of homozygosity for the most common allele (192 bp) in a dinucleotide repeat 1 kb upstream from the transcription start site of the IGF-I gene. This compared with a frequency of only 32% in healthy populations (both men and women) (P < 0.004). Next, we determined that for 116 healthy Caucasian men and women the 192/192 genotype was associated with lower serum IGF-I levels than all other genotypes (192/192: 129 +/- 7 ng/mL vs. others: 154 +/- 7 ng/mL, P = 0.03). We also noted that subjects possessing one 194-bp allele exhibited serum IGF-I levels 25% higher than those homozygous for 192 bp (192/192), (P < 0.005) even after correction for age and sex. Similarly, for men with the 192/192 genotype, serum IGF-I concentrations were lower than any other genotype (145 +/- 10 ng/mL vs. 183 +/- 9 ng/ml P < 0.02). In conclusion, low serum IGF-I levels found in men with IOM are associated with homozygosity for a specific allele of the IGF-I microsatellite (192/192), and individual variation in serum IGF-I levels is influenced by genetic factors and may be specifically influenced by variation at the IGF-I structural locus. Further family and pedigree studies are needed to characterize the relationship of bone mass acquisition to the IGF-I genotype.
Keywords: Aged; Alleles; Bone Density; Dinucleotide Repeats; Female; Gene Frequency; Genotype; Humans; Insulin-Like Growth Factor I; Male; Middle Aged; Phenotype; Polymorphism, Genetic

BEAUTY-X: enhanced BLAST searches for DNA queries. - Kim C Worley; Culpepper, P; Wiese, B A; Smith, R F (Bioinformatics, 1998)
UNLABELLED: BEAUTY (BLAST Enhanced Alignment Utility) is an enhanced version of the BLAST database search tool that facilitates identification of the functions of matched sequences. Three recent improvements to the BEAUTY program described here make the enhanced output (1) available for DNA queries, (2) available for searches of any protein database, and (3) more up-to-date, with periodic updates of the domain information. AVAILABILITY: BEAUTY searches of the NCBI and EMBL non-redundant protein sequence databases are available from the BCM Search Launcher Web pages (http://gc.bcm.tmc. edu:8088/search-launcher/launcher.html). BEAUTY Post-Processing of submitted search results is available using the BCM Search Launcher Batch Client (version 2.6) (ftp://gc.bcm.tmc. edu/pub/software/search-launcher/). SUPPLEMENTARY INFORMATION: Example figures are available at http://dot.bcm.tmc. edu:9331/papers/beautypp.html CONTACT: (kworley,culpep)@bcm.tmc.edu
Keywords: Amino Acid Sequence; Computational Biology; Databases, Factual; DNA; Molecular Sequence Data; Proteins; Sequence Alignment; Software

DNA deletion confined to the iduronate-2-sulfatase promoter abolishes IDS gene expression. - Timms, K M; Huckett, L E; Belmont, J W; Shapira, S K; Richard A Gibbs (Hum Mutat, 1998)
Deficiency of the enzyme iduronate-2-sulfatase (IDS) results in Hunter syndrome, an X-linked recessive lysosomal storage disorder. In this study, analysis of a patient with features of moderate to severe Hunter syndrome identified a 178-bp deletion upstream of IDS exon 1 spanning a predicted promoter element. Sequencing of all nine IDS exons from this patient failed to identify any additional mutations within the coding regions or in intron-exon boundaries. The 178-bp deletion is flanked by two 13-bp direct repeats and potential DNA topoisomerase II recognition sites. These findings point toward nonhomologous recombination as a possible mechanism for this mutation. Expression studies on this patient do not detect any IDS transcripts, indicating that the deletion spans sequences essential for IDS expression. Complete lack of expression of IDS is consistent with the moderate to severe phenotype observed in this patient.
Keywords: Base Sequence; Child, Preschool; DNA Mutational Analysis; Gene Expression Regulation; Humans; Iduronate Sulfatase; Male; Molecular Sequence Data; Mucopolysaccharidosis II; Pedigree; Phenotype; Promoter Regions, Genetic; Sequence Analysis, DNA; Sequence Deletion

Elimination of residual natural nucleotides from 3'-O-modified-dNTP syntheses by enzymatic mop-up. - Metzker, M L; Raghavachari, R; Burgess, K; Richard A Gibbs (Biotechniques, 1998)
Here, we describe a novel strategy called enzymatic "Mop-Up" that efficiently removes contaminating dNTPs from reverse-phase, high-performance liquid chromatography (RP-HPLC) purified 3'-O-modified dNTP syntheses. Enzymatic mop-up takes advantage of the high selectivity of DNA polymerases for the former nucleoside triphosphates over the latter nucleotide analogs. We demonstrate the selective removal of contaminating dATP and dTTP from RP-HPLC purified 3'-O-methyl-dATP and 3'-O-(2-nitrobenzyl)-dTTP syntheses, respectively. These data highlight the importance of natural nucleotide contamination when interpreting enzymatic incorporation data and provide an alternative hypothesis for the observed property of catalytic editing of DNA polymerases. Moreover, the effective removal of natural nucleotides from 3'-O-modified analogs addresses the important issue of nucleotide read-through for stop-start DNA sequencing strategies, such as the base addition sequencing scheme (BASS).
Keywords: Base Sequence; Chromatography, High Pressure Liquid; Deoxyribonucleotides; DNA; DNA-Directed DNA Polymerase

Generation and testing of mutants of Enterococcus faecalis in a mouse peritonitis model. - Singh, K V; Xiang Qin; Weinstock, G M; Murray, B E (J Infect Dis, 1998)
A previously described mouse peritonitis model was used to study derivatives of Enterococcus faecalis strain OG1RF. The addition of sterile rat fecal extracts (SRFE) lowered the LD50 of OG1RF >10-fold. Hemolysin production caused a 35-fold lower LD50 and a much shorter survival, similar to previous results using a peritonitis model without SRFE. A purine (but not a pyrimidine) auxotroph was considerably less lethal than wild type; gelatinase mutants were also attenuated. A suicide vector was generated with an enterococcal selectable marker in order to disrupt a gene encoding an E. faecalis antigen; the resulting mutant was not attenuated despite a slower growth rate. In conclusion, this model allows attenuated mutants to be detected, corroborates prior reports that hemolysin is a virulence factor, and suggests a role for gelatinase in virulence of E. faecalis in mice; the attenuated purine auxotroph may provide a system for developing vectors for in vivo expression systems.
Keywords: Animals; Disease Models, Animal; Enterococcus faecalis; Feces; Female; Gelatinases; Gram-Positive Bacterial Infections; Hemolysin Proteins; Mice; Mutation; Peritonitis; Rats

The genomic organization of Isopeptidase T-3 (ISOT-3), a new member of the ubiquitin specific protease family (UBP). - Timms, K M; Ansari-Lari, M A; Morris, W; Brown, S N; Richard A Gibbs (Gene, 1998)
A novel Isopeptidase T gene (ISOT-3) has been identified on human mosome 3q26.2--q26.3. gene shows 67.3% nucleotide identity and 54.8% amino acid identity to n Isopeptidase (ISOT-1). Northern blot analysis has shown that ISOT-3 is highly essed in ovary and testes, low-level expression in six other tissues tested. In contrast, ISOT-1 is essed at high levels in brain, and there is no detectable expression in ovary. The exonic nization of these two genes highly conserved with only one variant intron position. Intron 15 in -3 is absent in ISOT-1, there is an alternate splice site at the same location. Although the --intron structure has been erved between the two genes, ISOT-3 has significantly larger intronic ons, and the overall of this gene is at least 90 kb compared to 15 kb for ISOT-1. These data suggest that both ISOT-1 and ISOT-3 have descended from a common ancestor. In addition, the low overall sequence identity and different expression patterns may reflect differences in substrate specificity.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Carbon-Nitrogen Lyases; Chromosome Mapping; Chromosomes, Human, Pair 3; Consensus Sequence; DNA, Complementary; Exons; Female; Gene Library; Humans; Male; Mice; Molecular Sequence Data; Organ Specificity; Ovary; Polymerase Chain Reaction; Recombinant Proteins; Saccharomyces cerevisiae; Sequence Alignment; Sequence Homology, Amino Acid; Substrate Specificity; Testis; Ubiquitins

Quantitation of mixed-base populations of HIV-1 variants by automated DNA sequencing with BODIPY dye-labeled primers. - Metzker, M L; Ansari-Lari, M A; Liu, X M; Holder, D J; Richard A Gibbs (Biotechniques, 1998)
Direct DNA sequencing of human immunodeficiency virus type 1 (HIV-1) pol and env gene regions was characterized for accuracy and precision. Restricted maximum likelihood (REML) analysis of molecular clone reconstruction experiments using a primer-walking strategy showed that the BODIPY and BODIPY energy-transfer (BET) dye primers sets were significantly more accurate in quantitating heterogenous base mixtures than the fluorescein/rhodamine dye primers. Of the three sets examined, the BET dye primers were the most accurate. The improved accuracy correlated with the reduced emission band-widths of BODIPY and BET dye primers and the more uniform signal intensities of BET dye primers. However, comparing % coefficients of variation (CV) for the three dye primer sets, revealed that BODIPY dye primers gave better precision than both BET and fluorescein/rhodamine dye primer sets. Several sequence-dependent motifs were identified that showed specific nucleotide-biased incorporation and were determined to be the major variable component of the total %CV. Taken together, these results show that BODIPY and BET direct DNA sequencing can accurately and precisely characterize complex mixed-base populations.
Keywords: Boron Compounds; DNA Primers; DNA, Viral; DNA-Directed DNA Polymerase; Genes, env; Genes, pol; Genetic Heterogeneity; Genetic Variation; Genome, Viral; HIV Envelope Protein gp120; HIV-1; Humans; Reproducibility of Results; Sequence Analysis, DNA

Reassessment of biochemically determined Hunter syndrome carrier status by DNA testing. - Timms, K M; Edwards, F J; Belmont, J W; Yates, J R; Gibbs, R A (J Med Genet, 1998)
Deficiency of iduronate-2-sulphatase (IDS) results in the X linked recessive lysosomal storage disorder Hunter syndrome. Determination of carrier status in families affected by this disorder has been performed using a variety of enzymatic tests. None of these tests has proved to be 100% effective at identifying carriers. The aim of this study was to perform carrier testing in a family affected by the disorder, where testing was complicated by the fact that no surviving affected subjects were available for study. Direct dye primer sequencing of PCR products was used to identify mixed bases in an obligate carrier. Two mixed bases were observed within exon VIII. The first base change (T-->A) at nucleotide position 1150 results in a missense mutation (H342Q), while the second base change (G-->T) at nucleotide position 1151 results in a nonsense mutation (G343X). Four additional female family members were screened for the same mutation. Using this approach it is possible to provide unambiguous information about a subject's carrier status and, unlike biochemical testing, this approach will be equally effective when applied to families with the mild form of this disorder.
Keywords: DNA; Female; Heterozygote; Humans; Iduronate Sulfatase; Male; Mucopolysaccharidosis II; Pedigree

Relationship of HIV testing and high-risk behaviors among clients in methadone maintenance treatment. - Grella, C E; Campos, M; Anglin, M D (AIDS Educ Prev, 1998)
This article reports on the association between frequency of HIV testing and high-risk behaviors among 339 individuals in the Los Angeles Enhanced Methadone Maintenance Project. Individuals who reported taking three or more HIV tests prior to entering treatment (45% of the sample) were more likely to know someone who was HIV positive, to engage in illegal activity, to perceive their risk for HIV as high, and to use condoms; they were less likely to disinfect injection equipment; and they scored higher on measures of HIV knowledge and depression as compared with less frequent testers. The strongest predictor of frequent HIV testing (three or more tests) after treatment entry, reported by 43% of the sample, was having a high number of injection-sharing partners. Although a substantial number of individuals in methadone maintenance treatment continued to take HIV tests, test taking was more strongly related to high-risk injection behavior than to sexual behavior.
Keywords: Adult; Data Interpretation, Statistical; Depression; Female; Heroin Dependence; HIV Infections; HIV Seropositivity; Humans; Logistic Models; Male; Methadone; Risk-Taking; Sexual Behavior; Substance Abuse, Intravenous

Using BODIPY dye-primer chemistry in large-scale sequencing. - Donna M Muzny; Metzker, M L; Bouck, J; Gorrell, J H; Ding, Y; Maxim, E; Richard A Gibbs (IEEE Eng Med Biol Mag, 1998)
Keywords: Boron Compounds; Chromosome Mapping; DNA Primers; Drug Storage; Fluorescent Dyes; Humans; Quality Control; Reproducibility of Results; Robotics; Sequence Analysis, DNA

WebWise: guide to the Baylor College of Medicine Human Genome Sequencing Center's web site. - Pruitt, K D (Genome Res, 1998)
Keywords: Computer Communication Networks; Databases, Factual; Human Genome Project; Humans; Online Systems; Sequence Analysis, DNA

Baboons as an animal model for genetic studies of common human disease. - Rogers, J; Hixson, J E (Am J Hum Genet, 1997)
Keywords: Animals; Arteriosclerosis; Chromosome Mapping; Disease Models, Animal; Genetic Diseases, Inborn; Humans; Models, Genetic; Osteoporosis; Papio

Beyond one gene-one disease: alternative strategies for deciphering genetic determinants of osteoporosis. - Rogers, J; Mahaney, M C; Beamer, W G; Donahue, L R; Rosen, C J (Calcif Tissue Int, 1997)
Keywords: Animals; Bone and Bones; Bone Density; Chromosome Mapping; Disease Models, Animal; Humans; Osteoporosis; Papio; Pedigree; Point Mutation; Risk Factors

Cloning and characterization of the region III flagellar operons of the four Shigella subgroups: genetic defects that cause loss of flagella of Shigella boydii and Shigella sonnei. - al Mamun, A A; Tominaga, A; Enomoto, M (J Bacteriol, 1997)
To detect genetic defects that might have caused loss of flagella in Shigella boydii and Shigella sonnei, the region III flagellar (fli) operons were cloned from certain strains and analyzed with reference to the restriction maps and genetic maps of Escherichia coli fli operons. S. boydii NCTC9733 (strain C5 in this paper) had the 988-bp internal deletion in the fliF gene that encodes a large substructural protein of the basal body. Two strains (C1 and C8) had deletions of the entire fliF operon, and the remaining three (C3, C4, and C9) differed in the size of the restriction fragments carrying the fliF and fliL operons. Loss of flagella in S. boydii appears to originate in some defect in the fliF operon. S. sonnei IID969 lacked the fliD gene and, in place of it, carried two IS600 elements as inverted repeats. Genes downstream from fliD were not detected in the cloned fragment despite its large size but did appear elsewhere in the chromosome. The fliD gene encodes a cap protein of the flagellar filament, and its deletion results in overexpression of class 3 operons by the increased amount of FliA (sigmaF) caused by the excess export of the anti-sigma factor FlgM. Three other strains also had the fliD deletion, and two of them had another deletion in the fliF-fliG-fliH region. The fliD deletion might be the primary cause of loss of flagella in S. sonnei. The lack of FliF or FliD in each subgroup is discussed in connection with the maintenance of virulence and bacterial growth. We also discuss the process of loss of flagella in relation to transposition of IS elements and alterations of the noncoding region, which were found to be common to at least three subgroups.
Keywords: Bacterial Proteins; Chromosome Mapping; Cloning, Molecular; DNA Transposable Elements; Escherichia coli Proteins; Flagella; Gene Deletion; Membrane Proteins; Molecular Sequence Data; Movement; Operon; Sequence Analysis, DNA; Shigella; Shigella boydii; Shigella sonnei

Growth factor-induced transcription of GluR1 increases functional AMPA receptor density in glial progenitor cells. - Chew, L J; Fleck, M W; Wright, P; Scherer, S E; Mayer, M L; Gallo, V (J Neurosci, 1997)
We analyzed the effects of two growth factors that regulate oligodendrocyte progenitor (O-2A) development on the expression of glutamate receptor (GluR) subunits in cortical O-2A cells. In the absence of growth factors, GluR1 was the AMPA subunit mRNA expressed at the lowest relative level. Basic fibroblast growth factor (bFGF) caused an increase in GluR1 and GluR3 steady-state mRNA levels. Platelet-derived growth factor (PDGF) did not modify the mRNA levels for any of the AMPA subunits but selectively potentiated the effects of bFGF on GluR1 mRNA (4.5-fold increase). The kainate-preferring subunits GluR7, KA1, and KA2 mRNAs were increased by bFGF, but these effects were not modified by cotreatment with PDGF. Nuclear run-on assays demonstrated that PDGF+bFGF selectively increased the rate of GluR1 gene transcription (2.5-fold over control). Western blot analysis showed that GluR1 protein levels were increased selectively (sixfold over control) by PDGF+bFGF. Functional expression was assessed by rapid application of AMPA to cultured cells. AMPA receptor current densities (pA/pF) were increased nearly fivefold in cells treated with PDGF+bFGF, as compared with untreated cells. Further, AMPA receptor channels in cells treated with PDGF+bFGF were more sensitive to voltage-dependent block by intracellular polyamines, as expected from the robust and selective enhancement of GluR1 expression. Our combined molecular and electrophysiological findings indicate that AMPA receptor function can be regulated by growth factor-induced changes in the rate of gene transcription.
Keywords: Animals; Cell Division; Drug Combinations; Fibroblast Growth Factor 2; Growth Substances; Neuroglia; Oligodendroglia; Platelet-Derived Growth Factor; Rats; Rats, Sprague-Dawley; Receptors, AMPA; Receptors, Glutamate; RNA, Messenger; Stem Cells; Time Factors; Transcription, Genetic

The Healthcare Administrator's Associate: an experiment in distributed healthcare information systems. - Fowler, J; Martin, G (Proc AMIA Annu Fall Symp, 1997)
The Healthcare Administrator's Associate is a collection of portable tools designed to support analysis of data retrieved via the Internet from diverse distributed healthcare information systems by means of the InfoSleuth system of distributed software agents. Development of these tools is part of an effort to enhance access to diverse and geographically distributed healthcare data in order to improve the basis upon which administrative and clinical decisions are made.
Keywords: Computer Communication Networks; Computer Systems; Decision Support Systems, Management; Delivery of Health Care; Hospital Information Systems; Management Information Systems; Software

Large-scale sequencing in human chromosome 12p13: experimental and computational gene structure determination. - Ansari-Lari, M A; Shen, Y; Donna M Muzny; Lee, W; Richard A Gibbs (Genome Res, 1997)
The detailed genomic organization of a gene-dense region at human chromosome 12p13, spanning 223 kb of contiguous sequence, was determined. This region is composed of 20 genes and several other expressed sequences. Experimental tools including RT-PCR and cDNA sequencing, combined with gene prediction programs, were utilized in the analysis of the sequence. Various computer software programs were employed for sequence similarity searches and functional predictions. The high number of genes with diverse functions and complex transcriptional patterns make this region ideal for addressing challenges of gene discovery and genomic characterization amenable to large-scale sequence analysis.
Keywords: Alternative Splicing; Amino Acid Sequence; Chromosome Mapping; Chromosomes, Human, Pair 12; Computational Biology; DNA, Complementary; Exons; Gene Expression; Genomic Library; Glycolysis; Humans; Introns; Molecular Sequence Data; Multigene Family; Nerve Tissue Proteins; Polymerase Chain Reaction; RNA-Directed DNA Polymerase; Sequence Analysis, DNA; Sequence Homology, Amino Acid; Signal Transduction; Software

Sequencing and functional analysis of the SNRPN promoter: in vitro methylation abolishes promoter activity. - Huq, A H; Sutcliffe, J S; Nakao, M; Shen, Y; Gibbs, R A; Beaudet, A L (Genome Res, 1997)
The gene encoding the small nuclear ribonucleoprotein-associated polypeptide N (SNRPN) maps to the Prader-Willi syndrome critical region on chromosome 15 and is expressed preferentially from the paternal allele. A CpG island encompassing the first exon of SNRPN is methylated on the inactive maternal allele. DNA sequence was determined for a cosmid containing the first three exons of SNRPN and extending 20 kb upstream and 15 kb downstream from the CpG island. This region is extremely rich in Alu elements and other repetitive sequences and contains a single CpG island, which includes numerous short direct repeat sequences. Functional analysis of the first exon revealed strong promoter activity for a 260-bp fragment extending 207 bp upstream from the exon. In vitro methylation of this 260-bp fragment abolished promoter activity completely, suggesting that the silencing of the maternal SNRPN allele may be a direct consequence of methylation of the promoter region.
Keywords: Alleles; Autoantigens; Cells, Cultured; Chromosomes, Human, Pair 15; Cloning, Molecular; CpG Islands; DNA Methylation; DNA-Cytosine Methylases; Exons; Gene Expression; HeLa Cells; Humans; Methylation; Molecular Sequence Data; Polymerase Chain Reaction; Prader-Willi Syndrome; Promoter Regions, Genetic; Repetitive Sequences, Nucleic Acid; Ribonucleoproteins, Small Nuclear; Sequence Analysis, DNA; snRNP Core Proteins; Transfection

Simian T-lymphotropic virus type 1 (STLV-1) infection in wild yellow baboons (Papio hamadryas cynocephalus) from Mikumi National Park, Tanzania. - Voevodin, A; Samilchuk, E; Allan, J; Rogers, J; Broussard, S (Virology, 1997)
Serum and peripheral blood leukocytes from wild yellow baboons (Papio hamadryas cynocephalus) were tested for the presence of STLV-1-specific antibodies and proviral DNA. Fourteen of 30 sera tested positive by radioimmunoprecipitation assay (RIPA) with HTLV-1. Among 36 DNA samples tested by PCR 15 were positive by double nested PCR for a fragment of the STLV-1 env gene, the most sensitive assay among PCR tests employed. Of 30 animals that were tested both serologically and by PCR in only 1 case were the results discordant (PCR-positive, antibody-negative). The DNA sequences from env (378 bp), pol (212 bp), and LTR (705 bp) were determined for 5, 5, and 2 Mikumi STLV-1 isolates, respectively. The DNA sequences of Mikumi STLV-1 isolates were virtually identical and phylogenetic analysis revealed that they were clearly distinct from previously published baboon STLV-1 sequences, including those STLV-1 isolates presumed to be from yellow baboons. The results of this study suggest that reliable placement of individual STLV-1 within the PTLV-1 phylogeny requires genomic sequences of STLV-1 isolates from wild animals whose taxonomic identity and geographical origin are firmly established and that the LTR is the genomic region of STLV-1 which is the most informative for cladistic analysis of these viruses.
Keywords: Animals; Base Sequence; Deltaretrovirus Antibodies; Deltaretrovirus Infections; DNA, Viral; Gene Products, env; Gene Products, pol; Genome, Viral; Humans; Molecular Sequence Data; Monkey Diseases; Papio; Phylogeny; Polymerase Chain Reaction; Repetitive Sequences, Nucleic Acid; Sequence Homology, Nucleic Acid; Simian T-lymphotropic virus 1; Tanzania; Tumor Cells, Cultured

Simultaneous shotgun sequencing of multiple cDNA clones. - Andersson, B; Lu, J; Shen, Y; Wentland, M A; Richard A Gibbs (DNA Seq, 1997)
This study describes an efficient method for the rapid sequencing of DNA fragments in the size range 1-5 kb. Individual fragments, here cDNA inserts, are purified by restriction enzyme digestion and gel purification, pooled and concatenated by ligation. The concatamers are sheared and cloned randomly into M13, followed by random sequencing. The sequences of the individual cDNA inserts are obtained at the assembly stage using restriction enzyme sites as "tags' for the ends of each fragment. In this study the sequencing of two libraries containing 7 and 16 cDNA inserts with an average length of 2.5 kb is described. The results show that of the shotgun sequencing of large fragments, and that the method compares favorably to alternative strategies, such as primer walking.
Keywords: Animals; Cloning, Molecular; DNA, Complementary; Drosophila; Gene Expression; Gene Library; Restriction Mapping; Sequence Analysis, DNA

Test of the potential of a dATP surrogate for sequencing via MALDI-MS. - Jacutin, S; Zhang, A J; Russell, D H; Gibbs, R A; Burgess, K (Nucleic Acids Res, 1997)
1-(2'-Deoxy-beta-d-ribofuranosyl)-3-nitropyrrole phosphate was incorporated into a DNA decamer and analyzed via matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS). The extent and composition of the various fragment peaks were compared with those in the MALDI-MS spectrum of dT4AT5. The nitropyrrole-containing oligomer proved to be more robust. Two different DNA template assays were then used to attempt to identify DNA replicating enzymes that would incorporate the corresponding triphosphate, i.e. 1-(2'-deoxy-beta-d-ribofuranosyl)-3-nitropyrrole triphosphate (dXTP). It was shown that dXTP was not incorporated by some enzymes and it inhibited others. However, DNA polymerase I Klenow fragment and avian myeloblastosis virus reverse transcriptase incorporated dXTP in place of dATP and then replicated the template overhang in the usual way. The potential of dXTP as a surrogate for dATP in DNA sequencing with MALDI-MS analysis is discussed.
Keywords: Deoxyadenine Nucleotides; DNA Polymerase I; DNA-Directed DNA Polymerase; Mass Spectrometry; Nucleotides; Pyrroles; Retroviridae; RNA-Directed DNA Polymerase; Sequence Analysis, DNA; Substrate Specificity; Taq Polymerase; Templates, Genetic

BCM Search Launcher--an integrated interface to molecular biology data base search and analysis services available on the World Wide Web. - Smith, R F; Wiese, B A; Wojzynski, M K; Davison, D B; Kim C Worley (Genome Res, 1996)
The BCM Search Launcher is an integrated set of World Wide Web (WWW) pages that organize molecular biology-related search and analysis services available on the WWW by function, and provide a single point of entry for related searches. The Protein Sequence Search Page, for example, provides a single sequence entry form for submitting sequences to WWW servers that offer remote access to a variety of different protein sequence search tools, including BLAST, FASTA, Smith-Waterman, BEAUTY, PROSITE, and BLOCKS searches. Other Launch pages provide access to (1) nucleic acid sequence searches, (2) multiple and pair-wise sequence alignments, (3) gene feature searches, (4) protein secondary structure prediction, and (5) miscellaneous sequence utilities (e.g., six-frame translation). The BCM Search Launcher also provides a mechanism to extend the utility of other WWW services by adding supplementary hypertext links to results returned by remote servers. For example, links to the NCBI's Entrez data base and to the Sequence Retrieval System (SRS) are added to search results returned by the NCBI's WWW BLAST server. These links provide easy access to auxiliary information, such as Medline abstracts, that can be extremely helpful when analyzing BLAST data base hits. For new or infrequent users of sequence data base search tools, we have preset the default search parameters to provide the most informative first-pass sequence analysis possible. We have also developed a batch client interface for Unix and Macintosh computers that allows multiple input sequences to be searched automatically as a background task, with the results returned as individual HTML documents directly to the user's system. The BCM Search Launcher and batch client are available on the WWW at URL http:@gc.bcm.tmc.edu:8088/search-launcher.html.
Keywords: Animals; Computer Communication Networks; Database Management Systems; Databases, Factual; Humans; Molecular Biology

A comparative transcription map of the murine bare patches (Bpa) and striated (Str) critical regions and human Xq28. - Levin, M L; Chatterjee, A; Pragliola, A; Kim C Worley; Wehnert, M; Zhuchenko, O; Smith, R F; Lee, C C; Herman, G E (Genome Res, 1996)
The X-linked developmental mouse mutations bare patches (Bpa) and striated (Str) may be homologous to human X-linked dominant chondrodysplasia punctata (CDPX2) and incontinentia pigmenti (IP2), respectively, based on their genetic mapping and clinical phenotypes. Bpa and Str have been localized to an overlapping critical region of 600 kb that demonstrates conserved gene order with loci in human Xq28 between DXS1104 and DXS52. As part of efforts to isolate the genes involved in these disorders, we have begun to develop a comparative transcription map spanning this region in both species. Using techniques of cross-species conservation and hybridization, exon trapping, and cDNA selection we have identified four known genes or members of gene families--caltractin, a member of the gamma-aminobutyric acid (GABAA) receptor gene family, a member of the melanoma antigen gene (MAGE) family, and several members of the murine-specific, X-linked lymphocyte regulated gene (Xlr3) family. Trapped exons and, in some cases, longer cDNAs have been isolated for potentially 7-9 additional genes. One cDNA demonstrates highly significant homology with members of the Krüppel family of zinc finger transcription factors. A second novel cDNA demonstrates homology at the 3' end of the predicted amino acid sequence to a LIM domain consensus. Gene order appears conserved among those cDNAs determined to be present in both human and mouse. Three of the murine transcripts appear to be present in multiple copies within the Bpa/Str critical region and could be associated with a predisposition to genomic rearrangements. Reverse transcriptase PCR (RT-PCR) and Northern analysis demonstrate that several of the transcripts are expressed in mid-gestation murine embryos and neonatal skin, making them candidates for the Bpa and Str mutations and their respective homologous human disorders.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Blotting, Northern; Blotting, Southern; Chondrodysplasia Punctata; Chromosome Mapping; Cloning, Molecular; DNA, Complementary; Exons; Genetic Markers; Humans; Incontinentia Pigmenti; Mice; Molecular Sequence Data; Restriction Mapping; Sequence Analysis; Sequence Homology, Amino Acid; X Chromosome; Zinc Fingers

Detection and characterization of the flagellar master operon in the four Shigella subgroups. - al Mamun, A A; Tominaga, A; Enomoto, M (J Bacteriol, 1996)
Strains in the genus Shigella are nonmotile, but they retain some cryptic flagellar operons whether functional or defective (A.Tominaga, M. A.-H. Mahmoud, T. Mukaihara, and M. Enomoto, Mol. Microbiol. 12:277-285, 1994). To disclose the cause of motility loss in shigellae, the presence or defectiveness of the flhD and flhC genes, composing the master operon whose mutation causes inactivation of the entire flagellar regulon, was examined in the four Shigella subgroups. The flhD operon cloned from Shigella boydii and Shigella sonnei can activate, though insufficiently, the regulon in the Escherichia coli flhD or flhC mutant background. The clone from Shigella dysenteriae has a functional flhD gene and nonfunctional flhC gene, and its inactivation has been caused by the IS1 element inserted in its 5' end. The operon of Shigella flexneri is nonfunctional and has suffered an IS1-insertion mutation at the 5' end of the flhD gene. Comparison of restriction maps indicates that only the central 1.8-kb region, including part of the flhC gene and its adjacent mot operon, is conserved among the four Shigella subgroups as well as in E. coli, but in Salmonella typhimurium the whole map is quite different from the others. Motility loss in shigellae is not attributable to genetic damage in the master operon of a common ancestor, but it occurs separately in respective ancestors of the four subgroups, and in both S. dysenteriae and S.flexneri IS1 insertion in the master operon might be the primary cause of motility loss.
Keywords: Chromosome Mapping; Cloning, Molecular; DNA-Binding Proteins; Escherichia coli Proteins; Flagella; Mutagenesis, Insertional; Operon; Shigella; Shigella boydii; Shigella dysenteriae; Shigella flexneri; Shigella sonnei; Trans-Activators

Development of a faculty research interest resource. - Fowler, J; Wheeler, D A; Camerino, P W; Bat, O; Burch, P E (Proc AMIA Annu Fall Symp, 1996)
We have developed a faculty research interests resource by "mining" MEDLINE for relationships that are not directly queryable through the normal MEDLINE schema. Faculty citations are retrieved and World-Wide Web pages built to interconnect authors, their citations, and the MeSH terms that have been assigned to these citations. The design and development of the resource are discussed and examples of the results illustrated.
Keywords: Databases, Factual; Faculty, Medical; Hypermedia; MEDLINE; Publishing; Research; Subject Headings

Electrophoretically uniform fluorescent dyes for automated DNA sequencing. - Metzker, M L; Lu, J; Richard A Gibbs (Science, 1996)
A class of dyes, BODIPY fluorophores, has been identified for automated DNA sequencing that has improved spectral characteristics compared with conventional fluorescein and rhodamine dyes. Single and double BODIPY dye primers were characterized in commercially available DNA sequencers and showed uniform electrophoretic mobilities and high fluorescence intensities. The improved physical properties of BODIPY dye primers were demonstrated by direct base-calling from the unprocessed fluorescent signals and improved heterozygote analyses of mixed-base populations. The high sensitivity of BODIPY dye primers requires at least 33 percent less reagent consumed per reaction than conventional dye primers, which should affect the costs of large genome-sequencing efforts.
Keywords: Autoanalysis; Base Sequence; Boron Compounds; DNA Primers; Electrophoresis, Polyacrylamide Gel; Fluorescent Dyes; Molecular Sequence Data; Sensitivity and Specificity; Sequence Analysis, DNA; Spectrometry, Fluorescence

A gene-rich cluster between the CD4 and triosephosphate isomerase genes at human chromosome 12p13. - Ansari-Lari, M A; Donna M Muzny; Lu, J; Lu, F; Lilley, C E; Spanos, S; Malley, T; Richard A Gibbs (Genome Res, 1996)
The genomic sequence of the human CD4 gene and its neighboring region, located at chromosome 12p13, was generated using the large-scale shotgun sequencing strategy. A total of 117 kb of genomic sequence and approximately 11 kb of cDNA sequence were obtained. Six genes, including CD4, triosephosphate isomerase, B3 subunit of G proteins (GNB3), and ubiquitin isopeptidase T (ISOT), with known functions, and two new genes with unknown functions were identified. Using a battery of strategies, the exon/intron boundaries, splice variants, and tissue expression patterns of the genes were determined. Various computer software was utilized for analyses of the DNA and amino acid sequences. The results of the analyses and sequence-based strategies for gene identification are discussed.
Keywords: Alternative Splicing; Amino Acid Sequence; Base Sequence; CD4 Antigens; Chromosome Mapping; Chromosomes, Human, Pair 12; DNA, Complementary; Humans; Molecular Sequence Data; Multigene Family; Sequence Homology, Amino Acid; Triose-Phosphate Isomerase

Identification of FMR2, a novel gene associated with the FRAXE CCG repeat and CpG island. - Gu, Y; Shen, Y; Richard A Gibbs; Nelson, D L (Nat Genet, 1996)
Five folate-sensitive fragile sites have been identified at the molecular level to date. Each is characterized by an expanded and methylated trinucleotide repeat CGG (CCG). Of the three X chromosome sites, FRAXA, FRAXE and FRAXF, the former two are associated with mental retardation in their expanded forms. FRAXA expansion results in fragile X syndrome due to down regulation of expression of the FMR1 gene, which carries the hypermutable CGG repeat in the 5' untranslated portion of its first exon. Mild mental retardation without consistent physical findings has been found associated with expanded CCG repeats at FRAXE. We have identified a large gene (FMR2) transcribed distally from the CpG island at FRAXE, and down-regulated by repeat expansion and methylation. The gene is novel, expressed in adult brain and placenta, and shows similarity with another human protein, MLLT2, expressed from a gene at chromosome 4q21 involved in translocations found in acute lymphoblastic leukaemia (ALL) cells. Identification of this gene will facilitate further studies to determine the role of its product in FRAXE associated mental deficiency.
Keywords: Adult; Amino Acid Sequence; Base Sequence; Brain; Chromosomes, Human, Pair 4; Cloning, Molecular; Dinucleoside Phosphates; DNA Primers; Female; Fragile X Syndrome; Gene Expression; Humans; Intellectual Disability; Molecular Sequence Data; Nuclear Proteins; Organ Specificity; Placenta; Polymerase Chain Reaction; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Pregnancy; Protein Biosynthesis; Proteins; Repetitive Sequences, Nucleic Acid; RNA, Messenger; Sequence Homology, Amino Acid; Trans-Activators; Transcription, Genetic; X Chromosome

Improved ligation-anchored PCR strategy for identification of 5' ends of transcripts. - Ansari-Lari, M A; Jones, S N; Timms, K M; Richard A Gibbs (Biotechniques, 1996)
Keywords: Alternative Splicing; Animals; Bacteriophage T4; Biotin; DNA Primers; DNA, Complementary; Exons; Humans; Mice; Nuclear Proteins; Polymerase Chain Reaction; Proto-Oncogene Proteins; Proto-Oncogene Proteins c-mdm2; RNA Ligase (ATP); RNA, Messenger; Thiolester Hydrolases; Ubiquitin Thiolesterase

Method for 96-well M13 DNA template preparations for large-scale sequencing. - Andersson, B; Lu, J; Edwards, K E; Donna M Muzny; Richard A Gibbs (Biotechniques, 1996)
Efficient preparation of DNA templates is an important step in large-scale DNA sequencing. The ensure high-quality sequence data, we have prepared M13 phage DNA templates using a glass fiber-filtration method. We present the adaptation of this protocol to a 96-well format using commercially available filter plates. Two variations are described: one using polyethylene glycol precipitation and a second where the phage particles are disrupted before filtration, thus eliminating the need for precipitation. Using either of these protocols, 96 templates can be prepared in less than 2 h. Sufficient DNA for 1-2 dye primer sequencing reactions is routinely obtained from 1 mL of culture, and the resulting sequence data are of high quality.
Keywords: Bacteriophage M13; DNA, Viral; Genetic Vectors; Polyethylene Glycols; Polymerase Chain Reaction; Sequence Analysis, DNA; Templates, Genetic

Potential salmon sperm origin of the E3 region insert of the adenovirus 5 dl309 mutant. - Marie-Claude Gingras; Arevalo, P; Aguilar-Cordova, E (Cancer Gene Ther, 1996)
The plasmid pJM17 is a commonly used adenoviral backbone derived from the dl309 mutant virus. It contains unknown sequences inserted in the E3 region during construction of the dl309 mutant. Complete description of the backbone sequence is required for interpretation of potential vector effects and for regulatory approval of a vector to be used in clinical trials. The anonymous E3 insert was sequenced and analyzed. The insert fragment is 646 base pairs (bp) long and is 100 bp shorter than the vector sequences it replaces. It interrupts the expression of the E3B 10.4K, 14.6K, and 14.7K genes, but not the E3A glycoprotein (gp) 19K gene. Sequence analysis and Southern blotting suggest that the insert might originate from salmon sperm DNA used as carrier during the construction of dl309. Transcription from the insert was not detected by Northern blot analysis of vector-transduced cells but was detected by reverse transcriptase polymerase chain reaction.
Keywords: Adenovirus E3 Proteins; Adenoviruses, Human; Animals; Avian Sarcoma Viruses; Base Sequence; DNA; DNA Primers; Genetic Vectors; HeLa Cells; Humans; Male; Molecular Sequence Data; Plasmids; Polymerase Chain Reaction; Prolactin; Proton-Translocating ATPases; Repetitive Sequences, Nucleic Acid; Salmon; Sequence Homology, Nucleic Acid; Spermatozoa; Thymidine Kinase; Transfection

A recombination hotspot responsible for two inherited peripheral neuropathies is located near a mariner transposon-like element. - Reiter, L T; Murakami, T; Koeuth, T; Pentao, L; Donna M Muzny; Richard A Gibbs; James R Lupski (Nat Genet, 1996)
The Charcot-Marie Tooth disease type 1A (CMT1A) duplication and hereditary neuropathy with liability to pressure palsies (HNPP) deletion are reciprocal products of an unequal crossing-over event between misaligned flanking CMT1A-REP repeats. The molecular aetiology of this apparently homologous recombination event was examined by sequencing the crossover region. Through the detection of novel junction fragments from the recombinant CMT1A-REPs in both CMT1A and HNPP patients, a 1.7-kb recombination hotspot within the approximately 30-kb CMT1A-REPs was identified. This hotspot is 98% identical between CMT1A-REPs indicating that sequence identity is not likely the sole factor involved in promoting crossover events. Sequence analysis revealed a mariner transposon-like element (MITE) near the hotspot which we hypothesize could mediate strand exchange events via cleavage by a transposase at or near the 3' end of the element.
Keywords: Amino Acid Sequence; Base Sequence; Charcot-Marie-Tooth Disease; DNA; DNA Transposable Elements; Gene Deletion; Humans; Molecular Sequence Data; Multigene Family; Peripheral Nervous System Diseases; Recombination, Genetic; Repetitive Sequences, Nucleic Acid; Restriction Mapping; Sequence Homology, Amino Acid

Accurate determination of DNA in agarose gels using the novel algorithm GelScann(1.0). - Metzker, M L; Allain, K M; Richard A Gibbs (Comput Appl Biosci, 1995)
GelScann(1.0) is a user-friendly program that accurately quantitates DNA from CCD imaged agarose gels. The algorithm automatically locates lanes, locates bands within a given lane, and quantitates the intensity of each band. GelScann (1.0) uses a statistical method to discriminate DNA from local background fluorescence. The sensitivity of the LaneFinder and BandFinder can be adjusted by the user interacting with GelScann (1.0)'s option box. We demonstrate that GelScann(1.0) can accurately determine DNA that GelScann(1.0) can accurately determine DNA concentrations for routine molecular biology applications and determine the relative intensities of PCR amplified fragments for genetic testing.
Keywords: Algorithms; Bacteriophage M13; DNA, Viral; Electrophoresis, Agar Gel; Female; Genetic Carrier Screening; HIV Infections; HIV-1; Humans; Image Processing, Computer-Assisted; Microcomputers; Muscular Dystrophies; Polymerase Chain Reaction

Analysis of human immunodeficiency virus type 1 integrase mutants. - Ansari-Lari, M A; Donehower, L A; Richard A Gibbs (Virology, 1995)
The human immunodeficiency virus type-1 (HIV-1) integrase protein (IN) mediates the insertion of linear double-stranded viral DNA into the host genome. Mutations in IN can have different effects on the virus life cycle. In this study, Gag-Pol polyprotein processing, Tat synthesis, and viral replication were investigated in integrase-defective HIV-1 mutants. In the absence of IN synthesis, the Gag-Pol polyprotein stability, packaging, and/or processing was reduced. There was limited expression of Tat observed in IN mutants, but no viral replication.
Keywords: Base Sequence; Blotting, Western; Cell Line; Defective Viruses; DNA Nucleotidyltransferases; DNA Primers; Gene Products, gag; Gene Products, pol; Genome, Viral; HIV Reverse Transcriptase; HIV-1; Humans; Integrases; Molecular Sequence Data; Point Mutation; Polymerase Chain Reaction; RNA-Directed DNA Polymerase; Transfection; Viral Proteins

The architecture of a distributed medical dictionary. - Fowler, J; Buffone, G; Moreau, D (Medinfo, 1995)
Exploiting high-speed computer networks to provide a national medical information infrastructure is a goal for medical informatics. The Distributed Medical Dictionary under development at Baylor College of Medicine is a model for an architecture that supports collaborative development of a distributed online medical terminology knowledge-base. A prototype is described that illustrates the concept. Issues that must be addressed by such a system include high availability, acceptable response time, support for local idiom, and control of vocabulary.
Keywords: Artificial Intelligence; Dictionaries, Medical as Topic; Terminology as Topic; Unified Medical Language System

BEAUTY: an enhanced BLAST-based search tool that integrates multiple biological information resources into sequence similarity search results. - Worley, K C; Wiese, B A; Smith, R F (Genome Res, 1995)
BEAUTY (BLAST enhanced alignment utility) is an enhanced version of the NCBI's BLAST data base search tool that facilitates identification of the functions of matched sequences. We have created new data bases of conserved regions and functional domains for protein sequences in NCBI's Entrez data base, and BEAUTY allows this information to be incorporated directly into BLAST search results. A Conserved Regions Data Base, containing the locations of conserved regions within Entrez protein sequences, was constructed by (1) clustering the entire data base into families, (2) aligning each family using our PIMA multiple sequence alignment program, and (3) scanning the multiple alignments to locate the conserved regions within each aligned sequence. A separate Annotated Domains Data Base was constructed by extracting the locations of all annotated domains and sites from sequences represented in the Entrez, PROSITE, BLOCKS, and PRINTS data bases. BEAUTY performs a BLAST search of those Entrez sequences with conserved regions and/or annotated domains. BEAUTY then uses the information from the Conserved Regions and Annotated Domains data bases to generate, for each matched sequence, a schematic display that allows one to directly compare the relative locations of (1) the conserved regions, (2) annotated domains and sites, and (3) the locally aligned regions matched in the BLAST search. In addition, BEAUTY search results include World-Wide Web hypertext links to a number of external data bases that provide a variety of additional types of information on the function of matched sequences. This convenient integration of protein families, conserved regions, annotated domains, alignment displays, and World-Wide Web resources greatly enhances the biological informativeness of sequence similarity searches. BEAUTY searches can be performed remotely on our system using the "BCM Search Launcher" World-Wide Web pages (URL is < http:/ /gc.bcm.tmc.edu:8088/ search-launcher/launcher.html > ).
Keywords: Amino Acid Sequence; Computer Communication Networks; Databases, Factual; Information Storage and Retrieval; Molecular Sequence Data; Sequence Alignment; Software

Complete sequence of a 38.4-kb human cosmid insert containing the polymorphic marker DXS455 from Xq28. - Andersson, B; Lu, F; Donna M Muzny; Warren, S T; Richard A Gibbs (DNA Seq, 1995)
The complete DNA sequence of a cosmid mapping to human Xq28 (DXS455) has been determined using a shotgun approach (genbank accession number: L31948). The cosmid insert is 38.4 kb in length, and contains several repetitive sequences, including a highly repetitive region located in a fragment previously shown to contain a polymorphic VNTR locus, as well as short di- and tri-nucleotide repeats. In addition to the previously known VNTR locus, a CA-repeat and an unusual 800-bp repetitive region have been found to be polymorphic. The repeated sequence mapping to the site of the VNTR locus spans 480 bp in the cosmid. In addition to several AT-dinucleotide stretches, this repeat has four copies of a 25 bp repeat unit and flanking sequences similar to this 25-mer. No expressed sequences have so far been identified in this cosmid.
Keywords: Bacteriophage M13; Base Sequence; Cosmids; DNA; Gene Library; Genetic Markers; Humans; Minisatellite Repeats; Molecular Sequence Data; Repetitive Sequences, Nucleic Acid; X Chromosome

Detection and genetic analysis of beta-thalassemia mutations by competitive oligopriming. - Athanassiadou, A; Papachatzopoulou, A; Richard A Gibbs (Hum Mutat, 1995)
A new approach for the detection of beta-thalassemia mutations has been applied, based on competitive oligonucleotide priming (COP) of in vitro DNA amplification at the mutation site. This method allows genotyping of the template DNA, through differential labeling of the allele-specific competitive oligoprimers and biotinylation of the common reverse primer. The system provides a basis for rapid, simple, and reliable detection of the numerous known beta-thalassemia mutations, revealing the precise nature of the mismatch in each case, and thereby facilitating the molecular genetic analysis of the disease.
Keywords: Base Sequence; beta-Thalassemia; DNA; DNA Mutational Analysis; DNA Primers; Globins; Humans; Molecular Sequence Data; Oligodeoxyribonucleotides

Identification of new members of a carbohydrate kinase-encoding gene family. - Kim C Worley; King, K Y; Chua, S; McCabe, E R; Smith, R F (J Comput Biol, 1995)
In a sequence database search using the human glycerol kinase-encoding sequence (HUMGLYKINB) as a query, we identified six previously unidentified carbohydrate kinase sequences. Five of the six newly identified sequences appear to be known types of carbohydrate kinases, four are glycerol kinases and one is a gluconokinase. The sixth newly identified sequence, the Caenorhabditis elegans gene, CER08D7.7-CEF59B2.1, shows similarity to the family of carbohydrate kinases including other glycerol kinases, xylulokinases, gluconokinases, ribulokinases, rhamnulokinases, and fucokinases. A phylogenetic comparison of this newly identified Caenorhabditis elegans gene with the other members of the carbohydrate kinase family demonstrated that this sequence cannot be assigned to one of the known classes of carbohydrate kinases.
Keywords: Amino Acid Sequence; Animals; Caenorhabditis elegans; Carbohydrates; Conserved Sequence; Databases, Factual; Genes, Helminth; Glucokinase; Glycerol Kinase; Humans; Molecular Sequence Data; Multigene Family; Phosphotransferases (Alcohol Group Acceptor); Phylogeny; Sequence Alignment; Sequence Homology, Amino Acid; Software

Pressing ahead with human genome sequencing. - Richard A Gibbs (Nat Genet, 1995)
While waiting for revolutionary techniques to emerge, conventional approaches have been used to generate more than 40 million bases of DNA sequence from large scale projects involving different organisms. About eight megabases are from the human genome. Does this progress signal the time to move ahead for a massive human genomic sequencing effort, or should we bide our time, waiting for more technical developments? The answer is to move ahead now, choosing carefully those strategies that can be easily adapted to future methodologies.
Keywords: Animals; Base Sequence; Caenorhabditis; DNA; Genome, Fungal; Genome, Human; Human Genome Project; Humans; Molecular Sequence Data; Saccharomyces cerevisiae

When is ancient polymorphism a potential problem for molecular phylogenetics? - Rogers, J; Comuzzie, A G (Am J Phys Anthropol, 1995)
Keywords: Animals; Biological Evolution; DNA; DNA, Mitochondrial; Humans; Molecular Biology; Phylogeny; Polymorphism, Genetic; Primates; Sequence Homology, Nucleic Acid; Species Specificity

Working on the assembly line. - Richard A Gibbs; Cockerill, M (Trends Biochem Sci, 1995)
Keywords: Base Sequence; DNA; Molecular Sequence Data; Sequence Analysis, DNA; Software

Adaptor-based uracil DNA glycosylase cloning simplifies shotgun library construction for large-scale sequencing. - Andersson, B; Povinelli, C M; Wentland, M A; Shen, Y; Donna M Muzny; Richard A Gibbs (Anal Biochem, 1994)
An improved strategy for the preparation of libraries for the random sequencing of DNA is reported. The protocol is a modification of a previous adaptor-based strategy, and utilizes long (11 base) overhangs, which eliminates the unreliable step of vector-insert ligation. The random inserts are prepared by adaptor ligation, while the M13 vector is prepared as described for uracil DNA glycosylase (UDG) cloning of polymerase chain reaction (PCR) products, using PCR with uracil-containing primers, followed by UDG treatment to produce overhangs. This method has been found to reliably yield large numbers of clones. There is no background due to religation of the vector, and all clones contain inserts. In addition, the method is simple and suitable for export to other investigators. Libraries were constructed from cosmids containing human DNA and from human cDNAs in order to characterize a strategy for shotgun sequencing of multiple shorter fragments.
Keywords: Base Sequence; Cloning, Molecular; DNA Glycosylases; DNA Primers; DNA, Complementary; Genomic Library; Humans; Molecular Sequence Data; N-Glycosyl Hydrolases; Polymerase Chain Reaction; Sequence Analysis, DNA; Uracil-DNA Glycosidase

Analysis of HIV type 1 reverse transcriptase expression in a human cell line. - Ansari-Lari, M A; Richard A Gibbs (AIDS Res Hum Retroviruses, 1994)
The functional analysis of human immunodeficiency virus type-1 (HIV-1) reverse transcriptase (RT) subunits on transient and constitutive expression, in the absence or presence of the HIV-1 protease (PR) expression, in a human cell line is described. HIV-1 RT is a heterodimer composed of a 51-kDa subunit (p51) and a 66-kDa subunit (p66). Cloning and expression of the RT region of the HIV-1 pol gene in the HT-1080 human fibrosarcoma cell line yielded p66 without any detectable p51 and a low level of RT activity could be measured. Transient expression of PR and RT in cis generated p51 and p66, but when RT and PR were expressed in trans only p66 was produced. Attempts to establish a stable cell line expressing the PR-RT region of the pol gene were hampered by an apparent intolerance of HT-1080 cells to the HIV-1 PR expression. Therefore, to generate p51 independent of PR expression, the 51-kDa subunit was cloned separately. p51 lacked detectable RT activity. Coexpression of p51 and p66 resulted in a dramatic increase in RT activity. Stable HT-1080 cells producing both p51 and p66 exhibited on average a 15-fold increase in RT activity compared to the parental cell line. Immunofluorescence revealed a diffuse cytoplasmic localization of p51 and p66. To date, this is the first example of a human cell line that is constitutively expressing HIV-1 RT in the absence of HIV-1 infection.
Keywords: Base Sequence; Cell Line; Cloning, Molecular; DNA Primers; Fibrosarcoma; Fluorescent Antibody Technique; Genes, pol; HIV Protease; HIV Reverse Transcriptase; HIV-1; Humans; Macromolecular Substances; Molecular Sequence Data; Molecular Weight; Polymerase Chain Reaction; Recombinant Proteins; Restriction Mapping; RNA-Directed DNA Polymerase; Transfection; Tumor Cells, Cultured

A dosage sensitive locus at chromosome Xp21 is involved in male to female sex reversal. - Bardoni, B; Zanaria, E; Guioli, S; Floridia, G; Kim C Worley; Tonini, G; Ferrante, E; Chiumello, G; McCabe, E R; Fraccaro, M (Nat Genet, 1994)
Male to female sex reversal has been observed in individuals with duplications of the short arm of the X chromosome. Here we demonstrate that sex reversal results from the presence of two active copies of an Xp locus rather than from its rearrangement and that alterations at this locus constitute one of the causes of sex reversal in individuals with a normal 46,XY karyotype. We have named this locus DSS (Dosage Sensitive Sex reversal) and localized it to a 160 kilobase region of chromosome Xp21, adjacent to the adrenal hypoplasia congenita locus. The identification of male individuals deleted for DSS suggests that this locus is not required for testis differentiation. We propose that DSS has a role in ovarian development and/or functions as a link between ovary and testis formation.
Keywords: Chromosome Mapping; Dosage Compensation, Genetic; Female; Gene Deletion; Genetic Markers; Humans; Male; Multigene Family; Ovary; Phenotype; Sex Differentiation; Testis; X Chromosome

Expression of the platelet-derived growth factor beta receptor during organogenesis and tissue differentiation in the mouse embryo. - Shinbrot, E; Peters, K G; Williams, L T (Dev Dyn, 1994)
In this study we used in situ hybridization to localize expression of the platelet-derived growth factor beta (PDGF beta) receptor mRNA during organogenesis in the mouse embryo (E 9.5-16.5). Expression was first seen in periaortic mesenchyme (E 9.5-10.5). Later (E 12.5-E 16.5), the receptor was expressed in the mesenchymal component of many developing tissues and organs, particularly derivatives of the primitive gut. The expression was exceptionally high in mesenchyme directly supporting an epithelium, typical of many developing organs such as the trachea and intestine. However, as the mesenchyme differentiated into smooth muscle, PDGF beta receptor mRNA was no longer detected. The expression of the PDGF beta receptor mRNA in mesenchymal components of developing organs, along with its absence in epithelial tissues, indicates that it may play a role in mesenchymal-epithelial interactions during organ development. Somewhat unexpectedly, the PDGF beta receptor was highly expressed in the endothelium of small blood vessels and vascular structures such as the hyaloid plexus and choroid plexus. In large blood vessels, PDGF beta receptor mRNA was found in the mesenchyme surrounding the endothelium. This suggests that the PDGF beta receptor is involved in growth and development of blood vessels.
Keywords: Animals; Blood Vessels; Bone and Bones; Bone Development; Cell Differentiation; DNA; Embryo, Mammalian; Embryonic and Fetal Development; Immunohistochemistry; In Situ Hybridization; Mesoderm; Mice; Myocardium; Receptors, Platelet-Derived Growth Factor; RNA, Messenger

Infection of a yellow baboon with simian immunodeficiency virus from African green monkeys: evidence for cross-species transmission in the wild. - Jin, M J; Rogers, J; Phillips-Conroy, J E; Allan, J S; Desrosiers, R C; Shaw, G M; Sharp, P M; Hahn, B H (J Virol, 1994)
Many African primates are known to be naturally infected with simian immunodeficiency viruses (SIVs), but only a fraction of these viruses has been molecularly characterized. One primate species for which only serological evidence of SIV infection has been reported is the yellow baboon (Papio hamadryas cynocephalus). Two wild-living baboons with strong SIVAGM seroreactivity were previously identified in a Tanzanian national park where baboons and African green monkeys shared the same habitat (T. Kodama, D. P. Silva, M. D. Daniel, J. E. Phillips-Conroy, C. J. Jolly, J. Rogers, and R. C. Desrosiers, AIDS Res. Hum. Retroviruses 5:337-343, 1989). To determine the genetic identity of the viruses infecting these animals, we used PCR to examine SIV sequences directly in uncultured leukocyte DNA. Targeting two different, nonoverlapping genomic regions, we amplified and sequenced a 673-bp gag gene fragment and a 908-bp env gene fragment from one of the two baboons. Phylo-genetic analyses revealed that this baboon was infected with an SIVAGM strain of the vervet subtype. These results provide the first direct evidence for simian-to-simian cross-species transmission of SIV in the wild.
Keywords: Amino Acid Sequence; Animals; Animals, Wild; Base Sequence; Chlorocebus aethiops; DNA Primers; DNA, Viral; Female; Genes, env; Genes, gag; Genome, Viral; HIV Envelope Protein gp120; Infectious Disease Transmission, Vertical; Leukocytes; Membrane Glycoproteins; Molecular Sequence Data; Papio; Phylogeny; Polymerase Chain Reaction; Retroviridae Proteins; Sequence Homology, Amino Acid; Simian Acquired Immunodeficiency Syndrome; Simian Immunodeficiency Virus; Viral Envelope Proteins

A novel beta-thalassaemia mutation in the 5' untranslated region of the beta-globin gene. - Athanassiadou, A; Papachatzopoulou, A; Zoumbos, N; Maniatis, G M; Richard A Gibbs (Br J Haematol, 1994)
A thymidine deletion at position +10 of the 5' untranslated region of the beta-globin gene was detected in a beta-thalassaemia intermedia patient carrying a beta(0)39 stop codon mutation on the other chromosome; this new mutation, +10(-T), was detected by automated fluorescent DNA sequencing and verified by dot-blot allele-specific hybridizations. The +10(-T) mutation is a 'silent carrier', is associated with a reduced amount of steady-state beta-globin mRNA, and establishes a connection between the 5' untranslated region of the beta-globin gene and the regulation of its expression.
Keywords: Aged; Base Sequence; beta-Thalassemia; Blotting, Northern; DNA Mutational Analysis; Female; Globins; Humans; Molecular Sequence Data; RNA, Messenger; Sequence Deletion; Thymidine

Termination of DNA synthesis by novel 3'-modified-deoxyribonucleoside 5'-triphosphates. - Metzker, M L; Raghavachari, R; Stephen Richards; Jacutin, S E; Civitello, A; Burgess, K; Richard A Gibbs (Nucleic Acids Res, 1994)
Eight 3'-modified-dNTPs were synthesized and tested in two different DNA template assays for incorporation activity. From this enzymatic screen, two 3'-O-methyl-dNTPs were shown to terminate DNA syntheses mediated by a number of polymerases and may be used as alternative terminators in Sanger sequencing. 3'-O-(2-Nitrobenzyl)-dATP is a UV sensitive nucleotide and was shown to be incorporated by several thermostable DNA polymerases. Base specific termination and efficient photolytic removal of the 3'-protecting group was demonstrated. Following deprotection, DNA synthesis was reinitiated by the incorporation of natural nucleotides into DNA. The identification of this labile terminator and the demonstration of a one cycle stop-start DNA synthesis are initial steps in the development of a novel sequencing strategy.
Keywords: Base Sequence; Chromatography, High Pressure Liquid; Deoxyribonucleotides; DNA; DNA-Directed DNA Polymerase; Molecular Sequence Data; Molecular Structure; Templates, Genetic

Detection and significance of HIV sequences in HIV infection. - Lewis, D E; Richard A Gibbs (Prog Med Virol, 1993)
Keywords: Base Sequence; DNA, Viral; HIV; HIV Infections; Humans; In Situ Hybridization; Molecular Sequence Data; Polymerase Chain Reaction; RNA, Viral; Sequence Analysis, DNA

Large-scale sequencing library production: an adaptor-based strategy. - Povinelli, C M; Richard A Gibbs (Anal Biochem, 1993)
A significant bottleneck in large-scale DNA sequencing projects is the creation of high-quality random libraries suitable for sequencing. We have utilized an adaptor-based strategy and developed a simple protocol to reliably generate single-insert random subclone M13 libraries yielding uniform coverage and > 10(3) clones per microgram of DNA. Of the resulting white plaques, 95% contained inserts, < 0.5% were due to adaptors with no insert, and none of the clones were found to contain extraneous DNA (0/600) or multiple inserts (0/300).
Keywords: Base Sequence; Biotechnology; CD4 Antigens; Cloning, Molecular; DNA; Evaluation Studies as Topic; Gene Library; Genetic Techniques; Genetic Vectors; Humans; Molecular Sequence Data; Sequence Analysis, DNA; Software Design

Multiple cDNA sequences of bovine tracheal lysozyme. - Takeuchi, K; Irwin, D M; Gallup, M; Shinbrot, E; Kai, H; Stewart, C B; Basbaum, C (J Biol Chem, 1993)
The principal role of lysozyme is to prevent bacterial invasion at body surfaces. We are interested in how lysozyme is regulated at the surface of the respiratory tract, where the serous gland cell is regarded as the primary cellular source of this enzyme. Since the cow genome contains at least 10 lysozyme-like genes, our objective was to determine which of them are expressed in the cow tracheal gland serous cell. By screening tracheal cDNA libraries with a probe constructed from the cDNA encoding stomach lysozyme 2, we obtained 3 lysozyme cDNAs: 5a (1023 base pairs (bp)), 7a (1060 bp), and 14d (1249 bp). cDNA 7a corresponds to a previously reported gene (showing sequence identity to the stomach 2 lysozyme gene), whereas cDNAs 5a and 14d correspond to lysozyme genes not previously reported. Northern blot analysis of cow tracheal RNA showed lysozyme mRNAs of three distinct lengths. Based on hybridization with probes specific for each cDNA, we determined that the longest transcript corresponded to cDNA 5a, the shortest to 7a, and the intermediate-length transcript to 14d. Cultured cow tracheal gland serous cell RNA, reverse transcribed and amplified by the polymerase chain reaction with primers common to all three cDNAs, yielded a product that hybridized to oligonucleotide probes specific for all three cDNAs but most strongly to that for 5a. These results indicate that multiple lysozyme mRNAs are expressed in the cow trachea and that the lysozyme encoded by cDNA 5a is the major form expressed in the tracheal gland serous cell. This serous cell lysozyme is predicted to differ importantly in structure from both 7a and 14d lysozymes, with an arginine:lysine ratio almost 10-fold higher. The sequence differences may underlie functional differences, including variable resistance to proteolysis and variable affinity for large polyanions (e.g. mucins) found in the respiratory tract lumen.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Blotting, Southern; Cattle; Cells, Cultured; DNA Primers; DNA, Complementary; Electrophoresis, Polyacrylamide Gel; Molecular Sequence Data; Muramidase; Polymerase Chain Reaction; Sequence Homology, Amino Acid; Sequence Homology, Nucleic Acid; Trachea

Multiplex DNA amplification and solid-phase direct sequencing for mutation analysis at the hprt locus in Chinese hamster cells. - Zu, Z; Yu, Y; Richard A Gibbs; Caskey, C T; Hsie, A W (Mutat Res, 1993)
We report here the development of multiplex in vitro DNA amplification and solid-phase direct exon sequencing for the analysis of mutations at the hypoxanthine-guanine phosphoribosyltransferase (hprt) locus in Chinese hamster cells. 18 representative HPRT-deficient mutants, derived either spontaneously, or after exposure to UV light or ionizing radiation, were analyzed. All 9 hprt exons were simultaneously amplified via the polymerase chain reaction (PCR) for rapid deletion detection. 5 mutants involve single- or multiple-exon deletions. Altered multiplex PCR patterns were detected in mutants Bsp-040, Bsp-065 and BGR-606. Subsequent direct sequence analysis reveals that Bsp-040 and Bsp-065 carry a 52-bp and a 13-bp intragenic DNA deletion in exon 3, respectively. BGR-606 contains a 223-bp insertion accompanied by a 10-bp deletion of intron sequence within exon 4 fragment. Other subtle DNA alterations identified by direct exon sequence analysis include single-base substitutions, small deletions and insertions, and RNA splicing mutations.
Keywords: Animals; Base Sequence; CHO Cells; Chromosome Mapping; Cricetinae; DNA Mutational Analysis; Hypoxanthine Phosphoribosyltransferase; Molecular Sequence Data; Mutation; Polymerase Chain Reaction; Sequence Analysis, DNA

Nuclear DNA polymorphisms in a wild population of yellow baboons (Papio hamadryas cynocephalus) from Mikumi National Park, Tanzania. - Rogers, J; Kidd, K K (Am J Phys Anthropol, 1993)
Yellow baboons (Papio hamadryas cynocephalus) from Mikumi National Park, Tanzania were studied for polymorphisms in nuclear DNA. The study population consists of four social groups that inhabit overlapping home ranges and exchange males. As a result, these groups are considered to be members of a single interbreeding population. Human DNA clones were used as probes to screen five loci (AT3, REN, HEXB, VIM, and APOB) for restriction fragment length polymorphisms (RFLP). A total of 14 polymorphisms, at least one at each locus, was detected in a panel of 27 baboons tested using six restriction enzymes for each locus. Eleven of these RFLP systems have average heterozygosity values greater than 0.40. This initial screening demonstrates that human DNA clones can be used to detect significant numbers of informative DNA polymorphisms in single-copy nuclear genes of this species and suggests that the average proportion of nucleotides polymorphic across nuclear loci in this population may be between 1.0% and 1.3%.
Keywords: Animals; Antithrombin III; Apolipoproteins B; beta-N-Acetylhexosaminidases; DNA; Hexosaminidase B; Papio; Polymorphism, Genetic; Polymorphism, Restriction Fragment Length; Renin; Tanzania; Vimentin

Rapid characterization of HIV-1 sequence diversity using denaturing gradient gel electrophoresis and direct automated DNA sequencing of PCR products. - Andersson, B; Ying, J H; Lewis, D E; Richard A Gibbs (PCR Methods Appl, 1993)
A direct method for visualization and isolation of sequence variants of human immunodeficiency virus type 1 (HIV-1) utilizing denaturing gradient gel electrophoresis (DGGE) combined with automated direct DNA sequencing was developed. Two fragments from the env gene and one from the nef gene of HIV-1, which together constitute approximately 1.0 kb of sequence, were amplified by PCR and analyzed. HIV-1 variants from each region were resolved and excised from the gel; this was followed by direct sequencing of different viral variants. In 9 infected patients, a limited number of dominant sequence variants could be seen in the three regions, together with a faint background of minor variants. The use of DGGE makes it possible to obtain a direct estimate of overall HIV-1 sequence diversity within patient samples without an intermediate DNA cloning step.
Keywords: Base Sequence; DNA, Viral; Electrophoresis; HIV-1; Humans; Molecular Sequence Data; Polymerase Chain Reaction; Sequence Analysis, DNA

Characterization of human genomic yeast artificial chromosome inserts containing hexokinase 1 coding information on chromosome 10. - Gelb, B D; Kim C Worley; Griffin, L D; Adams, V; Chinault, A C; McCabe, E R (Biochem Med Metab Biol, 1992)
Hexokinase 1 (HK1) is one of four mammalian HK isoenzymes and maps to human chromosome 10. Two yeast artificial chromosomes (YACs) were identified in the Washington University human YAC library using polymerase chain reaction (PCR) primers designed with knowledge of the human HK1 cDNA sequence. YAC B129B12 is 120 kb in length and maps entirely to chromosome 10. YAC A159D5 is 400 kb in length and appears to have resulted from a recombination of chromosome 10 with non-chromosome 10 material. We report these YACs as potential resources for those interested in HK1 gene organization and mapping, as well as those desiring additional genomic information and markers on chromosome 10.
Keywords: Animals; Base Sequence; Chromosome Mapping; Chromosomes, Fungal; Chromosomes, Human, Pair 10; Cricetinae; DNA; Genome, Human; Hexokinase; Humans; Isoenzymes; Molecular Sequence Data; Polymerase Chain Reaction; Yeasts

Genotypic confirmation from the original dried blood specimens in a neonatal hemoglobinopathy screening program. - Descartes, M; Huang, Y; Zhang, Y H; McCabe, L L; Richard A Gibbs; Therrell, B L; McCabe, E R (Pediatr Res, 1992)
Dried blood spots are used for newborn screening because of ease of sample collection, handling, and shipment. DNA is stable and accessible in the filter paper matrix. Genotypic confirmation using initial specimens is demonstrated for a regional screening program. Seventy-five blinded samples underwent DNA analysis after Hb electrophoresis. DNA was microextracted from a 1/2-inch semicircle (25 microL whole blood equivalent), amplified, and analyzed by four different methods. Direct amplification without microextraction and automated sequencing from microextracted DNA also was performed. All four analyses agreed for the A and S alleles in 70 of 75 specimens. Three disagreements were clarified by the other semicircle from the original sample: two were due to polymerase chain reaction contamination and one to contamination of one of four analytical tests. Two would have required analysis of a second specimen, one because of polymerase chain reaction failure and the second because the patient had S/beta-thalassemia. Direct amplification without microextraction was successful in an additional 77 of 78 specimens for analysis of the A, S, C, and E alleles. Automated direct sequencing from microextracted DNA was demonstrated for the A, S, and C alleles. Analysis of microextracted DNA from dried blood specimens for A and S alleles reduced the need for and costs of obtaining a second specimen for confirmation by 97%. Direct amplification without microextraction for analysis of A, S, and C alleles permits additional reduction in personnel time and costs. We have demonstrated that microextracted DNA is amenable to automated sequencing after asymmetric polymerase chain reaction. Direct genotypic confirmation can facilitate diagnosis and initiation of medical intervention.
Keywords: Alleles; Base Sequence; Blood Specimen Collection; DNA Mutational Analysis; Genotype; Hemoglobinopathies; Hemoglobins, Abnormal; Humans; Infant, Newborn; Mass Screening; Molecular Sequence Data

A human dimorphism resulting from loss of an Alu. - Edwards, M C; Richard A Gibbs (Genomics, 1992)
The molecular phylogeny of Alu and other repeated sequences in the human genome provides clues to events during primate evolution. A subclass of human Alu's has been previously identified as dimorphic insertions within members of the medium reiteration frequency (mer) class of repeats, reflecting the complicated sequence of insertion and radiation events leading to the current human genome structure. One dimorphic Alu is located within a previously unidentified mer family member, in the first intron of the human T4 (CD4) gene. The insertion (Alu+ allele) has a frequency of approximately 70% in Europeans and Africans and is homozygous in 20 Asian samples. Polymerase chain reaction amplification, direct DNA sequencing, and Southern analysis using oligonucleotide probes revealed that the Alu- allele was derived from the Alu+ allele by loss of part of the inserted sequence. Comparison with a tightly linked marker within the human genome and studies of baboon DNA samples revealed that the original insertion was a relatively early event in primate evolution, but that the Alu sequence loss leading to the dimorphism has occurred much more recently. Loss of Alu insertions therefore represents one mechanism for the generation of human Alu dimorphisms.
Keywords: Animals; Base Sequence; Blotting, Southern; CD4 Antigens; DNA; Genetic Linkage; Humans; Molecular Sequence Data; Papio; Polymerase Chain Reaction; Polymorphism, Genetic; Repetitive Sequences, Nucleic Acid; Retroviruses, Simian; Sequence Homology, Nucleic Acid

Identification of a 2 base pair nonsense mutation causing a cryptic splice site in a DMD patient. - Winnard, A V; Jia-Hsu, Y; Richard A Gibbs; Mendell, J R; Burghes, A H (Hum Mol Genet, 1992)
Keywords: Amino Acid Sequence; Base Sequence; DNA; Female; Humans; Molecular Sequence Data; Muscular Dystrophies; Mutation; Polymerase Chain Reaction; RNA Splicing; RNA, Messenger

Identification of new markers in Xp21 between DXS28 (C7) and DMD. - Kim C Worley; Towbin, J A; Zhu, X M; Barker, D F; Ballabio, A; Chamberlain, J; Biesecker, L G; Blethen, S L; Brosnan, P; Fox, J E (Genomics, 1992)
Characterization of Xp21 distal to Duchenne muscular dystrophy (DMD) in the region containing the genes for adrenal hypoplasia congenita (AHC) and glycerol kinase deficiency (GKD) has been limited due to a paucity of probes. Two probes were localized between DXS28 (C7) and AHC, the yeast artificial chromosome insert YHX39 (DXS727) and the polymorphic phage clone QST59 (DXS319). A genomic clone, FT1 (DXS726), 3' to DMD, was also characterized. Portions of the three probes were sequenced and primer pairs were generated to amplify a sequence-tagged site within each probe. Amplification of DNA from patients confirmed the deletion results obtained by Southern blot analysis, and these three sequence-tagged sites were successfully combined for triplex PCR. In addition to facilitating molecular genetic diagnosis in Xp21, these probes can be used to identify additional YACs and other probes to further increase the genomic information and diagnostic capabilities in this region.
Keywords: Base Sequence; Blotting, Southern; Chromosome Mapping; Chromosomes, Fungal; DNA; Gene Library; Genetic Markers; Genome, Human; Humans; Molecular Sequence Data; Muscular Dystrophies; Oligonucleotides; Phenotype; Polymerase Chain Reaction; X Chromosome

Polymerase chain reaction-based comprehensive procedure for the analysis of the mutation spectrum at the hypoxanthine-guanine phosphoribosyltransferase locus in Chinese hamster cells. - Yu, Y J; Xu, Z; Richard A Gibbs; Hsie, A W (Environ Mol Mutagen, 1992)
We have established a comprehensive procedure based on the polymerase chain reaction (PCR) to analyze the molecular spectrum of mutations at the hypoxanthine-guanine phosphoribosyltransferase (hprt) locus in Chinese hamster cells. The procedure includes direct sequencing of PCR-amplified hprt cDNA for locating point mutations in the expressed coding sequences, multiplex PCR amplification of the hprt exons for screening large deletions, and direct sequencing of PCR-amplified hprt exons and their flanking regions for detecting intronic mutations resulting in mRNA splicing errors. Using this procedure, we have identified different types of mutations among a representative collection of spontaneous and induced HPRT-deficient Chinese hamster cell mutants. This procedure is simple, rapid, accurate, and practical for a comprehensive study of the mutation spectrum in a large number of HPRT-deficient Chinese hamster cell mutants.
Keywords: Animals; Base Sequence; CHO Cells; Cricetinae; DNA; Exons; Hypoxanthine Phosphoribosyltransferase; Molecular Sequence Data; Mutation; Polymerase Chain Reaction

A simple protocol for the automation of DNA cycle sequencing reactions and polymerase chain reactions. - Civitello, A B; Stephen Richards; Richard A Gibbs (DNA Seq, 1992)
Automated DNA sequencing methods using robotic workstations have been previously reported, however it is often an arduous task to import these technologies into a laboratory. We describe protocols making use of a Beckman Biomek 1000 robotic workstation to prepare polymerase chain reactions (PCRs) and "cycle sequencing" reactions to be performed in a Perkin Elmer Cetus System 9600 thermocycler. The combination of these two instruments allows a high throughput of PCR and DNA sequencing reactions. The programs described are freely available via anonymous file transfer protocol (FTP).
Keywords: Bacteriophage M13; Base Sequence; DNA, Viral; Electrophoresis, Agar Gel; Molecular Sequence Data; Polymerase Chain Reaction; Robotics; Sequence Analysis, DNA

A transposon-like element in the deletion-prone region of the dystrophin gene. - Pizzuti, A; Pieretti, M; Fenwick, R G; Richard A Gibbs; Caskey, C T (Genomics, 1992)
The central portion of the dystrophin gene locus is a preferential site for deletions causing progressive muscular dystrophy of the Duchenne type (DMD). The nucleotide sequence of a deletion junction fragment from a DMD patient was determined, revealing that the proximal breakpoint of the deletion in intron 43 fell within the sequence of a transposon-like element. This segment, belonging to the THE-1 family of human transposable elements, is normally present in a complete form in intron 43 of the dystrophin gene. The deletion mutation was maternally transmitted and eliminated two-thirds of the THE-1 element. Analysis of DNA from additional DMD patients revealed a second deletion with the proximal breakpoint mapping within the same THE-1 element.
Keywords: Base Sequence; Chromosome Deletion; DNA; DNA Mutational Analysis; DNA Transposable Elements; Dystrophin; Humans; Introns; Male; Molecular Sequence Data; Muscular Dystrophies; Restriction Mapping; Sequence Homology, Nucleic Acid

Alu-primed polymerase chain reaction for regional assignment of 110 yeast artificial chromosome clones from the human X chromosome: identification of clones associated with a disease locus. - Nelson, D L; Ballabio, A; Victoria, M F; Pieretti, M; Bies, R D; Gibbs, R A; Maley, J A; Chinault, A C; Webster, T D; Caskey, C T (Proc Natl Acad Sci U S A, 1991)
Over 400 yeast artificial chromosome (YAC) clones were isolated from the human X chromosome, and 110 of these were assigned to regions defined by chromosome translocation and deletion breakpoints. Polymerase chain reaction using Alu primers was applied to YAC clones in order to generate probes, to identify overlapping clones, and to derive "fingerprints" and sequence data directly from total yeast DNA. Several clones were identified in regions of medical interest. One set of three overlapping clones was found to cross a chromosomal translocation implicated in Lowe syndrome. The regional assignment of groups of YAC clones provides initiation points for further attempts to develop large cloned contiguous sequences, as well as material for investigation of regions involved in genetic diseases.
Keywords: Base Sequence; Blotting, Southern; Chromosome Mapping; Chromosomes, Fungal; Cloning, Molecular; Deoxyribonucleases, Type II Site-Specific; Gene Library; Genetic Diseases, Inborn; Humans; Molecular Sequence Data; Nucleotide Mapping; Oligonucleotide Probes; Polymerase Chain Reaction; Restriction Mapping; Saccharomyces cerevisiae; X Chromosome

Carrier detection and prenatal diagnosis in Duchenne and Becker muscular dystrophy families, using dinucleotide repeat polymorphisms. - Clemens, P R; Fenwick, R G; Chamberlain, J S; Gibbs, R A; de Andrade, M; Chakraborty, R; Caskey, C T (Am J Hum Genet, 1991)
To improve carrier detection and prenatal diagnosis for Duchenne and Becker muscular dystrophy families, we determined allele frequencies and measures of variation for four (dC-dA)n.(dG-dT)n loci identified within a deletion-prone region of the human dystrophin gene. The loci are highly polymorphic, with predicted heterozygosities of 71.6%-93.3%. Direct DNA sequence analysis of the (dC-dA)n.(dG-dT)n locus in intron 49 revealed an additional length polymorphism which varies by single-basepair increments, is adjacent to the dinucleotide repeat block, and enhances the polymorphic content of this marker. The four (dC-dA)n.(dG-dT)n loci are each easily amplified by PCR in two diplex reactions. The variability of allele lengths at these loci makes them ideal for carrier detection and prenatal diagnosis, often providing diagnostic information when RFLP analysis is uninformative. These markers have aided in identification of deletion mutations, exclusion of maternal cell contamination of chorionic villus samples, confirmation of paternity, and mapping of gene recombinations. The allele identification of these loci can be performed either with a radiolabel or with an automated, nonradioactive, fluorescent gel detection system.
Keywords: Alleles; Base Sequence; Cells, Cultured; Dystrophin; Female; Gene Frequency; Genetic Carrier Screening; Genetic Markers; Humans; Male; Molecular Sequence Data; Muscular Dystrophies; Pedigree; Polydeoxyribonucleotides; Polymerase Chain Reaction; Polymorphism, Genetic; Pregnancy; Prenatal Diagnosis; Repetitive Sequences, Nucleic Acid

Evolution of human immunodeficiency virus type 1 nucleotide sequence diversity among close contacts. - Burger, H; Weiser, B; Flaherty, K; Gulla, J; Nguyen, P N; Gibbs, R A (Proc Natl Acad Sci U S A, 1991)
The degree of change in the nucleotide sequence of human immunodeficiency virus type 1 (HIV-1) that occurs when it is transmitted sexually from one individual to another or vertically from mother to child is unknown. Previous studies have shown that most cultured HIV-1 isolates from the same individuals differed in the entire envelope gene nucleotide sequence by up to 2%, although most isolates from unrelated individuals differed by 6-22%. To examine diversity among HIV-1 isolates from close contacts, we determined the nucleotide sequences of viruses from a family with a known epidemiologic profile, in which a woman transmitted HIV-1 heterosexually to her partner and vertically to her daughter. Direct DNA sequence analysis of primary HIV-1 isolates amplified by PCR was used to distinguish the major and minor viral sequences, termed quasispecies, to rapidly determine the predominant sequences and their phylogenetic relationships. The nucleotide sequence diversity of a major portion of the HIV-1 envelope gene was 3.7% between isolates from the woman and her heterosexual partner and 8.5% between isolates from this woman and her daughter, who had been infected for a longer period than the partner. The configuration of the phylogenetic tree demonstrated that the daughter's predominant isolate evolved from a progenitor of her mother's current strain. This study provides evidence of a continuous spectrum of sequence diversity between any two isolates ranging from those derived from the same person to those from close contacts and, ultimately, those from unrelated individuals. These data and methods can be applied to epidemiologic investigations of possible HIV-1 transmission between health care workers and their patients.
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Adult; Amino Acid Sequence; Base Sequence; Biological Evolution; DNA, Viral; Female; Genes, env; Genetic Variation; HIV-1; Humans; Male; Molecular Sequence Data; Oligodeoxyribonucleotides; Phylogeny; Polymerase Chain Reaction; Sequence Homology, Nucleic Acid

Long HIV-1 incubation periods and dynamics of transmission within a family. - Burger, H; Belman, A L; Grimson, R; Kaell, A; Flaherty, K; Gulla, J; Richard A Gibbs; Nguyun, P N; Weiser, B (Lancet, 1990)
The incubation period of human immunodeficiency virus type 1 (HIV-1) infection was studied in a family of five in which vertical and heterosexual transmission occurred from one index case. This investigation documented incubation periods of longer than 12 years in a mother and her daughter; although neither has symptoms, both are definitely infected and have very low CD4(+)-lymphocyte counts. The study confirmed the predictions of incubation periods longer than 10 years in a small proportion of infected individuals. It provides evidence that vertically HIV-1-infected teenagers can be expected to appear in the population.
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Adult; CD4-Positive T-Lymphocytes; Child; DNA, Viral; Family; Family Health; Female; HIV Antibodies; HIV Seropositivity; HIV-1; Humans; Leukocyte Count; Male; Sexual Behavior; Substance Abuse, Intravenous; Time Factors

Multiplex DNA deletion detection and exon sequencing of the hypoxanthine phosphoribosyltransferase gene in Lesch-Nyhan families. - Richard A Gibbs; Nguyen, P N; Edwards, A; Civitello, A B; Caskey, C T (Genomics, 1990)
The Lesch-Nyhan (LN) syndrome is a genetically lethal human neurological disease that results from mutations that inactivate the hypoxanthine phosphoribosyltransferase (HPRT) gene. The elucidation of the complete DNA sequence of the human HPRT gene locus has enabled the construction of multiple oligonucleotide primer sets for the simultaneous in vitro amplification of all nine HPRT exons. The multiplex polymerase chain reaction provides a facile assay for the detection of HPRT exon deletions and the reaction products can be analyzed by direct automated fluorescent DNA sequencing to identify subtle alterations in the gene. Alterations have been identified in the HPRT genes from 15 independent LN cases, and 10 LN family studies were performed. The sequencing method uses solid supports and is sufficiently simple and sensitive to be a favored approach for LN diagnosis. LN heterozygotes can be diagnosed without reference to the affected male. In addition, these procedures will be useful for somatic mutagenesis studies.
Keywords: Base Sequence; Chromosome Deletion; DNA; Exons; Female; Genes; Genetic Carrier Screening; Humans; Hypoxanthine Phosphoribosyltransferase; Lesch-Nyhan Syndrome; Male; Molecular Sequence Data; Pedigree; Polymerase Chain Reaction

The use of primers from highly conserved pol regions to identify uncharacterized retroviruses by the polymerase chain reaction. - Donehower, L A; Bohannon, R C; Ford, R J; Richard A Gibbs (J Virol Methods, 1990)
Two degenerate oligonucleotide primers derived from regions of pol conserved among retroviruses have been synthesized. Polymerase chain reactions utilizing these primers amplify a 135-bp pol fragment in every retrovirus DNA tested to date. The polymerase chain reaction has been linked to a reverse transcriptase step so that a pol-specific DNA fragment can be obtained from a moderate amount of a purified retrovirus or viral RNA. The identity of an unknown retrovirus can be determined by sequencing of the amplified fragment following molecular cloning. This procedure was tested on an unidentified (non-HIV) retrovirus expressed by a B-cell lymphoma line obtained from an AIDS patient. Our PCR assay identified the retrovirus as being highly similar to Mason-Pfizer monkey virus (MPMV) and simian retrovirus 1, which are closely related immunosuppressive type D viruses that cause simian AIDS.
Keywords: Amino Acid Sequence; Base Sequence; DNA, Viral; Gene Amplification; Genes, pol; Humans; Molecular Sequence Data; Oligonucleotides; Polymerase Chain Reaction; Retroviridae; Retroviruses, Simian; RNA-Directed DNA Polymerase; Sequence Homology, Nucleic Acid; Simian Immunodeficiency Virus; Templates, Genetic

Automated DNA sequencing methods for detection and analysis of mutations: applications to the Lesch-Nyhan syndrome. - Edwards, A; Richard A Gibbs; Nguyen, P N; Ansorge, W; Caskey, C T (Trans Assoc Am Physicians, 1989)
Keywords: Base Sequence; Chromosome Deletion; DNA; Female; Genetic Carrier Screening; Humans; Hypoxanthine Phosphoribosyltransferase; Lesch-Nyhan Syndrome; Male; Mutation; Pedigree; Polymerase Chain Reaction; Polymorphism, Genetic; Pregnancy; Prenatal Diagnosis; Repetitive Sequences, Nucleic Acid; Restriction Mapping

Deletion screening at the hypoxanthine-guanine phosphoribosyltransferase locus in Chinese hamster cells using the polymerase chain reaction. - Xu, Z D; Yu, Y J; Hsie, A W; Caskey, C T; Rossiter, B; Richard A Gibbs (Teratog Carcinog Mutagen, 1989)
We have developed a rapid screening method using the polymerase chain reaction (PCR) for detecting deletion mutations at the hypoxanthine-guanine phosphoribosyltransferase (hprt) locus in Chinese hamster cells. DNA was extracted from spontaneous and ultraviolet (UV) light- and X-ray-induced hprt-deficient mutants. Two primer sets were used to amplify 276 bp and 344 bp fragments containing the entire exon 3 and exon 9 coding sequence, respectively. The PCR was performed using Taq DNA polymerase for 40 cycles, and the PCR product was directly analyzed for the presence of the respective amplified DNA using electrophoresis on agarose gels stained with ethidium bromide. With this assay, we have analyzed 39 independently derived hprt-deficient mutants. Four of ten spontaneous mutants were found to have deletions in exon 9. UV light produced mutants with predominantly wild-type amplification patterns (10/14). X-ray induced mostly deletion patterns (11/15); six of these occurred only in exon 9, and five occurred in both exons 3 and 9. These observations are consistent with the classical notion that UV light induces predominantly missense mutations and X-ray produces a high proportion of deletion mutations. Deletion mutations occurred most frequently at the 3' end of the hprt gene, suggesting the possible existence of hot spots for deletions in this region. The PCR assay for deletion detection has the advantage that it can be completed in less than 4 hr without using radioisotopes. This assay should be useful for routine deletion screening.
Keywords: Animals; Cells, Cultured; Chromosome Deletion; DNA; DNA-Directed DNA Polymerase; Electrophoresis, Agar Gel; Exons; Gene Amplification; Hypoxanthine Phosphoribosyltransferase; Ultraviolet Rays; X-Rays

Detection of single DNA base differences by competitive oligonucleotide priming. - Richard A Gibbs; Nguyen, P N; Caskey, C T (Nucleic Acids Res, 1989)
Synthetic DNA oligonucleotides can serve as efficient primers for DNA synthesis even when there is a single base mismatch between the primers and the corresponding DNA template. However, when the primer-template annealing is carried out with a mixture of primers and at low stringency the binding of a perfectly matched primer is strongly favored relative to a primer differing by a single base. This primer competition is observed over a range of oligonucleotide sizes from twelve to sixteen bases and with a variety of base mismatches. When coupled with the polymerase chain reaction, for the amplification of specific DNA sequences, competitive oligonucleotide priming provides a simple general strategy for the detection of single DNA base differences.
Keywords: Animals; Base Sequence; Binding, Competitive; DNA; DNA, Single-Stranded; DNA-Directed DNA Polymerase; Gene Amplification; Mice; Mice, Mutant Strains; Molecular Sequence Data; Mutation; Oligonucleotides; Taq Polymerase; Templates, Genetic

Identification of mutations leading to the Lesch-Nyhan syndrome by automated direct DNA sequencing of in vitro amplified cDNA. - Gibbs, R A; Nguyen, P N; McBride, L J; Koepf, S M; Caskey, C T (Proc Natl Acad Sci U S A, 1989)
The Lesch-Nyhan (LN) syndrome is a severe X chromosome-linked disease that results from a deficiency of the purine salvage enzyme hypoxanthine phosphoribosyltransferase (HPRT). The mutations leading to the disease are heterogeneous and frequently arise as de novo events. We have identified nucleotide alterations in 15 independently arising HPRT-deficiency cases by direct DNA sequencing of in vitro amplified HPRT cDNA. We also demonstrate that the direct DNA sequence analysis can be automated, further simplifying the detection of new mutations at this locus. The mutations include DNA base substitutions, small DNA deletions, a single DNA base insertion, and errors in RNA splicing. The application of these procedures allows DNA diagnosis and carrier identification by the direct detection of the mutant alleles within individual families affected by LN.
Keywords: Alleles; Autoanalysis; Base Sequence; DNA; DNA-Directed DNA Polymerase; Gene Amplification; Humans; Hypoxanthine Phosphoribosyltransferase; Lesch-Nyhan Syndrome; Mutation; Nucleic Acid Hybridization; Oligonucleotide Probes; Pedigree; RNA Splicing; Software

Deletion screening of the Duchenne muscular dystrophy locus via multiplex DNA amplification. - Chamberlain, J S; Richard A Gibbs; Ranier, J E; Nguyen, P N; Caskey, C T (Nucleic Acids Res, 1988)
The application of recombinant DNA technology to prenatal diagnosis of many recessively inherited X-linked diseases is complicated by a high frequency of heterogeneous, new mutations (1). Partial gene deletions account for more than 50% of Duchenne muscular dystrophy (DMD) lesions, and approximately one-third of all cases result from a new mutation (2-5). We report the isolation and DNA sequence of several deletion prone exons from the human DMD gene. We also describe a rapid method capable of detecting the majority of deletions in the DMD gene. This procedure utilizes simultaneous genomic DNA amplification of multiple widely separated sequences and should permit deletion scanning at any hemizygous locus. We demonstrate the application of this multiplex reaction for prenatal and postnatal diagnosis of DMD.
Keywords: Base Sequence; Chromosome Deletion; Cloning, Molecular; DNA; Female; Gene Amplification; Humans; Male; Molecular Sequence Data; Muscular Dystrophies; Prenatal Diagnosis

Diagnosis of human heritable defects by recombinant DNA methods. - Caskey, C T; Richard A Gibbs; Witkowski, J A; Hejtmancik, J F (Philos Trans R Soc Lond B Biol Sci, 1988)
Recombinant DNA methods provide highly sensitive means for the detection of DNA alterations that lead to human disease mutations. In this paper I shall illustrate the approaches currently available and discuss new technologies that show promise of replacing the present methods. Medical diagnosis by means of recombinant DNA methods has an expanding role in clinical medicine.
Keywords: DNA, Recombinant; Female; Genetic Diseases, Inborn; Genetic Engineering; Genetic Techniques; Humans; Mutation; Pregnancy; Prenatal Diagnosis

Enhancer and promoter elements directing activation and glucocorticoid repression of the alpha 1-fetoprotein gene in hepatocytes. - Guertin, M; LaRue, H; Bernier, D; Wrange, O; Chevrette, M; Gingras, M C; Bélanger, L (Mol Cell Biol, 1988)
Mutations were introduced in 7 kilobases of 5'-flanking rat alpha 1-fetoprotein (AFP) genomic DNA, linked to the chloramphenicol acetyltransferase gene. AFP promoter activity and its repression by a glucocorticoid hormone were assessed by stable and transient expression assays. Stable transfection assays were more sensitive and accurate than transient expression assays in a Morris 7777 rat hepatoma recipient (Hepa7.6), selected for its strong AFP repression by dexamethasone. The segment of DNA encompassing a hepatocyte-constitutive chromatin DNase I-hypersensitive site at -3.7 kilobases and a liver developmental stage-specific site at -2.5 kilobases contains interacting enhancer elements sufficient for high AFP promoter activity in Hepa7.6 or HepG2 cells. Deletions and point mutations define an upstream promoter domain of AFP gene activation, operating with at least three distinct promoter-activating elements, PEI at -65 base pairs, PEII at -120 base pairs, and DE at -160 base pairs. PEI and PEII share homologies with albumin promoter sequences, PEII is a near-consensus nuclear factor I recognition sequence, and DE overlaps a glucocorticoid receptor recognition sequence. An element conferring glucocorticoid repression of AFP gene activity is located in the upstream AFP promoter domain. Receptor-binding assays indicate that this element is the glucocorticoid receptor recognition sequence which overlaps with promoter-activating element DE.
Keywords: Acetyltransferases; alpha-Fetoproteins; Animals; Base Sequence; Chloramphenicol O-Acetyltransferase; Cloning, Molecular; Cytosol; Dexamethasone; Enhancer Elements, Genetic; Enzyme Induction; Gene Expression Regulation; Genes; Genes, Regulator; Liver; Liver Neoplasms, Experimental; Molecular Sequence Data; Plasmids; Promoter Regions, Genetic; Rats; Transcriptional Activation; Transfection; Tyrosine Transaminase

Expression of the murine Duchenne muscular dystrophy gene in muscle and brain. - Chamberlain, J S; Pearlman, J A; Donna M Muzny; Richard A Gibbs; Ranier, J E; Caskey, C T; Reeves, A A (Science, 1988)
Complementary DNA clones were isolated that represent the 5' terminal 2.5 kilobases of the murine Duchenne muscular dystrophy (Dmd) messenger RNA (mRNA). Mouse Dmd mRNA was detectable in skeletal and cardiac muscle and at a level approximately 90 percent lower in brain. Dmd mRNA is also present, but at much lower than normal levels, in both the muscle and brain of three different strains of dystrophic mdx mice. The identification of Dmd mRNA in brain raises the possibility of a relation between human Duchenne muscular dystrophy (DMD) gene expression and the mental retardation found in some DMD males. These results also provide evidence that the mdx mutations are allelic variants of mouse Dmd gene mutations.
Keywords: Animals; Brain; DNA; DNA, Recombinant; Gene Expression Regulation; Intellectual Disability; Mice; Mice, Inbred ICR; Mice, Mutant Strains; Muscles; Muscular Dystrophy, Animal; Mutation; Nucleic Acid Hybridization; Ribonuclease, Pancreatic; RNA, Messenger

Generation of cDNA probes directed by amino acid sequence: cloning of urate oxidase. - Lee, C C; Wu, X W; Richard A Gibbs; Cook, R G; Donna M Muzny; Caskey, C T (Science, 1988)
Urate oxidase (E.C. 1.7.3.3) catalyzes the oxidation of uric acid to allantoin in most mammals except humans and certain primates. The amino-terminal amino acid sequence for porcine urate oxidase was determined and used in a novel procedure for generating complementary DNA (cDNA) probes to this amino acid sequence. The procedure is based on the polymerase chain reaction and utilizes mixed oligonucleotide primers complementary to the reverse translation products of an amino acid sequence. This rapid and simple cDNA cloning procedure is generally applicable and requires only a partial amino acid sequence. A cDNA probe developed by this procedure was used to isolate a full-length porcine urate oxidase cDNA and to demonstrate the presence of homologous genomic sequences in humans.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Cloning, Molecular; DNA; Gene Amplification; Liver; Mice; Molecular Sequence Data; Nucleic Acid Hybridization; Swine; Urate Oxidase

The genetic structure of mouse ornithine transcarbamylase. - Steven E Scherer; Veres, G; Caskey, C T (Nucleic Acids Res, 1988)
The gene encoding the mouse urea cycle enzyme, ornithine transcarbamylase has been isolated on five partially overlapping bacteriophage lambda clones. We have characterized the gene and found that it is split between ten exons distributed over approximately 70 kb of the X chromosome. The introns range in size from 88 bases to the relatively unusual size of approximately 26 kilobases, while the splice donor/splice acceptor sequences conform to the consensus established for other eukaryotic genes.
Keywords: Animals; Base Sequence; DNA Restriction Enzymes; DNA, Recombinant; Genes; Mice; Molecular Sequence Data; Nucleic Acid Hybridization; Ornithine Carbamoyltransferase

Loss of growth factor dependence and conversion of transforming growth factor-beta 1 inhibition to stimulation in metastatic H-ras-transformed murine fibroblasts. - Schwarz, L C; Marie-Claude Gingras; Goldberg, G; Greenberg, A H; Wright, J A (Cancer Res, 1988)
Cell lines with varying tumorigenic and metastatic potentials have been obtained by transformation of 10T 1/2 fibroblasts using radiation or transfection with T-24 H-ras. We have observed an inverse relationship between metastatic potential and dependence on serum for growth. The effects of basic fibroblast growth factor, platelet-derived growth factor, epidermal growth factor, and transforming growth factor-beta 1 (TGF-beta 1) on these lines were then examined to determine if the changes in the serum dependence of metastatic cells may be due to altered responsiveness to specific growth factors (GFs). Cells were grown in monolayer culture and DNA synthesis was measured by [CH3-3H]thymidine incorporation experiments. Both metastatic and nonmetastatic cells were shown to be equivalent in their diminished responsiveness to basic fibroblast growth factor, platelet-derived growth factor, and epidermal growth factor as compared to their nontransformed, parental 10T 1/2 cells. However, a unique response of metastatic cells to TGF-beta 1 was identified. While TGF-beta 1 inhibited DNA synthesis in 10T 1/2 cells and a nonmetastatic tumor, cells with intermediate to high metastatic ability were stimulated up to 5.8-fold by TGF-beta 1. Interestingly, epidermal growth factor abrogated the TGF-beta 1 inhibition of the parental 10T 1/2 cells, but had no effect on the TGF-beta 1 response of any metastatic line. Therefore, metastatic but not nonmetastatic cells, demonstrated a dramatically altered sensitivity to TGF-beta 1, a response which may be important in determining metastatic potential.
Keywords: Animals; Cell Line; Cell Transformation, Neoplastic; DNA Replication; Epidermal Growth Factor; Fibroblast Growth Factors; Fibroblasts; Fibrosarcoma; Genes, ras; Growth Substances; Mice; Mice, Inbred BALB C; Neoplasm Metastasis; Platelet-Derived Growth Factor; Transforming Growth Factors

The molecular basis of the sparse fur mouse mutation. - Veres, G; Richard A Gibbs; Steven E Scherer; Caskey, C T (Science, 1987)
The ornithine transcarbamylase-deficient sparse fur mouse is an excellent model to study the most common human urea cycle disorder. The mutation has been well characterized by both biochemical and enzymological methods, but its exact nature has not been revealed. A single base substitution in the complementary DNA for ornithine transcarbamylase from the sparse fur mouse has been identified by means of a combination of two recently described techniques for rapid mutational analysis. This strategy is simpler than conventional complementary DNA library construction, screening, and sequencing, which has often been used to find a new mutation. The ornithine transcarbamylase gene in the sparse fur mouse contains a C to A transversion that alters a histidine residue to an asparagine residue at amino acid 117.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Disease Models, Animal; DNA; Genes; Mice; Mice, Mutant Strains; Mutation; Ornithine Decarboxylase; RNA, Messenger

Molecular characterization of 125I decay and X-ray-induced HPRT mutants in CHO cells. - Richard A Gibbs; Camakaris, J; Hodgson, G S; Martin, R F (Int J Radiat Biol Relat Stud Phys Chem Med, 1987)
The predominant initial lesion induced by 125I decay in DNa is a double-strand DNA break comprising a 'mini deletion' of up to several base pairs (bp). However, Southern analysis of the structure of 125I decay-induced HPRT mutants in Chinese hamster ovary cells revealed that most of the mutants are deletions of thousands of bps. A similar predominance of substantial deletions was also found in X-ray-induced mutants.
Keywords: Animals; Chromosome Deletion; Cricetinae; DNA Repair; Gamma Rays; Hypoxanthine Phosphoribosyltransferase; Iodine Radioisotopes; Mutation; Polymorphism, Restriction Fragment Length; X-Rays

Oncodevelopmental and hormonal regulation of alpha 1-fetoprotein gene expression. - Bélanger, L; Baril, P; Guertin, M; Marie-Claude Gingras; Gourdeau, H; Anderson, A; Hamel, D; Boucher, J M (Adv Enzyme Regul, 1983)
The main features of the oncodevelopmental biology of alpha 1-fetoprotein (AFP) are reviewed. Progress made in the molecular biology of AFP gene regulation is discussed and we present our recent data on the mechanisms of AFP suppression by glucocorticoid hormones. The relationship between AFP gene transcription and cell replication is examined, and it is suggested that the degree of methylation of the AFP gene (or of co-methylated regulatory DNA sequences) conditions its response to hormones.
Keywords: Albumins; alpha-Fetoproteins; Animals; Base Sequence; Dexamethasone; DNA Replication; Gene Expression Regulation; Hormones; Humans; Liver; Medroxyprogesterone; Methionine; Oncogenes; Rats; RNA, Messenger; Transcription, Genetic

Glucocorticosteroid suppression of alpha1-fetoprotein synthesis in developing rat liver. Evidence for selective gene repression at the transcriptional level. - Bélanger, L; Frain, M; Baril, P; Marie-Claude Gingras; Bartkowiak, J; Sala-Trepat, J M (Biochemistry, 1981)
Keywords: alpha-Fetoproteins; Animals; Dexamethasone; Genes; Kinetics; Liver; Nucleic Acid Hybridization; Prednisolone; Rats; Rats, Inbred Strains; RNA, Messenger; Serum Albumin; Transcription, Genetic